Hydrothermal Seepage of Altered Crustal Formation Water Seaward of the Middle America Trench, Offshore Costa Rica - Parsons, Patrice K. F.; Wheat, C. Geoffrey; Fisher, Andrew T.; Silver, Eli A.; Hutnak, Michael (Geochemistry, Geophysics, Geosystems, 2024)
Chemical compositions of sediment pore waters are presented from 13 piston and gravity cores that were collected on ∼24 Ma crust of the Cocos Plate seaward of the Middle America Trench and near the onset of crustal faulting from subduction. Cores were collected mainly within a 1.75 km2 area overlying a buried basement topographic high that supports an elevated heat flux, consistent with seawater transport within the upper volcanic crust. Systematic variations in pore water chemical profiles indicate upward seepage speeds (up to 1.7 cm yr−1 providing a net flux of 0.1 L s−1), constrain the chemical composition of the formation water within the underlying upper basaltic basement, and elucidate diagenetic reactions in the sediment. Relative to seawater, formation water has an elevated temperature (70–80°C) and concentrations or values of Ca, chlorinity, Sr, Ba, Li, Fe, Mn, Si, Cs, D/H, and Mo, and lower concentrations or values of Mg, Na, sulfate, alkalinity, TCO2, K, B, F, phosphate, 87Sr/86Sr, δ13C, δ18O, U, and Rb. Although this site is located only 30 km from the trench axis, there is no chemical evidence for subduction-related hydrologic influences. Instead, the data are explained by a combination of seawater-basalt reactions within the upper basement and diffusive exchange with overlying sediment, as part of a shallow, ridge-flank hydrothermal system. It is unclear why this site has an elevated heat flux relative to neighboring crust, but this may result from variations in crustal properties or modification related to flexural faulting outboard of the trench.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1029/2023GC011246
Keywords: formation water; hydrogeology; hydrothermal; Middle American Trench; pore water; ridge flank

Interactions between local glaciers and adjacent grounded Ross Sea ice in the Royal Society Range, Antarctica - Miles, Maraina; Hall, Brenda; Denton, George (Quaternary Science Reviews, 2024)
The Antarctic Ice Sheet (AIS) has the potential to exert a major control on future global sea level. Here, we gain insight into the response of the Antarctic Ice Sheet (AIS) to changing climate through assessment of ice-sheet behavior during and since the Last Glacial Maximum (LGM) along the western coast of McMurdo Sound. We examine whether expansion of grounded ice in this sector of the Ross Embayment during the last glaciation was caused by increased flux from East Antarctic outlets and local glaciers or was produced by marine influences, such as lowered sea level or reduced melting of submarine grounded ice. During the LGM, grounded ice derived from the Ross Sea deposited a well-defined drift sheet along the Royal Society headlands on the western coast of McMurdo Sound. Twenty-six new radiocarbon dates of subfossil algae within this drift sheet suggest that the ice sheet was at its maximum extent by at least ∼18.4 ka and maintained this position for about five thousand years. Cross-cutting relationships show that local alpine glaciers did not contribute to the grounded ice but rather fluctuated asynchronously. This same relationship held true during the penultimate glaciation, dated to roughly 137–191 ka with 10Be exposure ages. An explanation for this out-of-phase relationship is that different mechanisms controlled their respective extents. Because they lack significant surface melting ablation zones, the local alpine glaciers, which largely terminate on land, were driven by changes in accumulation. These glaciers likely expanded during warmer times when accumulation was higher. In contrast, marine factors, such as global sea-level change and/or subglacial melting, controlled ice fluctuations in the Ross Embayment, including McMurdo Sound, leading to advance during the LGM.
Keywords: Alpine glaciers; Antarctica; Be exposure age dating; Last glacial maximum; radiocarbon; Ross Sea

Puzzling parrotfishes: Radiocarbon age validation and updated longevity estimates for western Atlantic species in support of sustainable fisheries management - Hernandez, Jesus M. Rivera; Shervette, Virginia R. (PLOS ONE, 2024)
For management efforts to succeed in Caribbean fisheries, local fishers must support and be willing to comply with fishing regulations. This is more likely when fishers are included in a stock assessment process that utilizes robust scientific evidence, collected in collaboration with fishers, to evaluate the health of fish stocks. Caribbean parrotfishes are important contributors to coral reef ecosystem health while also contributing to local fisheries. Scientifically robust stock assessments require regional species-specific information on age-based key life history parameters, derived from fish age estimates. Evaluation of the accuracy of age estimation methods for fish species is a critical initial step in managing species for long-term sustainable harvest. The current study resulted from a collaborative research program between fish biologists and local fishers investigating age, growth, and reproductive biology of the seven parrotfish species landed in U.S. Caribbean fisheries; specifically, we validated age estimation for stoplight parrotfish Sparisoma viride and queen parrotfish Scarus vetula. This is the first study to directly validate age estimation for any parrotfish species through analysis of Δ14C from eye lens cores. Our age estimation validation results show that enumeration of opaque zones from thin sections of sagittal otoliths for a Sparisoma and a Scarus species provides accurate age estimates. The oldest stoplight parrotfish and queen parrotfish in the Δ14C age estimation validation series were 14 y and 16 y; while the oldest stoplight parrotfish and queen parrotfish we aged to-date using the Δ14C validated age estimation method were 20 y and 21 y, respectively. Fish longevity (maximum age attained/life span) is a key life history parameter used for estimation of natural mortality, survivorship, and lifetime reproductive output. Past reviews on parrotfishes from the Pacific and Atlantic concluded that most Caribbean/western Atlantic parrotfish species are relatively short-lived with estimated maximum ages ranging from 3–9 y. However, information from our collaborative research in the U.S. Caribbean combined with recently published age estimates for Brazilian parrotfish species indicate that many western Atlantic parrotfishes are relatively long-lived with several species attaining maximum ages in excess of 20 y.
Publisher: Public Library of Science
Keywords: Caribbean; coral reefs; Eye lens; Fish biology; Fisheries; Marine fish; Otolith; Spawning

Comparability of Radiocarbon Measurements in Dissolved Inorganic Carbon of Seawater Produced at ETH-Zurich - Castrillejo, Maxi; Hansman, Roberta L.; Graven, Heather D.; Lester, Joanna G.; Bollhalder, Silvia; Kündig, Kayley; Wacker, Lukas (Radiocarbon, 2023)
Radiocarbon observations (Δ14C) in dissolved inorganic carbon (DIC) of seawater provide useful information about ocean carbon cycling and ocean circulation. To deliver high-quality observations, the Laboratory of Ion Beam Physics (LIP) at ETH-Zurich developed a new simplified method allowing the rapid analysis of radiocarbon in DIC of small seawater samples, which is continually assessed by following internal quality controls. However, a comparison with externally produced 14C measurements to better establish an equivalency between methods was still missing. Here, we make the first intercomparison with the National Ocean Sciences Accelerator Mass Spectrometry (NOSAMS) facility based on 14 duplicate seawater samples collected in 2020. We also compare with prior deep-water observations from the 1970s to 1990s. The results show a very good agreement in both comparisons. The mean Δ14C of 12 duplicate samples measured by LIP and NOSAMS were statistically identical within one sigma uncertainty while two other duplicate samples agreed within two sigma. Based on this small number of duplicate samples, LIP values appear to be slightly lower than the NOSAMS values, but more measurements will be needed for confirmation. We also comment on storage and preservation techniques used in this study, including the freezing of samples collected in foil bags.
Publisher: Cambridge University Press
Keywords: 14C; comparison; DIC; dissolved inorganic carbon; radiocarbon; SEAWATER

Earthquake-enhanced dissolved carbon cycles in ultra-deep ocean sediments - Chu, Mengfan; Bao, Rui; Strasser, Michael; Ikehara, Ken; Everest, Jez; Maeda, Lena; Hochmuth, Katharina; Xu, Li; McNichol, Ann; Bellanova, Piero; Rasbury, Troy; Kölling, Martin; et al. (Nature Communications, 2023)
Hadal trenches are unique geological and ecological systems located along subduction zones. Earthquake-triggered turbidites act as efficient transport pathways of organic carbon (OC), yet remineralization and transformation of OC in these systems are not comprehensively understood. Here we measure concentrations and stable- and radiocarbon isotope signatures of dissolved organic and inorganic carbon (DOC, DIC) in the subsurface sediment interstitial water along the Japan Trench axis collected during the IODP Expedition 386. We find accumulation and aging of DOC and DIC in the subsurface sediments, which we interpret as enhanced production of labile dissolved carbon owing to earthquake-triggered turbidites, which supports intensive microbial methanogenesis in the trench sediments. The residual dissolved carbon accumulates in deep subsurface sediments and may continue to fuel the deep biosphere. Tectonic events can therefore enhance carbon accumulation and stimulate carbon transformation in plate convergent trench systems, which may accelerate carbon export into the subduction zones., Earthquakes enhance dissolved carbon production and fuel the microbial activities in hadal trench subsurface sediments, and ultimately strengthen carbon accumulation and transformation in the subduction zones.

Independent age estimates resolve the controversy of ancient human footprints at White Sands - Pigati, Jeffrey S.; Springer, Kathleen B.; Honke, Jeffrey S.; Wahl, David; Champagne, Marie R.; ZIMMERMAN, SUSAN R. H.; Gray, Harrison J.; Santucci, Vincent L.; Odess, Daniel; Bustos, David; Bennett, Matthew R. (Science, 2023)
Human footprints at White Sands National Park, New Mexico, USA, reportedly date to between ~23,000 and 21,000 years ago according to radiocarbon dating of seeds from the aquatic plant Ruppia cirrhosa. These ages remain controversial because of potential old carbon reservoir effects that could compromise their accuracy. We present new calibrated 14C ages of terrestrial pollen collected from the same stratigraphic horizons as those of the Ruppia seeds, along with optically stimulated luminescence ages of sediments from within the human footprint–bearing sequence, to evaluate the veracity of the seed ages. The results show that the chronologic framework originally established for the White Sands footprints is robust and reaffirm that humans were present in North America during the Last Glacial Maximum.
Publisher: American Association for the Advancement of Science

Machine learning based anomaly detection for sedimentological data: Application to a Holocene multi-proxy paleoenvironmental reconstruction from Laguna Boquita, Jalisco, Mexico - Bianchette, Thomas A.; Pandey, Vijitashwa; Mollan, Calahan; Hall, Sawyer; McCloskey, Terrence A.; Liu, Kam-biu (Marine Geology, 2023)
Paleoenvironmental reconstructions are critical to determine past climatological and hydrological conditions, such as sea-level rise (SLR) and extreme events including hurricanes and tsunamis. While established quantitative methods, such as principal components analysis and discriminant analysis, have effectively aided reconstructions by demarcating stratigraphic zones, they suffer from limitations due to the underlying assumptions (linearity, normality). Here, we introduce the machine learning technique anomaly detection for sedimentological reconstructions, capable of objectively pinpointing events (anomalies) in sediment cores. We tested this technique on five sediment cores extracted from Laguna Boquita, located along the Pacific coast of Mexico. Each core was subjected to high resolution loss-on-ignition, while the most representative core (core 1) was deemed the training core and scanned with a handheld XRF unit. In general, the sediment cores were dominated by thick units of peat and/or clay, and most cores contained sand layers. This reconstruction represents many environmental settings, ranging from a sandy terrestrial environment (∼6830- ∼ 6370 cal yr BP), organic-rich wetland (∼6370- ∼ 5170 cal yr BP), and clastic-rich backbarrier lagoon (∼5170 cal yr BP to present). The anomaly detection technique proved effective in marking many events, including marine transgression, evidence of SLR, transitions separating dominant depositional environments, and, perhaps most notably, a faded blue clay layer with minimal LOI variability that may represent a shift in backbarrier water level. The anomaly detection also registered anomalies when events were not visually distinct nor present in the LOI datasets (false positives), which represent sediment core sections that require further investigation with multiple proxies. However, anomaly detection failed to register anomalies in certain core sections that should have registered as events due to their distinct nature. Future efforts will look to improve anomaly detection by choosing different train cores and adding additional proxy datasets.
Keywords: Loss-on-ignition; Machine learning; Paleoclimate; peat; Radiocarbon dating; x-ray fluorescence

More Frequent Hurricane Passage Across the Bahamian Archipelago During the Little Ice Age - Winkler, T. S.; van Hengstum, P. J.; Donnelly, J. P.; Wallace, E. J.; Albury, N. A.; D’Entremont, N.; Hawkes, A. D.; Maio, C. V.; Roberts, J.; Sullivan, R. M.; Woodruff, J. D. (Paleoceanography and Paleoclimatology, 2023)
The year 2020 Common Era (CE) experienced the highest number of named tropical cyclones in the Atlantic Ocean since 1850 CE, but the short instrumental record makes it challenging to assess if this level of activity is statistically meaningful. Here, we present two near-annually resolved hurricane reconstructions from sediment archived in two blue holes located only 300 m apart on the northern margin of Grand Bahama. These two blue holes provide a replicated signal of hurricanes passing within a 50–100 km radius over the last 1,800 years, and the long-term reconstructions document multiple 50-to-150-year intervals when hurricane frequency was significantly higher than it has been over the last 100 years. These two records were first merged into a single stack, and then compiled with five other high-resolution reconstructions from across the Bahamian Archipelago to form a single 1500-year record of Bahamian hurricane frequency. This new Bahamian Compilation documents more hurricanes passing ∼75°W from 21°N to 26°N during the Little Ice Age (LIA; 1300–1850 CE) relative to the prior millennium and the last 170 years. The US Eastern Seaboard also experienced heightened hurricane activity during the LIA, whereas the Gulf of Mexico and Southern Caribbean were inactive. This suggests that despite a globally cooler climate, regional climate conditions during the LIA remained favorable for cyclogenesis and intensification along certain Atlantic hurricane pathways. Perhaps heightened Sahel rainfall during the LIA indicates an increase in African Easterly waves, which in turn possibly seeded more tropical cyclones in the Atlantic Main Development Region.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1029/2023PA004623
Keywords: Bahamas; Carbonate; common era; hurricanes; Paleoclimate; sedimentology

Sequential thermal analysis of complex organic mixtures: Procedural standards and improved CO2 purification capacity - Hanke, Ulrich M.; Gagnon, Alan R.; Reddy, Christopher M.; Gaylord, Mary C. Lardie; Cruz, Anne J.; Galy, Valier; Hansman, Roberta L.; Kurz, Mark D. (Radiocarbon, 2023)
Sequential thermal analysis allows for deconvoluting the refractory nature and complexity of carbon mixtures embedded in mineral matrices for subsequent offline stable carbon and radiocarbon (14C) isotope analyses. Originally developed to separate Holocene from more ancient sedimentary organic matter to improve dating of marine sediments, the Ramped Pyrolysis and Oxidation (RPO) apparatus, or informally, the “dirt burner” is now used to address pressing questions in the broad field of biogeochemistry. The growing interest in the community now necessitates improved handling and procedures for routine analyses of difficult sample types. Here we report on advances in CO2 purification during sample processing, modifications to the instrumentation at the National Ocean Sciences Accelerator Mass Spectrometry (NOSAMS) facility, and introduce sodium bicarbonate procedural standards with differing natural abundance 14C signatures for blank assessment. Measurements from different environmental samples are used to compare the procedure to the different generations of sequential thermal analyses. With this study, we aim to improve the standardization of the procedures and prepare this instrumentation for innovations in online stable carbon isotopes and direct AMS-interface measurements in the future.
Publisher: Cambridge University Press
Keywords: chemical analysis; dirt burner; full oxidation (FOX) mode; Radiocarbon dating; ramped pyrolysis oxidation

A Tropical Cocktail of Organic Matter Sources: Variability in Supraglacial and Glacier Outflow Dissolved Organic Matter Composition and Age Across the Ecuadorian Andes - Holt, Amy D.; Kellerman, Anne M.; Battin, Tom. I.; McKenna, Amy M.; Hood, Eran; Andino, Patricio; Crespo-Pérez, Verónica; Peter, Hannes; Schön, Martina; De Staercke, Vincent; Styllas, Michail; Tolosano, Matteo; et al. (Journal of Geophysical Research: Biogeosciences, 2023)
The biogeochemistry of rapidly retreating Andean glaciers is poorly understood, and Ecuadorian glacier dissolved organic matter (DOM) composition is unknown. This study examined molecular composition and carbon isotopes of DOM from supraglacial and outflow streams (n = 5 and 14, respectively) across five ice capped volcanoes in Ecuador. Compositional metrics were paired with streamwater isotope analyses (δ18O) to assess if outflow DOM composition was associated with regional precipitation gradients and thus an atmospheric origin of glacier DOM. Ecuadorian glacier outflows exported ancient, biolabile dissolved organic carbon (DOC), and DOM contained a high relative abundance (RA) of aliphatic and peptide-like compounds (≥27%RA). Outflows were consistently more depleted in Δ14C-DOC (i.e., older) compared to supraglacial streams (mean −195.2 and −61.3‰ respectively), perhaps due to integration of spatially heterogenous and variably aged DOM pools across the supraglacial environment, or incorporation of aged subglacial OM as runoff was routed to the outflow. Across Ecuador, Δ14C-DOC enrichment was associated with decreased aromaticity of DOM, due to increased contributions of organic matter (OM) from microbial processes or atmospheric deposition of recently fixed and subsequently degraded OM (e.g., biomass burning byproducts). There was a regional gradient between glacier outflow DOM composition and streamwater δ18O, suggesting covariation between regional precipitation gradients and the DOM exported from glacier outflows. Ultimately, this highlights that atmospheric deposition may exert a control on glacier outflow DOM composition, suggesting regional air circulation patterns and precipitation sources in part determine the origins and quality of OM exported from glacier environments.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1029/2022JG007188
Keywords: cryosphere; dissolved organic carbon; Dissolved organic matter; Ecuador; FT-ICR MS; glaciers; δ13C-DOC; Δ14C-DOC

An 11,300 yr record of paleoclimatology and paleoceanography of the central California coast in a gravity core from Pioneer Seamount - Barron, John A.; Addison, Jason A.; Heusser, Linda E.; Bukry, David; Schwartz, Valerie; Wagner, Amy (Quaternary International, 2022)
Diatom, pollen, silicoflagellate, and biogenic opal analyses from a 155 cm-long gravity core from Pioneer Seamount, offshore Santa Cruz, California (PS1410-06 GC, latitude 37.3°N, longitude 123.4°W, water depth 2165 m) are compiled for the last ~11,300 years and compared with those of ODP 1019 and TN062-O550 from northern California. The relative abundance record of the subtropical diatom Fragilariopsis doliolus has similar bimodal Holocene patterns in all three cores, suggesting that sea surface temperatures (SST) were lower during the middle part of the Holocene than they were during the later and earlier parts. The relative abundance of coastal redwood (Sequoia sempervirens) pollen, a proxy for fog and coastal upwelling, displays stepwise increases in ODP 1019 and TN062-O550 between ~ 4000 and 3000 cal yr. BP, but its relative abundance in PS1410-06 GC increases gradually throughout the past 10,200 yr without any major steps. Similarly, biogenic silica (opal) displays stepwise increases at ~3600 and 2900 cal yr. BP in ODP 1019 and TN062-O550, respectively, whereas opal increases more gradually in PS1410-06 GC during the past 10,100 yr with relatively minor steps at ~3100 and ~2600 cal yr. BP. Together, coastal redwood and opal argue for a more gradual late Holocene increase in coastal upwelling along the coast of central California compared with that off northern California, where onshore-offshore gradients are more distinct.

Age and water-quality characteristics of groundwater discharge to the South Loup River, Nebraska, 2019 - Hobza, Christopher M.; Solder, John E. (Scientific Investigations Report, 2022)
Streams in the Loup River Basin are sensitive to groundwater withdrawals because of the close hydrologic connection between groundwater and surface water. The U.S. Geological Survey, in cooperation with the Upper Loup and Lower Loup Natural Resources Districts, and the Nebraska Environmental Trust, studied the age and water-quality characteristics of groundwater near the South Loup River to assess the possible effects of a multiyear drought on streamflow. Groundwater sampled in wells screened in Quaternary-age deposits displayed a wide range of mean ages (27 to 2,100 years), fraction modern, and susceptibility index values. Groundwater with higher concentrations of chloride and higher specific conductance was indicative of younger groundwater with a narrower age distribution and is more sensitive to climatic disturbances such as short-term drought conditions, based on the calculated susceptibility index. Groundwater samples from wells and springs in Pliocene-age deposits were categorized into two groups with different geochemical and age characteristics. One sample group of springs and wells, called the Western Pliocene, had higher concentrations of chloride and nitrate with young mean ages (18 to 77 years) and narrow age distributions. Groundwater in the Western Pliocene sample group is susceptible to short-term drought. In contrast, the other sample group from Pliocene-age deposits to the east (called Pliocene) had lower concentrations of nitrate, chloride, and mean groundwater ages ranging from 1,900 to 2,900 years old and is less likely to be affected by short-term drought conditions. Groundwater sampled from three wells screened in the Ogallala Formation was shown to have the oldest mean ages ranging from 8,700 to 23,000 years and the lowest calculated susceptibility index values observed in this study. Strong upward hydraulic gradients measured in wells indicated that groundwater from the Ogallala Formation is likely contributing to streamflow of the South Loup River. Continuously measured gage height and specific conductance data indicated groundwater discharge from Quaternary-age deposits was highly responsive to precipitation events. In contrast, groundwater discharge from Pliocene-age deposits (Pliocene sample group) was far less responsive, indicating groundwater discharge from Pliocene-age deposits is likely more resilient to short-term drought conditions.

Black carbon and organic carbon dataset over the Third Pole - Kang, Shichang; Zhang, Yulan; Chen, Pengfei; Guo, Junming; Zhang, Qianggong; Cong, Zhiyuan; Kaspari, Susan; Tripathee, Lekhendra; Gao, Tanguang; Niu, Hewen; Zhong, Xinyue; Chen, Xintong; et al. (Earth System Science Data, 2022)
Abstract. The Tibetan Plateau and its surroundings, also known as the Third Pole, play an important role in the global and regional climate and hydrological cycle. Carbonaceous aerosols (CAs), including black carbon (BC) and organic carbon (OC), can directly or indirectly absorb and scatter solar radiation and change the energy balance on the Earth. CAs, along with the other atmospheric pollutants (e.g., mercury), can be frequently transported over long distances into the inland Tibetan Plateau. During the last decades, a coordinated monitoring network and research program named “Atmospheric Pollution and Cryospheric Changes” (APCC) has been gradually set up and continuously operated within the Third Pole regions to investigate the linkage between atmospheric pollutants and cryospheric changes. This paper presents a systematic dataset of BC, OC, water-soluble organic carbon (WSOC), and water-insoluble organic carbon (WIOC) from aerosols (20 stations), glaciers (17 glaciers, including samples from surface snow and ice, snow pits, and 2 ice cores), snow cover (2 stations continuously observed and 138 locations surveyed once), precipitation (6 stations), and lake sediment cores (7 lakes) collected across the Third Pole, based on the APCC program. These data were created based on online (in situ) and laboratory measurements. High-resolution (daily scale) atmospheric-equivalent BC concentrations were obtained by using an Aethalometer (AE-33) in the Mt. Everest (Qomolangma) region, which can provide new insight into the mechanism of BC transportation over the Himalayas. Spatial distributions of BC, OC, WSOC, and WIOC from aerosols, glaciers, snow cover, and precipitation indicated different features among the different regions of the Third Pole, which were mostly influenced by emission sources, transport pathways, and deposition processes. Historical records of BC from ice cores and lake sediment cores revealed the strength of the impacts of human activity since the Industrial Revolution. BC isotopes from glaciers and aerosols identified the relative contributions of biomass and fossil fuel combustion to BC deposition on the Third Pole. Mass absorption cross sections of BC and WSOC from aerosol, glaciers, snow cover, and precipitation samples were also provided. This updated dataset is released to the scientific communities focusing on atmospheric science, cryospheric science, hydrology, climatology, and environmental science. The related datasets are presented in the form of excel files. BC and OC datasets over the Third Pole are available to download from the National Cryosphere Desert Data Center (https://doi.org/10.12072/ncdc.NIEER.db0114.2021; Kang and Zhang, 2021).

Carbon Accumulation, Flux, and Fate in Stordalen Mire, a Permafrost Peatland in Transition - Holmes, M. E.; Crill, P. M.; Burnett, W. C.; McCalley, C. K.; Wilson, R. M.; Frolking, S.; Chang, K.‐Y.; Riley, W. J.; Varner, R. K.; Hodgkins, S. B.; McNichol, A. P.; Saleska, S. R.; et al. (Global Biogeochemical Cycles, 2022)
Stordalen Mire is a peatland in the discontinuous permafrost zone in arctic Sweden that exhibits a habitat gradient from permafrost palsa, to Sphagnum bog underlain by permafrost, to Eriophorum‐dominated fully thawed fen. We used three independent approaches to evaluate the annual, multi‐decadal, and millennial apparent carbon accumulation rates (aCAR) across this gradient: seven years of direct semi‐continuous measurement of CO2 and CH4 exchange, and 21 core profiles for 210Pb and 14C peat dating. Year‐round chamber measurements indicated net carbon balance of −13 ± 8, −49 ± 15, and −91 ± 43 g C m−2 y−1 for the years 2012–2018 in palsa, bog, and fen, respectively. Methane emission offset 2%, 7%, and 17% of the CO2 uptake rate across this gradient. Recent aCAR indicates higher C accumulation rates in surface peats in the palsa and bog compared to current CO2 fluxes, but these assessments are more similar in the fen. aCAR increased from low millennial‐scale levels (17–29 g C m−2 y−1) to moderate aCAR of the past century (72–81 g C m−2 y−1) to higher recent aCAR of 90–147 g C m−2 y−1. Recent permafrost collapse, greater inundation and vegetation response has made the landscape a stronger CO2 sink, but this CO2 sink is increasingly offset by rising CH4 emissions, dominated by modern carbon as determined by 14C. The higher CH4 emissions result in higher net CO2‐equivalent emissions, indicating that radiative forcing of this mire and similar permafrost ecosystems will exert a warming influence on future climate. Stordalen Mire, a permafrost peatland, has become a stronger carbon sink due to shifts in vegetation and inundation accompanying thaw This stronger carbon sink is offset by an increase in methane emission, resulting in higher net CO2‐equivalent emissions Analysis of respiration products indicates that methane emission from the fen and bog are dominated by modern carbon Stordalen Mire, a permafrost peatland, has become a stronger carbon sink due to shifts in vegetation and inundation accompanying thaw This stronger carbon sink is offset by an increase in methane emission, resulting in higher net CO2‐equivalent emissions Analysis of respiration products indicates that methane emission from the fen and bog are dominated by modern carbon

Community practice and religion at an Early Islamic cemetery in highland Central Asia - Bullion, Elissa; Maksudov, Farhod; Henry, Edward R.; Merkle, Ann; Frachetti, Michael (Antiquity, 2022)
Archaeological studies of Early Islamic communities in Central Asia have focused on lowland urban communities. Here, the authors report on recent geophysical survey and excavation of an Early Islamic cemetery at Tashbulak in south-eastern Uzbekistan. AMS dating places the establishment of the cemetery in the mid-eighth century AD, making it one of the earliest Islamic burial grounds documented in Central Asia. Burials at Tashbulak conform to Islamic prescriptions for grave form and body deposition. The consistency in ritual suggests the existence of a funerary community of practice, challenging narratives of Islamic conversion in peripheral areas as a process of slow diffusion and emphasising the importance of archaeological approaches for documenting the diversity of Early Islamic communities.

Cultural Keystone Places and the Chumash Landscapes of Kumqaq’, Point Conception, California - Rick, Torben C.; Braje, Todd J.; Graham, Lain; Easterday, Kelly; Hofman, Courtney A.; Holguin, Brian E.; Mychajliw, Alexis M.; Reeder-Myers, Leslie A.; Reynolds, Mark D. (American Antiquity, 2022)
The places in which people live and spend time are steeped in history, memory, and meaning from the intersection of daily life, environmental interactions, cultural practices, and ritual. Geologic features, plants, animals, and ecosystems merge with these cultural histories, forming critical parts of the landscape and areas of “high cultural salience,” or “cultural keystone places” (CKPs). We identify Kumqaq’ (Point Conception) and the surrounding area in California as a Chumash CKP. Ethnohistoric accounts and contemporary Chumash community members have long demonstrated the importance of Point Conception in Chumash worldview and identity, whereas biologists, ecologists, and conservationists reference the area's rich biodiversity and significance as a biogeographical boundary. Recent archaeological survey of the coastline surrounding Kumqaq’ highlights these connections, identifying over 50 archaeological sites—including shell middens, villages, lithic scatters, and rock art—with at least 9,000 years of occupation. Ongoing collaborations among archaeologists, the Nature Conservancy, and Chumash community members help document and understand the long-term linkages between cultural and biological diversity and how integrating these perspectives can help ensure the resilience of this nexus of human and natural history in the Anthropocene future.

Geochemistry and Provenance of Springs in a Baja California Sur Mountain Catchment - Lerback, Jory C.; Bowen, Brenda B.; Humphrey, C. E.; Fernandez, Diego. P.; Bernau, Jeremiah A.; Macfarlan, Shane J.; Schniter, Eric; Garcia, J. J. (Groundwater, 2022)
Fractured rock aquifers cover much of Earth's surface and are important mountain sites for groundwater recharge but are poorly understood. To investigate groundwater systematics of a fractured-dominated aquifer in Baja California Sur, Mexico, we examined the spatial patterns of aquifer recharge and connectivity using the geochemistry of springs. We evaluate a range of geochemical data within the context of two endmember hypotheses describing spatial recharge patterns and fracture connectivity. Hypothesis 1 is that the aquifer system is segmented, and springs are fed by local recharge. Hypothesis 2 is that the aquifer system is well connected, with dominant recharge occurring in the higher elevations. The study site is a small <15 km2 catchment. Thirty-four distinct springs and two wells were identified in the study area, and 24 of these sites were sampled for geochemical analyses along an elevation gradient and canyon transect. These analyses included major ion composition, trace element and strontium isotopes, δ18 O and δ2 H isotopes, radiocarbon, and tritium. δ18 O and δ2 H isotopes suggest that the precipitation feeding the groundwater system has at least two distinct sources. Carbon isotopes showed a change along the canyon transect, suggesting that shorter flowpaths feed springs in the top of the transect, and longer flowpaths discharge near the bottom. Geochemical interpretations support a combination of the two proposed hypotheses. Understanding of the connectivity and provenance of these springs is significant as they are the primary source of water for the communities that inhabit this region and may be impacted by changes in recharge and use.

The giant 1960 tsunami in the context of a 6000‐year record of paleotsunamis and coastal evolution in south‐central Chile - Matos‐Llavona, Pedro I.; Ely, Lisa L.; MacInnes, Breanyn; Dura, Tina; Cisternas, Marco A.; Bourgeois, Joanne; Bruce, David; DePaolis, Jessica; Dolcimascolo, Alexander; Horton, Benjamin P.; Melnick, Daniel; Nelson, Alan R.; et al. (Earth Surface Processes and Landforms, 2022)
The tsunami associated with the giant 9.5 Mw 1960 Chile earthquake deposited an extensive sand layer above organic‐rich soils near Queule (39.3°S, 73.2°W), south‐central Chile. Using the 1960 tsunami deposits, together with eye‐witness observations and numerical simulations of tsunami inundation, we tested the tsunami inundation sensitivity of the site to different earthquake slip distributions. Stratigraphically below the 1960 deposit are two additional widespread sand layers interpreted as tsunami deposits with maximum ages of 4960–4520 and 5930–5740 cal BP. This >4500‐year gap of tsunami deposits preserved in the stratigraphic record is inconsistent with written and geological records of large tsunamis in south‐central Chile in 1575, 1837, and possibly 1737. We explain this discrepancy by: (1) poor preservation of tsunami deposits due to reduced accommodation space from relative sea‐level fall during the late Holocene; (2) recently evolved coastal geomorphology that increased sediment availability for tsunami deposit formation in 1960; and/or (3) the possibility that the 1960 tsunami was significantly larger at this particular location than other tsunamis in the past >4500 years. Our research illustrates the complexities of reconstructing a complete stratigraphic record of past tsunamis from a single site for tsunami hazard assessment. The coastal geomorphology near Queule, Chile preserves evidence of the giant Mw 9.51960 Chile earthquake and two buried paleotsunami deposits within the last 6000 years. Using the 1960 tsunami deposits, eye‐witness observations, and numerical simulations of tsunami inundation, we tested the sensitivity of the site to different earthquake slip distributions. We consider the role of coastal geomorphic evolution, sea‐level history, and tsunami magnitude in the preservation of paleotsunami depositional records.

Iberian hydroclimate variability and the Azores High during the last 1200 years: evidence from proxy records and climate model simulations - Thatcher, Diana L.; Wanamaker, A. D.; Denniston, R. F.; Ummenhofer, C. C.; Asmerom, Y.; Polyak, V. J.; Cresswell-Clay, N.; Hasiuk, F.; Haws, J.; Gillikin, D. P. (Climate Dynamics, 2022)
The state of the atmospheric circulation and the associated hydroclimate in the North Atlantic during the last millennium remain the subject of considerable debate in both proxy- and model-based studies. Of particular interest in the Iberian region is the Azores High (AH) system, the southern node of the North Atlantic Oscillation (NAO), an atmospheric dipole closely tied to regional hydroclimate. Hydroclimate-sensitive proxy reconstructions from this region offer some insights into atmospheric dynamics, but large spatiotemporal gaps in these data inhibit a robust evaluation of hydroclimate variability. In this study, we present a continuous, sub-decadally-resolved composite stalagmite carbon isotopic record from three partially overlapping stalagmites from Buraca Gloriosa (BG) cave, western Portugal, situated within the center of the AH, that preserves evidence of regional hydroclimate variability from approximately 800 CE to the present. Chronologies are derived from U/Th dating and annual laminae. Stalagmite carbon isotopic values primarily reflect the amount of effective moisture and reveal generally dry conditions during the Medieval Climate Anomaly (MCA; 850–1250 CE) and Modern Climate/Industrial Era (1850 CE-present), and wetter conditions during the Little Ice Age (LIA; 1400–1850 CE). Multidecadal to centennial variability in the BG record and state-of-the-art last millennium climate model simulations show considerable coherence with precipitation-sensitive records from Spain and Morocco that, like BG, are strongly influenced by the intensity, size, and location of the AH. Model-proxy synthesis suggests that western Portugal was persistently dry during much of the MCA consistent with other NAO reconstructions; however, even considering age uncertainties, the apparent timing in the transition from a relatively dry MCA to a wetter LIA is spatially variable and confirms the non-stationary behavior of the AH system indicated by model output.
Keywords: Azores High; Hydroclimate; last millennium; Last Millennium Ensemble; Paleoclimate; Stalagmite

Ice-sheet expansion from the Ross Sea into McMurdo Sound, Antarctica, during the last two glaciations - Heath, Stephanie; Hall, Brenda L.; Denton, George H.; Henderson, Gideon M.; Hendy, Chris H. (Quaternary Science Reviews, 2022)
An understanding of Antarctic Ice Sheet (AIS) behavior is important for future sea-level predictions. Here, we examine past ice-sheet history in the McMurdo Sound region of the western Ross Sea over the last two glacial-interglacial cycles in order to gain insight into the drivers of ice-sheet change. Surficial mapping, along with radiocarbon dates of lacustrine algae and uranium-thorium disequilibrium dates of lacustrine carbonates from ice-dammed lakes, allow reconstruction of the timing and origin of grounded ice in McMurdo Sound during the last glacial maximum (LGM) and penultimate glaciation. During the LGM, ice-surface elevation profiles and distribution of erratics indicate ice flow into southern McMurdo Sound from the Ross Sea, rather than seaward expansion of local glaciers from the Royal Society Range. The grounded ice in McMurdo Sound flowed westward to block the mouths of valleys in the Royal Society Range and to dam proglacial lakes. In Marshall Valley, maximum ice extent during what is termed the Ross Sea glaciation, was achieved by 18 ka and remained close to this position until after 14 ka. The pattern of surficial deposits suggests that ice during the penultimate glaciation, locally named the Marshall glaciation, was slightly more extensive than that of the LGM but had a similar Ross Sea origin. Maximum ice extent in Marshall Valley occurred at ∼145–150 ka; the grounded ice may have receded from the valley mouth shortly after 138 ka. Both ice expansions occurred broadly during times of low Antarctic air temperatures, which have been linked to insolation minima. However, the lack of widespread surface melting ablation zones on the AIS indicates that the link between ice expansion and orbital forcing is likely to be indirect and possibly driven through the ocean. Closer examination of the precise timing of the glacial maxima in Marshall Valley shows that the Marshall glaciation occurred synchronously with the penultimate global maximum; ice recession took place during Termination II. In contrast, maximum ice extent during the Ross Sea glaciation along the Royal Society Range occurred after the global LGM, during Termination I. Deglaciation was primarily an early Holocene event. We attribute this delayed maximum and deglaciation (relative to global events) to the effect of rising accumulation on ice-sheet mass balance.

Implications of Single-Step Graphitization For Reconstructing Late Holocene Relative Sea-Level Using Radiocarbon-Dated Organic Coastal Sediment - Sefton, Juliet P.; Kemp, Andrew C.; Elder, Kathryn L.; Hansman, Roberta L.; Roberts, Mark L. (Radiocarbon, 2022)
Late Holocene relative sea-level reconstructions are commonly generated using proxies preserved in salt-marsh and mangrove sediment. These depositional environments provide abundant material for radiocarbon dating in the form of identifiable macrofossils (salt marshes) and bulk organic sediment (mangroves). We explore if single-step graphitization of these samples in preparation for radiocarbon dating can increase the number and temporal resolution of relative sea-level reconstructions without a corresponding increase in cost. Dating of salt-marsh macrofossils from the northeastern United States and bulk mangrove sediment from the Federated States of Micronesia indicates that single-step graphitization generates radiocarbon ages that are indistinguishable from replicates prepared using traditional graphitization, but with a modest increase in error (mean/maximum of 6.25/15 additional 14C yr for salt-marsh macrofossils). Low 12C currents measured on bulk mangrove sediment following single-step graphitization likely render them unreliable despite their apparent accuracy. Simulated chronologies for six salt-marsh cores indicate that having twice as many radiocarbon dates (since single-step graphitization costs ∼50% of traditional graphitization) results in narrower confidence intervals for sample age estimated by age-depth models when the additional error from the single-step method is less than ∼50 14C yr (∼30 14C yr if the chronology also utilizes historical age markers). Since these thresholds are greater than our empirical estimates of the additional error, we conclude that adopting single-step graphitization for radiocarbon measurements on plant macrofossils is likely to increase precision of age-depth models by more than 20/10% (without/with historical age markers). This improvement can be implemented without additional cost.
Keywords: age-depth model; mangrove; Massachusetts; Micronesia; Salt marsh

In-phase millennial-scale glacier changes in the tropics and North Atlantic regions during the HoloceneAbstract - Jomelli, V.; Swingedouw, D.; Vuille, M.; Favier, V.; Goehring, B.; Shakun, J.; Braucher, R.; Schimmelpfennig, I.; Menviel, L.; Rabatel, A.; Martin, L. C. P.; Blard, P.-H.; et al. (Nature Communications, 2022)
Based on new and published cosmic-ray exposure chronologies, we show that glacier extent in the tropical Andes and the north Atlantic regions (TANAR) varied in-phase on millennial timescales during the Holocene, distinct from other regions. Glaciers experienced an early Holocene maximum extent, followed by a strong mid-Holocene retreat and a re-advance in the late Holocene. We further explore the potential forcing of TANAR glacier variations using transient climate simulations. Since the Atlantic Meridional Overturning Circulation (AMOC) evolution is poorly represented in these transient simulations, we develop a semi-empirical model to estimate the “AMOC-corrected” temperature and precipitation footprint at regional scales. We show that variations in the AMOC strength during the Holocene are consistent with the observed glacier changes. Our findings highlight the need to better constrain past AMOC behavior, as it may be an important driver of TANAR glacier variations during the Holocene, superimposed on other forcing mechanisms.

Large fluxes of continental-shelf-borne dissolved organic carbon in the East China Sea and the Yellow Sea - Han, Heejun; Na, Taehee; Cho, Hyung-Mi; Kim, Guebuem; Hwang, Jeomshik (Marine Chemistry, 2022)
Fluxes of dissolved organic carbon (DOC) from continental shelves to the ocean may play a critical role in marine carbon cycling and budget. However, these fluxes have been poorly constrained because complicated biogeochemical reactions of riverine, atmospheric, and marine organic carbon occur in continental shelf-waters. We used multiple tracers of DOC such as stable- and radiocarbon isotope ratios of DOC, fluorescent properties of dissolved organic matter (FDOM), and 228Ra as a water age tracer to investigate the sources and fluxes of DOC in the northwest Pacific continental margin of the East China Sea and the Yellow Sea. Here, we show that there are significant additional (excess) supplies of DOC in the central Yellow Sea relative to the Changjiang (Yangtze River) source, based on these tracers. The marine δ13C signature (−21.1 ± 1.1‰) and the radiocarbon age (2000 ± 400 yr) of DOC suggest that the additional DOC (Δ14DOC = −44‰) is supplied from a combination of newly produced DOC and the degradation of particulate as well as sedimentary organic matter. The flux of this additional DOC produced in the continental shelf of the East China Sea to the open ocean is estimated to be ~1.9 ± 0.8 Tg C yr−1, which is comparable to that from the Changjiang discharge. Our study implies that the fluxes of continental shelf-borne DOC may be important globally and should be considered in estimating global DOC budgets in the marine environment.

Mangrove Peat Radiocarbon Ages From Snipe and Swan Key, FL - Khan, Nicole S; Toth, Lauren T; Moyer, Ryan P; Shaw, Jaimie E; Capar, Paulina; Kemp, Andrew C; Engelhart, Simon E; Horton, Benjamin P (U.S. Geological Survey, 2022)
In 2016, researchers collected cores of mangrove peat from two islands in the Florida Keys: Snipe Key (24.679°N, 81.653°W) and Swan Key (25.349N, 80.251W) (Fig. 1). This data release contains the radiocarbon ages and associated data for peat samples analyzed throughout the two cores. These data were used by Khan and others (in preparation) to reconstruct the millennial-scale sea level variability of the two locations.
Medium: csv,xlsx Type: dataset
Keywords: core analysis; push coring; Radiometric Dating

Oceanic passage of hurricanes across Cay Sal Bank in The Bahamas over the last 530 years - Winkler, Tyler S.; van Hengstum, Peter J.; Donnelly, Jeffrey P.; Wallace, Elizabeth J.; D'Entremont, Nicole; Hawkes, Andrea D.; Maio, Christopher V.; Sullivan, Richard M.; Woodruff, Jonathan D. (Marine Geology, 2022)
Islands across the Bahamian Archipelago have been devastated by five major hurricanes from 2010 to 2020 CE, including Category 5 Hurricane Dorian in 2019 that inundated parts of Abaco and Grand Bahama with up to 4 m of surge, killing 84 people and leaving >245 others missing. Up to 1 m relative sea-level rise is estimated for The Bahamas by 2100 CE, which could enhance flooding from weaker storms (<Category 3) in low-lying coastal areas. Problematically, Bahamian hurricane activity is highly spatially-heterogenous over the last 170 years, meaning that long-term regional hurricane frequency remains poorly constrained, especially for weaker Category 1–2 events that are less-likely to be detected by most sediment-based paleo-hurricane reconstructions. We present a 530-year record of hurricane passage from Hine's Blue Hole on Cay Sal Bank, The Bahamas. Hine's Hole has an accumulation rate of 2–3.2 cm/yr, making it among the highest-resolution hurricane reconstructions to date. Unlike many paleo-hurricane reconstruction sites, Hine's Hole is not surrounded by coastal landmasses that can dampen currents and waves produced by hurricanes, so it archives most ≥Category 1 hurricanes passing within 115 km during the 170-year instrumental record (1850 CE-present) and may also document intense tropical or winter storms. Hine's Hole archives ~16 intense storms per century from 1850 to 2016 CE, but documents three periods from 1505 to 1530 CE, 1570 to 1620 CE, and ~ 1710 to 1875 CE with over twice as many intense storms per century. These active periods correspond to other high-resolution reconstructions from the Bahamian Archipelago and Florida Keys, but the magnitude of the increase is much higher given that Hine's Hole archives evidence of weaker and more distal storms. As such, this reconstruction provides unprecedented insight into changes in hurricane activity within the pre-industrial climate system and demonstrates that recurrence intervals based on the 170-year instrumental record can severely underestimate the threat hurricanes pose certain localities.

Over a third of groundwater in USA public-supply aquifers is Anthropocene-age and susceptible to surface contamination - Jurgens, Bryant C.; Faulkner, Kirsten; McMahon, Peter B.; Hunt, Andrew G.; Casile, Gerolamo; Young, Megan B.; Belitz, Kenneth (Communications Earth & Environment, 2022)
The distribution of groundwater age is useful for evaluating the susceptibility and sustainability of groundwater resources. Here, we compute the aquifer-scale cumulative distribution function to characterize the age distribution for 21 Principal Aquifers that account for ~80% of public-supply pumping in the United States. The aquifer-scale cumulative distribution function for each Principal Aquifer was derived from an ensemble of modeled age distributions (~60 samples per aquifer) based on multiple tracers: tritium, tritiogenic helium-3, sulfur hexafluoride, chlorofluorocarbons, carbon-14, and radiogenic helium-4. Nationally, the groundwater is 38% Anthropocene (since 1953), 34% Holocene (75 – 11,800 years ago), and 28% Pleistocene (>11,800 years ago). The Anthropocene fraction ranges from <5 to 100%, indicating a wide range in susceptibility to land-surface contamination. The Pleistocene fraction of groundwater exceeds 50% in 7 eastern aquifers that are predominately confined. The Holocene fraction of groundwater exceeds 50% in 5 western aquifers that are predominately unconfined. The sustainability of pumping from these Principal Aquifers depends on rates of recharge and release of groundwater stored in fine-grained layers.
Keywords: Environmental impact; hydrology; Sustainability

Persistence of old soil carbon under changing climate: The role of mineral-organic matter interactions - Grant, Katherine E.; Galy, Valier V.; Haghipour, Negar; Eglinton, Timothy I.; Derry, Louis A. (Chemical Geology, 2022)
Globally, soils store between 1500 and 2800 Pg of organic carbon (OC). The physical and chemical stability of these terrestrial soil carbon stores under plausible climate change scenarios is unclear. Soil organic carbon (SOC), especially in volcanic soils, is stabilized through mineral matrix interactions. How susceptible are these mineral-organic matter interactions to environmental change? Here we present a study of SOC age along a climate gradient of andisols from Kohala volcano on the Island of Hawai'i. We measure carbon isotope composition (14C/12C, 13C/12C) in bulk samples and extracted biomarkers for 4–8 horizons of 15 soil profiles to understand variability in SOC age and persistence across incremental differences in mean annual precipitation. Bulk OC in the subsoil has radiocarbon fraction modern (Fm) values as low as 0.28 to 0.16 (~10,160 to ~14,630 conventional radiocarbon years). Coexisting plant-derived long chain fatty acids (LCFAs) are older, over 22,500 yrs. (Fm = 0.060), implying that these are among the most stable compounds in the soil, while corresponding shorter-chain (C16) fatty acids are much younger, consistent with an origin from active microbial communities assimilating young OC percolating from surface horizons. There is significant Fe loss at higher mean annual precipitation (MAP) (>2200 mm yr−1) sites associated with episodic soil saturation and microbial Fe reduction. %OC is higher at these sites, consistent with the expectation that saturated conditions promote SOC storage. However, in these higher MAP sites iron depletion is associated with much younger bulk SOC and LCFAs 14C ages (~2900 14C years) than at equivalent sample depths in sites that retain most Fe (~14,200 14C years). The remaining mineral matrix consists primarily of Si, Al, and Ti as SRO minerals. The data imply that modest increases in precipitation resulting from environmental change at locations near a potential saturation or redox threshold could result in destabilization of Fe-SOC complexes, rendering previously stabilized carbon available for rapid degradation, potentially irreversibly decreasing the size of the old SOC reservoir. The destabilization of an old, persistent Fe-SOC reservoir can decrease SOC storage and ultimately increase the amount of CO2 released to the atmosphere.

Queen triggerfish Balistes vetula: Validation of otolith-based age, growth, and longevity estimates via application of bomb radiocarbon - Shervette, Virginia R.; Rivera Hernández, Jesús M. (PLOS ONE, 2022)
Ensuring the accuracy of age estimation in fisheries science through validation is an essential step in managing species for long-term sustainable harvest. The current study used Δ14 C in direct validation of age estimation for queen triggerfish Balistes vetula and conclusively documented that triggerfish sagittal otoliths provide more accurate and precise age estimates relative to dorsal spines. Caribbean fish samples (n = 2045) ranged in size from 67-473 mm fork length (FL); 23 fish from waters of the southeastern U.S. (SEUS) Atlantic coast ranged in size from 355-525 mm FL. Otolith-based age estimates from Caribbean fish range from 0-23 y, dorsal spine-based age estimates ranged from 1-14 y. Otolith-based age estimates for fish from the SEUS ranged from 8-40 y. Growth function estimates from otoliths in the current study (L∞ = 444, K = 0.13, t0 = -1.12) differed from spined-derived estimates in the literature. Our work indicates that previously reported maximum ages for Balistes species based on spine-derived age estimates may underestimate longevity of these species since queen triggerfish otolith-based ageing extended maximum known age for the species by nearly three-fold (14 y from spines versus 40 y from otoliths). Future research seeking to document age and growth population parameters of Balistes species should strongly consider incorporating otolith-based ageing in the research design.

RADIOCARBON IN DISSOLVED CARBON BY UV OXIDATION: AN UPDATE OF PROCEDURES AND BLANK CHARACTERIZATION AT NOSAMSABSTRACT - Xu, Li; Roberts, Mark L; Elder, Kathryn L; Hansman, Roberta L; Gagnon, Alan R; Kurz, Mark D (Radiocarbon, 2022)
This note describes improvements of UV oxidation method that is used to measure carbon isotopes of dissolved organic carbon (DOC) at the National Ocean Sciences Accelerator Mass Spectrometry Facility (NOSAMS). The procedural blank is reduced to 2.6 +/- 0.6 mu g C, with Fm of 0.42 +/- 0.10 and delta C-13 of -28.43 +/- 1.19 parts per thousand. The throughput is improved from one sample per day to two samples per day.

Reconciling the apparent absence of a Last Glacial Maximum alpine glacial advance, Yukon Territory, Canada, through cosmogenic beryllium-10 and carbon-14 measurements - Goehring, Brent M.; Menounos, Brian; Osborn, Gerald; Hawkins, Adam; Ward, Brent (Geochronology, 2022)
We present a new in situ produced cosmogenic beryllium-10 and carbon-14 nuclide chronology from two sets (outer and inner) of alpine glacier moraines from the Grey Hunter massif of southern Yukon Territory, Canada. The chronology of moraines deposited by alpine glaciers outside the limits of the Last Glacial Maximum (LGM) ice sheets potentially provides a less-ambiguous archive of mass balance, and hence climate, than can be inferred from the extents of ice sheets themselves. Results for both nuclides are inconclusive for the outer moraines, with evidence for pre-LGM deposition (beryllium-10) and Holocene deposition (carbon-14). Beryllium-10 results from the inner moraine are suggestive of canonical LGM deposition but with relatively high scatter. Conversely, in situ carbon-14 results from the inner moraines are tightly clustered and suggestive of terminal Younger Dryas deposition. We explore plausible scenarios leading to the observed differences between nuclides and find that the most parsimonious explanation for the outer moraines is that of pre-LGM deposition, but many of the sampled boulder surfaces were not exhumed from within the moraine until the Holocene. Our results thus imply that the inner and outer moraines sampled pre- and post-date the canonical LGM and that moraines dating to the LGM are lacking likely due to overriding by the subsequent Late Glacial/earliest Holocene advance.

Relative sea-level change in South Florida during the past ~5000 years - Khan, Nicole S.; Ashe, Erica; Moyer, Ryan P.; Kemp, Andrew C.; Engelhart, Simon E.; Brain, Matthew J.; Toth, Lauren T.; Chappel, Amanda; Christie, Margaret; Kopp, Robert E.; Horton, Benjamin P. (Global and Planetary Change, 2022)
A paucity of detailed relative sea-level (RSL) reconstructions from low latitudes hinders efforts to understand the global, regional, and local processes that cause RSL change. We reconstruct RSL change during the past ~5 ka using cores of mangrove peat at two sites (Snipe Key and Swan Key) in the Florida Keys. Remote sensing and field surveys established the relationship between peat-forming mangroves and tidal elevation in South Florida. Core chronologies are developed from age-depth models applied to 72 radiocarbon dates (39 mangrove wood macrofossils and 33 fine-fraction bulk peat). RSL rose 3.7 m at Snipe Key and 5.0 m at Swan Key in the past 5 ka, with both sites recording the fastest century-scale rate of RSL rise since ~1900 CE (~2.1 mm/a). We demonstrate that it is feasible to produce near-continuous reconstructions of RSL from mangrove peat in regions with a microtidal regime and accommodation space created by millennial-scale RSL rise. Decomposition of RSL trends from a network of reconstructions across South Florida using a spatio-temporal model suggests that Snipe Key was representative of regional RSL trends, but Swan Key was influenced by an additional local-scale process acting over at least the past five millennia. Geotechnical analysis of modern and buried mangrove peat indicates that sediment compaction is not the local-scale process responsible for the exaggerated RSL rise at Swan Key. The substantial difference in RSL between two nearby sites highlights the critical need for within-region replication of RSL reconstructions to avoid misattribution of sea-level trends, which could also have implications for geophysical modeling studies using RSL data for model tuning and validation.
Keywords: Holocene; mangrove; Proxy reconstruction; Reproducibility; sea level

Relative sea-level data preclude major late Holocene ice-mass change in Pine Island Bay - Braddock, Scott; Hall, Brenda L.; Johnson, Joanne S.; Balco, Greg; Spoth, Meghan; Whitehouse, Pippa L.; Campbell, Seth; Goehring, Brent M.; Rood, Dylan H.; Woodward, John (Nature Geoscience, 2022)
The rapidly retreating Thwaites and Pine Island glaciers together dominate present-day ice loss from the West Antarctic Ice Sheet and are implicated in runaway deglaciation scenarios. Knowledge of whether these glaciers were substantially smaller in the mid-Holocene and subsequently recovered to their present extents is important for assessing whether current ice recession is irreversible. Here we reconstruct relative sea-level change from radiocarbon-dated raised beaches at sites immediately seawards of these glaciers, allowing us to examine the response of the earth to loading and unloading of ice in the Amundsen Sea region. We find that relative sea level fell steadily over the past 5.5 kyr without rate changes that would characterize large-scale ice re-expansion. Moreover, current bedrock uplift rates are an order of magnitude greater than the rate of long-term relative sea-level fall, suggesting a change in regional crustal unloading and implying that the present deglaciation may be unprecedented in the past 5.5 kyr. While we cannot preclude minor grounding-line fluctuations, our data are explained most easily by early Holocene deglaciation followed by relatively stable ice positions until recent times and imply that Thwaites and Pine Island glaciers have not been substantially smaller than present during the past 5.5 kyr.

Review article: Existing and potential evidence for Holocene grounding line retreat and readvance in Antarctica - Johnson, Joanne S.; Venturelli, Ryan A.; Balco, Greg; Allen, Claire S.; Braddock, Scott; Campbell, Seth; Goehring, Brent M.; Hall, Brenda L.; Neff, Peter D.; Nichols, Keir A.; Rood, Dylan H.; Thomas, Elizabeth R.; et al. (The Cryosphere, 2022)
Widespread existing geological records from above the modern ice sheet surface and outboard of the current ice margin show that the Antarctic Ice Sheet (AIS) was much more extensive at the Last Glacial Maximum (∼20 ka) than at present. However, whether it was ever smaller than present during the last few millennia, and (if so) by how much, is known only for a few locations because direct evidence lies within or beneath the ice sheet, which is challenging to access. Here, we describe how retreat and readvance (henceforth “readvance”) of AIS grounding lines during the Holocene could be detected and quantified using subglacial bedrock, subglacial sediments, marine sediment cores, relative sea-level (RSL) records, geodetic observations, radar data, and ice cores. Of these, only subglacial bedrock and subglacial sediments can provide direct evidence for readvance. Marine archives are of limited utility because readvance commonly covers evidence of earlier retreat. Nevertheless, stratigraphic transitions documenting change in environment may provide support for direct evidence from subglacial records, as can the presence of transgressions in RSL records, and isostatic subsidence. With independent age control, ice structure revealed by radar can be used to infer past changes in ice flow and geometry, and therefore potential readvance. Since ice cores capture changes in surface mass balance, elevation, and atmospheric and oceanic circulation that are known to drive grounding line migration, they also have potential for identifying readvance. A multidisciplinary approach is likely to provide the strongest evidence for or against a smaller-than-present AIS in the Holocene.
Publisher: Copernicus GmbH

Sources and Behavior of Particulate Organic Carbon in the Yellow Sea and the East China Sea Based on 13C, 14C, and 234Th - Seo, Junhyeong; Kim, Guebuem; Hwang, Jeomshik (Frontiers in Marine Science, 2022)
The cycling of particulate organic carbon (POC) in continental shelf regions of the Yellow Sea (YS) and the East China Sea (ECS) was investigated by analyzing the concentrations and carbon isotope signatures (δ13C, Δ14C) of POC, together with the particulate aluminum (Al) concentration and 234Th activity over the period 10–20 August 2020. POC concentrations in the surface layer (0–20 m) were twice as high as those in the middle layer (20–50 m); the highest concentrations of all were observed in the bottom layer (> 50 m) of the YS and the region affected by Changjiang Diluted Water (CDW). Particulate Al concentrations in the bottom layer were three times higher than those in the overlying water column, indicating extensive sediment resuspension. Based on the three-endmember mixing model for the dual carbon isotopes, the estimated contribution of resuspended sedimentary organic carbon to POC ranged from 18% in the surface layer to 65% in the bottom layer. The contribution of riverine input to POC ranged from < 5% in the CDW region to ∼45% in the surface layer of the YS region, whereas that of in situ production was ∼40% in the entire study region. A deficiency of 234Th relative to 238U indicates short residence times of particles in the entire water column (2.6 ± 2.2 d). The flux of POC settling to the seafloor, calculated based on 234Th–238U disequilibrium, was 47–125 mmol m–2 d–1. The POC settling flux was one to two orders of magnitude higher than the burial rate of POC in the underlying sediment, implying the rapid decomposition of POC before incorporation into the sediment. Thus, sediment resuspension is prevalent and an important component of the POC cycling in this shelf region. Overall, our study revealed the complex nature of POC cycling on this shelf, quantified the relative importance of each source of POC, and determined POC flux to the sediment.

Characteristics of sediment resuspension on a deep abyssal plain in the Eastern Tropical Pacific Ocean - Kim, Minkyoung; Kim, Hyung Jeek; Ko, Ara; Yoo, Chan Min; Ju, Se-Jong; Hwang, Jeomshik (Journal of Sea Research, 2021)

Climate control on terrestrial biospheric carbon turnover - Eglinton, Timothy I.; Galy, Valier V.; Hemingway, Jordon D.; Feng, Xiaojuan; Bao, Hongyan; Blattmann, Thomas M.; Dickens, Angela F.; Gies, Hannah; Giosan, Liviu; Haghipour, Negar; Hou, Pengfei; Lupker, Maarten; et al. (Proceedings of the National Academy of Sciences, 2021)
Terrestrial vegetation and soils hold three times more carbon than the atmosphere. Much debate concerns how anthropogenic activity will perturb these surface reservoirs, potentially exacerbating ongoing changes to the climate system. Uncertainties specifically persist in extrapolating point-source observations to ecosystem-scale budgets and fluxes, which require consideration of vertical and lateral processes on multiple temporal and spatial scales. To explore controls on organic carbon (OC) turnover at the river basin scale, we present radiocarbon (C-14) ages on two groups of molecular tracers of plant-derived carbon-leaf-wax lipids and lignin phenols-from a globally distributed suite of rivers. We find significant negative relationships between the C-14 age of these biomarkers and mean annual temperature and precipitation. Moreover, riverine biospheric-carbon ages scale proportionally with basin-wide soil carbon turnover times and soil C-14 ages, implicating OC cycling within soils as a primary control on exported biomarker ages and revealing a broad distribution of soil OC reactivities. The ubiquitous occurrence of a long-lived soil OC pool suggests soil OC is globally vulnerable to perturbations by future temperature and precipitation increase. Scaling of riverine biospheric-carbon ages with soil OC turnover shows the former can constrain the sensitivity of carbon dynamics to environmental controls on broad spatial scales. Extracting this information from fluvially dominated sedimentary sequences may inform past variations in soil OC turnover in response to anthropogenic and/or climate perturbations. In turn, monitoring riverine OC composition may help detect future climate-change-induced perturbations of soil OC turnover and stocks.
Keywords: Carbon cycle; carbon turnover times; fluvial carbon; plant biomarkers; radiocarbon

Event-dominated transport, provenance, and burial of organic carbon in the Japan Trench - Schwestermann, T.; Eglinton, T.I.; Haghipour, N.; McNichol, A.P.; Ikehara, K.; Strasser, M. (Earth and Planetary Science Letters, 2021)
The delivery of organic carbon (OC) to the ocean's deepest trenches in the hadal zone is poorly understood, but may be important for the carbon cycle, contain crucial information on sediment provenance and event-related transport processes, and provide age constraints on stratigraphic sequences in this terminal sink. In this study, we systematically characterize bulk organic matter (OM) and OC signatures (TOC/TN, delta C-13, C-14), as well as those from application of serial thermal oxidation (ramped pyrolysis/oxidation) of sediment cores recovered along an entire hadal trench encompassing high stratigraphic resolution records spanning nearly 2000 years of deposition. We analyze two cores from the southern and northern Japan Trench, where submarine canyon systems link shelf with trench. We compare results with previously published data from the central Japan Trench, where canyon systems are absent. Our analyses enable refined dating of the stratigraphic record and indicate that event deposits arise from remobilization of relatively surficial sediment coupled with deeper erosion along turbidity current pathways in the southern and central study site and from canyon flushing events in the northern study site. Furthermore, our findings indicate deposition of predominantly marine OC within hemipelagic background sediment as well as associated with event deposits along the entire trench axis. This implies that canyon systems flanking the Japan Trench do not serve as a short-circuit for injection of terrestrial OC to the hadal zone, and that tropical cyclones are not major agents for sediment and carbon transfer into this trench system. These findings further support previous Japan Trench studies interpreting that event deposits originate from the landward trench slope and are earthquake-triggered. The very low terrestrial OC input into the Japan Trench can be explained by the significant distance between trench and hinterland (>180 km), and the physiography of the canyons that do not connect to coast and river systems. We suggest that detailed analyzes of long sedimentary records are essential to understand OC transfer, deposition and burial in hadal trenches. (C) 2021 The Author(s). Published by Elsevier B.V.
Keywords: carbon isotopes; carbon provenance; carbon transfer; hadal zone event-stratigraphy; Japan Trench; ramped Pyr/Ox

Evidence of humans in North America during the Last Glacial Maximum - Bennett, Matthew R.; Bustos, David; Pigati, Jeffrey S.; Springer, Kathleen B.; Urban, Thomas M.; Holliday, Vance T.; Reynolds, Sally C.; Budka, Marcin; Honke, Jeffrey S.; Hudson, Adam M.; Fenerty, Brendan; Connelly, Clare; et al. (Science, 2021)
Archaeologists and researchers in allied fields have long sought to understand human colonization of North America. Questions remain about when and how people migrated, where they originated, and how their arrival affected the established fauna and landscape. Here, we present evidence from excavated surfaces in White Sands National Park (New Mexico, United States), where multiple in situ human footprints are stratigraphically constrained and bracketed by seed layers that yield calibrated radiocarbon ages between ~23 and 21 thousand years ago. These findings confirm the presence of humans in North America during the Last Glacial Maximum, adding evidence to the antiquity of human colonization of the Americas and providing a temporal range extension for the coexistence of early inhabitants and Pleistocene megafauna.
Publisher: American Association for the Advancement of Science

Geomorphic expression and slip rate of the Fairweather fault, southeast Alaska, and evidence for predecessors of the 1958 rupture - Witter, Robert C.; Bender, Adrian M.; Scharer, Katherine M.; DuRoss, Christopher B.; Haeussler, Peter J.; Lease, Richard O. (Geosphere, 2021)
Active traces of the southern Fairweather fault were revealed by light detection and ranging (lidar) and show evidence for transpressional deformation between North America and the Yakutat block in southeast Alaska. We map the Holocene geomorphic expression of tectonic deformation along the southern 30 km of the Fairweather fault, which ruptured in the 1958 moment magnitude 7.8 earthquake. Digital maps of surficial geology, geomorphology, and active faults illustrate both strike-slip and dip-slip deformation styles within a 10°–30° double restraining bend where the southern Fairweather fault steps offshore to the Queen Charlotte fault. We measure offset landforms along the fault and calibrate legacy 14C data to reassess the rate of Holocene strike-slip motion (≥49 mm/yr), which corroborates published estimates that place most of the plate boundary motion on the Fairweather fault. Our slip-rate estimates allow a component of oblique-reverse motion to be accommodated by contractional structures west of the Fairweather fault consistent with geodetic block models. Stratigraphic and structural relations in hand-dug excavations across two active fault strands provide an incomplete paleoseismic record including evidence for up to six surface ruptures in the past 5600 years, and at least two to four events in the past 810 years. The incomplete record suggests an earthquake recurrence interval of ≥270 years—much longer than intervals <100 years implied by published slip rates and expected earthquake displacements. Our paleoseismic observations and map of active traces of the southern Fairweather fault illustrate the complexity of transpressional deformation and seismic potential along one of Earth's fastest strike-slip plate boundaries.

Inverted channel variations identified on a distal portion of a bajada in the central Atacama Desert, Chile - Williams, Rebecca M.E.; Irwin, Rossman P.; Noe Dobrea, Eldar Z.; Howard, Alan D.; Dietrich, William E.; Cawley, J.C. (Geomorphology, 2021)
In deserts, the interplay between occasional fluvial events and persistent aeolian erosion can form composite modern and relict surfaces, especially on the distal portion of alluvial fans. There, relief inversion of alluvial deposits by differential erosion can form longitudinal ridges. We identified two distinct ridge types formed by relief inversion on converging alluvial fans in the hyperarid Chilean Atacama Desert. Although they are co-located and similar in scale, the ridge types have different ages and formation histories that apparently correspond to minor paleoclimate variations. Gravel-armored ridges are remnants of deflated alluvial deposits with a bimodal sediment distribution (gravel and sand) dated to a minor pluvial phase at the end of the Late Pleistocene (similar to 12 kyr). In contrast, younger (similar to 9 kyr) sulfate-capped ridges formed during a minor arid phase with evaporite deposition in a pre-existing channel that armored the underlying deposits. Collectively, inverted channels at Salar de Llamara resulted from multiple episodes of surface overland flow and standing water spanning several thousand years. Based on ridge relief and age, the minimum long-term deflation rate is 0.1-0.2 m/kyr, driven primarily by wind erosion. This case study is an example of the equifinality concept whereby different processes lead to similar landforms. The complex history of the two ridge types can only be generally constrained in remotely sensed data. In situ observations are required to discern the specifics of the aqueous history, including the flow type, magnitude, sequence, and paleoenvironment. These findings have relevance for interpreting similar landforms on Mars.

Lacustrine leaf wax hydrogen isotopes indicate strong regional climate feedbacks in Beringia since the last ice age - Daniels, W.C.; Russell, J.M.; Morrill, C.; Longo, W.M.; Giblin, A.E.; Holland-Stergar, P.; Welker, J.M.; Wen, X.; Hu, A.; Huang, Y. (Quaternary Science Reviews, 2021)

Long-term cultural eutrophication in White and Walden Ponds (Concord, Massachusetts, USA), Thoreau's lakes of light - Stager, J. Curt; Harvey, Lydia; Chimileski, Scott (Lake and Reservoir Management, 2021)
Two historically important ponds in the vicinity of Boston, MA, were subjected to a comparative paleolimnological investigation of the timing and causes of eutrophication trends in each. The remarkable clarity of White Pond during the early 19th century led Henry David Thoreau to compare it favorably to nearby Walden Pond, but during the 20th century water quality in both ponds declined. Sediment core studies show that cultural eutrophication began at Walden during the 1930s, but no long-term sediment records have been available for White Pond, which makes it more difficult to determine the history and causes of eutrophication there. Here we use microfossil and geochemical analyses of sediment cores to show that major changes in the diatom community of White Pond began around 1900, when fish stocking commenced and soil erosion due to land use in the watershed increased, and that the trend intensified around 1960 and 1990. We also describe efforts to mitigate eutrophication at White Pond, highlight the ecological importance of benthic vegetation in nutrient cycling, and suggest that threats to water quality in both of these ponds will likely increase due to anticipated climatic changes in the region.
Keywords: diatoms; eutrophication; paleolimnology; reclamation; Thoreau; Walden

A maximum rupture model for the central and southern Cascadia subduction zone—reassessing ages for coastal evidence of megathrust earthquakes and tsunamis - Nelson, Alan R.; DuRoss, Christopher B.; Witter, Robert C.; Kelsey, Harvey M.; Engelhart, Simon E.; Mahan, Shannon A.; Gray, Harrison J.; Hawkes, Andrea D.; Horton, Benjamin P.; Padgett, Jason S. (Quaternary Science Reviews, 2021)
A new history of great earthquakes (and their tsunamis) for the central and southern Cascadia subduction zone shows more frequent (17 in the past 6700 yr) megathrust ruptures than previous coastal chronologies. The history is based on along-strike correlations of Bayesian age models derived from evaluation of 554 radiocarbon ages that date earthquake evidence at 14 coastal sites. We reconstruct a history that accounts for all dated stratigraphic evidence with the fewest possible ruptures by evaluating the sequence of age models for earthquake or tsunami contacts at each site, comparing the degree of temporal overlap of correlated site age models, considering evidence for closely spaced earthquakes at four sites, and hypothesizing only maximum-length megathrust ruptures. For the past 6700 yr, recurrence for all earthquakes is 370e420 yr. But correlations suggest that ruptures at-1.5 ka and-1.1 ka were of limited extent (<400 km). If so, post-3-ka recurrence for ruptures extending throughout central and southern Cascadia is 510e540 yr. But the range in the times between earthquakes is large: two instances may be-50 yr, whereas the longest are-550 and-850 yr. The closely spaced ruptures about 1.6 ka may illustrate a pattern common at subduction zones of a long gap ending with a great earthquake rupturing much of the subduction zone, shortly followed by a rupture of more limited extent. The ruptures of limited extent support the continued inclusion of magnitude-8 earthquakes, with longer ruptures near magnitude 9, in assessments of seismic hazard in the region.

Molluscan aminostratigraphy of the US Mid-Atlantic Quaternary coastal system: Implications for onshore-offshore correlation, paleochannel and barrier island evolution, and local late Quaternary sea-level history - Wehmiller, John F.; Brothers, Laura L.; Ramsey, Kelvin W.; Foster, David S.; Mattheus, C.R.; Hein, Christopher J.; Shawler, Justin L. (Quaternary Geochronology, 2021)
The Quaternary record of the US Mid-Atlantic coastal system includes onshore emergent late Pleistocene shoreline deposits, offshore inner shelf and barrier island units, and paleovalleys formed during multiple glacial stage sea-level lowstands. The geochronology of this coastal system is based on uranium series, radiocarbon, amino acid racemization (AAR), and optically stimulated luminescence (OSL) methods. We report over 600 mollusk AAR results from 93 sites between northeastern North Carolina and the central New Jersey shelf, representing samples from both onshore cores or outcrops, sub-barrier and offshore cores, and transported shells from barrier island beaches. AAR age estimates are constrained by paired C-14 analyses on specific shells and associated U-series coral ages from onshore sites. AAR data from offshore cores are interpreted in the context of detailed seismic stratigraphy. The distribution of Pleistocene-age shells on the island beaches is linked to the distribution of inner shelf or sub-barrier source units. Age mixing over a range of time-scales (similar to 1 ka to similar to 100 ka) is identified by AAR results from onshore, beach, and shelf collections, often contributing insights into the processes forming individual barrier islands. The regional aminostratigraphic framework identifies a widespread late Pleistocene (Marine Isotope Stage 5) aminozone, with isolated records of middle and early Pleistocene deposition. AAR results provide age estimates for the timing of formation of the three major paleochannels that underlie the Delmarva Peninsula: Persimmon Point paleochannel >= 800 ka; Exmore paleochannel similar to 400-500 ka (MIS 12); and Eastville paleochannel > 125 ka (MIS 6). The results demonstrate the value of synthesizing abundant AAR chronologic data across various coastal environments, integrating multiple distinct geologic studies. The ages and elevations of the Quaternary units are important for current hypotheses about relative sea level history and crustal dynamics in the region, which was likely influenced by the Laurentide ice sheet, the margin just similar to 400 km to the north.

Plastic Formulation is an Emerging Control of Its Photochemical Fate in the Ocean - Walsh, Anna N.; Reddy, Christopher M.; Niles, Sydney F.; McKenna, Amy M.; Hansel, Colleen M.; Ward, Collin P. (Environmental Science & Technology, 2021)
Sunlight exposure is a control of long-term plastic fate in the environment that converts plastic into oxygenated products spanning the polymer, dissolved, and gas phases. However, our understanding of how plastic formulation influences the amount and composition of these photoproducts remains incomplete. Here, we characterized the initial formulations and resulting dissolved photoproducts of four single-use consumer polyethylene (PE) bags from major retailers and one pure PE film. Consumer PE bags contained 15–36% inorganic additives, primarily calcium carbonate (13–34%) and titanium dioxide (TiO2; 1–2%). Sunlight exposure consistently increased production of dissolved organic carbon (DOC) relative to leaching in the dark (3- to 80-fold). All consumer PE bags produced more DOC during sunlight exposure than the pure PE (1.2- to 2.0-fold). The DOC leached after sunlight exposure increasingly reflected the 13C and 14C isotopic composition of the plastic. Ultrahigh resolution Fourier transform ion cyclotron resonance mass spectrometry revealed that sunlight exposure substantially increased the number of DOC formulas detected (1.1- to 50-fold). TiO2-containing bags photochemically degraded into the most compositionally similar DOC, with 68–94% of photoproduced formulas in common with at least one other TiO2-containing bag. Conversely, only 28% of photoproduced formulas from the pure PE were detected in photoproduced DOC from the consumer PE. Overall, these findings suggest that plastic formulation, especially TiO2, plays a determining role in the amount and composition of DOC generated by sunlight. Consequently, studies on pure, unweathered polymers may not accurately represent the fates and impacts of the plastics entering the ocean.

RADIOCARBON IN DISSOLVED ORGANIC CARBON BY UV OXIDATION: PROCEDURES AND BLANK CHARACTERIZATION AT NOSAMSABSTRACT - Xu, Li; Roberts, Mark L; Elder, Kathryn L; Kurz, Mark D; McNichol, Ann P; Reddy, Christopher M; Ward, Collin P; Hanke, Ulrich M (Radiocarbon, 2021)
This study describes a procedural blank assessment of the ultraviolet photochemical oxidation (UV oxidation) method that is used to measure carbon isotopes of dissolved organic carbon (DOC) at the National Ocean Sciences Accelerator Mass Spectrometry Facility (NOSAMS). A retrospective compilation of Fm and δ 13 C results for secondary standards (OX-II, glycine) between 2009 and 2018 indicated that a revised blank correction was required to bring results in line with accepted values. The application of a best-fit mass-balance correction yielded a procedural blank of 22.0 ± 6.0 μg C with Fm of 0.30 ± 0.20 and δ 13 C of-32.0 ± 3.0‰ for this period, which was notably higher and more variable than previously reported. Changes to the procedure, specifically elimination of higher organic carbon reagents and improved sample and reactor handling, reduced the blank to 11.0 ± 2.75 μg C, with Fm of 0.14 ± 0.10 and δ 13 C of-31.0 ± 5.5‰. A thorough determination of the entire sample processing blank is required to ensure accurate isotopic compositions of seawater DOC using the UV oxidation method. Additional efforts are needed to further reduce the procedural blank so that smaller DOC samples can be analyzed, and to increase sample throughput.
Keywords: blank; dissolved organic carbon; radiocarbon; UV oxidation

Aquifer-Scale Observations of Iron Redox Transformations in Arsenic-Impacted Environments to Predict Future Contamination - Nghiem, Athena A.; Shen, Yating; Stahl, Mason; Sun, Jing; Haque, Ezazul; DeYoung, Beck; Nguyen, Khue N.; Thi Mai, Tran; Trang, Pham Thi Kim; Pham, Hung Viet; Mailloux, Brian; Harvey, Charles F.; et al. (Environmental Science & Technology Letters, 2020)
Iron oxides control the mobility of a host of contaminants in aquifer systems, and the microbial reduction of iron oxides in the subsurface is linked to high levels of arsenic in groundwater that affects greater than 150 million people globally. Paired observations of groundwater and solid-phase aquifer composition are critical to understand spatial and temporal trends in contamination and effectively manage changing water resources, yet field-representative mineralogical data are sparse across redox gradients relevant to arsenic contamination. We characterize iron mineralogy using X-ray absorption spectroscopy across a natural gradient of groundwater arsenic contamination in Vietnam. Hierarchical cluster analysis classifies sediments into meaningful groups delineating weathering and redox changes, diagnostic of depositional history, in this first direct characterization of redox transformations in the field. Notably, these groupings reveal a signature of iron minerals undergoing active reduction before the onset of arsenic contamination in groundwater. Pleistocene sediments undergoing postdepositional reduction may be more extensive than previously recognized due to previous misclassification. By upscaling to similar environments in South and Southeast Asia via multinomial logistic regression modeling, we show that active iron reduction, and therefore susceptibility to future arsenic contamination, is more widely distributed in presumably pristine aquifers than anticipated.
Keywords: BANGLADESH; BENGAL BASIN; groundwater; PLEISTOCENE AQUIFER; POLLUTION; RELEASE; RIVER DELTA; Sediment; TRANSPORT; VIETNAM

Deep Equatorial Pacific Ocean Oxygenation and Atmospheric CO2 Over The Last Ice Age - Marcantonio, Franco; Hostak, Ryan; Hertzberg, Jennifer E.; Schmidt, Matthew W. (Scientific Reports, 2020)
Ventilation of carbon stored in the deep ocean is thought to play an important role in atmospheric CO2 increases associated with Pleistocene deglaciations. The presence of this respired carbon has been recorded by an array of paleoceanographic proxies from various locations across the global ocean. Here we present a new sediment core from the Eastern Equatorial Pacific (EEP) Ocean spanning the last 180,000 years and reconstruct high-resolution 230Th-derived fluxes of 232Th and excess barium, along with redox-sensitive uranium concentrations to examine past variations in dust delivery, export productivity, and bottom-water oxygenation, respectively. Our bottom-water oxygenation record is compared to other similar high-resolution records from across the Pacific and in the Southern Ocean. We suggest that the deep Pacific is a site of respired carbon storage associated with periods of decreased global atmospheric CO2 concentration during the LGM, confirming the conclusions from a wealth of previous studies. However, our study is the first to show a similar relationship beyond the last glacial, extending to at least 70,000 years

Delayed maximum and recession of an East Antarctic outlet glacierAbstract - King, Courtney; Hall, Brenda; Hillebrand, Trevor; Stone, John (Geology, 2020)
During the last glaciation, East Antarctic outlet glaciers contributed to a grounded ice sheet in the Ross Embayment. The timing of maximum ice extent, as well as of subsequent deglaciation of these outlets, has implications for the behavior of the Antarctic Ice Sheet (AIS) and its impact on global sea level. We present 45 radiocarbon ages of lacustrine cyanobacteria from the Lake Wellman region alongside Hatherton Glacier, which are the first terrestrial data to both record advance of an Antarctic glacier to its maximum position as well as document a high-resolution chronology of subsequent retreat. Seventeen new exposure ages are widely scattered, but the youngest four are in broad agreement with the radiocarbon data. Hatherton Glacier slowly thickened from 13,000 to 9500 yr B.P. and then thinned steadily until at least ca. 2800 yr B.P. Our work affords evidence of both a delayed maximum and recession of an East Antarctic outlet glacier compared to the global Last Glacial Maximum (LGM) and supports growing evidence of a time-transgressive local LGM within the Ross Sea sector of the ice sheet. Both observations are consistent with the idea that the timing of outlet glacier expansion and timing of recession are controlled by the balance between dynamic thinning from ocean forcing and increased accumulation due to atmospheric warming.

Effects of agricultural and tillage practices on isotopic signatures and fluxes of organic and inorganic carbon in headwater streams - Kelsey, Scott A.; Grottoli, Andrea G.; Bauer, James E.; Lorenz, Klaus; Lal, Rattan; Matsui, Yohei; Huey-Sanders, Teresa M. (Aquatic Sciences, 2020)

Efficient preservation of young terrestrial organic carbon in sandy turbidity-current depositsAbstract - Hage, S.; Galy, V.V.; Cartigny, M.J.B.; Acikalin, S.; Clare, M.A.; Gröcke, D.R.; Hilton, R.G.; Hunt, J.E.; Lintern, D.G.; McGhee, C.A.; Parsons, D.R.; Stacey, C.D.; et al. (Geology, 2020)
Burial of terrestrial biospheric particulate organic carbon in marine sediments removes CO2 from the atmosphere, regulating climate over geologic time scales. Rivers deliver terrestrial organic carbon to the sea, while turbidity currents transport river sediment further offshore. Previous studies have suggested that most organic carbon resides in muddy marine sediment. However, turbidity currents can carry a significant component of coarser sediment, which is commonly assumed to be organic carbon poor. Here, using data from a Canadian fjord, we show that young woody debris can be rapidly buried in sandy layers of turbidity current deposits (turbidites). These layers have organic carbon contents 10× higher than the overlying mud layer, and overall, woody debris makes up >70% of the organic carbon preserved in the deposits. Burial of woody debris in sands overlain by mud caps reduces their exposure to oxygen, increasing organic carbon burial efficiency. Sandy turbidity current channels are common in fjords and the deep sea; hence we suggest that previous global organic carbon burial budgets may have been underestimated.

Identifying the Greatest Earthquakes of the Past 2000 Years at the Nehalem River Estuary, Northern Oregon Coast, USA - Nelson, Alan R.; Hawkes, Andrea D.; Sawai, Yuki; Engelhart, Simon E.; Witter, Rob; Grant-Walter, Wendy C.; Bradley, Lee-Ann; Dura, Tina; Cahill, Niamh; Horton, Ben (Open Quaternary, 2020)
We infer a history of three great megathrust earthquakes during the past 2000 years at the Nehalem River estuary based on the lateral extent of sharp (≤3 mm) peat-mud stratigraphic contacts in cores and outcrops, coseismic subsidence as interpreted from fossil diatom assemblages and reconstructed with foraminiferal assemblages using a Bayesian transfer function, and regional correlation of 14C-modeled ages for the times of subsidence. A subsidence contact from 1700 CE (contact A), sometimes overlain by tsunami-deposited sand, can be traced over distances of 7 km. Contacts B and D, which record subsidence during two earlier megathrust earthquakes, are much less extensive but are traced across a 700-m by 270-m tidal marsh. Although some other Cascadia studies report evidence for an earthquake between contacts B and D, our lack of extensive evidence for such an earthquake may result from the complexities of preserving identifiable evidence of it in the rapidly shifting shoreline environments of the lower river and bay. Ages (95% intervals) and subsidence for contacts are: A, 1700 CE (1.1 ± 0.5 m); B, 942–764 cal a BP (0.7 ± 0.4 m and 1.0 m ± 0.4 m); and D, 1568–1361 cal a BP (1.0 m ± 0.4 m). Comparisons of contact subsidence and the degree of overlap of their modeled ages with ages for other Cascadia sites are consistent with megathrust ruptures many hundreds of kilometers long. But these data cannot conclusively distinguish among different types or lengths of ruptures recorded by the three great earthquake contacts at the Nehalem River estuary.
Keywords: Bayesian transfer function; Cascadia subduction zone; Coseismic subsidence; earthquake hazards; Paleoseismology; salt-marsh stratigraphy; Sea-level changes; tidal foraminifera and diatoms

Insolation and greenhouse gases drove Holocene winter and spring warming in Arctic Alaska - Longo, William M.; Huang, Yongsong; Russell, James M.; Morrill, Carrie; Daniels, William C.; Giblin, Anne E.; Crowther, Josue (Quaternary Science Reviews, 2020)
Global surface temperature changes and their drivers during the Holocene Epoch remain controversial. Syntheses of proxy data indicate that global mean annual temperature declined from the mid-Holocene until the Pre-industrial Era, a trend linked to decreasing Northern Hemisphere summer insolation. In contrast, global climate models simulate increasing mean annual temperatures driven by retreating ice sheets and increasing greenhouse gas concentrations. This proxy-model disagreement may originate from a warm season bias in Northern Hemisphere proxy reconstructions, highlighting the need for new proxies that quantify cold season temperature, especially in Arctic regions that were devoid of continental ice sheets during the Holocene. Here, we present a new 16,000-year winter-spring temperature reconstruction derived from the unsaturation ratio of alkenones (U-3(7)K) in a continuous sedimentary sequence from Lake E5, northern Alaska. We employ a thermodynamic lake model to convert alkenone-inferred lake temperatures into winter-spring air temperature anomalies and we contextualize our proxy reconstruction with climate model output from the region. Our reconstruction shows that winter-spring temperatures warmed rapidly during the deglaciation at 16 and 14 thousand years before present and continued to warm gradually throughout the middle and late Holocene (0.12-0.28 degrees C/thousand years) in concert with regional sea surface temperature and sea ice records. Our results are consistent with climate model simulations and we attribute Holocene warming to rising winter-spring insolation, radiative forcing from rising greenhouse gas concentrations and regional feedbacks. Our reconstructed cold season warming equaled or exceeded summer cooling according to a regional synthesis of temperature records, suggesting that seasonal biases in temperature reconstructions may account for proxy-model disagreements in Holocene temperature trends from Eastern Beringia. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Alkenone; Beringia; Continental biomarkers; Holocene; North America; paleoclimatology; paleolimnology; Proxy data-model comparison; seasonality; Temperature reconstruction

Neotectonic and Paleoseismic Analysis of the Northwest Extent of Holocene Surface Deformation along the Meers Fault, OklahomaABSTRACT - Hornsby, Kristofer T.; Streig, Ashley R.; Bennett, Scott E. K.; Chang, Jefferson C.; Mahan, Shannon (Bulletin of the Seismological Society of America, 2020)
The Meers fault (Oklahoma) is one of few seismogenic structures with evidence for Holocene surface rupture in the stable continental region of North America. The 37-kilometer-long southeast section of the full 54-kilometer-long Meers fault is interpreted to be Holocene active. The 17-kilometer-long northwest section is considered Quaternary active, but not Holocene active.We reevaluate surface expression and earthquake timing of the northwest Meers fault to improve seismic source characterization.We use airborne light detection and ranging and historical stereo paired aerial photos to evaluate the fault scarp and local fault zone geomorphology. In the northwest, complex surface deformation includes fault splays, subtle monoclinal warping, and a minor change in fault strike. We interpret that the along strike transition from surface faulting on the southeast Meers fault to surface folding on the northwest Meers fault occurs at the lithologic contact between Permian Post Oak conglomerate and Hennessey shale. We excavated a paleoseismic trench to evaluate the timing of surface-deforming earthquakes on the northwest section of the fault. The excavation revealed weathered Permian Hennessey shale and an ∼1–2-meter-thick veneer of Holocene alluvial deposits that were progressively deformed during two surface-folding earthquakes likely related to blind fault rupture beneath the site. Repeated onlapping to overlapping stratigraphic sequences and associated unconformities are intimately related to folding events along the monocline. OxCal paleoearthquake age modeling indicates that earthquakes occurred 4704–3109 yr B.P. and 5955–4744 yr B.P., and that part of the northwest section of the Meers fault is Holocene active. We find the Holocene-active section of the Meers fault should be lengthened 6.1 km to the northwest, to a total Holocene-active fault length of 43 km. Empirical scaling relationships between surface rupture length and magnitude reveal that the fault could generate an Mw 7.0 earthquake.

Removal of Refractory Dissolved Organic Carbon in the Amundsen Sea, Antarctica - Fang, Ling; Lee, SangHoon; Lee, Shin-Ah; Hahm, Doshik; Kim, Guebuem; Druffel, Ellen R. M.; Hwang, Jeomshik (Scientific Reports, 2020)
The removal mechanism of refractory deep-ocean dissolved organic carbon (deep-DOC) is poorly understood. The Amundsen Sea Polynya (ASP) serves as a natural test basin for assessing the fate of deep-DOC when it is supplied with a large amount of fresh-DOC and exposed to strong solar radiation during the polynya opening in austral summer. We measured the radiocarbon content of DOC in the water column on the western Amundsen shelf. The radiocarbon content of DOC in the surface water of the ASP reflected higher primary production than in the region covered by sea ice. The radiocarbon measurements of DOC, taken two years apart in the ASP, were different, suggesting rapid cycling of DOC. The increase in DOC concentration was less than expected from the observed increase in radiocarbon content from those at the greatest depths. Based on a radiocarbon mass balance, we show that deep-DOC is consumed along with fresh-DOC in the ASP. Our observations imply that water circulation through the surface layer, where fresh-DOC is produced, may play an important role in global DOC cycling.
Keywords: CIRCUMPOLAR DEEP-WATER; cycle; DOC; glaciers; INFLOW; MATTER; pacific; phytoplankton; poc; radiocarbon

Silicified wood from around Old Faithful Geyser, Yellowstone National Park: U.S. Geological Survey data release - Hurwitz, Shaul; Peek, Sara E; Pigati, Jeff; Honke, Jeff; Damby, David E; Stricker, Craig A; King, John (U.S. Geological Survey, 2020)
Radiocarbon dating of silicified wood was performed at the U.S. Geological Survey’s Radiocarbon Laboratory in Denver, Colorado. All samples were chemically treated using the standard acid-base-acid (ABA) procedure before being combusted online in the presence of excess high-purity oxygen. Water and other contaminant gases were removed using cryogenic separation techniques, and the resulting purified CO2 gas was measured manometrically and converted to graphite using an iron catalyst and hydrogen reduction (Vogel et al., 1984). Graphite targets were then submitted for accelerator mass spectrometry 14C analysis at the National Ocean Sciences Accelerator Mass Spectrometry facility in Woods Hole, Massachusetts. All 14C ages were calibrated using the IntCal13 dataset and CALIB 7.1html (Stuiver and Reimer, 1993; Reimer et al., 2013). Calibrated age ranges are presented in calibrated years before present (BP; 0 yr BP = 1950 A.D.), and uncertainties are given at the 95% (2sigma) confidence level. Select sub-samples of silicified wood were excised with a stainless-steel razor blade and massed into 4 x 6 mm tin capsules (Costech Analytical, Inc, USA). Stable carbon isotope (δ13C) analysis was conducted by continuous flow-isotope ratio mass spectrometry at the U.S. Geological Survey’s Stable Isotope Laboratory in Denver, Colorado using a Carlo Erba NC1500 interfaced to a Micromass Optima mass spectrometer.  Isotopic data are reported in per mil notation after normalization to VPDB with USGS 40 (δ13C = -26.39 ‰) and USGS 41A (δ13C = 36.55 ‰). This research was conducted under Yellowstone Research Permit YELL-SCI-8030.
Type: dataset

The southern Gulf of Mexico: A baseline radiocarbon isoscape of surface sediments and isotopic excursions at depth - Bosman, Samantha H.; Schwing, Patrick T.; Larson, Rebekka A.; Wildermann, Natalie E.; Brooks, Gregg R.; Romero, Isabel C.; Sanchez-Cabeza, Joan-Albert; Ruiz-Fernández, Ana Carolina; Machain-Castillo, Maria Luisa; Gracia, Adolfo; Escobar-Briones, Elva; Murawski, Steven A.; et al. (PLOS ONE, 2020)
The southern Gulf of Mexico (sGoM) is home to an extensive oil recovery and development infrastructure. In addition, the basin harbors sites of submarine hydrocarbon seepage and receives terrestrial inputs from bordering rivers. We used stable carbon, nitrogen, and radiocarbon analyses of bulk sediment organic matter to define the current baseline isoscapes of surface sediments in the sGoM and determined which factors might influence them. These baseline surface isoscapes will be useful for accessing future environmental impacts. We also examined the region for influence of hydrocarbon deposition in the sedimentary record that might be associated with hydrocarbon recovery, spillage and seepage, as was found in the northern Gulf of Mexico (nGoM) following the Deepwater Horizon (DWH) oil spill in 2010. In 1979, the sGoM experienced a major oil spill, Ixtoc 1. Surface sediment δ13C values ranged from -22.4‰ to -19.9‰, while Δ14C values ranged from -337.1‰ to -69.2‰. Sediment δ15N values ranged from 2.8‰ to 7.2‰, while the %C on a carbonate-free basis ranged in value of 0.65% to 3.89% and %N ranged in value of 0.09% to 0.49%. Spatial trends for δ13C and Δ14C were driven by water depth and distance from the coastline, while spatial trends for δ15N were driven by location (latitude and longitude). Location and distance from the coastline were significantly correlated with %C and %N. At depth in two of twenty (10%) core profiles, we found negative δ13C and Δ14C excursions from baseline values in bulk sedimentary organic material, consistent with either oil-residue deposition or terrestrial inputs, but likely the latter. We then used 210Pb dating on those two profiles to determine the time in which the excursion-containing horizons were deposited. Despite the large spill in 1979, no evidence of hydrocarbon residue remained in the sediments from this specific time period.
Keywords: Gulf of Mexico; hydrocarbons; Oil spills; Oils; Petroleum; Sediment

Yellowstone's Old Faithful Geyser Shut Down by a Severe Thirteenth Century Drought - Hurwitz, Shaul; King, John C.; Pederson, Gregory T.; Martin, Justin T.; Damby, David E.; Manga, Michael; Hungerford, Jefferson D. G.; Peek, Sara (Geophysical Research Letters, 2020)
To characterize eruption activity of the iconic Old Faithful Geyser in Yellowstone National Park over past centuries, we obtained 41 new radiocarbon dates of mineralized wood preserved in the mound of silica that precipitated from erupted waters. Trees do not grow on active geyser mounds, implying that trees grew on the Old Faithful Geyser mound during a protracted period of eruption quiescence. Rooted stumps and root crowns located on higher parts of the mound are evidence that at the time of tree growth, the geyser mound closely resembled its current appearance. The range of calibrated radiocarbon dates (1233–1362 CE) is coincident with a series of severe multidecadal regional droughts toward the end of the Medieval Climate Anomaly, prior to the onset of the Little Ice Age. Climate models project increasingly severe droughts by mid-21st century, suggesting that geyser eruptions could become less frequent or completely cease.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1029/2020GL089871
Keywords: drought; Medieval Climate Anomaly; mineralization; Old Faithful Geyser; radiocarbon; Yellowstone

14C Blank Corrections for 25–100 μg Samples at the National Ocean Sciences AMS Laboratory - Roberts, M. L.; Elder, K. L.; Jenkins, W. J.; Gagnon, A. R.; Xu, L.; Hlavenka, J. D.; Longworth, B. E. (Radiocarbon, 2019)
Replicate radiocarbon (14C) measurements of organic and inorganic control samples, with known Fraction Modern values in the range Fm = 0–1.5 and mass range 6 μg–2 mg carbon, are used to determine both the mass and radiocarbon content of the blank carbon introduced during sample processing and measurement in our laboratory. These data are used to model, separately for organic and inorganic samples, the blank contribution and subsequently “blank correct” measured unknowns in the mass range 25–100 μg. Data, formulas, and an assessment of the precision and accuracy of the blank correction are presented.
Keywords: AMS; AMS dating; blank corrections

Age, Growth and Death of a National Icon: The Historic Chapman Baobab of Botswana - Patrut, Adrian; Woodborne, Stephan; Patrut, Roxana T.; Hall, Grant; Rakosy, Laszlo; Winterbach, Christiaan; von Reden, Karl F. (Forests, 2019)
The year 2016 witnessed the fall of a symbol of the botanical world: the historic Chapman baobab of Botswana. This article presents the results of our investigation of the standing and fallen tree. The Chapman baobab had an open ring-shaped structure composed of six partially fused stems. Several wood samples collected from the stems prior and after their collapse were analysed by using radiocarbon dating. The radiocarbon date of the oldest sample was 1381 ± 22 BP, which corresponds to a calibrated age of 1345 (+10, −15) calendar years. The dating results show that the six stems of the Chapman baobab belonged to three different generations, which were 1350–1400, 800–1000 and 500–600 years old. The growth rate variation of the largest and oldest stem is presented and correlated with the climate evolution in the area over the past 1000 years. The factors that determined the sudden fall and death of the Chapman baobab are also presented and discussed.

Analysis of multiple cosmogenic nuclides constrains Laurentide Ice Sheet history and process on Mt. Mansfield, Vermont's highest peak - Corbett, Lee B.; Bierman, Paul R.; Wright, Stephen F.; Shakun, Jeremy D.; Davis, P. Thompson; Goehring, Brent M.; Halsted, Christopher T.; Koester, Alexandria J.; Caffee, Marc W.; Zimmerman, Susan R. (Quaternary Science Reviews, 2019)
Constraining glacial history and process on Mt Mansfield, the highest peak in Vermont (1339 m a.s.l.), provides insight into how the Laurentide Ice Sheet shaped the underlying landscape, when latest Pleistocene ice retreated, and how upland and lowland glacial histories relate. Here, we quantify in situ cosmogenic 10Be in 20 bedrock and boulder surfaces, as well as in situ cosmogenic 14C in three of those surfaces, to assess subglacial erosion and exposure history. Isotopic concentrations indicate that Mt. Mansfield's lower elevations (∼400–1200 m a.s.l.) were deeply eroded by at least several meters during the last glaciation and then deglaciated rapidly; 10Be ages across this elevation span are indistinguishable and average 13.9 ± 0.6 ka (n = 15), suggesting that 800 m of ice thinning occurred within at most about a millennium. Conversely, the higher elevations (>1200 m a.s.l.) preserve a more complex geomorphic history. Mt. Mansfield's summit surfaces contain 10Be from previous periods of exposure, indicating that the mountaintop landscapes were likely preserved beneath cold-based, weakly-erosive glacial ice. Exposure ages from the shorter-lived isotope, 14C, are younger (9.7 and 11.7 ka), suggesting that Mt. Mansfield's summit was covered until the early Holocene, perhaps by snowfields, ice carapaces, and/or till. Our findings, in context of previous work, suggest that thinning Laurentide ice flowed through the valleys for at most hundreds of years following deglaciation of the uplands, but that the summit remained shielded by ice or sediment for millennia after the valleys became ice-free.
Keywords: Cosmogenic isotopes; erosion; Geochronology; Glaciation; Last glacial maximum; North America; Pleistocene

Antarctic Relic Microbial Mat Community Revealed by Metagenomics and Metatranscriptomics - Zaikova, Elena; Goerlitz, David S.; Tighe, Scott W.; Wagner, Nicole Y.; Bai, Yu; Hall, Brenda L.; Bevilacqua, Julie G.; Weng, Margaret M.; Samuels-Fair, Maya D.; Johnson, Sarah Stewart (Frontiers in Ecology and Evolution, 2019)
Buried upslope from the modern lakes in the McMurdo Dry Valleys of Antarctica are relict lake deposits embedded in valley walls. Within these relict deposits, ancient microbial mats, or paleomats, have been preserved under extremely arid and cold conditions since the receding of larger paleolakes thousands of years ago, and now serve as a sheltered niche for microbes in a highly challenging oligotrophic environment. To explore whether paleomats could be repositories for ancient lake cells or were later colonized by soil microbes, determine what types of metabolic pathways might be present, analyze potential gene expression, and explore whether the cells are in a vegetative or dormant state, we collected paleomat samples from ancient lake facies on the northern slopes of Lake Vanda in Wright Valley in December 2016. Using a gentle lysis technique optimized to preserve longer molecules, combined with a polyenzymatic treatment to maximize yields from different cell types, we isolated high-molecular weight DNA and RNA from ancient paleomat samples. Community composition analysis suggests that the paleomat community may retain a population of indigenous mat cells that may flourish once more favorable conditions are met. In addition to harboring a diverse microbial community, paleomats appear to host heterotrophs in surrounding soils utilizing the deposits as a carbon source. Whole genome long-read PacBio sequencing of native DNA and Illumina metagenomic sequencing of size-sorted DNA (>2,500 nt) indicated possible cell viability, with mat community composed of bacterial taxa. Metagenome assemblies identified genes with predicted roles in nitrogen cycling and complex carbohydrate degradation, and we identified key metabolic pathways such as stress response, DNA repair, and sporulation. Metatranscriptomic data revealed that the most abundant transcripts code for products involved in genetic information processing pathways, particularly translation, DNA replication, and DNA repair. Our results lend new insight into the functional ecology of paleomat deposits, with implications for our understanding of cell biology, Antarctic microbiology and biogeography, and the limits of life in extremely harsh environments.

The application of delta C-13, TOC and C/N geochemistry of mangrove sediments to reconstruct Holocene paleoenvironments and relative sea levels, Puerto Rico - Khan, Nicole S.; Vane, Christopher H.; Engelhart, Simon E.; Kendrick, Chris; Horton, Benjamin P. (MARINE GEOLOGY, 2019)
We assessed the use of delta C-13, TOC and C/N values of bulk sedimentary organic matter (OM) to reconstruct paleoenvironmental and relative sea-level change from mangrove environments in Puerto Rico. The modern distribution of delta C-13, TOC and C/N values was described from 63 vegetation and 59 surface sediment samples collected from three sites containing basin and riverine mangrove stands, and was compared to microfossil (foraminiferal and thecamoebian) assemblages. Four vertically-zoned environments were identified: tidal flat (delta C-13: -18.6 +/- 2.8 parts per thousand; TOC: 10.2 +/- 5.7%; C/N: 12.7 +/- 3.1), mangrove (delta C-13: -26.4 +/- 1.0 parts per thousand; TOC: 33.9 +/- 13.4%; C/N: 24.3 +/- 6.2), brackish transition (delta C-13: -28.8 +/- 0.7 parts per thousand; TOC: 40.8 +/- 11.7%; C/N: 21.7 +/- 3.7), and freshwater swamp (delta C-13: -28.4 +/- 0.4 parts per thousand; TOC: 42.8 +/- 4.8%; C/N: 17.0 +/- 1.1). These environments had distinct delta C-13, TOC and C/N values, with the exception of the brackish transition and freshwater swamp zones that were difficult to distinguish on a geochemical basis alone. The foraminiferal assemblages were complicated by a group that did not show a relationship to elevation due to the presence of calcareous foraminifera occurring above mean higher high water (MHHW), likely resulting from washover or transport by storms. However, the ratio of foraminifera to thecamoebians (F/T) along with delta C-13, TOC and C/N values refines the distinction between brackish and freshwater environments. Using linear discriminant analysis, we applied the delta C-13, TOC, C/N and F/T distributions to a 1.7 m core containing a continuous sequence of Rhizophora mangle peat, which began accumulating at similar to 1650-1930 CE. Together, microfossils, delta C-13, TOC, and C/N values, and the core chronology from Cs-137 and radiocarbon dating revealed that sediments in the core likely accumulated in response to anthropogenic sediment delivery, making it unsuitable for relative sea-level reconstruction. We caution that in the absence of detailed litho-, bio-, chemo-, or chrono-stratigraphic analyses as presented here, care should be taken in interpreting sea-level histories derived from single dates on mangrove peats.

CO2-dependent carbon isotope fractionation in Archaea, Part II: The marine water column - Hurley, Sarah J.; Close, Hilary G.; Elling, Felix J.; Jasper, Claire E.; Gospodinova, Kalina; McNichol, Ann P.; Pearson, Ann (GEOCHIMICA ET COSMOCHIMICA ACTA, 2019)
Stable carbon isotope ratios of archaeal glycerol dibiphytanyl glycerol tetraether (GDGT) lipids have been proposed as a proxy to infer past changes in the carbon isotope composition (delta C-13) of dissolved inorganic carbon (DIC). The premise for paleo-delta C-13(DIC) reconstructions from GDGTs is based on observations of relatively constant delta C-13(GDGT) values in recent depositional environments. Marine Thaumarchaeota, thought to be the dominant source of GDGTs to marine sediments, fix inorganic carbon using the 3-hydroxypropionate/4-hydroxybutyrate (3HP/4HB) pathway, which is specific to HCO3- as the substrate. Bicarbonate-dependent autotrophy has been the basis for predicting that the stable carbon isotopic composition of GDGTs (delta C-13(GDGT)) should vary in parallel with water column delta C-13(DIC) values, because HCO3- is by far the dominant fraction of DIC in modern seawater. However, this relationship has never been systematically tested. Here we examine the carbon isotopic composition of GDGTs from four water column profiles in the Southwest and Equatorial Atlantic Ocean. Values of delta C-13(GDGT) increase with depth in the water column, in contrast to the characteristic decrease in delta C-13(DIC) values. These divergent trends imply a decrease in the observed total biosynthetic isotope effect (epsilon(Ar)) with depth, i.e., the offset between delta(13)(DIC) and delta C-13(GDGT) is not constant. Instead, we find that values of epsilon(Ar) specifically correlate with oceanographic variables associated with extent of organic remineralization, decreasing as CO2 concentration increases. This observed relationship is consistent in both magnitude and direction with the results of an isotope flux-balance model for Thaumarchaeota that suggests epsilon(Ar) should be sensitive to growth rate (mu) and CO2 availability under conditions of atmospheric pCO(2) < 4 times the pre-anthropogenic Holocene level. Further tests of the sensitivity of epsilon(Ar) to u and CO2 in the modern marine environment will be essential to exploring the potential for a new, archaeal lipid-derived pCO(2) paleobarometer. (C) 2019 Elsevier Ltd. All rights reserved.

Comparing and improving methods for reconstructing peatland water-table depth from testate amoebae - Nolan, Connor; Tipton, John; Booth, Robert K; Hooten, Mevin B; Jackson, Stephen T (The Holocene, 2019)
Proxies that use changes in the composition of ecological communities to reconstruct temporal changes in an environmental covariate are commonly used in paleoclimatology and paleolimnology. Existing methods, such as weighted averaging and modern analog technique, relate compositional data to the covariate in very simple ways, and different methods are seldom compared systematically. We present a new Bayesian model that better represents the underlying data and the complexity in the relationships between species’ abundances and a paleoenvironmental covariate. Using testate amoeba–based reconstructions of water-table depth as a test case, we systematically compare new and existing models in a cross-validation experiment on a large training dataset from North America. We then apply the different models to a new 7500-year record of testate amoeba assemblages from Caribou Bog in Maine and compare the resulting water-table depth reconstructions. We find that Bayesian models represent an improvement over existing methods in three key ways: more complete use of the underlying compositional data, full and meaningful treatment of uncertainty, and clear paths toward methodological improvements. Furthermore, we highlight how developing and systematically comparing methods lead to an improved understanding of the proxy system. This paper focuses on testate amoebae and water-table depth, but the framework and ideas are widely applicable to other proxies based on compositional data.
Keywords: Bayesian statistics; compositional data; Holocene; hydrology; North America; Northeast United States; Paleoclimate; peatlands; statistical methods; testate amoebae

Evaluating the Radiocarbon Reservoir Effect in Lake Kutubu, Papua New GuineaABSTRACT - Schneider, Larissa; Pain, Colin F; Haberle, Simon; Blong, Russell; Alloway, Brent V; Fallon, Stewart J; Hope, Geoff; Zawadzki, Atun; Heijnis, Henk (Radiocarbon, 2019)
Conceptual models predict a tight coupling between the Intertropical Convergence Zone (ITCZ) and the Southern Westerly Winds (SWW) in response to glacial-interglacial transitions, yet little is known about this relationship under Holocene boundary conditions. Here we present a synthesis of Holocene pollen data from the southwest Pacific mid-latitudes that tracks changes in the SWW. Comparison of our SWW paleoclimate records with data tracking the ITCZ, oceanic circulation, and insolation reveals clearly synchronous and in-phase ITCZ-SWW dynamics between 12 and 5 ka, indicating a tight coupling between the tropics and southern mid-latitudes in response to ocean circulation and insolation. An apparent decoupling of the SWW and ITCZ in the Pacific region after 5 ka is attributable to the overriding influence of the El Niño–Southern Oscillation (ENSO) over the proxy data.

Evidence of Ice Age humans in eastern Beringia suggests early migration to North America - Vachula, Richard S.; Huang, Yongsong; Longo, William M.; Dee, Sylvia G.; Daniels, William C.; Russell, James M. (Quaternary Science Reviews, 2019)
Our understanding of the timing and pathway of human arrival to the Americas remains an important and polarizing topic of debate in archaeology and anthropology. Traditional consensus, supported by archaeological and paleoenvironmental data, favors a 'swift peopling' of the Americas from Asia via the Bering Land Bridge during the last Glacial termination. More recent genetic data and archaeological finds have challenged this view, proposing the 'Beringian standstill hypothesis' (BSH), wherein a population of proto-Americans migrated from Asia during, or even prior to the Last Glacial Maximum (LGM) and lived in Beringia for thousands of years before their eventual spread across the American continents. Using a sediment archive from Lake E5 (68.641667 degrees N, 149.457706 degrees W), located on Alaska's North Slope, we present new data supporting the BSH and shedding new light on the environmental impact of these early American populations. Fecal biomarkers support human presence in the environs of the lake, and our data demonstrate elevated biomass burning in this region during the last Glacial. Elevated burning defies the expectation that natural fires would be less frequent in the Arctic during the last Glacial, thereby suggesting human ignition as the likely culprit. Our data shed new light on the pathway and timing of human migration to the Americas and demonstrate the possibility of the sustainable coexistence of humans and the Ice Age megafauna in Beringia prior to their extinction. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Beringia; charcoal; Fecal sterols; Last Glacial; Paleofire; Polycyclic aromatic hydrocarbons (PAHs)

Four centuries of vegetation change in the mid-elevation Andean forests of Ecuador - Huisman, Seringe N.; Bush, Mark B.; McMichael, Crystal N. H. (Vegetation History and Archaeobotany, 2019)
Mid-elevation Andean ecosystems have immense species richness and endemism. Taxonomic composition is known to change through time on the eastern slopes of the Andes as a result of climatic change and disturbance events, both natural and by human actions. Fossil phytoliths can capture local scale vegetation changes, especially among monocotyledonous plants. Phytolith production is high in grasses and palms, plant groups that are particularly sensitive to climatic changes and disturbance events in Andean ecosystems. Here, we reconstruct four centuries of local-scale vegetation change and the corresponding fire history from lake sediment records retrieved from Lagunas Cormorán and Chimerella, located at ca. 1,700 m a.s.l. in the mid-elevation Andean forests of eastern Ecuador. The charcoal analysis of the lake sediments showed no sign of past fires, and no evidence of cultivation was found at either lake. The phytolith assemblages indicated changes in the relative abundances of palms, grasses and trees over the last few centuries, suggesting that mid-elevation Andean phytolith assemblages are sensitive to local scale vegetation dynamics. The largest change in vegetation occurred at the end of the Little Ice Age, at which point the diversity of palm phytoliths decreases. These phytolith assemblages are probably responding to changes in the cloud base position through time, which strongly influences the distributions of many plants and animals.

Glacial–interglacial Nd isotope variability of North Atlantic Deep Water modulated by North American ice sheet - Zhao, Ning; Oppo, Delia W.; Huang, Kuo-Fang; Howe, Jacob N. W.; Blusztajn, Jerzy; Keigwin, Lloyd D. (Nature Communications, 2019)
The Nd isotope composition of seawater has been used to reconstruct past changes in the contribution of different water masses to the deep ocean. In the absence of contrary information, the Nd isotope compositions of endmember water masses are usually assumed constant during the Quaternary. Here we show that the Nd isotope composition of North Atlantic Deep Water (NADW), a major component of the global overturning ocean circulation, was significantly more radiogenic than modern during the Last Glacial Maximum (LGM), and shifted towards modern values during the deglaciation. We propose that weathering contributions of unradiogenic Nd modulated by the North American Ice Sheet dominated the evolution of the NADW Nd isotope endmember. If water mass mixing dominated the distribution of deep glacial Atlantic Nd isotopes, our results would imply a larger fraction of NADW in the deep Atlantic during the LGM and deglaciation than reconstructed with a constant northern endmember.

Growth and longevity of Hawaiian grouper (Hyporthodus quernus) — input for management and conservation of a large, slow-growing grouper - Andrews, Allen H.; DeMartini, Edward E.; Brodziak, Jon; Nichols, Ryan S.; Humphreys, Robert L. (Canadian Journal of Fisheries and Aquatic Sciences, 2019)
Hawaiian grouper (Hyporthodus quernus) is endemic to the Hawaiian Islands and is regionally important, yet little is known about its life history. This large species is managed within the Deep 7 bottom fish complex, which includes six snapper species that are assumed to have similar life history traits. Previous age estimates were not validated and suggested a maximum age of 34 years. To evaluate the preliminary study and provide a valid basis for life history parameters, we aged otoliths using bomb radiocarbon (14C) dating. Measured 14C values provided ages for smallest to largest fish that differed from the original study. The fundamental information provided here when evaluating Hawaiian grouper conservation status is longevity (valid to 50 years and estimated to 76 years) — no male sampled was <80 cm total length (TL) and younger than 34 years — and age-at-sexual maturity and age-at-sex change, which were indirectly estimated and compared with prior published estimates for this and other groupers. Updated life history parameters (k = 0.078, L∞ = 95.8 cm TL) should be used to improve future management and conservation assessments.

Holocene glacier fluctuations on the northern flank of Cordillera Darwin, southernmost South America - Hall, B.L.; Lowell, T.V.; Bromley, G.R.M.; Denton, G.H.; Putnam, A.E. (Quaternary Science Reviews, 2019)

Holocene sea-level variability from Chesapeake Bay Tidal Marshes, USA - Cronin, Thomas M; Clevenger, Megan K; Tibert, Neil E; Prescott, Tammy; Toomey, Michael; Hubeny, J Bradford; Abbott, Mark B; Seidenstein, Julia; Whitworth, Hannah; Fisher, Sam; Wondolowski, Nick; Ruefer, Anna (The Holocene, 2019)
We reconstructed the last 10,000 years of Holocene relative sea-level rise (RSLR) from sediment core records near Chesapeake Bay, eastern United States, including new marsh records from the Potomac and Rappahannock Rivers, Virginia. Results show mean RSLR rates of 2.6 mm yr−1 from 10 to 8 kilo-annum (ka) due to combined final ice-sheet melting during deglaciation and glacio-isostatic adjustment (GIA subsidence). Mean RSLR rates from ~6 ka to present were 1.4 mm yr−1 due mainly to GIA, consistent with other East Coast marsh records and geophysical models. However, a progressively slower mean rate (<1.0 mm yr−1) characterized the last 1000 years when a multi-century-long period of tidal marsh development occurred during the ‘Medieval Climate Anomaly’ (MCA) and ‘Little Ice Age’ (LIA) in the Chesapeake Bay region and other East Coast marshes. This decrease was most likely due to climatic and glaciological processes and, correcting for GIA, represents a fall in global mean sea level (GMSL) near the end of Holocene Neoglacial cooling. These pre-historical climate- and GIA-driven Chesapeake Bay sea-level changes contrast sharply with those based on Chesapeake Bay tide-gauge rates (3.1–4.5 mm yr−1) (back to 1903). After subtracting the GIA subsidence component, these rates can be attributed to long-term (millennial) global factors of accelerated ocean thermal expansion (~1.0 mm yr−1) and mass loss from alpine glaciers and Greenland and Antarctic Ice Sheets (1.5–2.0 mm yr−1).
Keywords: chesapeake bay; Foraminifera; Holocene; sea level; tidal marsh; US East Coast

Improved C− efficiency and ion beam currents by modifying SNICS cathode material - Hlavenka, Joshua D.; Abrams, Henry; Roberts, Mark L.; Longworth, Brett E.; Fallon, Stewart (Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms, 2019)
We investigated the possibility of increasing the C-14 AMS efficiency and maximizing C- beam currents by modifying sample cathode geometry and material. Previously, we reported results which showed an increase in C- beam current and improved ionization efficiency when reducing the cathode sample well diameter from 1 mm to 0.75 mm and using zinc inserts, pressed into the aluminum cathode holder [4]. In this study we expand that effort by using cathodes with inserts made of Fe, Mo, Ni, Ti, Cu, and Zn. We pressed cathodes with 100 mu g of Oxalic Acid I (OX-I) and ran them to exhaustion. C-12 beam currents, C-14 counts, and graphite weight were used to determine ion source efficiency.
Keywords: Cathode; Efficiency; Ion source; SNICS

INFLUENCE OF DIFFERENT ACID TREATMENTS ON THE RADIOCARBON CONTENT SPECTRUM OF SEDIMENTARY ORGANIC MATTER DETERMINED BY RPO/ACCELERATOR MASS SPECTROMETRY - Bao, Rui; McNichol, Ann P.; Hemingway, Jordon D.; Gaylord, Mary C. Lardie; Eglinton, I, Timothy (RADIOCARBON, 2019)
In practice, obtaining radiocarbon (C-14) composition of organic matter (OM) in sediments requires first removing inorganic carbon (IC) by acid-treatment. Two common treatments are acid rinsing and fumigation. Resulting C-14 content obtained by different methods can differ, but underlying causes of these differences remain elusive. To assess the influence of different acid-treatments on C-14 content of sedimentary OM, we examine the variability in C-14 content for a range of marine and river sediments. By comparing results for unacidified and acidified sediments [HCl rinsing (Rinse(HCl)) and HCl fumigation (Fume(HCl))], we demonstrate that the two acid-treatments can affect C-14 content differentially. Our findings suggest that, for low-carbonate samples, Rinse(HCl) affects the Fm values due to loss of young labile organic carbon (OC). Fume(HCl) makes the Fm values for labile OC decrease, leaving the residual OC older. High-carbonate samples can lose relatively old organic components during Rinse(HCl), causing the Fm values of remaining OC to increase. Fume(HCl) can remove thermally labile, usually young, OC and reduce the Fm values. We suggest three factors should be taken into account when using acid to remove carbonate from sediments: IC abundance, proportions of labile and refractory OC, and environmental matrix.

Influence of Different Acid Treatments on the Radiocarbon Content Spectrum of Sedimentary Organic Matter Determined by RPO/Accelerator Mass SpectrometryABSTRACT - Bao, Rui; McNichol, Ann P; Hemingway, Jordon D; Lardie Gaylord, Mary C; Eglinton, Timothy I (Radiocarbon, 2019)
In practice, obtaining radiocarbon (C-14) composition of organic matter (OM) in sediments requires first removing inorganic carbon (IC) by acid-treatment. Two common treatments are acid rinsing and fumigation. Resulting C-14 content obtained by different methods can differ, but underlying causes of these differences remain elusive. To assess the influence of different acid-treatments on C-14 content of sedimentary OM, we examine the variability in C-14 content for a range of marine and river sediments. By comparing results for unacidified and acidified sediments [HCl rinsing (Rinse(HCl)) and HCl fumigation (Fume(HCl))], we demonstrate that the two acid-treatments can affect C-14 content differentially. Our findings suggest that, for low-carbonate samples, Rinse(HCl) affects the Fm values due to loss of young labile organic carbon (OC). Fume(HCl) makes the Fm values for labile OC decrease, leaving the residual OC older. High-carbonate samples can lose relatively old organic components during Rinse(HCl), causing the Fm values of remaining OC to increase. Fume(HCl) can remove thermally labile, usually young, OC and reduce the Fm values. We suggest three factors should be taken into account when using acid to remove carbonate from sediments: IC abundance, proportions of labile and refractory OC, and environmental matrix.

Intense Hurricane Activity Over the Past 1500 Years at South Andros Island, The Bahamas - Wallace, E. J.; Donnelly, J. P.; Hengstum, P. J.; Wiman, C.; Sullivan, R. M.; Winkler, T. S.; d'Entremont, N. E.; Toomey, M.; Albury, N. (Paleoceanography and Paleoclimatology, 2019)
Hurricanes cause substantial loss of life and resources in coastal areas. Unfortunately, historical hurricane records are too short and incomplete to capture hurricane‐climate interactions on multi‐decadal and longer timescales. Coarse‐grained, hurricane‐induced deposits preserved in blue holes in the Caribbean can provide records of past hurricane activity extending back thousands of years. Here we present a high resolution record of intense hurricane events over the past 1500 years from a blue hole on South Andros Island on the Great Bahama Bank. This record is corroborated by shorter reconstructions from cores collected at two nearby blue holes. The record contains coarse‐grained event deposits attributable to known historical hurricane strikes within age uncertainties. Over the past 1500 years, South Andros shows evidence of four active periods of hurricane activity. None of these active intervals occurred in the past 163 years. We suggest that Intertropical Convergence Zone position modulates hurricane activity on the island based on a correlation with Cariaco Basin titanium concentrations. An anomalous gap in activity on South Andros Island in the early 13th century corresponds to a period of increased volcanism. The patterns of hurricane activity reconstructed from South Andros Island closely match those from the northeastern Gulf of Mexico but are anti‐phased with records from New England. We suggest that either changes in local environmental conditions (e.g., SSTs) or a northeastward shift in storm tracks can account for the increased activity in the western North Atlantic when the Gulf of Mexico and southeastern Caribbean are less active.

Laser ablation–accelerator mass spectrometry reveals complete bomb 14C signal in an otolith with confirmation of 60-year longevity for red snapper (Lutjanus campechanus) - Andrews, Allen H.; Yeman, Christiane; Welte, Caroline; Hattendorf, Bodo; Wacker, Lukas; Christl, Marcus (Marine and Freshwater Research, 2019)
Bomb-produced14C has been used to make valid estimates of age for various marine organisms for 25 years, but fish ages that lead to birth years earlier than the period of increase in14C lose their time specificity. As a result, bomb14Cdating is limited to a minimum age from the last year of prebomb levels because the temporal variation in14C in the marine surface layer is negligible for decades before c. 1958. The longevity of red snapper (Lutjanus campechanus) in the Gulf of Mexico remains unresolved despite various forms of support for ages near 50–60 years. Although the age and growth of red snapper have been verified or validated to a limited extent, some scepticism remains about longevity estimates that exceed30 years. In this study, red snapper otoliths were analysed for14C using a novel laser ablation–accelerator mass spectrometry technique to provide a continuousrecordof14C uptake. This approach provided a basis for age validation that extends beyond the normal limits of bomb14C dating with confirmation of a 60-year longevity for red snapper in the Gulf of Mexico.
Keywords: Age validation; Carbon-14; Gulf of Mexico; Lutjanidae; radiocarbon.

Legacy sediment storage in New England river valleys: Anthropogenic processes in a postglacial landscape - Johnson, Kaitlin M.; Snyder, Noah P.; Castle, Stephanie; Hopkins, Austin J.; Waltner, Mason; Merritts, Dorothy J.; Walter, Robert C. (Geomorphology, 2019)
Legacy sediment associated with erosion from land clearing is a common feature in river valleys of the unglaciated Mid-Atlantic Piedmont region. Here, we quantify the volume of legacy sediment storage in three watersheds in New England, a formerly glaciated region with similar history and intensity of forest clearing and milldam construction during the seventeenth to nineteenth centuries. We combine field observations of bank stratigraphy, radiocarbon dating, and mapping of terraces and floodplains using lidar digital elevation models and other GIS datasets. The 68 km2 South River watershed in western Massachusetts exhibits the most extensive evidence for legacy sediment storage. We visited 18 historic dam sites in the watershed and found field evidence for up to 2.2 m of fine sand and silt legacy sediment storage at 14 of the sites. In the 555 km2 Sheepscot River watershed in coastal Maine, we visited 13 historic dam sites and found likely legacy sediment up to 2.3 m thick at six of the dams. In the 171 km2 upper Charles River watershed in eastern Massachusetts, we investigated 14 dam sites, and found legacy sediment up to 1.8 m thick at two of them. Stratigraphically, we identified the base of fine-grained legacy sediment from a change to much coarser grain size (gravel at most sites) or to glacial lacustrine or marine deposits. Along the Sheepscot River, we observed cut timbers underlying historic sediment at several locations, likely associated with sawmill activities. Only at the Charles River were we able to radiocarbon date the underlying gravel layer (1281–1391 calibrated CE). At no site did we find a buried organic-rich Holocene soil, in contrast to the field relations commonly observed in the Mid-Atlantic region. We use lidar elevation data to map planar terrace extents in each watershed, estimate thickness of remaining legacy sediment found stored behind breached or removed milldams, and estimate volumes of remaining legacy sediment storage in valley bottoms for entire watersheds. The maximum volume of stored legacy sediment estimated for the South, Sheepscot, and upper Charles watersheds is 2.5 × 106 m3, 3.7 × 106 m3, and 2.6 × 104 m3, respectively. These volumes of legacy sediment can be translated to an equivalent thickness of soil eroded from each watershed: 37 mm, 7 mm, and 0.2 mm, respectively. We attribute the variation in presence and thickness of legacy sediment at the New England sites to the existence or absence of upstream sediment supply in the form of thick glacial deposits and to sinks such as lakes and wetlands along valley bottoms. Of the three study watersheds, the South River has the most extensive glacial sediments, fewest sinks, and the most legacy sediment in storage along the river corridor.
Keywords: Anthropogenic sediment; Legacy sedimen; Milldams

Mapping Isotopic and Dissolved Organic Matter Baselines in Waters and Sediments of the Gulf of Mexico - Chanton, Jeffrey P.; Jaggi, Aprami; Radović, Jagoš R.; Rosenheim, Brad E.; Walker, Brett D.; Larter, Stephen R.; Rogers, Kelsey; Bosman, Samantha; Oldenburg, Thomas B. P. (Springer International Publishing, 2019)
The Deepwater Horizon oil spill released petroleum hydrocarbons that were depleted in δ13C and Δ14C at depth into the Gulf of Mexico. Stable-carbon and radiocarbon isotopic values and high-resolution mass spectrometry were used to follow the distributions of this petroleum and to track its transformation into petrocarbon, a term used to describe crude oil or transformed crude oil following biodegradation, weathering, oxygenation, or loss of lighter components. The term petrocarbon includes oil- or methane-derived carbon assimilated or incorporated into microbial biomass or into the food web as well as degraded and undegraded petroleum constituents. Here we report (1) the increase in the relative abundance of oxygen-containing carbon compounds making up the dissolved organic matter (DOM) with increasing depth through the water column, indicating the biodegradation of DOM as it was transported to depth in the water column, (2) the finding of 14C depletion in DOM indicating petrocarbon inputs, and (3) the decrease and subsequent increase of 14C in the isotopic composition of sinking particles indicating the capture of petrocarbon in sediment traps. In addition, we discuss the 14C depletion of this material once it is sedimented to the seafloor and the implications for oil spill budgets of seafloor petrocarbon deposition.
Keywords: Dissolved organic matter; FTICR-MS; Gulf baselines; High-resolution mass spectrometry; organic carbon; radiocarbon; Ramped pyrolysis; Sediment organic matter

The Mighty Susquehanna—Extreme Floods in Eastern North America During the Past Two Millennia - Toomey, Michael; Cantwell, Meagan; Colman, Steven; Cronin, Thomas; Donnelly, Jeffrey; Giosan, Liviu; Heil, Clifford; Korty, Robert; Marot, Marci; Willard, Debra (Geophysical Research Letters, 2019)
The hazards posed by infrequent major floods to communities along the Susquehanna River and the ecological health of Chesapeake Bay remain largely unconstrained due to the short length of streamgage records. Here we develop a history of high‐flow events on the Susquehanna River during the late Holocene from flood deposits contained in MD99‐2209, a sediment core recovered in 26 m of water from Chesapeake Bay near Annapolis, Maryland, United States. We identify coarse‐grained deposits left by Hurricane Agnes (1972) and the Great Flood of 1936, as well as during three intervals that predate instrumental flood records (~1800–1500, 1300–1100, and 400–0 CE). Comparison to sedimentary proxy data (pollen and ostracode Mg/Ca ratios) from the same core site indicates that prehistoric flooding on the Susquehanna often accompanied cooler‐than‐usual winter/spring temperatures near Chesapeake Bay—typical of negative phases of the North Atlantic Oscillation and conditions thought to foster hurricane landfalls along the East Coast.

Millennial-scale carbon accumulation and molecular transformation in a permafrost core from Interior Alaska - Hutchings, J.A.; Bianchi, T.S.; Kaufman, D.S.; Kholodov, A.L.; Vaughn, D.R.; Schuur, E.A.G. (Geochimica et Cosmochimica Acta, 2019)
Organic carbon stored in high-latitude permafrost represents a potential positive feedback to climate warming as well as a valuable store of paleoenvironmental information. The below-freezing conditions have effectively removed permafrost organic material from the modern carbon cycle and preserved its pre-freezing bulk and molecular states. The conditions that lead to efficient burial of organic carbon (OC) within permafrost were investigated by measuring OC stocks, past accumulation rates, and biogeochemical composition of a permafrost core taken from Interior Alaska dating back to 40 ka. The post-glacial Marine Isotope Stage 1 is represented by the top 1.2 m of the core and contains 64.7 kg OC/m2 with an accumulation rate of 4.3 g OC/m2/yr. The sediments that accumulated around the Last Glacial Maximum contain 9.9 kg OC/m2 with an accumulation rate of 0.5 g OC/m2/yr. Carbon storage (144.7 kg OC/m2) and accumulation (26.1 g OC/m2/yr) are both observed to be greatest between 35 and 40 ka, late during the Marine Isotope Stage 3 global interstadial. The extent of OC degradation was assessed using lignin and amino acid biomarkers with both approaches indicating well-preserved contemporary active layer and interstadial OC, whereas stadial OC was highly degraded. Lignin compositional indices throughout the core appear altered by sorptive processes that confounded some expected trends in the overall organic matter composition, while amino acids provided a more integrated pattern of change. Significant correlations between carbon-normalized hydroxyproline and total lignin concentrations further support the usefulness of hydroxyproline as an indicator for the abundance of plant organic matter. A novel amino acid plant-microbial index of the ratio of microbial-specific muramic acid and diaminopimelic acid biomarkers to the plant-specific hydroxyproline biomarker, indicate a transition from plant-dominated organic matter in fresh organic soils (index values of 0.01–0.20) to more microbial-dominated organic matter in degraded mineral soils (index values of 0.50–2.50). The branched glycerol dialkyl glycerol tetraether composition is complex and is not immediately compatible with existing temperature transfer functions. Residence time within the active layer is interpreted to integrate key factors such as primary productivity, inorganic sediment delivery, and other climate factors that control soil organic matter degradation. The Marine Isotope Stage 3, mid-Wisconsin interstadial period at this locality was forest-dominated and suggests the currently prevailing tundra ecotone is sensitive to environmental change. The majority of buried permafrost OC is high in degradability and if thawed, would be expected to be highly vulnerable to microbial decomposition.
Keywords: amino acids; biomarkers; branched GDGTs; lignin phenols; organic carbon; permafrost

Millennial-scale fluctuations in water volume transported by the Tsushima Warm Current in the Japan Sea during the Holocene - Horikawa, Keiji; Kodaira, Tomohiro; Ikehara, Ken; Murayama, Masafumi; Zhang, Jing (Global and Planetary Change, 2019)
Cyclic changes in volume transport of the Tsushima Warm Current (TWC) have been argued from diatom records in the southern Japan Sea off the Japanese islands during the Holocene. Although this phenomenon has not yet been confirmed by various proxy data, determining whether or not these oceanographic changes occurred is crucial for clarifying the nature of oceanographic changes in the southern Japan Sea. Here, we conducted a coupled analysis of Mg/Ca ratios and oxygen isotopes (δ18O) in shallow-dwelling Neogloboquadrina incompta from 13 core-top sediments in southern Japan, and developed a new equation for Mg/Ca temperature calibration (Mg/Ca = 0.311 × exp (0.07 × T)) as a proxy for spring sea surface temperature (SST). Using the newly developed, species-specific Mg/Ca-paleothermometry, we reconstructed SST variability for the past 6800 years from core YK10-7-PC09 in the southern Japan Sea. The Mg/Ca-derived SST record clearly represented five warmer periods at 6200–6000, 4900–4500, 4200–3800, 2600–2100, and 900–400 cal. year BP, almost consistent with previously published diatom records. These warmer events also corresponded to the periods in which warm molluscan assemblages increased at the northern end of the TWC, suggesting that periods of higher SST can be seen as reflecting the increased volume transport of the TWC. We interpreted the results of a model study showing that higher solar irradiance provoked positive Arctic Oscillation (AO)-like spatial patterns and the negative phase of the Pacific Decadal Oscillation (PDO) to mean that increased (reduced) TWC volume transport on the multi-centennial to millennial time scales was caused by high (low) solar insolation via a potential link between AO and PDO. Given that larger and more frequent volcanic eruptions occurred in the mid Holocene than in the late Holocene, volcanic forcing on the TWC volume transport changes would have been more significant during the former, as seen in the highly variable SST from this period and distinct decreases in SST around ~5900 cal. year BP and ~6400 cal. year BP. The millennial-scale fluctuations seen in SSTs in the southern Japan Sea would have had a large impact on the evolution of vegetation and human adaptation in the northern Japanese islands, adjacent to the Japan Sea, over the last 6800 years.
Keywords: Holocene; Mg/Ca-derived; Neogloboquadrina incompta; sea-surface temperature; Solar forcing; The Japan Sea; Tsushima; Warm Current

Mineral protection regulates long-term global preservation of natural organic carbon - Hemingway, Jordon D.; Rothman, Daniel H.; Grant, Katherine E.; Rosengard, Sarah Z.; Eglinton, Timothy I.; Derry, Louis A.; Galy, Valier V. (Nature, 2019)
The balance between photosynthetic organic carbon production and respiration controls atmospheric composition and climate1,2. The majority of organic carbon is respired back to carbon dioxide in the biosphere, but a small fraction escapes remineralization and is preserved over geological timescales3. By removing reduced carbon from Earth’s surface, this sequestration process promotes atmospheric oxygen accumulation2 and carbon dioxide removal1. Two major mechanisms have been proposed to explain organic carbon preservation: selective preservation of biochemically unreactive compounds4,5 and protection resulting from interactions with a mineral matrix6,7. Although both mechanisms can operate across a range of environments and timescales, their global relative importance on 1,000-year to 100,000-year timescales remains uncertain4. Here we present a global dataset of the distributions of organic carbon activation energy and corresponding radiocarbon ages in soils, sediments and dissolved organic carbon. We find that activation energy distributions broaden over time in all mineral-containing samples. This result requires increasing bond-strength diversity, consistent with the formation of organo-mineral bonds8 but inconsistent with selective preservation. Radiocarbon ages further reveal that high-energy, mineral-bound organic carbon persists for millennia relative to low-energy, unbound organic carbon. Our results provide globally coherent evidence for the proposed7 importance of mineral protection in promoting organic carbon preservation. We suggest that similar studies of bond-strength diversity in ancient sediments may reveal how and why organic carbon preservation—and thus atmospheric composition and climate—has varied over geological time.

New Last Glacial Maximum ice thickness constraints for the Weddell Sea Embayment, Antarctica - Nichols, Keir A.; Goehring, Brent M.; Balco, Greg; Johnson, Joanne S.; Hein, Andrew S.; Todd, Claire (The Cryosphere, 2019)
We describe new Last Glacial Maximum (LGM) ice thickness constraints for three locations spanning the Weddell Sea Embayment (WSE) of Antarctica. Samples collected from the Shackleton Range, Pensacola Mountains, and the Lassiter Coast constrain the LGM thickness of the Slessor Glacier, Foundation Ice Stream, and grounded ice proximal to the modern Ronne Ice Shelf edge on the Antarctic Peninsula, respectively. Previous attempts to reconstruct LGM-to-present ice thickness changes around the WSE used measurements of long-lived cosmogenic nuclides, primarily Be-10. An absence of post-LGM apparent exposure ages at many sites led to LGM thickness reconstructions that were spatially highly variable and inconsistent with flow line modelling. Estimates for the contribution of the ice sheet occupying the WSE at the LGM to global sea level since deglaciation vary by an order of magnitude, from 1.4 to 14.1m of sea level equivalent. Here we use a short-lived cosmogenic nuclide, in situ-produced C-14, which is less susceptible to inheritance problems than Be-10 and other long-lived nuclides. We use in situ C-14 to evaluate the possibility that sites with no post-LGM exposure ages are biased by cosmogenic nuclide inheritance due to surface preservation by cold-based ice and non-deposition of LGM-aged drift. Our measurements show that the Slessor Glacier was between 310 and up to 655m thicker than present at the LGM. The Foundation Ice Stream was at least 800m thicker, and ice on the Lassiter Coast was at least 385m thicker than present at the LGM. With evidence for LGM thickening at all of our study sites, our in situ C-14 measurements indicate that the long-lived nuclide measurements of previous studies were influenced by cosmogenic nuclide inheritance. Our inferred LGM configuration, which is primarily based on minimum ice thickness constraints and thus does not constrain an upper limit, indicates a relatively modest contribution to sea level rise since the LGM of < 4.6 m, and possibly as little as < 1.5 m.

On the Origin of Aged Sedimentary Organic Matter Along a River‐Shelf‐Deep Ocean Transect - Bao, Rui; Zhao, Meixun; McNichol, Ann; Wu, Ying; Guo, Xinyu; Haghipour, Negar; Eglinton, Timothy I. (Journal of Geophysical Research: Biogeosciences, 2019)
To assess the influences of carbon sources and transport processes on the C-14 age of organic matter (OM) in continental margin sediments, we examined a suite of samples collected along a river-shelf-deep ocean transect in the East China Sea (ECS). Ramped pyrolysis-oxidiation was conducted on suspended particulate matter in the Yangtze River and on surface sediments from the ECS shelf and northern Okinawa Trough. C-14 ages were determined on OM decomposition products within different temperature windows. These measurements suggest that extensive amounts of pre-old (i.e., millennial age) organic carbon (OC) are subject to degradation within and beyond the Yangtze River Delta, and this process is accompanied by an exchange of terrestrial and marine OM. These results, combined with fatty acid concentration data, suggest that both the nature and extent of OM preservation/degradation as well as the modes of transport influence the C-14 ages of sedimentary OM. Additionally, we find that the age of (thermally) refractory OC increases during across-shelf transport and that the age offset between the lowest and highest temperature OC decomposition fractions also increases along the shelf-to-trough transect. Amplified interfraction spread or C-14 heterogeneity is the greatest in the Okinawa Trough. Aged sedimentary OM across the transect may be a consequence of several reasons including fossil OC input, selective degradation of younger OC, hydrodynamic sorting processes, and aging during lateral transport. Consequently, each of them should be considered in assessing the C-14 results of sedimentary OM and its implications for the carbon cycle and interpretation of sedimentary records.
Keywords: Carbon cycle; hydrodynamic processes; organic carbon; radiocarbon; sediments

Paleoseismic Investigation of the Levan and Fayette Segments of the Wasatch Fault Zone, Juab and Sanpete Counties, Utah - McDonald, Greg N.; Hiscock, Adam I.; Hylland, Micheal D. (Utah Geological Survey, 2019)

Salt marsh ecosystem restructuring enhances elevation resilience and carbon storage during accelerating relative sea-level rise - Gonneea, Meagan Eagle; Maio, Christopher V.; Kroeger, Kevin D.; Hawkes, Andrea D.; Mora, Jordan; Sullivan, Richard; Madsen, Stephanie; Buzard, Richard M.; Cahill, Niamh; Donnelly, Jeffrey P. (Estuarine, Coastal and Shelf Science, 2019)
Salt marshes respond to sea-level rise through a series of complex and dynamic bio-physical feedbacks. In this study, we found that sea-level rise triggered salt marsh habitat restructuring, with the associated vegetation changes enhancing salt marsh elevation resilience. A continuous record of marsh elevation relative to sea level that includes reconstruction of high-resolution, sub-decadal, marsh elevation over the past century, coupled with a lower-resolution 1500-year record, revealed that relative sea-level rose 1.5 ± 0.4 m, following local glacial isostatic adjustment (1.2 mm/yr). As sea-level rise has rapidly accelerated, the high marsh zone dropped 11 cm within the tidal frame since 1932, leading to greater inundation and a shift to flood- and salt-tolerant low marsh species. Once the marsh platform fell to the elevation favored by low-marsh Spartina alterniflora, the elevation stabilized relative to sea level. Currently low marsh accretion keeps pace with sea-level rise, while present day high marsh zones that have not transitioned to low marsh have a vertical accretion deficit. Greater biomass productivity, and an expanding subsurface accommodation space favorable for salt marsh organic matter preservation, provide a positive feed-back between sea-level rise and marsh platform elevation. Carbon storage was 46 ± 28 g C/m2/yr from 550 to 1800 CE, increasing to 129 ± 50 g C/m2/yr in the last decade. Enhanced carbon storage is controlled by vertical accretion rates, rather than soil carbon density, and is a direct response to anthropogenic eustatic sea-level rise, ultimately providing a negative feedback on climate warming.
Keywords: 14-Carbon; accretion; Carbon storage; Elevation; Salt marsh; Sea level index point; sea-level rise

Significance of Perylene for Source Allocation of Terrigenous Organic Matter in Aquatic SedimentsSignificance of Perylene for Source Allocation of Terrigenous Organic Matter in Aquatic Sediments - Hanke, Ulrich M.; Lima-Braun, Ana L.; Eglinton, Timothy I.; Donnelly, Jeffrey P.; Galy, Valier; Poussart, Pascale; Hughen, Konrad; McNichol, Ann P.; Xu, Li; Reddy, Christopher M. (Environmental Science & Technology, 2019)
Perylene is a frequently abundant, and sometimes the only polycyclic aromatic hydrocarbon (PAH) in aquatic sediments, but its origin has been subject of a longstanding debate in geochemical research and pollutant forensics because its historical record differs markedly from typical anthropogenic PAHs. Here we investigate whether perylene serves as a source-specific molecular marker of fungal activity in forest soils. We use a well-characterized sedimentary record (1735-1999) from the anoxic-bottom waters of the Pettaquamscutt River basin, RI to examine mass accumulation rates and isotope records of perylene, and compare them with total organic carbon and the anthropogenic PAH fluoranthene. We support our arguments with radiocarbon (14C) data of higher plant leaf-wax n-alkanoic acids. Isotope-mass balance-calculations of perylene and n-alkanoic acids indicate that ∼40% of sedimentary organic matter is of terrestrial origin. Further, both terrestrial markers are pre-aged on millennial time-scales prior to burial in sediments and are insensitive to elevated 14C concentrations following nuclear weapons testing in the mid-20th Century. Instead, changes coincide with enhanced erosional flux during urban sprawl. These findings suggest that perylene is definitely a product of soil-derived fungi, and a powerful chemical tracer to study the spatial and temporal connectivity between terrestrial and aquatic environments.

Sinking particle flux and composition at three sites of different annual sea ice cover in the Amundsen Sea, Antarctica - Kim, Minkyoung; Yang, Eun J.; Kim, Dongseon; Jeong, Jin-Hyun; Kim, Hyung J.; Park, Jisoo; Jung, Jinyoung; Ducklow, Hugh W.; Lee, SangHoon; Hwang, Jeomshik (Journal of Marine Systems, 2019)
This study examines the sinking particle flux and composition of samples collected at three sites in the western Amundsen Sea, Antarctica: a perennial sea-ice-covered area, the central region of the Amundsen Sea polynya, and close to the Dotson Ice Shelf within the polynya. Time series sediment traps were deployed for one year at depths of 400-500 m from February and March 2012. Observations from the three sites confirm previously reported findings that the majority of annual POC (particulate organic carbon) flux in the Amundsen Sea occurs during the austral summer, with much smaller POC fluxes during other seasons. In the perennial ice-covered area, sea ice diatoms were the dominant source of sinking particles. In this region, the summertime POC flux is similar to that in the central polynya. However, the POC flux exhibited large interannual variability, with the reduction in sea ice cover and sufficient insolation being critical to enhanced sinking POC flux. Within the Amundsen Sea polynya, the sinking POC flux was higher in the central region than near the Dotson Ice Shelf, consistent with spatial variability in primary production. The site near the Dotson Ice Shelf had the lowest contribution of diatoms to sinking particles and the smallest POC flux among the three sites.
Keywords: Amundsen sea; Biological pump; particulate organic carbon; Perennial ice-covered area; Polynya

Sortable silt records of intermediate-depth circulation and sedimentation in the Southwest Labrador Sea since the Last Glacial Maximum - Hoffmann, Sharon S.; Dalsing, Risa E.; Murphy, Sarah C. (Quaternary Science Reviews, 2019)
The Labrador Sea is a vital region for the Atlantic Meridional Overturning Circulation (AMOC), where overflow waters from the Nordic Seas mix with locally produced Labrador Sea Water (LSW), before exiting to the interior of the Atlantic Ocean. The dynamical sedimentary proxy of mean sortable silt size () can give information on past changes in deep water circulation speed and the strength of AMOC. We have produced records from two core sites at depths between 1500 and 2000 m on the continental slope east of Newfoundland, to reconstruct changes in intermediate depth water circulation speed, including Glacial North Atlantic Intermediate Water and Labrador Sea Water over the past 22,000 years. Increases in appear to coincide with much of the deglaciation as well as the mid-late Holocene. End-member modeling suggests that ice-rafted debris (IRD) is an important factor in interpreting during the deglaciation. We find that a robust increase in is likely unrelated to IRD during the past 5 ka, and probably reflects increased flow at intermediate depths due to local production of LSW strengthening as Nordic Seas overflows weakened at this depth. Our results highlight both the complications of producing records in IRD-rich, slope environments and the promise that this proxy nevertheless has for reconstructing dynamical changes in deep ocean currents.
Keywords: Holocene; labrador sea; paleoceanography; Sedimentology-marine cores

Springwater provenance and flowpath evaluation in Blue Lake, Bonneville basin, Utah - Lerback, Jory Chapin; Hynek, Scott A.; Bowen, Brenda B.; Bradbury, Christopher D.; Solomon, D. Kip; Fernandez, Diego P. (Chemical Geology, 2019)
Water in Utah and Nevada is important for agriculture, municipal use, solute transport, and ecosystem preservation. Large spring wetland systems occur on the playa margin of the Bonneville basin, including Blue Lake, 15 km south of the Bonneville Salt Flats on the Utah-Nevada state border. Large spring systems have historically been studied as water budgets don't apparently balance from direct mountain front recharge (Nelson and Mayo, 2014; Gardner and Heilweil, 2014; and others). Blue Lake is no exception; prior studies here have suggested discharge rates 0.04 - 0.05 km3/yr (Louderback and Rhode, 2009), greater than expected for modelled recharge in the surrounding mountain range (0.03 km3/yr). Three hypothesized recharge mechanisms for Blue Lake are tested: mountain-front recharge, interbasinal groundwater flow, and infiltration from historic Lake Bonneville. Remote sensing suggests that a conservative estimate of Blue Lake discharge constitutes 50-64% of modelled mountain-front recharge (Flint et al., 2011). Major ions, δ18O, δ2H, dissolved gases (14C, 3He, 4He, Ne, Ar, Kr, Xe) and trace elements (Sr and 87Sr/86Sr isotopes) comprehensively constrain recharge conditions, water-rock interactions, flowpaths, and groundwater provenance of this large spring system. 14C signatures suggest that Blue Lake discharge has a transit time between 5,600 and 12,200 years, older than that of Fish Springs. Noble gas concentrations in Blue Lake water suggest an elevated recharge temperature greater than 19°C and low salinity, indicating a deep water table and high geothermal gradient in the recharge area. 87Sr/86Sr ratios of playa-margin springs are elevated from that of mid-playa groundwaters, springwaters from the adjacent mountain range, and alluvial fill groundwater from the valley directly south of Blue Lake. Playa-margin spring Sr isotope values (0.713-0.714) are most similar to direct runoff from the Deep Creek Range granodiorite outcrop (>0.713). Interbasinal groundwater flow in combination with mountain-front recharge is best supported by chemical data rather than mountain-front recharge alone or the slow discharge of regional aquifers recharged by lacustrine infiltration from Lake Bonneville.
Keywords: Bonneville basin; Geochemistry; groundwater; Isotope chemistry

Temperature-controlled tundra fire severity and frequency during the last millennium in the Yukon-Kuskokwim Delta, Alaska - Sae-Lim, Jarunetr; Russell, James M; Vachula, Richard S; Holmes, Robert M; Mann, Paul J; Schade, John D; Natali, Susan M (The Holocene, 2019)
Wildfire is an important disturbance to Arctic tundra ecosystems. In the coming decades, tundra fire frequency, intensity, and extent are projected to increase because of anthropogenic climate change. To more accurately predict the effects of climate change on tundra fire regimes, it is critical to have detailed knowledge of the natural frequency and extent of past wildfires and how they responded to past climate variability. We present analyses of fire frequency and temperature from a lake sediment core from the Yukon-Kuskokwim (YK) Delta. Our ca. 1000 macroscopic charcoal record shows more frequent but possibly less severe tundra fires during the first half of the last millennium, whereas less frequent, possibly more severe fires characterize the latter half. Our temperature reconstruction, based on distributional changes of branched glycerol dialkyl glycerol tetraethers (brGDGTs), shows slightly warmer conditions from ca. AD 1000 to 1500, and cooler conditions thereafter (ca. AD 1500 to 2000), suggesting that fire frequency increases when climate is relatively warmer in this region. When wildfires occur more frequently, fire severity may decrease because of limited biomass (fuel source) accumulating between fires. The data suggest that tundra ecosystems are highly sensitive to climate change, and that a warmer climate, which is predicted to develop in the near future, will result in more frequent tundra wildfires.
Keywords: alaska; Arctic; charcoal; glycerol dialkyl glycerol tetraethers (GDGTs); late-holocene; Paleoclimate; Paleofire

Temporal constraints on lateral organic matter transport along a coastal mud belt - Bao, Rui; Zhao, Meixun; McNichol, Ann; Galy, Valier; McIntyre, Cameron; Haghipour, Negar; Eglinton, Timothy I. (Organic Geochemistry, 2019)
Constraints on timescales of lateral transport of sedimentary organic carbon (OC) over continental shelves and associated influences on the distribution and abundance of OC remain sparse. Preferential degradation of labile, young OC during lateral transport results in apparent “diagenetic aging” of OC. Additionally, sediment translocation can also result in “transport time-associated aging” of associated organic matter (OM) as a function of the lateral transport time (LTT). Here, we use a coupled thermal decomposition and radiocarbon (14C) approach to constrain timescales of lateral transport and concomitant loss of OC associated with different grain size fractions of sediments collected from two locations ∼275 km apart along a dispersal pathway on the inner shelf of the East China Sea. The 14C age contrasts between corresponding thermal fractions are used to distinguish these two components of sedimentary OM “aging”. To minimize interferences from hydrodynamic sorting and diagenetic aging of OC accompanying lateral transport, we assess 14C age differences of decomposition products from the most thermally-refractory OC components associated with specific grain size fractions between locations. We show that LTTs vary among different grain size fractions, and examine relationships between LTTs and sedimentary OC loss in order to assess the decomposition of OC as a consequence of lateral transport. We suggest that the decomposition of OC associated with protracted lateral transport exerts a strong influence on OC burial efficiency, with broad implications for carbon cycling over continental shelves.
Keywords: 14C aging; Continental shelf seas; East China Sea; Mud belt; organic matter; Sediment resuspension

Temporal deconvolution of vascular plant-derived fatty acids exported from terrestrial watersheds - Vonk, Jorien E.; Drenzek, Nicholas J.; Hughen, Konrad A.; Stanley, Rachel H.R.; McIntyre, Cameron; çon, Daniel B.; Giosan, Liviu; Southon, John R.; Santos, Guaciara M.; Druffel, Ellen R.M.; Andersson, August A.; öld, Martin; et al. (Geochimica et Cosmochimica Acta, 2019)
Relatively little is known about the amount of time that lapses between the photosynthetic fixation of carbon by vascular land plants and its incorporation into the marine sedimentary record, yet the dynamics of terrestrial carbon sequestration have important implications for the carbon cycle. Vascular plant carbon may encounter multiple potential intermediate storage pools and transport trajectories, and the age of vascular plant carbon accumulating in marine sediments will reflect these different pre-depositional histories. Here, we examine down-core C-14 profiles of higher plant leaf wax-derived fatty acids isolated from high fidelity sedimentary sequences spanning the so-called "bomb-spike", and encompassing a ca. 60-degree latitudinal gradient from tropical (Cariaco Basin), temperate (Saanich Inlet), and polar (Mackenzie Delta) watersheds to constrain integrated vascular plant carbon storage/transport times ("residence times"). Using a modeling framework, we find that, in addition to a "young" (conditionally defined as < 50 y) carbon pool, an old pool of compounds comprises 49 to 78 % of the fractional contribution of organic carbon (OC) and exhibits variable ages reflective of the environmental setting. For the Mackenzie Delta sediments, we find a mean age of the old pool of 28 ky (+/- 9.4, standard deviation), indicating extensive pre-aging in permafrost soils, whereas the old pools in Saanich Inlet and Cariaco Basin sediments are younger, 7.9 (+/- 5.0) and 2.4 (+/- 0.50) to 3.2 (+/- 0.54) ky, respectively, indicating less protracted storage in terrestrial reservoirs. The "young" pool showed clear annual contributions for Saanich Inlet and Mackenzie Delta sediments (comprising 24% and 16% of this pool, respectively), likely reflecting episodic transport of OC from steep hillside slopes surrounding Saanich Inlet and annual spring flood deposition in the Mackenzie Delta, respectively. Contributions of 5-10 year old OC to the Cariaco Basin show a short delay of OC inflow, potentially related to transport time to the offshore basin. Modeling results also indicate that the Mackenzie Delta has an influx of young but decadal material (20-30 years of age), pointing to the presence of an intermediate reservoir. Overall, these results show that a significant fraction of vascular plant C undergoes pre-aging in terrestrial reservoirs prior to accumulation in deltaic and marine sediments. The age distribution, reflecting both storage and transport times, likely depends on landscape-specific factors such as local topography, hydrographic characteristics, and mean annual temperature of the catchment, all of which affect the degree of soil buildup and preservation. We show that catchment-specific carbon residence times across landscapes can vary by an order of magnitude, with important implications both for carbon cycle studies and for the interpretation of molecular terrestrial paleoclimate records preserved in sedimentary sequences.
Keywords: british-columbia; CARIACO BASIN; compound-specific radiocarbon; MACKENZIE DELTA; marine-sediments; odp leg 169s; saanich inlet; SANTA-MONICA BASIN; SOIL ORGANIC-MATTER; TROPICAL VEGETATION

Testing the Utility of Geochemical Proxies to Reconstruct Holocene Coastal Environments and Relative Sea Level: A Case Study from Hungry Bay, Bermuda - Kemp, Andrew C.; Vane, Christopher H.; Khan, Nicole S.; Ellison, Joanna C.; Engelhart, Simon E.; Horton, Benjamin P.; Nikitina, Daria; Smith, Struan R.; Rodrigues, Lisa J.; Moyer, Ryan P. (Open Quaternary, 2019)
On low-lying, tropical and sub-tropical coastlines freshwater marshes may be replaced by salt‑tolerant mangroves in response to relative sea-level rise. Pollen analysis of radiocarbon‑dated sediment cores showed that such a change occurred in Hungry Bay, Bermuda during the late Holocene. This well-established paleoenvironmental trajectory provides an opportunity to explore if geochemical proxies (bulk-sediment δ13C and Rock-Eval pyrolysis) can reconstruct known environmental changes and relative sea level. We characterized surface sediment from depositional environments in Bermuda (freshwater wetlands, saline mangroves, and wrack composed of Sargassum natans macroalgae) using geochemical measurements and demonstrate that a multi-proxy approach can objectively distinguish among these environments. However, application of these techniques to the transgressive sediment succession beneath Hungry Bay suggests that freshwater peat and mangrove peat cannot be reliably distinguished in the sedimentary record, possibly because of post‑depositional convergence of geochemical characteristics on decadal to multi‑century timescales and/or the relatively small number of modern samples analyzed. Sediment that includes substantial contributions from Sargassum is readily identified by geochemistry, but has a limited spatial extent. Radiocarbon dating indicates that beginning at –700 CE, episodic marine incursions into Hungry Bay (e.g., during storms) carried Sargassum that accumulated as wrack and thickened through repeated depositional events until ~300 CE. It took a further ~550 years for a peat‑forming mangrove community to colonize Hungry Bay, which then accumulated sediment rapidly, but likely out of equilibrium with regional relative sea-level rise.
Keywords: mangrove; radiocarbon; Rock-Eval pyrolysis; Sargassum; δ13C

The Utility of Stable and Radioisotopes in Fish Tissues as Biogeochemical Tracers of Marine Oil Spill Food Web Effects - Patterson III, William F.; Chanton, Jeffery P.; Hollander, David J.; Goddard, Ethan A.; Barnett, Beverly K.; Tarnecki, Joseph H. (Springer International Publishing, 2019)
Direct exposure to petroleum compounds was widely reported for a variety of taxa following the DWH. Evidence of exposure ranged from oiling of skin, shells, or feathers, depending on the taxa, to observation of ingested oil in small translucent, invertebrates, to biomarkers of petroleum compounds within an organism’s tissues, such as PAHs in the hepatopancreas of invertebrates or the liver of fishes, or metabolic products of PAH catabolism in the bile of various vertebrate taxa. Development of natural biogeochemical tracers to examine indirect effects, especially over long (months to years) time scales, can be much more problematic. In this chapter, we describe the utility of employing stable isotopes and radioisotopes to 1) examine whether food web effects can be inferred from shifts in stable isotope values measured in vertebrate taxa; 2) examine the assimilation and trophic transfer of petrocarbon in marine food webs; and, 3) serve as long-term biogeochemical tracers either of petrocarbon assimilation or trophic shifts that are indicative of food web effects of marine oil spills. Data and analyses are largely drawn from DWH-related studies but with broader implications to marine oil spills in general.
Keywords: Petrocarbon; radiocarbon; Reef fish; Stable isotopes

1500 years of lake sedimentation due to fire, earthquakes, floods and land clearance in the Oregon Coast Range: geomorphic sensitivity to floods during timber harvest period - Richardson, K.N.D.; Hatten, J.A.; Wheatcroft, R.A. (Earth Surface Processes and Landforms, 2018)
Sediment cores retrieved from landslide-dammed Loon Lake recorded events back to the 5th century AD in a forested, mountainous catchment, thereby providing an opportunity to compare the impacts of known recent perturbations, including floods and timber harvesting with those of an early period in the cores, floods, fires, and earthquakes. High-resolution multi-parameter (grain size, %TC, %TN, and magnetic susceptibility) data allowed the core stratigraphy to be classified as background sedimentation and events. Cs-137 and radiocarbon dating, as well as a varved record in the last 75years provided age control. Mean mass accumulation rate from 1939 to 1978AD, the time of peak timber harvest and a cool wet phase of the Pacific Decadal Oscillation, was 0.79 (0.74-0.92, 95% C.L.) g cm(-2) y(-1), significantly higher than mean rates of both the more recent contemporary period (coincident with the passing of the legislation that regulated harvesting practices in the region), 1979-2012AD, at 0.58 (0.48-0.70) and the entire early period, 0.44 (0.41-0.46). Several event deposits are coeval with independently estimated ages of eight Cascadia subduction zone earthquakes in the early period, including the 1700AD Mw 9.0 event. These deposits are predominantly formed by hyperpycnal flows, as are the known event deposits in the contemporary period. The high mass accumulation rate and greater frequency of thick event deposits during the early contemporary period point to the extraordinary role of timber harvesting in priming the landscape for subsequent sedimentary delivery during floods. Copyright (c) 2017 John Wiley & Sons, Ltd.
Keywords: erosion; GREAT EARTHQUAKES; history; NEW-ZEALAND; radiocarbon age; record; TEMPORAL PATTERNS; USA; WASHINGTON; WESTERN OREGON

Aging and Molecular Changes of Dissolved Organic Matter Between Two Deep Oceanic End-Members - Bercovici, S. K.; Koch, B. P.; Lechtenfeld, O. J.; McCallister, S. L.; Schmitt-Kopplin, P.; Hansell, D. A. (Global Biogeochemical Cycles, 2018)
The global ocean contains a massive reservoir of dissolved organic carbon (DOC), rivaling the atmosphere's pool of CO2. The most recalcitrant fractions have mean radiocarbon ages of ~4,000 years in the Atlantic to ~6,000 years in the Pacific. Knowing the radiocarbon signatures of DOC and the molecular composition of dissolved organic matter (DOM) is crucial to develop understanding of the persistence and lifetime of the DOC pool. In this research, we collected samples from the deep North Pacific in August 2013 (aboard the RV Melville) to couple the Δ14C content of solid‐phase‐extracted DOM (Δ14C‐SPE‐DOM) with its molecular composition in the ocean's oldest deep waters. We find that deep waters in this region held a mean Δ14C‐SPE‐DOM value of −554 ± 9‰ (~6,400 14C years), substantially more depleted than that in the deep Atlantic, which held a mean Δ14C‐SPE‐DOM value of −445 ± 5‰. While we find a more degraded molecular composition of DOM in the deep Pacific than the deep Atlantic, the molecular formulae within the Island of Stability (Lechtenfeld et al., 2014, https://doi.org/10.1016/j.gca.2013.11.009), are largely retained. These results imply that a fraction of deep DOM is resistant to removal and present in both the deep Atlantic and Pacific Oceans.

Asynchronous behavior of the Antarctic Ice Sheet and local glaciers during and since Termination 1, Salmon Valley, Antarctica - Jackson, Margaret S.; Hall, Brenda L.; Denton, George H. (Earth and Planetary Science Letters, 2018)
The stability of the Antarctic Ice Sheet under future warming remains an open question with broad implications for sea-level prediction and adaptation. In particular, knowledge of whether the ice sheet has the capacity for rapid drawdown or collapse, or whether it can remain stable during periods of warming, is essential for predicting its future behavior. Here we use 55 radiocarbon dates, coupled with geomorphologic mapping, to reconstruct the timing of changes in ice extent and elevation during the last ice-age termination in Salmon Valley, adjacent to McMurdo Sound in the western Ross Sea Embayment. Results indicate that a grounded ice sheet in the Ross Sea Embayment achieved its maximum elevation and extent along the headlands of Salmon Valley at ∼18,000 yr BP, during a period of increasing temperatures and accumulation over the Antarctic continent. This ice remained at or near its maximum on the headlands near the valley mouth until after ∼14,000 yr BP. Removal of grounded Ross Sea ice from Salmon Valley was complete shortly after ∼7900 yr BP, indicating that the grounding line had retreated through southern McMurdo Sound by that time. We suggest the primary driver of Ross Sea ice removal from McMurdo Sound was marine-based, either through basal melting or calving due to sea-level rise. When combined with regional data, the Salmon Valley record suggests that this sector of the Antarctic Ice Sheet did not contribute in a significant way to deglacial meltwater pulses, such as meltwater pulse 1a. In contrast to the Ross Sea ice, our work also shows that local, independent alpine glaciers in Salmon Valley have advanced through the Holocene. Land-terminating glaciers such as these elsewhere in the region show a similar pattern, and may reflect the continued influence of increased accumulation following the termination of the last ice age.
Keywords: Antarctic Ice Sheet; glacial geomorphology; ice sheet stability; Termination I

Blue marlin ( Makaira nigricans ) longevity estimates confirmed with bomb radiocarbon dating - Andrews, Allen H.; Humphreys, Robert L.; Sampaga, Jeffery D. (Canadian Journal of Fisheries and Aquatic Sciences, 2018)
The longevity of blue marlin (Makaira nigricans) remains unresolved. The use of fin spines and sagittal otoliths for age reading has led to unconfirmed longevity estimates near 20-30 years. Age validation has been elusive because large individuals are uncommonly caught, and a technique that can be applied to structures that provide estimates of age was absent. The use of otolith chemical signatures has been limited by sagittal otoliths that are very small-whole otolith mass of adult blue marlin rarely exceeds 10 mg for the largest fish. Recent advances in the detection limits of radiocarbon (14C) with accelerator mass spectrometry-coupled with recently acquired knowledge of marine bomb 14C signals spanning the tropical Pacific Ocean-have led to an opportunity to age blue marlin from small amounts of otolith material. In this study, otoliths from a recently collected 1245 lb (565 kg) female blue marlin at a measured 146-inch (371 cm) lower jaw fork length were analyzed for 14C. Estimated longevity was either 12-21 or 32-44 years on the basis of bomb 14C dating. Using multiple lines of evidence, it was determined that the young age scenario was most likely, with evidence for an age close to 20 years using a series of deductions in the bomb 14C dating method.
Keywords: Accelerator mass spectrometry; Biology; Blue marlin; Ecology; Fish measurement; FisheryLongevity; Otolith; Radiocarbon dating

Climate variability and cultural eutrophication at Walden Pond (Massachusetts, USA) during the last 1800 years - Stager, J. Curt; Wiltse, Brendan; Hubeny, J. Bradford; Yankowsky, Eric; Nardelli, David; Primack, Richard (PLOS ONE, 2018)
Recent shifts in the ecological condition of Walden Pond, MA, are of potentially wide interest due to the lake's importance as a cultural, historical, and recreational resource in addition to its scientific value as an indicator of local and global environmental change. Algal microfossils in six sediment cores document changes in hydroclimate and trophic status of the lake during the last 1800 years and extend two previous sediment core records of shorter length. Low percentages of planktonic diatoms in the longest cores (WAL-3, WAL-15) indicate shallowing and/or greater water clarity associated with a relatively arid interval during the Medieval Climate Anomaly, ca. A.D. 1150-1300, Cultural eutrophication of the lake since the A.D. 1920s caused diatoms in the genera Asterionella and Synedra to increase in relative abundance at the expense of Cyclotella, Discostella, and the chrysophyte alga Mallomonas allorgel. Percentages of Asterionella and Synedra have remained fairly stable since A.D. 2000 when a previous sediment core study was conducted, but scaled chrysophytes have become more numerous. These findings suggest that, although mitigation efforts have curtailed anthropogenic nutrient inputs to Walden Pond, the lake has not returned to the pre-impact condition described by Henry David Thoreau and may become increasingly vulnerable to further changes in water quality in a warmer and possibly wetter future.
Keywords: BOREAL LAKES; canada; CRAWFORD LAKE; DEPTH MODELS; ENVIRONMENTAL-CHANGE; ice-age; new-england; NORTH-AMERICA; NORTHEASTERN UNITED-STATES; organic-matter

The collapse of the North Song dynasty and the AD 1048–1128 Yellow River floods: Geoarchaeological evidence from northern Henan Province, China - Storozum, Michael J; Zhen, Qin; Xiaolin, Ren; Haiming, Li; Yifu, Cui; Kui, Fu; Haiwang, Liu (The Holocene, 2018)
From AD 1048 to 1128, Yellow River flooding killed over a million people, left many more homeless and destitute, and turned parts of the once fertile North China Plain into a silted-up agricultural wasteland. Brought on in part by climate change and the Northern Song dynasty’s (AD 960–1127) mismanagement of the environment, the Yellow River floods likely hastened the collapse of the Northern Song dynasty. Despite the magnitude of this flood event, no sedimentary deposits have yet been linked to these historically recorded floods. In this research paper, we provide archaeological, sedimentary, and radiocarbon evidence of the AD 1048–1128 Yellow River floods at the Dazhanglongcun, Xidacheng, and Daguxiancun sites in Neihuang County, Henan Province. Based on our data, we argue that the AD 1048–1128 Yellow River floods deposited over 5 m of alluvium on villages in the North China Plain, radically changing both the physical and political landscape of Northern Song dynasty China.
Keywords: floods; Geoarchaeology; land use; North China Plain; Song dynasty; Yellow River

Combining Conflicting Bayesian Models to Develop Paleoseismic Records: An Example from the Wasatch Fault Zone, Utah - DuRoss, Christopher B.; Bennett, Scott E. K.; Briggs, Richard W.; Personius, Stephen F.; Gold, Ryan D.; Reitman, Nadine G.; Hiscock, Adam I.; Mahan, Shannon A. (Bulletin of the Seismological Society of America, 2018)
Bayesian statistical analyses of paleoseismic data result in the probabilistic determination of earthquake times using geochronological data evaluated in the context of a stratigraphic model. However, a fundamental problem in paleoseismology is how to use the Bayesian approach to model sparse and/or conflicting geochronological datasets, such as those derived from sites exhibiting episodic sedimentary and pedogenic processes in moderate‐ to high‐energy environments (e.g., a normal‐faulted alluvial fan). Using paleoseismic data for the Corner Canyon site on the Salt Lake City segment of the Wasatch fault zone (Utah), we develop an approach by which multiple Bayesian models are combined to generate an earthquake history at a site. This approach accommodates mutually exclusive interpretations of the geochronological data and thereby limits the influence of sparse data, stratigraphically inconsistent ages, or a single, subjective model interpretation. For the Corner Canyon site, we integrate four OxCal Bayesian models to generate a chronology of six events between ∼4.8 and ∼0.5  ka. Late Holocene (post‐5 ka) mean recurrence and vertical slip‐rate estimates are ∼0.9  ky (0.7–1.0 ky; 95% confidence) and 1.1  mm/yr (0.8–1.7  mm/yr range), respectively. Although our method increases the uncertainty in the timing of individual earthquakes, it more objectively accounts for potential geochronological errors and different interpretations of stratigraphic age control. By relaxing the need to select a single age model, our approach yields more accurate earthquake‐timing results that will better facilitate evaluations of along‐fault event correlation and earthquake rupture length.

Data Constraints on Glacial Atlantic Water Mass Geometry and Properties - Oppo, Delia W.; Gebbie, Geoffrey; Huang, Kuo‐Fang; Curry, William B.; Marchitto, Thomas M.; Pietro, Kathryn R. (Paleoceanography and Paleoclimatology, 2018)
The chemical composition of benthic foraminifera from marine sediment cores provides information on how glacial subsurface water properties differed from modern, but separating the influence of changes in the origin and end‐member properties of subsurface water from changes in flows and mixing is challenging. Spatial gaps in coverage of glacial data add to the uncertainty. Here we present new data from cores collected from the Demerara Rise in the western tropical North Atlantic, including cores from the modern tropical phosphate maximum at Antarctic Intermediate Water (AAIW) depths. The results suggest lower phosphate concentration and higher carbonate saturation state within the phosphate maximum than modern despite similar carbon isotope values, consistent with less accumulation of respired nutrients and carbon, and reduced air‐sea gas exchange in source waters to the region. An inversion of new and published glacial data confirms these inferences and further suggests that lower preformed nutrients in AAIW, and partial replacement of this still relatively high‐nutrient AAIW with nutrient‐depleted, carbonate‐rich waters sourced from the region of the modern‐day northern subtropics, also contributed to the observed changes. The results suggest that glacial preformed and remineralized phosphate were lower throughout the upper Atlantic, but deep phosphate concentration was higher. The inversion, which relies on the fidelity of the paleoceanographic data, suggests that the partial replacement of North Atlantic sourced deep water by Southern Ocean Water was largely responsible for the apparent deep North Atlantic phosphate increase, rather than greater remineralization.

Decreased sedimentation efficiency of petro- and non-petro-carbon caused by a dispersant for Macondo surrogate oil in a mesocosm simulating a coastal microbial community - Xu, Chen; Zhang, Saijin; Beaver, Morgan; Wozniak, Andrew; Obeid, Wassim; Lin, Youmin; Wade, Terry L.; Schwehr, Kathleen A.; Lin, Peng; Sun, Luni; Hatcher, Patrick G.; Chin, Wei-Chun; et al. (Marine Chemistry, 2018)
Large amounts of mucous-rich oil-containing marine snow formed in surface waters adjacent to the Deepwater Horizon spill. This marine oil snow (MOS) was implicated in oil delivery to the seafloor. Whether the use of chemical dispersants increased or decreased MOS sedimentation remains controversial. We conducted mesocosm experiments testing the effects of oil and oil plus a dispersant on MOS formation and sedimentation, in coastal seawater. The four treatments used were a surrogate Macondo oil water accommodated fraction (“WAF”), two concentrations of chemically-enhanced WAF (“CEWAF” and diluted CEWAF, “DCEWAF”) containing a dispersant and oil, and Controls (no additions). Based on radiocarbon and 13C NMR results, the presence of dispersants enhanced the amounts of petro-carbon being incorporated into the sinking oil-carrying aggregates (aka MOS). However, most of the chemically-dispersed oil preferentially partitioned into the colloidal and suspended particulate fractions rather than into the rapidly forming MOS. Thus the oil and non-petro-carbon sedimentation efficiency in treatments with a dispersant was much lower, compared to those in the Control and WAF treatments, during the four-day mesocosm experiment. Formation of MOS and its subsequent sinking sequestered the oil in two stages: first via terrestrial-derived detritus containing humic compounds, and subsequently via freshly produced material, such as exopolymeric substances produced by phytoplankton and bacteria.

The demise of the largest and oldest African baobabs - Patrut, Adrian; Woodborne, Stephan; Patrut, Roxana T.; Rakosy, Laszlo; Lowy, Daniel A.; Hall, Grant; von Reden, Karl F. (Nature Plants, 2018)
The African baobab is the biggest and longest-living angiosperm tree. By using radiocarbon dating we identified the stable architectures that enable baobabs to reach large sizes and great ages. We report that 9 of the 13 oldest and 5 of the 6 largest individuals have died, or at least their oldest parts/stems have collapsed and died, over the past 12 years; the cause of the mortalities is still unclear.

Early Holocene sea level in the Canadian Beaufort Sea constrained by radiocarbon dates from a deep borehole in the Mackenzie Trough, Arctic Canada - O'Regan, Matt; Coxall, Helen; Hill, Philip; Hilton, Robert; Muschitiello, Francesco; Swärd, Henrik (Boreas, 2018)
Deglacial and Holocene relative sea level (RSL) in the Canadian Beaufort Sea was influenced by the timing and extent of glacial ice in the Mackenzie River corridor and adjacent coastal plains. Considerable evidence indicates extensive ice cover in this region of northwestern Canada during the Late Wisconsinan. However, no absolute ages exist to constrain maximum RSL lowering before the late Holocene (4.2–0 ka). In 1984, the Geological Survey of Canada drilled an 81.5‐m‐deep borehole in the western Mackenzie Trough at 45 m water depth (MTW01). The lower 52.5 m of the borehole was interpreted as a deltaic progradational sequence deposited during a period of rising sea level. The upper 29 m was described as foraminifer‐bearing marine sediments deposited after transgression of the site, when RSL rose above ~−74 m. Here, we present radiocarbon measurements from MTW01, acquired from benthic foraminifera, mollusc fragments and particulate organic carbon in the >63 μm fraction (POC>63 μm) in an attempt to constrain the chronology of sediments within this borehole and date the timing of transgression. The deepest carbonate macrofossil was acquired from 8 m above the transgressive surface (equivalent to 21 m b.s.l.), where mollusc fragments returned a date of 9400 +180–260 cal. a BP (2σ). This provides the oldest constraint on Holocene sea‐level lowering in the region, and implies that transgression at this site occurred prior to the early Holocene. Ages obtained from the lower 52.5 m of the borehole are limited to POC>63 μm samples. These indicate that progradational sediments were deposited rapidly after 24 820 +390–380 cal. a BP (2σ). Due to the incorporation of older reworked organic matter, the actual age of progradation is likely to be younger, occurring after Late Wisconsinan glacial ice retreated from the coast.

Ecological history of a long-lived conifer in a disjunct population - Herring, Erin M.; Gavin, Daniel G.; Dobrowski, Solomon Z.; Fernandez, Matias; Hu, Feng Sheng (Journal of Ecology, 2018)
In northern Idaho (USA), more than 100 vascular plant species are disjunct >160 km from their main distribution along the Pacific Northwest coast. It remains unclear whether most species within this interior forest disjunction, including Tsuga mertensiana, survived the last glacial period in a north‐Idaho refugium or whether these species colonized the region via long‐distance dispersal during the Holocene. Sediment cores were extracted from three mid‐ to high‐elevation lakes within T. mertensiana‐dominated forests in the Northern Rocky Mountains of Idaho. Pollen and macrofossils were used to reconstruct forest composition, determine the timing of T. mertensiana establishment, examine the hypothesis that the region was a glacial refugium, and contrast how climate, competition and/or dispersal limitation have influenced its modern distribution. The modern distribution of T. mertensiana was analysed by constructing a range map and modelling the potential species distribution. The presence of outlier populations surrounding the Idaho disjunction along with broad areas of unoccupied suitable habitat indicates that the range of T. mertensiana is currently expanding. To assess the accuracy of T. mertensiana pollen at detecting its range limit, a network of pollen surface samples was used to analyse the probability of detecting T. mertensiana pollen as a function of distance from its geographical range limit. Consistent T. mertensiana pollen occurrence at ≥1% abundance is likely only within 42 km of its range limit. Tsuga mertensiana first appears in the pollen and macrofossil record at the highest‐elevation site at c. 4,100 cal year bp, then at the next highest‐elevation site at c. 1,600 cal year bp, and last at the mid‐elevation site at 800 cal year bp. Tsuga mertensiana pollen occurs continuously at ≥1% at all three sites by c. 300 cal year bp suggesting regional presence. The timing of arrival suggests that T. mertensiana is a recent component of the forests of Idaho, having arrived during the Holocene via long‐distance dispersal from coastal populations over 160 km away. Synthesis. Comparison with palaeoclimate reconstructions from the broader region suggests that climate was a greater limiting factor than dispersal in the Holocene establishment in the interior, indicating little difficulty overcoming a large dispersal barrier. However, T. mertensiana remained at low abundances for millennia until Little Ice Age climates promoted its recent increase in abundance. Unoccupied areas of suitable habitat suggest that competition, rather than climate or dispersal, is a limiting range infilling in the interior mesic forests today.
Keywords: climate; disjunction; dispersal; Holocene; Idaho; mertensiana; Palaeoecology; pollen; refugia; Tsuga

The Ephemeral Signature of Permafrost Carbon in an Arctic Fluvial Network - Drake, Travis W.; Guillemette, François; Hemingway, Jordon D.; Chanton, Jeffery P.; Podgorski, David C.; Zimov, Nikita S.; Spencer, Robert G. M. (Journal of Geophysical Research: Biogeosciences, 2018)
Arctic fluvial networks process, outgas, and transport significant quantities of terrestrial organic carbon (C), particularly dissolved organic carbon (DOC). The proportion of permafrost C in these fluxes, however, is poorly constrained. A primary obstacle to the quantification of permafrost‐derived DOC is that it is rapidly respired without leaving a unique tracer of its presence. In this study, we investigated the production of bacterial respiratory carbon dioxide (CO2; measured as dissolved inorganic carbon; DIC) during maximum late‐summer thaw in sites spanning a fluvial network (Kolyma Basin, Siberia) to assess whether the biodegradation of permafrost DOC could be detected by the presence of a persistent aged (14C‐depleted) signature on the DIC pool. Using Keeling plot interpretation of DIC produced in bioincubations of river water, we show that bacteria respire varying sources of DOC moving downstream through the fluvial network. Respiration of permafrost (production of aged CO2) was only detected in heavily permafrost thaw influenced sites. In nonpermafrost thaw impacted sites, ambient DIC was modern (14C‐enriched), but rather than precluding the respiration of permafrost OC upstream, we suggest that 14C‐depleted DIC is overwhelmed by modern DIC. Investigation of dissolved organic matter composition via Fourier transform ion cyclotron resonance mass spectrometry highlighted that elevated levels of aliphatic and nitrogen‐containing compounds were associated with the production of aged DIC, providing molecular‐level insight as to why permafrost‐derived dissolved organic matter is rapidly respired. Overall, results from this study demonstrate the difficulty of tracing inputs of a highly reactive substrate to systems with diverse organic matter sources.

Evidence for Stable Holocene Basin‐Scale Overturning Circulation Despite Variable Currents Along the Deep Western Boundary of the North Atlantic Ocean - Hoffmann, Sharon S.; McManus, Jerry F.; Swank, Emerson (Geophysical Research Letters, 2018)
While substantial changes in thermohaline circulation related to deglacial climate variability are well established, the role of this circulation in Holocene climate variability remains uncertain. Here we use two dynamical proxies, 231Pa/230Th ratios and mean sortable silt size ( urn:x-wiley:00948276:media:grl58406:grl58406-math-0001), to reconstruct Holocene bottom water circulation at the intermediate‐depth Carolina Slope. We find no substantial change in deep current speed or 231Pa export at this site during the Holocene, suggesting consistent 231Pa export via the Deep Western Boundary Current. urn:x-wiley:00948276:media:grl58406:grl58406-math-0002 shows increasing millennial‐scale variability in the middle‐late Holocene, which may reflect Labrador Sea Water contribution to current speed. We conclude that deepwater export from the North Atlantic has remained remarkably stable during the Holocene, decoupled from changing rates of specific water masses, while production of these water masses varied at millennial to centennial time scales. The persistence of the large‐scale overturning may reflect the ocean's stabilizing influence on Holocene climate.
Keywords: chemical tracers; interglacial; Radioactivity and radioisotopes; sedimentation (1861); thermohaline

Five Younger Dryas black mats in Mexico and their stratigraphic and paleoenvironmental context - Israde-Alcántara, Isabel; Domínguez-Vázquez, G.; Gonzalez, S.; Bischoff, J.; West, A.; Huddart, D. (Journal of Paleolimnology, 2018)
The Younger Dryas interval (YD) was a period of widespread, abrupt climate change that occurred between 12,900 and 11,700 cal yr BP (10,900–10,000 14C BP). Many sites in the Northern Hemisphere preserve a sedimentary record across the onset of the YD interval, including sites investigated in sedimentary basins located in central Mexico (Chapala, Cuitzeo, Acambay), the Basin of Mexico (Tocuila), and northern Mexico (El Cedral). Deposits consist of lacustrine or marginal lake sediments that were deposited during the Pleistocene and the Holocene. At the Tocuila and Acambay sites, Pleistocene fossil vertebrate assemblages, mainly mammoths (Mammuthus columbi), are found in association with a distinctive organic layer, sometimes called the black mat that formed during the YD. At the Chapala, Cuitzeo, Acambay, and Tocuila sites the black mats contain a suite of distinctive microscopic and mineralogical signatures and are accompanied by a sharp change in the depositional environments as supported by diatom and pollen studies reported here. The signatures include magnetic, Fe-rich microspherules, silica melted droplets with aerodynamic shapes (tektites), large amounts of charcoal, and sometimes nanodiamonds (Cuitzeo), all of which were deposited at the onset of the YD. The geochemistry of the microspherules indicates that they are not anthropogenic, authigenic or of cosmic or volcanic origin, and instead, were produced by melting and quenching of terrestrial sediments. Here, we present the stratigraphy at five field sites, the analyses of magnetic microspherules, including major element composition and scanning electron microscopy images. All of these materials are associated with charcoal and soot, which are distinctive stratigraphic markers for the YD layer at several sites in Mexico.

Holocene history of the Greenland Ice-Sheet margin in Northern Nunatarssuaq, Northwest Greenland - Farnsworth, Lauren B.; Kelly, Meredith A.; Bromley, Gordon R. M.; Axford, Yarrow; Osterberg, Erich C.; Howley, Jennifer A.; Jackson, Margaret S.; Zimmerman, Susan R. (arktos, 2018)
Records of past Greenland Ice-Sheet (GrIS) extents are important for understanding the response of the ice sheet to climate conditions, providing a longer term perspective on present ice-margin fluctuations, and evaluating ice-sheet models. We present a record of Holocene GrIS extents in Nunatarssuaq, Northwest Greenland, based on geomorphic mapping combined with 10Be surface exposure dating of rock surfaces and 14C dating of subfossil plants. 10Be ages of boulders and bedrock exposed during deglaciation from the Last Glacial Maximum range from ~ 81 to 15 ka. The apparently old ages of some samples and scatter in the dataset indicate the presence of 10Be inherited from prior periods of exposure and suggest that overriding ice was minimally erosive. Subfossil plants exposed on a debris band in the GrIS margin date to ~ 4.7 cal ka BP and register a time when the Northwest GrIS was smaller than at present. Geomorphic evidence, including a drift sheet, grounding-line moraines, and higher levels of Nordsø, document an advance of the Nuna and Tunge Rampen (GrIS outlet glaciers). 14C ages of in situ subfossil plants and 10Be ages of boulders bracket this advance to ~ 3.2–2.1 ka, a period of regional cooling. Unweathered, lichen-free drift occurs < 50 m beyond the present GrIS margin in most locations. 10Be ages of this drift are 2.2–0.5 ka and likely contain inherited nuclides. 14C ages of in situ subfossil plants atop this drift are between cal AD ~ 1640 and 2001, suggesting recent ice-margin fluctuations.

How Could a Freshwater Swamp Produce a Chemical Signature Characteristic of a Saltmarsh?How Could a Freshwater Swamp Produce a Chemical Signature Characteristic of a Saltmarsh? - McCloskey, Terrence A.; Smith, Christopher G.; Liu, Kam-biu; Marot, Marci; Haller, Christian (ACS Earth and Space Chemistry, 2018)
Reduction–oxidation (redox) reaction conditions, which are of great importance for the soil chemistry of coastal marshes, can be temporally dynamic. We present a transect of cores from northwest Florida wherein radical postdepositional changes in the redox regime has created atypical geochemical profiles at the bottom of the sedimentary column. The stratigraphy is consistent along the transect, consisting of, from the bottom upward, carbonate bedrock, a gray clay, an organic mud section, a dense clay layer, and an upper organic mud unit representing the current saltwater marsh. However, the geochemical signature of the lower organic mud unit suggests pervasive redox reactions, although the interval has been identified as representing a freshwater marsh, an unlikely environment for such conditions. Analyses indicate that this discrepancy results from postdepositional diagenesis driven by millennial-scale environmental parameters. Rising sea level that led to the deposition of the capping clay layer, created anaerobic conditions in the freshwater swamp interval, and isolated it hydrologically from the rest of the sediment column. The subsequent infiltration of marine water into this organic material led to sulfate reduction, the buildup of H2S and FeS, and anoxic conditions. Continued sulfidation eventually resulted in euxinic conditions, as evidenced by elevated levels of Fe, S, and especially Mo, the diagnostic marker of euxinia. Because this chemical transformation occurred long after the original deposition the geochemical signature does not reflect soil chemistry at the time of deposition and cannot be used to infer syn-depositional environmental conditions, emphasizing the importance of recognizing diagenetic processes in paleoenvironmental studies.
Keywords: anoxic; diagenesis; euxinic; florida; Molybdenum; reactions; redox; XRF

An Investigation of Gas Exchange and Water Circulation in the Amundsen Sea Based On Dissolved Inorganic Radiocarbon - Kim, Bumsoo; Lee, SangHoon; Kim, Minkyoung; Hahm, Doshik; Rhee, Tae Siek; Hwang, Jeomshik (Geophysical Research Letters, 2018)
We used radiocarbon isotope ratios in dissolved inorganic carbon to assess gas exchange and water circulation in the western Amundsen Sea. Radiocarbon isotope ratios indicate that Circumpolar Deep Water enters the basin along the seafloor and that the upper layer is formed through modification of this water mass. In the Amundsen Sea Polynya, radiocarbon isotope ratios of surface water are higher than those of underlying Winter Water, implying rapid absorption of atmospheric CO2. A CO2 absorption rate of 45mmol m(-2) d(-1) calculated for a site in the central polynya is higher than that near the Dotson Ice Shelf (28mmolm(-2) d(-1)). The turnover time of water in the Dotson Trough region of the western Amundsen Sea is estimated to be 10-30years, based on results from a box model and radiocarbon mass balance. Plain Language Summary The western Amundsen Sea is experiencing raid physical changes including rapid glacial melting and declining sea ice cover. The suggested heat source is the intrusion of warm Circumpolar Deep Water (CDW) along the seafloor of the Amundsen Shelf. Therefore, understanding the behavior of the intruded CDW, especially how long it stays on the shelf, is important. Physical oceanographic studies have examined the flux of CDW onto and out of the Amundsen Shelf. However, the turnover time of water in the Amundsen Sea is still poorly understood. In this paper, we use radiocarbon isotope signature from dissolved inorganic carbon to examine how rapidly atmospheric CO2 is absorbed into the Amundsen Sea Polynya and how long the water should stay in the western Amundsen Shelf to have the observed radiocarbon isotope signature. Based on our results and the current understanding of the water circulation in the western Amundsen Sea, we found that the water sits on the Amundsen Shelf for a few decades before it moves off shelf.
Keywords: Amundsen sea; dissolved inorganic carbon; gas exchange; radiocarbon; water circulation

Linear decline in red snapper (Lutjanus campechanus) otolith Δ14C extends the utility of the bomb radiocarbon chronometer for fish age validation in the Northern Gulf of Mexico - Barnett, Beverly K; Thornton, Laura; Allman, Robert; Chanton, Jeffrey P; Patterson, William F (ICES Journal of Marine Science, 2018)
Radiocarbon (D14C) was analyzed in northern Gulf of Mexico (nGOM) red snapper (Lutjanus campechanus) otolith cores (n¼23), otolith edge samples (n¼12), and whole age-0 otoliths (n¼9), with edge samples and whole age-0 otoliths constituting known-age samples. There was no significant difference in the linear relationship of D14C versus year of formation between regional corals and known-age otolith samples, and a linear regression fit to the combined data from 1980 to 2015 extends the utility of the bomb radiocarbon chronometer for age validation. The entire regional coral and known-age otolith data set (1940 to 2015) was then utilized as a reference series to validate otolith-derived red snapper age estimates for cored otolith samples. A loess regression was fit to the reference data and then the sum of squared residuals (SSR) was computed from predicted versus observed birth years for cored adult otolith samples. This process was then repeated for ages biased 61–4 years. Ages with no bias applied had the lowest SSR, thus validating red snapper age estimates and demonstrating the utility of the combined regional coral and known-age red snapper otolith D14C time series for age validation of nGOM marine fishes.
Keywords: Age validation; otoliths; radiocarbon; red snapper

Maar sediment in central Vietnam Highland near Pleiku: An archive of regional monsoon intensity? - Schimmelmann, A., H.; Nguyễn-Văn, D.; Nguyễn-Thùy, J.P.; Schimmelmann, A.E.K.; Ojala, N.; Nguyễn-Ánh, Q.; Trọng Đỗ, D.; Thùy Nguyễn, P.; Hòa Tạ, V.; Huỳnh-Kim, N.; Quỳnh Phạm-Nữ, B.; Zolitschka, I. (2018)
Keywords: flood layer; land use; monsoon

Microbial decomposition of marine dissolved organic matter in cool oceanic crust - Shah Walter, Sunita R.; Jaekel, Ulrike; Osterholz, Helena; Fisher, Andrew T.; Huber, Julie A.; Pearson, Ann; Dittmar, Thorsten; Girguis, Peter R. (Nature Geoscience, 2018)
Marine dissolved organic carbon (DOC) is one of the largest active reservoirs of reduced carbon on Earth. In the deep ocean, DOC has been described as biologically recalcitrant and has a radiocarbon age of 4,000 to 6,000 years, which far exceeds the timescale of ocean overturning. However, abiotic removal mechanisms cannot account for the full magnitude of deep-ocean DOC loss. Deep-ocean water circulates at low temperatures through volcanic crust on ridge flanks, but little is known about the associated biogeochemical processes and carbon cycling. Here we present analyses of DOC in fluids from two borehole observatories installed in crustal rocks west of the Mid-Atlantic Ridge, and show that deep-ocean DOC is removed from these cool circulating fluids. The removal mechanism is isotopically selective and causes a shift in specific features of molecular composition, consistent with microbe-mediated oxidation. We suggest organic molecules with an average radiocarbon age of 3,200 years are bioavailable to crustal microbes, and that this removal mechanism may account for at least 5% of the global loss of DOC in the deep ocean. Cool crustal circulation probably contributes to maintaining the deep ocean as a reservoir of 'aged' and refractory DOC by discharging the surviving organic carbon constituents that are molecularly degraded and depleted in C-14 and C-13 into the deep ocean.
Keywords: carbon; community; deep-ocean; DISTINCT; extraction; fluid-flow; HEAT; MID-ATLANTIC RIDGE; SEAWATER; WESTERN FLANK

Microbial oxidation of lithospheric organic carbon in rapidly eroding tropical mountain soils - Hemingway, Jordon D.; Hilton, Robert G.; Hovius, Niels; Eglinton, Timothy I.; Haghipour, Negar; Wacker, Lukas; Chen, Meng-Chiang; Galy, Valier V. (Science, 2018)
Lithospheric organic carbon (“petrogenic”; OCpetro) is oxidized during exhumation and subsequent erosion of mountain ranges. This process is a considerable source of carbon dioxide (CO2) to the atmosphere over geologic time scales, but the mechanisms that govern oxidation rates in mountain landscapes are poorly constrained. We demonstrate that, on average, 67 ± 11% of the OCpetro initially present in bedrock exhumed from the tropical, rapidly eroding Central Range of Taiwan is oxidized in soils, leading to CO2 emissions of 6.1 to 18.6 metric tons of carbon per square kilometer per year. The molecular and isotopic evolution of bulk OC and lipid biomarkers during soil formation reveals that OCpetro remineralization is microbially mediated. Rapid oxidation in mountain soils drives CO2 emission fluxes that increase with erosion rate, thereby counteracting CO2 drawdown by silicate weathering and biospheric OC burial.

Millennial-scale variations in dustiness recorded in Mid-Atlantic sediments from 0 to 70 ka - Middleton, Jennifer L.; Mukhopadhyay, Sujoy; Langmuir, Charles H.; McManus, Jerry F.; Huybers, Peter J. (Earth and Planetary Science Letters, 2018)
Sedimentary records of dust deposition in the subtropical Atlantic provide important constraints on millennial- and orbital-scale variability in atmospheric circulation and North African aridity. Constant flux proxies, such as extraterrestrial helium-3, yield dust flux records that are independent of the biases caused by lateral sediment transport and limited resolution that may be associated with age-model-derived mass accumulation rates. However, Atlantic dust records constrained using constant flux proxies are sparsely distributed and generally limited to the past 20 ka. Here we extend the Atlantic record of North African dust deposition to 70 ka using extraterrestrial helium-3 and measurements of titanium, thorium, and terrigenous helium-4 in two sediment cores collected at 26°N and 29°N on the Mid-Atlantic Ridge and compare results to model estimates for dust deposition in the subtropical North Atlantic. Dust proxy fluxes between 26°N and 29°N are well correlated, despite variability in lateral sediment transport, and underscore the utility of extraterrestrial helium-3 for constraining millennial-scale variability in dust deposition. Similarities between Mid-Atlantic dust flux trends and those observed along the Northwest African margin corroborate previous interpretations of dust flux variability over the past 20 ka and suggest that long distance transport and depositional processes do not overly obscure the signal of North African dust emissions. The 70 ka Mid-Atlantic record reveals a slight increase in North African dustiness from Marine Isotope Stage 4 through the Last Glacial Maximum and a dramatic decrease in dustiness associated with the African Humid Period. On the millennial-scale, the new records exhibit brief dust maxima coincident with North Atlantic cold periods such as the Younger Dryas, and multiple Heinrich Stadials. The correlation between Mid-Atlantic dust fluxes and previous constraints on North African aridity is high. However, precipitation exerts less control on dust flux variability prior to the African Humid Period, when wind variability governs dust emissions from consistently dry dust source regions. Thus, the Mid-Atlantic dust record supports the hypothesis that both aridity and wind strength drive dust flux variability across changing climatic conditions.
Keywords: helium-3; mass accumulation rate; mineral dust; North Africa; Subtropical North Atlantic; thorium-232

Organic Carbon Aging During Across‐Shelf Transport - Bao, Rui; Uchida, Masao; Zhao, Meixun; Haghipour, Negar; Montlucon, Daniel; McNichol, Ann; Wacker, Lukas; Hayes, John M.; Eglinton, Timothy I. (Geophysical Research Letters, 2018)
Compound-specific radiocarbon analysis (CSRA) was performed on different grain-size fractions of surficial sediments to examine and compare lateral transport times (LTTs) of organic carbon. 14C aging of long-chain leaf wax fatty acids along two dispersal pathways of fluvially-derived material on adjacent continental margins implies LTTs over distances of ~30 to 500 km that range from hundreds to thousands of years. The magnitude of aging differs among grain size fractions. Our finding suggests that LTTs vary both temporally and spatially as a function of the specific properties of different continental shelf settings. Observations suggest that 14C aging is widespread during lateral transport over continental shelves, with hydrodynamic particle sorting inducing age variations among organic components residing in different grain sizes. Consideration of these phenomena is of importance for understanding carbon cycle processes and interpretation on sedimentary records on continental margins.

Paleomagnetism and rock magnetism from sediments along a continental shelf-to-slope transect in the NW Barents Sea: Implications for geomagnetic and depositional changes during the past 15 thousand years - Caricchi, C.; Lucchi, R.G.; Sagnotti, L.; MacrÌ, P.; Morigi, C.; Melis, R.; Caffau, M.; Rebesco, M.; Hanebuth, T.J.J. (Global and Planetary Change, 2018)
Paleomagnetic and rock magnetic data were measured on glaciomarine silty-clay successions along an E-W sediment-core transect across the continental shelf and slope of the Kveithola paleo-ice stream system (south of Svalbard, north-western Barents Sea), representing a stratigraphic interval spanning the last deglaciation and the Holocene. The records indicate that magnetite is the main magnetic mineral and that magnetic minerals are distinctly less abundant on the shelf than at the continental slope. The paleomagnetic properties allow for the reconstruction of a well-defined characteristic remanent magnetization (ChRM) throughout the sedimentary successions. The stratigraphic trends of rock magnetic and paleomagnetic parameters are used for a shelf-slope core correlation and sediment facies analysis is applied for depositional processes reconstruction. The new paleomagnetic records compare to the PSV and RPI variation predicted for the core sites by a simulation using the global geomagnetic field variation models SHA.DIF.14k and CALS7K.2 and closest PSV and RPI regional stack curves. The elaborated dataset, corroborated by available 14C ages, provides a fundamental chronological framework to constrain the coupling of shelf-slope sedimentary processes and environmental changes in the NW Barents Sea region during and after deglaciation.
Keywords: Barents Sea; Kveithola glacial trough; Paleomagnetism; Rock magnetism

Paleoseismic Results from the Alpine Site, Wasatch Fault Zone: Timing and Displacement Data for Six Holocene Earthquakes at the Salt Lake City–Provo Segment Boundary - Bennett, S. E. K.; DuRoss, C. B.; Gold, R. D.; Briggs, R. W.; Personius, S. F.; Reitman, N. G.; Devore, J. R.; Hiscock, A. I.; Mahan, S. A.; Gray, H. J.; Gunnarson, S.; Stephenson, W. J.; et al. (Bulletin of the Seismological Society of America, 2018)
To improve the characterization of Holocene earthquakes on the Wasatch fault zone (WFZ), we conducted light detection and ranging (lidar)‐based neotectonic mapping and excavated a paleoseismic trench across an 8‐m‐high fault scarp near Alpine, Utah, located <1  km south of the boundary between the Salt Lake City and Provo segments (SLCS and PS). We document evidence for six paleoearthquakes (AL6–AL1) from scarp‐derived colluvial wedges and crosscutting relations. A ground‐penetrating radar survey across the scarp resolved fault‐zone width, but not paleoearthquake stratigraphy. Bayesian (OxCal) modeling of 13 radiocarbon and 13 optically stimulated luminescence ages indicates that six earthquakes occurred ∼6.2–0.4  ka. Interseismic recurrence ranges from 0.2 to 1.8 ky (mean 1.2 ky). We estimate 6.5±0.7  m of cumulative vertical tectonic displacement across the ≥14‐m‐wide fault zone used near‐field observations of scarp‐derived colluvial‐wedge thicknesses, antithetic faulting, and graben backtilting. This is similar to our independent estimate of 6.5±0.5  m using far‐field observations of the offset ground surface and correlation of alluvial‐fan stratigraphy across the WFZ. These results suggest that colluvial‐wedge thickness at the Alpine site approximates one‐half the original west‐facing fault scarp height. Per‐event vertical displacements range from 0.8 to 1.2 m (mean 1.1 m), which we use to estimate surface rupture lengths that may exceed 50 km from earthquakes as large as moment magnitude (Mw) ∼7.0. The late Holocene average vertical slip rate is 0.9  mm/yr (0.7–1.2  mm/yr range). Earthquake frequency has increased in the past ∼1  ky, whereas displacement per event has been similar for the past ∼6  ky, suggesting that strain accumulation is not the sole factor that controls the frequency and size of earthquakes at the SLCS–PS segment boundary. These findings can be used for a more nuanced characterization of earthquakes at the SLCS–PS boundary and improve earthquake hazard assessments along the Wasatch Front.

Radiocarbon Content of Dissolved Organic Carbon in the South Indian Ocean - Bercovici, S. K.; McNichol, A. P.; Xu, L.; Hansell, D. A. (Geophysical Research Letters, 2018)
We report four profiles of the radiocarbon content of dissolved organic carbon (DOC) spanning the South Indian Ocean (SIO), ranging from the Polar Front (56°S) to the subtropics (29°S). Surface waters held mean DOC Δ14C values of −426 ± 6‰ (~4,400 14C years) at the Polar Front and DOC Δ14C values of −252 ± 22‰ (~2,000 14C years) in the subtropics. At depth, Circumpolar Deep Waters held DOC Δ14C values of −491 ± 13‰ (~5,400 years), while values in Indian Deep Water were more depleted, holding DOC Δ14C values of −503 ± 8‰ (~5,600 14C years). High‐salinity North Atlantic Deep Water intruding into the deep SIO had a distinctly less depleted DOC Δ14C value of −481 ± 8‰ (~5,100 14C years). We use multiple linear regression to assess the dynamics of DOC Δ14C values in the deep Indian Ocean, finding that their distribution is characteristic of water masses in that region.
Keywords: dissolved organic carbon; indian ocean; radiocarbon

Rapid precipitation changes in the tropical West Pacific linked to North Atlantic climate forcing during the last deglaciation - Xiong, Zhifang; Li, Tiegang; Chang, Fengming; Algeo, Thomas J.; Clift, Peter D.; Bretschneider, Lisa; Lu, Zhengyao; Zhu, Xiao; Frank, Martin; Sauer, Peter E.; Jiang, FuQing; Wan, Shiming; et al. (Quaternary Science Reviews, 2018)
The cause of rapid hydrological changes in the tropical West Pacific during the last deglaciation remains controversial. In order to test whether these changes were triggered by abrupt climate change events in the North Atlantic Ocean, variations in precipitation during the last deglaciation (18-10 ka) were extracted from proxy records of chemical weathering and terrigenous input in the western Philippine Sea (WPS). The evolution of chemical weathering and terrigenous input since 27 ka was reconstructed using the chemical index of alteration (CIA), elemental ratios (K/Al, TOC/TN and Ti/Ca), δ13Corg, terrigenous fraction abundance and flux data from International Marine Global Change Study Program (IMAGES) core MD06-3054 collected on the upper continental slope of eastern Luzon (northern Philippines). Sediment deposited during the Last Glacial Maximum (LGM) shows weathering equal to or slightly greater than Holocene sediment in the WPS. This unusual state of chemical weathering, which is inconsistent with lower air temperatures and decreased precipitation in Luzon during the LGM, may be due to reworking of poorly consolidated sediments on the eastern Luzon continental shelf during the LGM sea-level lowstand. Rapid changes in chemical weathering, characterized by higher intensity during the Heinrich event 1 (H1) and Younger Dryas (YD) and lower intensity during the Bølling-Allerød (B/A), were linked to rapid variations in precipitation in the WPS during the last deglaciation. The higher terrigenous inputs during the LGM relative to those of the Holocene were controlled by sea-level changes rather than precipitation. The terrigenous inputs show a long-term decline during the last deglaciation, punctuated by brief spikes during the H1 and YD related to sea-level rises and rapid precipitation changes in the WPS, respectively. The proxy records of chemical weathering and terrigenous input from eastern Luzon suggest high rainfall during the H1 and YD events, consistent with inferred rainfall patterns based on Fe/Ca records from offshore Mindanao. Rapid precipitation changes in the WPS did not coincide with migrations of the Intertropical Convergence Zone (ITCZ) but, rather, were related to state shifts of the El Niño-Southern Oscillation (ENSO) during the last deglaciation. Based on proxy records and modeling results, we argue that the Atlantic meridional overturning circulation (AMOC) controlled rapid precipitation changes in the tropical West Pacific through zonal shifts of ENSO or meridional migration of the ITCZ during the last deglaciation. Our findings highlight the dominant role of the North Atlantic Ocean in the tropical hydrologic cycle during the last deglaciation.
Keywords: AMOC; Chemical weathering; enso; ITCZ; Terrigenous input; Western Philippine Sea

Relative sea-level change in Newfoundland, Canada during the past ∼3000 years - Kemp, Andrew C.; Wright, Alexander J.; Edwards, Robin J.; Barnett, Robert L.; Brain, Matthew J.; Kopp, Robert E.; Cahill, Niamh; Horton, Benjamin P.; Charman, Dan J.; Hawkes, Andrea D.; Hill, Troy D.; van de Plassche, Orson (Quaternary Science Reviews, 2018)
Several processes contributing to coastal relative sea-level (RSL) change in the North Atlantic Ocean are observed and/or predicted to have distinctive spatial expressions that vary by latitude. To expand the latitudinal range of RSL records spanning the past ∼3000 years and the likelihood of recognizing the characteristic fingerprints of these processes, we reconstructed RSL at two sites (Big River and Placentia) in Newfoundland from salt-marsh sediment. Bayesian transfer functions established the height of former sea level from preserved assemblages of foraminifera and testate amoebae. Age-depth models constrained by radiocarbon dates and chronohorizons estimated the timing of sediment deposition. During the past ∼3000 years, RSL rose by ∼3.0 m at Big River and by ∼1.5 m at Placentia. A locally calibrated geotechnical model showed that post-depositional lowering through sediment compaction was minimal. To isolate and quantify contributions to RSL from global, regional linear, regional non-linear, and local-scale processes, we decomposed the new reconstructions (and those in an expanded, global database) using a spatio-temporal statistical model. The global component confirms that 20th century sea-level rise occurred at the fastest, century-scale rate in over 3000 years (P > 0.999). Distinguishing the contributions from local and regional non-linear processes is made challenging by a sparse network of reconstructions. However, only a small contribution from local-scale processes is necessary to reconcile RSL reconstructions and modeled RSL trends. We identified three latitudinally-organized groups of sites that share coherent regional non-linear trends and indicate that dynamic redistribution of ocean mass by currents and/or winds was likely an important driver of sea-level change in the North Atlantic Ocean during the past ∼3000 years.

The role of sediment compaction and groundwater withdrawal in local sea-level rise, Sandy Hook, New Jersey, USA - Johnson, Christopher S.; Miller, Kenneth G.; Browning, James V.; Kopp, Robert E.; Khan, Nicole S.; Fan, Ying; Stanford, Scott D.; Horton, Benjamin P. (Quaternary Science Reviews, 2018)
The rate of relative sea-level (RSL) rise at Sandy Hook, NJ (4.0 ± 0.5 mm/yr) was higher than The Battery, NY (3.0 ± 0.3 mm/yr) from 1900 to 2012 despite being separated by just 26 km. The difference cannot be explained by differential glacial isostatic adjustment (GIA; 1.4 ± 0.4 and 1.3 ± 0.4 mm/yr RSL rise, respectively) alone. We estimate the contribution of sediment compaction to subsidence at Sandy Hook using high-resolution grain size, percent organic matter, and porosity data from three upper Quaternary (≤13,350 cal yr) cores. The organic matter content (<2%) is too low to contribute to local subsidence. However, numerical modeling of the grain size-depth-age-porosity relationship indicates that compaction of deglacial silts likely reduced the column thickness by 10–20% over the past 13,350 cal yrs. While compaction rates were high immediately after the main silt deposition (13,350–13,150 cal yrs BP), rates decreased exponentially after deposition to an average 20th century rate of 0.16 mm/yr (90% Confidence Interval (C.I.), 0.06–0.32 mm/yr). The remaining ∼0.7 mm/yr (90% C.I. 0.3–1.2 mm/yr) difference in subsidence between Sandy Hook and The Battery is likely due to anthropogenic groundwater withdrawal. Historical data from Fort Hancock wells (2 km to the southeast of the Sandy Hook tide gauge) and previous regional work show that local and regional water extraction lowered the water levels in the aquifers underlying Sandy Hook. We suggest that the modern order of contribution to subsidence (highest to lowest) appears to be GIA, local/regional groundwater extraction, and compaction of thick Quaternary silts.
Keywords: Marginal marine; North America; numerical modeling; Quaternary; Sea-level change; sedimentology

Tectonically-triggered sediment and carbon export to the Hadal zone - Bao, Rui; Strasser, Michael; McNichol, Ann P.; Haghipour, Negar; McIntyre, Cameron; Wefer, Gerold; Eglinton, Timothy I. (Nature Communications, 2018)
Sediments in deep ocean trenches may contain crucial information on past earthquake history and constitute important sites of carbon burial. Here we present 14C data on bulk organic carbon (OC) and its thermal decomposition fractions produced by ramped pyrolysis/oxidation for a core retrieved from the >7.5 km-deep Japan Trench. High-resolution 14C measurements, coupled with distinctive thermogram characteristics of OC, reveal hemipelagic sedimentation interrupted by episodic deposition of pre-aged OC in the trench. Low δ13C values and diverse 14C ages of thermal fractions imply that the latter material originates from the adjacent margin, and the co-occurrence of pre-aged OC with intervals corresponding to known earthquake events implies tectonically triggered, gravity-flow-driven supply. We show that 14C ages of thermal fractions can yield valuable chronological constraints on sedimentary sequences. Our findings shed new light on links between tectonically driven sedimentological processes and marine carbon cycling, with implications for carbon dynamics in hadal environments.

Tracing biogeochemical subsidies from glacier runoff into Alaska's coastal marine food webs - Arimitsu, Mayumi L.; Hobson, Keith A.; Webber, D'Arcy N.; Piatt, John F.; Hood, Eran W.; Fellman, Jason B. (Global Change Biology, 2018)
Nearly half of the freshwater discharge into the Gulf of Alaska originates from landscapes draining glacier runoff, but the influence of the influx of riverine organic matter on the trophodynamics of coastal marine food webs is not well understood. We quantified the ecological impact of riverine organic matter subsidies to glacier‐marine habitats by developing a multi‐trophic level Bayesian three‐isotope mixing model. We utilized large gradients in stable (δ13C, δ15N, δ2H) and radiogenic (Δ14C) isotopes that trace riverine and marine organic matter sources as they are passed from lower to higher trophic levels in glacial‐marine habitats. We also compared isotope ratios between glacial‐marine and more oceanic habitats. Based on isotopic measurements of potential baseline sources, ambient water and tissues of marine consumers, estimates of the riverine organic matter source contribution to upper trophic‐level species including fish and seabirds ranged from 12% to 44%. Variability in resource use among similar taxa corresponded to variation in species distribution and life histories. For example, riverine organic matter assimilation by the glacier‐nesting seabirds Kittlitz's murrelet (Brachyramphus brevirostris) was greater than that of the forest‐nesting marbled murrelet (B. marmoratus). The particulate and dissolved organic carbon in glacial runoff and near surface coastal waters was aged (12100–1500 years BP 14C‐age) but dissolved inorganic carbon and biota in coastal waters were young (530 years BP 14C‐age to modern). Thus terrestrial‐derived subsidies in marine food webs were primarily composed of young organic matter sources released from glacier ecosystems and their surrounding watersheds. Stable isotope compositions also revealed a divergence in food web structure between glacial‐marine and oceanic sites. This work demonstrates linkages between terrestrial and marine ecosystems, and facilitates a greater understanding of how climate‐driven changes in freshwater runoff have the potential to alter food web dynamics within coastal marine ecosystems in Alaska.
Keywords: Bayesian isotope mixing model; glacier runoff; marine ecosystem; marine food web; δ13C; Δ14C; δ15N; δ2H

Tropical peatland carbon storage linked to global latitudinal trends in peat recalcitrance - Hodgkins, Suzanne B.; Richardson, Curtis J.; Dommain, René; Wang, Hongjun; Glaser, Paul H.; Verbeke, Brittany; Winkler, B. Rose; Cobb, Alexander R.; Rich, Virginia I.; Missilmani, Malak; Flanagan, Neal; Ho, Mengchi; et al. (Nature Communications, 2018)
Peatlands represent large terrestrial carbon banks. Given that most peat accumulates in boreal regions, where low temperatures and water saturation preserve organic matter, the existence of peat in (sub)tropical regions remains enigmatic. Here we examined peat and plant chemistry across a latitudinal transect from the Arctic to the tropics. Near-surface low-latitude peat has lower carbohydrate and greater aromatic content than near-surface high-latitude peat, creating a reduced oxidation state and resulting recalcitrance. This recalcitrance allows peat to persist in the (sub)tropics despite warm temperatures. Because we observed similar declines in carbohydrate content with depth in high-latitude peat, our data explain recent field-scale deep peat warming experiments in which catotelm (deeper) peat remained stable despite temperature increases up to 9 °C. We suggest that high-latitude deep peat reservoirs may be stabilized in the face of climate change by their ultimately lower carbohydrate and higher aromatic composition, similar to tropical peats.

Variance and Rate-of-Change as Early Warning Signals for a Critical Transition in an Aquatic Ecosystem State: A Test Case From Tasmania, Australia - Beck, Kristen K.; Fletcher, Michael-Shawn; Gadd, Patricia S.; Heijnis, Henk; Saunders, Krystyna M.; Simpson, Gavin L.; Zawadzki, Atun (Journal of Geophysical Research: Biogeosciences, 2018)
Critical transitions in ecosystem states are often sudden and unpredictable. Consequently, there is a concerted effort to identify measurable early warning signals (EWS) for these important events. Aquatic ecosystems provide an opportunity to observe critical transitions due to their high sensitivity and rapid response times. Using palaeoecological techniques, we can measure properties of time series data to determine if critical transitions are preceded by any measurable ecosystem metrics, that is, identify EWS. Using a suite of palaeoenvironmental data spanning the last 2,400 years (diatoms, pollen, geochemistry, and charcoal influx), we assess whether a critical transition in diatom community structure was preceded by measurable EWS. Lake Vera, in the temperate rain forest of western Tasmania, Australia, has a diatom community dominated by Discostella stelligera and undergoes an abrupt compositional shift at ca. 820 cal yr BP that is concomitant with increased fire disturbance of the local vegetation. This shift is manifest as a transition from less oligotrophic acidic diatom flora (Achnanthidium minutissimum, Brachysira styriaca, and Fragilaria capucina) to more oligotrophic acidic taxa (Frustulia elongatissima, Eunotia diodon, and Gomphonema multiforme). We observe a marked increase in compositional variance and rate‐of‐change prior to this critical transition, revealing these metrics are useful EWS in this system. Interestingly, vegetation remains complacent to fire disturbance until after the shift in the diatom community. Disturbance taxa invade and the vegetation system experiences an increase in both compositional variance and rate‐of‐change. These trends imply an approaching critical transition in the vegetation and the probable collapse of the local rain forest system.
Keywords: carbon and nitrogen stable isotopes; critical transitions; diatoms; early warning signals; polleen; Tasmania

3000 Years of Human Subsistence and Estuarine Resource Exploitation on the Rhode River Estuary, Chesapeake Bay, Maryland - Rick, Torben C.; Reeder-Myers, Leslie A.; Carr, Michael J.; Hines, Anson H. (Journal of the North Atlantic, 2017)
Chesapeake Bay is home to highly productive marine ecosystems that were a key part of Native American subsistence for millennia. Despite a number of archaeological projects focused on Chesapeake Bay prehistory, key questions remain about the nature of human use of the estuary through time and across space. Recent work at 7 shell middens on the Rhode River Estuary, MD, provides insight into human subsistence and estuarine res ource exploitation from ∼3200 years ago through the mid-19th century. This is an important diachronic sequence of coastal land use and subsistence for the Chesapeake and helps fill a gap in our understanding of coastal adaptations along North America's Atlantic Coast. Despite climate change, fluctuating sea levels, and the likely appearance of maize agriculture in the area ∼1000 years ago, Native American exploitation of oysters and estuarine resources remained fairly consistent across the Early to Late Woodland. These data stand in contrast to the mid-1800s assemblage, which was likely deposited by 19th-century Euro-Americans and contains overall larger oysters perhaps obtained from deeper waters that may not have been a focus of Native American harvest. When placed in the context of other regional data, our analysis illustrates the value of shell middens for helping understand human subsistence strategies and the historical ecol ogy of the North American Atlantic Coast.

A ~6000 yr diatom record of mid- to late Holocene fluctuations in the level of Lago Wiñaymarca, Lake Titicaca (Peru/Bolivia)Abstract - Weide, D. Marie; Fritz, Sherilyn C.; Hastorf, Christine A.; Bruno, Maria C.; Baker, Paul A.; Guedron, Stephane; Salenbien, Wout (Quaternary Research, 2017)
A multidecadal-scale lake-level reconstruction for Lago Wiñaymarca, the southern basin of Lake Titicaca, has been generated from diatom species abundance data. These data suggest that ~6500 cal yr BP Lago Wiñaymarca was dry, as indicated by a sediment unconformity. At ~4400 cal yr BP, the basin began to fill, as indicated by the dominance of shallow epiphytic species. It remained somewhat saline with extensive wetlands and abundant aquatic plants until ~3800 cal yr BP, when epiphytic species were replaced by planktic saline-indifferent species, suggesting a saline shallow lake. Wiñaymarca remained a relatively shallow lake that fluctuated on a multidecadal scale until ~1250 cal yr BP, when freshwater planktic species increased, suggesting a rise in lake level with a concomitant decrease in salinity. The lake became gradually fresher, dominated by deep, freshwater species from ~850 cal yr BP. By ~80 cal yr BP, saline-tolerant species were rare, and the lake was dominated by freshwater planktic diatoms, resembling the fresh and deep lake of today. These results reveal a more dynamic and chronologically specific record of lake-level fluctuations and associated ecological conditions that provide important new data for paleoclimatologists and archaeologists, to better understand human-environmental dynamics during the mid- to late Holocene.
Keywords: diatoms; Lago Huiñaimarca; Lago Wiñaymarca; Lake level; lake titicaca; Mid-Holocene; Tropical Andes

Analysis of piston cores and high-resolution sub-bottom profiler data, Baffin Bay slope, Nunavut - Campbell, D C; Jenner, K A; Higgins, J; Piper, D J W (2017)
Preface This Open File report summarizes a set of 20 piston cores, up to 822 cm long, taken from the continental slope of Baffin Bay, Canada, in water depths between 833 and 1715 m. It provides down-core lithostratigraphy, physical properties measurements, core photography and core X-radiography, in addition to high-resolution seismic data over most core sites, selected grain size data and portable X-ray fluorescence data. Preliminary along-slope correlation between cores and AMS radiocarbon ages are also provided. Further information on these cores is available through the Expedition Database at http://ed.gdr.nrcan.gc.ca/index_e.php Acknowledgments We thank Dan Meagher, Jesse Sherwin and Meaghan MacQuarrie for assistance with core processing and core logging and Jessica Parkinson and Simon Poirier for core data compilation. Owen Brown completed grain size analyses and Linda Fan assisted with these analyses and plotted the grain size data.We also thank Kate Jarrett for assistance with core subsampling.

Assessing the Blank Carbon Contribution, Isotope Mass Balance, and Kinetic Isotope Fractionation of the Ramped Pyrolysis/Oxidation Instrument at NOSAMS - Hemingway, Jordon D; Galy, Valier V; Gagnon, Alan R; Grant, Katherine E; Rosengard, Sarah Z; Soulet, Guillaume; Zigah, Prosper K; McNichol, Ann P (Radiocarbon, 2017)
We estimate the blank carbon mass over the course of a typical Ramped PyrOx (RPO) analysis (150-1000 degrees C; 5 degrees C x min(-1)) to be (3.7 +/- 0.6) mu g C with an Fm value of 0.555 +/- 0.042 and a delta C-13 value of (-29.0 +/- 0.1)parts per thousand VPDB. Additionally, we provide equations for RPO Fm and delta C-13 blank corrections, including associated error propagation. By comparing RPO mass-weighted mean and independently measured bulk delta C-13 values for a compilation of environmental samples and standard reference materials (SRMs), we observe a small yet consistent delta C-13 depletion within the RPO instrument (mean-bulk: mu = -0.8 parts per thousand; +/- 1 sigma = 0.9 parts per thousand; n = 66). In contrast, because they are fractionation-corrected by definition, mass-weighted mean Fm values accurately match bulk measurements (mean-bulk: mu = 0.005; +/- 1 sigma = 0.014; n = 36). Lastly, we show there exists no significant intra-sample delta C-13 variability across carbonate SRM peaks, indicating minimal mass-dependent kinetic isotope fractionation during RPO analysis. These data are best explained by a difference in activation energy between C-13- and C-12-containing compounds ((13-12)Delta E) of 0.3-1.8 J x mol(-1), indicating that blank and mass-balance corrected RPO delta C-13 values accurately retain carbon source isotope signals to within 1-2 parts per thousand.
Keywords: Ramped PyrOx; blank assessment; kinetic fractionation

ASSESSING THE EFFECTS OF ANTHROPOGENIC EUTROPHICATION ON MARINE BIVALVE LIFE HISTORY IN THE NORTHERN GULF OF MEXICO - HARNIK, PAUL G.; TORSTENSON, MORGAN L.; WILLIAMS, MARIO A. (PALAIOS, 2017)
Natural and anthropogenic eutrophication can increase food supply to basal consumers in aquatic food webs. All else being equal, increased food supply is expected to relax life history trade-offs between egg size and number, resulting in a reduction in egg size over time as individuals that produce more numerous, small eggs exhibit greater fitness. We tested this hypothesis by comparing the sizes of larval shells (PI) of the marine bivalve Nuculana acuta in living and death assemblages collected from surficial seafloor sediments on the Alabama continental shelf; PI size is positively correlated with egg size and can be measured from adult shells. We found that the mean PI size of living N. acuta was approximately three microns smaller than that of the associated death assemblage and that this difference was robust to potential taphonomic biases. This life history shift occurred relatively recently as no trend exists in PI size over the past 3100 years. The live-dead disagreement that we observed is consistent with the history of anthropogenic eutrophication in the Mississippi Bight. These data provide a baseline for comparison with other regions in the Gulf of Mexico that have more sustained histories of anthropogenic eutrophication. More broadly, live-dead comparisons of molluscan life history coupled with age dating of molluscan shells can complement community-level metrics when assessing the impacts of anthropogenic eutrophication on coastal ecosystems, and offer a unique study system for investigating life history adaptation in a field context.

Biogeochemical properties of sinking particles in the southwestern part of the East Sea (Japan Sea) - Minkyoung Kim; Jeomshik Hwang; TaeKeun Rho; Tongsup Lee; Dong-Jin Kang; Kyung-Il Chang; Suyun Noh; HuiTae Joo; Jung Hyun Kwak; Chang-Keun Kang; Kyung-Ryul Kim (Journal of Marine Systems, 2017)
Abstract This study investigates the biological pump system in the East Sea (Japan Sea) by conducting an analysis of the total particle flux, biogenic material composition, and carbon isotope ratios of sinking particles. The samples were collected for one year starting from March 2011 using time-series sediment traps deployed at depths of 1040 m and 2280 m on bottom-tethered mooring at Station \{EC1\} (37.33°N, 131.45°E; 2300 m water depth) in the Ulleung Basin (UB), southwestern part of the East Sea. The temporal variation in the particulate organic carbon (POC) flux at 1000 m shows a good relationship with the primary production in the corresponding surface water. The ratio of \{POC\} flux at 1000 m to satellite-based primary production in the corresponding region in the \{UB\} was   3%, which is comparable to the values of 2 to 5% estimated from previous studies of other part of the East Sea. The lithogenic material accounted for > 17% of the sinking particles at 1000 m and for a larger fraction of 40 to 60% at 2280 m. The radiocarbon contents of the sinking \{POC\} at both trap depths imply the additional supply of aged POC, with a much greater contribution at 2280 m. Overall, the particle flux in the deep interior of the East Sea appears to be controlled by the supply of complex sources, including aeolian input, the lateral supply of resuspended sediments, and biological production in the surface water.
Keywords: East Sea (Japan Sea)

Biological and physical controls on the flux and characteristics of sinking particles on the Northwest Atlantic margin - Hwang, Jeomshik; Manganini, Steven J.; Park, JongJin; çon, Daniel B.; Toole, John M.; Eglinton, Timothy I. (Journal of Geophysical Research: Oceans, 2017)
Biogenic matter characteristics and radiocarbon contents of organic carbon (OC) were examined on sinking particle samples intercepted at three nominal depths of 1000 m, 2000 m, and 3000 m (similar to 50 m above the seafloor) during a 3 year sediment trap program on the New England slope in the Northwest Atlantic. We have sought to characterize the sources of sinking particles in the context of vertical export of biogenic particles from the overlying water column and lateral supply of resuspended sediment particles from adjacent margin sediments. High aluminum (Al) abundances and low OC radiocarbon contents indicated contributions from resuspended sediment which was greatest at 3000 m but also significant at shallower depths. The benthic source (i.e., laterally supplied resuspended sediment) of opal appears negligible based on the absence of a correlation with Al fluxes. In comparison, CaCO3 fluxes at 3000 m showed a positive correlation with Al fluxes. Benthic sources accounted for 42 similar to 63% of the sinking particle flux based on radiocarbon mass balance and the relationship between Al flux and CaCO3 flux. Episodic pulses of Al at 3000 m were significantly correlated with the near-bottom current at a nearby hydrographic mooring site, implying the importance of current variability in lateral particle transport. However, Al fluxes at 1000 m and 2000 m were coherent but differed from those at 3000 m, implying more than one mode of lateral supply of particles in the water column.

Carbon geochemistry of plankton-dominated samples in the Laptev and East Siberian shelves: contrasts in suspended particle composition - Tesi, Tommaso; Geibel, Marc C.; Pearce, Christof; Panova, Elena; Vonk, Jorien E.; Karlsson, Emma; Salvado, Joan A.; Kruså, Martin; Broder, Lisa; Humborg, Christoph; Semiletov, Igor; Gustafsson, Örjan (Ocean Science, 2017)
Recent Arctic studies suggest that sea ice decline and permafrost thawing will affect phytoplankton dynamics and stimulate heterotrophic communities. However, in what way the plankton composition will change as the warming proceeds remains elusive. Here we investigate the chemical signature of the plankton-dominated fraction of particulate organic matter (POM) collected along the Siberian Shelf. POM (> 10 µm) samples were analysed using molecular biomarkers (CuO oxidation and IP25) and dual-carbon isotopes (δ13C and Δ14C). In addition, surface water chemical properties were integrated with the POM (> 10 µm) dataset to understand the link between plankton composition and environmental conditions. δ13C and Δ14C exhibited a large variability in the POM (> 10 µm) distribution while the content of terrestrial biomarkers in the POM was negligible. In the Laptev Sea (LS), δ13C and Δ14C of POM (> 10 µm) suggested a heterotrophic environment in which dissolved organic carbon (DOC) from the Lena River was the primary source of metabolisable carbon. Within the Lena plume, terrestrial DOC probably became part of the food web via bacteria uptake and subsequently transferred to relatively other heterotrophic communities (e.g. dinoflagellates). Moving eastwards toward the sea-ice-dominated East Siberian Sea (ESS), the system became progressively more autotrophic. Comparison between δ13C of POM (> 10 µm) samples and CO2aq concentrations revealed that the carbon isotope fractionation increased moving towards the easternmost and most productive stations. In a warming scenario characterised by enhanced terrestrial DOC release (thawing permafrost) and progressive sea ice decline, heterotrophic conditions might persist in the LS while the nutrient-rich Pacific inflow will likely stimulate greater primary productivity in the ESS. The contrasting trophic conditions will result in a sharp gradient in δ13C between the LS and ESS, similar to what is documented in our semi-synoptic study.

Changes in glacial meltwater alter algal communities in lakes of Scoresby Sund, Renland, East Greenland throughout the Holocene: Abrupt reorganizations began 1000 years before present - Slemmons, Krista EH; Medford, Aaron; Hall, Brenda L; Stone, Jeffery R; McGowan, Suzanne; Lowell, Thomas; Kelly, Meredith; Saros, Jasmine E (The Holocene, 2017)
We investigated the response of lake algal communities to changes in glacial meltwater from the Renland Ice Cap (Greenland) through the Holocene to assess whether influxes always elicit consistent responses or novel responses. We measured sedimentary algal pigments in two proximal lakes, snow-fed Raven and glacier- and snow-fed Bunny Lake, and diatom community structure and turnover in Bunny Lake. Diatom data were not available in Raven Lake. We also modeled lake-level change in Bunny Lake to identify how glacial meltwater may have altered diatom habitat availability through time. Through a series of glacier advances and retreats over the Holocene, the algal response in Bunny Lake was relatively constant until approximately 1015 yr BP, after which there were major changes in sedimentary algal remains. Algal pigment concentrations sharply declined, and diatom species richness increased. Diatom community structure underwent three reorganizations. Until 1015 yr BP, assemblages were dominated by Pinnularia braunii and Aulacoseira pffaffiana. However, approximately 1015–480 yr BP, these species declined and Tabellaria flocculosa and Hannaea arcus became a significant component of the assemblage. Approximately 440 yr BP, A. pfaffiana increased along with species indicating elevated nitrogen. In contrast, the algal pigment records from nearby snow-fed Raven Lake showed different and minimal change through time. Our results suggest that changes in the magnitude and composition of meltwater in our two study lakes were unique over the last 1000 yr BP and elicited a non-linear threshold response absent during other periods of glacier advance and retreat. Deciphering the degree to which glaciers structure algal communities over time has strong implications for lakes as glaciers continue to recede.
Keywords: climate; Diatom; East Greenland; glacier; Holocene; Lake level

Coastal Research LibraryCoastline Changes of the Baltic Sea from South to EastConstraints of Radiocarbon Dating in Southeastern Baltic Lagoons: Assessing the Vital Effects - Bitinas, Albertas; žeika, Jonas; Buynevich, Ilya V.; šytė, Aldona; Molodkov, Anatoly; ė, Alma (Coastline Changes of the Baltic Sea from South to East, 2017)
During the past decades, a suite of radiocarbon (14C), infrared optically stimulated luminescence (IR-OSL), and electron spin resonance (ESR) dates were compiled on a variety of materials from the Curonian and Vistula lagoons and spits of the southeastern Baltic Sea. These dated materials generally included lagoon sediments and mollusc shells, along with samples of fossil fish remains, peat, wood, and water bicarbonates. A growing number of 14C dates (conventional and AMS) demonstrates disparities and contradictions with the associated IR-OSL dates and palaeobotanical investigations of contemporary materials. Detailed analyses of 14C, IR-OSL and ESR chronologies and experimental 14C dating of modern live molluscs and water bicarbonates from the Curonian Lagoon and its main tributary – Nemunas-Neris River system – reveals a substantial influx of “old” carbonates into the lagoon. As a result, the uncertainty of reservoir effect added a considerable error to the 14C ages. Moreover, fossil molluscs of the same species extracted from boreholes and outcrops yield significantly younger ages (up to several millennia) than the enclosing sediments. Both of these trends – aging and rejuvenation – highlight an urgent need for constraining the local reservoir correction (ΔR). Several scenarios are presented to explain the impact of vital effects on radiocarbon chronology of carbonates and to offer strategies to account for them in future studies.
Keywords: Curonian lagoon; ESR; IR-OSL; Molluscs; radiocarbon; Reservoir effect; Vistula lagoon

Comparative growth, age at maturity and sex change, and longevity of Hawaiian parrotfishes with bomb radiocarbon validation - DeMartini, Edward E; Andrews, Allen H; Howard, Kathrine G; Taylor, Brett M; Lou, Dongchun; Donovan, Mary K. (Canadian Journal of Fisheries and Aquatic Sciences, 2017)
Growth rates and longevities were estimated for five major fishery species of parrotfishes (“uhu”) at Oahu, Hawai'i. All species grew rapidly with von Bertalanffy Growth Formula (VBGF) k values ≥ 0.4 yr-1. Longevities were found to range broadly among the three SMALL species—4 yr in Calotomus carolinus and 6 and 11 yr in Scarus psittacus and Chlorurus spilurus—and to 15-20 yr in S. rubroviolaceus and Chlorurus perspicillatus for the two LARGE species. Age-reading and growth curves for the latter two LARGE species were validated using bomb radiocarbon dating. Median ages at sexual maturity as females (AM50) and at sex change (from female to terminal phase male, A∆50) were estimated using logistic models. Sexual maturation occurred at 1–2 yr for the SMALL species and at 3–3½ yr in the LARGE species. A∆50 estimates ranged from 2–4 yr in the SMALL species and were about 5 and 7 yr in S. rubroviolaceus and C. perspicillatus, respectively. Estimated milestones poorly corresponded to the current minimum legal size for uhu in Hawai'i (12" or 30.5 cm fork length). Pooling these parrotfishes for management seems generally inappropriate, especially for the two LARGE species. Age-based metrics are more informative than size-based metrics for these fishes

Comprehensive radiocarbon analysis of benzene polycarboxylic acids (BPCAs) derived from pyrogenic carbon in environmental samples - Hanke, U M; Wacker, L; Haghipour, N; Schmidt, M W I; Eglinton, T I; McIntyre, C P (Radiocarbon, 2017)
Compound-specific radiocarbon analysis (CSRA) of benzene polycarboxylic acids (BPCAs) yields molecular-level, source-specific information necessary to constrain isotopic signatures of pyrogenic carbon. However, the purification of individual BPCAs requires a multistep procedure that typically results in only microgram quantities of the target analyte(s). Such small samples are highly susceptible to contamination by extraneous carbon, which needs to be minimized and carefully accounted for in order to yield accurate results. Here, we undertook comprehensive characterization and quantification of contamination associated with molecular radiocarbon (14C) BPCA analyses through systematic processing of multiple authentic standards with both fossil and modern 14C signatures at various concentrations. Using this approach, we precisely apportion the contribution of extraneous carbon with respect to the four implemented subprocedures. Assuming a constant source and quantity of extraneous carbon we correct and statistically evaluate uncertainties in resulting 14C data. Subsequently, we examine the results of triplicate analyses of reference materials representing four different environmental matrices (sediment, soil, aerosol, riverine natural organic matter) and apportion their BPCA sources in terms of carbon residues derived from biomass or fossil fuel combustion. This comprehensive approach to CSRA facilitates retrieval of robust 14C data, with application in environmental studies of the continuum of pyrogenic carbon.

Coupling of the Intertropical Convergence Zone and Southern Hemisphere mid-latitude climate during the early to mid-Holocene - Mariani, Michela; Fletcher, Michael-Shawn; Drysdale, Russell N.; Saunders, Krystyna M.; Heijnis, Henk; Jacobsen, Geraldine; Zawadzki, Atun (Geology, 2017)
Conceptual models predict a tight coupling between the Intertropical Convergence Zone (ITCZ) and the Southern Westerly Winds (SWW) in response to glacial-interglacial transitions, yet little is known about this relationship under Holocene boundary conditions. Here we present a synthesis of Holocene pollen data from the southwest Pacific mid-latitudes that tracks changes in the SWW. Comparison of our SWW paleoclimate records with data tracking the ITCZ, oceanic circulation, and insolation reveals clearly synchronous and in-phase ITCZ-SWW dynamics between 12 and 5 ka, indicating a tight coupling between the tropics and southern mid-latitudes in response to ocean circulation and insolation. An apparent decoupling of the SWW and ITCZ in the Pacific region after 5 ka is attributable to the overriding influence of the El Niño–Southern Oscillation (ENSO) over the proxy data.

The distribution and utility of sea-level indicators in Eurasian sub-Arctic salt marshes (White Sea, Russia) - Kemp, Andrew C.; Horton, Benjamin P.; Nikitina, Daria; Vane, Christopher H.; Potapova, Marina; Weber-Bruya, Elizabeth; Culver, Stephen J.; Repkina, Tatyana; Hill, David F. (Boreas, 2017)
In support of efforts to reconstruct relative sea level (RSL), we investigated the utility of foraminifera, diatoms and bulk‐sediment geochemistry (δ13C, C:N and parameters measured by Rock‐Eval pyrolysis) as sea‐level indicators in Eurasian sub‐Arctic salt marshes. At three salt marshes (<15 km apart) in Dvina Bay (White Sea, Russia), we collected surface sediment samples along transects from subtidal to Taiga forest environments. Foraminifera at all sites formed bipartite assemblages, where elevations below mean high higher water (MHHW) were dominated by Miliammina spp. and elevations between MHHW and the highest occurrence of foraminifera were dominated by Jadammina macrescens and Balticammina pseudomacrescens. Five high‐diversity groups of diatoms were identified and they displayed pronounced variability amongst the study sites. Bulk‐sediment geochemistry recognized two groups (clastic‐dominated environments below MHHW and organic‐rich environments above MHHW). As one group included subtidal elevations and the other included supratidal elevations, we conclude that the measured geochemical parameters are not stand‐alone sea‐level indicators. Core JT2012 captured a regressive sediment succession of clastic, tidal‐flat sediment overlain by salt‐marsh organic silt and freshwater peat. The salt‐marsh sediment accumulated at 2804±52 years before present and preserved foraminifera (Jadammina macrescens and Balticammina pseudomacrescens) with good analogy to modern assemblages indicating that RSL was +2.60±0.47 m at this time. Diatoms confirm that marine influence decreased through time, but the lack of analogy between modern and core assemblages limited their utility as sea‐level indicators. Geochemical parameters also indicate a reduction in marine influence through time. We conclude that RSL reconstructions derived from salt‐marsh sediment preserved beneath Eurasian sub‐Arctic peatlands can provide valuable insight into the spatio‐temporal evolution of the Fennoscandian and Eurasian ice sheets.

Divergent Evolution of Carbonaceous Aerosols during Dispersal of East Asian Haze - Fang, Wenzheng; Andersson, August; Zheng, Mei; Lee, Meehye; Holmstrand, Henry; Kim, Sang-Woo; Du, Ke; Gustafsson, Örjan (Scientific Reports, 2017)
Wintertime East Asia is plagued by severe haze episodes, characterized by large contributions of carbonaceous aerosols. However, the sources and atmospheric transformations of these major components are poorly constrained, hindering development of efficient mitigation strategies and detailed modelling of effects. Here we present dual carbon isotope (δ13C and Δ14C) signatures for black carbon (BC), organic carbon (OC) and water-soluble organic carbon (WSOC) aerosols collected in urban (Beijing and BC for Shanghai) and regional receptors (e.g., Korea Climate Observatory at Gosan) during January 2014. Fossil sources (>50%) dominate BC at all sites with most stemming from coal combustion, except for Shanghai, where liquid fossil source is largest. During source-to-receptor transport, the δ13C fingerprint becomes enriched for WSOC but depleted for water-insoluble OC (WIOC). This reveals that the atmospheric processing of these two major pools are fundamentally different. The photochemical aging (e.g., photodissociation, photooxidation) during formation and transport can release CO2/CO or short-chain VOCs with lighter carbon, whereas the remaining WSOC becomes increasingly enriched in δ13C. On the other hand, several processes, e.g., secondary formation, rearrangement reaction in the particle phase, and photooxidation can influence WIOC. Taken together, this study highlights high fossil contributions for all carbonaceous aerosol sub-compartments in East Asia, and suggests different transformation pathways for different classes of carbonaceous aerosols.

Evidence for coseismic subsidence events in a southern California coastal saltmarsh - Leeper, Robert; Rhodes, Brady; Kirby, Matthew; Scharer, Katherine; Carlin, Joseph; Hemphill-Haley, Eileen; Avnaim-Katav, Simona; MacDonald, Glen; Starratt, Scott; Aranda, Angela (Scientific Reports, 2017)
Paleoenvironmental records from a southern California coastal saltmarsh reveal evidence for repeated late Holocene coseismic subsidence events. Field analysis of sediment gouge cores established discrete lithostratigraphic units extend across the wetland. Detailed sediment analyses reveal abrupt changes in lithology, percent total organic matter, grain size, and magnetic susceptibility. Microfossil analyses indicate that predominantly freshwater deposits bury relic intertidal deposits at three distinct depths. Radiocarbon dating indicates that the three burial events occurred in the last 2000 calendar years. Two of the three events are contemporaneous with large-magnitude paleoearthquakes along the Newport-Inglewood/Rose Canyon fault system. From these data, we infer that during large magnitude earthquakes a step-over along the fault zone results in the vertical displacement of an approximately 5-km2 area that is consistent with the footprint of an estuary identified in pre-development maps. These findings provide insight on the evolution of the saltmarsh, coseismic deformation and earthquake recurrence in a wide area of southern California, and sensitive habitat already threatened by eustatic sea level rise.
Keywords: Geomorphology; Natural hazards; Structural geology; tectonics

Extended late Holocene relative sea-level histories for North Carolina, \{USA\} - Andrew C. Kemp; Jessica J. Kegel; Stephen J. Culver; Donald C. Barber; David J. Mallinson; Eduardo Leorri; Christopher E. Bernhardt; Niamh Cahill; Stanley R. Riggs; Anna L. Woodson; Ryan P. Mulligan; Benjamin P. Horton (Quaternary Science Reviews, 2017)
Abstract We produced ∼3000-year long relative sea-level (RSL) histories for two sites in North Carolina (USA) using foraminifera preserved in new and existing cores of dated salt-marsh sediment. At Cedar Island, \{RSL\} rose by ∼2.4 m during the past ∼3000 years compared to ∼3.3 m at Roanoke Island. This spatial difference arises primarily from differential \{GIA\} that caused late Holocene \{RSL\} rise to be 0.1–0.2 mm/yr faster at Roanoke Island than at Cedar Island. However, a non-linear difference in \{RSL\} between the two study regions (particularly from ∼0 \{CE\} to ∼1250 CE) indicates that additional local- to regional-scale processes drove centennial-scale \{RSL\} change in North Carolina. Therefore, the Cedar Island and Roanoke Island records should be considered as independent of one another. Between-site differences on sub-millennial timescales cannot be adequately explained by non-stationary tides, sediment compaction, or local sediment dynamics. We propose that a period of accelerating \{RSL\} rise from ∼600 \{CE\} to 1100 \{CE\} that is present at Roanoke Island (and other sites north of Cape Hatteras at least as far as Connecticut), but absent at Cedar Island (and other sites south of Cape Hatteras at least as far as northeastern Florida) is a local-to regional-scale effect of dynamic ocean and/or atmospheric circulation.
Keywords: Salt marsh

Extreme waves in the British Virgin Islands during the last centuries before 1500 CE - Atwater, Brian F.; ten Brink, Uri S.; Cescon, Anna Lisa; Feuillet, Nathalie; Fuentes, Zamara; Halley, Robert B.; ñez, Carlos; Reinhardt, Eduard G.; Roger, Jean H.; Sawai, Yuki; Spiske, Michaela; Tuttle, Martitia P.; et al. (Geosphere, 2017)
Extraordinary marine inundation scattered clasts southward on the island of Anegada, 120 km south of the Puerto Rico Trench, sometime between 1200 and 1480 calibrated years (cal yr) CE. Many of these clasts were likely derived from a fringing reef and from the sandy flat that separates the reef from the island’s north shore. The scattered clasts include no fewer than 200 coral boulders, mapped herein for the first time and mainly found hundreds of meters inland. Many of these are complete colonies of the brain coral Diploria strigosa. Other coral species represented include Orbicella (formerly Montastraea) annularis, Porites astreoides, and Acropora palmata. Associated bioclastic carbonate sand locally contains articulated cobble-size valves of the lucine Codakia orbicularis and entire conch shells of Strombus gigas, mollusks that still inhabit the sandy shallows between the island’s north shore and a fringing reef beyond. italicmbricated limestone slabs are clustered near some of the coral boulders. In addition, fields of scattered limestone boulders and cobbles near sea level extend mainly southward from limestone sources as much as 1 km inland. Radiocarbon ages have been obtained from 27 coral clasts, 8 lucine valves, and 3 conch shells. All these additional ages predate 1500 cal yr CE, all but 2 are in the range 1000–1500 cal yr CE, and 16 of 22 brain coral ages cluster in the range 1200–1480 cal yr CE. The event marked by these coral and mollusk clasts likely occurred in the last centuries before Columbus (before 1492 CE). The pre-Columbian deposits surpass Anegada’s previously reported evidence for extreme waves in post-Columbian time. The coarsest of the modern storm deposits consist of coral rubble that lines the north shore and sandy fans on the south shore; neither of these storm deposits extends more than 50 m inland. More extensive overwash, perhaps by the 1755 Lisbon tsunami, is marked primarily by a sheet of sand and shells found mainly below sea level beneath the floors of modern salt ponds. This sheet extends more than 1 km southward from the north shore and dates to the interval 1650–1800 cal yr CE. Unlike the pre-Columbian deposits, it lacks coarse clasts from the reef or reef flat; its shell assemblage is instead dominated by cerithid gastropods that were merely stirred up from a marine pond in the island’s interior. In their inland extent and clustered pre-Columbian ages, the coral clasts and associated deposits suggest extreme waves unrivaled in recent millennia at Anegada. Bioclastic sand coats limestone 4 m above sea level in areas 0.7 and 1.3 km from the north shore. A coral boulder of nearly 1 m3 is 3 km from the north shore by way of an unvegetated path near sea level. As currently understood, the extreme flooding evidenced by these and other clasts represents either an extraordinary storm or a tsunami of nearby origin. The storm would need to have produced tsunami-like bores similar to those of 2013 Typhoon Haiyan in the Philippines. Normal faults and a thrust fault provide nearby tsunami sources along the eastern Puerto Rico Trench.

Final Radiocarbon Investigation of Platland Tree, the Biggest African Baobab - Patrut, Adrian; Woodborne, Stephan; Patrut, Roxana T.; Rakosy, Laszlo; Hall, Grant; Ratiu, Ileana-Andreea; von Reden, Karl F. (Studia Universitatis Babeș-Bolyai Chemia, 2017)
The article discloses the main results of our new investigation of Platland tree, a.k.a. Sunland baobab, the largest known African baobab. Our recent research was motivated by the three successive splits of 2016 and 2017, which determined the collapse and demise of the stems that have built the main unit of the tree. According to our new findings concerning the architecture of large and old baobabs, we established that Platland tree has a double closed-ring shaped structure and consists of two units/rings that close two separate false cavities. The larger unit was composed of five fused stems, out of which four toppled and died, while the fifth stem is already broken. The smaller unit, which is still standing, consists of three fused stems. We also determined that the larger unit had an age of 800 yr, while the smaller unit is 1100 yr old.

Greenhouse gas balance over thaw-freeze cycles in discontinuous zone permafrost - Wilson, R. M.; Fitzhugh, L.; Whiting, G. J.; Frolking, S.; Harrison, M. D.; Dimova, N.; Burnett, W. C.; Chanton, J. P. (Journal of Geophysical Research: Biogeosciences, 2017)
Peat in the discontinuous permafrost zone contains a globally significant reservoir of carbon that has undergone multiple permafrost-thaw cycles since the end of the mid-Holocene (~3700 years before present). Periods of thaw increase C decomposition rates which leads to the release of CO2 and CH4 to the atmosphere creating potential climate feedback. To determine the magnitude and direction of such feedback, we measured CO2 and CH4 emissions and modeled C accumulation rates and radiative fluxes from measurements of two radioactive tracers with differing lifetimes to describe the C balance of the peatland over multiple permafrost-thaw cycles since the initiation of permafrost at the site. At thaw features, the balance between increased primary production and higher CH4 emission stimulated by warmer temperatures and wetter conditions favors C sequestration and enhanced peat accumulation. Flux measurements suggest that frozen plateaus may intermittently (order of years to decades) act as CO2 sources depending on temperature and net ecosystem respiration rates, but modeling results suggest that—despite brief periods of net C loss to the atmosphere at the initiation of thaw—integrated over millennia, these sites have acted as net C sinks via peat accumulation. In greenhouse gas terms, the transition from frozen permafrost to thawed wetland is accompanied by increasing CO2 uptake that is partially offset by increasing CH4 emissions. In the short-term (decadal time scale) the net effect of this transition is likely enhanced warming via increased radiative C emissions, while in the long-term (centuries) net C deposition provides a negative feedback to climate warming.

The Growth Stop Phenomenon Of Baobabs (Adansonia Spp.) Identified By Radiocarbon DatingAbstract - Patrut, Adrian; Woodborne, Stephan; von Reden, Karl F; Hall, Grant; Patrut, Roxana T; Rakosy, Laszlo; Danthu, Pascal; Pock-Tsy, Jean-Michel Leong; Lowy, Daniel A; Margineanu, Dragos (Radiocarbon, 2017)
The article reports the growth stop phenomenon, which was documented only for baobabs, i.e. for trees belonging to the Adansonia genus. The identification of growth stop was enabled by radiocarbon dating, which allows a complex investigation of samples collected from the trunk/stems of baobabs. In several cases, the outermost rings of baobabs, which were close to the bark, were found to be old, with ages of several hundreds of years, instead of being very young. Dating results of samples collected from six baobabs are presented. For multistemmed baobabs, the growth stop may occur only for one or several stems. We identified four factors that may induce the growth stop: (i) stress determined by severe climate conditions, (ii) old age, (iii) the need to keep a stable internal architecture, and (iv) the collapse of stems that survive this trauma. Baobabs and their stems affected by growth stop may survive for several centuries, by continuing to produce leaves, flowers, and fruits. This phenomenon was associated with the capacity of baobabs to store large amounts of water in their trunks/stems in the rainy season. This reservoir of water is used during the dry season and allows the trees to survive prolonged drought periods.
Keywords: Age determination; AMS; growth stop; Radiocarbon dating; tropical trees

High-resolution climate of the past ∼7300 years of coastal northernmost California: Results from diatoms, silicoflagellates, and pollen - John A. Barron; David Bukry; Linda E. Heusser; Jason A. Addison; Clark R. Alexander (Quaternary International, 2017)
Abstract Piston core TN062-O550, collected about 33 km offshore of Eureka, California, contains a high-resolution record of the climate and oceanography of coastal northernmost California during the past ∼7.34 kyr. Chronology established by nine \{AMS\} ages on a combination of planktic foraminifers, bivalve shell fragments, and wood yields a mean sedimentation rate of 103 cm kyr−1. Marine proxies (diatoms and silicoflagellates) and pollen transported by the nearby Eel River reveal a stepwise development of both modern offshore surface water oceanography and coastal arboreal ecosystems. Beginning at ∼5.4 cal ka the relative abundance of coastal redwood pollen, a proxy for coastal fog, displays a two fold increase suggesting enhanced coastal upwelling. A decline in the relative contribution of subtropical diatoms at ∼5.0 cal ka implies cooling of sea surface temperatures (SSTs). At ∼3.6 cal ka an increase in the relative abundance of alder and oak at the expense of coastal redwood likely signals intensified riverine transport of pollen from inland environments. Cooler offshore \{SSTs\} and increased precipitation characterize the interval between ∼3.6 and 2.8 cal ka. A rapid, stepwise change in coastal climatology and oceanography occurs between ∼2.8 and 2.6 cal ka that suggests an enhanced expression of modern Pacific Decadal Oscillation-like (PDO) cycles. A three-fold increase in the relative abundance of the subtropical diatom Fragilariopsis doliolus at 2.8 cal ka appears to mark an abrupt warming of winter SSTs. Soon afterwards at 2.6 cal ka, a two fold increase in the relative abundance of coastal redwood pollen is suggestive of an abrupt intensification of spring upwelling. After ∼2.8 cal ka a sequence of cool-warm, PDO-like cycles occurs wherein cool cycles are characterized by relative abundance increases in coastal redwood pollen and decreased contributions of subtropical diatoms, whereas opposite proxy trends distinguish warm cycles.

Holocene climate and environmental history of East Greenland inferred from lake sediments - Lusas, Amanda R.; Hall, Brenda L.; Lowell, Thomas V.; Kelly, Meredith A.; Bennike, Ole; Levy, Laura B.; Honsaker, William (Journal of Paleolimnology, 2017)
Prediction of future Arctic climate and environmental changes, as well as associated ice-sheet behavior, requires placing present-day warming and reduced ice extent into a long-term context. Here we present a record of Holocene climate and glacier fluctuations inferred from the paleolimnology of small lakes near Istorvet ice cap in East Greenland. Calibrated radiocarbon dates of organic remains indicate deglaciation of the region before ~10,500 years BP, after which time the ice cap receded rapidly to a position similar to or less extensive than present, and lake sediments shifted from glacio-lacustrine clay to relatively organic-rich gyttja. The lack of glacio-lacustrine sediments throughout most of the record suggests that the ice cap was similar to or smaller than present throughout most of the Holocene. This restricted ice extent suggests that climate was similar to or warmer than present, in keeping with other records from Greenland that indicate a warm early and middle Holocene. Middle Holocene magnetic susceptibility oscillations, with a ~200-year frequency in one of the lakes, may relate to solar influence on local catchment processes. Following thousands of years of restricted extent, Istorvet ice cap advanced to within 365 m of its late Holocene limit at ~AD 1150. Variability in the timing of glacial and climate fluctuations, as well as of sediment organic content changes among East Greenland lacustrine records, may be a consequence of local factors, such as elevation, continentality, water depth, turbidity, and seabirds, and highlights the need for a detailed spatial array of datasets to address questions about Holocene climate change.
Keywords: De Vries cycle; Glacially fed lakes; Greenland; Holocene; Paleoclimate

Hydrologic controls on seasonal and inter-annual variability of Congo River particulate organic matter source and reservoir age - Hemingway, Jordon D.; Schefuß, Enno; Spencer, Robert G.M.; Dinga, Bienvenu Jean; Eglinton, Timothy I.; McIntyre, Cameron; Galy, Valier V. (Chemical Geology, 2017)
We present dissolved organic carbon (DOC) concentrations, particulate organic matter (POM) composition (δ13C, δ15N, ∆14C, N/C), and particulate glycerol dialkyl glycerol tetraether (GDGT) distributions from a 34-month time-series near the mouth of the Congo River. An end-member mixing model using δ13C and N/C indicates that exported POM is consistently dominated by C3 rainforest soil sources, with increasing contribution from C3 vegetation and decreasing contribution from phytoplankton at high discharge. Large C4 inputs are never observed despite covering ≈ 13% of the catchment. Low and variable ∆14C values during 2011 [annual mean = (− 148 ± 82) ‰], when discharge from left-bank tributaries located in the southern hemisphere reached record lows, likely reflect a bias toward pre-aged POM derived from the Cuvette Congolaise swamp forest. In contrast, ∆14C values were stable near − 50‰ between January and June 2013, when left-bank discharge was highest. We suggest that headwater POM is replaced and/or diluted by C3 vegetation and pre-aged soils during transit through the Cuvette Congolaise, whereas left-bank tributaries export significantly less pre-aged material. GDGT distributions provide further evidence for seasonal and inter-annual variability in soil provenance. The cyclization of branched tetraethers and the GDGT-0 to crenarchaeol ratio are positively correlated with discharge (r ≥ 0.70; p-value ≤ 4.3 × 10− 5) due to the incorporation of swamp-forest soils when discharge from right-bank tributaries located in the northern hemisphere is high. Both metrics reach record lows during 2013, supporting our interpretation of increased left-bank contribution at this time. We conclude that hydrologic variability is a major control of POM provenance in the Congo River Basin and that tropical wetlands can be a significant POM source despite their small geographic coverage.
Keywords: biomarkers; Congo River; GDGTs; Particulate organic matter; radiocarbon

Land-use change and managed aquifer recharge effects on the hydrogeochemistry of two contrasting atoll island aquifers, Roi-Namur Island, Republic of the Marshall Islands - Mehrdad Hejazian; Jason J. Gurdak; Peter Swarzenski; Kingsley O. Odigie; Curt D. Storlazzi (Applied Geochemistry, 2017)
Abstract Freshwater resources on low-lying atoll islands are highly vulnerable to climate change and sea-level rise. In addition to rainwater catchment, groundwater in the freshwater lens is a critically important water resource on many atoll islands, especially during drought. Although many atolls have high annual rainfall rates, dense natural vegetation and high evapotranspiration rates can limit recharge to the freshwater lens. Here we evaluate the effects of land-use/land-cover change and managed aquifer recharge on the hydrogeochemistry and supply of groundwater on Roi-Namur Island, Republic of the Marshall Islands. Roi-Namur is an artificially conjoined island that has similar hydrogeology on the Roi and Namur lobes, but has contrasting land-use/land-cover and managed aquifer recharge only on Roi. Vegetation removal and managed aquifer recharge operations have resulted in an estimated 8.6 × 105 m3 of potable groundwater in the freshwater lens on Roi, compared to only 1.6 × 104 m3 on Namur. We use groundwater samples from a suite of 33 vertically nested monitoring wells, statistical testing, and geochemical modeling using \{PHREEQC\} to show that the differences in land-use/land-cover and managed aquifer recharge on Roi and Namur have a statistically significant effect on several groundwater-quality parameters and the controlling geochemical processes. Results also indicate a six-fold reduction in the dissolution of carbonate rock in the freshwater lens and overlying vadose zone of Roi compared to Namur. Mixing of seawater and the freshwater lens is a more dominant hydrogeochemical process on Roi because of the greater recharge and flushing of the aquifer with freshwater as compared to Namur. In contrast, equilibrium processes and dissolution-precipitation non-equilibrium reactions are more dominant on Namur because of the longer residence times relative to the rate of geochemical reactions. Findings from Roi-Namur Island support selective land-use/land-cover change and managed aquifer recharge as a promising management approach for communities on other low-lying atoll islands to increase the resilience of their groundwater supplies and help them adapt to future climate change related stresses.

Micromorphology of late Pleistocene and Holocene sediments and a new interpretation of the Holocene chronology at Anderson Pond, Tennessee, USAAbstract - Driese, Steven G.; Horn, Sally P.; Ballard, Joanne P.; Boehm, Mathew S.; Li, Zhenghua (Quaternary Research, 2017)
Thin-section (micromorphological) analysis of samples from the upper 1.5 m of a core obtained in 2007 from Anderson Pond, Tennessee, reveals a coherent but discontinuous record of late Pleistocene and Holocene climate change that supports some interpretations from previous pollen and charcoal analyses but indicates a revised Holocene chronology for this classic pollen site. Legacy sediments recording anthropogenic disturbance compose the upper 65 cm of the core (<160 cal yr BP) and are characterized by mixed, darker-colored, and coarser-grained deposits containing reworked soil aggregates, which sharply overlie finer-grained and lighter-colored, rooted middle Holocene sediments interpreted as a paleosol. These mid-Holocene sediments (95–65 cm; 7100–5600 cal yr BP) record extensive warm-dry subaerial soil conditions during the middle Holocene thermal maximum, manifested by illuviated clay lining root pores, and also contain abundant charcoal. Late Pleistocene sediments (150–95 cm), dark-colored and organic-rich, record open-water conditions and include siliceous aggregate grains at 143–116 cm (14,300–13,900 cal yr BP), recording intense fires. Thin sections are not commonly used in studies of paleoclimate from Quaternary lacustrine sediments, but we advocate for their inclusion in multianalytical approaches because they enhance resolution of depositional and pedogenic processes.

Millennial-scale iron fertilization of the eastern equatorial Pacific over the past 100,000 years - Loveley, Matthew R.; Marcantonio, Franco; Wisler, Marilyn M.; Hertzberg, Jennifer E.; Schmidt, Matthew W.; Lyle, Mitchell (Nature Geoscience, 2017)
The eastern equatorial Pacific Ocean plays a crucial role in global climate, as it is a substantial source of CO2 to the atmosphere and accounts for a significant portion of global new export productivity. Here we present a 100,000-year sediment core from the eastern equatorial Pacific, and reconstruct dust flux, export productivity and bottom-water oxygenation using excess-230Th-derived fluxes of 232Th and barium, and authigenic uranium concentrations, respectively. We find that during the last glacial period (71,000 to 41,000 years ago), increased delivery of dust to the eastern equatorial Pacific was coeval with North Atlantic Heinrich stadial events. Millennial-scale pulses of increased dust flux coincided with episodes of heightened biological productivity, suggesting that dissolution of dust released iron that promoted ocean fertilization. We also find that periods of low atmospheric CO2 concentrations were associated with suboxic conditions and increased storage of respired carbon in the deep eastern equatorial Pacific. Increases in CO2 concentrations during the deglaciation are coincident with increases in deep Pacific and Southern Ocean water oxygenation levels. We suggest that deep-ocean ventilation was a primary control on CO2 outgassing in this region, with superimposed pulses of high productivity providing a negative feedback.

Permafrost Organic Carbon Mobilization From the Watershed to the Colville River Delta: Evidence From 14C Ramped Pyrolysis and Lignin Biomarkers - Zhang, Xiaowen; Bianchi, Thomas S.; Cui, Xingqian; Rosenheim, Brad E.; Ping, Chien‐Lu; Hanna, Andrea J. M.; Kanevskiy, Mikhail; Schreiner, Kathryn M.; Allison, Mead A. (Geophysical Research Letters, 2017)
The deposition of terrestrial‐derived permafrost particulate organic carbon (POC) has been recorded in major Arctic river deltas. However, associated transport pathways of permafrost POC from the watershed to the coast have not been well constrained. Here we utilized a combination of ramped pyrolysis‐oxidation radiocarbon analysis (RPO 14C) along with lignin biomarkers, to track the linkages between soils and river and delta sediments. Surface and deep soils showed distinct RPO thermographs which may be related to degradation and organo‐mineral interaction. Soil material in the bed load of the river channel was mostly derived from deep old permafrost. Both surface and deep soils were transported and deposited to the coast. Hydrodynamic sorting and barrier island protection played important roles in terrestrial‐derived permafrost POC deposition near the coast. On a large scale, ice processes (e.g., ice gauging and strudel scour) and ocean currents controlled the transport and distribution of permafrost POC on the Beaufort Shelf.
Keywords: Arctic; carbon cycling; Colville River; Lignin; permafrost; pyrolysis

Proceedings of the International Ocean Discovery ProgramExpedition 357 methods - Früh-Green, G.L.; Orcutt, B.N.; Green, S.L.; Cotterill, C.; Morgan, S.; Akizawa, N.; Bayrakci, G.; Behrmann, J.-H.; Boschi, C.; Brazleton, W.J.; Cannat, M.; Dunkel, K.G.; et al. (International Ocean Discovery Program, 2017)

Quantifying bamboo coral growth rate nonlinearity with the radiocarbon bomb spike: A new model for paleoceanographic chronology development - Frenkel, M.M.; LaVigne, M.; Miller, H.R.; Hill, T.M.; McNichol, A.; Gaylord, M. Lardie (Deep Sea Research Part I: Oceanographic Research Papers, 2017)
Bamboo corals, long-lived cold water gorgonin octocorals, offer unique paleoceanographic archives of the intermediate ocean. These Isididae corals are characterized by alternating gorgonin nodes and high Mg-calcite internodes, which synchronously extend radially. Bamboo coral calcite internodes have been utilized to obtain geochemical proxy data, however, growth rate uncertainty has made it difficult to construct precise chronologies for these corals. Previous studies have relied upon a single tie point from records of the anthropogenic Δ14C bomb spike preserved in the gorgonin nodes of live-collected corals to calculate a mean radial extension rate for the outer ~50 years of skeletal growth. Bamboo coral chronologies are typically constructed by applying this mean extension rate to the entire coral record, assuming constant radial extension with coral age. In this study, we aim to test this underlying assumption by analyzing the organic nodes of six California margin bamboo corals at high enough resolution (<0.5 mm) to identify the Δ14C bomb spike, including two tie points at 1957 and 1970, plus the coral collection date (2007.5) for four samples. Radial extension rates between tie points ranged from 10 to 204 µm/year, with a decrease in growth rate evident between the 1957–1970 and 1970–2007.5 periods for all four corals. A negative correlation between growth rate and coral radius (r =−0.7; p=0.04) was determined for multiple bamboo coral taxa and individuals from the California margin, demonstrating a decline in radial extension rate with specimen age and size. To provide a mechanistic basis for these observations, a simple mathematical model was developed based on the assumption of a constant increase in circular cross sectional area with time to quantify this decline in radial extension rate with coral size between chronological tie points. Applying the area-based model to our Δ14C bomb spike time series from individual corals improves chronology accuracy for all live-collected corals with complete Δ14C bomb spikes. Hence, this study provides paleoceanographers utilizing bamboo corals with a method for reducing age model uncertainty within the anthropogenic bomb spike era (~1957-present). Chronological uncertainty is larger for the earliest portion of coral growth, particularly for skeleton precipitated prior to bomb spike tie points, meaning age estimations for samples living before 1957 remain uncertain. Combining this technique with additional chronological markers could improve age models for an entire bamboo coral. Finally, the relative consistency in growth rate in similarly-aged corals of the same depth and location supports the hypothesis that skeletal growth may be limited by local environmental conditions.
Keywords: 14C nuclear bomb spike; Bamboo coral; Chronologies; Gorgonin; Growth rate; paleoceanography; radiocarbon

Relative sea-level trends in New York City during the past 1500 years - Kemp, Andrew C; Hill, Troy D; Vane, Christopher H; Cahill, Niamh; Orton, Philip M; Talke, Stefan A; Parnell, Andrew C; Sanborn, Kelsey; Hartig, Ellen K (The Holocene, 2017)
New York City (NYC) is threatened by 21st-century relative sea-level (RSL) rise because it will experience a trend that exceeds the global mean and has high concentrations of low-lying infrastructure and socioeconomic activity. To provide a long-term context for anticipated trends, we reconstructed RSL change during the past ~1500 years using a core of salt-marsh sediment from Pelham Bay in The Bronx. Foraminifera and bulk-sediment δ13C values were used as sea-level indicators. The history of sediment accumulation was established by radiocarbon dating and recognition of pollution and land-use trends of known age in down-core elemental, isotopic, and pollen profiles. The reconstruction was generated within a Bayesian hierarchical model to accommodate multiple proxies and to provide a unified statistical framework for quantifying uncertainty. We show that RSL in NYC rose by ~1.70 m since ~575 CE (including ~0.38 m since 1850 CE). The rate of RSL rise increased markedly at 1812–1913 CE from ~1.0 to ~2.5 mm/yr, which coincides with other reconstructions along the US Atlantic coast. We investigated the possible influence of tidal-range change in Long Island Sound on our reconstruction using a regional tidal model, and we demonstrate that this effect was likely small. However, future tidal-range change could exacerbate the impacts of RSL rise in communities bordering Long Island Sound. The current rate of RSL rise is the fastest that NYC has experienced for >1500 years, and its ongoing acceleration suggests that projections of 21st-century local RSL rise will be realized.
Keywords: Bayesian transfer function; carbon isotope; Foraminifera; Salt marsh; sedimentation; The Bronx

Reversible adsorption and flushing of arsenic in a shallow, Holocene aquifer of Bangladesh - Kathleen A. Radloff; Yan Zheng; Martin Stute; Beth Weinman; Benjamin Bostick; Ivan Mihajlov; Margaret Bounds; M.Moshiur Rahman; M.Rezaul Huq; Kazi M. Ahmed; Peter Schlosser; Alexander van Geen (Applied Geochemistry, 2017)
Abstract The spatial heterogeneity of dissolved arsenic (As) concentrations in shallow groundwater of the Bengal Basin has been attributed to transport of As (and reactive carbon) from external sources or to the release of As from within grey sand formations. We explore the latter scenario in this detailed hydrological and geochemical study along a 300 m transect of a shallow aquifer extending from a groundwater recharge area within a sandy channel bar to its discharge into a nearby stream. Within the 10–20 m depth range, groundwater ages along the transect determined by the 3H–3He method increase from <10 yr in the recharge area to a maximum of 40 yr towards the stream. Concentrations of groundwater As within the same grey sands increase from 10 to 100 to ∼500 μg/L along this transect. Evidence of reversible adsorption of As between the groundwater and sediment was obtained from a series of push–pull experiments, traditional batch adsorption experiments, and the accidental flooding of a shallow monitoring well. Assuming reversible adsorption and a distribution coefficient, Kd, of 0.15–1.5 L/kg inferred from these observations, a simple flushing model shows that the increase in As concentrations with depth and groundwater age at this site, and at other sites in the Bengal and Red River Basins, can be attributed to the evolution of the aquifer over 100–1000 years as aquifer sands are gradually flushed of their initial As content. A wide range of As concentrations can thus be maintained in groundwater with increases with depth governed by the history of flushing and local recharge rates, without external inputs of reactive carbon or As from other sources.
Environmental and Health Roles of Geogenic Arsenic
Keywords: Push–pull tests

Sedimentary record from the Canada Basin, Arctic Ocean: implications for late to middle Pleistocene glacial history - Dong, Linsen; Liu, Yanguang; Shi, Xuefa; Polyak, Leonid; Huang, Yuanhui; Fang, Xisheng; Liu, Jianxing; Zou, Jianjun; Wang, Kunshan; Sun, Fuqiang; Wang, Xuchen (Climate of the Past, 2017)
ediment core ARC4-BN05 collected from the Canada Basin, Arctic Ocean, covers the late to middle Quaternary (Marine Isotope Stage – MIS – 1–15, ca. 0.5–0.6 Ma) as estimated by correlation to earlier proposed Arctic Ocean stratigraphies and AMS14C dating of the youngest sediments. Detailed examination of clay and bulk mineralogy along with grain size, content of Ca and Mn, and planktic foraminiferal numbers in core ARC4–BN05 provides important new information about sedimentary environments and provenance. We use increased contents of coarse debris as an indicator of glacier collapse events at the margins of the western Arctic Ocean, and identify the provenance of these events from mineralogical composition. Notably, peaks of dolomite debris, including large dropstones, track the Laurentide Ice Sheet (LIS) discharge events to the Arctic Ocean. Major LIS inputs occurred during the stratigraphic intervals estimated as MIS 3, intra-MIS 5 and 7 events, MIS 8, and MIS 10. Inputs from the East Siberian Ice Sheet (ESIS) are inferred from peaks of smectite, kaolinite, and chlorite associated with coarse sediment. Major ESIS sedimentary events occurred in the intervals estimated as MIS 4, MIS 6 and MIS 12. Differences in LIS vs. ESIS inputs can be explained by ice-sheet configurations at different sea levels, sediment delivery mechanisms (iceberg rafting, suspension plumes, and debris flows), and surface circulation. A long-term change in the pattern of sediment inputs, with an apparent step change near the estimated MIS 7–8 boundary (ca. 0.25 Ma), presumably indicates an overall glacial expansion at the western Arctic margins, especially in North America.

Siberian Arctic black carbon sources constrained by model and observation - Winiger, Patrik; Andersson, August; Eckhardt, Sabine; Stohl, Andreas; Semiletov, Igor P.; Dudarev, Oleg V.; Charkin, Alexander; Shakhova, Natalia; Klimont, Zbigniew; Heyes, Chris; Gustafsson, Örjan (Proceedings of the National Academy of Sciences, 2017)
Black carbon (BC) in haze and deposited on snow and ice can have strong effects on the radiative balance of the Arctic. There is a geographic bias in Arctic BC studies toward the Atlantic sector, with lack of observational constraints for the extensive Russian Siberian Arctic, spanning nearly half of the circum-Arctic. Here, 2 y of observations at Tiksi (East Siberian Arctic) establish a strong seasonality in both BC concentrations (8 ng⋅m−3 to 302 ng⋅m−3) and dual-isotope–constrained sources (19 to 73% contribution from biomass burning). Comparisons between observations and a dispersion model, coupled to an anthropogenic emissions inventory and a fire emissions inventory, give mixed results. In the European Arctic, this model has proven to simulate BC concentrations and source contributions well. However, the model is less successful in reproducing BC concentrations and sources for the Russian Arctic. Using a Bayesian approach, we show that, in contrast to earlier studies, contributions from gas flaring (6%), power plants (9%), and open fires (12%) are relatively small, with the major sources instead being domestic (35%) and transport (38%). The observation-based evaluation of reported emissions identifies errors in spatial allocation of BC sources in the inventory and highlights the importance of improving emission distribution and source attribution, to develop reliable mitigation strategies for efficient reduction of BC impact on the Russian Arctic, one of the fastest-warming regions on Earth.
Keywords: Arctic haze; atmospheric transport modeling; carbon isotopes; Climate change; emission inventory

Subduction zone slip variability during the last millennium, south-central Chile - Dura, Tina; Horton, Benjamin P.; Cisternas, Marco; Ely, Lisa L.; Hong, Isabel; Nelson, Alan R.; Wesson, Robert L.; Pilarczyk, Jessica E.; Parnell, Andrew C.; Nikitina, Daria (Quaternary Science Reviews, 2017)
The Arauco Peninsula (37°-38°S) in south-central Chile has been proposed as a possible barrier to the along-strike propagation of megathrust ruptures, separating historical earthquakes to the south (1960 AD 1837, 1737, and 1575) and north (2010 AD, 1835, 1751, 1657, and 1570) of the peninsula. However, the 2010 (Mw 8.8) earthquake propagated into the Arauco Peninsula, re-rupturing part of the megathrust that had ruptured only 50 years earlier during the largest subduction zone earthquake in the instrumental record (Mw 9.5). To better understand long-term slip variability in the Arauco Peninsula region, we analyzed four coastal sedimentary sections from two sites (Tirúa, 38.3°S and Quidico, 38.1°S) located within the overlap of the 2010 and 1960 ruptures to reconstruct a ∼600-year record of coseismic land-level change and tsunami inundation. Stratigraphic, lithologic, and diatom results show variable coseismic land-level change coincident with tsunami inundation of the Tirúa and Quidico marshes that is consistent with regional historical accounts of coseismic subsidence during earthquakes along the Valdivia portion of the subduction zone (1960 AD and 1575) and coseismic uplift during earthquakes along the Maule portion of the subduction zone (2010 AD, 1835, 1751). In addition, we document variable coseismic land-level change associated with three new prehistoric earthquakes and accompanying tsunamis in 1470–1570 AD, 1425–1455, and 270–410. The mixed record of coseismic subsidence and uplift that we document illustrates the variability of down-dip and lateral slip distribution at the overlap of the 2010 and 1960 ruptures, showing that ruptures have repeatedly propagated into, but not through the Arauco Peninsula and suggesting the area has persisted as a long-term impediment to slip through at least seven of the last megathrust earthquakes (∼600 years).
Keywords: Coastal hazards; Coastal paleoseismology; Diatom paleoecology; Prehistoric earthquakes; Subduction zone segmentation; Tsunami Deposits

Technical note: An inverse method to relate organic carbon reactivity to isotope composition from serial oxidation - Hemingway, Jordon D.; Rothman, Daniel H.; Rosengard, Sarah Z.; Galy, Valier V. (Biogeosciences, 2017)

Timing and magnitude of early to middle Holocene warming in East Greenland inferred from chironomids - Axford, Yarrow; Levy, Laura B.; Kelly, Meredith A.; Francis, Donna R.; Hall, Brenda L.; Langdon, Peter G.; Lowell, Thomas V. (Boreas, 2017)
Much of Greenland experienced summers warmer than present in parts of the early to middle Holocene, during a precession‐driven positive anomaly in summer insolation. However, the magnitude of that warmth remains poorly known, and its timing and spatial pattern are uncertain. Here we describe the first quantitative Holocene palaeotemperature reconstruction from central East Greenland based upon insect (chironomid) assemblages preserved in lake sediments. We postulate that landscapes like our study site, characterized by minimal soil and vegetation development through the Holocene and thus little influenced by some important secondary gradients, are especially well suited to the use of chironomids to reconstruct Holocene temperatures. The inferred timing of warmth at our study site near Scoresby Sund agrees well with other nearby evidence, including glacial geological reconstructions and temperatures inferred from precipitation isotopes at Renland ice cap, supporting the use of chironomids to reconstruct temperatures at this site. We infer highest temperatures from c. 10 to 5.5 ka, followed by gradual cooling after 5.5 ka and progressively colder and less productive conditions after 3.5 ka. Models based upon two independent training sets yield similar inferred temperature trends, and suggest an average summer temperature anomaly from c. 10 to 5.5 ka of 3 to 4 °C relative to the preindustrial last millennium. The estimated overall rate of Neoglacial cooling averaged over the period from 5.5 to 0.5 ka was 0.6 to 0.8 °C per thousand years, more than twice the rate previously estimated for the Arctic as a whole. Given strong apparent spatial variability in Holocene climate around the Arctic, and the utility of palaeoclimate data for improving climate and ice‐sheet models, it should be a priority to further quantify past temperature changes around the margins of the Greenland Ice Sheet, where few quantitative reconstructions exist and future warming will affect global sea level.

Tropical Pacific climate variability over the last 6000 years as recorded in Bainbridge Crater Lake, Galápagos - Thompson, Diane M.; Conroy, Jessica L.; Collins, Aaron; Hlohowskyj, Stephan R.; Overpeck, Jonathan T.; Riedinger-Whitmore, Melanie; Cole, Julia E.; Bush, Mark B.; Whitney, H.; Corley, Timothy L.; Kannan, Miriam Steinitz (Paleoceanography, 2017)
Finely laminated sediments within Bainbridge Crater Lake, Galápagos, provide a record of El Niño–Southern Oscillation (ENSO) events over the Holocene. Despite the importance of this sediment record, hypotheses for how climate variability is preserved in the lake sediments have not been tested. Here we present results of long‐term monitoring of the local climate and limnology and a revised interpretation of the sediment record. Brown‐green, organic‐rich, siliciclastic laminae reflect warm, wet conditions typical of El Niño events, whereas carbonate and gypsum precipitate during cool, dry La Niña events and persistent dry periods, respectively. Applying this new interpretation, we find that ENSO events of both phases were generally less frequent during the mid‐Holocene (~6100–4000 calendar years B.P.) relative to the last ~1500 calendar years. Abundant carbonate laminations between 3500 and 3000 calendar years B.P. imply that conditions in the Galápagos region were cool and dry during this period when the tropical Pacific E‐W sea surface temperature (SST) gradient likely strengthened. The frequency of El Niño and La Niña events then intensified dramatically around 1750–2000 calendar years B.P., consistent with a weaker SST gradient and an increased frequency of ENSO events in other regional records. This strong interannual variability persisted until ~700 calendar years B.P., when ENSO‐related variability at the lake decreased as the SST gradient strengthened. Persistent, dry conditions then dominated between 300 and 50 calendar years B.P. (A.D. 1650–1900, ± ~100 years), whereas wetter conditions and frequent El Niño events dominated in the most recent century.
Keywords: Climate variability; El Niño–Southern Oscillation(ENSO); Galápagos archipelago; mid‐Holocene; monitoring; tropical Pacific Ocean

Utility of salt-marsh foraminifera, testate amoebae and bulk-sediment δ13C values as sea-level indicators in Newfoundland, Canada - Kemp, Andrew C.; Wright, Alexander J.; Barnett, Robert L.; Hawkes, Andrea D.; Charman, Dan J.; Sameshima, Colby; King, Alexandra N.; Mooney, Hailey C.; Edwards, Robin J.; Horton, Benjamin P.; van de Plassche, Orson (Marine Micropaleontology, 2017)
We investigated the utility of foraminifera, testate amoebae and bulk-sediment δ13C measurements for reconstructing Holocene relative sea level from sequences of salt-marsh sediment in Newfoundland, Canada. Modern, surface sediment was collected along transects from low to supra-tidal elevations in eastern (at Placentia) and western (at Hynes Brook and Big River) Newfoundland. Consistent with previous work, low-diversity assemblages of foraminifera display an almost binary division into a higher salt-marsh assemblage dominated by Jadammina macrescens and Balticammina pseudomacrescens and a lower salt-marsh assemblage comprised of Miliammina fusca. This pattern and composition resembles those identified at other high latitude sites with cool climates and confirms that foraminifera are sea-level indicators. The lowest occurrence of testate amoebae was at approximately mean higher high water. The composition of high salt-marsh testate amoebae assemblages (Centropyxis cassis type, Trinema spp., Tracheleuglypha dentata type, and Euglypha spp.) in Newfoundland was similar to elsewhere in the North Atlantic, but preservation bias favors removal of species with idiosomic tests over those with xenosomic tests. The mixed high salt-marsh plant community in Newfoundland results in bulk surface-sediment δ13C values that are typical of C3 plants, making them indistinguishable from freshwater sediment. Therefore we propose that the utility of this proxy for reconstructing RSL in eastern North America is restricted to the coastline between Chesapeake Bay and southern Nova Scotia. Using a simple, multi-proxy approach to establish that samples in three radiocarbon-dated sediment cores formed between the lowest occurrence of testate amoebae and the highest occurrence of foraminifera, we generated three example late Holocene sea-level index points at Hynes Brook.

What on Earth Have We Been Burning? Deciphering Sedimentary Records of Pyrogenic CarbonWhat on Earth Have We Been Burning? Deciphering Sedimentary Records of Pyrogenic Carbon - Hanke, Ulrich M.; Reddy, Christopher M.; Braun, Ana L. L.; Coppola, Alysha I.; Haghipour, Negar; McIntyre, Cameron P.; Wacker, Lukas; Xu, Li; McNichol, Ann P.; Abiven, Samuel; Schmidt, Michael W. I.; Eglinton, Timothy I. (Environmental Science & Technology, 2017)
Humans have interacted with fire for thousands of years, yet the utilization of fossil fuels marked the beginning of a new era. Ubiquitous in the environment, pyrogenic carbon (PyC) arises from incomplete combustion of biomass and fossil fuels, forming a continuum of condensed aromatic structures. Here, we develop and evaluate 14C records for two complementary PyC molecular markers, benzene polycarboxylic acids (BPCAs) and polycyclic aromatic hydrocarbons (PAHs), preserved in aquatic sediments from a suburban and a remote catchment in the United States (U.S.) from the mid-1700s to 1998. Results show that the majority of PyC stems from local sources and is transferred to aquatic sedimentary archives on subdecadal to millennial time scales. Whereas a small portion stems from near-contemporaneous production and sedimentation, the majority of PyC (∼90%) experiences delayed transmission due to “preaging” on millennial time scales in catchment soils prior to its ultimate deposition. BPCAs (soot) and PAHs (precursors of soot) trace fossil fuel-derived PyC. Both markers parallel historical records of the consumption of fossil fuels in the U.S., yet never account for more than 19% total PyC. This study demonstrates that isotopic characterization of multiple tracers is necessary to constrain histories and inventories of PyC and that sequestration of PyC can markedly lag its production.

The AD 1755 tsunami deposits onshore and offshore of Algarve (south Portugal): Sediment transport interpretations based on the study of Foraminifera assemblages - Maria Quintela; Pedro J.M. Costa; Francisco Fatela; Teresa Drago; Natalia Hoska; César Andrade; Maria C. Freitas (Quaternary International, 2016)
Abstract Tsunamis are amongst the most catastrophic natural hazards affecting worldwide coastal areas. Their impacts are recorded in the geological archives and its study provides crucial insights into the dynamics and intensity of these events. The accurate establishment of return periods can also be derived using sedimentological data. Onshore tsunami deposits have been extensively described over recent years through the application of a wide range of sedimentological proxies, including micropalaeontological analysis. In this work, the identification of palaeotsunami evidence, in both the onshore and offshore sedimentary record of south Portugal, was performed, relying mostly on the study of Foraminifera assemblages. Three onshore trenches and one offshore core were analyzed and imprints of the \{AD\} 1755 tsunami were observed based in the identification of allochthonous foraminiferal species, increase in the number of broken/abraded tests and its correlation with coarser mean grain size. This was possible after micropalaeontological environmental characterization of both low-energy onshore and offshore present-day sedimentation regimes. In the onshore record, three distinct sediment transport phases were differentiated within the tsunamigenic unit. The basal phase portraying the initial inundation represented by the dominance of marine Foraminifera species in a highly diverse assemblage. The higher energetic character of this phase was also reflected in the identification of the highest number of broken/abraded tests. The intermediate phase reflects an unspecified number of inundation and backwash pulses that were recognized based in the well-balanced presence of estuarine (brackish) and marine species, the sharp decrease in the diversity index and in the number of broken/abraded tests. The final phase recorded in the tsunamigenic unit registers the imprint of the last relevant backwash which was identified based on the dominance of estuarine (brackish) fauna. The overlying unit is dominated by tidal marsh species, demonstrating the start of the coastal system recovery phase. In the offshore record, it was possible to identify 2 distinct historical tsunami events (AD 1755 and \{AD\} 1969). This was achieved through the identification of significant increases in coastal Foraminifera species coupled with the presence of coarser layers. This interpretation was sustained by indirect age-estimation methods (radiocarbon and 210Pb) that ascribed compatible ages to the historical tsunami events. The results obtained in this study stress the relevance and innovative character of this onshore and offshore multiproxy approach in the recognition and understanding of tsunami events.
QuicklakeH Special Issue: Rapidly changing large lakes and human response
Keywords: Portugal

Age and growth of bluespine unicornfish (Naso unicornis): a half-century life-span for a keystone browser, with a novel approach to bomb radiocarbon dating in the Hawaiian Islands - Andrews, A.H.; DeMartini, Edward E.; Eble, Jeff A.; Taylor, Brett M.; Lou, Dong Chun; Humphreys, Robert L. (Canadian Journal of Fisheries and Aquatic Sciences, 2016)
Bluespine unicornfish (Naso unicornis) from Hawaii were aged to >50 years using cross-sectioned sagittal otoliths. Fish length was a poor indicator of age because of rapid and variable early growth, exemplified by fish aged to be 4 years near maximum length. Growth was deterministic with adult ages decoupled from body length. Otolith mass and thickness were evaluated as proxies for age and both were encouraging; thickness explained more variance but mass was easier to measure. An age estimation protocol was validated through ontogeny using bomb radiocarbon (14C) dating. Use of the postbomb 14C decline period from a regional reference chronology enabled age validation of young fish — a novel approach for the Pacific Ocean. A probabilistic procedure for assigning bomb 14C dates (CALIBomb) was used for the first time to determine fish birth years. The age-reading protocol was generally validated, and it was possible to describe length-at-age despite difficulties in counting otolith annuli beyond 30–40 years. Growth curves differed between the sexes, and a four-parameter generalized von Bertalanffy growth function provided the best fit.

Age of the Mt. Ortles ice cores, the Tyrolean Iceman and glaciation of the highest summit of South Tyrol since the Northern Hemisphere Climatic Optimum - Gabrielli, Paolo; Barbante, Carlo; Bertagna, Giuliano; ó, Michele; Binder, Daniel; Carton, Alberto; Carturan, Luca; Cazorzi, Federico; Cozzi, Giulio; Dalla Fontana, Giancarlo; Davis, Mary; De Blasi, Fabrizio; et al. (The Cryosphere, 2016)
In 2011 four ice cores were extracted from the summit of Alto dell’Ortles (3859 m), the highest glacier of South Tyrol in the Italian Alps. This drilling site is located only 37 km southwest from where the Tyrolean Iceman, ∼5.3 kyrs old, was discovered emerging from the ablating ice field of Tisenjoch (3210 m, near the Italian–Austrian border) in 1991. The excellent preservation of this mummy suggested that the Tyrolean Iceman was continuously embedded in prehistoric ice and that additional ancient ice was likely preserved elsewhere in South Tyrol. Dating of the ice cores from Alto dell’Ortles based on 210Pb, tritium, beta activity and 14C determinations, combined with an empirical model (COPRA), provides evidence for a chronologically ordered ice stratigraphy from the modern glacier surface down to the bottom ice layers with an age of ∼7 kyrs, which confirms the hypothesis. Our results indicate that the drilling site has continuously been glaciated on frozen bedrock since ∼7 kyrs BP. Absence of older ice on the highest glacier of South Tyrol is consistent with the removal of basal ice from bedrock during the Northern Hemisphere Climatic Optimum (6–9 kyrs BP), the warmest interval in the European Alps during the Holocene. Borehole inclinometric measurements of the current glacier flow combined with surface ground penetration radar (GPR) measurements indicate that, due to the sustained atmospheric warming since the 1980s, an acceleration of the glacier Alto dell’Ortles flow has just recently begun. Given the stratigraphic chronological continuity of the Mt. Ortles cores over millennia, it can be argued that this behaviour has been unprecedented at this location since the Northern Hemisphere Climatic Optimum.

Anatomy of Labrador Sea Heinrich layers - Reinhard Hesse; Saeed Khodabakhsh (Marine Geology, 2016)
Abstract Heinrich layers (H-layers) are distinct, decimetre to centimetre thick layers of ice-rafted debris (IRD) that were deposited in the North Atlantic during the Late and middle Pleistocene. H-layers (H-layers) are characterized by high detrital carbonate and low foraminifera contents. In the Labrador Sea, H-layers reach metre thickness in some proximal core sites near the iceberg source of the Hudson Strait ice stream and show five distinct depositional facies involving sediment lofting and low-density turbidity currents as sediment delivery processes besides ice rafting. Thick massive ice-rafted layers (type I H-layers) occur in the most proximal parts of H-layer 3 and older H-layers. Within 300 km distance from the assumed Hudson Strait ice stream terminus, H-layers somewhat more distal than type I H-layers consist predominantly of stacked thin layers of graded muds containing İRD\} (type İI\} H-layers). The graded muds that are spiked with İRD\} resulted from the deposition of fine-grained lofted sediment that collected dropstones and grains under the iceberg route. At greater distance from the Hudson Strait outlet on the slope and rise south of the strait, H-layers on the levees of tributary canyons to the Northwest Atlantic Mid-Ocean Channel (NAMOC) consist of alternations of thin mud turbidites with intercalated laminae of İRD\} (type İII\} H-layers). On the levees of NAMOC, type İV\} H-layers consist of layers of İRD\} alternating with fewer fine-grained spill-over turbidites, because the spill-over frequency from the deep channel was less than that from the less deep canyons on the slope. Type V is made up of bioturbated hemipelagic muds with coarser İRD\} and occurs in regions between canyons not reached by spill-over turbidity currents and in distal regions of the open ocean or on seamounts. Transport of significant portions of the sediment in H-layers by suspended sediment columns lofted from sand-carrying fresh-water turbidity currents (type II) and by low-density turbidity currents (types İII\} and IV) explains the high percentage of detrital carbonate in the fine (< 63 μm) grain-size fractions (> 80% of the total detrital carbonate of the bulk sediment), which cannot be derived from icebergs alone. It also explains the low magnetic susceptibility and low grey levels on the colour scale compared to H-layers in the North Atlantic east of Greenland. The anomalously great thickness of individual H-layers on the slope and rise off the Hudson Strait as documented in isopach maps reflects the combined effect of the various processes involved in their deposition. Four hypotheses for the origin of H-events are discussed — (i) the binge–purge model, (ii) the subglacial outburst–flow model, (iii) the external forcing model, and (iv) the catastrophic ice-shelf break-up model
Keywords: Ice-proximal environments

Arctic Deltaic Lake Sediments As Recorders of Fluvial Organic Matter Deposition - Vonk, Jorien E.; Dickens, Angela F.; Giosan, Liviu; Hussain, Zainab A.; Kim, Bokyung; Zipper, Samuel C.; Holmes, Robert M.; Montluçon, Daniel B.; Galy, Valier; Eglinton, Timothy I. (2016)
Arctic deltas are dynamic and vulnerable regions that play a key role in land-ocean interactions and the global carbon cycle. Delta lakes may provide valuable historical records of the quality and quantity of fluvial fluxes, parameters that are challenging to investigate in these remote regions. Here we study lakes from across the Mackenzie Delta, Arctic Canada, that receive fluvial sediments from the Mackenzie River when spring flood water levels rise above natural levees. We compare downcore lake sediments with suspended sediments collected during the spring flood, using bulk (% organic carbon, % total nitrogen, 13C, 14C) and molecular organic geochemistry (lignin, leaf waxes). High-resolution age models (137Cs, 210Pb) of downcore lake sediment records (n=11) along with lamina counting on high-resolution radiographs show sediment deposition frequencies ranging between annually to every 15 years. Down-core geochemical variability in a representative delta lake sediment core is consistent with historical variability in spring flood hydrology (variability in peak discharge, ice jamming, peak water levels). Comparison with earlier published Mackenzie River depth profiles shows that (i) lake sediments reflect the riverine surface suspended load, and (ii) hydrodynamic sorting patterns related to spring flood characteristics are reflected in the lake sediments. Bulk and molecular geochemistry of suspended particulate matter from the spring flood peak and lake sediments are relatively similar showing a mixture of modern higher-plant derived material, older terrestrial permafrost material, and old rock-derived material. This suggests that deltaic lake sedimentary records hold great promise as recorders of past (century-scale) riverine fluxes and may prove instrumental in shedding light on past behaviour of arctic rivers, as well as how they respond to a changing climate.

Clumped isotope composition of cold-water corals: A role for vital effects? - Peter T. Spooner; Weifu Guo; Laura F. Robinson; Nivedita Thiagarajan; Katharine R. Hendry; Brad E. Rosenheim; Melanie J. Leng (Geochimica et Cosmochimica Acta, 2016)
Abstract The carbonate clumped isotope thermometer is a promising tool for determining past ocean temperatures. It is based on the temperature dependence of rare isotopes ‘clumping’ into the same carbonate ion group in the carbonate mineral lattice. The extent of this clumping effect is independent of the isotope composition of the water from which carbonate precipitates, providing unique advantages over many other paleotemperature proxies. Existing calibrations of this thermometer in cold-water and warm-water corals suggest clumped isotope ‘vital effects’ are negligible in cold-water corals but may be significant in warm-water corals. Here, we test the calibration of the carbonate clumped isotope thermometer in cold-water corals with a recently collected and well characterised sample set spanning a range of coral genera (Balanophyllia, Caryophyllia, Dasmosmilia, Desmophyllum, Enallopsammia and Javania). The clumped isotope compositions (Δ47) of these corals exhibit systematic dependences on their growth temperatures, confirming the basis of the carbonate clumped isotope thermometer. However, some cold-water coral genera show Δ47 values that are higher than the expected equilibrium values by up to 0.05‰ (equivalent to underestimating temperature by ∼9 °C) similar to previous findings for some warm-water corals. This finding suggests that the vital effects affecting corals Δ47 are common to both warm- and cold-water corals. By comparison with models of the coral calcification process we suggest that the clumped isotope offsets in these genera are related to the kinetic isotope effects associated with \{CO2\} hydration/hydroxylation reactions in the corals’ calcifying fluid. Our findings complicate the use of the carbonate clumped isotope thermometer in corals, but suggest that species- or genus-specific calibrations could be useful for the future application of this paleotemperature proxy.

Comparison of eastern tropical Pacific TEX 86 and Globigerinoides ruber Mg/Ca derived sea surface temperatures: Insights from the Holocene and Last Glacial Maximum - Hertzberg, Jennifer E.; Schmidt, Matthew W.; Bianchi, Thomas S.; Smith, Richard W.; Shields, Michael R.; Marcantonio, Franco (Earth and Planetary Science Letters, 2016)
The use of the TEX86TEX86 temperature proxy has thus far come to differing results as to whether TEX86TEX86 temperatures are representative of surface or subsurface conditions. In addition, although TEX86TEX86 temperatures might reflect sea surface temperatures based on core-top (Holocene) values, this relationship might not hold further back in time. Here, we investigate the TEX86TEX86 temperature proxy by comparing TEX86TEX86 temperatures to Mg/Ca temperatures of multiple species of planktonic foraminifera for two sites in the eastern tropical Pacific (on the Cocos and Carnegie Ridges) across the Holocene and Last Glacial Maximum. Core-top and Holocene View the MathML sourceTEX86H temperatures at both study regions agree well, within error, with the Mg/Ca temperatures of Globigerinoides ruber , a surface dwelling planktonic foraminifera. However, during the Last Glacial Maximum, View the MathML sourceTEX86H temperatures are more representative of upper thermocline temperatures, and are offset from G. ruber Mg/Ca temperatures by 5.8 °C and 2.9 °C on the Cocos Ridge and Carnegie Ridge, respectively. This offset between proxies cannot be reconciled by using different TEX86TEX86 temperature calibrations, and instead, we suggest that the offset is due to a deeper export depth of GDGTs at the LGM. We also compare the degree of glacial cooling at both sites based on both temperature proxies, and find that View the MathML sourceTEX86H temperatures greatly overestimate glacial cooling, especially on the Cocos Ridge. This study has important implications for applying the TEX86TEX86 paleothermometer in the eastern tropical Pacific.
Keywords: Foraminifera; Holocene; LGM; Pacific Ocean; Mg/Ca; TEX86TEX86

Complex coastal change in response to autogenic basin infilling: An example from a sub-tropical Holocene strandplain - Hein, Christopher J.; FitzGerald, Duncan M.; de Souza, Luis H. P.; Georgiou, Ioannis Y.; Buynevich, Ilya V.; Klein, Antonio H. da F.; de Menezes, ão Thadeu; Cleary, William J.; Scolaro, Thelma L. (Sedimentology, 2016)
Thick bay-fill sequences that often culminate in strandplain development serve as important sedimentary archives of land–ocean interaction, although distinguishing between internal and external forcings is an ongoing challenge. This study employs sediment cores, ground-penetrating radar surveys, radiocarbon dates, palaeogeographic reconstructions and hydrodynamic modelling to explore the role of autogenic processes – notably a reduction in wave energy in response to coastal embayment infilling – in coastal evolution and shoreline morphodynamics. Following a regional 2 to 4 m highstand at ca 5·8 ka, the 75 km2 Tijucas Strandplain in southern Brazil built from fluvial sediments deposited into a semi-enclosed bay. Holocene regressive deposits are underlain by fluvial sands and a Pleistocene transgressive–regressive sequence, and backed by a highstand barrier-island. The strandplain is immediately underlain by 5 to 16 m of seaward-thickening, fluvially derived, Holocene-age, basin-fill mud. Several trends are observed from the landward (oldest) to the seaward (youngest) sections of the strandplain: (i) the upper shoreface and foreshore become finer and thinner and shift from sand-dominated to mud-dominated; (ii) beachface slopes decrease from >11° to ca 7°; and (iii) progradation rates increase from 0·4 to 1·8 m yr−1. Hydrodynamic modelling demonstrates a correlation between progressive shoaling of Tijucas Bay driven by sea-level fall and sediment infilling and a decrease in onshore wave-energy transport from 18 to 4 kW m−1. The combination of allogenic (sediment supply, falling relative sea-level and geology) and autogenic (decrease in wave energy due to bay shoaling) processes drove the development of a regressive system with characteristics that are rare, if not unique, in the Holocene and rock records. These findings demonstrate the complexities in architecture styles of highstand and regressive systems tracts. Furthermore, this article highlights the diverse internal and external processes and feedbacks responsible for the development of these intricate marginal marine sedimentary systems.

Controls on the stratigraphic framework and paleoenvironmental change within a Holocene estuarine system: Pamlico Sound, North Carolina, USA - Nicholas Zaremba; David J. Mallinson; Eduardo Leorri; Stephen Culver; Stanley Riggs; Ryan Mulligan; Eric Horsman; Siddhartha Mitra (Marine Geology, 2016)
Abstract This study examines the Holocene stratigraphic record and paleoenvironmental evolution of a large estuarine system, at high temporal and spatial resolution, in the context of changing climate, sea level, and hydrodynamics. New data are used to examine two time periods of increased marine influence within Pamlico Sound in northeastern North Carolina interpreted to be the result of extensive barrier island segmentation synchronous with periods of rapid climate change during the late Holocene. The study reveals the controls on the stratigraphic development and the highly dynamic character of the coastal system in response to climate, and sea-level change as it interacts with paleotopography. These findings can be used to inform projections of future environmental changes. Estuarine waters occupied paleovalleys in the Pamlico Sound region as early as ca. 7500 cal \{BP\} and Pleistocene interfluves separated the paleovalleys from the Atlantic Ocean until ca. 5500 cal BP, when they were flooded by rising sealevel forming the broad, shallow Pamlico Sound. Initial barrier islands and shoals likely formed sometime between 5500 and 5000 cal BP, providing the geomorphic setting for continued estuarine conditions behind the barriers. At ca. 4000 cal BP, an increase in marine influence and sand content is detected in multiple cores, and is correlated to seismic data within the Pamlico Sound basin. This change is interpreted to be the result of increased segmentation of barrier islands (thus a greater number of inlets, or wider inlets), which is consistent with a rapid transgression seen in other areas of the U.S. east coast. The segmentation may have been partially facilitated by a rapid increase in lagoonal area and tidal prism by overtopping of interfluves. Greater barrier island continuity is evident from 3500 to 1200 cal BP, as indicated by muddy deposits with low brackish estuarine foraminiferal assemblages. At ca. 1200 cal BP, seismic, sedimentological and micropaleontological data suggest an increase in wave and current energy and marine influence throughout southeastern Pamlico Sound. These changes are interpreted to represent extensive segmentation of the barrier islands during the Medieval Climate Anomaly (MCA). Since ca. 500 cal BP, the Pamlico Sound system has returned to a more restricted state, as inlets have closed. Currently only three major inlets segment the Outer Banks, the barrier island system fronting Pamlico Sound, but warming climate and increasing rates of sea-level rise suggest that another episode of barrier island segmentation began about a half century ago and appears that it may extend into the near future.
Keywords: Coastal geology

Detrital cave sediments record Late Quaternary hydrologic and climatic variability in northwestern Florida, USA - Winkler, Tyler S.; van Hengstum, Peter J.; Horgan, Meghan C.; Donnelly, Jeffrey P.; Reibenspies, Joseph H. (Sedimentary Geology, 2016)
Detrital sediment in Florida's (USA) submerged cave systems may preserve records of regional climate and hydrologic variability. However, the basic sedimentology, mineralogy, stratigraphic variability, and emplacement history of the successions in Florida's submerged caves remains poorly understood. Here we present stratigraphic, mineralogical, and elemental data on sediment cores from two phreatic cave systems in northwestern Florida (USA), on the Dougherty Karst Plain: Hole in the Wall Cave (HITW) and Twin Cave. Water flowing through these caves is subsurface flow in the Apalachicola River drainage basin, and the caves are located just downstream from Jackson Blue (1st magnitude spring, > 2.8 m3 s− 1 discharge). Sedimentation in these caves is dominated by three primary sedimentary styles: (i) ferromanganese deposits dominate the basal recovered stratigraphy, which pass upsection into (ii) poorly sorted carbonate sediment, and finally into (iii) fine-grained organic matter (gyttja) deposits. Resolving the emplacement history of the lower stratigraphic units was hampered by a lack of suitable material for radiocarbon dating, but the upper organic-rich deposits have a punctuated depositional history beginning in the earliest Holocene. For example, gyttja primarily accumulated in HITW and Twin Caves from ~ 5500 to 3500 cal yr. BP, which coincides with regional evidence for water-table rise of the Upper Floridian Aquifer associated with relative sea-level rise in the Gulf of Mexico, and evidence for invigorated drainage through the Apalachicola River drainage basin. Gyttja sediments were also deposited in one of the caves during the Bølling/Allerød climate oscillation. Biologically, these results indicate that some Floridian aquatic cave (stygobitic) ecosystems presently receive minimal organic matter supply in comparison to prehistoric intervals. The pre-Holocene poorly sorted carbonate sediment contains abundant invertebrate fossils, and likely documents a period of enhanced limestone dissolution and cave formation (speleogenesis) during lower paleo water levels. Further work is still required to (a) determine whether precipitation of the ferromanganese deposits is inorganically or biologically mediated, (b) temporally constrain the emplacement history of the primary sedimentary styles, and (c) determine the full geographic extent of these sedimentary signals. However, these preliminary observations suggest that sedimentation in the inland underwater caves of northwestern Florida is related to Quaternary-scale hydrographic variability in the Apalachicola River drainage basin in response to broader ocean and atmospheric forcing.
Keywords: Apalachicola; florida; Karst; Phreatic; Underwater cave

Differences in coastal subsidence in southern Oregon (USA) during at least six prehistoric megathrust earthquakes - Milker, Yvonne; Nelson, Alan R.; Horton, Benjamin P.; Engelhart, Simon E.; Bradley, Lee-Ann; Witter, Robert C. (Quaternary Science Reviews, 2016)
Stratigraphic, sedimentologic (including CT 3D X-ray tomography scans), foraminiferal, and radiocarbon analyses show that at least six of seven abrupt peat-to-mud contacts in cores from a tidal marsh at Talbot Creek (South Slough, Coos Bay), record sudden subsidence (relative sea-level rise) during great megathrust earthquakes at the Cascadia subduction zone. Data for one contact are insufficient to infer whether or not it records a great earthquake—it may also have formed through local, non-seismic, hydrographic processes. To estimate the amount of subsidence marked by each contact, we expanded a previous regional modern foraminiferal dataset to 174 samples from six Oregon estuaries. Using a transfer function derived from the new dataset, estimates of coseismic subsidence across the six earthquake contacts vary from 0.31 m to 0.75 m. Comparison of subsidence estimates for three contacts in adjacent cores shows within-site differences of ≤0.10 m, about half the ±0.22 m error, although some estimates may be minimums due to uncertain ecological preferences for Balticammina pseudomacrescens in brackish environments and almost monospecific assemblages of Miliammina fusca on tidal flats. We also account for the influence of taphonomic processes, such as infiltration of mud with mixed foraminiferal assemblages into peat, on subsidence estimates. Comparisons of our subsidence estimates with values for correlative contacts at other Oregon sites suggest that some of our estimates are minimums and that Cascadia's megathrust earthquake ruptures have been heterogeneous over the past 3500 years.
Keywords: Cascadia subduction zone; Coseismic subsidence; Megathrust earthquakes; Paleoseismology; Salt-marsh foraminifera; Sea-level change; Transfer functions

Factors influencing 14C concentrations of algal and archaeal lipids and their associated sea surface temperature proxies in the Black Sea - Stephanie Kusch; Janet Rethemeyer; Ellen C. Hopmans; Lukas Wacker; Gesine Mollenhauer (Geochimica et Cosmochimica Acta, 2016)
Abstract Understanding the preservation and deposition history of organic molecules is crucial for the understanding of paleoenvironmental information contained in their abundance ratios such as Uk′37 and \{TEX86\} used as proxies for sea surface temperature (SST). Based on their relatively high refractivity, alkenones and glycerol dialkyl glycerol tetraethers (GDGTs) can survive postdepositional processes like lateral transport, potentially causing inferred \{SSTs\} to be misleading. Likewise, selective preservation of alkenones and \{GDGTs\} may cause biases of the \{SST\} proxies themselves and can lead to decoupling of both proxy records. Here we report compound-specific radiocarbon data of marine biomarkers including alkenones, GDGTs, and low molecular weight (LMW) n-fatty acids from Black Sea sediments deposited under different redox regimes to evaluate the potentially differential preservation of both biomarker classes and its effect on the \{SST\} indices Uk′37 and TEX86. The decadal Δ14C values of alkenones, GDGTs, and \{LMW\} n-fatty acids indicate similar preservation under oxic, suboxic, and anoxic redox regimes and no contribution of pre-aged compounds, e.g., by lateral supply. Moreover, similar 14C concentrations of crenarchaeol, alkenones, and \{LMW\} n-fatty acids imply that the thaumarchaeotal \{GDGTs\} preserved in these sediments are produced in the euphotic zone rather than in subsurface/thermocline waters. However, we observe biomarker-based \{SSTs\} that strongly deviate (ΔSST up to 8.4 °C) from in situ measured mean annual \{SSTs\} in the Black Sea. This is not due to redox-dependent differential biomarker preservation as implied by their Δ14C values and spatial \{SST\} pattern. Since contributions from different sources can largely be excluded, the deviation of the Uk′37 and \{TEX86\} proxy-derived \{SSTs\} from in situ \{SSTs\} requires further study of phylogenetic and other yet unknown environmental controls on alkenone and \{GDGT\} lipid distributions in the Black Sea.
Keywords: sea surface temperature proxies; TEX86; Uk37; Uk′37

Incorporation of bomb-produced 14C into fish otoliths: A novel approach for evaluating age validation and bias with an application to yellowfin sole and northern rockfish - Kastelle, Craig R.; Helser, Thomas E.; Wischniowski, Stephen G.; Loher, Timothy; Goetz, Betty J.; Kautzi, Lisa A. (Ecological Modelling, 2016)
Fish age validation with bomb-produced radiocarbon (14C) requires a known-age Δ14C reference chronology spanning the era of a marine increase in bomb-produced 14C (1950s to 1960s). Concordance between otolith Δ14C in a validation sample and the reference chronology indicates accurate test ages. Here, we present an information-theoretic approach to hypothesis testing and use Bayesian data analysis with Markov chain Monte Carlo simulation as a probabilistic framework to quantitatively estimate age determination bias and its uncertainty. Using this approach, we compare a new Δ14C reference chronology from the eastern Bering Sea and a previously established reference from the Gulf of Alaska with otolith Δ14C in two validation species, eastern Bering Sea yellowfin sole (Limanda aspera) and Gulf of Alaska northern rockfish (Sebastes polyspinis). Our goals were twofold: (i) to validate the age determination methods for northern rockfish and yellowfin sole using comparisons within oceanic basins, and (ii) to explore the outcome of making naïve comparisons of these validation data sets to reference chronologies across oceanic basins. Based on within-basin comparisons we concluded that estimated ages for eastern Bering Sea yellowfin sole and Gulf of Alaska northern rockfish were accurate. We further concluded that there were important differences in otolith 14C uptake between fish from the two ocean basins.

A major increase in winter snowfall during the middle Holocene on western Greenland caused by reduced sea ice in Baffin Bay and the Labrador Sea - Thomas, Elizabeth K.; Briner, Jason P.; Ryan-Henry, John J.; Huang, Yongsong (Geophysical Research Letters, 2016)
Recent observations indicate that ice-ocean interaction drives much of the recent increase in mass loss from the Greenland Ice Sheet; however, the role of ocean forcing in driving past glacier change is poorly understood. To extend the observational record and our understanding of the ocean-cryosphere link, we used a multi-proxy approach that combines new data from proglacial lake sediments, C-14-dated in situ moss that recently emerged from beneath cold-based ice caps, and Be-10 ages to reconstruct centennial-scale records of mountain glacier activity for the past similar to 10 k. y. in West Greenland. Proglacial lake sediment records and C-14 dating of moss indicate the onset of Neoglaciation in West Greenland at ca. 5 ka with substantial snowline lowering and glacier expansion at ca. 3.7 ka followed by additional ice expansion phases at ca. 2.9, ca. 1.7, and ca. 1.4 ka and during the Little Ice Age. We find that widespread glacier growth at ca. 3.7 ka in West Greenland coincides with marked cooling and reduced strength of the West Greenland Current in Disko Bugt. The transition to cooler ocean conditions at ca. 3.7 ka identified in Disko Bugt is registered by marine proxy data farther afield in East Greenland and on the northwestern Icelandic shelf, implying large-scale paleoceanographic changes across the North Atlantic during this interval. The similarity between glacier change on West Greenland and multiple marine and terrestrial records across the North Atlantic suggests that glaciers are strongly influenced by changes in ocean circulation and consequently implies that the ocean-cryosphere teleconnection is a persistent feature of the Arctic system.

Micropaleontologic record of Pliocene and Quaternary paleoenvironments in the southern Albemarle Embayment, North Carolina, U.S.A - Stephen J. Culver; Kathleen M. Farrell; David J. Mallinson; Debra A. Willard; Benjamin P. Horton; Stanley R. Riggs; E. Robert Thieler; John F. Wehmiller; Peter R. Parham; Jessica Pierson Moore; Scott W. Snyder; Caroline Hillier (Palaeogeography, Palaeoclimatology, Palaeoecology, 2016)
Abstract The Albemarle Embayment, a Cenozoic depositional basin on the Atlantic coast of the USA, is an ideal setting to understand the temporal and spatial variation of eustatic sea-level fluctuations, glacio-hydro-isostasy, tectonics, subsidence, environments and sedimentation patterns of a passive margin Quaternary section. A NE–SW transect of cores and seismic data in the southern Albemarle Embayment were analyzed using micropaleontologic (foraminifera, diatoms, pollen), sedimentologic, stratigraphic, and geochronologic data to reconstruct the paleoenvironmental evolution and paleoclimates in the nearly 90 m thick Quaternary section. The study area is a very low gradient Quaternary landscape that is cross-cut by several Pleistocene incised valleys; a Holocene barrier island complex forms its eastern margin. In the subsurface, the Albemarle Embayment is bordered to the north by the Norfolk Arch and to the south by the depositionally-constructed Cape Lookout High, which is positioned on the northern flank of the structural Carolina Platform. The Quaternary section overlies mid-Pliocene carbonates in three cores; the contact rises in elevation towards the Cape Lookout High. Fossils and sediment characteristics suggest a subtropical, shallow, high energy marine environment during the Pliocene. Overlying units include incomplete Pleistocene, clastic, transgressive-regressive (T-R) deposits. These have similar ages and stratigraphic signatures as the T-R cycles in the central and north-central Albemarle Embayment, although mid-Pleistocene deposits may be older in the southern region. The bulk of the early and mid-Pleistocene record consists of inner to mid-shelf sand and muddy sand. In contrast, late Pleistocene sands are of inner shelf origin, reflecting the infilling of the basin. Lowstand paleovalleys, with fluvial, wetland and estuarine fill, dissect the early, mid- and late Pleistocene marine units; their locations reflect antecedent topography. Holocene sediments were deposited in shoreface and barrier island environments. Quaternary foraminiferal assemblages in the southern Albemarle Embayment exhibit greater species richness than those in the central and north-central embayment reflecting the presence of a major biogeographic boundary at the same location as the modern biogeographic boundary at Cape Hatteras.
Keywords: Holocene

A new late Quaternary palaeohydrological record from the humid tropics of northeastern Australia - M.A. Burrows; H. Heijnis; P. Gadd; S.G. Haberle (Palaeogeography, Palaeoclimatology, Palaeoecology, 2016)
Abstract High resolution X-ray fluorescence (XRF) is presented as a robust palaeoclimatic proxy, suitable for use on Late Pleistocene to Holocene sediments located in a volcanic crater on the Atherton Tableland in northeastern Queensland, Australia. The proxy allows identification of wet and dry shifts in a complex sedimentary sequence comprised of peat, gyttja, laminated organic rich muds and fine clastic silt-rich sediments. Significant correlation is found between the \{XRF\} record and other proxies including magnetic susceptibility, humification, grain size, macrocharcoal, δ13C and C/N and pollen. Sixteen wetter periods are identified in the 37 ka sedimentary record for Bromfield Swamp. Three wetter periods commence in late Marine Isotope Stage 3, nine in the early glacial, one in the late de-glacial and four in Holocene. Nineteen drier periods are identified, four in late \{MIS\} 3, seven in the early glacial, one during the LGM, one in the late de-glacial period and six in the Holocene. The \{XRF\} record for Bromfield Swamp is specifically used to identify periods of abrupt climate change. Marked changes in effective precipitation are detected at 32,690, 30,080, 24,660, 21,870, 11,880, 10,020, 9170 and 5120 cal. yr BP. The detection of these abrupt climate events may allow correlation with records from terrestrial sites across the Southern Hemisphere and potentially, the Northern Hemisphere.
Keywords: Late Quaternary

Parent material influence on soil response to vegetation change, Southeastern Minnesota, U.S.A. - Joseph A. Mason; Peter M. Jacobs; Kristine E. Gruley; Paul Reyerson; Paul R. Hanson (Geoderma, 2016)
Abstract Soil morphology changes dramatically across the former transition from forest to grassland in the Midwestern U.S.A. That vegetation boundary shifted as a result of Holocene climatic change and fire suppression following Euroamerican settlement, but the timescale of soil response to those vegetation changes and the factors that influence it are poorly known. On steep colluvial slopes of southeastern Minnesota, Mollisols with thick, dark A horizons typically associated with grassland are found today under deciduous forest. Soils with much thinner and/or lighter-colored A horizons occur immediately up- and downslope of the forest-covered Mollisols. Most of the soils with thick A horizons are not in topographic settings found to favor organic matter accumulation in other landscapes. Principal component analysis highlights important axes of textural and mineralogical variation among horizons of these soils, often related to parent material properties. Soils with and without thick A horizons are separated along one principal component heavily loaded by high pH, reflecting the presence of dolomite fragments in the hillslope sediment that soils with thick, dark A horizons formed in. Stable C isotope analysis reveals that the Mollisols with thick, dark A horizons under forest had C input from vegetation with abundant \{C4\} grasses in the past. Public land survey data also indicate replacement of grassland or savanna by forest since 1854 on colluvial slopes where forest-covered Mollisols occur today. We propose that the soils with thick, dark A horizons under forest today reflect a lagged response to vegetation change, from grassland or savanna to closed forest. Their thick A horizons and some C4-derived organic matter may be preserved because dolomite weathering releases abundant Ca++ and Mg++ that favor aggregation and organic matter stabilization. Soils with thin A horizons just up- or downslope may also have formed partly under grasses, but have responded more quickly and/or more substantially to vegetation change.
Keywords: Parent material

Prehistoric human responses to volcanic tephra fall events in the Ust-Kamchatsk region, Kamchatka Peninsula (Kamchatsky Krai, Russian Federation) during the middle to late Holocene (6000–500 cal BP) - I. Florin Pendea; Hans Harmsen; Dustin Keeler; Ezra B.W. Zubrow; Gregory Korosec; Erika Ruhl; Irina Ponkratova; Eva Hulse (Quaternary International, 2016)
Abstract Prehistoric peoples in Kamchatka coped with recurrent volcanic tephra fall events during the middle to late Holocene. Recent data collected by the International Collaborative Circumpolar Archaeological Project (ICAAP) between 2009 and 2011 explores the long-term relationships between drastic landscape change and concomitant human response. A combination of new archaeological, paleoenvironmental and tephrochronological data demonstrate how the major Ksudach 1750 cal BP (KS1) eruption accelerated settlement relocation from the interior to the paleo-coastline.
Volcanic Activity and Human Society
Keywords: Tephra

Relative sea-level change in northeastern Florida (USA) during the last ∼8.0 ka - Hawkes, Andrea D.; Kemp, Andrew C.; Donnelly, Jeffrey P.; Horton, Benjamin P.; Peltier, W. Richard; Cahill, Niamh; Hill, David F.; Ashe, Erica; Alexander, Clark R. (Quaternary Science Reviews, 2016)
An existing database of relative sea-level (RSL) reconstructions from the U.S. Atlantic coast lacked valid sea-level index points from Georgia and Florida. This region lies on the edge of the collapsing forebulge of the former Laurentide Ice Sheet making it an important location for understanding glacio-isostatic adjustment and the history of ice-sheet melt. To address the paucity of data, we reconstruct RSL in northeastern Florida (St. Marys) over the last ∼8.0 ka from samples of basal salt-marsh sediment that minimize the influence of compaction. The analogy between modern salt-marsh foraminifera and their fossil counterparts preserved in the sedimentary record was used to estimate paleomarsh surface elevation. Sample ages were determined by radiocarbon dating of identifiable and in-situ plant macrofossils. This approach yielded 25 new sea-level index points that constrain a ∼5.7 m rise in RSL during the last ∼8.0 ka. The record shows that no highstand in sea level occurred in this region over the period of the reconstruction. We compared the new reconstruction to Earth-ice models ICE 6G-C VM5a and ICE 6G-C VM6. There is good fit in the later part of the Holocene with VM5a and for a brief time in the earlier Holocene with VM6. However, there are discrepancies in model-reconstruction fit in the early to mid Holocene in northeastern Florida and elsewhere along the Atlantic coast at locations with early Holocene RSL reconstructions. The most pronounced feature of the new reconstruction is a slow down in the rate of RSL rise from approximately 5.0 to 3.0 ka. This trend may reflect a significant contribution from local-scale processes such as tidal-range change and/or change in base flow of the St. Marys River in response to paleoclimate changes. However, the spatial expression (local vs. regional) of this slow down is undetermined and corroborative records are needed to establish its geographical extent.
Keywords: Foraminifera; Georgia; Holocene; Salt marsh; St. Marys River

Sedimentation of particulate organic carbon on the Amundsen Shelf, Antarctica - Minkyoung Kim; Jeomshik Hwang; Sang H. Lee; Hyung J. Kim; Dongseon Kim; Eun J. Yang; SangHoon Lee (Deep Sea Research Part II: Topical Studies in Oceanography, 2016)
Abstract We examined the recent history of sedimentary organic carbon (SOC) accumulation on the western Amundsen Shelf, to help characterize the biological carbon pump in the Amundsen Sea, Antarctica. Vertical sedimentary profiles (in the upper 21-cm) of \{SOC\} content, radio- and stable-carbon isotopes were obtained at four locations in the western Amundsen Sea: near the shelf break, inside the polynya near the Dotson Ice Shelf, and at both the periphery and the center of the Amundsen Sea polynya. Profiles were representative not only of various distances from the coast, but also of various summertime sea ice conditions and bottom depths. The \{SOC\} content (up to 1.1%) and the radiocarbon content were distinctly higher at the periphery and at the center of the polynya than at the other sites. The \{SOC\} and 14C contents were generally consistent with the spatial distribution of primary productivity in the surface water. A linear \{SOC\} accumulation rate of about 1.0 g C m−2 yr−1 was determined from the conventional 14C ages of bulk \{SOC\} below the surface mixed layer at the periphery and at the center of the polynya, for the time period of 3.1–4.7 kyr before present (BP). This linear \{SOC\} accumulation rate was about 20 times greater than the rates determined at the two other sites for the period of 4.6–15.7 kyr BP. Note that all values are for uncorrected 14C ages. At the center of the polynya, a sudden change in \{SOC\} accumulation rate was observed at about 16 cm depth, corresponding to 4.7 kyr BP, implying that changes (during this time period) in physical environments greatly affected primary production, \{SOC\} burial and/or supply of allochthonous particles to this site. The vertical distribution of 14C content in the sediments implies that aged organic matter, likely associated with resuspended sediments, was also being deposited inside the polynya, in addition to autochthonous biogenic particles. If our estimation of \{SOC\} accumulation is extrapolated to the western Amundsen Shelf between 110°W and 120°W, approximately 3×1010 g C yr−1 is buried on the shelf, with  90% of \{SOC\} accumulation occurring in the Amundsen Sea polynya.
International efforts to understanding of the changing Antarctic climate: The \{KOPRI\} expedition to the Amundsen Sea
Keywords: Global carbon cycling

Sedimentation, stratigraphy and physical properties of sediment on the Juan de Fuca Ridge - K.M. Costa; J.F. McManus; B. Boulahanis; S.M. Carbotte; G. Winckler; P.J. Huybers; C.H. Langmuir (Marine Geology, 2016)
Abstract Sedimentation near mid-ocean ridges may differ from pelagic sedimentation due to the influence of the ridges' rough topography on sediment deposition and transport. This study explores whether the near-ridge environment responds to glacial-interglacial changes in climate and oceanography. New benthic δ18O, radiocarbon, multi-sensor track, and physical property (sedimentation rates, density, magnetic susceptibility) data for seven cores on the Juan de Fuca Ridge provide multiple records covering the past 700,000 years of oceanographic history of the Northeast Pacific Ocean. Systematic variations in sediment density and coarse fraction correspond to glacial-interglacial cycles identified in benthic δ18O, and these observations may provide a framework for mapping the δ18O chronostratigraphy via sediment density to other locations on the Juan de Fuca Ridge and beyond. Sedimentation rates generally range from 0.5 to 3 cm/kyr, with background pelagic sedimentation rates close to 1 cm/kyr. Variability in sedimentation rates close to the ridge likely reflects remobilization of sediment caused by the high relief of the ridge bathymetry. Sedimentation patterns primarily reflect divergence of sedimentation rates with distance from the ridge axis and glacial-interglacial variation in sedimentation that may reflect carbonate preservation cycles as well as preferential remobilization of fine material.
Keywords: Oxygen isotope stratigraphy

Stability of peatland carbon to rising temperatures - Wilson, R. M.; Hopple, A. M.; Tfaily, M. M.; Sebestyen, S. D.; Schadt, C. W.; Pfeifer-Meister, L.; Medvedeff, C.; McFarlane, K. J.; Kostka, J. E.; Kolton, M.; Kolka, R.K.; Kluber, L. A.; et al. (Nature Communications, 2016)
Peatlands contain one-third of soil carbon (C), mostly buried in deep, saturated anoxic zones (catotelm). The response of catotelm C to climate forcing is uncertain, because prior experiments have focused on surface warming. We show that deep peat heating of a 2 m-thick peat column results in an exponential increase in CH4 emissions. However, this response is due solely to surface processes and not degradation of catotelm peat. Incubations show that only the top 20–30 cm of peat from experimental plots have higher CH4 production rates at elevated temperatures. Radiocarbon analyses demonstrate that CH4 and CO2 are produced primarily from decomposition of surface-derived modern photosynthate, not catotelm C. There are no differences in microbial abundances, dissolved organic matter concentrations or degradative enzyme activities among treatments. These results suggest that although surface peat will respond to increasing temperature, the large reservoir of catotelm C is stable under current anoxic conditions.

Stratigraphy, morphology, and geochemistry of late Quaternary buried soils on the High Plains of southwestern Kansas, USA - Anthony L. Layzell; Rolfe D. Mandel; Tammy M. Rittenour; Jon J. Smith; R. Hunter Harlow; Greg A. Ludvigson (CATENA, 2016)
Abstract This study investigated two stratigraphic sequences that record the complex interplay of sedimentation and pedogenesis over the past ca. 84 ka on the High Plains of southwestern Kansas. Up to eight eolian sand and loess units with associated soils were identified in two cores collected from an upland setting. Soil morphological and geochemical data were used to quantitatively assess and compare soil development between multiple buried soils. Chronostratigraphic relationships indicate that 1) loess and eolian sands were episodically deposited during late Marine Isotope Stage (MIS) 5 (ca. 84–70 ka), 2) the Sangamon soil at this site formed between \{MIS\} 3/4 (ca. 70–52 ka), which is consistent with age estimates for renewed Sangamon pedogenesis in the Mississippi River valley, and 3) soil development in the Gilman Canyon Formation began at ca. 44 ka and continued until at least 29.2 ka. Multiple lines of evidence, including grain-size distributions, structure, clay content, and chemical weathering index data, indicate that the morphology and chemistry of the Ak horizon developed in the Gilman Canyon Formation is a product of cumulization by slow loess additions. Similar evidence suggests that cumulization processes are also responsible for the morphology and chemistry of other buried soils in the stratigraphic sequence. Overall, loess inputs during pedogenesis complicate the quantification of weathering processes in these soils.
Keywords: Sangamon soil

Time in tortoiseshell: a bomb radiocarbon-validated chronology in sea turtle scutes - Van Houtan, K. S.; Andrews, A. H.; Jones, T. T.; Murakawa, S. K. K.; Hagemann, M. E. (Proceedings of the Royal Society of London B: Biological Sciences, 2016)
Some of the most basic questions of sea turtle life history are also the most elusive. Many uncertainties surround lifespan, growth rates, maturity and spatial structure, yet these are critical factors in assessing population status. Here we examine the keratinized hard tissues of the hawksbill (Eretmochelys imbricata) carapace and use bomb radiocarbon dating to estimate growth and maturity. Scutes have an established dietary record, yet the large keratin deposits of hawksbills evoke a reliable chronology. We sectioned, polished and imaged posterior marginal scutes from 36 individual hawksbills representing all life stages, several Pacific populations and spanning eight decades. We counted the apparent growth lines, microsampled along growth contours and calibrated Δ14C values to reference coral series. We fit von Bertalanffy growth function (VBGF) models to the results, producing a range of age estimates for each turtle. We find Hawaii hawksbills deposit eight growth lines annually (range 5–14), with model ensembles producing a somatic growth parameter (k) of 0.13 (range 0.1–0.2) and first breeding at 29 years (range 23–36). Recent bomb radiocarbon values also suggest declining trophic status. Together, our results may reflect long-term changes in the benthic community structure of Hawaii reefs, and possibly shed light on the critical population status for Hawaii hawksbills.
Van Houtan, Kyle SAndrews, Allen HJones, T ToddMurakawa, Shawn K KHagemann, Molly EengResearch Support, U.S. Gov't, Non-P.H.S.England2016/01/08 06:00Proc Biol Sci. 2016 Jan 13;283(1822). pii: 20152220. doi: 10.1098/rspb.2015.2220.

Unusually large tsunamis frequent a currently creeping part of the Aleutian megathrust - Witter, Robert C.; Carver, Gary A.; Briggs, Richard W.; Gelfenbaum, Guy; Koehler, Richard D.; La Selle, SeanPaul; Bender, Adrian M.; Engelhart, Simon E.; Hemphill-Haley, Eileen; Hill, Troy D. (Geophysical Research Letters, 2016)
Current models used to assess earthquake and tsunami hazards are inadequate where creep dominates a subduction megathrust. Here we report geological evidence for large tsunamis, occurring on average every 300–340 years, near the source areas of the 1946 and 1957 Aleutian tsunamis. These areas bookend a postulated seismic gap over 200 km long where modern geodetic measurements indicate that the megathrust is currently creeping. At Sedanka Island, evidence for large tsunamis includes six sand sheets that blanket a lowland facing the Pacific Ocean, rise to 15 m above mean sea level, contain marine diatoms, cap terraces, adjoin evidence for scour, and date from the past 1700 years. The youngest sheet and modern drift logs found as far as 800 m inland and >18 m elevation likely record the 1957 tsunami. Previously unrecognized tsunami sources coexist with a presently creeping megathrust along this part of the Aleutian Subduction Zone.

Variations in microbial carbon sources and cycling in the deep continental subsurface - Danielle N. Simkus; Greg F. Slater; Barbara Sherwood Lollar; Kenna Wilkie; Thomas L. Kieft; Cara Magnabosco; Maggie C.Y. Lau; Michael J. Pullin; Sarah B. Hendrickson; K. Eric Wommack; Eric G. Sakowski; Esta van Heerden; et al. (Geochimica et Cosmochimica Acta, 2016)
Abstract Deep continental subsurface fracture water systems, ranging from 1.1 to 3.3 km below land surface (kmbls), were investigated to characterize the indigenous microorganisms and elucidate microbial carbon sources and their cycling. Analysis of phospholipid fatty acid (PLFA) abundances and direct cell counts detected varying biomass that was not correlated with depth. Compound-specific carbon isotope analyses (δ13C and Δ14C) of the phospholipid fatty acids (PLFAs) and carbon substrates combined with genomic analyses did identify, however, distinct carbon sources and cycles between the two depth ranges studied. In the shallower boreholes at circa 1 kmbls, isotopic evidence indicated microbial incorporation of biogenic \{CH4\} by the in situ microbial community. At the shallowest site, 1.05 kmbls in Driefontein mine, this process clearly dominated the isotopic signal. At slightly deeper depths, 1.34 kmbls in Beatrix mine, the isotopic data indicated the incorporation of both biogenic \{CH4\} and dissolved inorganic carbon (DIC) derived from \{CH4\} oxidation. In both of these cases, molecular genetic analysis indicated that methanogenic and methanotrophic organisms together comprised a small component (<5%) of the microbial community. Thus, it appears that a relatively minor component of the prokaryotic community is supporting a much larger overall bacterial community in these samples. In the samples collected from >3 kmbls in Tau Tona mine (TT107, \{TT109\} Bh2), the \{CH4\} had an isotopic signature suggesting a predominantly abiogenic origin with minor inputs from microbial methanogenesis. In these samples, the isotopic enrichments (δ13C and Δ14C) of the \{PLFAs\} relative to \{CH4\} were consistent with little incorporation of \{CH4\} into the biomass. The most 13C-enriched \{PLFAs\} were observed in \{TT107\} where the dominant CO2-fixation pathway was the acetyl-CoA pathway by non-acetogenic bacteria. The differences in the δ13C of the \{PLFAs\} and the \{DIC\} and \{DOC\} for \{TT109\} Bh2 were ∼−24‰ and 0‰, respectively. The dominant CO2-fixation pathways were 3-HP/4-HB cycle > acetyl-CoA pathway > reductive pentose phosphate cycle.

African Baobabs with False Inner Cavities: The Radiocarbon Investigation of the Lebombo Eco Trail Baobab - Patrut, Adrian; Woodborne, Stephan; von Reden, Karl F.; Hall, Grant; Hofmeyr, Michele; Lowy, Daniel A.; Patrut, Roxana T. (PLoS One, 2015)
The article reports the radiocarbon investigation results of the Lebombo Eco Trail tree, a representative African baobab from Mozambique. Several wood samples collected from the large inner cavity and from the outer part of the tree were investigated by AMS radiocarbon dating. According to dating results, the age values of all samples increase from the sampling point with the distance into the wood. For samples collected from the cavity walls, the increase of age values with the distance into the wood (up to a point of maximum age) represents a major anomaly. The only realistic explanation for this anomaly is that such inner cavities are, in fact, natural empty spaces between several fused stems disposed in a ring-shaped structure. We named them false cavities. Several important differences between normal cavities and false cavities are presented. Eventually, we dated other African baobabs with false inner cavities. We found that this new architecture enables baobabs to reach large sizes and old ages. The radiocarbon date of the oldest sample was 1425 +/- 24 BP, which corresponds to a calibrated age of 1355 +/- 15 yr. The dating results also show that the Lebombo baobab consists of five fused stems, with ages between 900 and 1400 years; these five stems build the complete ring. The ring and the false cavity closed 800-900 years ago. The results also indicate that the stems stopped growing toward the false cavity over the past 500 years.
PT: J; TC: 0; UT: WOS:000348470400021

Analysis of bomb radiocarbon data for common thresher sharks, Alopias vulpinus, in the northwestern Atlantic Ocean with revised growth curves - Natanson, Lisa J.; Hamady, Li Ling; Gervelis, Brian J. (ENVIRONMENTAL BIOLOGY OF FISHES, 2015)
Bomb radiocarbon dating was used to determine the periodicity of band pair formation in the vertebral centra of three common thresher sharks (Alopias vulpinus). The traditional interpretation of band pairs were accurate (i.e. annual) up to approximately 14 years of age. In older individuals, band pair counts underestimated age. A new maximum validated age was estimated to be 38 years (an increase of 18 years over the band count estimates). Previously reported length at age estimates for common thresher sharks up to 14 years were used in conjunction with the two older validated estimates to develop a revised growth curve for the species, which was described using the Schnute general model (sexes combined). Updated estimates of age at maturity remained the same for males (8 years) and increased by one year to 13 years for females. The primary finding was the increase in longevity for this species from a band pair count estimate of 24 years to a bomb radiocarbon validated estimate of 38 years, indicating this species lives much longer than previously thought.
Keywords: Age; Carbon-14; Centra; Elasmobranchs; Vertebral column

Applications and limitations of U–Th disequilibria systematics for determining ages of carbonate alteration minerals in peridotite - Mervine, Evelyn M.; Sims, Kenneth W.W.; Humphris, Susan E.; Kelemen, Peter B. (Chemical Geology, 2015)
238U–234U–230Th dating was conducted on carbonate alteration minerals in the peridotite layer of the Samail Ophiolite, Sultanate of Oman, in order to assess the applicability of U-series dating techniques to these types of Quaternary terrestrial carbonates and also to further constrain natural rates of carbonation of the peridotite. Due to their low U concentrations and relatively high Th/U ratios, Samail carbonates are challenging to date with the 230Th technique because of the sensitivity of ages to corrections for initial 230Th. Uncorrected 230Th ages for Ca-rich travertines are consistently older than previously obtained 14C ages. However, geologically reasonable initial 230Th corrections bring the two sets of ages into concordance. This age concordance suggests that the travertines are generally closed systems, adding a level of credence to the reliability of previously obtained 14C ages. In contrast, uncorrected 230Th ages for Mg-rich carbonate veins are generally younger than previously obtained 14C ages. These young ages are interpreted in terms of remobilization of hexavalent U, which is subsequently deposited as tetravalent U by reduced serpentinization fluids. Two Mg-rich carbonate veins sampled at a roadcut have near-equilibrium (230Th/238U) and (234U/238U) values, which indicate that these veins are > 375,000 years in age, consistent with their “14C dead” (> 50,000 years BP) ages. The variable young and old ages for these Mg-rich carbonate veins indicate that carbonation of the peridotite layer of the Samail Ophiolite is an ongoing process and that there have been multiple generations of subsurface carbonate vein formation. Overall, this study provides insights into some of the challenges associated with applying U-series dating methods to Quaternary terrestrial carbonates, in particular carbonate alteration minerals in peridotites, and highlights some areas where there is room for improvement, such as obtaining better constraints on the isotopic composition of admixed detritus, and also some advantages, such as the ability to identify open system behavior not apparent from 14C dating and stable C and O isotopic analysis alone.

Beach ridges as paleoseismic indicators of abrupt coastal subsidence during subduction zone earthquakes, and implications for Alaska-Aleutian subduction zone paleoseismology, southeast coast of the Kenai Peninsula, Alaska - Kelsey, Harvey M.; Witter, Robert C.; Engelhart, Simon E.; Briggs, Richard; Nelson, Alan; Haeussler, Peter; Corbett, D. Reide (Megathrust Earthquakes and Sea-level Change: a Tribute to George Plafker, 2015)
The Kenai section of the eastern Alaska-Aleutian subduction zone straddles two areas of high slip in the 1964 great Alaska earthquake and is the least studied of the three megathrust segments (Kodiak, Kenai, Prince William Sound) that ruptured in 1964. Investigation of two coastal sites in the eastern part of the Kenai segment, on the southeast coast of the Kenai Peninsula, identified evidence for two subduction zone earthquakes that predate the 1964 earthquake. Both coastal sites provide paleoseismic data through inferred coseismic subsidence of wetlands and associated subsidence-induced erosion of beach ridges. At Verdant Cove, paleo-beach ridges record the paleoseismic history; whereas at Quicksand Cove, buried soils in drowned coastal wetlands are the primary indicators of paleoearthquake occurrence and age. The timing of submergence and death of trees mark the oldest earthquake at Verdant Cove that is consistent with the age of a well documented ∼900-year-ago subduction zone earthquake that ruptured the Prince William Sound segment of the megathrust to the east and the Kodiak segment to the west. Soils buried within the last 400–450 years mark the penultimate earthquake on the southeast coast of the Kenai Peninsula. The penultimate earthquake probably occurred before AD 1840 from its absence in Russian historical accounts. The penultimate subduction zone earthquake on the Kenai segment did not rupture in conjunction with the Prince William Sound to the northeast. Therefore the Kenai segment, which is presently creeping, can rupture independently of the adjacent Prince William Sound segment that is presently locked.

Climate forcing of unprecedented intense-hurricane activity in the last 2000 years - Donnelly, Jeffrey P.; Hawkes, Andrea D.; Lane, Philip; MacDonald, Dana; Shuman, Bryan N.; Toomey, Michael R.; van Hengstum, Peter J.; Woodruff, Jonathan D. (EARTHS FUTURE, 2015)
How climate controls hurricane variability has critical implications for society is not well understood. In part, our understanding is hampered by the short and incomplete observational hurricane record. Here we present a synthesis of intense-hurricane activity from the western North Atlantic over the past two millennia, which is supported by a new, exceptionally well-resolved record from Salt Pond, Massachusetts (USA). At Salt Pond, three coarse grained event beds deposited in the historical interval are consistent with severe hurricanes in 1991 (Bob), 1675, and 1635 C.E., and provide modern analogs for 32 other prehistoric event beds. Two intervals of heightened frequency of event bed deposition between 1400 and 1675 C.E. (10 events) and 150 and 1150 C.E. (23 events), represent the local expression of coherent regional patterns in intense-hurricane-induced event beds. Our synthesis indicates that much of the western North Atlantic appears to have been active between 250 and 1150 C.E., with high levels of activity persisting in the Caribbean and Gulf of Mexico until 1400 C.E. This interval was one with relatively warm sea surface temperatures (SSTs) in the main development region (MDR). A shift in activity to the North American east coast occurred ca. 1400 C.E., with more frequent severe hurricane strikes recorded from The Bahamas to New England between 1400 and 1675 C.E. A warm SST anomaly along the western North Atlantic, rather than within the MDR, likely contributed to the later active interval being restricted to the east coast.
Keywords: Climate change; common era; Holocene; sea surface temperature; tropical cyclones

Coastal evidence for Holocene subduction-zone earthquakes and tsunamis in central Chile - Dura, Tina; Cisternas, Marco; Horton, Benjamin P.; Ely, Lisa L.; Nelson, Alan R.; Wesson, Robert L.; Pilarczyk, Jessica E. (Quaternary Science Reviews, 2015)
The ∼500-year historical record of seismicity along the central Chile coast (30–34°S) is characterized by a series of ∼M 8.0–8.5 earthquakes followed by low tsunamis (<4 m) occurring on the megathrust about every 80 years. One exception is the AD 1730 great earthquake (M 9.0–9.5) and high tsunami (>10 m), but the frequency of such large events is unknown. We extend the seismic history of central Chile through a study of a lowland stratigraphic sequence along the metropolitan coast north of Valparaíso (33°S). At this site, higher relative sea level during the mid Holocene created a tidal marsh and the accommodation space necessary for sediment that preserves earthquake and tsunami evidence. Within this 2600-yr-long sequence, we traced six laterally continuous sand beds probably deposited by high tsunamis. Plant remains that underlie the sand beds were radiocarbon dated to 6200, 5600, 5000, 4400, 3800, and 3700 cal yr BP. Sediment properties and diatom assemblages of the sand beds—for example, anomalous marine planktonic diatoms and upward fining of silt-sized diatom valves—point to a marine sediment source and high-energy deposition. Grain-size analysis shows a strong similarity between inferred tsunami deposits and modern coastal sediment. Upward fining sequences characteristic of suspension deposition are present in five of the six sand beds. Despite the lack of significant lithologic changes between the sedimentary units under- and overlying tsunami deposits, we infer that the increase in freshwater siliceous microfossils in overlying units records coseismic uplift concurrent with the deposition of five of the sand beds. During our mid-Holocene window of evidence preservation, the mean recurrence interval of earthquakes and tsunamis is ∼500 years. Our findings imply that the frequency of historical earthquakes in central Chile is not representative of the greatest earthquakes and tsunamis that the central Chilean subduction zone has produced.
Keywords: Coastal hazards; Coastal paleoseismology; Diatom paleoecology; Prehistoric earthquakes; Tsunami Deposits

Comparing dust flux records from the Subarctic North Pacific and Greenland: Implications for atmospheric transport to Greenland and for the application of dust as a chronostratigraphic tool - Serno, Sascha; Winckler, Gisela; Anderson, Robert F.; Maier, Edith; Ren, Haojia; Gersonde, Rainer; Haug, Gerald H. (PALEOCEANOGRAPHY, 2015)
We present a new record of eolian dust flux to the western Subarctic North Pacific (SNP) covering the past 27,000years based on a core from the Detroit Seamount. Comparing the SNP dust record to the North Greenland Ice Core Project (NGRIP) ice core record shows significant differences in the amplitude of dust changes to the two regions during the last deglaciation, while the timing of abrupt changes is synchronous. If dust deposition in the SNP faithfully records its mobilization in East Asian source regions, then the difference in the relative amplitude must reflect climate-related changes in atmospheric dust transport to Greenland. Based on the synchronicity in the timing of dust changes in the SNP and Greenland, we tie abrupt deglacial transitions in the Th-230-normalized He-4 flux record to corresponding transitions in the well-dated NGRIP dust flux record to provide a new chronostratigraphic technique for marine sediments from the SNP. Results from this technique are complemented by radiocarbon dating, which allows us to independently constrain radiocarbon paleoreservoir ages. We find paleoreservoir ages of 745140years at 11,653year B.P., 680228years at 14,630year B.P., and 790498years at 23,290year B.P. Our reconstructed paleoreservoir ages are consistent with modern surface water reservoir ages in the western SNP. Good temporal synchronicity between eolian dust records from the Subantarctic Atlantic and equatorial Pacific and the ice core record from Antarctica supports the reliability of the proposed dust tuning method to be used more widely in other global ocean regions.
Keywords: atmospheric circulation; chronostratigrapy; eolian dust; helium-4; paleoreservoir age; Subarctic North Pacific

Field techniques for sea-level reconstruction - Coastal sediment - Shennan, I.; Long, A.J.; Horton, B.E. (Handbook of Sea-Level Research, 2015)
Measuring sea-level change – be that rise or fall – is one of the most pressing scientific goals of our time and requires robust scientific approaches and techniques. This Handbook aims to provide a practical guide to readers interested in this challenge, from the initial design of research approaches through to the practical issues of data collection and interpretation from a diverse range of coastal environments. Building on thirty years of international research, the Handbook comprises 38 chapters that are authored by leading experts from around the world. The Handbook will be an important resource to scientists interested and involved in understanding sea-level changes across a broad range of disciplines, policy makers wanting to appreciate our current state of knowledge of sea-level change over different timescales, and many teachers at the university level, as well as advanced-level undergraduates and postgraduate research students, wanting to learn more about sea-level change.

Freshening of the Marmara Sea prior to its post-glacial reconnection to the Mediterranean Sea - Aloisi, G.; Soulet, G.; Henry, P.; Wallmann, K.; Sauvestre, R.; Vallet-Coulomb, C.; Lecuyer, C.; Bard, E. (EARTH AND PLANETARY SCIENCE LETTERS, 2015)
During the last glaciation the Marmara Sea was isolated from the Mediterranean Sea because global sea level was below the depth of the Dardanelles sill. Prior to the postglacial reconnection to the Mediterranean Sea (similar to 14.7 cal kyr BP), the surface waters of the Marmara Sea were brackish (Marmara Lake). Freshening of a previously saline Marmara Sea could have happened via spill-out of brackish to fresh water from the surface water of the Black Sea through the Bosphorus Strait. This hypothesis has not been tested against alternative possibilities (salt flushing by river run-off and precipitation). Here we use the dissolved Cl- and stable isotope composition (delta O-18 and delta D) of Marmara Sea sediment pore water to estimate the salinity and stable isotope composition of Marmara Lake bottom water and to evaluate possible freshening scenarios. We use a transport model to simulate pore water Cl-, delta O-18 and delta D in Marmara Sea sediments in the past 130 kyr, which includes the last interglacial (130-75 cal kyr BP), the last glacial (75-14 cal kyr BP) and the current postglacial period. Our results show that the bottom waters of the Marmara Lake were brackish (similar to 4 parts per thousand salinity) and isotopically depleted (delta O-18 similar to -10.2 parts per thousand and delta D similar to -70 parts per thousand, respectively) compared to modern seawater. Their salinity and stable isotope ratios show that they are a mixture of Mediterranean waters and Danube-like waters implying that the freshening took place via spill-out of freshwater through the Bosphorus. Our modelling approach indicates that the transit of fresh water from glacial Eurasia to the Mediterranean via the Marmara Sea started at least 50 cal kyr BP, was continuous throughout most of the last glaciation and persisted up to the post glacial reconnection to the Mediterranean through the Dardanelles sill (14.7 cal kyr BP). These results are consistent with previously published micropaleontological and geochemical investigations of sediment cores that indicate lacustrine conditions in the Marmara Sea from about 75 to 14.7 cal kyr BP. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Black Sea outflow; Last glacial maximum; Marmara Lake; pore water isotope composition

Glacial-interglacial changes in central tropical Pacific surface seawater property gradients - Lynch-Stieglitz, Jean; Polissar, Pratigya J.; Jacobel, Allison W.; Hovan, Steven A.; Pockalny, Robert A.; Lyle, Mitchell; Murray, Richard W.; Ravelo, A. Christina; Bova, Samantha C.; Dunlea, Ann G.; Ford, Heather L.; Hertzberg, Jennifer E.; et al. (Paleoceanography, 2015)
Much uncertainty exists about the state of the oceanic and atmospheric circulation in the tropical Pacific over the last glacial cycle. Studies have been hampered by the fact that sediment cores suitable for study were concentrated in the western and eastern parts of the tropical Pacific, with little information from the central tropical Pacific. Here we present information from a suite of sediment cores collected from the Line Islands Ridge in the central tropical Pacific, which show sedimentation rates and stratigraphies suitable for paleoceanographic investigations. Based on the radiocarbon and oxygen isotope measurements on the planktonic foraminifera Globigerinoides ruber, we construct preliminary age models for selected cores and show that the gradient in the oxygen isotope ratio of G. ruber between the equator and 8°N is enhanced during glacial stages relative to interglacial stages. This stronger gradient could reflect enhanced equatorial cooling (perhaps reflecting a stronger Walker circulation) or an enhanced salinity gradient (perhaps reflecting increased rainfall in the central tropical Pacific).

Handbook of Sea-Level ResearchPre-fieldwork surveys - Witter, Robert C. (John Wiley & Sons, Ltd, 2015)
Using maps, imagery, tidal measurements, and other historical data to assess the geomorphology of a study area prior to fieldwork helps select optimal sites, identify the most effective field methods to test research hypotheses, highlight the primary geomorphic processes, and may provide preliminary estimates of sea-level change. Here, I review the common types of data useful for pre-fieldwork surveys in sea-level research and discuss the many benefits of assessing the geomorphology of a site in advance of fieldwork. I also review briefly some case studies where historical data led to new directions in research and a scientific breakthrough.
Keywords: aerial photography; barrier island; bathymetric data; beach ridge; coastal geomorphology; geomorphological map; LiDAR; nautical chart; remote sensing; satellite imagery

Incorporation of bomb-produced 14C into fish otoliths. An example of basin-specific rates from the North Pacific Ocean - Wischniowski, Stephen G.; Kastelle, Craig R.; Loher, Timothy; Helser, Thomas E. (Canadian Journal of Fisheries and Aquatic Sciences, 2015)

Multimolecular tracers of terrestrial carbon transfer across the pan-Arctic: C-14 characteristics of sedimentary carbon components and their environmental controls - Feng, Xiaojuan; Gustafsson, Örjan; Holmes, R. Max; Vonk, Jorien E.; van Dongen, Bart E.; Semiletov, Igor P.; Dudarev, Oleg V.; Yunker, Mark B.; Macdonald, Robie W.; Wacker, Lukas; Montluçon, Daniel B.; Eglinton, Timothy I. (GLOBAL BIOGEOCHEMICAL CYCLES, 2015)
Distinguishing the sources, ages, and fate of various terrestrial organic carbon (OC) pools mobilized from heterogeneous Arctic landscapes is key to assessing climatic impacts on the fluvial release of carbon from permafrost. Through molecular C-14 measurements, including novel analyses of suberin- and/or cutin-derived diacids (DAs) and hydroxy fatty acids (FAs), we compared the radiocarbon characteristics of a comprehensive suite of terrestrial markers (including plant wax lipids, cutin, suberin, lignin, and hydroxy phenols) in the sedimentary particles from nine major arctic and subarctic rivers in order to establish a benchmark assessment of the mobilization patterns of terrestrial OC pools across the pan-Arctic. Terrestrial lipids, including suberin-derived longer-chain DAs (C-24,C-26,C-28), plant wax FAs (C(24,26,2)8), and n-alkanes (C-27,C-29,C-31), incorporated significant inputs of aged carbon, presumably from deeper soil horizons. Mobilization and translocation of these ``old{''} terrestrial carbon components was dependent on nonlinear processes associated with permafrost distributions. By contrast, shorter-chain (C-16,C-18) DAs and lignin phenols (as well as hydroxy phenols in rivers outside eastern Eurasian Arctic) were much more enriched in C-14, suggesting incorporation of relatively young carbon supplied by runoff processes from recent vegetation debris and surface layers. Furthermore, the radiocarbon content of terrestrial markers is heavily influenced by specific OC sources and degradation status. Overall, multitracer molecular C-14 analysis sheds new light on the mobilization of terrestrial OC from arctic watersheds. Our findings of distinct ages for various terrestrial carbon components may aid in elucidating fate of different terrestrial OC pools in the face of increasing arctic permafrost thaw.

Refined bomb radiocarbon dating of two iconic fishes of the Great Barrier Reef - Andrews, Allen H.; Choat, John H.; Hamilton, Richard J.; DeMartini, Edward E. (Marine and Freshwater Research, 2015)
PT: J; TC: 0; UT: WOS:000351621600003

Relative sea-level change in Connecticut (USA) during the last 2200 yrs - Kemp, Andrew C.; Hawkes, Andrea D.; Donnelly, Jeffrey P.; Vane, Christopher H.; Horton, Benjamin P.; Hill, Troy D.; Anisfeld, Shimon C.; Parnell, Andrew C.; Cahill, Niamh (Earth and Planetary Science Letters, 2015)
We produced a relative sea-level (RSL) reconstruction from Connecticut (USA) spanning the last ∼2200 yrs that is free from the influence of sediment compaction. The reconstruction used a suite of vertically- and laterally-ordered sediment samples ≤2 cm above bedrock that were collected by excavating a trench along an evenly-sloped bedrock surface. Paleomarsh elevation was reconstructed using a regional-scale transfer function trained on the modern distribution of foraminifera on Long Island Sound salt marshes and supported by bulk-sediment δ13C measurements. The history of sediment accumulation was estimated using an age-elevation model constrained by radiocarbon dates and recognition of pollution horizons of known age. The RSL reconstruction was combined with regional tide-gauge measurements spanning the last ∼150 yrs before being quantitatively analyzed using an error-in-variables integrated Gaussian process model to identify sea-level trends with formal and appropriate treatment of uncertainty and the temporal distribution of data. RSL rise was stable (∼1 mm/yr) from ∼200 BCE to ∼1000 CE, slowed to a minimum rate of rise (0.41 mm/yr) at ∼1400 CE, and then accelerated continuously to reach a current rate of 3.2 mm/yr, which is the fastest, century-scale rate of the last 2200 yrs. Change point analysis identified that modern rates of rise in Connecticut began at 1850–1886 CE. This timing is synchronous with changes recorded at other sites on the U.S. Atlantic coast and is likely the local expression of a global sea-level change. Earlier sea-level trends show coherence north of Cape Hatteras that are contrasted with southern sites. This pattern may represent centennial-scale variability in the position and/or strength of the Gulf Stream. Comparison of the new record to three existing and reanalyzed RSL reconstructions from the same site developed using sediment cores indicates that compaction is unlikely to significantly distort RSL reconstructions produced from shallow (∼2–3 m thick) sequences of salt-marsh peat.
Keywords: Atlantic Ocean; Foraminifera; Gulf Stream; Late Holocene; Salt marsh

A sea-level database for the Pacific coast of central North America - Engelhart, Simon E.; Vacchi, Matteo; Horton, Benjamin P.; Nelson, Alan R.; Kopp, Robert E. (Quaternary Science Reviews, 2015)
A database of published and new relative sea-level (RSL) data for the past 16 ka constrains the sea-level histories of the Pacific coast of central North America (southern British Columbia to central California). Our reevaluation of the stratigraphic context and radiocarbon age of sea-level indicators from geological and archaeological investigations yields 600 sea-level index points and 241 sea-level limiting points. We subdivided the database into 12 regions based on the availability of data, tectonic setting, and distance from the former Cordilleran ice sheet. Most index (95%) and limiting points (54%) are <7 ka; older data come mainly from British Columbia and San Francisco Bay. The stratigraphic position of points was used as a first-order assessment of compaction. Formerly glaciated areas show variable RSL change; where data are present, highstands of RSL occur immediately post-deglaciation and in the mid to late Holocene. Sites at the periphery and distant to formerly glaciated areas demonstrate a continuous rise in RSL with a decreasing rate through time due to the collapse of the peripheral forebulge and the reduction in meltwater input during deglaciation. Late Holocene RSL change varies spatially from falling at 0.7 ± 0.8 mm a−1 in southern British Columbia to rising at 1.5 ± 0.3 mm a−1 in California. The different sea-level histories are an ongoing isostatic response to deglaciation of the Cordilleran and Laurentide Ice Sheets.
Keywords: Cascadia subduction zone; Glacial isostatic adjustment; Holocene; Pacific North America; Sea-level database

Sedimentary response to Milankovitch-type climatic oscillations and formation of sediment undulations: evidence from a shallow-shelf setting at Gela Basin on the Sicilian continental margin - Kuhlmann, Jannis; Asioli, Alessandra; Trincardi, Fabio; Klügel, Andreas; Huhn, Katrin (Quaternary Science Reviews, 2015)
A multi-proxy chronological framework along with sequence-stratigraphic interpretations unveils composite Milankovitch cyclicity in the sedimentary records of the Last Glacial–Interglacial cycle at NE Gela Basin on the Sicilian continental margin. Chronostratigraphic data (including foraminifera-based eco-biostratigraphy and δ18O records, tephrochronological markers and 14C AMS radiometric datings) was derived from the shallow-shelf drill sites GeoB14403 (54.6 m recovery) and GeoB14414 (27.5 m), collected with both gravity and drilled MeBo cores in 193 m and 146 m water depth, respectively. The recovered intervals record Marine Isotope Stages and Substages (MIS) from MIS 5 to MIS 1, thus comprising major stratigraphic parts of the progradational deposits that form the last 100-ka depositional sequence. Calibration of shelf sedimentary units with borehole stratigraphies indicates the impact of higher-frequency (20-ka) sea level cycles punctuating this 100-ka cycle. This becomes most evident in the alternation of thick interstadial highstand (HST) wedges and thinner glacial forced-regression (FSST) units mirroring seaward shifts in coastal progradation. Albeit their relatively short-lived depositional phase, these subordinate HST units form the bulk of the 100-ka depositional sequence. Two mechanisms are proposed that likely account for enhanced sediment accumulation ratios (SAR) of up to 200 cm/ka during these intervals: (1) intensified activity of deep and intermediate Levantine Intermediate Water (LIW) associated to the drowning of Mediterranean shelves, and (2) amplified sediment flux along the flooded shelf in response to hyperpycnal plumes that generate through extreme precipitation events during overall arid conditions. Equally, the latter mechanism is thought to be at the origin of undulated features resolved in the acoustic records of MIS 5 Interstadials, which bear a striking resemblance to modern equivalents forming on late-Holocene prodeltas of other Mediterranean shallow-shelf settings.

Sedimentation Pulse in the NE Gulf of Mexico following the 2010 DWH Blowout - Brooks, Gregg R.; Larson, Rebekka A.; Schwing, Patrick T.; Romero, Isabel; Moore, Christopher; Reichart, Gert-Jan; Jilbert, Tom; Chanton, Jeff P.; Hastings, David W.; Overholt, Will A.; Marks, Kala P.; Kostka, Joel E.; et al. (PLOS ONE, 2015)
The objective of this study was to investigate the impacts of the Deepwater Horizon (DWH) oil discharge at the seafloor as recorded in bottom sediments of the DeSoto Canyon region in the northeastern Gulf of Mexico. Through a close coupling of sedimentological, geochemical, and biological approaches, multiple independent lines of evidence from 11 sites sampled in November/December 2010 revealed that the upper ~1 cm depth interval is distinct from underlying sediments and results indicate that particles originated at the sea surface. Consistent dissimilarities in grain size over the surficial ~1 cm of sediments correspond to excess 234Th depths, which indicates a lack of vertical mixing (bioturbation), suggesting the entire layer was deposited within a 4–5 month period. Further, a time series from four deep-sea sites sampled up to three additional times over the following two years revealed that excess 234Th depths, accumulation rates, and 234Th inventories decreased rapidly, within a few to several months after initial coring. The interpretation of a rapid sedimentation pulse is corroborated by stratification in solid phase Mn, which is linked to diagenesis and redox change, and the dramatic decrease in benthic formanifera density that was recorded in surficial sediments. Results are consistent with a brief depositional pulse that was also reported in previous studies of sediments, and marine snow formation in surface waters closer to the wellhead during the summer and fall of 2010. Although sediment input from the Mississippi River and advective transport may influence sedimentation on the seafloor in the DeSoto Canyon region, we conclude based on multidisciplinary evidence that the sedimentation pulse in late 2010 is the product of marine snow formation and is likely linked to the DWH discharge.

Sinking particle flux in the sea ice zone of the Amundsen Shelf, Antarctica - Kim, Minkyoung; Hwang, Jeomshik; Kim, Hyung J.; Kim, Dongseon; Yang, Eun J.; Ducklow, Hugh W.; Hyoung, S. La; Lee, Sang H.; Park, Jisoo; Lee, SangHoon (Deep Sea Research Part I: Oceanographic Research Papers, 2015)
We have examined the flux, biogenic composition, and isotopic values of sinking particles collected by a time-series sediment trap deployed in the sea ice zone (SIZ) of the Amundsen Sea from January 2011 for 1 year. The major portion of the particle flux occurred during the austral summer in January and February when sea ice concentration was reduced to 30 %) and a low bio-Si/POC ratio (<0.5) during the austral winter. CaCO3 content and its contribution to total particle flux was low (~6 %) throughout the study period. Aged POC likely supplied from sediment resuspension accounted for a considerable fraction only from October to December, which was evidenced by a low radiocarbon content and relatively high (30–50 %) content of the non-biogenic components. When compared with POC flux inside the Amundsen Sea polynya obtained by the US Amundsen Sea Polynya International Research Expedition (ASPIRE), the POC flux integrated over the austral summer in the SIZ was virtually identical, although the maximum POC flux was approximately half that inside the Amundsen Sea polynya. This comparatively high POC flux integrated over the austral summer in the SIZ may be caused by phytoplankton blooms persisting over a longer periods and more efficient export of organic matter potentially owing to the diatom-dominant plankton community. If this observation is a general phenomenon on the Amundsen Shelf, the role of the SIZ, compared with the polynyas, need to be examined more carefully when trying to characterize the POC export in this region.
Ck4reTimes Cited:4Cited References Count:38

South Asian monsoon history over the past 60 kyr recorded by radiogenic isotopes and clay mineral assemblages in the Andaman Sea - Ali, Sajid; Hathorne, Ed C.; Frank, Martin; Gebregiorgis, Daniel; Stattegger, Karl; Stumpf, Roland; Kutterolf, Steffen; Johnson, Joel E.; Giosan, Liviu (Geochemistry, Geophysics, Geosystems, 2015)
The Late Quaternary variability of the South Asian (or Indian) monsoon has been linked with glacial-interglacial and millennial scale climatic changes but past rainfall intensity in the river catchments draining into the Andaman Sea remains poorly constrained. Here we use radiogenic Sr, Nd, and Pb isotope compositions of the detrital clay-size fraction and clay mineral assemblages obtained from sediment core NGHP Site 17 in the Andaman Sea to reconstruct the variability of the South Asian monsoon during the past 60 kyr. Over this time interval εNd values changed little, generally oscillating between −7.3 and −5.3 and the Pb isotope signatures are essentially invariable, which is in contrast to a record located further northeast in the Andaman Sea. This indicates that the source of the detrital clays did not change significantly during the last glacial and deglaciation suggesting the monsoon was spatially stable. The most likely source region is the Irrawaddy river catchment including the Indo-Burman Ranges with a possible minor contribution from the Andaman Islands. High smectite/(illite + chlorite) ratios (up to 14), as well as low 87Sr/86Sr ratios (0.711) for the Holocene period indicate enhanced chemical weathering and a stronger South Asian monsoon compared to marine oxygen isotope stages 2 and 3. Short, smectite-poor intervals exhibit markedly radiogenic Sr isotope compositions and document weakening of the South Asian monsoon, which may have been linked to short-term northern Atlantic climate variability on millennial time scales.

Spatial Variation in the Origin of Dissolved Organic Carbon in Snow on the Juneau Icefield, Southeast Alaska - Fellman, Jason B.; Hood, Eran; Raymond, Peter A.; Stubbins, Aron; Spencer, Robert G.M. (Environmental Science & Technology, 2015)
Dissolved organic carbon (DOC) plays a fundamental role in the biogeochemistry of glacier ecosystems. However, the specific sources of glacier DOC remain unresolved. To assess the origin and nature of glacier DOC, we collected snow from 10 locations along a transect across the Juneau Icefield, Alaska extending from the coast toward the interior. The Δ14C-DOC of snow varied from −743 to −420‰ showing progressive depletion across the Icefield as δ18O of water became more depleted (R2 = 0.56). Older DOC corresponded to lower DOC concentrations in snow (R2 = 0.31) and a decrease in percent humic-like fluorescence (R2 = 0.36), indicating an overall decrease in modern DOC across the Icefield. Carbon isotopic signatures (13C and 14C) combined with a three-source mixing model showed that DOC deposited in snow across the Icefield reflects fossil fuel combustion products (43–73%) and to a lesser extent marine (21–41%) and terrestrial sources (1–26%). Our finding that combustion aerosols are a large source of DOC to the glacier ecosystem during the early spring (April–May) together with the pronounced rates of glacier melting in the region suggests that the delivery of relic DOC to the ocean may be increasing and consequently impacting the biogeochemistry of glacial and proglacial ecosystems in unanticipated ways.

Using Natural Abundance Radiocarbon To Trace the Flux of Petrocarbon to the Seafloor Following the Deepwater Horizon Oil Spill - Chanton, Jeffrey; Zhao, Tingting; Rosenheim, Brad E.; Joye, Samantha; Bosman, Samantha; Brunner, Charlotte; Yeager, Kevin M.; Diercks, Arne R.; Hollander, David (Environmental Science & Technology, 2015)
In 2010, the Deepwater Horizon accident released 4.6–6.0 × 1011 grams or 4.1 to 4.6 million barrels of fossil petroleum derived carbon (petrocarbon) as oil into the Gulf of Mexico. Natural abundance radiocarbon measurements on surface sediment organic matter in a 2.4 × 1010 m2 deep-water region surrounding the spill site indicate the deposition of a fossil-carbon containing layer that included 1.6 to 2.6 × 1010 grams of oil-derived carbon. This quantity represents between 0.5 to 9.1% of the released petrocarbon, with a best estimate of 3.0–4.9%. These values may be lower limit estimates of the fraction of the oil that was deposited on the seafloor because they focus on a limited mostly deep-water area of the Gulf, include a conservative estimate of thickness of the depositional layer, and use an average background or prespill radiocarbon value for sedimentary organic carbon that produces a conservative value. A similar approach using hopane tracer estimated that 4–31% of 2 million barrels of oil that stayed in the deep sea settled on the bottom. Converting that to a percentage of the total oil that entered into the environment (to which we normalized our estimate) converts this range to 1.8 to 14.4%. Although extrapolated over a larger area, our independent estimate produced similar values.

Adélie penguin dietary remains reveal Holocene environmental changes in the western Ross Sea (Antarctica) - Lorenzini, Sandra; Baroni, Carlo; Baneschi, Ilaria; Salvatore, Maria Cristina; Fallick, Anthony E.; Hall, Brenda L. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2014)
Carbon and nitrogen stable isotope analyses were performed on modern and Holocene Adélie penguin guano samples collected from ornithogenic soils along the Scott Coast (Southern Victoria Land, Antarctica), from Cape Irizar to Dunlop Island, and at Cape Bird (Ross Island). Guano samples also were sieved and sorted under stereomicroscope in order to select penguin dietary remains, such as fish bones and otoliths. Carbon and nitrogen stable isotope composition, coupled with the taxonomic identification of fish otoliths from Scott Coast Holocene samples, indicated a mainly fish-based diet for this area, with Pleuragramma antarcticum as the most eaten prey throughout the investigated period (from 390 cal BP to ca 7300 cal BP). The isotopic values of Ross Island samples (from modern to 3850 cal BP) showed a krill consumption increase in the samples younger than 2000 cal BP, with the maximum in modern samples. Scott Coast and Ross Island Holocene samples showed δ13C and δ15N trends similar to those previously published from Terra Nova Bay (northern Victoria Land), whereas modern samples from Ross Island have similar δ15N composition but different δ13C values. This δ13C divergence started at ca 2000 BP and follows the abandonment of the Scott Coast colonies. The δ13C trend observed in Ross Island and Terra Nova Bay samples and the abandonment of the Scott Coast colonies could suggest the stability and the persistence of the previous oceanographic conditions (i.e. polynya) for the Terra Nova Bay area and the establishment of new conditions for water circulation in the Southern Ross Sea since ~ 2000 BP when persistent sea-ice sealed the Scott Coast.
id: 2347

Age and growth of the giant sea bass, Stereolepis gigas - A. Hawk, Holly; Allen, Larry (California Cooperative Oceanic Fisheries Investigations Reports, 2014)
In January 2010, a massive giant sea bass (500 lbs, 227 kg; near maximum reported size of 557 lbs, 253 kg) was captured off Santa Cruz Island by commercial gill-netters. This specimen presented a unique opportunity to estimate and validate of the potential longevity of the largest nearshore teleost of the northeastern Pacific. A transverse section of the sagittal otolith produced consistent counts of 62 opaque annuli along two different axes of the ventral sulcus region, translating into an estimated birth year of 1948. This age estimate was supported by measurements of radiocarbon (14 C) in the other sagittal otolith core (within the first year of growth), relative to D 14 C reference records used for bomb radiocarbon dating. Two otolith core samples produced D 14 C values that were classified as pre-bomb (prior to ,1958–59), indicating a minimum lifespan of 51 years. It is likely that giant sea bass can live more than 60 or 70 years based on growth zone counts, but there is no evidence in the literature or this study to support longevity of 100 years.
Keywords: Age and growth; Carbon-14; lifespan; Longevity; Otolith; Polyprionidae; Stereolepis

Carbonation rates of peridotite in the Samail Ophiolite, Sultanate of Oman, constrained through 14C dating and stable isotopes - Mervine, Evelyn M.; Humphris, Susan E.; Sims, Kenneth W. W.; Kelemen, Peter B.; W. J. Jenkins (Geochimica et Cosmochimica Acta, 2014)
Detailed 14C dating as well as stable C and O isotope analyses were conducted on carbonates formed during alteration of the peridotite layer of the Samail Ophiolite, Sultanate of Oman. 14C results obtained in this and previous studies indicate that surface travertines range in age from modern to >45,000 yr BP, indicating long-term deposition and preservation. Travertine deposition rates in two localities were ∼0.1 to 0.3 mm/yr between ∼30,000 and 45,000 yr BP. Using an estimate of total travertine area, this would result in a maximum of ∼1000 to 3000 m3/yr of travertine being deposited throughout the ophiolite during this time period. This travertine deposition would have sequestered a maximum of ∼1 to 3 × 106 kg CO2/yr. Ca-rich carbonate veins that are associated with the surface travertine deposits have ages ranging from ∼4000 to 36,000 yr BP (average: 15,000 yr BP). Mg-rich carbonate veins exposed in outcrops have ages ranging from ∼8000 to 45,000 yr BP (average: 35,000 yr BP). Detailed sampling from numerous locations (3 locations in this study and 10 locations in the previous studies) indicates that no carbonate veins from the natural peridotite weathering surface are older than the ∼50,000 yr BP dating limit of 14C. However, 14C dating of Mg-rich carbonate veins from three roadcut exposures (Qafeefah, Fanja, and Al-Wuqbah) indicates that a significant number of roadcut veins are 14C dead (>50,000 yr BP). A location weighted average indicates that ∼40% of veins sampled at the three roadcuts are 14C dead. An average including veins sampled at both roadcuts and outcrops indicates that overall ∼8% of Mg-rich carbonate veins are 14C dead. Mg-rich carbonate veins are estimated to sequester on the order of 107 kg CO2/yr throughout the ophiolite.

Coastal response to late-stage transgression and sea-level highstand - Hein, C. J.; FitzGerald, D. M.; Thadeu de Menezes, J.; Cleary, W. J.; Klein, A. H. F.; Albernaz, M. B. (Geological Society of America Bulletin, 2014)
Coastal morphologic features associated with past shoreline transgressions and sea-level highstands can provide insight into the rates and processes associated with coastal response to the modern global rise in sea level. Along the eastern and southern Brazilian coasts of South America, 6000 years of sea-level fall have preserved late-stage transgressive and sea-level highstand features 1–4 m above present mean sea level and several kilome ters landward of modern shore-lines. GPS with real-time kinematics data, ground-penetrating radar, stratigraphy, and radiocarbon dating within a 2–3-km-wide river-associated strandplain in central Santa Catarina (southern Brazil) uncovered a diverse set of late-stage transgressive and high- stand deposits. Here, the highstand took the forms of (1) an exposed bedrock coast in areas of high wave energy and low sediment supply; (2) a 3.8-m-high transgressive barrier ridge where landward barrier migration was prohibited by the presence of shallow bedrock; and (3) a complete barrier-island complex containing a 5.2-m-high barrier ridge, washover deposits, a paleo-inlet, and a backbarrier lowland, formed in a protected cove with ample sediment supply from small local streams and the erosion of upland sediments. Similar signatures of the mid-Holocene highstand can be traced across all coastal Brazilian states. This study presents the first complete compilation of the diversity of these sedimentary sequences. They are broadly classified here as exposed bedrock coasts (type A), back barrier deposits (type B), transgressive barrier ridges (type C), and barrier-island complexes (type D), according to localized conditions of upland migration potential, wave exposure, and sediment supply. These Brazilian systems present a paradigm for understanding future coastal response to climate change and accelerated sea-level rise: the recognition of a minimum threshold sea-level-rise rate of ~2 mm yr–1 above which transgression proceeded too rapidly for the formation of these stable accretionary shoreline features demonstrates the nonlinearity of coastal response to sea-level change, and the site specificity of conditions associated with the formation of each highstand deposit type, even within a single small embayment, demonstrates the non-uniformity of that response.

A continuous multi-millennial record of surficial bivalve mollusk shells from the São Paulo Bight, Brazilian shelf - Dexter, Troy A.; Kaufman, Darrell S.; Krause Jr, Richard A.; Barbour Wood, Susan L.; Simões, Marcello G.; Huntley, John Warren; Yanes, Yurena; Romanek, Christopher S.; Kowalewski, Michał (Quaternary Research, 2014)
To evaluate the potential of using surficial shell accumulations for paleoenvironmental studies, an extensive time series of individually dated specimens of the marine infaunal bivalve mollusk Semele casali was assembled using amino acid racemization (AAR) ratios (n = 270) calibrated against radiocarbon ages (n = 32). The shells were collected from surface sediments at multiple sites across a sediment-starved shelf in the shallow sub-tropical São Paulo Bight (São Paulo State, Brazil). The resulting 14C-calibrated AAR time series, one of the largest AAR datasets compiled to date, ranges from modern to 10,307 cal yr BP, is right skewed, and represents a remarkably complete time series: the completeness of the Holocene record is 66% at 250-yr binning resolution and 81% at 500-yr binning resolution. Extensive time-averaging is observed for all sites across the sampled bathymetric range indicating long water depth-invariant survival of carbonate shells at the sediment surface with low net sedimentation rates. Benthic organisms collected from active depositional surfaces can provide multi-millennial time series of biomineral records and serve as a source of geochemical proxy data for reconstructing environmental and climatic trends throughout the Holocene at centennial resolution. Surface sediments can contain time-rich shell accumulations that record the entire Holocene, not just the present.

Cryostratigraphy and Permafrost Evolution in the Lacustrine Lowlands of West-Central Alaska - Kanevskiy, Mikhail; Jorgenson, Torre; Shur, Yuri; O'Donnell, Jonathan A.; Harden, Jennifer W.; Zhuang, Qianlai; Fortier, Daniel (Permafrost and Periglacial Processes, 2014)
The influence of permafrost growth and thaw on the evolution of ice-rich lowland terrain in the Koyukuk-Innoko region of interior Alaska is fundamental but poorly understood. To elucidate this influence, the cryostratigraphy and properties of perennially frozen sediments from three areas in this region are described and interpreted in terms of permafrost history. The upper part of the late Quaternary sediments at the Koyukuk and Innoko Flats comprise frozen organic soils up to 4.5 m thick underlain by ice-rich silt characterised by layered and reticulate cryostructures. The volume of visible segregated ice in silt locally reaches 50 per cent, with ice lenses up to 10 cm thick. A conceptual model of terrain evolution from the Late Pleistocene to the present day identifies four stages of yedoma degradation and five stages of subsequent permafrost aggradation-degradation: (1) partial thawing of the upper ice wedges and the formation of small shallow ponds in the troughs above the wedges; (2) formation of shallow thermokarst lakes above the polygons; (3) deepening of thermokarst lakes and yedoma degradation beneath the lakes; (4) complete thawing of yedoma beneath the lakes; (5) lake drainage; (6) peat accumulation; (7) permafrost aggradation in drained lake basins; (8) formation of permafrost plateaus; and (9) formation and expansion of a new generation of thermokarst features. These stages can occur in differing places and times, creating a highly complex mosaic of terrain conditions, complicating predictions of landscape response to future climatic changes or human impact. Copyright © 2014 John Wiley & Sons, Ltd.

Decreased influence of Antarctic intermediate water in the tropical Atlantic during North Atlantic cold events - Huang, Kuo-Fang; Oppo, Delia W.; Curry, William B. (Earth and Planetary Science Letters, 2014)
Antarctic Intermediate Water (AAIW) is a key player in the global ocean circulation, contributing to the upper limb of the Atlantic Meridional Overturning Circulation (AMOC), and influencing interhemispheric heat exchange and the distribution of salinity, nutrients and carbon. However, the deglacial history of AAIW flow into the North Atlantic is controversial. Here we present a multicore-top neodymium isotope calibration, which confirms the ability of unclean foraminifera to faithfully record bottom water neodymium isotopic composition () values in their authigenic coatings. We then present the first foraminifera-based reconstruction of from three sediment cores retrieved from within modern AAIW, in the western tropical North Atlantic. Our records reveal similar glacial and interglacial contributions of AAIW, and a pronounced decrease in the AAIW fraction during North Atlantic deglacial cold episodes, Heinrich Stadial 1 (HS1) and Younger Dryas (YD). Our results suggest two separate phases of reduced fraction of AAIW in the tropical Atlantic during HS1, with a greater reduction during early HS1. If a reduction in AAIW fraction also reflects reduced AMOC strength, this finding may explain why, in many regions, there are two phases of hydrologic change within HS1, and why atmospheric CO2 rose more rapidly during early than late HS1. Our result suggesting less flow of AAIW into the Atlantic during North Atlantic cold events contrasts with evidence from the Pacific, where intermediate-depth records may indicate increased flow of AAIW into the Pacific during the these same events. Antiphased behavior between intermediate depths of the North Atlantic and Pacific implies that the flow of AAIW into Atlantic and Pacific seesawed during the last deglaciation.
Keywords: antarctic intermediate water; Atlantic meridional overturning circulation; deglacial variability; Nd isotopes; North Atlantic cold events

Glacial to deglacial ventilation and productivity changes in the southern Okhotsk Sea - Okazaki, Yusuke; Kimoto, Katsunori; Asahi, Hirofumi; Sato, Miyako; Nakamura, Yuriko; Harada, Naomi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2014)
As a source region of North Pacific Intermediate Water, the Okhotsk Sea plays an important role in the ventilation of the North Pacific. To understand the detailed oceanographic changes in this marginal sea since the last glaciation, we studied decadal to centennial scale proxy records from new sediment cores from the southwestern Okhotsk Sea. Glacial to Holocene Δ14C records of benthic foraminiferal shells suggested enhanced ventilation in the Okhotsk Sea during the early deglacial period between 18 and 15 ka, corresponding to Heinrich Event 1. Although the Δ14C reconstruction has considerable uncertainties, the Okhotsk Sea may have acted as a source for vigorous ventilation of the subarctic Pacific during this period. CaCO3 preservation events appear to be better explained by the ventilation history of the Okhotsk Sea than by coccolithophores and foraminifera production. CaCO3 preservation started to improve during 18 to 15 ka, and pronounced peaks in the CaCO3 content corresponded to the Bølling–Allerød (15 to 13 ka) and Preboreal (11.5 to 10 ka) warm periods. Diatom and coccolithophore productivity remained low in the Okhotsk Sea throughout the glacial to deglacial periods, different from the situation in the open subarctic Pacific, where high productivity was observed during the Bølling–Allerød period. After the Preboreal period, biogenic opal gradually increased and δ15N decreased in the southern Okhotsk Sea, suggesting that productivity was enhanced by a relaxation of the nitrate limitation.
Keywords: Glacial–deglacial change; Okhotsk Sea; productivity; ventilation

The high-supply, current-dominated continental margin of southeastern South America during the late Quaternary - Lantzsch, Hendrik; Hanebuth, Till J. J.; Chiessi, Cristiano M.; Schwenk, Tilmann; Violante, Roberto A. (Quaternary Research, 2014)
The continental margin off the La Plata Estuary (SE South America) is characterized by high fluvial sediment supply and strong ocean currents. High-resolution sediment-acoustic data combined with sedimentary facies analysis, AMS-14C ages, and neodymium isotopic data allowed us to reconstruct late Quaternary sedimentary dynamics in relation to the two major sediment sources, the La Plata Estuary and the Argentine margin. Sediments from these two provinces show completely different dispersal patterns. We show that the northward-trending La Plata paleo-valley was the sole transit path for the huge volumes of fluvial material during lower sea levels. In contrast, material from the Argentine margin sector was transported northwards by the strong current system. Despite the large sediment volumes supplied by both sources, wide parts of the shelf were characterized by either persistent non-deposition or local short-term depocenter formation. The location and formation history of these depocenters were primarily controlled by the interplay of sea level with current strength and local morphology. The high sediment supply was of secondary importance to the stratigraphic construction, though locally resulting in high sedimentation rates. Thus, the shelf system off the La Plata Estuary can be considered as a hydrodynamic-controlled end-member.

Holocene fluctuations of Bregne ice cap, Scoresby Sund, east Greenland: a proxy for climate along the Greenland Ice Sheet margin - Levy, Laura B.; Kelly, Meredith A.; Lowell, Thomas V.; Hall, Brenda L.; Hempel, Laura A.; Honsaker, William M.; Lusas, Amanda R.; Howley, Jennifer A.; Axford, Yarrow L. (APEX II: Arctic Palaeoclimate and its Extremes, 2014)
The Greenland Ice Sheet is a major component of the Arctic cryosphere and the magnitude of its response to future climate changes remains uncertain. Longer-term records of climate near the ice sheet margin provide information about natural climate variability and can be used to understand the causes of past changes in the Greenland Ice Sheet. As a proxy for Holocene climate near the ice sheet margin, we reconstruct the fluctuations of Bregne ice cap in the Scoresby Sund region of central east Greenland. Bregne is a small ice cap (2.5 km2 in area) and responds sensitively to summer temperatures. We employ a multi-proxy approach to reconstruct the ice cap fluctuations using geomorphic mapping, 10Be ages of boulders and bedrock and lake sediment records. Past extents of Bregne ice cap are marked by moraines and registered by sediments in downvalley lakes. 10Be ages of bedrock and boulders outboard of the moraines indicate that Bregne ice cap was within ∼250 m of its present-day limit by at least 10.7 ka. Multi-proxy data from sediments in Two Move lake, located downvalley from Bregne ice cap, indicate that the ice cap likely completely disappeared during early and middle Holocene time. Increasing magnetic susceptibility and percent clastic material from ∼6.5 to ∼1.9 cal ka BP in Two Move lake sediments suggest progressively colder conditions and increased snow accumulation on the highlands west of the lake. Laminated silt deposited at ∼2.6 cal ka BP and ∼1.9 cal ka BP to present registers the onset and persistence of Bregne ice cap during the late Holocene. 10Be ages of boulders on an unweathered, unvegetated moraine in the Bregne ice cap forefield range from 0.74 to 9.60 ka. The youngest 10Be age (0.74 ka) likely represents the age of the moraine whereas older ages may be due to 10Be inherited from prior periods of exposure. This late Holocene moraine marks the second largest advance of the ice cap since deglaciation of the region at the end of the last ice age. The oldest moraine in the forefield dates to ≤2.6 cal ka BP. The fluctuations of Bregne ice cap were likely influenced by Northern Hemisphere summer insolation throughout the Holocene and abrupt late Holocene cold events.

An investigation of size-fractionated organic matter from Lake Superior and a tributary stream using radiocarbon, stable isotopes and NMR - Zigah, Prosper K.; Minor, Elizabeth C.; Abdulla, Hussain A. N.; Werne, Josef P.; Hatcher, Patrick G. (Geochimica et Cosmochimica Acta, 2014)
This study investigated the concentration and isotopic composition of different size fractions of organic matter (OM) in Lake Superior and in one of its many tributary streams and rivers (Amity Creek, Duluth, Minnesota, USA). Structural compositional drivers of the Δ14C of high molecular weight (HMW, >1 kDa) dissolved organic carbon (DOC) in the lake were also evaluated. Low molecular weight (LMW, 0.7 μm) was generally 13C-depleted (−29 ± 1.2‰) relative to “bulk” (<0.7 μm) DOC (−26.4 ± 0.7‰), “init” (<0.2 μm) DOC (−26.6 ± 0.8‰), HMW DOC (−26.9 ± 0.3‰) and LMW DOC (−26.5 ± 0.9‰), and had more variable 14C content (Δ14C of −94‰ to 53‰; 735 years BP to modern) than the other size fractions. Init DOC (Δ14C of 17–59‰), HMW DOC (Δ14C of 23–64‰) and LMW DOC (Δ14C of 16–62‰) all reflected contemporary (modern) radiocarbon signatures. Bulk DOC (Δ14C of −19‰ to 57‰; 90 years BP to modern) had modern radiocarbon values in the offshore sites (Δ14C of 2–57‰) with pre-aged samples (Δ14C of −8‰ to −19‰) seen at the nearshore site. HMW DOM was relatively N-poor (C:N of 12–19) compared to particulate organic matter (POM, C:N of 8–10) revealing either a more diagenetically altered state or contrasting sources. 13C NMR data showed that biochemical composition of HMW DOC in Lake Superior was dominated by carbohydrates (53–65%) with only trace aromatic components (2–4%). Structurally complex components such as heteropolysaccharides (HPS), amide/peptides and amino sugars (AMS) constitute 75–84% of HMW DOC whereas carboxylic-rich alicyclic molecules (CRAM) made up 16–25% of HMW DOC in the lake. Combined HPS and AMS, O-alkyl carbohydrate carbon, and total carbohydrate carbon contents were significantly positively correlated to the Δ14C of HMW DOC suggesting they contribute a contemporary 14C-enriched component to the HMW DOC in the lake. In contrast, CRAM and aliphatic carbons were significantly inversely correlated with Δ14C of HMW DOC implying that these represent 14C-depleted (older) components of HMW DOC in the lake. At Amity Creek, storm events led to larger loads of bulk DOC and POC, which were both 14C-enriched (modern). However, in baseflow conditions 14C-depleted bulk DOC and POC were exported. LMW DOC from the creek was considerably 14C-depleted compared to concurrent HMW DOC.

An investigation of size-fractionated organic matter from Lake Superior and a tributary stream using radiocarbon, stable isotopes and NMR - Zigah, Prosper K.; Minor, Elizabeth C.; Abdulla, Hussain A.N.; Werne, Josef P.; Hatcher, Patrick G. (Geochimica et Cosmochimica Acta, 2014)

Late Holocene sea- and land-level change on the U.S. southeastern Atlantic coast - Kemp, Andrew C.; Bernhardt, Christopher E.; Horton, Benjamin P.; Kopp, Robert E.; Vane, Christopher H.; Peltier, W. Richard; Hawkes, Andrea D.; Donnelly, Jeffrey P.; Parnell, Andrew C.; Cahill, Niamh (Marine Geology, 2014)
Late Holocene relative sea-level (RSL) reconstructions can be used to estimate rates of land-level (subsidence or uplift) change and therefore to modify global sea-level projections for regional conditions. These reconstructions also provide the long-term benchmark against which modern trends are compared and an opportunity to understand the response of sea level to past climate variability. To address a spatial absence of late Holocene data in Florida and Georgia, we reconstructed ~ 1.3 m of RSL rise in northeastern Florida (USA) during the past ~ 2600 years using plant remains and foraminifera in a dated core of high salt-marsh sediment. The reconstruction was fused with tide-gauge data from nearby Fernandina Beach, which measured 1.91 ± 0.26 mm/year of RSL rise since 1900 CE. The average rate of RSL rise prior to 1800 CE was 0.41 ± 0.08 mm/year. Assuming negligible change in global mean sea level from meltwater input/removal and thermal expansion/contraction, this sea-level history approximates net land-level (subsidence and geoid) change, principally from glacio-isostatic adjustment. Historic rates of rise commenced at 1850–1890 CE and it is virtually certain (P = 0.99) that the average rate of 20th century RSL rise in northeastern Florida was faster than during any of the preceding 26 centuries. The linearity of RSL rise in Florida is in contrast to the variability reconstructed at sites further north on the U.S. Atlantic coast and may suggest a role for ocean dynamic effects in explaining these more variable RSL reconstructions. Comparison of the difference between reconstructed rates of late Holocene RSL rise and historic trends measured by tide gauges indicates that 20th century sea-level trends along the U.S. Atlantic coast were not dominated by the characteristic spatial fingerprint of melting of the Greenland Ice Sheet.

Late Holocene sea- and land-level change on the U.S. southeastern Atlantic coast - Kemp, Andrew C.; Bernhardt, Christopher E.; Horton, Benjamin P.; Kopp, Robert E.; Vane, Christopher H.; Peltier, W. Richard; Hawkes, Andrea D.; Donnelly, Jeffrey P.; Parnell, Andrew C.; Cahill, Niamh (Marine Geology, 2014)
Late Holocene relative sea-level (RSL) reconstructions can be used to estimate rates of land-level (subsidence or uplift) change and therefore to modify global sea-level projections for regional conditions. These reconstructions also provide the long-term benchmark against which modern trends are compared and an opportunity to understand the response of sea level to past climate variability. To address a spatial absence of late Holocene data in Florida and Georgia, we reconstructed ~ 1.3 m of RSL rise in northeastern Florida (USA) during the past ~ 2600 years using plant remains and foraminifera in a dated core of high salt-marsh sediment. The reconstruction was fused with tide-gauge data from nearby Fernandina Beach, which measured 1.91 ± 0.26 mm/year of RSL rise since 1900 CE. The average rate of RSL rise prior to 1800 CE was 0.41 ± 0.08 mm/year. Assuming negligible change in global mean sea level from meltwater input/removal and thermal expansion/contraction, this sea-level history approximates net land-level (subsidence and geoid) change, principally from glacio-isostatic adjustment. Historic rates of rise commenced at 1850–1890 CE and it is virtually certain (P = 0.99) that the average rate of 20th century RSL rise in northeastern Florida was faster than during any of the preceding 26 centuries. The linearity of RSL rise in Florida is in contrast to the variability reconstructed at sites further north on the U.S. Atlantic coast and may suggest a role for ocean dynamic effects in explaining these more variable RSL reconstructions. Comparison of the difference between reconstructed rates of late Holocene RSL rise and historic trends measured by tide gauges indicates that 20th century sea-level trends along the U.S. Atlantic coast were not dominated by the characteristic spatial fingerprint of melting of the Greenland Ice Sheet.
Keywords: florida; Foraminifera; Glacio-isostatic adjustment Greenland fingerprint; Salt marsh

Late Holocene sedimentation in a high Arctic coastal setting: Simpson Lagoon and Colville Delta, Alaska - Hanna, Andrea J. M.; Allison, Mead A.; Bianchi, Thomas S.; Marcantonio, Franco; Goff, John A. (Continental Shelf Research, 2014)
Arctic coastal environments near major river outfalls, like Simpson Lagoon, Alaska and the adjacent Colville River Delta, potentially contain high-resolution sediment records useful in elucidating late Holocene Arctic sediment transport pathways and coupled terrestrial-ocean evidence of paleoclimate variability. This study utilizes a multi-tracer geochronology approach (137Cs, 239,240Pu, and 14C) tailored for high-latitude environments to determine the age models for cores collected from Simpson Lagoon, and to date seismic boundaries in shallow acoustic reflection data (CHIRP) to examine late Holocene infill patterns. Modern (~100 y) sediment accumulation rates range from 5 m of late Holocene interbedded sediments, likely derived primarily from the Colville River, with onset of accumulation occurring prior to ~3500 y BP. A paleo-high in central Simpson Lagoon, separating the two depocenters, was subaerially exposed prior to ~600 y BP. The millimeters-per-year sedimentation rates across the lagoon, coupled with the undisturbed, interbedded sediment record, indicate that these settings hold great potential to develop new Arctic paleoenvironmental records.

Late Quaternary sedimentary record and Holocene channel avulsions of the Jamuna and Old Brahmaputra River valleys in the upper Bengal delta plain - Pickering, Jennifer L.; Goodbred, Steven L.; Reitz, Meredith D.; Hartzog, Thomas R.; Mondal, Dhiman R.; Hossain, Md Saddam (Tropical Rivers of South and South-east Asia: Landscape evolution, morphodynamics and hazards, 2014)
The first Holocene stratigraphic record of river-channel occupation and switching between the Brahmaputra–Jamuna and Old Brahmaputra paleovalleys is presented here. Motivated by the Brahmaputra River's historic avulsion from the Old Brahmaputra channel to its present-day Jamuna course, we have obtained sediment and radiocarbon samples from 41 boreholes along a 120 km transect crossing these two braided-river valleys. The stratigraphy along this transect reveals sand-dominated Holocene channel systems, each bound by remnant, mud-capped Pleistocene stratigraphy. Using sediment lithology and bulk strontium concentration as a provenance indicator, we define the geometry and channel-occupation history of each paleovalley. The western Brahmaputra–Jamuna valley is broad and somewhat deeper compared with the Old Brahmaputra valley, the latter actually comprising a composite of two narrower sub-valleys bifurcated by an antecedent topographic remnant. The gently sloped valley margins (slope: 0.002 to 0.007) and high width-to-thickness ratio (W/T: ~ 1000) of the Brahmaputra–Jamuna valley suggest that it was filled primarily through lateral channel migration and the reworking of braidbelt and overbank deposits. Conversely, the two Old Brahmaputra sub-valleys have comparatively steeper valley margins (slope: 0.007 to 0.022) and lower width-to-thickness ratios (W/T: ~ 125 and ~ 250), indicating that these were filled primarily through vertical aggradation of channel sands. We attribute this disparity in valley geometry and fill processes to the different occupation histories for each valley. In this case, the much larger Brahmaputra–Jamuna valley represents the principal, if not singular, river course during the last lowstand of sea-level, with a prominent gravel lag underlying the valley. In contrast the smaller Old Brahmaputra valleys do not appear to have been present, or at least well developed, at the last lowstand. Rather these courses were first occupied during the early Holocene transgression, and we infer that the river had been previously excluded from this region by the relatively higher elevation between the Madhupur Terrace and the Shillong Massif. We also demonstrate that the Brahmaputra River experienced 3–4 major avulsions during the Holocene, with considerably longer occupation times within the principal Brahmaputra–Jamuna valley. Together these observations indicate that occupation history and antecedent topography have been important controls on river course mobility and avulsion behavior.

Modeling environmental factors affecting assimilation of bomb-produced Δ14C in the North Pacific Ocean: Implications for age validation studies - Helser, Thomas E.; Kastelle, Craig R.; Lai, Han-lin (Ecological Modelling, 2014)
The bomb-produced radiocarbon (14C) chronometer has become the gold standard for assessing the accuracy of otolith growth ring based fish age estimates. In the northeast Pacific Ocean, nearly a dozen age validation studies have been conducted, ranging from California to Alaska, most of which have relied on a single reference chronology from the Gulf of Alaska. We developed a Bayesian hierarchical model using data sets of bomb-produced radiocarbon in the northeast Pacific Ocean and investigated whether latitude and upwelling exerts an influence on the parameters that describe the rapid Δ14C increase in marine calcium carbonates. Models incorporating both latitude and upwelling as linear covariates of a 4-parameter logistic model were favored based on ΔDIC statistics. There was substantial evidence to support that the timing of the Δ14C pulse was advanced and that total Δ14C uptake increased with increasing latitude. In contrast, increased oceanographic upwelling resulted in lower total radiocarbon input as well as a delay in the timing of the pulse curve, as was demonstrated in the upwelling dominated California Current System. Within the observed latitudinal and upwelling range of the data sets examined in this study the predicted timing of the bomb pulse curve varied by as much as 3 years, which could be misinterpreted as aging error. Our results suggest that new reference chronologies may be needed for regions of the North Pacific Ocean differing in latitude, seasonal upwelling strength and other mixing factors that can potentially change the functional form of the Δ14C curve.

A multiple-tracer approach to understanding regional groundwater flow in the Snake Valley area of the eastern Great Basin, USA - Gardner, Philip M.; Heilweil, Victor M. (Applied Geochemistry, 2014)
Groundwater in Snake Valley and surrounding basins in the eastern Great Basin province of the western United States is being targeted for large-scale groundwater extraction and export. Concern about declining groundwater levels and spring flows in western Utah as a result of the proposed groundwater withdrawals has led to efforts that have improved the understanding of this regional groundwater flow system. In this study, environmental tracers (δ2H, δ18O, 3H, 14C, 3He, 4He, 20Ne, 40Ar, 84Kr, and 129Xe) and major ions from 142 sites were evaluated to investigate groundwater recharge and flow-path characteristics. With few exceptions, δ2H and δ18O show that most valley groundwater has similar ratios to mountain springs, indicating recharge is dominated by relatively high-altitude precipitation. The spatial distribution of 3H, terrigenic helium (4Heterr), and 3H/3He ages shows that modern groundwater (11 °C to the east of Snake Valley and indicate a hydraulic discontinuity between Snake and Tule Valleys across the northern Confusion Range. The combination of NGTs and 4Heterr shows that the majority of Snake Valley groundwater discharges as springs, evapotranspiration, and well withdrawals within Snake Valley rather than continuing northeastward to discharge at either Fish Springs or the Great Salt Lake Playa. The refined understanding of groundwater recharge and flow paths acquired from this multi-tracer investigation has broad implications for interbasin subsurface flow estimates and future groundwater development.

Oceanographic regimes in the northwest Labrador Sea since Marine Isotope Stage 3 based on dinocyst and stable isotope proxy records - Gibb, Olivia T.; Hillaire-Marcel, Claude; de Vernal, Anne (APEX II: Arctic Palaeoclimate and its Extremes, 2014)
Sea surface temperature (SST), salinity and density gradients in the upper water column of the northwest Labrador Sea have been reconstructed based on high resolution analysis of a core (HU2008-029-004PC) spanning the last ∼36 ka, raised off Hudson Strait. The modern analogue technique was applied to dinocyst assemblages and combined with stable isotope data from Neogloboquadrina pachyderma left-coiled (Npl) for this purpose. Three oceanographic regimes were identified, broadly corresponding to the “glacial”, “deglacial” and “postglacial” intervals. The site remained under the direct influence of the Laurentide Ice Sheet (LIS) margin until the postglacial and did not record the Bølling-Allerød warming and weakly recorded the Younger Dryas event. The “glacial” regime lasted until ∼12.2 cal ka BP. It was characterized by generally low concentrations of dinocysts within an assemblage indicative of quasi-perennial sea ice. The “deglacial” regime (ca 12.2–8.3 cal ka BP) was marked by increased biogenic fluxes and more diversified dinocyst assemblages and possibly an enhanced subsurface inflow of North East Atlantic Deep Water. Warm summer (∼11 °C) but low winter (∼0 °C) sea surface temperatures, sea ice cover during about 3 months per year, and low summer salinity (∼28) suggest strong stratification in the upper water layer in relation to meltwater supply from the LIS. Following the final drainage of glacial Lake Agassiz through Hudson Strait, which is dated here at ∼8.3 cal ka BP, and the subsequent LIS collapse, increased summer salinity (up to ∼35) was accompanied by a reduced seasonal gradient of sea surface temperature from winter (∼3.8 °C) to summer (∼8.6 °C) suggesting enhanced penetration of North Atlantic Water. Weakened stratification of the surface water layer then allowed for winter convection and Labrador Sea Water formation, which is consistent with increased Npl-δ13C values in response to higher ventilation of the subsurface water layer.

Organic matter transformation in the peat column at Marcell Experimental Forest: Humification and vertical stratification - Tfaily, Malak M.; Cooper, William T.; Kostka, Joel E.; Chanton, Patrick R.; Schadt, Christopher W.; Hanson, Paul J.; Iversen, Colleen M.; Chanton, Jeffrey P. (JOURNAL OF GEOPHYSICAL RESEARCH-BIOGEOSCIENCES, 2014)
We characterized peat decomposition at the Marcell Experimental Forest (MEF), Minnesota, USA, to a depth of 2m to ascertain the underlying chemical changes using Fourier transform infrared (FT IR) and C-13 nuclear magnetic resonance (NMR) spectroscopy) and related these changes to decomposition proxies C:N ratio, C-13 and N-15, bulk density, and water content. FT IR determined that peat humification increased rapidly between 30 and 75cm, indicating a highly reactive intermediate-depth zone consistent with changes in C:N ratio, C-13 and N-15, bulk density, and water content. Peat decomposition at the MEF, especially in the intermediate-depth zone, is mainly characterized by preferential utilization of O-alkyl-C, carboxyl-C, and other oxygenated functionalities with a concomitant increase in the abundance of alkyl- and nitrogen-containing compounds. Below 75cm, less change was observed but aromatic functionalities and lignin accumulated with depth. Significant correlations with humification indices, identified by FT IR spectroscopy, were found for C:N ratios. Incubation studies at 22 degrees C revealed the highest methane production rates, greatest CH4:CO2 production ratios, and significant O-alkyl-C utilization within this 30 and 75cm zone. Oxygen-containing functionalities, especially O-alkyl-C, appear to serve as excellent proxies for soil decomposition rate and should be a sensitive indicator of the response of the solid phase peat to increased temperatures caused by climate change and the field study manipulations that are planned to occur at this site. Radiocarbon signatures of microbial respiration products in deeper pore waters at the MEF resembled the signatures of more modern dissolved organic carbon rather than solid phase peat, indicating that recently photosynthesized organic matter fueled the bulk of subsurface microbial respiration. These results indicate that carbon cycling at depth at the MEF is not isolated from surface processes.
Keywords: FT-IR spectroscopy; humification; NMR spectroscopy; organic matter; peatlands; vertical stratification

Origin, composition, and transformation of dissolved organic matter in tropical peatlands - Gandois, L.; Teisserenc, R.; Cobb, A. R.; Chieng, H. I.; Lim, L. B. L.; Kamariah, A. S.; Hoyt, A.; Harvey, C. F. (Geochimica et Cosmochimica Acta, 2014)
Solid and dissolved organic matter (DOM) compositions were investigated in a pristine and a deforested tropical peat forest in Brunei Darussalam. A combination of elemental (%C, %N, C/N), isotopic (δ15N, δ13C, Δ14C), molecular (lignin phenol biomarkers) and optical (Specific UV Absorbance at 280 nm (SUVA280), fluorescence index (FI)) analyses were performed to characterize DOM in porewater and river water. The DOM composition was compared to vegetation and peat to assess DOM origin and transformations in the ecosystem. Significant relationships were observed between optical properties (SUVA280, FI) and bulk (Δ14C) and molecular (ratio of cinnamyl to vanillyl phenols, C/V) composition of DOM. The radiocarbon content of DOM shows that it is modern at both sites for both surface and deep (to 4.5 m) samples (Δ14C = 74.58 ± 8.53‰ at the pristine site and Δ14C = 87.84 ± 4.5‰ at the deforested site for the first 2 meters), indicating transport of young DOM to deeper layers. Stable carbon-13 content of vegetation, peat and DOM showed only slight fractionation and ranged from −32.2‰ to −28.3‰. Nitrogen showed a greater shift between ecosystem pools. Nitrogen-15 content was higher in the solid peat (δ15N = −0.92 ± 0.49‰ in the pristine site, δ15N = −1.22 ± 1.37‰ in the deforested site) than in DOM (δ15N = −4.2 ± 2.5‰ in the pristine site, δ15N = −4.1 ± 2.3‰ in the deforested site). This difference in δ15N is significantly correlated with the C/N values of peat and DOM and attributable to higher microbial degradation in the peat compared to DOM. Porewater DOM contains less lignin (λ8 = 1.10 ± 0.27 mg 100 mg dw−1 in the pristine site and λ8 = 1.38 ± 0.46 mg 100 mg dw−1 in the deforested site) than does the solid peat (λ8 = 5.66 ± 2.14 mg 100 mg dw−1 in the pristine site and λ8 = 10.29 ± 4.69 mg 100 mg dw−1 in the deforested site). All indicators of lignin degradation (P/(V + S), 3,5Bd/V, (Ad/Al)V, (Ad/Al)S) are significantly higher in DOM than in the solid peat. This shows that lignin can be processed rapidly in the porewater of upper layers of tropical peatlands. Logging activity affected the composition of organic matter at the deforested site. Higher lignin content (λ8) was observed in the solid peat, and the composition of DOM differed greatly in the deforested site: Δ14C, FI, 3,5Bd/V, (Ad/Al)V are significantly different from the pristine site. Thus it appears that the composition of DOM is more sensitive than the solid phase to the effects of land use change on organic matter dynamic in tropical peatlands.

Phylogeny and phylogeography of functional genes shared among seven terrestrial subsurface metagenomes reveal N-cycling and microbial evolutionary relationships - Lau, Maggie C. Y.; Cameron, Connor; Magnabosco, Cara; Brown, C. Titus; Schilkey, Faye; Grim, Sharon; Hendrickson, Sarah; Pullin, Michael; Lollar, Barbara Sherwood; Van Heerden, Esta; Kieft, Thomas L.; Onstott, Tullis C. (FRONTIERS IN MICROBIOLOGY, 2014)
Comparative studies on community phylogenetics and phylogeography of microorganisms living in extreme environments are rare. Terrestrial subsurface habitats are valuable for studying microbial biogeographical patterns due to their isolation and the restricted dispersal mechanisms. Since the taxonomic identity of a microorganism does not always correspond well with its functional role in a particular community, the use of taxonomic assignments or patterns may give limited inference on how microbial functions are affected by historical, geographical and environmental factors. With seven metagenomic libraries generated from fracture water samples collected from five South African mines, this study was carried out to (1) screen for ubiquitous functions or pathways of biogeochemical cycling of CH4, S, and N; (2) to characterize the biodiversity represented by the common functional genes; (3) to investigate the subsurface biogeography as revealed by this subset of genes; and (4) to explore the possibility of using metagenomic data for evolutionary study. The ubiquitous functional genes are NarV, NPD, PAPS reductase, NifH, NifD, NifK, NifE, and NifN genes. Although these eight common functional genes were taxonomically and phylogenetically diverse and distinct from each other, the dissimilarity between samples did not correlate strongly with geographical or environmental parameters or residence time of the water. Por genes homologous to those of Thermodesulfovibrio yellowstonii detected in all metagenomes were deep lineages of Nitrospirae, suggesting that subsurface habitats have preserved ancestral genetic signatures that inform the study of the origin and evolution of prokaryotes.
Keywords: evolution; functional genes; N-cycle; phylogenetics; phylogeny; phylogeography; terrestrial subsurface

Pre-aged plant waxes in tropical lake sediments and their influence on the chronology of molecular paleoclimate proxy records - Douglas, Peter M. J.; Pagani, Mark; Eglinton, Tim E.; Brenner, Mark; Hodell, David A.; Curtis, Jason H.; Ma, Keith; Breckenridge, Andy (Geochimica et Cosmochimica Acta, 2014)
Sedimentary records of plant-wax hydrogen (δDwax) and carbon (δ13Cwax) stable isotopes are increasingly applied to infer past climate change. Compound-specific radiocarbon analyses, however, indicate that long time lags can occur between the synthesis of plant waxes and their subsequent deposition in marginal marine sediments. The influence of these time lags on interpretations of plant-wax stable isotope records is presently unconstrained, and it is unclear whether such time lags also affect lacustrine sediments. We present compound-specific radiocarbon (14Cwax) data for n-alkanoic acid plant waxes (n-C26 to n-C30) from: 1) a sediment core from Lake Chichancanab, Yucatan Peninsula, Mexico, 2) soils in the Lake Chichancanab catchment, and 3) surface sediments from three other lakes in southeastern Mexico and northern Guatemala. 14Cwax ages in the surface sediments are consistently older than modern, and may be negatively correlated with mean annual precipitation and positively correlated with lake catchment area. 14Cwax ages in soils surrounding Lake Chichancanab increase with soil depth, consistent with deep, subsoil horizons being the primary source of lacustrine aged plant waxes, which are likely delivered to lake sediments through subsurface transport. Plant waxes in the Lake Chichancanab core are 350 to 1200 years older than corresponding ages of bulk sediment deposition, determined by 14C dates on terrestrial plant macrofossils in the core. A δDwax time series is in closer agreement with other regional proxy hydroclimate records when a plant-wax 14C age model is applied, as opposed to the macrofossil-based core chronology. Inverse modeling of plant-wax age distribution parameters suggests that plant waxes in the Lake Chichancanab sediment core derive predominantly from millennial-age soil carbon pools that exhibit relatively little age variance (< 200 years). Our findings demonstrate that high-temporal-resolution climate records inferred from stable isotope measures on plant waxes in lacustrine sediments may suffer from possible chronologic distortions as a consequence of long residence times of plant waxes in soils. They also underscore the importance of direct radiocarbon dating of these organic molecules.

Preferential burial of permafrost-derived organic carbon in Siberian-Arctic shelf waters - Vonk, Jorien E.; Semiletov, Igor P.; Dudarev, Oleg V.; Eglinton, Timothy I.; Andersson, August; Shakhova, Natalia; Charkin, Alexander; Heim, Birgit; Gustafsson, Örjan (JOURNAL OF GEOPHYSICAL RESEARCH-OCEANS, 2014)
The rapidly changing East Siberian Arctic Shelf (ESAS) receives large amounts of terrestrial organic carbon (OC) from coastal erosion and Russian-Arctic rivers. Climate warming increases thawing of coastal Ice Complex Deposits (ICD) and can change both the amount of released OC, as well as its propensity to be converted to greenhouse gases (fueling further global warming) or to be buried in coastal sediments. This study aimed to unravel the susceptibility to degradation, and transport and dispersal patterns of OC delivered to the ESAS. Bulk and molecular radiocarbon analyses on surface particulate matter (PM), sinking PM and underlying surface sediments illustrate the active release of old OC from coastal permafrost. Molecular tracers for recalcitrant soil OC showed ages of 3.4-13 C-14-ky in surface PM and 5.5-18 C-14-ky in surface sediments. The age difference of these markers between surface PM and surface sediments is larger (i) in regions with low OC accumulation rates, suggesting a weaker exchange between water column and sediments, and (ii) with increasing distance from the Lena River, suggesting preferential settling of fluvially derived old OC nearshore. A dual-carbon end-member mixing model showed that (i) contemporary terrestrial OC is dispersed mainly by horizontal transport while being subject to active degradation, (ii) marine OC is most affected by vertical transport and also actively degraded in the water column, and (iii) OC from ICD settles rapidly and dominates surface sediments. Preferential burial of ICD-OC released into ESAS coastal waters might therefore lower the suggested carbon cycle climate feedback from thawing ICD permafrost.
Keywords: biomarkers; carbon; permafrost; radiocarbon

Seafloor fault ruptures along the North Anatolia Fault in the Marmara Sea, Turkey: Link with the adjacent basin turbidite record - McHugh, Cecilia M. G.; Braudy, Nicole; Çağatay, M. Namik; Sorlien, Christopher; Cormier, Marie-Helene; Seeber, Leonardo; Henry, Pierre (Marine Geology, 2014)
The relation between seafloor fault ruptures and the generation of turbidity currents was investigated to better understand the structural growth of tectonic basins with direct implications for earthquake hazard assessment. This study focuses on the Holocene earthquake record of transtensional basins in the Marmara Sea, Turkey, that are associated with the North Anatolian Fault system. The physical and chemical composition of three 10 m-long cores recovered from the Central Basin was studied at high-resolution and turbidite–homogenite units were identified. Turbidite–homogenite units (T–H units) are complex deposits that consist of a sharp basal contact and multiple fining upward beds of sand to coarse silt, above. All are capped by a 25 cm to 75 cm thick layer of medium to fine silt. A chronology developed from radiocarbon and short-lived radioisotopes allowed the correlation of these T–H units to the historical record of earthquakes that in Turkey goes back 2000 years. We found that the best location to recover the most complete sedimentation record is in the deepest part of a basin or “depocenter” where T–H units constitute ~ 80% of the sediments. A very good correlation was established between T–H units in Central Basin and proximal inferred historic epicentres along the central Marmara segment of the North Anatolia Fault that occurred in 1343, 860, 740, and 557 AD, and two more distal earthquakes that occurred in 268 and 1963 (or possibly1964). These sedimentation events can then be referred to as “seismo-turbidites”. The results when compared to findings from other transform basins in Marmara Sea reveal a very good correlation between T–H units and historic ruptures. Most importantly, there is a strong correlation between the inferred locations of historical earthquakes and the preservation of turbidite–homogenite units in the basin adjacent to the inferred rupture. The 740 AD earthquake correlates with T–H units in Izmit Gulf and Central Basin and could represent a multi-segment rupture of the NAF. Generally, T–H units appear to be clustered through the Holocene sections, suggesting temporal earthquake clustering in the Marmara Sea region. Such clustering may account for the lack of T–H units and hence large ruptures through the Central Basin since 1343.

Seasonal variability of organic matter composition in an Alaskan glacier outflow: insights into glacier carbon sources - Spencer, Robert G M; Vermilyea, Andrew; Fellman, Jason; Raymond, Peter; Stubbins, Aron; Scott, Durelle; Hood, Eran (Environmental Research Letters, 2014)
Glacier ecosystems are a significant source of bioavailable, yet ancient dissolved organic carbon (DOC). Characterizing DOC in Mendenhall Glacier out flow (southeast Alaska) we document a seasonal persistence to the radiocarbon-depleted signature of DOC, highlighting ancient DOC as a ubiquitous feature of glacier out flow. We observed no systematic depletion in Δ14C-DOC with increasing discharge during the melt season that would suggest mobilization of an aged subglacial carbon store. However, DOC concentration, δ13C-DOC,Δ14C-DOC and fluorescence signatures appear to have been in fluenced by runoff from vegetated hillslopes above the glacier during onset and senescence of melt. In the peak glacier melt period, the Δ 14 C-DOC of stream samples at the out flow (−181.7 to−355.3‰) was comparable to the Δ 14 C-DOC for snow samples from the accumulation zone (−207.2 to−390.9‰), suggesting that ancient DOC from the glacier surface is exported in glacier runoff. The pre-aged DOC in glacier snow and runoff is consistent with contributions from fossil fuel combustion sources similar to those documented previously in ice cores and thus provides evidence for anthropogenic perturbation of the carbon cycle. Overall, our results emphasize the need to further characterize DOC inputs to glacier ecosystems, particularly in light of predicted changes in glacier mass and runoff in the coming century.
Keywords: alaska; dissolved organic carbon; glacier; organic matter; radiocarbon

Sedimentation patterns on a cold-water coral mound off Mauritania - Eisele, Markus; Frank, Norbert; Wienberg, Claudia; Titschack, Jürgen; Mienis, Furu; Beuck, Lydia; Tisnerat-Laborde, Nadine; Hebbeln, Dierk (Biology and Geology of Deep-Sea Coral Ecosystems: Proceedings of the Fifth International Symposium on Deep Sea Corals, 2014)
An unconformity-bound glacial sequence (135 cm thick) of a coral-bearing sediment core collected from the flank of a cold-water coral mound in the Banda Mound Province off Mauritania was analysed. In order to study the relation between coral framework growth and its filling by hemipelagic sediments, U-series dates obtained from the cold-water coral species Lophelia pertusa were compared to 14C dates of planktonic foraminifera of the surrounding matrix sediments. The coral ages, ranging from 45.1 to 32.3 ka BP, exhibit no clear depositional trend, while on the other hand the 14C dates of the matrix sediment provide ages within a much narrower time window of <3000 yrs (34.6–31.8 cal ka BP), corresponding to the latest phase of the coral growth period. In addition, high-resolution computer tomography data revealed a subdivision of the investigated sediment package into three distinct parts, defined by the portion and fragmentation of corals and associated macrofauna as well as in the density of the matrix sediments. Grain size spectra obtained on the matrix sediments show a homogeneous pattern throughout the core sediment package, with minor variations. These features are interpreted as indicators of redeposition. Based on the observed structures and the dating results, the sediments were interpreted as deposits of a mass wasting event, namely a debris flow. During this event, the sediment unit must have been entirely mixed; resulting in averaging of the foraminifera ages from the whole unit and giving randomly distributed coral ages. In this context, for the first time mass wasting is proposed to be a substantial process of mound progradation by exporting material from the mound top to the flanks. Hence, it may not only be an erosional feature but also widening the base of the mound, thus allowing further vertical mound growth.

Silicon isotopes indicate enhanced carbon export efficiency in the North Atlantic during deglaciation - Hendry, Katharine R.; Robinson, Laura F.; McManus, Jerry F.; Hays, James D. (Nature Communications, 2014)
Today’s Sargasso Sea is nutrient starved, except for episodic upwelling events caused by wind-driven winter mixing and eddies. Enhanced diatom opal burial in Sargasso Sea sediments indicates that silicic acid, a limiting nutrient today, may have been more available in subsurface waters during Heinrich Stadials, millennial-scale climate perturbations of the last glacial and deglaciation. Here we use the geochemistry of opal-forming organisms from different water depths to demonstrate changes in silicic acid supply and utilization during the most recent Heinrich Stadial. We suggest that during the early phase (17.5–18 ka), wind-driven upwelling replenished silicic acid to the subsurface, resulting in low Si utilization. By 17 ka, stratification reduced the surface silicic acid supply leading to increased Si utilization efficiency. This abrupt shift in Si cycling would have contributed to high regional carbon export efficiency during the recent Heinrich Stadial, despite being a period of increasing atmospheric CO2.
Keywords: Biogeochemistry; Cryospheric science; Ocean sciences

Source and biolability of ancient dissolved organic matter in glacier and lake ecosystems on the Tibetan Plateau - Spencer, Robert G.M.; Guo, Weidong; Raymond, Peter A.; Dittmar, Thorsten; Hood, Eran; Fellman, Jason; Stubbins, Aron (Geochimica et Cosmochimica Acta, 2014)
The Tibetan Plateau is the world’s largest and highest plateau and holds the largest mass of ice on Earth outside the ice-sheets of Greenland and Antarctica, as well as abundant lakes. This study examined the molecular and isotopic signatures of dissolved organic matter (DOM) along with its biolability in glacier ice, glacier-fed streams, and alpine lakes on the Tibetan Plateau. The aim was to assess the sources of DOM and the potential of DOM to provide a carbon subsidy to downstream ecosystems. Tibetan glaciers and glacier streams exhibited low dissolved organic carbon (DOC) concentrations (17.7–27.9 μM) and ancient DOC radiocarbon ages (749–2350 ybp). The optical properties, stable carbon isotope ratios (δ13C-DOC) and the molecular composition (Fourier transform ion cyclotron resonance mass spectrometry) of Tibetan glacier DOM are consistent with data from other glacier systems around the world. The geochemical signatures and the ancient apparent ages of Tibetan glacier DOM suggest a significant fraction is derived from the atmospheric deposition of pre-aged, possibly fossil fuel derived organics. Within the Tibetan alpine lakes, DOC was also ancient (525–675 ybp), due to either inputs of pre-aged organics from glacier runoff, direct deposition, or due to the aging of organics in situ (i.e. a radiocarbon reservoir effect). The glacier ice and glacier stream sites exhibited high biolability of DOC and so provide a carbon subsidy to downstream environments that will change as glaciers on the Tibetan Plateau recede.

Submarine Paleoseismology Along Populated Transform Boundaries: The Enriquillo-Plantain-Garden Fault, Canal du Sud, Haiti, and the North Anatolian Fault, Marmara Sea, Turkey - McHugh, Cecilia M. G.; Seeber, Leonardo; Cormier, Marie-Helene; Hornbach, Matthew (OCEANOGRAPHY, 2014)
Continental transform boundaries cross heavily populated regions and are associated with destructive earthquakes worldwide. The devastating 1999 Turkey earthquakes and the offshore 2010 Haiti earthquake emphasized the urgent need to study the submerged segments of continental transforms. In response, the rapidly evolving field of submarine paleoseismology is focusing its attention on understanding the relationships between sedimentation, seafloor ruptures, and earthquake recurrence intervals along submarine faults. In Canal du Sud, Haiti, the 2010 earthquake-triggered sedimentation events were documented from nearshore to the deep basin by measuring the excess Th-234 in sediment cores. This radioisotope, with a half-life of 24 days, tracked mass wasting, turbidites, turbidite-homogenite units, and a sediment plume that remained in the water column for at least two months after the earthquake. However, the turbidite units in Canal du Sud, Haiti, provide an incomplete record of the region's earthquake history, likely because sedimentation rates are too low for sedimentation events to be triggered by all earthquakes. In contrast, in the Marmara Sea basins, there is very good correlation between turbidites and the historical record of earthquakes dating back 2,000 years. The difference between these correlations is likely related to both sedimentation rates and particulars of the ruptures. Future research along the Enriquillo-Plantain-Garden fault in Haiti and along similar low sedimentation plate boundaries should focus on multiple fault segments in order to obtain complete earthquake recurrence histories.

Ta'u and Ofu/Olosega volcanoes: The ``Twin Sisters'' of Samoa, their P, T, X melting regime, and global implications - Hart, Stanley R.; Jackson, Matthew G. (GEOCHEMISTRY GEOPHYSICS GEOSYSTEMS, 2014)
The Samoan islands of Ta'u and Ofu/Olosega (Ofol hereafter) are single shield volcanoes that have erupted alkali basalt for the past 70 and 440 kyr, respectively. They are 20 km apart, and are the easternmost subaerial expressions of the Samoan plume. The isotopic data for these islands are published; we report here the first major and trace element data for Ofol. The two islands are similar isotopically and in trace elements. Their high He-3/He-4 marks them as being a FOZO mantle end-member. By comparing data from both volcanoes, we test the efficacy of melting models in constraining the mantle compositions and their P-T of melting. We show that the mantle sources are similar, with spidergrams that peak at Ta ( 4 x BSE), and Lu similar to 0.5 x BSE. Melts and mantle sources both have Lu/Hf ratios that are too low to support measured Hf-176/Hf-177 ratios, pointing to a young enrichment event in the mantle source. Degrees of melting are 6.5% for Ta'u and 5.2% for Ofol. P-T of melting show a wide, overlapping range, but define a precise array; average values are 1475 degrees C-77 km for Ta'u and 1550 degrees C-110 km for Ofol. The deepest P-T estimate is 4.2 GPa and 1550 degrees C. The P-T array is either a melting adiabat, or a mixing line of melts equilibrated at various depths. Kinetic modeling shows melt re-equilibration will be likely for ascent velocities (m/yr) less than 40/(conduit radius in cm)(2). P-T estimates for melting may typically be minimum values.

Uplift and subsidence reveal a nonpersistent megathrust rupture boundary (Sitkinak Island, Alaska) - Briggs, Richard W.; Engelhart, Simon E.; Nelson, Alan R.; Dura, Tina; Kemp, Andrew C.; Haeussler, Peter J.; Corbett, D. Reide; Angster, Stephen J.; Bradley, Lee-Ann (Geophysical Research Letters, 2014)
We report stratigraphic evidence of land-level change and tsunami inundation along the Alaska-Aleutian megathrust during prehistoric and historical earthquakes west of Kodiak Island. On Sitkinak Island, cores and tidal outcrops fringing a lagoon reveal five sharp lithologic contacts that record coseismic land-level change. Radiocarbon dates, 137Cs profiles, computerized tomography scans, and microfossil assemblages are consistent with rapid uplift circa 290–0, 520–300, and 1050–790 cal yr B.P. and subsidence in A.D. 1964 and circa 640–510 cal yr B.P. Radiocarbon, 137Cs, and 210Pb ages bracketing a sand bed traced 1.5 km inland and evidence for sudden uplift are consistent with Russian accounts of an earthquake and tsunami in A.D. 1788. The mixed uplift and subsidence record suggests that Sitkinak Island sits above a nonpersistent boundary near the southwestern limit of the A.D. 1964 Mw 9.2 megathrust rupture.

Using Natural Abundance Radiocarbon To Trace the Flux of Petrocarbon to the Seafloor Following the Deepwater Horizon Oil Spill - Chanton, Jeffrey; Zhao, Tingting; Rosenheim, Brad E.; Joye, Samantha; Bosman, Samantha; Brunner, Charlotte; Yeager, Kevin M.; Diercks, Arne R.; Hollander, David (Environmental science & technology, 2014)
In 2010, the Deepwater Horizon accident released 4.6?6.0 ? 1011 grams or 4.1 to 4.6 million barrels of fossil petroleum derived carbon (petrocarbon) as oil into the Gulf of Mexico. Natural abundance radiocarbon measurements on surface sediment organic matter in a 2.4 ? 1010 m2 deep-water region surrounding the spill site indicate the deposition of a fossil-carbon containing layer that included 1.6 to 2.6 ? 1010 grams of oil-derived carbon. This quantity represents between 0.5 to 9.1% of the released petrocarbon, with a best estimate of 3.0?4.9%. These values may be lower limit estimates of the fraction of the oil that was deposited on the seafloor because they focus on a limited mostly deep-water area of the Gulf, include a conservative estimate of thickness of the depositional layer, and use an average background or prespill radiocarbon value for sedimentary organic carbon that produces a conservative value. A similar approach using hopane tracer estimated that 4?31% of 2 million barrels of oil that stayed in the deep sea settled on the bottom. Converting that to a percentage of the total oil that entered into the environment (to which we normalized our estimate) converts this range to 1.8 to 14.4%. Although extrapolated over a larger area, our independent estimate produced similar values.; In 2010, the Deepwater Horizon accident released 4.6?6.0 ? 1011 grams or 4.1 to 4.6 million barrels of fossil petroleum derived carbon (petrocarbon) as oil into the Gulf of Mexico. Natural abundance radiocarbon measurements on surface sediment organic matter in a 2.4 ? 1010 m2 deep-water region surrounding the spill site indicate the deposition of a fossil-carbon containing layer that included 1.6 to 2.6 ? 1010 grams of oil-derived carbon. This quantity represents between 0.5 to 9.1% of the released petrocarbon, with a best estimate of 3.0?4.9%. These values may be lower limit estimates of the fraction of the oil that was deposited on the seafloor because they focus on a limited mostly deep-water area of the Gulf, include a conservative estimate of thickness of the depositional layer, and use an average background or prespill radiocarbon value for sedimentary organic carbon that produces a conservative value. A similar approach using hopane tracer estimated that 4?31% of 2 million barrels of oil that stayed in the deep sea settled on the bottom. Converting that to a percentage of the total oil that entered into the environment (to which we normalized our estimate) converts this range to 1.8 to 14.4%. Although extrapolated over a larger area, our independent estimate produced similar values.

Validated age and growth estimates for Carcharhinus obscurus in the northwestern Atlantic Ocean, with pre- and post management growth comparisons - Natanson, Lisa J.; Gervelis, Brian J.; Winton, Megan V.; Hamady, Li Ling; Gulak, Simon J. B.; Carlson, John K. (Environmental Biology of Fishes, 2014)
Age and growth estimates for the dusky shark, Carcharhinus obscurus, were derived from vertebral centra collected in the northwestern Atlantic Ocean. Sample collection spanned the years prior to and following the implementation ofmanagementmeasures (1963– 2010). Growth was compared pre- and post- population depletion and pre- and post- management to investigate the possibility of density-mediated shifts in age and growth parameters over time. There was no evidence of difference between periods for either sex. Additionally, bomb radiocarbon dating was used to determine the periodicity of band pair formation. Results support the traditional interpretation of annual band pairs up to approximately 11 years of age. After this time, vertebral counts considerably underestimate true age. Maximum validated ages were estimated to be between 38 and 42 years of age (an increase of 15 to 19 years over the band count estimates), confirming longevity to at least 42 years of age. Growth curves estimated using only validated data were compared to those generated using band pair counts. Logistic growth parameters derived from validated vertebral length-at-age data were L∞=261.5 cm FL, Lo=85.5 cm, to=4.89 year and g=0.15 year−1 for the sexes combined. Revised estimates of age at maturity were 17.4 years for males and 17.6 years for females.
Keywords: Age and growth; bomb radiocarbon; Dusky shark; Elasmobranch; Validation; Vertebrae

Vertebral Bomb Radiocarbon Suggests Extreme Longevity in White Sharks - Hamady, Li Ling; Natanson, Lisa J.; Skomal, Gregory B.; Thorrold, Simon R. (Plos One, 2014)
Conservation and management efforts for white sharks (Carcharodon carcharias) remain hampered by a lack of basic demographic information including age and growth rates. Sharks are typically aged by counting growth bands sequentially deposited in their vertebrae, but the assumption of annual deposition of these band pairs requires testing. We compared radiocarbon (Delta C-14) values in vertebrae from four female and four male white sharks from the northwestern Atlantic Ocean (NWA) with reference chronologies documenting the marine uptake of C-14 produced by atmospheric testing of thermonuclear devices to generate the first radiocarbon age estimates for adult white sharks. Age estimates were up to 40 years old for the largest female (fork length [FL]: 526 cm) and 73 years old for the largest male (FL: 493 cm). Our results dramatically extend the maximum age and longevity of white sharks compared to earlier studies, hint at possible sexual dimorphism in growth rates, and raise concerns that white shark populations are considerably more sensitive to human-induced mortality than previously thought.
PT: J; TC: 0; UT: WOS:000329862500089

14.31 Radiocarbon Dating of Plant Macrofossils from Tidal-Marsh Sediment - Kemp, A. C.; Nelson, A. R.; Horton, B. P. (Treatise on Geomorphology, 2013)
Tidal-marsh sediment is an archive of Holocene environmental changes, including movements of sea and land levels, and extreme events such as hurricanes, earthquakes, and tsunamis. Accurate and precise radiocarbon dating of environmental changes is necessary to estimate rates of change and the recurrence interval (frequency) of events. Plant macrofossils preserved in growth position (or deposited soon after death) in tidal-marsh sediment are ideal samples for dating such changes. In this chapter, we focus on the selection of plant macrofossils for radiocarbon dating and the application of ages from different types of macrofossils to varied research projects, and make recommendations for selection and preparation of tidal-marsh samples for dating.
id: 2293

Annually Resolved Ice Core Records of Tropical Climate Variability over the Past similar to 1800 Years - Thompson, L. G.; Mosley-Thompson, E.; Davis, M. E.; Zagorodnov, V. S.; Howat, I. M.; Mikhatenko, V. N.; Lin, P. -N. (SCIENCE, 2013)
Ice cores from low Latitudes can provide a wealth of unique information about past climate in the tropics, but they are difficult to recover and few exist. Here, we report annually resolved ice core records from the Quelccaya ice cap (5670 meters above sea level) in Peru that extend back similar to 1800 years and provide a high-resolution record of climate variability there. Oxygen isotopic ratios (delta O-18) are linked to sea surface temperatures in the tropical eastern Pacific, whereas concentrations of ammonium and nitrate document the dominant role played by the migration of the Intertropical Convergence Zone in the region of the tropical Andes. Quetccaya continues to retreat and thin. Radiocarbon dates on wetland plants exposed along its retreating margins indicate that it has not been smaller for at least six millennia.

Bomb radiocarbon dating of the endangered white abalone (Haliotis sorenseni): investigations of age, growth and lifespan - Andrews, Allen H.; Leaf, Robert T.; Rogers-Bennett, Laura; Neuman, Melissa; Hawk, Heather; Cailliet, Gregor M. (Marine and Freshwater Research, 2013)
Understanding basic life-history characteristics of white abalone (Haliotis sorenseni), such as estimated lifespan, is critical to making informed decisions regarding the recovery of this endangered species. All predictive modelling tools used to forecast the status and health of populations following restoration activities depend on a validated estimate of adult lifespan. Of the seven Haliotis species in California, white abalone is considered to have the highest extinction risk and was the first marine invertebrate listed as an endangered species under the Federal Endangered Species Act (ESA). Lifespan was previously estimated from observations of early growth; however, no study has generated ages for the largest white abalone. To address questions of age and growth, bomb radiocarbon (C-14) dating was used on shells from large white abalone. Measured bomb C-14 levels were compared to regional C-14 reference records to provide estimates of age, growth and lifespan. Bomb radiocarbon dating indicated that growth was variable among individuals, with a maximum estimated age of 27 years. The findings presented here provide support for previous age and growth estimates and an estimated lifespan near 30 years. These age data support the perception of a critical need for restoring the remnant aging and potentially senescent population.
id: 2351; PT: J; TC: 0; UT: WOS:000326166400004

A California Current bomb radiocarbon reference chronology and petrale sole (Eopsetta jordani) age validation - Haltuch, Melissa A.; Hamel, Owen S.; Piner, Kevin R.; McDonald, Patrick; Kastelle, Craig R.; Field, John C. (Canadian Journal of Fisheries and Aquatic Sciences, 2013)

Evidence for a transgressive barrier within a regressive strandplain system: Implications for complex coastal response to environmental change - Hein, Christopher J.; FitzGerald, Duncan M.; Cleary, William J.; ALBERNAZ, MARCIO B.; De MENEZES, JOAO THADEU; Klein, Antonio H. da F. (Sedimentology, 2013)
Clastic, depositional strandplain systems have the potential to record changes in the primary drivers of coastal evolution: climate, sea-level, and the frequency of major meteorological and oceanographic events. This study seeks to use one such record from a southern Brazilian strandplain to highlight the potentially-complex nature of coastal sedimentological response to small changes in these drivers. Following a 2 to 4 m highstand at ca 5·8 ka in southern Brazil, falling sea-level reworked shelf sediment onshore, forcing coastal progradation, smoothing the irregular coastline and forming the 5 km wide Pinheira Strandplain, composed of ca 500 successive beach and dune ridges. Sediment cores, grab samples and >11 km of ground-penetrating radar profiles reveal that the strandplain sequence is composed of well-sorted, fine to very-fine quartz sand. Since the mid-Holocene highstand, the shoreline prograded at a rate of ca 1 to 2 m yr−1 through the deposition of a 4 to 6 m thick shoreface unit; a 1 to 3 m thick foreshore unit containing ubiquitous ridge and runnel facies; and an uppermost beach and foredune unit. However, the discovery of a linear, 100 m wide barrier ridge with associated washover units, a 3 to 4 m deep lagoon and 250 m wide tidal inlet within the strandplain sequence reveals a period of shoreline transgression at 3·3 to 2·8 ka during the otherwise regressive developmental history of the plain. The protected nature of Pinheira largely buffered it from changes in precipitation patterns, wave energy and fluvial sediment supply during the time of its formation. However, multiple lines of evidence indicate that a change in the rate of relative sea-level fall, probably due to either steric or ice-volume effects, may have affected this coastline. Thus, whereas these other potential drivers cannot be fully discounted, this study provides insights into the complexity of decadal-scale to millennial-scale coastal response to likely variability in sea-level change rates.

Export of submicron particulate organic matter to mesopelagic depth in an oligotrophic gyre - Close, H. G.; Shah, S. R.; Ingalls, A. E.; Diefendorf, A. F.; Brodie, E. L.; Hansman, R. L.; Freeman, K. H.; Aluwihare, L. I.; Pearson, A. (Proceedings of the National Academy of Sciences, 2013)
Sixty percent of the world ocean by area is contained in oligotrophic gyres [Longhurst A (1995) Prog Oceanog 36:77-16], the biomass of which is dominated by picophytoplankton, including cyanobacteria and picoeukaryotic algae, as well as picoheterotrophs. Despite their recognized importance in carbon cycling in the surface ocean, the role of small cells and their detrital remains in the transfer of particulate organic matter (POM) to the deep ocean remains disputed. Because oligotrophic marine conditions are projected to expand under current climate trends, a better understanding of the role of small particles in the global carbon cycle is a timely goal. Here we use the lipid profiles, radiocarbon, and stable carbon isotopic signatures of lipids from the North Pacific Subtropical Gyre to show that in the surface ocean, lipids from submicron POM (here called extra-small POM) are distinct from larger classes of suspended POM. Remarkably, this distinct extra-small POM signature dominates the total lipids collected at mesopelagic depth, suggesting that the lipid component of mesopelagic POM primarily contains the exported remains of small particles. Transfer of submicron material to mesopelagic depths in this location is consistent with model results that claim the biological origin of exported carbon should be proportional to the distribution of cell types in the surface community, irrespective of cell size [Richardson TL, Jackson GA (2007) Science 315:838-840]. Our data suggest that the submicron component of exported POM is an important contributor to the global biological pump, especially in oligotrophic waters.
Keywords: Biogeochemistry; biomarkers; carbon isotopes; Oceanography

Extensive recession of Cordillera Darwin glaciers in southernmost South America during Heinrich Stadial 1 - Hall, Brenda L.; Porter, Charles T.; Denton, George H.; Lowell, Thomas V.; Bromley, Gordon R. M. (Quaternary Science Reviews, 2013)
The geographic expression and phasing of events during the last termination are important for isolating mechanisms that caused Earth to emerge from the last ice age. Heinrich Stadial 1 (HS1; 14,600–18,000 yr BP) is a key because of the central role that its far-field effects had on the last termination in the Southern Hemisphere. Here, we present new data from Cordillera Darwin that show rapid glacier recession in southern South America during HS1. This retreat was coeval with ice recession elsewhere in South America and New Zealand, with increased upwelling in the Southern Ocean, with warming of SSTs offshore of Chile, and with a rise in atmospheric CO2. Together, these data indicate a coherent and rapid response to the effects of HS1 in the middle and high latitudes of the Southern Hemisphere.
id: 2331

Heterogeneous rupture in the great Cascadia earthquake of 1700 inferred from coastal subsidence estimates - Wang, Pei-Ling; Engelhart, Simon E.; Wang, Kelin; Hawkes, Andrea D.; Horton, Benjamin P.; Nelson, Alan R.; Witter, Robert C. (Journal of Geophysical Research: Solid Earth, 2013)
Past earthquake rupture models used to explain paleoseismic estimates of coastal subsidence during the great A.D. 1700 Cascadia earthquake have assumed a uniform slip distribution along the megathrust. Here we infer heterogeneous slip for the Cascadia margin in A.D. 1700 that is analogous to slip distributions during instrumentally recorded great subduction earthquakes worldwide. The assumption of uniform distribution in previous rupture models was due partly to the large uncertainties of then available paleoseismic data used to constrain the models. In this work, we use more precise estimates of subsidence in 1700 from detailed tidal microfossil studies. We develop a 3-D elastic dislocation model that allows the slip to vary both along strike and in the dip direction. Despite uncertainties in the updip and downdip slip extensions, the more precise subsidence estimates are best explained by a model with along-strike slip heterogeneity, with multiple patches of high-moment release separated by areas of low-moment release. For example, in A.D. 1700, there was very little slip near Alsea Bay, Oregon (~44.4°N), an area that coincides with a segment boundary previously suggested on the basis of gravity anomalies. A probable subducting seamount in this area may be responsible for impeding rupture during great earthquakes. Our results highlight the need for more precise, high-quality estimates of subsidence or uplift during prehistoric earthquakes from the coasts of southern British Columbia, northern Washington (north of 47°N), southernmost Oregon, and northern California (south of 43°N), where slip distributions of prehistoric earthquakes are poorly constrained.

Late Holocene expansion of Istorvet ice cap, Liverpool Land, east Greenland - Lowell, Thomas V.; Hall, Brenda L.; Kelly, Meredith A.; Bennike, Ole; Lusas, Amanda R.; Honsaker, William; Smith, Colby A.; Levy, Laura B.; Travis, Scott; Denton, George H. (Quaternary Science Reviews, 2013)
The Greenland Ice Sheet is undergoing dynamic changes that will have global implications if they continue into the future. In this regard, an understanding of how the ice sheet responded to past climate changes affords a baseline for anticipating future behavior. Small, independent ice caps adjacent to the Greenland Ice Sheet (hereinafter called “local ice caps”) are sensitive indicators of the response of Greenland ice-marginal zones to climate change. Therefore, we reconstructed late Holocene ice-marginal fluctuations of the local Istorvet ice cap in east Greenland, using radiocarbon dates of subfossil plants, 10Be dates of surface boulders, and analyses of sediment cores from both threshold and control lakes. During the last termination, the Istorvet ice cap had retreated close to its maximum Holocene position by ∼11,730 cal yr BP. Radiocarbon dates of subfossil plants exposed by recent recession of the ice margin indicate that the Istorvet cap was smaller than at present from AD 200 to AD 1025. Sediments from a threshold lake show no glacial input until the ice cap advanced to within 365 m of its Holocene maximum position by ∼AD 1150. Thereafter the ice cap remained at or close to this position until at least AD 1660. The timing of this, the most extensive of the Holocene, expansion is similar to that recorded at some glaciers in the Alps and in southern Alaska. However, in contrast to these other regions, the expansion in east Greenland at AD 1150 appears to have been very close to, if not at, a maximum Holocene value. Comparison of the Istorvet ice-cap fluctuations with Holocene glacier extents in Southern Hemisphere middle-to-high latitude locations on the Antarctic Peninsula and in the Andes and the Southern Alps suggests an out-of-phase relationship. If correct, this pattern supports the hypothesis that a bipolar see-saw of oceanic and/or atmospheric circulation during the Holocene produced asynchronous glacier response at some localities in the two polar hemispheres.
id: 2290

Long-term variations in Iceland–Scotland overflow strength during the Holocene - Thornalley, D. J. R.; Blaschek, M.; Davies, F. J.; Praetorius, S.; Oppo, D. W.; McManus, J. F.; Hall, I. R.; Kleiven, H.; Renssen, H.; McCave, I. N. (Climate of the Past, 2013)
The overflow of deep water from the Nordic seas into the North Atlantic plays a critical role in global ocean circulation and climate. Approximately half of this overflow occurs via the Iceland–Scotland (I–S) overflow, yet the history of its strength throughout the Holocene (~ 0–11 700 yr ago, ka) is poorly constrained, with previous studies presenting apparently contradictory evidence regarding its long-term variability. Here, we provide a comprehensive reconstruction of I–S overflow strength throughout the Holocene using sediment grain size data from a depth transect of 13 cores from the Iceland Basin. Our data are consistent with the hypothesis that the main axis of the I–S overflow on the Iceland slope was shallower during the early Holocene, deepening to its present depth by ~ 7 ka. Our results also reveal weaker I–S overflow during the early and late Holocene, with maximum overflow strength occurring at ~ 7 ka, the time of a regional climate thermal maximum. Climate model simulations suggest a shoaling of deep convection in the Nordic seas during the early and late Holocene, consistent with our evidence for weaker I–S overflow during these intervals. Whereas the reduction in I–S overflow strength during the early Holocene likely resulted from melting remnant glacial ice sheets, the decline throughout the last 7000 yr was caused by an orbitally induced increase in the amount of Arctic sea ice entering the Nordic seas. Although the flux of Arctic sea ice to the Nordic seas is expected to decrease throughout the next century, model simulations predict that under high emissions scenarios, competing effects, such as warmer sea surface temperatures in the Nordic seas, will result in reduced deep convection, likely driving a weaker I–S overflow.

Molecular and isotopic insights into particulate organic carbon sources and dynamics in Jordan Basin, Gulf of Maine - Hwang, Jeomshik; Montluçon, Daniel B.; Pilskaln, Cynthia H.; Eglinton, Timothy I. (Continental Shelf Research, 2013)
The carbon isotope and lipid biomarker composition of suspended particles and surface sediment was measured to examine the impact of sediment supply, redistribution and post-depositional alteration processes on organic matter cycling in the Gulf of Maine, a semi-enclosed shelf sea in the northwest Atlantic. A beam attenuation profile revealed a >50 m-thick benthic nepheloid layer (BNL) in the Jordan Basin at the time of sampling (April 2006). The relatively low radiocarbon content of suspended particulate organic carbon (POC) in the BNL indicates that up to 82% of the POC in this layer was supplied from resuspension of sediment. The concentration of alkenones normalized to POC increased with increasing depth in the water column and was highest in the surface sediment. In contrast to these markers of surface ocean photoautotrophy, the vertical profiles for the concentration and composition of short-chain (C14–C18) n-alkanoic acids provided evidence for enhanced heterotrophic processes near the top of the BNL. Suspended POC samples from two depths within the BNL exhibited marked differences in radiocarbon content and fatty acid composition, suggesting that biological activity and associated processes within the BNL are vertically heterogeneous.

Onshore-offshore surficial geologic map of the Newburyport East and northern half of the Ipswich Quadrangles, Massachusetts - Hein, C.J.; FitzGerald, D.M.; Barnhardt, W.A.; Stone, B.D. (Geologic Map, 2013)
This geologic map shows the distribution of surficial subaerial and subaqueous materials in the Newburyport East and northern half of the Ipswich 7.5' quadrangles (northeast Massachusetts) and the area of the Gulf of Maine immediately offshore, to an approximate depth of 80 m below modern mean sea level (MSL). This map was compiled from the onshore surficial geologic map of Stone et al. (2006) and the offshore surficial mapping of Barnhardt et al. (2009), and includes newly mapped shallow offshore geologic features. Onshore and offshore units are continuous across the shallow- water zone (0-20 m below MSL). The definition of map units is based on lithologic characteristics (grain size, mineralogy and structure), stratigraphic relationships and relative ages, and sedimentologic processes. The map describes the evolution of the surficial geology in terms of the sediment sources, transportation mechanisms, and depositional, post-depositional and modern processes that have acted on the late Quaternary sediments that compose these units. Cross sections are derived from subsurface data compiled from the literature and collected as part of this study. This maps supersedes MGS OFR 2011-01

Persistent export of 231Pa from the deep central Arctic Ocean over the past 35,000 years - Hoffmann, Sharon S.; McManus, Jerry F.; Curry, William B.; Brown-Leger, L. Susan (Nature, 2013)
The Arctic Ocean has an important role in Earth’s climate, both through surface processes1 such as sea-ice formation and transport, and through the production and export of waters at depth that contribute to the global thermohaline circulation2, 3. Deciphering the deep Arctic Ocean’s palaeo-oceanographic history is a crucial part of understanding its role in climatic change. Here we show that sedimentary ratios of the radionuclides thorium-230 (230Th) and protactinium-231 (231Pa), which are produced in sea water and removed by particle scavenging on timescales of decades to centuries, respectively4, record consistent evidence for the export of 231Pa from the deep Arctic and may indicate continuous deep-water exchange between the Arctic and Atlantic oceans throughout the past 35,000 years. Seven well-dated box-core records provide a comprehensive overview of 231Pa and 230Th burial in Arctic sediments during glacial, deglacial and interglacial conditions. Sedimentary 231Pa/230Th ratios decrease nearly linearly with increasing water depth above the core sites, indicating efficient particle scavenging in the upper water column and greater influence of removal by lateral transport at depth. Although the measured 230Th burial is in balance with its production in Arctic sea water, integrated depth profiles for all time intervals reveal a deficit in 231Pa burial that can be balanced only by lateral export in the water column. Because no enhanced sink for 231Pa has yet been found in the Arctic, our records suggest that deep-water exchange through the Fram strait may export 231Pa. Such export may have continued for the past 35,000 years, suggesting a century-scale replacement time for deep waters in the Arctic Ocean since the most recent glaciation and a persistent contribution of Arctic waters to the global ocean circulation.
Keywords: Marine chemistry; Palaeoceanography; Palaeoclimate

Recharge Sources and Residence Times of Groundwater as Determined by Geochemical Tracers in the Mayfield Area, Southwestern Idaho, 2011–12 - Hopkins, C. B. (Scientific Investigations Report, 2013)

Resolving varve and radiocarbon chronology differences during the last 2000 years in the Santa Barbara Basin sedimentary record, California - Hendy, Ingrid L.; Dunn, L.; Schimmelmann, A.; Pak, D. K. (Quaternary International, 2013)
Santa Barbara Basin (SBB) is well known for producing high quality paleoclimate reconstructions, but the validity of correlations between the basin and other regions rests upon age model accuracy. Yet, the two independent and well-established chronologies based on varve counting and radiocarbon dating do not consistently agree during the last two millennia. Here the validity of age model assumptions is tested including whether 1) the regional reservoir age of surface waters was invariably 641 ± 119 years through time, and/or 2) SBB laminae couplets are consistently annual varves and counted with sufficient precision. This high-resolution 14C study of SBB sediments compares 49 mixed planktonic foraminiferal carbonate and 20 terrestrial organic carbon 14C dates to the varve chronology, to extend the high-resolution paleoclimate chronology of the basin back ∼2000 years. Evidence indicates that regional reservoir ages do not remain constant through time with ΔR, (i.e. regional reservoir age minus variations in the global mixed-layer ocean reservoir age) fluctuating between 80 and 350 years. Second, there is a consistent (R2 = 0.96) undercounting of the varves between 150 and ∼1700 AD based on a new varying ΔR 14C chronology, indicating that some laminae couplets may not be annual. Loss of varves may occur when low riverine input and infrequent winter storm activity during drought intervals fail to supply a siliciclastic layer.
id: 2289

Sea-level change during the last 2500 years in New Jersey, USA - Kemp, Andrew C.; Horton, Benjamin P.; Vane, Christopher H.; Bernhardt, Christopher E.; Corbett, D. Reide; Engelhart, Simon E.; Anisfeld, Shimon C.; Parnell, Andrew C.; Cahill, Niamh (Quaternary Science Reviews, 2013)
Relative sea-level changes during the last ∼2500 years in New Jersey, USA were reconstructed to test if late Holocene sea level was stable or included persistent and distinctive phases of variability. Foraminifera and bulk-sediment δ13C values were combined to reconstruct paleomarsh elevation with decimeter precision from sequences of salt-marsh sediment at two sites using a multi-proxy approach. The additional paleoenvironmental information provided by bulk-sediment δ13C values reduced vertical uncertainty in the sea-level reconstruction by about one third of that estimated from foraminifera alone using a transfer function. The history of sediment deposition was constrained by a composite chronology. An age–depth model developed for each core enabled reconstruction of sea level with multi-decadal resolution. Following correction for land-level change (1.4 mm/yr), four successive and sustained (multi-centennial) sea-level trends were objectively identified and quantified (95% confidence interval) using error-in-variables change point analysis to account for age and sea-level uncertainties. From at least 500 BC to 250 AD, sea-level fell at 0.11 mm/yr. The second period saw sea-level rise at 0.62 mm/yr from 250 AD to 733 AD. Between 733 AD and 1850 AD, sea level fell at 0.12 mm/yr. The reconstructed rate of sea-level rise since ∼1850 AD was 3.1 mm/yr and represents the most rapid period of change for at least 2500 years. This trend began between 1830 AD and 1873 AD. Since this change point, reconstructed sea-level rise is in agreement with regional tide-gauge records and exceeds the global average estimate for the 20th century. These positive and negative departures from background rates demonstrate that the late Holocene sea level was not stable in New Jersey.

Should dates trump context? Evaluation of the Cave 7 skeletal assemblage radiocarbon dates - Geib, Phil R.; Hurst, Winston B. (Journal of Archaeological Science, 2013)
“Massacre” was the accepted interpretation for a prehistoric skeletal assemblage of around 90 individuals from Cave 7 in the SE Utah of the North American Southwest since the 1890s. Coltrain and others (Journal of Archaeological Science 39, 2220–2230) rejected this account based on a dispersed suite of AMS radiocarbon dates on purified bone collagen from the interred individuals. Since dates from skeletons exhibiting perimortem damage were scattered across some 400 radiocarbon years, Coltrain et al. argued for multiple interments of victims of violence and related kin spread across several centuries. The temporal placement of interment events in Cave 7 clearly cannot be known independent of radiocarbon assays but such assays should not be privileged above contextual information about which individuals were interred together unless verified by an independent dating laboratory. Only by ignoring important information about burial context in the 1893 field record can the dates of Coltrain et al. be accepted as accurate estimates of time of death. We redated residual collagen from 11 of the Cave 7 individuals because of significant contextual anomalies with some of the prior results. The new assays combined with contextual evidence demonstrate that some of Coltrain et al.’s dates are either too old or too young; the dates are neither sufficiently accurate (true estimates of sample age) nor sufficiently precise (small confidence intervals) to refute a single-event massacre or to confirm multiple interment events in Cave 7. Nonetheless, dates that meet these criteria disclose at least two interment events, a large one of mostly adult males, many exhibiting perimortem damage (a massacre assemblage), and a small one consisting of an adult female with three children. A third interment event of a few adult females and child is possible based primarily on context since the date distribution in this case overlaps substantially with that of the massacre victims; context also hints at other interment events. Aside from chronology we clarify the number of Basketmaker individuals interred at the site and the incidence of perimortem violence. A single-event mass killing continues to be the most likely interpretation for around 58 individuals, mostly adult males (at least 35) but also adult females and children. This incident occurred between cal. AD 20–80 and doubtless had a significant social impact at the time because of its scale, reverberating throughout the early farming communities of the Southwest.
id: 2281

Anomalous biogeochemical behavior of cadmium in subantarctic surface waters: Mechanistic constraints from cadmium isotopes - Gault-Ringold, Melanie; Adu, Toyin; Stirling, Claudine H.; Frew, Russell D.; Hunter, Keith A. (Earth and Planetary Science Letters, 2012)
Cadmium, a highly toxic metal, exhibits a nutrient-type profile in the oceans that is closely correlated to that of the major nutrients phosphate and nitrate. Despite its complexity, the relationship between cadmium and phosphate has been used to infer historic phosphate utilization and biological controls on oceanic CO2 concentrations. Cadmium isotopes offer the potential to constrain the mechanisms controlling cadmium cycling in the oceans, reducing uncertainty associated with the cadmium paleonutrient proxy. Using techniques in double spiking and MC-ICPMS, we report seasonal Cd isotopic and concentration data along with major nutrients and other essential trace metal (Fe, Zn, and Co) concentrations from subantarctic surface waters. We show, for the first time, a 50-fold seasonal decrease in dissolved cadmium concentrations in subantarctic waters that is due to biological uptake. However, this drawdown in Cd is decoupled from phosphate and shows no coincident shift in cadmium isotopic composition. These data, along with the preferential removal of Cd from surface waters relative to Zn, imply that cadmium is supply-limited to phytoplankton and may have a more significant biological role in these low Zn subantarctic surface waters than in regions with higher Zn concentrations.
id: 2339

Anthropogenic aerosols as a source of ancient dissolved organic matter in glaciers - Stubbins, Aron; Hood, Eran; Raymond, Peter A.; Aiken, George R.; Sleighter, Rachel L.; Hernes, Peter J.; Butman, David; Hatcher, Patrick G.; Striegl, Robert G.; Schuster, Paul; Abdulla, Hussain A. N.; Vermilyea, Andrew W.; et al. (Nature Geoscience, 2012)
Glacier-derived dissolved organic matter represents a quantitatively significant source of ancient, yet highly bioavailable carbon to downstream ecosystems1. This finding runs counter to logical perceptions of age–reactivity relationships, in which the least reactive material withstands degradation the longest and is therefore the oldest2. The remnants of ancient peatlands and forests overrun by glaciers have been invoked as the source of this organic matter1, 3, 4. Here, we examine the radiocarbon age and chemical composition of dissolved organic matter in snow, glacier surface water, ice and glacier outflow samples from Alaska to determine the origin of the organic matter. Low levels of compounds derived from vascular plants indicate that the organic matter does not originate from forests or peatlands. Instead, we show that the organic matter on the surface of the glaciers is radiocarbon depleted, consistent with an anthropogenic aerosol source. Fluorescence spectrophotometry measurements reveal the presence of protein-like compounds of microbial or aerosol origin. In addition, ultrahigh-resolution mass spectrometry measurements document the presence of combustion products found in anthropogenic aerosols. Based on the presence of these compounds, we suggest that aerosols derived from fossil fuel burning are a source of pre-aged organic matter to glacier surfaces. Furthermore, we show that the molecular signature of the organic matter is conserved in snow, glacier water and outflow, suggesting that the anthropogenic carbon is exported relatively unchanged in glacier outflows.
Keywords: Atmospheric chemistry; Biogeochemistry; Cryospheric science

Chemical characteristics of particulate organic matter from a small, mountainous river in the Oregon Coast Range, USA - Hatten, J. A.; Goñi, M. A.; Wheatcroft, R. A. (Biogeochemistry, 2012)
id: 890submittedY

Chemical weathering and provenance evolution of Holocene–Recent sediments from the Western Indus Shelf, Northern Arabian Sea inferred from physical and mineralogical properties - Limmer, David R.; Köhler, Cornelia M.; Hillier, Stephen; Moreton, Steven G.; Tabrez, Ali R.; Clift, Peter D. (Marine Geology, 2012)
We present a multi-proxy mineral record based on X-ray diffraction and diffuse reflectance spectrophotometry analysis for two cores from the western Indus Shelf in order to reconstruct changing weathering intensities, sediment transport, and provenance variations since 13 ka. Core Indus-10 is located northwest of the Indus Canyon and exhibits fluctuations in smectite/(illite + chlorite) ratios that correlate with monsoon intensity. Higher smectite/(illite + chlorite) and lower illite crystallinity, normally associated with stronger weathering, peaked during the Early–Mid Holocene, the period of maximum summer monsoon. Hematite/goethite and magnetic susceptibility do not show clear co-variation, although they both increase at Indus-10 after 10 ka, as the monsoon weakened. At Indus-23, located on a clinoform just west of the canyon, hematite/goethite increased during a period of monsoon strengthening from 10 to 8 ka, consistent with increased seasonality and/or reworking of sediment deposited prior to or during the glacial maximum. After 2 ka terrigenous sediment accumulation rates in both cores increased together with redness and hematite/goethite, which we attribute to widespread cultivation of the floodplain triggering reworking, especially after 200 years ago. Over Holocene timescales sediment composition and mineralogy in two localities on the high-energy shelf were controlled by varying degrees of reworking, as well as climatically modulated chemical weathering.
id: 2271

Clay mineral variations in Holocene terrestrial sediments from the Indus Basin - Alizai, Anwar; Hillier, Stephen; Clift, Peter D.; Giosan, Liviu; Hurst, Andrew; VanLaningham, Sam; Macklin, Mark (Quaternary Research, 2012)
We employed X-ray diffraction methods to quantify clay mineral assemblages in the Indus Delta and flood plains since ~ 14 ka, spanning a period of strong climatic change. Assemblages are dominated by smectite and illite, with minor chlorite and kaolinite. Delta sediments integrate clays from across the basin and show increasing smectite input between 13 and 7.5 ka, indicating stronger chemical weathering as the summer monsoon intensified. Changes in clay mineralogy postdate changes in climate by 5–3 ka, reflecting the time needed for new clay minerals to form and be transported to the delta. Samples from the flood plains in Punjab show evidence for increased chemical weathering towards the top of the sections (6–
id: 2333

ENSO Drove 2500-Year Collapse of Eastern Pacific Coral Reefs - Toth, L. T.; Aronson, R. B.; Vollmer, S. V.; Hobbs, J. W.; Urrego, D. H.; Cheng, H.; Enochs, I. C.; Combosch, D. J.; van Woesik, R.; Macintyre, I. G. (Science, 2012)
Cores of coral reef frameworks along an upwelling gradient in Panamá show that reef ecosystems in the tropical eastern Pacific collapsed for 2500 years, representing as much as 40% of their history, beginning about 4000 years ago. The principal cause of this millennial-scale hiatus in reef growth was increased variability of the El Niño–Southern Oscillation (ENSO) and its coupling with the Intertropical Convergence Zone. The hiatus was a Pacific-wide phenomenon with an underlying climatology similar to probable scenarios for the next century. Global climate change is probably driving eastern Pacific reefs toward another regional collapse.

Loess mantle spatial variability and soil horizonation, southern Wisconsin, USA - Jacobs, Peter M.; Mason, Joseph A.; Hanson, Paul R. (Quaternary International, 2012)
Loess is an important Quaternary sediment that records evidence of landscape instability in sediment source areas and landscape stability in accumulation areas. In Wisconsin, USA loess mantles glaciogenic deposits dating to the last glaciation, but the landscape distribution and effects of the loess mantle on soil formation have received very little attention. This study investigates the influence of glacial landforms on the spatial pattern of loess thickness and how the presence or absence of a loess mantle overlying glaciogenic sediments has influenced soil profile morphology, namely thickness and nature of horizonation. Loess thickness follows systematic trends along hillslopes, with slope percentage explaining most loess thickness variation between summit and backslope positions. In the presence of a loess mantle, solum and Bt horizon thickness is proportional to the thickness of the loess mantle in well-drained profiles. In the absence of a loess mantle, landscape and sediment characteristics that control permeability and water throughflow appear to be the most important determinants of profile characteristics. The loess mantle modulates soil formation above the lithologic discontinuity with sandy calcareous glacial sediments by controlling soil water behavior and having physical and chemical characteristics conducive to transformation to soil genetic horizons.
id: 2151

Marine radiocarbon reservoir corrections (∆R) for Chesapeake Bay and the Middle Atlantic Coast of North America - Rick, Torben C.; Henkes, Gregory A.; Lowery, Darrin L.; Colman, Steven M.; Culleton, Brendan J. (Quaternary Research, 2012)
Radiocarbon dates from known age, pre-bomb eastern oyster (Crassostrea virginica) shells provide local marine reservoir corrections (∆R) for Chesapeake Bay and the Middle Atlantic coastal area of eastern North America. These data suggest subregional variability in ∆R, ranging from 148 ± 46 14C yr on the Potomac River to − 109 ± 38 14C yr at Swan Point, Maryland. The ∆R weighted mean for the Chesapeake's Western Shore (129 ± 22 14C yr) is substantially higher than the Eastern Shore (− 88 ± 23 14C yr), with outer Atlantic Coast samples falling between these values (106 ± 46 and 2 ± 46 14C yr). These differences may result from a combination of factors, including 14C-depleted freshwater that enters the bay from some if its drainages, 14C-depleted seawater that enters the bay at its mouth, and/or biological carbon recycling. We advocate using different subregional ∆R corrections when calibrating 14C dates on aquatic specimens from the Chesapeake Bay and coastal Middle Atlantic region of North America.
id: 2155

The Medieval Climate Anomaly in the Iberian Peninsula reconstructed from marine and lake records - Moreno, Ana; Pérez, Ana; Frigola, Jaime; Nieto-Moreno, Vanesa; Rodrigo-Gámiz, Marta; Martrat, Belén; González-Sampériz, Penélope; Morellón, Mario; Martín-Puertas, Celia; Corella, Juan Pablo; Belmonte, Ánchel; Sancho, Carlos; et al. (Quaternary Science Reviews, 2012)
Selected multi-proxy and accurately dated marine and terrestrial records covering the past 2000 years in the Iberian Peninsula (IP) facilitated a comprehensive regional paleoclimate reconstruction for the Medieval Climate Anomaly (MCA: 900–1300 AD). The sequences enabled an integrated approach to land–sea comparisons and, despite local differences and some minor chronological inconsistencies, presented clear evidence that the MCA was a dry period in the Mediterranean IP. It was a period characterized by decreased lake levels, more xerophytic and heliophytic vegetation, a low frequency of floods, major Saharan eolian fluxes, and less fluvial input to marine basins. In contrast, reconstruction based on sequences from the Atlantic Ocean side of the peninsula indicated increased humidity. The data highlight the unique characteristics of the MCA relative to earlier (the Dark Ages, DA: ca 500–900 years AD) and subsequent (the Little Ice Age, LIA: 1300–1850 years AD) colder periods. The reconstruction supports the hypothesis of Trouet et al. (2009), that a persistent positive mode of the North Atlantic Oscillation (NAO) dominated the MCA.
id: 2334

Oxygen control on Holocene cold-water coral development in the eastern Mediterranean Sea - Fink, Hiske G.; Wienberg, Claudia; Hebbeln, Dierk; McGregor, Helen V.; Schmiedl, Gerhard; Taviani, Marco; Freiwald, André (Deep Sea Research Part I: Oceanographic Research Papers, 2012)
Continuous sedimentary records from an eastern Mediterranean cold-water coral ecosystem thriving in intermediate water depths (∼600 m) reveal a temporary extinction of cold-water corals during the Early to Mid Holocene from 11.4–5.9 cal kyr BP. Benthic foraminiferal assemblage analysis shows low-oxygen conditions of 2 ml l−1 during the same period, compared to bottom-water oxygen values of 4–5 ml l−1 before and after the coral-free interval. The timing of the corals' demise coincides with the sapropel S1 event, during which the deep eastern Mediterranean basin turned anoxic. Our results show that during the sapropel S1 event low oxygen conditions extended to the rather shallow depths of our study site in the Ionian Sea and caused the cold-water corals temporary extinction. This first evidence for the sensitivity of cold-water corals to low oceanic oxygen contents suggests that the projected expansion of tropical oxygen minimum zones resulting from global change will threaten cold-water coral ecosystems in low latitudes in the same way that ocean acidification will do in the higher latitudes.
id: 2140

Paleoseismic and geomorphologic evidence of recent tectonic activity of the Pozohondo Fault (Betic Cordillera, SE Spain) - Rodriguez-Pascua, M. A.; Perez-Lopez, R.; Garduno-Monroy, V. H.; Giner-Robles, J. L.; Silva, P. G.; Perucha-Atienza, M. A.; Hernandez-Madrigal, V. M.; Bischoff, J. (JOURNAL OF IBERIAN GEOLOGY, 2012)
Instrumental and historical seismicity in the Albacete province (External Prebetic Zone) has been scarcely recorded. However, major strike-slip faults showing NW-SE trending provide geomorphologic and paleoseismic evidence of recent tectonic activity (Late Pleistocene to Present). Moreover, these faults are consistently well oriented under the present stress tensor and therefore, they can trigger earthquakes of magnitude greater than M6, according to the lengths of surface ruptures and active segments recognized in fieldwork. Present landscape nearby the village of Hellin (SE of Albacete) is determined by the recent activity of the Pozohondo Fault (FPH), a NW-SE right-lateral fault with 90 km in length. In this study, we have calculated the Late Quaternary tectonic slip-rate of the FPH from geomorphological, sedimentological, archaeoseimological, and paleoseismological approaches. All of these data suggest that the FPH runs with a minimum slip-rate of 0.1 mm/yr during the last 100 kyrs (Upper Pleistocene-Holocene). In addition, we have recognized the last two major paleoearthquakes associated to this fault. Magnitudes of these paleoearthquakes were gretarer than M6 and their recurrence intervals ranged from 6600 to 8600 yrs for the seismic cycle of FPH. The last earthquake was dated between the 1st and 6th centuries, though two earthquakes could be interpreted in this wide time interval, one at the FPH and other from a far field source. Results obtained here, suggest an increasing of the tectonic activity of the Pozohondo Fault during the last 10,000 yrs.
Keywords: Geomorphology; Paleoseismology; Prebetic; Quaternary; SE Spain

A reconstruction of late Pleistocene relative sea level in the south Bohai Sea, China, based on sediment grain-size analysis - Yi, Liang; Yu, Hongjun; Ortiz, Joseph D.; Xu, Xingyong; Qiang, Xiaoke; Huang, Haijun; Shi, Xuefa; Deng, Chenglong (Sedimentary Geology, 2012)
Future anthropogenic sea-level rise and its impact on coastal regions is an important issue facing human civilizations. Due to the short nature of the instrumental record of sea-level change, development of proxies for sea-level change prior to the advent of instrumental records is essential to reconstruct long-term background sea-level changes on local, regional and global scales. Here, we employ numerical methods to partition sediment grain size using a combined database of marine surface and core samples, and to quantitatively reconstruct sea-level variation since the late Pleistocene in the south Bohai Sea, China. Our sea-level reconstruction indicates that relative sea-level changes in the southern Bohai Sea track global sea-level variation for the duration of the record. The results also indicate substantial regression from 70 to 30 cal kyr BP, and potentially subarial exposure from 38 to 20 cal kyr BP. Our results document the feasibility of reconstructing relative sea-level change by numerical partitioning of sediment grain size data, demonstrating the potential for future applications.
id: 2312

Refining the model of barrier island formation along a paraglacial coast in the Gulf of Maine - Hein, Christopher J.; FitzGerald, Duncan M.; Carruthers, Emily A.; Stone, Byron D.; Barnhardt, Walter A.; Gontz, Allen M. (Marine Geology, 2012)
Details of the internal architecture and local geochronology of Plum Island, the longest barrier in the Gulf of Maine, have refined our understanding of barrier island formation in paraglacial settings. Ground-penetrating radar and shallow-seismic profiles coupled with sediment cores and radiocarbon dates provide an 8000-year evolutionary history of this barrier system in response to changes in sediment sources and supply rates as well as variability in the rate of sea-level change. The barrier sequence overlies tills of Wisconsinan and Illinoian glaciations as well as late Pleistocene glaciomarine clay deposited during the post-glacial sea-level highstand at approximately 17 ka. Holocene sediment began accumulating at the site of Plum Island at 7–8 ka, in the form of coarse fluvial channel-lag deposits related to the 50-m wide erosional channel of the Parker River that carved into underlying glaciomarine deposits during a lower stand of sea level. Plum Island had first developed in its modern location by ca. 3.6 ka through onshore migration and vertical accretion of reworked regressive and lowstand deposits. The prevalence of southerly, seaward-dipping layers indicates that greater than 60% of the barrier lithosome developed in its modern location through southerly spit progradation, consistent with a dominantly longshore transport system driven by northeast storms. Thinner sequences of northerly, landward-dipping clinoforms represent the northern recurve of the prograding spit. A 5–6-m-thick inlet-fill sequence was identified overlying the lower stand fluvial deposit; its stratigraphy captures events of channel migration, ebb-delta breaching, onshore bar migration, channel shoaling and inlet infilling associated with the migration and eventual closure of the inlet. This inlet had a maximum cross-sectional area of 2800 m2 and was active around 3.5–3.6 ka. Discovery of this inlet suggests that the tidal prism was once larger than at present. Bay infilling, driven by the import of sediment into the backbarrier environment through tidal inlets, as well as minor sediment contribution from local rivers, led to a vast reduction in the bay tidal prism. This study demonstrates that, prior to about 3 ka, Plum Island and its associated marshes, tidal flats, and inlets were in a paraglacial environment; that is, their main source of sediment was derived from the erosion and reworking of glaciogenic deposits. Since that time, Plum Island has been in a state of dynamic equilibrium with its non-glacial sediment sources and therefore can be largely considered to be in a stable, “post-paraglacial” state. This study is furthermore the first in the Gulf of Maine to show that spit accretion and inlet processes were the dominant mechanisms in barrier-island formation and thus serves as a foundation for future investigations of barrier development in response to backbarrier infilling.
Keywords: barrier-island formation; ground-penetrating radar; inlet processes; inlet-fill sequence; paraglacial; spit accretion

Small-scale lacustrine drifts in Lake Champlain, Vermont - Manley, Patricia L.; Manley, T. O.; Hayo, Kathryn; Cronin, Thomas (Journal of Great Lakes Research, 2012)
High resolution CHIRP (Compressed High Intensity Radar Pulse) seismic profiles reveal the presence of two lacustrine sediment drifts located in Lake Champlain's Juniper Deep. Both drifts are positive features composed of highly laminated sediments. Drift B sits on a basement high while Drift A is built on a trough-filling acoustically-transparent sediment unit inferred to be a mass-transport event. These drifts are oriented approximately north–south and are parallel to a steep ridge along the eastern shore of the basin. Drift A, located at the bottom of a structural trough, is classified as a confined, elongate drift that transitions northward to become a system of upslope asymmetric mudwaves. Drift B is perched atop a structural high to the west of Drift A and is classified as a detached elongate drift. Bottom current depositional control was investigated using Acoustic Doppler Current Profilers (ADCPs) located across Drift A. Sediment cores were taken at the crest and at the edges of the Drift A and were dated. Drift source, deposition, and evolution show that these drifts are formed by a water column shear with the highest deposition occurring along its crest and western flank and began developing circa 8700–8800 year BP.
id: 2179

Stratigraphic evidence for an early Holocene earthquake in Aceh, Indonesia - Grand Pre, C.; Horton, B. P.; Kelsey, H. M.; Rubin, C. M.; Hawkes, A. D.; Daryono, M.; Rosenberg, G.; Culver, S. J. (Quaternary Science Reviews, 2012)
The Holocene stratigraphy of the coastal plain of the Aceh Province of Sumatra contains 6 m of sediment with three regionally consistent buried soils above pre-Quaternary bedrock or pre-Holocene unconsolidated sediment. Litho-, bio-, and chronostratigraphic analyses of the lower buried soil reveals a rapid change in relative sea-level caused by coseismic subsidence during an earlyHolocene megathrust earthquake. Evidence for paleoseismic subsidence is preserved as a buried mangrove soil, dominated by a pollen assemblage of Rhizophora and/or Bruguiera/Ceriops taxa. The soil is abruptly overlain by a thin tsunami sand. The sand contains mixed pollen and abraded foraminiferal assemblages of both offshore and onshore environments. The tsunami sand grades upward into mud that contains both well-preserved foraminifera of intertidal origin and individuals of the gastropod Cerithidea cingulata. Radiocarbon ages from the pre- and post-seismic sedimentary sequences constrain the paleoearthquake to 6500–7000 cal. yrs. BP. We use micro-and macrofossil data to determine the local paleoenvironment before and after the earthquake. We estimate coseismic subsidence to be 0.45 ± 0.30 m, which is comparable to the 0.6 m of subsidence observed during the 2004 Aceh–Andaman earthquake on Aceh’s west coast.
id: 2139

The synchronization of palaeoclimatic events in the North Atlantic region during Greenland Stadial 3 (ca 27.5 to 23.3 kyr b2k) - Austin, W. E. N.; Hibbert, F. D.; Rasmussen, S. O.; Peters, C.; Abbott, P. M.; Bryant, C. L. (Quaternary Science Reviews, 2012)
Two high resolution marine sediment cores located 83 km apart in the NE Atlantic have been studied: MD95-2006 (Barra Fan; 57°01.82 N, 10°03.48 W; 2120 m water depth) and MD04-2822 (Rockall Trough; 56°50.54 N, 11°22.96 W; 2344 m water depth). The records are anchored to the NGRIP ice core stratigraphy and GICC05 chronology by the presence of geochemically characterized Fugloyarbanki tephra and further tested by radiocarbon age control. Replicated sea surface temperature (SST) records show evidence for an abrupt and short-lived warming within Greenland Stadial (GS)-3, to which we tentatively assign an age of ca 25.6–24.8 kyr GICC05 b2k. Based on these and another marine palaeoclimate record (LINK17) from the Faroe-Shetland Channel, we propose a new three-fold event stratigraphy for GS-3 within the North East Atlantic region. The recognition of this warming event within GS-3 in NE Atlantic SST records demonstrates that such events may not readily be identified within the coldest stadials of the Greenland ice cores, highlights the need for carefully constructed event stratigraphies (independently tested by the use of tephra isochrones and radiocarbon) and illustrates pervasive millennial-scale climate variability of the North Atlantic region (Dansgaard-Oeschger (D/O) events) is deeply embedded in the dynamics of Atlantic Meridional Overturning Circulation (AMOC).
id: 2145

Ventilation changes in the western North Pacific since the last glacial period - Okazaki, Y.; Sagawa, T.; Asahi, H.; Horikawa, K.; Onodera, J. (CLIMATE OF THE PAST, 2012)
We reconstructed the ventilation record of deep water at 2100m depth in the mid-latitude western North Pacific over the past 25 kyr from radiocarbon measurements of coexisting planktic and benthic foraminiferal shells in sediment with a high sedimentation rate. The C-14 data on fragile and robust planktic foraminiferal shells were concordant with each other, ensuring high quality of the reconstructed ventilation record. The radiocarbon activity changes were consistent with the atmospheric record, suggesting that no massive mixing of old carbon from the abyssal reservoir occurred throughout the glacial to deglacial periods. margin of the North Pacific, in a deep western boundary current analogous to the present one in the North Atlantic. However, our knowledge of paleo-ventilation, particularly in water deeper than 2000m in the western North Pacific, is limited because of poor preservation of foraminiferal shells in sediment. Here we present a detailed account of ventilation changes in the mid-latitude western North Pacific based on radiocarbon records from coexisting planktic and benthic foraminifera in sediment with high sedimentation rates. Because our ventilation reconstruction is based on radiocarbon data from multiple planktic species in the mid to high-latitude western North Pacific, our record provides robust evidence for the ventilation history in the region.

The application of foraminifera to reconstruct the rate of 20th century sea level rise, Morbihan Golfe, Brittany, France - Rossi, V.; Horton, B. P.; Corbett, D. R.; Leorri, E.; Perez-Belmonte, L.; Douglas, B. C. (Quaternary Research, 2011)
Foraminiferal assemblages preserved within salt-marsh sediment can provide an accurate and precise means to reconstruct relative sea level due to a strong relationship with elevation, which can be quantified using a transfer function. We collected a set of surface samples from two salt marshes in the Morbihan Golfe, France to determine foraminiferal distribution patterns. Dominant taxa included Jadammina macrescens, Trochammina inflata, Haplophragmoides spp. and Miliammina fusca. We developed a foraminifera-based transfer function using a modern training set of 36 samples and 23 species. The strong relationship between observed and predicted values (r(jack)(2) = 0.7) indicated that foraminiferal distribution is primarily controlled by elevation with respect to the tidal frame and precise reconstructions of former sea level are possible (RMSEP(jack) = 0.07 m). The application of the transfer function to a short salt-marsh core (0.32 m) allowed the reconstruction of former sea levels, which were placed in a chronological framework using short-lived radionuclides ((210)Pb and (137)Cs). The agreement between the foraminifera-based sea level curve and the Brest tide-gauge record confirms the reliability of transfer function estimates and the validity of this methodology to extend sea level reconstructions back into the pre-instrumental period. Both instrumental and microfossil records suggest an acceleration of sea level rise during the 20th century. (C) 2010 University of Washington. Published by Elsevier Inc. All rights reserved.
id: 1889; 713FR Times Cited:1 Cited References Count:71submittedY

Bomb-produced radiocarbon validation of growth-increment crossdating allows marine paleoclimate reconstruction - Kastelle, Craig R.; Helser, Thomas E.; Black, Bryan A.; Stuckey, Matthew J.; C. Gillespie, Darlene; McArthur, Judy; Little, Diana; D. Charles, Karen; Khan, Reziah S. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2011)
The bivalve Pacific geoduck (Panopea generosa) has been used in the eastern North Pacific Ocean to create proxies for environmental factors such as temperature and oceanographic conditions. This type of research depends upon accurate age determination of Pacific geoducks, which historically was based on shell growth-increment counts. A recent study comparing age estimates generated by the dendrochronology (tree-ring science) procedure of crossdating to those estimated from growth-increment counts found a significant difference between the methods for geoduck older than 30 years. Compared to the traditional age determination method of counting growth increments, the crossdating method estimates a greater longevity in this species, with some individuals living in excess of 150 years. In the present study, the accuracy of each method was independently assessed using bomb-produced radiocarbon (14C) techniques. Specimens whose birth years were estimated to be within the era of the bomb-produced marine 14C increase and where the differences between ages estimated by the two methods were greatest were selected for 14C analysis. The difference between age estimates from traditional growth-increment counts and those from crossdating was evaluated using their respective 14C chronologies in comparisons to a reference chronology as a standard. The comparisons relied on Bayesian nonlinear models using Markov Chain Monte Carlo simulation. This method of analysis showed that with a 50% probability geoducks were aged correctly when using the crossdating method, compared to the growth increment counts which had a 50% probability of underestimating the age by 4 years. Therefore, the crossdated age estimates were found to be more accurate than increment counts. Furthermore, these results provide new confidence in using Pacific geoduck biochronologies for paleoclimate and paleoenvironmental reconstruction.
id: 2167

Climate related sea-level variations over the past two millennia - Kemp, A. C.; Horton, B. P.; Donnelly, J. P.; Mann, M. E.; Vermeer, M.; Rahmstorf, S. (Proc Natl Acad Sci U S A, 2011)
We present new sea-level reconstructions for the past 2100 y based on salt-marsh sedimentary sequences from the US Atlantic coast. The data from North Carolina reveal four phases of persistent sea-level change after correction for glacial isostatic adjustment. Sea level was stable from at least BC 100 until AD 950. Sea level then increased for 400 y at a rate of 0.6 mm/y, followed by a further period of stable, or slightly falling, sea level that persisted until the late 19th century. Since then, sea level has risen at an average rate of 2.1 mm/y, representing the steepest century-scale increase of the past two millennia. This rate was initiated between AD 1865 and 1892. Using an extended semiempirical modeling approach, we show that these sea-level changes are consistent with global temperature for at least the past millennium.
id: 853; Kemp, Andrew C Horton, Benjamin P Donnelly, Jeffrey P Mann, Michael E Vermeer, Martin Rahmstorf, Stefan Proc Natl Acad Sci U S A. 2011 Jul 5;108(27):11017-22. Epub 2011 Jun 20.3131350submittedY

Coastal subsidence in Oregon, USA, during the giant Cascadia earthquake of AD 1700 - Hawkes, A. D.; Horton, B. P.; Nelson, A. R.; Vane, C. H.; Sawai, Y. (Quaternary Science Reviews, 2011)
Quantitative estimates of land-level change during the giant AD 1700 Cascadia earthquake along the Oregon coast are inferred from relative sea-level changes reconstructed from fossil foraminiferal assemblages preserved within the stratigraphic record. A transfer function, based upon a regional training set of modern sediment samples from Oregon estuaries, is calibrated to fossil assemblages in sequences of samples across buried peat-mud and peat-sand contacts marking the AD 1700 earthquake. Reconstructions of sample elevations with sample-specific errors estimate the amount of coastal subsidence during the earthquake at six sites along 400 km of coast. The elevation estimates are supported by lithological, carbon isotope, and faunal tidal zonation data. Coseismic subsidence at Nehalem River, Nestucca River, Salmon River, Alsea Bay, Siuslaw River and South Slough varies between 0.18 m and 0.85 m with errors between 0.18 m and 0.32 m. These subsidence estimates are more precise, consistent, and generally lower than previous semi-quantitative estimates. Following earlier comparisons of semi-quantitative subsidence estimates with elastic dislocation models of megathrust rupture during great earthquakes, our lower estimates for central and northern Oregon are consistent with modeled rates of strain accumulation and amounts of slip on the subduction megathrust, and thus, with a magnitude of 9 for the AD 1700 earthquake.
id: 2143

A decadally-resolved paleohurricane record archived in the late Holocene sediments of a Florida sinkhole - Lane, Philip; Donnelly, Jeffrey P.; Woodruff, Jonathan D.; Hawkes, Andrea D. (Marine Geology, 2011)
A 4500-year record of hurricane-induced storm surges is developed from sediment cores collected from a coastal sinkhole near Apalachee Bay, Florida. Recent deposition of sand layers in the upper sediments of the pond was found to be contemporaneous with significant, historic storm surges at the site modeled using SLOSH and the Best Track, post-1851 A.D. dataset. Using the historic portion of the record for calibration, paleohurricane deposits were identified by sand content and dated using radiocarbon-based age models. Marine-indicative foraminifera, some originating at least 5 km offshore, were present in several modern and ancient storm deposits. The presence and long-term preservation of offshore foraminifera suggest that this site and others like it may yield promising microfossil-based paleohurricane reconstructions in the future. Due to the sub-decadal (~ 7 years) resolution of the record and the site's high susceptibility to hurricane-generated storm surges, the average, local frequency of recorded events, approximately 3.9 storms per century, is greater than that of previously published paleohurricane records from the region. The high incidence of recorded events permitted a time series of local hurricane frequency during the last five millennia to be constructed. Variability in the frequency of the largest storm layers was found to be greater than what would likely occur by chance alone, with intervals of both anomalously high and low storm frequency identified. However, the rate at which smaller layers were deposited was relatively constant over the last five millennia. This may suggest that significant variability in hurricane frequency has occurred only in the highest magnitude events. The frequency of high magnitude events peaked near 6 storms per century between 2800 and 2300 years ago. High magnitude events were relatively rare with about 0–3 storms per century occurring between 1900 and 1600 years ago and between 400 and 150 years ago. A marked decline in the number of large storm deposits, which began around 600 years ago, has persisted through present with below average frequency over the last 150 years when compared to the preceding five millennia.
Keywords: Apalachee Bay; Gulf of Mexico; Holocene; hurricane; paleohurricane; Paleotempestology; sinkhole; SLOSH; storm surge; tropical cyclone

Evolution of a Pharaonic harbor on the Red Sea: Implications for coastal response to changes in sea level and climate - Hein, Christopher J.; FitzGerald, Duncan M.; Milne, Glenn A.; Bard, Kathryn; Fattovich, Rodolfo (GEOLOGY, 2011)
The evolution of coastal systems during the Holocene resulted from complex interactions and temporal shifts in the relative contribution of sea-level changes, climate change, and sedimentary processes. Along the Red Sea Coast, a 0.5-2 m highstand of sea level at 5 ka can be directly attributed to far-field effects resulting from the reduction in land ice following the last glacial maximum. At the ancient Egyptian harbor of Mersa/Wadi Gawasis, the site of the world's oldest archaeological evidence of long-distance seafaring, stratigraphic and geomorphologic evidence has been identified for this highstand. Here, wadi sediment input, enhanced by a period of wetter climate of the African Humid Period (early to mid-Holocene), forced the closure of coastal embayments, despite ongoing, relatively rapid sea-level rise. A stable, shallow bay persisted at Mersa/Wadi Gawasis as a result of coincidental aridization and a highstand of sea level during the mid-Holocene. This bay served as the primary harbor for ancient Egyptian trade along the Red Sea coast. During the late Holocene, shoreline progradation was dominated by sea-level fall, driven by isostatic processes. These results demonstrate the interplay of various global (sea level), regional (climate, sea level), and local (sedimentation, bathymetry) controls on the coastal evolution of the Red Sea and how these controls dictated the response of a complex civilization. Furthermore, they highlight the crucial role played by sedimentation in governing coastal response to changing sea levels.

Geological legacy of storm erosion along a high-energy indented coastline: northern Santa Catarina, Brazil - Buynevich, I. V.; Klein, A. H. F.; FitzGerald, D. M.; Cleary, W. J.; Hein, C.; Veiga, F. A.; Angulo, R. J.; Asp, N. E.; Petermann, R. (Journal of Coastal Research, 2011)
Along moderate to high-energy sandy coasts of the world, periods of accretion are often punctuated by episodes of erosion and retreat. However documenting the legacy of such events in sand-dominated sequences remains a challenge. The present-day moderate-relief coastlines of Camboriú Peninsula (CP) and the adjacent Navegantes coastal plain in Santa Catarina, Brazil, exhibit a variety of geological features related to recent intense storms, such as the Santa Catarina cyclone of record (March 2004) and subsequent events. These systems offer an opportunity to assess the use of modern indicators of storm erosion as a guide to reconstructing their counterparts from the sedimentary record. The 0.5-2.0-km-long, headland-segmented, coarse-grained, reflective beaches of the Camboriú Peninsula contrast with a 10-km-long, fine-grained, dissipative beach of the Navegantes plain. Morphological indicators of erosion include steep dune and berm scarps, as well as ephemeral washout channels produced by rainfall-induced runoff. Where modified by subsequent deposition, these features can still be identified by their diagnostic reflection geometries and variable-angle truncations (disconformities) in highresolution ground-penetrating radar (GPR) images. In addition to morphological indicators of erosion, coastal sedimentary sequences contain distinct lithological anomalies. Heavy-mineral concentrations (HMCs) are easily identifiable in sediment cores and trenches and produce strong reflections on GPR images. Along Estaleiro Beach (CP), a buried disconformity was identified in GPR images beneath a road, approximately 25 m landward of the November 2004 storm scarp. Its geometry is similar to the recent scarp and its strong geophysical signal return is due to a magnetite-enriched horizon at a depth of 2.6 m. At the Navegantes strandplain, patchy thin layers enriched in fine-grained heavy minerals are common on a gently sloping intertidal beach and near the base of foredunes. Moreover, in the landward portion of the plain that developed during the past 2,000 years, the presence of truncated tangential-oblique reflections in GPR records and HMCs reaching 10-30 cm in thickness indicates past reworking of beach and dune sediments by a series of intense erosional episodes. Low-field magnetic susceptibility measurements of vibracores indicate values from thick HMC layers exceeding 1,000 (*10-5 SI) in contrast to 0−15 (*10-5 SI) for background quartz-rich sands. Given the relatively constant background fraction of heavy minerals in beach sands, the thickness and degree of concentration in HMCs can be used as proxies for the relative impact of high-energy events, including their duration and magnitude. Despite the apparent low preservation potential of these features on high-energy coasts, post-storm accretion and rapid progradation increase their chances of being removed from wave action.
id: 2125

Glacial to Holocene swings of the Australian-Indonesian monsoon - Mohtadi, Mahyar; Oppo, Delia W.; Steinke, Stephan; Stuut, Jan-Berend W.; De Pol-Holz, Ricardo; Hebbeln, Dierk; Lueckge, Andreas (Nature Geoscience, 2011)
The Australian-Indonesian monsoon is an important component of the climate system in the tropical Indo-Pacific region(1). However, its past variability, relation with northern and southern high-latitude climate and connection to the other Asian monsoon systems are poorly understood. Here we present high-resolution records of monsoon-controlled austral winter upwelling during the past 22,000 years, based on planktic foraminiferal oxygen isotopes and faunal composition in a sedimentary archive collected offshore southern Java. We show that glacial-interglacial variations in the Australian-Indonesian winter monsoon were in phase with the Indian summer monsoon system, consistent with their modern linkage through cross-equatorial surface winds. Likewise, millennial-scale variability of upwelling shares similar sign and timing with upwelling variability in the Arabian Sea. On the basis of element composition and grain-size distribution as precipitation-sensitive proxies in the same archive, we infer that (austral) summer monsoon rainfall was highest during the Bolling-Allerod period and the past 2,500 years. Our results indicate drier conditions during Heinrich Stadial 1 due to a southward shift of summer rainfall and a relatively weak Hadley cell south of the Equator. We suggest that the Australian-Indonesian summer and winter monsoon variability were closely linked to summer insolation and abrupt climate changes in the northern hemisphere.
id: 2012; PT: J; UT: WOS:000293277100016

Micropaleontologic record of Quaternary paleoenvironments in the Central Albemarle Embayment, North Carolina, U.S.A - Culver, Stephen J.; Farrell, Kathleen M.; Mallinson, David J.; Willard, Debra A.; Horton, Benjamin P.; Riggs, Stanley R.; Thieler, E. Robert; Wehmiller, John F.; Parham, Peter; Snyder, Scott W.; Hillier, Caroline (Palaeogeography, Palaeoclimatology, Palaeoecology, 2011)
To understand the temporal and spatial variation of eustatic sea-level fluctuations, glacio–hydro–isostacy, tectonics, subsidence, geologic environments and sedimentation patterns for the Quaternary of a passive continental margin, a nearly complete stratigraphic record that is fully integrated with a three dimensional chronostratigraphic framework, and paleoenvironmental information are necessary. The Albemarle Embayment, a Cenozoic regional depositional basin in eastern North Carolina located on the southeast Atlantic coast of the USA, is an ideal setting to unravel these dynamic, interrelated processes. Micropaleontological data, coupled with sedimentologic, chronostratigraphic and seismic data provide the bases for detailed interpretations of paleoenvironmental evolution and paleoclimates in the 90 m thick Quaternary record of the Albemarle Embayment. The data presented here come from a transect of cores drilled through a barrier island complex in the central Albemarle Embayment. This area sits in a ramp-like setting between late Pleistocene incised valleys. The data document the episodic infilling of the Albemarle Embayment throughout the Quaternary as a series of transgressive–regressive (T–R) cycles, characterized by inner shelf, midshelf, and shoreface assemblages, that overlie remnants of fluvial to estuarine valley-fill. Barrier island and marginal marine deposits have a low preservation potential. Inner to mid-shelf deposits of the early Pleistocene are overlain by similar middle Pleistocene shelf sediments in the south of the study area but entirely by inner shelf deposits in the north. Late Pleistocene marine sediments are of inner shelf origin and Holocene deposits are marginal marine in nature. Pleistocene marine sediments are incised, particularly in the northern half of the embayment by lowstand paleovalleys, partly filled by fluvial/floodplain deposits and in some cases, overlain by remnants of transgressive estuarine sediments. The shallowing through time of Quaternary sediments reflects the eastward progradational geometry of the continental shelf. The preservation potential of marginal marine deposits (barrier island, shoreface, backbarrier deposits) is not high, except in topographic lows associated with late Pleistocene paleovalleys and inlets because the current interglacial highstand has not yet reached its highest level. Given the documented increase in rate of relative sea-level rise in this region, shallow marine conditions are likely to return to the central Albemarle Embayment in the near future.
id: 2182

Pb isotopic variability in the modern-Pleistocene Indus River system measured by ion microprobe in detrital K-feldspar grains - Alizai, Anwar; Clift, Peter D.; Giosan, Liviu; VanLaningham, Sam; Hinton, Richard; Tabrez, Ali R.; Danish, Muhammad (Geochimica et Cosmochimica Acta, 2011)
The western Himalaya, Karakoram and Tibet are known to be heterogeneous with regard to Pb isotope compositions in K-feldspars, which allows this system to be used as a sediment provenance tool. We used secondary ion mass spectrometry to measure the isotopic character of silt and sand-sized grains from the modern Sutlej and Chenab Rivers, together with Thar Desert sands, in order to constrain their origin. The rivers show a clear Himalayan provenance, contrasting with grains from the Indus Suture Zone, but with overlap to known Karakoram compositions. The desert dunes commonly show 207Pb/204Pb and 206Pb/204Pb values that are much higher than those seen in the rivers, most consistent with erosion from Nanga Parbat. This implies at least some origin from the trunk Indus, probably reworked by summer monsoon winds from the SW, a hypothesis supported by bulk Nd and U–Pb zircon dating. Further data collected from Holocene and Pleistocene sands shows that filled and abandoned channels on the western edge of the Thar Desert were sourced from Himalayan rivers before and at 6–8 ka, but that after that time the proportion of high isotopic ratio grains rose, indicating increased contribution from the Thar Desert dunes prior to ∼4.5 ka when flow ceased entirely. This may be linked to climatic drying, northward expansion of the Thar Desert, or changes in drainage style including regional capture, channel abandonment, or active local Thar tributaries. Our data further show a Himalayan river channel east of the present Indus, close to the delta, in the Nara River valley during the middle Holocene. While this cannot be distinguished from the Indus it is not heavily contaminated by reworking from the desert. The Pb system shows some use as a provenance tool, but is not effective at demonstrating whether these Nara sediments represent a Ghaggar-Hakra stream independent from the Indus. Our study highlights an important role for eolian reworking of floodplain sediments in arid rivers such as the Indus.
id: 2171

Precipitation as the main driver of Neoglacial fluctuations of Gualas glacier, Northern Patagonian Icefield - Bertrand, S.; Hughen, K. A.; Lamy, F.; Stuut, J. B. W.; Torrejon, F.; Lange, C. B. (Climate of the Past, 2011)
Glaciers are frequently used as indicators of climate change. However, the link between past glacier fluctuations and climate variability is still highly debated. Here, we investigate the mid- to late-Holocene fluctuations of Gualas Glacier, one of the northernmost outlet glaciers of the Northern Patagonian Icefield, using a multi-proxy sedimentological and geochemical analysis of a 15 m long fjord sediment core from Golfo Elefantes, Chile, and historical documents from early Spanish explorers. Our results show that the core can be sub-divided in three main lithological units that were deposited under very different hydrodynamic conditions. Between 5400 and 4180 cal yr BP and after 750 cal yr BP, sedimentation in Golfo Elefantes was characterized by the rapid deposition of fine silt, most likely transported by fluvio-glacial processes. By contrast, the sediment deposited between 4130 and 850 cal yr BP is composed of poorly sorted sand that is free of shells. This interval is particularly marked by high magnetic susceptibility values and Zr concentrations, and likely reflects a major advance of Gualas glacier towards Golfo Elefantes during the Neoglaciation. Several thin silt layers observed in the upper part of the core are interpreted as secondary fluctuations of Gualas glacier during the Little Ice Age, in agreement with historical and dendrochronological data. Our interpretation of the Golfo Elefantes glaciomarine sediment record in terms of fluctuations of Gualas glacier is in excellent agreement with the glacier chronology proposed for the Southern Patagonian Icefield, which is based on terrestrial (moraine) deposits. By comparing our results with independent proxy records of precipitation and sea surface temperature, we demonstrate that the fluctuations of Gualas glacier during the last 5400 yr were mainly driven by changes in precipitation in the Andes.
id: 2119

Rapid Holocene coastal change revealed by high-resolution micropaleontological analysis, Pamlico Sound, North Carolina, USA - Grand Pre, Candace; Culver, Stephen J.; Mallinson, David J.; Farrell, Kathleen M.; Corbett, D. Reide; Horton, Benjamin P.; Hillier, Caroline; Riggs, Stanley R.; Snyder, Scott W.; Buzas, Martin A. (Quaternary Research, 2011)
Foraminiferal analyses of 404 contiguous samples, supported by diatom, lithologic, geochronologic and seismic data, reveal both rapid and gradual Holocene paleoenvironmental changes in an 8.21-m vibracore taken from southern Pamlico Sound, North Carolina. Data record initial flooding of a latest Pleistocene river drainage and the formation of an estuary 9000 yr ago. Estuarine conditions were punctuated by two intervals of marine influence from approximately 4100 to 3700 and 1150 to 500 cal yr BP. Foraminiferal assemblages in the muddy sand facies that accumulated during these intervals contain many well-preserved benthic foraminiferal species, which occur today in open marine settings as deep as the mid shelf, and significant numbers of well-preserved planktonic foraminifera, some typical of Gulf Stream waters. We postulate that these marine-influenced units resulted from temporary destruction of the southern Outer Banks barrier islands by hurricanes. The second increase in marine influence is coeval with increased rate of sea-level rise and a peak in Atlantic tropical cyclone activity during the Medieval Climate Anomaly. This high-resolution analysis demonstrates the range of environmental variability and the rapidity of coastal change that can result from the interplay of changing climate, sea level and geomorphology in an estuarine setting.
id: 2164

Stratigraphic record of Holocene coseismic subsidence, Padang, West Sumatra - Dura, Tina; Rubin, Charles M.; Kelsey, Harvey M.; Horton, Benjamin P.; Hawkes, Andrea; Vane, Christopher H.; Daryono, Mudrik; Pre, Candace Grand; Ladinsky, Tyler; Bradley, Sarah (JOURNAL OF GEOPHYSICAL RESEARCH-SOLID EARTH, 2011)
Stratigraphic evidence is found for two coseismic subsidence events that underlie a floodplain 20 km south of Padang, West Sumatra along the Mentawai segment (0.5 S- 0.3 S) of the Sunda subduction zone. Each earthquake is marked by a sharp soil-mud contact that represents a sudden change from mangrove to tidal flat. The earthquakes occurred about 4000 and 3000 cal years B.P. based on radiocarbon ages of detrital plant fragments and seeds. The absence of younger paleoseismic evidence suggests that late Holocene relative sea level fall left the floodplain too high for an earthquake to lower it into the intertidal zone. Our results point to a brief, few thousand year window of preservation of subsidence events in tidal-wetland stratigraphic sequences, a result that is generally applicable to other emergent coastlines of West Sumatra.

Timescale dependence of glacial erosion rates: A case study of Marinelli Glacier, Cordillera Darwin, southern Patagonia - Fernandez, Rodrigo A.; Anderson, John B.; Wellner, Julia S.; Hallet, Bernard (Journal of Geophysical Research: Earth Surface, 2011)
Erosion rates have been estimated for a number of glaciated basins around the world, mostly based on modern observations (last few decades) of sediment fluxes to fjords. We use time‐constrained sediment volumes delivered by Marinelli Glacier (55°S), an outlet glacier of the Cordillera Darwin ice cap, southern Patagonian Andes, Tierra del Fuego, to determine erosion rates across different timescales. Sediment volumes are derived using a dense grid of high‐ and low‐frequency single channel seismic data and swath bathymetry data along with piston and Kasten cores. Our results show dramatic differences in erosion rates over different timescales. Erosion rates at Marinelli Glacier diminish about 80% (or by factor of ∼5) with each ten‐fold increase in the time span over which erosion rates are averaged: 29.3 mm/yr for the last 45 years, 5.3 mm/yr for the last 364 years, and 0.5 mm/yr for the last 12,500 years. These results indicate that modern sediment yields and erosion rates from temperate tidewater glaciers can exceed long‐term values over the time of deglaciation after the Last Glacial Maximum (centennial and millennial timescales) by up to 2 orders of magnitude. In view of the low exhumation rates of Cordillera Darwin (∼0.07 mm/yr average for the last 30 Myr), modern erosion rates could be up to 3 orders of magnitude higher than rates over geological time. We conclude that the pattern of erosion rate variation with time reflects the sensitivity of glaciers to climate variability.

The application of intertidal foraminifera to reconstruct coastal subsidence during the giant Cascadia earthquake of AD 1700 in Oregon, USA - Hawkes, A. D.; Horton, B. P.; Nelson, A. R.; Hill, D. F. (Quaternary International, 2010)
Changes in species assemblages of intertidal foraminifera can be used to estimate the amount of earthquake-related subsidence during plate-boundary earthquakes at the Cascadia subduction zone. The accuracy and precision of foraminiferal methods in paleoenvironmental reconstruction is underpinned by the relations between contemporary taxa and their environment, which are used to calibrate fossil foraminiferal assemblages in sediment sequences. A contemporary training set of surface sediment samples from five intertidal marshes along the Oregon coast was used to determine foraminiferal distributions and prevailing environmental control(s) along elevational transects. Dominant taxa include Balticammina pseudomacrescens, Trochamminita irregularis, Haplophragmoides wilberti, Trochammina inflata, Jadammina macrescens and Miliammina fusca. Unconstrained cluster analysis and detrended correspondence analysis was used to identify two elevation-dependent faunal zones: Faunal Zone I (upland, high marsh, middle marsh) dominated by Balticammina pseudomacrescens, Haplophragmoides wilberti and Trochammina inflata, and Faunal Zone II (low marsh and tidal flat) dominated by Miliammina fusca. Site-specific differences in assemblages at three marshes enabled further subdivision of Faunal Zone I. Zone la is based on one or more of Balticammina pseudomacrescens, Trochammina inflata, Trochamminita irregularis and Haplophragrnoides sp., and Zone Ib on Jadammina macrescens, Haplophragmoides sp., Trochammina inflata and Miliammina fusca. Canonical correspondence analysis (CCA) and partial CCA of the training set from the Nehalem River marsh transect was used to infer that the zonation of foraminifera is elevation-dependent (39% of explained variance). A transfer function was developed to reconstruct sudden changes in relative sea-level during plate-boundary earthquakes in Oregon. The results indicate a robust performance of the transfer function (r(jack)(2) = 0.82) with the error estimate (RMSEP(jack) = 0.20 m) comparable to local and regional transfer functions from other temperate marshes. To illustrate the potential of the technique, the transfer function was applied to reconstruct subsidence during the AD 1700 earthquake using at Alsea Bay, Oregon. The reconstruction (0.18 +/- 0.20 m) is less than half the subsidence estimate of Nelson et al. [2008. Great-earthquake palogeoesy and tsunamis of the past 2000 years at Alsea Bay, central Oregon coast, USA. Quaternary Science Reviews, 27, 747-768] using their foraminiferal transfer function, perhaps because of differences in taxonomy and the species relationship to elevation. (C) 2009 Elsevier Ltd and INQUA. All rights reserved.
id: 1981; PT: J; UT: WOS:000279551800012

Asphalt volcanoes as a potential source of methane to late Pleistocene coastal waters - Valentine, D. L.; Reddy, C. M.; Farwell, C.; Hill, T. M.; Pizarro, O.; Yoerger, D. R.; Camilli, R.; Nelson, R. K.; Peacock, E. E.; Bagby, S. C.; Clarke, B. A.; Roman, C. N.; et al. (Nature Geoscience, 2010)
Every year, natural petroleum seepage emits 0.2-2 Tg of oil to the ocean(1). Significant oil seepage can build large underwater mounds, consisting of tar deposits with morphologies similar to volcanic lava flows, known as asphalt volcanoes(2,3). Such events are typically accompanied by large fluxes of the greenhouse gas methane(4,5). Marine sediments from the Santa Barbara basin, California, contain a record of elevated methane concentrations(6), anoxia and tar deposition(7) during the Pleistocene epoch that had been attributed to dissolution of methane hydrates. However, the region is known to have exhibited oil seepage in the past(7). Here, we document the discovery of seven extinct asphalt volcanoes off the coast of southern California. The morphology of the deposits and geochemistry of samples taken from the two largest structures supports their classification as asphalt volcanoes, derived from a common source. We estimate that the two structures resulted from seepage of 0.07-0.4 Tg of oil, accompanied by the emission of 0.35-1.8 Tg of methane. Radiocarbon dating of carbonate deposits entrained with the asphalt indicates formation of the volcanoes between 44 and 31 kyr ago. The timing and volume of erupted hydrocarbons from the asphalt structures can explain some or all of the documented methane release and tar accumulation in the Santa Barbara basin during the Pleistocene.
id: 1866; Sp. Iss. SI 589XW Times Cited:0 Cited References Count:28; YY

Climatic controls of interannual variability in regional carbon fluxes from top-down and bottom-up perspectives RID B-8211-2009 - Desai, Ankur R.; Helliker, Brent R.; Moorcroft, Paul R.; Andrews, Arlyn E.; Berry, Joseph A. (Journal of Geophysical Research-Biogeosciences, 2010)
Observations of regional net ecosystem exchange (NEE) of CO(2) for 1997-2007 were analyzed for climatic controls on interannual variability (IAV). Quantifying IAV of regional (10(4)-10(6) km(2)) NEE over long time periods is key to understanding potential feedbacks between climate and the carbon cycle. Four independent techniques estimated monthly regional NEE for 10(4) km(2) in a spatially heterogeneous temperate-boreal transition region of the north central United States, centered on the Park Falls, Wisconsin, United States, National Oceanic and Atmospheric Administration tall tower site. These techniques included two bottom-up methods, based on flux tower upscaling and forest inventory based demographic modeling, respectively, and two top-down methods, based on tall tower equilibrium boundary layer budgets and tracer-transport inversion, respectively. While all four methods revealed a moderate carbon sink, they diverged significantly in magnitude. Coherence of relative magnitude and variability of NEE anomalies was strong across the methods. The strongest coherence was a trend of declining carbon sink since 2002. Most climatic controls were not strongly correlated with IAV. Significant controls on IAV were those related to hydrology, such as water table depth, and atmospheric CO(2). Weaker relationships were found with phenological controls such as autumn soil temperature. Hydrologic relationships were strongest with a 1 year lag, potentially highlighting a previously unrecognized predictor of IAV in this region. These results highlight a need for continued development of techniques to estimate regional IAV and incorporation of hydrologic cycling into couple carbon-climate models.
id: 1941; PT: J; UT: WOS:000277259700003

Coastal New England pilot study to determine fossil and biogenic formaldehyde source contributions using radiocarbon - Shen, Haiwei; Heikes, Brian G.; Merrill, John T.; McNichol, Ann P.; Xu, Li (JOURNAL OF GEOPHYSICAL RESEARCH-ATMOSPHERES, 2010)
Compound specific radiocarbon analyses of atmospheric formaldehyde are reported as fraction modern (Fm) for a limited number of winter and summer air samples collected in coastal southern New England in 2007. The 11 of 13 samples with Fm < 0.2 were collected under the influence of the semipermanent Bermuda high-pressure system with transport from the Washington, D. C., to New York City urban corridor. The two samples with Fm > 0.2 (max similar to 0.35) were collected on days with strong northwesterly flow and the least urban impact. The Fm data were combined with VOC observations from the Rhode Island Department of Environmental Management, estimates of oxygenated VOC (OVOC), and back trajectories to interpret the relative contributions of biogenic and fossil carbon sources. It is argued that CH2O sources were dominated by pollutant VOCs and OVOCs from upwind coastal cities as opposed to more local biogenic VOCs at the times of sample collection.

Constant Holocene Southern-Ocean 14C reservoir ages and ice-shelf flow rates - Hall, Brenda L.; Henderson, Gideon M.; Baroni, Carlo; Kellogg, Thomas B. (2010)
Southern Ocean radiocarbon reservoir ages (i.e. non-zero radiocarbon ages in seawater) are the highest in the world's surface ocean. Constraining these reservoir ages at present and in the past is important not only because unknown reservoir ages limit the interpretation of Antarctic radiocarbon chronologies, but also because reservoir ages provide information about ocean circulation (as a recorder of past circulation and as an end member for major deep-water masses in today's ocean). In this study, we use paired U/Th and 14C ages of an unusual set of solitary coral samples trapped by fringing ice shelves in the Ross Sea to provide the first detailed study of Holocene reservoir ages for the Southern Ocean. Our results indicate a relatively constant marine radiocarbon reservoir age of 1144 ± 120 years for the past 6000 years. These results are consistent with extrapolation of the relationship between 14C and alkalinity seen elsewhere, supporting the use of this empirical relationship in high latitudes. The results also suggest constant deep-ocean circulation and air–sea exchange during the Holocene and provide a good target for tuning ocean models of modern circulation. Combining the new ages for corals with their distance from the modern-day ice-shelf grounding line provides some of the first long-term records of ice-shelf velocities for any region and indicates constant flow of the McMurdo Ice Shelf during the Holocene, at a rate similar to that observed today.
Keywords: coral; marine reservoir effect; McMurdo Ice Shelf; radiocarbon; Southern Ocean; U/Th dating

Constant Holocene Southern-Ocean C-14 reservoir ages and ice-shelf flow rates - Hall, Brenda L.; Henderson, Gideon M.; Baroni, Carlo; Kellogg, Thomas B. (EARTH AND PLANETARY SCIENCE LETTERS, 2010)
Southern Ocean radiocarbon reservoir ages (i.e. non-zero radiocarbon ages in seawater) are the highest in the world's surface ocean. Constraining these reservoir ages at present and in the past is important not only because unknown reservoir ages limit the interpretation of Antarctic radiocarbon chronologies, but also because reservoir ages provide information about ocean circulation (as a recorder of past circulation and as an end member for major deep-water masses in today's ocean). In this study, we use paired U/Th and C-14 ages of an unusual set of solitary coral samples trapped by fringing ice shelves in the Ross Sea to provide the first detailed study of Holocene reservoir ages for the Southern Ocean. Our results indicate a relatively constant marine radiocarbon reservoir age of 1144 +/- 120 years for the past 6000 years. These results are consistent with extrapolation of the relationship between C-14 and alkalinity seen elsewhere, supporting the use of this empirical relationship in high latitudes. The results also suggest constant deep-ocean circulation and air-sea exchange during the Holocene and provide a good target for tuning ocean models of modern circulation. Combining the new ages for corals with their distance from the modern-day ice-shelf grounding line provides some of the first long-term records of ice-shelf velocities for any region and indicates constant flow of the McMurdo Ice Shelf during the Holocene, at a rate similar to that observed today. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: coral; marine reservoir effect; McMurdo Ice Shelf; radiocarbon; Southern Ocean; U/Th dating

Contrasting multiproxy reconstructions of surface ocean hydrography in the Agulhas Corridor and implications for the Agulhas Leakage during the last 345,000 years - Martinez-Mendez, Gema; Zahn, Rainer; Hall, Ian R.; Peeters, Frank J. C.; Pena, Leopoldo D.; Cacho, Isabel; Negre, Cesar (PALEOCEANOGRAPHY, 2010)
Planktonic delta(18)O and Mg/Ca-derived sea surface temperature (SST) records from the Agulhas Corridor off South Africa display a progressive increase of SST during glacial periods of the last three climatic cycles. The SST increases of up to 4 degrees C coincide with increased abundance of subtropical planktonic foraminiferal marker species which indicates a progressive warming due to an increased influence of subtropical waters at the core sites. Mg/Ca-derived SST maximizes during glacial maxima and glacial Terminations to values about 2.5 degrees C above full-interglacial SST. The paired planktonic delta(18)O and Mg/Ca-derived SST records yield glacial seawater delta(18)O anomalies of up to 0.8%, indicating measurably higher surface salinities during these periods. The SST pattern along our record is markedly different from a U(37)(K')-derived SST record at a nearby core location in the Agulhas Corridor that displays SST maxima only during glacial Terminations. Possible explanations are lateral alkenone advection by the vigorous regional ocean currents or the development of SST contrasts during glacials in association with seasonal changes of Agulhas water transports and lateral shifts of the Agulhas retroflection. The different SST reconstructions derived from U(37)(K') and Mg/Ca pose a significant challenge to the interpretation of the proxy records and demonstrate that the reconstruction of the Agulhas Current and interocean salt leakage is not as straightforward as previously suggested.

Deepwater Formation in the North Pacific During the Last Glacial Termination - Okazaki, Y.; Timmermann, A.; Menviel, L.; Harada, N.; Abe-Ouchi, A.; Chikamoto, M. O.; Mouchet, A.; Asahi, H. (Science, 2010)
Between ~17,500 and 15,000 years ago, the Atlantic meridional overturning circulation weakened substantially in response to meltwater discharges from disintegrating Northern Hemispheric glacial ice sheets. The global effects of this reorganization of poleward heat flow in the North Atlantic extended to Antarctica and the North Pacific. Here we present evidence from North Pacific paleo surface proxy data, a compilation of marine radiocarbon age ventilation records, and global climate model simulations to suggest that during the early stages of the Last Glacial Termination, deep water extending to a depth of ~2500 to 3000 meters was formed in the North Pacific. A switch of deepwater formation between the North Atlantic and the North Pacific played a key role in regulating poleward oceanic heat transport during the Last Glacial Termination.

A High-Performance (14)c Accelerator Mass Spectrometry System - Roberts, M. L.; Burton, J. R.; Elder, K. L.; Longworth, B. E.; McIntyre, C. P.; von Reden, K. F.; Han, B. X.; Rosenheim, B. E.; W. J. Jenkins; Galutschek, E.; McNichol, A. P. (Radiocarbon, 2010)
A new and unique radiocarbon accelerator mass spectrometry (AMS) facility has been constructed at the Woods Hole Oceanographic Institution. The defining characteristic of the new system is its large-gap optical elements that provide a larger-than-standard beam acceptance. Such a system is ideally suited for high-throughput, high-precision measurements of (14)C. Details and performance of the new system are presented.
id: 2095; PT: J; CT: 20th International Radiocarbon Conference; CY: MAY 31-JUN 05, 2009; CL: Big Isl, HI; SI: 1; UT: WOS:000285437800005

Megadroughts and late Holocene dune activation at the eastern margin of the Great Plains, north-central Kansas, USA - Hanson, P. R.; Arbogast, A. F.; Johnson, W. C.; Joeckel, R. M.; Young, A. R. (Aeolian Research, 2010)
Optical and radiocarbon dating indicates that alluvium underlying dunes near Abilene was deposited at or before similar to 45 ka, and that the overlying dunes were active at similar to 1.1-0.5 ka. Geochemical data indicate that the Abilene dune sand is immature and was derived from the underlying Pleistocene alluvium, and not from Holocene age Smoky Hill River deposits. These findings suggest that dune activation was a response to increased aridity and local reduction in vegetation cover as opposed to changes in sediment availability from nearby rivers. The time interval of dune activation at Abilene overlaps Medieval Warm Period megadroughts, similar to the larger and more westerly dune fields on the Great Plains, including the Nebraska Sand Hills and the Great Bend Sand Prairie. The activation of smaller dune fields such as the Abilene dunes near the more humid eastern margin of the Great Plains shows the geographic extent and severity of paleodrought events. Unlike the Duncan dunes, another plains-marginal dune field, however, the Abilene dunes show no evidence for multiple drought events during the Holocene. This difference in dune activity, if it is not a result of sampling or preservation bias, indicates variations in the extent and severity of older drought events at the eastern margin of the Great Plains. Published by Elsevier B.V.
851alTimes Cited:20Cited References Count:35

A molecular perspective on Late Quaternary climate and vegetation change in the Lake Tanganyika basin, East Africa - Tierney, J. E.; Russell, J. M.; Huang, Y. S. (Quaternary Science Reviews, 2010)
Characterizing the nature of past hydrological change and its interactions with vegetation is fundamental to acquiring a better understanding of continental tropical climate dynamics. Here, we outline major shifts in the climate and ecosystem of tropical East Africa for the past 60,000 years (60 ka) by examining molecular records of hydrology, vegetation, and temperature from a sediment sequence from Lake Tanganyika. We demonstrate, via comparison with pollen spectra, that stable carbon isotopes measured on higher plant leaf waxes (delta C-13(wax)) are a reliable proxy for vegetation change. In addition we argue that the D/H ratio of higher plant leaf waxes (delta D-wax) is a robust and independent indicator of past changes in aridity, and is not affected by regional vegetation change directly. Our paired, compound-specific isotope data show that shifts in vegetation lead major changes in hydrology in the Tanganyika basin at several major climate transitions during the past 60,000 years, suggesting that vegetation in the Tanganyika basin is not as sensitive to aridity as previous studies have suggested and that variations in carbon dioxide, temperature, and internal ecosystem dynamics are equally, if not more, important. We hypothesize that regional vegetation change may exert a positive feedback on regional hydrology, thus partially accounting for the abrupt threshold behavior evident in our paleohydrological data. Furthermore, we find that past changes in Tanganyika basin climate and ecology are closely linked to concentrations of atmospheric trace gases, highlighting the paramount influence of global climatic shifts upon regional tropical climate over glacial/interglacial timescales. (C) 2009 Elsevier Ltd. All rights reserved.
id: 1850; 574XV Times Cited:0 Cited References Count:111Y

No signature of abyssal carbon n intermediate waters off Chile during deglaciation - dePol-Holz, R.; Keigwin, L.; Southon, J.; Hebbeln, D.; Mohtadi, M. (Nature Geosciences, 2010)
id: 772; YY

Photosynthetic isotope biosignatures in laminated micro-stromatolitic and non-laminated nodules associated with modern, freshwater microbialites in Pavilion Lake, BC RID B-8520-2011 - Brady, A. L.; Slater, G. F.; Omelon, C. R.; Southam, G.; Druschel, G.; Andersen, D. T.; Hawes, I.; Laval, B.; Lim, D. S. S. (Chemical Geology, 2010)
The influence of microbial activity on carbonate precipitation was investigated within micro-stromatolitic nodules associated with modem, freshwater microbialites located in Pavilion Lake, B.C. Observed carbonate delta(13)C values enriched by up to +3.6 parts per thousand as compared to predicted abiotic carbonate delta(13)C values from measured dissolved inorganic carbon (mean -1.2 parts per thousand, n=13) were consistent with microbial photosynthetic influence on in situ precipitation within the nodule microenvironment. Estimated carbonate precipitation temperatures within the nodules based on delta(18)O were consistent with recorded summertime temperatures, indicative of precipitation during the period of highest levels of photosynthetic activity. Low delta(13)C values of organic matter within the nodules (-30.6 to 21.1 parts per thousand) and an average inorganic to organic carbon Delta delta(13)C value of 26.8 parts per thousand reflected the preferential uptake of (12)C during non-CO(2) limited photosynthesis, supporting the generation of (13)C-enriched DIC. Microelectrode profiles through the nodules showed oxygen supersaturation of up to similar to 275%, elevated pH compared to ambient water and a lack of any observable dissolved sulphide, Mn or Fe further indicated that photosynthetic activity was the predominant metabolic process within the nodule during light exposure. Microbial phospholipid fatty acid profiles of the nodule communities were indicative of bacteria rather than eukaryotes and PLFA delta(13)C values were depleted relative to the bulk cell by 2.6-6.6 parts per thousand, consistent with a predominance of photosynthetic microbes. Scanning electron microscopy images of the relationship between carbonate minerals and filaments indicated that carbonate precipitation had occurred in situ due to microbial influences on the geochemistry within the nodule microenvironment rather than due to cell surface effects or trapping and binding. The observation of photosynthetically induced (13)C-enrichment of in situ precipitated carbonate within the nodule microenvironment is thus a biosignature of the activity of these surface communities and is consistent with the hypothesized role of biology in the formation of microbialites. (C) 2010 Elsevier B.V. All rights reserved.
id: 2056; PT: J; UT: WOS:000279094700005

Postglacial changes in El Nino and La Nina behavior - Makou, Matthew C.; Eglinton, Timothy I.; Oppo, Delia W.; Hughen, Konrad A. (Geology, 2010)
Paleoclimate reconstructions suggest distinctive changes in the Ell Nino-Southern Oscillation (ENSO), the dominant mode of tropical climate variability, over the last glacial cycle and throughout the Holocene. However, to the best of our knowledge, no studies provide parallel reconstructions of warm (El Nino) and cold (La Nina) phase variability, thus precluding distinction between variations in ENSO activity and the mean state of the tropical Pacific. Here we provide the first such records, generated using molecular organic geochemical proxies in a sediment core from the Peru margin region. The opposing influences of El Nino and La Nina on coastal upwelling and phytoplankton community structure produce distinct sedimentary sterol records describing the evolution of each ENSO phase. We document changes in surface ocean productivity on the Peru margin over the past 16 ka that indicate enhanced La Nina-like conditions alone during deglaciation, but concomitant increases in both El Nino and La Nina activity during the past 2 ka. We propose that the preponderance of La Nina-like conditions prior to 11.5 ka reflects the influence of waning glacial boundary conditions. By contrast, warm and cold phase covariability during the late Holocene suggests centennial-scale changes in ENSO activity, rather than the Pacific mean state, driven by tropical insolation.
id: 1985; PT: J; UT: WOS:000273346200011

The potential of New Zealand kauri (Agathis australis) for testing the synchronicity of abrupt climate change during the Last Glacial Interval (60,000-11,700 years ago) - Turney, Chris S. M.; Fifield, L. Keith; Hogg, Alan G.; Palmer, Jonathan G.; Hughen, Konrad; Baillie, Mike G. L.; Galbraith, Rex; Ogden, John; Lorrey, Andrew; Tims, Stephen G.; Jones, Richard T. (Quaternary Science Reviews, 2010)
The latter part of the Last Glacial Interval (LGI; 60,000 to 11,700 years ago) experienced a range of climatic and environment extremes. To elucidate the mechanisms of these changes requires records of past variability that are precisely dated and correlated on the same absolute timescale. However, despite decades of research, it is still not possible to align most marine and terrestrial records of past change with ice-core records, largely because of ongoing uncertainties over the conversion of pre-Holocene (14)C ages on to a calendar timescale and uncertainties with in ice-core chronologies. As a result, it is equivocal whether climate changes in both hemispheres during the LGI led, lagged or were synchronous with one another. A decadally-resolved radiocarbon calibration is urgently required to test these models of the Earth system. Here we report radiocarbon measurements obtained from subfossil New Zealand kauri (Agathis australis) spanning a collective 3500 years dated between 25,000 and 45,000 years ago. The results are compared to the recently published international calibration curve IntCal09 and to the marine Cariaco Basin datasets. We show that kauri have considerable potential for development of a Southern Hemisphere component of a unified global calibration curve suite, and that tree-ring sequences can be superposed on other radiocarbon records to constrain atmospheric marine offsets and precisely test the synchronicity of abrupt climate change. (C) 2010 Elsevier Ltd. All rights reserved.
id: 1982; PT: J; UT: WOS:000285222000001

Radiocarbon Dating of Individual Lignin Phenols: A New Approach for Establishing Chronology of Late Quaternary Lake Sediments - Hou, Juzhi; Huang, Yongsong; Brodsky, Corynn; Alexandre, Marcelo R.; McNichol, Ann P.; King, John W.; Hu, Feng Sheng; Shen, Ji (ANALYTICAL CHEMISTRY, 2010)
The reliability of chronology is a prerequisite for meaningful paleoclimate reconstructions from sedimentary archives. The conventional approach of radiocarbon dating bulk organic carbon in lake sediments is often hampered by the old carbon effect, i.e., the assimilation of ancient dissolved inorganic carbon (DIC) derived from carbonate bedrocks or other sources. Therefore, radiocarbon dating is ideally performed on organic compounds derived from land plants that use atmospheric CO(2) and rapidly delivered to sediments. We demonstrate that lignin phenols isolated from lake sediments using reversed phase high performance liquid chromatography (HPLC) can serve as effective (14)C dating materials for establishing chronology during the late Quaternary. We developed a procedure to purify lignin phenols, building upon a published method. By isolating lignin from standard wood reference substances, we show that our method yields pure lignin phenols and consistent ages as the consensus ages and that our procedure does not introduce radiocarbon contamination. We further demonstrate that lignin phenol ages are compatible with varve counted and macrofossil dated sediment horizons in Steel Lake and Fayetteville Green Lake. Applying the new method to lake sediment cores from Lake Qinghai demonstrates that lignin phenol ages in Lake Qinghai are consistently younger than bulk total organic carbon (TOC) ages which are contaminated by old carbon effect. We also show that the age offset between lignin and bulk organic carbon differs at different Lake Qinghai sedimentary horizons, suggesting a variable hard water effect at different times and that a uniform age correction throughout the core is inappropriate.

Reconstructing Holocene conditions under the McMurdo Ice Shelf using Antarctic barnacle shells - Burgess, S. N.; Henderson, G. M.; Hall, B. L. (Earth and Planetary Science Letters, 2010)
This study evaluates the potential of barnacles for paleoceanographic reconstruction and, in particular, of the Antarctic species Bathylasma corolliforme to reconstruct past under ice shelves Like other barnacle species, this Antarctic barnacle secretes a robust low-Mg calcite shell with distinct growth increments on the external surface indicating growth over a number of years (30-50 in samples studied here). The Bathylasma samples used in this study grew in the Ross Sea and became entrained at the grounding line of a coastal ice shelf in McMurdo Sound, offering potential as an archive of changing conditions in this difficult to access environment under the McMurdo ice shelf. Nine barnacle shells were subsampled at high resolution (60 pun) for delta(18)O and delta(13)C analysis. These samples were dated with (14)C and U-Th techniques, although the later did not yield useful age information due to open-system behaviour of barnacle calcite. Measured delta(18)O values indicate that Bathylasma calcifies close to equilibrium with ambient seawater. One older sample (approximate to 200 ka) has similar delta(18)O and delta(13)C values as the eight Holocene samples, suggesting that barnacle calcite is not prone to significant diagenesis in this setting. Apparent isotope equilibrium and lack of diagenesis make barnacles a promising archive for reconstruction of past ocean conditions. Cycles of delta(18)O observed within each sample sometimes correlate with the external growth ridges, but not always, and have amplitudes of typically 0.6 parts per thousand. This magnitude of variation suggests shell growth during a significant portion of the year. although it remains unclear whether growth continues throughout the year. However, the prominent growth bands suggest at least a signficant seasonal slowing in growth rate. Variations in barnacle delta(18)O within each plate and between plates are too large to be caused by temperature. and instead reflect changes in delta(18)O of the seawater, allowing some assessment of seawater salinity under the ice shelf. Salinities are lowered by addition of meltwaters, but the barnacle delta(18)O data suggest values do not go below 33 parts per thousand.. These data indicate that Bathylasma has potential as an archive of paleoclimate information for shallow/intermediate water depths and, in particular, for difficult to reach environments such as below ice-shelves of Antarctica. Crown Copyright (C) 2010 Published by Elsevier B.V. All rights reserved
id: 1960; PT: J; UT: WOS:000283756600013

Reduced ice extent on the western Antarctic Peninsula at 700–970 cal. yr B.P. - Hall, B.L.; Koffman, T.; Denton, G.H. (Geology, 2010)
Rapid warming and consequent ice-shelf collapse have focused attention on the glacial record of the Antarctic Peninsula. Here, we present the first record of terrestrial organic material exposed by recently retreating ice that bears on past glacier extent and climate in this sensitive region. Radiocarbon dates show that ice on Anvers Island was at or behind its present position at 700–970 cal. yr B.P., coincident with ice reduction elsewhere in the Southern Hemisphere. Moreover, the data indicate that present reduced ice extent on the western Antarctic Peninsula is not unprecedented and is similar to that experienced during at least three periods in the last 5600 yr.

Reduced North Atlantic Central Water formation in response to early Holocene ice-sheet melting - Bamberg, A.; Rosenthal, Y.; Paul, A.; Heslop, D.; Mulitza, S.; Ruhlemann, C.; Schulz, M. (Geophysical Research Letters, 2010)
Central waters of the North Atlantic are fundamental for ventilation of the upper ocean and are also linked to the strength of the Atlantic Meridional Overturning Circulation (AMOC). Here, we show based on benthic foraminiferal Mg/Ca ratios, that during times of enhanced melting from the Laurentide Ice Sheet (LIS) between 9.0-8.5 thousand years before present (ka) the production of central waters weakened the upper AMOC resulting in a cooling over the Northern Hemisphere. Centered at 8.54 +/- 0.2 ka and 8.24 +/- 0.1 ka our dataset records two similar to 150-year cooling events in response to the drainage of Lake Agassiz/Ojibway, indicating early slow-down of the upper AMOC in response to the initial freshwater flux into the subpolar gyre (SPG) followed by a more severe weakening of both the upper and lower branches of the AMOC at 8.2 ka. These results highlight the sensitivity of regional North Atlantic climate change to the strength of central-water overturning and exemplify the impact of both gradual and abrupt freshwater fluxes on eastern SPG surface water convection. In light of the possible future increase in Greenland Ice Sheet melting due to global warming these findings may help us to better constrain and possibly predict future North Atlantic climate change. Citation: Bamberg, A., Y. Rosenthal, A. Paul, D. Heslop, S. Mulitza, C. Ruhlemann, and M. Schulz (2010), Reduced North Atlantic Central Water formation in response to early Holocene ice-sheet melting, Geophys. Res. Lett., 37, L17705, doi: 10.1029/2010GL043878.
id: 874; 649FZ Times Cited:3 Cited References Count:32submittedY

Relative sea-level changes, Schuchert Dal, East Greenland, with implications for ice extent in late-glacial and Holocene times - Hall, B. L.; Baroni, C.; Denton, G. H. (Quaternary Science Reviews, 2010)
The chronology of late-glacial and Holocene ice fluctuations in East Greenland is important for documenting glacier response to climate change and for determining the mechanisms behind abrupt climate switches. Raised marine sediments and landforms suggest culmination of the late-glacial Milne Land Stade in Schuchert Dal alongside Scoresby Sund before similar to 11,900-12,300 cal yr B.P. Ice in Schuchert Dal apparently receded during the later part of the Younger Dryas, consistent with the idea that this period was characterized by strong seasonality. A stillstand or slight readvance probably interrupted overall recession just prior to 11,000 cal yr B.P. In many locations, ice was back close to present positions by the start of the Holocene. The most extensive glacier advance of the Holocene occurred during the Little Ice Age and was restricted to within a few kilometers of present-day ice margins. (C) 2010 Elsevier Ltd. All rights reserved.
id: 1953; PT: J; SI: SI; UT: WOS:000284724400003

The role of glacio-eustasy in sequence formation: Mid-Atlantic Continental Margin, USA - McHugh, Cecilia M.; Hartin, Corinne A.; Mountain, Gregory S.; Gould, Helene M. (Marine Geology, 2010)
Previous studies of the Mid-Atlantic Continental Margin had shown the lack of correlation between Pleistocene glacio-eustatic oscillations and sequence boundaries. This study documents late Pleistocene to Holocene paleoenvironments within a seismic stratigraphic sequence in order to characterize sequence formation and the development of unconformities in response to glacio-eustatic oscillations. The data, high-resolution CHIRP subbottom profiling and 28 vibracores, were collected in water depths of 38 m to 145 m as part of the R/V Endeavor cruise 370 survey to the Mid-Atlantic Continental Margin. Sediment sources, sedimentary and seismic facies associated with the last major glaciation, and oxygen isotope stages OIS 5 to OIS 1 were examined and a chronology was constructed from mollusk assemblages of intertidal origin that allowed tracking the paleoshoreline from 19 to 6 ka BP. The maximum extent of the Last Glacial Maximum (LGM) paleoshoreline at 17 ka BP was documented near the 120 m modern isobath. The shoreline was marked by sediment mounds up to 5 m high and troughs 15 m deep and 1 km wide (interpreted as shoreface and tidal inlet or lagoons) formed from 17 to 15 ka BP. Five kilometers seaward from the LGM shoreline and the head of the Hudson Canyon is a wedge-shaped feature interpreted as a lowstand delta. Sediments older than the last glacial, possibly OIS 3 or OIS 5, onlap a basal unconformity. We correlate this unconformity to a previously identified sequence boundary. Approximately 20 m to 30 m of sediment accumulated on the outer shelf NE of the Hudson Canyon during the last glacial and little deposition has occurred since ~ 11 ka BP. The modern outershelf is covered by ~ 1 m of mollusk-rich glauconitic sand deposited from latest Pleistocene to early Holocene, 15 to 11 ka BP. These results showed a close correspondence between depositional environments and glacio-eustasy but sequence development and sequence boundary formation appeared to be influenced by the incomplete filling of accommodation space due to poor preservation during OIS 2 and low accumulation during the Holocene.
Keywords: Hudson Canyon; Hudson Shelf Valley; Last glacial maximum; Mid-Atlantic Continental Margin; paleoshoreline; sequence stratigraphy

Sr-Nd-Os evidence for a stable erosion regime in the Himalaya during the past 12 Myr - Galy, Valier; France-Lanord, Christian; Peucker-Ehrenbrink, Bernhard; Huyghe, Pascale (EARTH AND PLANETARY SCIENCE LETTERS, 2010)
Modern erosion of the Himalaya, the world's largest mountain range, transfers huge dissolved and particulate loads to the ocean. It plays an important role in the long-term global carbon cycle, mostly through enhanced organic carbon burial in the Bengal Fan. To understand the role of past Himalayan erosion, the influence of changing climate and tectonic on erosion must be determined. Here we use a 12 Myr sedimentary record from the distal Bengal Fan (Deep Sea Drilling Project Site 218) to reconstruct the Mio-Pliocene history of Himalayan erosion. We use carbon stable isotopes (delta(13)C) of bulk organic matter as paleo-environmental proxy and stratigraphic tool. Multi-isotopic - Sr, Nd and Os - data are used as proxies for the source of the sediments deposited in the Bengal Fan over time. delta(13)C values of bulk organic matter shift dramatically towards less depleted values, revealing the widespread Late Miocene (ca. 7.4 Ma) expansion of C4 plants in the basin. Sr, Nd and Os isotopic compositions indicate a rather stable erosion pattern in the Himalaya range during the past 12 Myr. This supports the existence of a strong connection between the southern Tibetan plateau and the Bengal Fan. The tectonic evolution of the Himalaya range and Southern Tibet seems to have been unable to produce large re-organisation of the drainage system. Moreover, our data do not suggest a rapid change of the altitude of the southern Tibetan plateau during the past 12 Myr. Variations in Sr and Nd isotopic compositions around the late Miocene expansion of C4 plants are suggestive of a relative increase in the erosion of High Himalaya Crystalline rock (i.e. a simultaneous reduction of both Transhimalayan batholiths and Lesser Himalaya relative contributions). This could be related to an increase in aridity as Suggested by the ecological and sedimentological changes at that time. A reversed trend in Sr and Nd isotopic compositions is observed at the Plio-Pleistocene transition that is likely related to higher precipitation and the development of glaciers in the Himalaya. These almost synchronous moderate changes in erosion pattern and climate changes during the late Miocene and at the Plio-Pleistocene transition support the notion of a dominant control of climate on Himalayan erosion during this time period. However, stable erosion regime during the Pleistocene is suggestive of a limited influence of the glacier development on Himalayan erosion. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Bengal Fan; climate; erosion; Himalaya; Miocene; radiogenic isotopes

The Ties That Bind: 3000 Years of Fabric Production and Fiber Use in the Ozark Plateau - Horton, Elizabeth T. (75th annual Conference of the Society for American Archaeology, 2010)
id: 776

Were last glacial climate events simultaneous between Greenland and France? A quantitative comparison using non-tuned chronologies RID E-4539-2011 RID A-2643-2010 - Blaauw, Maarten; Wohlfarth, Barbara; Christen, J. Andres; Ampel, Linda; Veres, Daniel; Hughen, Konrad A.; Preusser, Frank; Svensson, Anders (Journal of Quaternary Science, 2010)
Several large abrupt climate fluctuations during the last glacial have been recorded in Greenland ice cores and archives from other regions. Often these Dansgaard-Oeschger events are assumed to have been synchronous over wide areas, and then used as tie-points to link chronologies between the proxy archives. However, it has not yet been tested independently whether or not these events were indeed synchronous over large areas. Here, we compare Dansgaard-Oeschger-type events in a well-dated record from southeastern France with those in Greenland ice cores. Instead of assuming simultaneous climate events between both archives, we keep their age models independent. Even these well-dated archives possess large chronological uncertainties that prevent us from inferring synchronous climate events at decadal to multi-centennial time scales. If possible, comparisons between proxy archives should be based on independent, non-tuned time-scales. Copyright (C) 2009 John Wiley & Sons, Ltd.
id: 1986; PT: J; UT: WOS:000276090800014

A 24,900-year paleolimnological history from the Peruvian Andes - Hillyer, R.; Valencia, B. G.; Bush, M. B.; Silman, M. R.; Steinitz-Kannan, M. (Quaternary Research, 2009)
id: 1902

Abrupt mid-Holocene onset of centennial-scale climate variability on the Peru-Chile Margin - Chazen, C. R.; Altabet, M. A.; Herbert, T. D. (Geophysical Research Letters, 2009)
Understanding the natural climate variations in the eastern tropical Pacific (ETP) is crucial for predicting the evolution of the El Nino-Southern Oscillation (ENSO). Here we present the first continuous, decadal-resolution Holocene climate record from the Peru-Chile Margin, near the epicenter of the modern ENSO system. Geochemical proxies allow us to reconstruct sea surface temperature, phytoplankton productivity, and thermocline ventilation, variables that are tightly correlated to ENSO events today. Despite the observation that the mean state of all three variables did not change over the past 10,000 years, our data reveal a dramatic increase in climate variability near 5 ka; represented by prolonged periods (50-200 yrs) of climate extremes, which are absent in the early Holocene. These centennial-scale oscillations do not show typical El Nino-La Nina correlations between proxies. We therefore posit that a significant fraction of super-ENSO variance may originate outside the tropics, through processes that ventilate the ETP subsurface waters. Citation: Chazen, C. R., M. A. Altabet, and T. D. Herbert (2009), Abrupt mid-Holocene onset of centennial-scale climate variability on the Peru-Chile Margin, Geophys. Res. Lett., 36, L18704, doi:10.1029/2009GL039749.
id: 1890; 499OY Times Cited:0 Cited References Count:41Y

Coral growth rates from the Holocene Canada Honda fossil reef, Southwestern Dominican Republic: Comparisons with modern counterparts in high sedimentation settings - Cuevas, D. N.; Sherman, C. E.; Ramírez, W.; Hubbard, D. K. (Caribbean Journal of Science, 2009)
The Holocene Canada Honda fossil reef, located in southwestern Dominican Republic, provides a unique opportunity to examine a well-preserved fossil coral reef that thrived in a high-sedimentation environment between 9,000 to 5,000 years ago. Measurements of coral growth rates from the corals Montastraea faveolata and Siderastrea siderea were conducted and comparisons made with growth rate data of these same species from modern coral reefs throughout the Caribbean. Also, assessments of coral species abundance, morphology, age, and distribution, as well as reef sediment composition, were made to determine the paleoenvironment of reef accretion. This reef is characterized by a high relative abundance of sediment-tolerant coral species that have a tendency to form almost monospecific stands. Individual colonies have a propensity to grow as encrusting, dome-shaped, platy-like forms and specimens of Montastraea faveolata commonly contain bands of sediment incorporated into the skeleton. Calibrated radiocarbon ages of fossil corals range from 9,256 +/- 137 to 6,737 +/- 94.5 BP. Correlation of radiocarbon ages with well-established Holocene sea-level curves indicates that most corals on this reef developed at depths >15m. Measured growth rates in Siderastrea siderea (0.2-0.4 cm/yr) and Montastraea faveolata (0.09-0.44 cm/yr) are relatively low compared with growth rates from modern reef sites, indicating reduced light intensity caused by coral growth at depths greater than 15 m. Reef sediment is characterized by more than 85% carbonate material. A significant portion of the carbonate is allochtonous and was derived from nearby Neogene limestones. The reef was able to survive under high-sedimentation conditions because the high carbonate content of incoming terrigenous sediment would have allowed better light penetration and probable sporadic storms would provide intervening low-sedimentation periods during which reef corals could respond and grow back, keeping-up with sedimentation.
695voTimes Cited:0 Cited References Count:47
Keywords: australia; Belize; Caribbean; community; degradation; enriquillo valley; florida; great-barrier-reef; linear extension; montastraea-annularis; paluma shoals; record; siltation stress; skeletal extension; turbidity

Dynamics of particle export on the Northwest Atlantic margin - Hwang, J.; Manganini, S. J.; Montlucon, D. B.; Eglinton, T. I. (Deep-Sea Research Part I-Oceanographic Research Papers, 2009)
The Northwest Atlantic margin is characterized by high biological productivity in shelf and slope surface waters. In addition to carbon supply to underlying sediments, the persistent, intermediate depth nepheloid layers emanating from the continental shelves, and bottom nepheloid layers maintained by strong bottom currents associated with the southward flowing Deep Western Boundary Current (DWBC), provide conduits for export of organic carbon over the margin and/or to the interior ocean. As a part of a project to understand dynamics of particulate organic carbon (POC) cycling in this region, we examined the bulk and molecular properties of time-series sediment trap samples obtained at 968 m, 1976 m, and 2938 m depths from a bottom-tethered mooring on the New England slope (water depth, 2988 m). Frequent occurrences of higher fluxes in deep relative to shallower sediment traps and low Delta C-14 values of sinking POC together provide strong evidence for significant lateral transport of aged organic matter over the margin. Comparison of biogeochemical properties such as aluminum concentration and flux, and iron concentration between samples intercepted at different depths shows that particles collected by the deepest trap had more complex sources than the shallower ones. These data also suggest that at least two modes of lateral transport exist over the New England margin. Based on radiocarbon mass balance, about 30% (+/- 10%) of sinking POC in all sediment traps is estimated to be derived from lateral transport of resuspended sediment. A strong correlation between Delta C-14 values and aluminum concentrations suggests that the aged organic matter is associated with lithogenic particles. Our results suggest that lateral transport of organic matter, particularly that resulting from sediment resuspension, should be considered in addition to vertical supply of organic matter derived from primary production, in order to understand carbon cycling and export over continental margins. (C) 2009 Elsevier Ltd. All rights reserved.
id: 1829; 490AT Times Cited:0 Cited References Count:61Y

Evidence of paleo-cold seep activity from the Bay of Bengal, offshore India - Mazumdar, A.; Dewangan, P.; Joao, H. M.; Peketi, A.; Khosla, V. R.; Kocherla, M.; Badesab, F. K.; Joshi, R. K.; Roxanne, P.; Ramamurty, P. B.; Karisiddaiah, S. M.; Patil, D. J.; et al. (Geochemistry Geophysics Geosystems, 2009)
We report evidence of paleo-cold seep associated activities, preserved in methane-derived carbonates in association with chemosynthetic clams (Calyptogena sp.) from a sediment core in the Krishna-Godavari basin, Bay of Bengal. Visual observations and calculations based on high-resolution wet bulk density profile of a core collected on board R/V Marion Dufresne (May 2007) show zones of sharp increase in carbonate content (10-55 vol%) within 16-20 meters below seafloor (mbsf). The presence of Calyptogena clam shells, chimneys, shell breccias with high Mg calcite cement, and pyrite within this zone suggest seepage of methane and sulfide-bearing fluid to the seafloor in the past. Highly depleted carbon isotopic values (delta C-13 ranges from -41 to -52% VPDB) from these carbonates indicate carbon derived via anaerobic oxidation of methane. Extrapolated mean calendar age (similar to 58.7 ka B. P.) of the clastic sediments at a depth of 16 mbsf is close to the upper limit of the U-Th based depositional age (46.2 +/- 3.7 and 53.0 +/- 1.6 ka) of authigenic carbonates sampled from this level, thereby constraining the younger age limit of the carbonate deposition/methane expulsion events. The observed carbonate deposition might have resulted from the flow of methane-enriched fluids through the fracture network formed because of shale diapirism.
id: 794; 458FC Times Cited:0 Cited References Count:80Y

Fishing from past to present: continuity and resilience of red abalone fisheries on the Channel Islands, California - Braje, Todd J.; Erlandson, Jon M.; Rick, Torben C.; Dayton, Paul K.; Hatch, Marco B. A. (Ecological Applications, 2009)
Archaeological data from coastal shell middens provide a window into the structure of ancient marine ecosystems and the nature of human impacts on fisheries that often span millennia. For decades Channel Island archaeologists have studied Middle Holocene shell middens visually dominated by large and often whole shells of the red abalone (Haliotis rufescens). Here we use modern ecological data, historical accounts, commercial red abalone catch records, and zooarchaeological data to examine long-term spatial and temporal variation in the productivity of red abalone fisheries on the Northern Channel Islands, California (USA). Historical patterns of abundance, in which red abalone densities increase from east to west through the islands, extend deep into the Holocene. The correlation of historical and archaeological data argue for long-term spatial continuity in productive red abalone fisheries and a resilience of abalone populations despite dramatic ecological changes and intensive human predation spanning more than 8000 years. Archaeological, historical, and ecological data suggest that California kelp forests and red abalone populations are structured by a complex combination of top-down and bottom-up controls.
id: 2060; PT: J; UT: WOS:000266281400008

Formal definition and dating of the GSSP (Global Stratotype Section and Point) for the base of the Holocene using the Greenland NGRIP ice core, and selected auxiliary records RID B-5560-2008 RID F-1111-2011 - Walker, Mike; Johnsen, Sigfus; Rasmussen, Sune Olander; Popp, Trevor; Steffensen, Jorgen-Peder; Gibbard, Phil; Hoek, Wim; Lowe, John; Andrews, John; Bjorck, Svante; Cwynar, Les C.; Hughen, Konrad; et al. (Journal of Quaternary Science, 2009)
The Greenland ice core from NorthGRIP (NGRIP) contains a proxy climate record across the Pleistocene-Holocene boundary of unprecedented clarity and resolution. Analysis of an array of physical and chemical parameters within the ice enables the base of the Holocene, as reflected in the first signs of climatic warming at the end of the Younger Dryas/Greenland Stadial 1 cold phase, to be located with a high degree of precision. This climatic event is most clearly reflected in an abrupt shift in deuterium excess values, accompanied by more gradual changes in delta(18)O, dust concentration, a range of chemical species, and annual layer thickness. A timescale based on multi-parameter annual layer counting provides an age of 11 700 calendar yr b2k (before AD 2000) for the base of the Holocene, with a maximum counting error of 99 yr. A proposal that an archived core from this unique sequence should constitute the Global Stratotype Section and Point (GSSP) for the base of the Holocene Series/Epoch (Quaternary System/Period) has been ratified by the International Union of Geological Sciences. Five auxiliary stratotypes for the Pleistocene-Holocene boundary have also been recognised. Copyright (C) 2008 John Wiley & Sons, Ltd.
id: 1989; PT: J; UT: WOS:000262615700002

High mitogenomic evolutionary rates and time dependency - Subramanian, Sankar; Denver, Dee R.; Millar, Craig D.; Heupink, Tim; Aschrafi, Angelique; Emslie, Steven D.; Baroni, Carlo; Lambert, David M. (Trends in Genetics, 2009)
Using entire modern and ancient mitochondrial genomes of Adelie penguins (Pygoscelis adeliae) that are up to 44000 years old, we show that the rates of evolution of the mitochondrial genome are two to six times greater than those estimated from phylogenetic comparisons. Although the rate of evolution at constrained sites, including nonsynonymous positions and RNAs, varies more than twofold with time (between shallow and deep nodes), the rate of evolution at synonymous sites remains the same. The time-independent neutral evolutionary rates reported here would be useful for the study of recent evolutionary events.
id: 1917; PT: J; NR: 27; TC: 19; J9: TRENDS GENET; PG: 5; GA: 518TW; UT: WOS:000271717800004

Holocene sea-level changes along the North Carolina Coastline and their implications for glacial isostatic adjustment models - Horton, B. P.; Peltier, W. R.; Culver, S. J.; Drummond, R.; Engelhart, S. E.; Kemp, A. C.; Mallinson, D.; Thieler, E. R.; Riggs, S. R.; Ames, D. V.; Thomson, K. H. (Quaternary Science Reviews, 2009)
We have synthesized new and existing relative sea-level (RSL) data to produce a quality-controlled, spatially comprehensive database from the North Carolina coastline. The RSL database consists of 54 sea-level index points that are quantitatively related to an appropriate tide level and assigned an error estimate, and a further 33 limiting dates that confine the maximum and minimum elevations of RSL The temporal distribution of the index points is very uneven with only five index points older than 4000 cal a BP, but the form of the Holocene sea-level trend is constrained by both terrestrial and marine limiting dates. The data illustrate RSL rapidly rising during the early and mid Holocene from an observed elevation of -35.7 +/- 1.1 m MSL at 11062-10576 cal a BP to -4.2 m +/- 0.4 m MSL at 4240-3592 cal a BP. We restricted comparisons between observations and predictions from the ICE-5G(VM2) with rotational feedback Glacial Isostatic Adjustment (GIA) model to the Late Holocene RSL (last 4000 cal a BP) because of the wealth of sea-level data during this time interval. The ICE-5G(VM2) model predicts significant spatial variations in RSL across North Carolina, thus we subdivided the observations into two regions. The model forecasts an increase in the rate of sea-level rise in Region 1 (Albemarle, Currituck, Roanoke, Croatan, and northern Pamlico sounds) compared to Region 2 (southern Pamlico, Core and Bogue sounds, and farther south to Wilmington). The observations show Late Holocene sea-level rising at 1.14 +/- 0.03 mm year(-1) and 0.82 +/- 0.02 mm year(-1) in Regions 1 and 2, respectively. The ICE-5G(VM2) predictions capture the general temporal trend of the observations, although there is an apparent misfit for index points older than 2000 cal a BR It is presently unknown whether these misfits are caused by possible tectonic uplift associated with the mid-Carolina Platform High or a flaw in the CIA model. A comparison of local tide gauge data with the Late Holocene RSL trends from Regions 1 and 2 support the spatial variation in RSL across North Carolina, and imply an additional increase of mean sea level of greater than 2 mm year(-1) during the latter half of the 20th century; this is in general agreement with historical tide gauge and satellite altimetry data. (C) 2009 Elsevier Ltd. All rights reserved.
id: 814; Sp. Iss. SI 484ZD Times Cited:1 Cited References Count:108Y

Human impacts, climate change, and aquatic ecosystem response during the past 2000 yr at Lake Wandakara, Uganda - Russell, James M.; McCoy, S. J.; Verschuren, D.; Bessems, I.; Huang, Y. (Quaternary Research, 2009)
Analyses of carbon and hydrogen isotope ratios of terrestrial leaf waxes and the carbon and nitrogen abundance. ratio, and isotopic composition of bulk sediments from Like Wandakara, a crater lake in western Uganda, East Africa. document human and climatic controls on the aquatic system and oil the Surrounding terrestrial vegetation during the past two millennia Our data indicate that Wandakara was a relatively stable, productive lake Surrounded by C(3) vegetation from AD 70 to 1000. Abrupt changes in the delta(13)C of terrestrial leaf waxes indicate a series of abrupt shifts in the relative abundance of C(3) and C(4) vegetation caused by a combination of climate change and human activities around Wandakara beginning at AD 1000. Abrupt shifts in bulk sediment organic geochemistry. particularly C/N ratios and delta(15)N, indicate that human activities at this time caused permanent changes in the limnology of Lake Wandakara. including eutrophication Our results suggest that the biogeochemistry of Like Wandakara was more sensitive to shifting human impacts than to climate variations during the past millennium, highlighting the importance of understanding the intensity of pre-colonial human impacts on Africa's aquatic ecosystems (C) 2009 University of Washington Published by Elsevier Inc All rights reserved
id: 2052; PT: J; UT: WOS:000271254000002

Intcal09 and Marine09 Radiocarbon Age Calibration Curves, 0-50,000 Years Cal Bp Rid F-4952-2011 Rid B-7298-2008 - Reimer, P. J.; Baillie, M. G. L.; Bard, E.; Bayliss, A.; Beck, J. W.; Blackwell, P. G.; Ramsey, C. Bronk; Buck, C. E.; Burr, G. S.; Edwards, R. L.; Friedrich, M.; Grootes, P. M.; et al. (Radiocarbon, 2009)
The IntCal04 and Marine04 radiocarbon calibration curves have been updated from 12 cal kBP (cal kBP is here defined as thousands of calibrated years before AD 1950), and extended to 50 cal kBP, utilizing newly available data sets that meet the IntCal Working Group criteria for pristine corals and other carbonates and for quantification of uncertainty in both the (14)C and calendar timescales as established in 2002. No change was made to the curves from 0-12 cal kBP. The curves were constructed using a Markov chain Monte Carlo (MCMC) implementation of the random walk model used for IntCal04 and Marine04. The new curves were ratified at the 20th International Radiocarbon Conference in June 2009 and; ire available in the Supplemental Material at www.radiocarbon.org.
id: 1983; PT: J; UT: WOS:000274407500002

Interhemispheric Atlantic seesaw response during the last deglaciation - Barker, S.; Diz, P.; Vautravers, M. J.; Pike, J.; Knorr, G.; Hall, I. R.; Broecker, W. S. (Nature, 2009)
The asynchronous relationship between millennial-scale temperature changes over Greenland and Antarctica during the last glacial period has led to the notion of a bipolar seesaw which acts to redistribute heat depending on the state of meridional overturning circulation within the Atlantic Ocean. Here we present new records from the South Atlantic that show rapid changes during the last deglaciation that were instantaneous (within dating uncertainty) and of opposite sign to those observed in the North Atlantic. Our results demonstrate a direct link between the abrupt changes associated with variations in the Atlantic meridional overturning circulation and the more gradual adjustments characteristic of the Southern Ocean. These results emphasize the importance of the Southern Ocean for the development and transmission of millennial-scale climate variability and highlight its role in deglacial climate change and the associated rise in atmospheric carbon dioxide.
id: 856; Barker, Stephen Diz, Paula Vautravers, Maryline J Pike, Jennifer Knorr, Gregor Hall, Ian R Broecker, Wallace S England Nature. 2009 Feb 26;457(7233):1097-102.Y

Lake Sturgeon Age Validation using Bomb Radiocarbon and Known-Age Fish - Bruch, R. M.; Campana, S. E.; Davis-Foust, S. L.; Hansen, M. J.; Janssen, J. (Transactions of the American Fisheries Society, 2009)
Pectoral fin spines have been the accepted structure for estimating the age of various sturgeon species for nearly 100 years, though other structures have also been used (otoliths, pectoral girdle, scutes, and caudal fulcra). Accuracy of age estimates using any of these structures has not been validated, so we report the first use of bomb radiocarbon (C-14) assays to assess the validity of ages estimated using growth increments on pectoral fin spine and otolith frontal cross sections from lake sturgeon Acipenser fulvescens: we also assessed age estimates from pectoral fin spines of known-age lake sturgeon. Growth increments on pectoral fin spine cross sections underestimated true age of fish older than 14 years and error increased with age, whereas otoliths accurately estimated true age up to at least 52 years. Increment formation on pectoral fin spine and otolith cross sections from juvenile lake sturgeon (ages 2-11) was similar, although pectoral spines were clearer and easier to interpret. A power function (true age = [estimated age](1.054796), where estimated age was determined from pectoral spines; r(2) = 0.98) provides a means for correcting existing age estimates obtained from lake sturgeon pectoral fin spines.
id: 1855; 477EI Times Cited:1 Cited References Count:33Y

Land-sea linkage of Holocene paleoclimate on the Southern Bering Continental Shelf - Katsuki, K.; Khim, B. K.; Itaki, T.; Harada, N.; Sakai, H.; Ikeda, T.; Takahashi, K.; Okazaki, Y.; Asahi, H. (Holocene, 2009)
Detailed diatom records within surface and core sediments from the Southern Bering Continental Shelf (SBCS) reveal that the Holocene evolution of sea-ice distribution is associated with low pressure patterns. Holocene sea-ice distribution over the SBCS was mainly controlled by the location of the Aleutian Low. The corresponding paleoceanographic and paleoclimate conditions can be divided into three stages. (1) the early Holocene K before 7000 cal. yr BP) was characterized by extensive sea-ice distribution under two low-pressure cells, which covered the western Bering-Sea and the Gulf of Alaska, respectively. (2) Between 3000 and 7000 cal. yr BP, the low-pressure system over the Gulf of Alaska became weak, causing total sea-ice mass over the SBCS to retreat. (3) In the past 3000 years, prevailing southwesterly winds over the SBCS due to the developing Aleutian Low have reduced further sea-ice cover on the SBCS. These paleoclimatic changes were probably a response to ENSO variation. The timings of water mass exchanges on the SBCS coincided with sea-level change along the Alaskan Peninsula. As a result, subsequent morphologic alterations have also influenced the paleoceanographic condition of the SBCS. The effect of the surface coastal water and bottom marine water on the SBCS intensified about 6000 cal. yr BP when sea level increased.
id: 1878; 470HQ Times Cited:1 Cited References Count:76Y

Late Holocene sea-surface temperature and precipitation variability in northern Patagonia, Chile (Jacaf Fjord, 44 degrees S) - Sepulveda, J.; Pantoja, S.; Hughen, K. A.; Bertrand, S.; Figueroa, D.; Leon, T.; Drenzek, N. J.; Lange, C. (Quaternary Research, 2009)
A high-resolution multi-proxy study including the elemental and isotopic composition of bulk organic matter, land plant-derived biomarkers, and alkenone-based sea-surface temperature (SST) from a marine sedimentary record obtained from the Jacaf Fjord in northern Chilean Patagonia (similar to 44 degrees 20'S) provided a detailed reconstruction of continental runoff, precipitation, and summer SST spanning the last 1750 yr We observed two different regimes of climate variability in our record a relatively dry/warm period before 900 cal yr BP (lower runoff and average SST 1 degrees C warmer than present day) and a wet/cold period after 750 cal yr BP (higher runoff and average SST 1 degrees C colder than present clay). Relatively colder SSTs were found during 750-600 and 450-250 cal yr BP, where the latter period roughly corresponds to the interval defined for the Little Ice Age (LIA) Similar climatic swings have been observed previously in continental and marine archives of the last two millennia from central and southern Chile, suggesting a strong latitudinal sensitivity to changes in the Southern Westerly Winds, the main Source Of precipitation in southern Chile, and validating the regional nature of the LIA Our results reveal the importance of the Chilean fjord system for recording climate changes of regional and global significance (C) 2009 University of Washington Published by Elsevier Inc All rights reserved.
id: 1858; 512MQ Times Cited:0 Cited References Count:53Y

Marine shellfish harvest on Middle and Late Holocene Santa Barbara Island, California - Rick, Torben C.; Erlandson, Jon M.; Horton, Kristina (California Archaeology, 2009)
id: 2077

Millennial time scale changes in surface to intermediate-deep layer circulation recorded in the sediment cores from the northwestern North Pacific - Harada, N.; Kimoto, K.; Okazaki, Y.; Nagashima, K.; Timmermann, A.; Abe-Ouchi, A. (The Quaternary Research, 2009)
id: 1877

Molecular and isotopic constraints on the sources of suspended particulate organic carbon on the northwestern Atlantic margin - Hwang, J.; Montlucon, D.; Eglinton, T. I. (Deep-Sea Research Part I-Oceanographic Research Papers, 2009)
The abundance, carbon isotopic composition (Delta C-14 and delta C-13), and lipid biomarker (alkenones and saturated fatty acids) distributions of suspended particulate organic matter were investigated at three stations centered on the 2000, 3000, and 3500 m isobaths over the New England slope in order to assess particulate carbon sources and dynamics in this highly productive and energetic region. Transmissometry profiles reveal that particle abundances exhibit considerable fine structure, with several distinct layers of elevated suspended particulate matter concentration at intermediate water depths in addition to the presence of a thick bottom nepheloid layer at each station. Excluding surface water samples, the Delta C-14 values of particulate organic carbon (POC) indicated the presence of a pre-aged component in the suspended POC pool (Delta C-14
id: 774; 471WJ Times Cited:1 Cited References Count:73Y

A new look at old carbon in active margin sediments RID F-1809-2010 - Drenzek, Nicholas J.; Hughen, Konrad A.; Montluçon, Daniel B.; Southon, John R.; dos Santos, Guaciara M.; Druffel, Ellen R. M.; Giosan, Liviu; Eglinton, Timothy I. (Geology, 2009)
Recent studies suggest that as much as half of the organic carbon (OC) undergoing burial in the sediments of tectonically active continental margins may be the product of fossil shale weathering. These estimates rely on the assumption that vascular plant detritus spends little time sequestered in intermediate reservoirs such as soils, freshwater sediments, and river deltas, and thus only minimally contributes to the extraneously old (14)C ages of total organic matter often observed on adjacent shelves. Here we test this paradigm by measuring the (14)C and delta(13)C values of individual higher plant wax fatty acids as well as the d13C values of extractable alkanes isolated from the Eel River margin (California). The isotopic signatures of the long chain fatty acids indicate that vascular plant material has been sequestered for several thousand years before deposition. A coupled molecular isotope mass balance used to reassess the sedimentary carbon budget indicates that the fossil component is less abundant than previously estimated, with pre-aged terrestrial material instead composing a considerable proportion of all organic matter. If these findings are characteristic of other continental margins proximal to small mountainous rivers, then the importance of petrogenic OC burial in marine sediments may need to be reevaluated.
id: 1987; PT: J; UT: WOS:000263842200012

Pre-Columbian settlement of Carriacou, West Indies - Fitzpatrick, S. M.; Kappers, M.; Kaye, Q.; Giovas, C. M.; LeFebvre, M. J.; Harris, M. H.; Burnett, S.; Pavia, J. A.; Marsaglia, K.; Feathers, J. (Journal of Field Archaeology, 2009)
id: 830

Radiocarbon Analysis of Atmospheric Formaldehyde Using Cystamine Derivatization - Shen, Haiwei; McNichol, Ann P.; Xu, Li; Gagnon, Alan; Heikes, Brian G. (ANALYTICAL CHEMISTRY, 2009)
A compound specific radiocarbon analysis method was developed to evaluate the C-14 composition of atmospheric formaldehyde. In this method, gaseous formaldehyde was collected with a high-volume air sampler using glass-fiber filters pretreated with sodium bisulfite. Collected formaldehyde was then released into water and derivatized with cysteamine to thiazolidine. The thiazolidine was extracted into dichloromethane and concentrated by evaporation. Concentrated thiazolidine was separated from other compounds using preparative capillary gas chromatography and uniquely collected as a phosphate salt with a fraction collector. The C-14 composition of the salt was analyzed by accelerator mass spectrometry after combustion to CO2 and subsequent reduction to graphite. In a pilot study, ambient formaldehyde samples collected on the roof of the CACS building at Narragansett Bay Campus, Narragansett, RI, showed a significantly larger fraction of fossil carbon than modern carbon.

Rapid Response of a Marine Mammal Species to Holocene Climate and Habitat Change - de Bruyn, Mark; Hall, Brenda L.; Chauke, Lucas F.; Baroni, Carlo; Koch, Paul L.; Hoelzel, A. Rus (Plos Genetics, 2009)
Environmental change drives demographic and evolutionary processes that determine diversity within and among species. Tracking these processes during periods of change reveals mechanisms for the establishment of populations and provides predictive data on response to potential future impacts, including those caused by anthropogenic climate change. Here we show how a highly mobile marine species responded to the gain and loss of new breeding habitat. Southern elephant seal, Mirounga leonina, remains were found along the Victoria Land Coast (VLC) in the Ross Sea, Antarctica, 2,500 km from the nearest extant breeding site on Macquarie Island (MQ). This habitat was released after retreat of the grounded ice sheet in the Ross Sea Embayment 7,500-8,000 cal YBP, and is within the range of modern foraging excursions from the MQ colony. Using ancient mtDNA and coalescent models, we tracked the population dynamics of the now extinct VLC colony and the connectivity between this and extant breeding sites. We found a clear expansion signal in the VLC population similar to 8,000 YBP, followed by directional migration away from VLC and the loss of diversity at similar to 1,000 YBP, when sea ice is thought to have expanded. Our data suggest that VLC seals came initially from MQ and that some returned there once the VLC habitat was lost, similar to 7,000 years later. We track the founder-extinction dynamics of a population from inception to extinction in the context of Holocene climate change and present evidence that an unexpectedly diverse, differentiated breeding population was founded from a distant source population soon after habitat became available.
id: 1914; PT: J; NR: 58; TC: 11; J9: PLOS GENET; PG: 11; GA: 486SZ; UT: WOS:000269219500031

Recently exposed vegetation reveals Holocene changes in the extent of the Quelccaya Ice Cap, Peru - Buffen, Aron M.; Thompson, Lonnie G.; Mosley-Thompson, Ellen; Huh, Kyung In (QUATERNARY RESEARCH, 2009)
Radiocarbon dating of well-preserved, in-place vegetation exposed by the retreating Quelccaya Ice Cap of southeastern Peru constrains the last time the ice cap's extent was smaller than at present. Seventeen plant samples from two sites along the central western margin collectively date to 4700 and 5100 cal yr BP and strongly indicate that current ice cap retreat is unprecedented over the past similar to 5 millennia. Seventeen vegetation samples interbedded in a nearby clastic sedimentary sequence suggest ice-free conditions at this site from similar to 5200 to at least similar to 7000 cal yr BP, and place minimum constraint on early- to mid-Holocene ice cap extent. (C) 2009 University of Washington. Published by Elsevier Inc. All rights reserved.
Keywords: 14C dating; Andes; Climate change; Glacier retreat; Holocene; Peru; Quelccaya Ice Cap; South America; Tropical glaciers

Sinking deltas due to human activities - Syvitski, J. P. M.; Kettner, A. J.; Overeem, I.; Hutton, E. W. H.; Hannon, M. T.; Brakenridge, G. R.; Day, J.; Vorosmarty, C.; Saito, Y.; Giosan, L.; Nicholls, R. J. (Nature Geoscience, 2009)
Many of the world's largest deltas are densely populated and heavily farmed. Yet many of their inhabitants are becoming increasingly vulnerable to flooding and conversions of their land to open ocean. The vulnerability is a result of sediment compaction from the removal of oil, gas and water from the delta's underlying sediments, the trapping of sediment in reservoirs upstream and floodplain engineering in combination with rising global sea level. Here we present an assessment of 33 deltas chosen to represent the world's deltas. We find that in the past decade, 85% of the deltas experienced severe flooding, resulting in the temporary submergence of 260,000 km(2). We conservatively estimate that the delta surface area vulnerable to flooding could increase by 50% under the current projected values for sea-level rise in the twenty-first century. This figure could increase if the capture of sediment upstream persists and continues to prevent the growth and buffering of the deltas.
id: 799; 501BW Times Cited:2 Cited References Count:38; YY

Spatial variability of late Holocene and 20th century sea-level rise along the Atlantic coast of the United States - Engelhart, Simon E.; Horton, Benjamin P.; Douglas, Bruce C.; Peltier, W. Richard; Törnqvist, Torbjörn E. (Geology, 2009)
id: 1872Y

Timing and magnitude of recent accelerated sea-level rise (North Carolina, United States) - Kemp, A. C.; Horton, B. P.; Culver, S. J.; Corbett, D. R.; van de Plassche, O.; Gehrels, W. R.; Douglas, B. C.; Parnell, A. C. (Geology, 2009)
We provide records of relative sea level since A. D. 1500 from two salt marshes in North Carolina to complement existing tide-gauge records and to determine when recent rates of accelerated sea-level rise commenced. Reconstructions were developed using foraminifera-based transfer functions and composite chronologies, which were validated against regional twentieth century tide-gauge records. The measured rate of relative sea-level rise in North Carolina during the twentieth century was 3.0-3.3 mm/a, consisting of a background rate of similar to 1 mm/a, plus an abrupt increase of 2.2 mm/a, which began between A. D. 1879 and 1915. This acceleration is broadly synchronous with other studies from the Atlantic coast. The magnitude of the acceleration at both sites is larger than at sites farther north along the U. S. and Canadian Atlantic coast and may be indicative of a latitudinal trend.
id: 829; 512AY Times Cited:15 Cited References Count:30Y

Towards a quantitative and independent reconstruction of Holocene temperature and precipitation in Northern Great Plains using novel organic proxies - Toney, J. L.; Huang, Y.; Fritz, S. C.; Baker, P.; Grimm, E. C.; Nyren, P. E. (Eos, Transactions, American Geophysical Union, 2009)
id: 891

3500 yr record of centennial-scale climate variability from the Western Pacific Warm Pool - Langton, S. J.; Linsley, B. K.; Robinson, R. S.; Rosenthal, Y.; Oppo, D. W.; Eglinton, T. I.; Howe, S. S.; Djajadihardja, Y. S.; Syamsudin, F. (Geology, 2008)
We use geochemical data from a sediment core in the shallow-silled and intermittently dysoxic Kau Bay in Halmahera (Indonesia, lat 1 degrees N, long 127.5 degrees E) to reconstruct century-scale climate variability within the Western Pacific Warm Pool over the past similar to 3500 yr. Downcore variations in bulk sedimentary delta N-15 appear to reflect century-scale variability in basin ventilation, attributed to changes in oceanographic conditions related to century-scale fluctuations in El Nino Southern Oscillation (ENSO). We infer an increase in century-scale El Nino activity beginning ca. 1700 yr B.P. with peaks in El Nino activity ca. 1500 yr B.P., 1150 yr B.P., and ca. 700 yr B.P. The Kau Bay results suggest that there was diminished ENSO amplitude or frequency, or a departure from El Nino-like conditions during the Medieval Warm Period, and distinctive, but steadily decreasing, El Nino activity during and after the Little Ice Age.
id: 1894; ISI Document Delivery No.: 357HB Times Cited: 1 Cited Reference Count: 36 Cited References: ALDRIAN E, 2003, INT J CLIMATOL, V23, P1435, DOI 10.1002/joc.950 ALTABET MA, 1994, GLOBAL BIOGEOCHEM CY, V8, P103 ALTABET MA, 2001, LIMNOL OCEANOGR, V46, P368 ARRUDA WZ, 2003, J PHYS OCEANOGR, V33, P2815 BRANDES JA, 1998, LIMNOL OCEANOGR, V43, P1680 BRANDES JA, 2002, GLOBAL BIOGEOCHEMICA, V16 CASCIOTTI KL, 2002, ANAL CHEM, V74, P4905, DOI 10.1021/ac020113w CHRISTIAN JR, 2004, DEEP-SEA RES PT II, V51, P209, DOI 10.1016/j.dsr2.2003.06.002 DEUTSCH C, 2007, NATURE, V445, P163, DOI 10.1038/nature05392 GANESHRAM RS, 2000, PALEOCEANOGRAPHY, V15, P361 GRANGER J, 2004, EOS T AM GEOPHYS U S, V85 GRANGER J, 2004, LIMNOL OCEANOGR, V49, P1763 HAUG GH, 1998, PALEOCEANOGRAPHY, V13, P427 HAUG GH, 2001, SCIENCE, V293, P1304 HODELL DA, 2005, QUATERNARY SCI REV, V24, P1413, DOI 10.1016/j.quascirev.2004.10.013 LIU KK, 1989, LIMNOL OCEANOGR, V34, P820 MAKOU MC, 2007, ORG GEOCHEM, V38, P1680, DOI 10.1016/j.orggeochem.2007.06.003 MARIOTTI A, 1981, PLANT SOIL, V62, P413 MASUMOTO Y, 2001, GEOPHYS RES LETT, V28, P1631 MIDDELBURG JJ, 1990, GEOL ULTRIECTIN, V71, P177 MOY CM, 2002, NATURE, V420, P162 NEWTON A, 2006, GEOPHYS RES LETT, V33, ARTN L19710 REIN B, 2004, GEOPHYS RES LETT, V31, ARTN L17211 REIN B, 2005, PALEOCEANOGRAPHY, V20, ARTN PA4003 REYNOLDS RW, 1994, J CLIMATE, V7, P929 RODBELL DT, 1999, SCIENCE, V283, P516 SIGMAN DM, 2003, GEOCHEM GEOPHY GEOSY, V4, ARTN 1040 SIGMAN DM, 2005, GLOBAL BIOGEOCHEM CY, V19, ARTN GB4022 STOTT L, 2004, NATURE, V431, P56, DOI 10.1038/nature02903 STREETPERROTT FA, 1997, SCIENCE, V278, P1422 THUNELL R, 2004, GLOBAL BIOGEOCHEMICA, V18, UNSP GB3001 UEKI I, 2003, J GEOPHYS RES-OCEANS, V108, ARTN 3243 VANAKEN HMV, 1988, NETHERLANDS J SEA RE, V22, P403, DOI 10.1016/0077-7579(88)90011-7 VANDERWEIJDEN CH, 1989, NETH J SEA RES, V24, P583 VANRIEL PM, 1943, OCEANOGRAPHIC RESU 5, V2 WYRTKI K, 1961, NAGA REPORT, V2 Langton, S. J. Linsley, B. K. Robinson, R. S. Rosenthal, Y. Oppo, D. W. Eglinton, T. I. Howe, S. S. Djajadihardja, Y. S. Syamsudin, F. U.S. National Science Foundation [OCE-0502550, OCE-0502504, OCE-052960] This work was supported by the U.S. National Science Foundation (grants OCE-0502550, OCE-0502504, and OCE-052960). We thank the captain, crew, technicians, and the scientific crew who helped with sample collection on the R/V Baruna Jaya VIII. Geological soc amer, inc Boulder; YY

Abrupt changes in Antarctic Intermediate Water circulation over the past 25,000 years - Pahnke, Katharina; Goldstein, Steven L.; Hemming, Sidney R. (Nature Geoscience, 2008)
The circulation of Antarctic Intermediate Water is thought to make an important contribution to the global ocean-climate system, but the details of this interaction are not fully understood. Furthermore, the behaviour of Antarctic Intermediate Water under glacial and interglacial conditions is not well constrained. Here we present a 25,000-year-long record of neodymium isotopic variations-a tracer of water-mass mixing-from the middle depths of the tropical Atlantic Ocean. Our data reveal abruptly enhanced northward advection of Antarctic Intermediate Water during periods of reduced North Atlantic overturning circulation during the last deglaciation. These events coincide with an increase in the formation of Antarctic Intermediate Water and warming in the southwest Pacific Ocean, which suggests a tight link with Southern Hemisphere climate. In contrast, the initial incursion of southern source water into the North Atlantic similar to 19,000 years ago coincided with weak Antarctic Intermediate Water formation in the Pacific and reduced overturning in the North Atlantic. We conclude that reduced competition at intermediate water depth at this time allowed expansion of Antarctic Intermediate Water into the North Atlantic. This early incursion of Antarctic Intermediate Water may have contributed to freshening of the North Atlantic, perhaps spurring the subsequent collapse of North Atlantic deep convection.
id: 2026; PT: J; UT: WOS:000261278700021

Antarctic sediment chronology by programmed-temperature pyrolysis: Methodology and data treatment - Rosenheim, B. E.; Day, M. B.; Domack, E.; Schrum, H.; Benthien, A.; Hayes, J. M. (Geochemistry Geophysics Geosystems, 2008)
We report a detailed programmed-temperature pyrolysis/ combustion methodology for radiocarbon (C-14) dating of Antarctic sub-ice shelf sediments. The method targets the autochthonous organic component in sediments that contain a distribution of acid-insoluble organic components from several sources of different ages. The approach has improved sediment chronology in organic-rich sediments proximal to Antarctic ice shelves by yielding maximum age constraints significantly younger than bulk radiocarbon dates from the same sediment horizons. The method proves adequate in determining isotope ratios of the pre-aged carbon end-member; however, the isotopic compositions of the low-temperature measurements indicate that no samples completely avoided mixing with some proportion of pre-aged organic material. Dating the unresolved but desired young end-member must rely on indirect methods, but a simple mixing model cannot be developed without knowledge of the sedimentation rate or comparable constraints. A mathematical approach allowing for multiple mixing components yields a maximum likelihood age, a first-order approximation of the relative proportion of the autochthonous component, and the temperature at which allochthonous carbon begins to volatilize and mix with the autochthonous component. It is likely that our estimation of the cutoff temperature will be improved with knowledge of the pyrolysis kinetics of the major components. Chronology is improved relative to bulk acid-insoluble organic material ages from nine temperature interval dates down to two, but incorporation of inherently more pre-aged carbon in the first division becomes more apparent with fewer and larger temperature intervals.
id: 1847; 284ON Times Cited:5 Cited References Count:27Y

A Be-10 chronology of lateglacial and Holocene mountain glaciation in the Scoresby Sund region, east Greenland: implications for seasonality during lateglacial time - Kelly, M. A.; Lowell, T. V.; Hall, B. L.; Schaefer, J. M.; Finkel, R. C.; Goehring, B. M.; Alley, R. B.; Denton, G. H. (Quaternary Science Reviews, 2008)
Thirty-eight new cosmogenic (Be-10) exposure ages from the Scoresby Sund region of east Greenland indicate that prominent moraine sets deposited by mountain glaciers date from 780 to 310 yr, approximately during the Little Ice Age, from 11660 to 10 630 yr, at the end of the Younger Dryas cold interval or during Preboreal time, and from 13 010 to 11630 yr, during lateglacial time. Equilibrium line altitudes (ELAs) interpreted from lateglacial to Early Holocene moraines indicate summertime cooling between similar to 3.9 and 6.6 degrees C relative to today's value, much less than the extreme Younger Dryas cooling registered by Greenland ice cores (mean-annual temperatures of similar to 15 degrees C colder than today's value). This apparent discrepancy between paleotemperature records supports the contention that Younger Dryas cooling was primarily a wintertime phenomenon. Be-10 ages of lateglacial and Holocene moraines show that mountain glaciers during the Little Ice Age were more extensive than at any other time since the Early Holocene Epoch. In addition, 10Be ages of lateglacial moraines show extensive reworking of boulders with cosmogenic nuclides inherited from prior periods of exposure, consistent with our geomorphic observations and cosmogenic-exposure dating studies in other Arctic regions. (C) 2008 Elsevier Ltd. All rights reserved.
id: 1868; 389XX Times Cited:7 Cited References Count:75Y

Constraints on the Pleistocene chronology of sediments from the Lomonosov Ridge - O'Regan, M.; King, J.; Backman, J.; Jakobsson, M.; Palike, H.; Moran, K.; Heil, C.; Sakamoto, T.; Cronin, T. M.; Jordan, R. W. (Paleoceanography, 2008)
[1] Despite its importance in the global climate system, age-calibrated marine geologic records reflecting the evolution of glacial cycles through the Pleistocene are largely absent from the central Arctic Ocean. This is especially true for sediments older than 200 ka. Three sites cored during the Integrated Ocean Drilling Program's Expedition 302, the Arctic Coring Expedition ( ACEX), provide a 27 m continuous sedimentary section from the Lomonosov Ridge in the central Arctic Ocean. Two key biostratigraphic datums and constraints from the magnetic inclination data are used to anchor the chronology of these sediments back to the base of the Cobb Mountain subchron ( 1215 ka). Beyond 1215 ka, two best fitting geomagnetic models are used to investigate the nature of cyclostratigraphic change. Within this chronology we show that bulk and mineral magnetic properties of the sediments vary on predicted Milankovitch frequencies. These cyclic variations record "glacial'' and "interglacial'' modes of sediment deposition on the Lomonosov Ridge as evident in studies of ice-rafted debris and stable isotopic and faunal assemblages for the last two glacial cycles and were used to tune the age model. Potential errors, which largely arise from uncertainties in the nature of downhole paleomagnetic variability, and the choice of a tuning target are handled by defining an error envelope that is based on the best fitting cyclostratigraphic and geomagnetic solutions.
id: 868; 281YL Times Cited:22 Cited References Count:55; YY

Deepwater circulation on Blake Outer Ridge (western North Atlantic) during the Holocene, Younger Dryas, and Last Glacial Maximum - Evans, H. K.; Hall, I. R. (Geochemistry Geophysics Geosystems, 2008)
Three depth transects containing a total of 33 sediment cores were investigated along the Blake Outer Ridge in the western subtropical North Atlantic. Sortable silt mean ((SS) over bar) grain size and stable isotope records were used to assess the position and relative intensity of the Western Boundary Undercurrent (WBUC) during the Holocene, the Last Glacial Maximum (LGM), and the Younger Dryas (YD) intervals. The Holocene reconstruction is consistent with modern physical and chemical hydrographic measurements in the area, suggesting a deep position for the fast flowing core of the WBUC (3000-4000 m, deepening to similar to 4500 m water depth on the ridge flanks) and a water column dominated by North Atlantic Deep Water (NADW). The LGM and YD reconstructions show that a comparable hydrographic regime was present during both these intervals, suggesting a similar mode of circulation that was appreciably different from the Holocene reconstruction. The WBUC's zone of maximum flow speed during these intervals is suggested to have shifted above 2500 m water depth, consistent with nutrient depleted Glacial North Atlantic Intermediate Water formation with an increasing influence of Southern Source Water (SSW) beneath. Below 4000 m water depth, (SS) over bar results hint at increased SSW flow vigor during both the LGM and YD with higher flow speeds than during the Holocene. This study provides a framework for aiding the interpretation of time series records of paleocurrent flow speed changes in the region of the WBUC.
id: 839; 281XG Times Cited:1 Cited References Count:84Y

Environmental and Climatic Controls on the Occurrence and Abundance of Long Chain Alkenones in Lakes of the Interior United States - Toney, J. L.; Fritz, S.; Baker, P.; Grim, E.; Nyren, P.; Theroux, S.; Huang, Y. (Eos, Transactions, American Geophysical Union, 2008)
id: 892

Environmental Factors Controlling Community Structure, Morphology and Linear Extension of Mid-Holocene Reef Corals from Cañada Honda, Southwestern, Dominican Republic - Cuevas, D.; Sherman, C.; Ramírez, W.; Hubbard, D. (Proceedings of the 11th International Coral Reef Symposium, Ft. Lauderdale, Florida, 2008)
The Cañada Honda (CH) fossil coral reef, located in SW Dominican Republic, provides a unique opportunity to examine reef accretion in a high-sedimentation environment between 9.0-5.0 ky ago. Annual linear extension of fossil corals was determined for comparison with data from modern coral reefs. The reef is characterized by the high abundance of sediment-tolerant coral species, their tendency to form almost monospecific stands and grow as domes-cones with ragged margins. Also, colonies of Montastraea faveolata commonly contain bands of sediment incorporated within their skeletons. Calibrated radiocarbon ages of fossil corals range from 9,256±137 to 6,737±94.5 BP. Correlation with Holocene sea-level curves indicates that most corals on CH developed at depths greater than 15m. Growth rates varied from 0.09-0.44 cm/yr and suggest reduced light penetration caused by coral growth at such depths. Reef sediment is characterized by more than 85% carbonate material. A significant portion of the carbonate is allochtonous and was derived from nearby Neogene limestones. The reef was able to survive under these conditions because of the high carbonate content of incoming terrigenous sediment and that storms probably occurred sporadically providing intervening lowsedimentation periods during which reef corals could respond and grow back, “keeping-up” with sedimentation.
id: 1979
Keywords: Caribbean; Holocene; ICRS11; Lessons from the past; linear extension; siltation

Eruptive history, geochronology, and magmatic evolution of the Puyehue-Cordon Caulle volcanic complex, Chile - Singer, B. S.; Jicha, B. R.; Harper, M. A.; Naranjo, J. A.; Lara, L. E.; Moreno-Roa, H. (Geological Society of America Bulletin, 2008)
Forty-three Ar-40/Ar-39 age determinations of lava flows, domes, ignimbrites, and dikes, plus C-14 dates from seven distal tephra layers, combined with stratigraphy, geochemistry, and Sr and Th isotope data, establish an eruptive chronology for the Puyehue-Cordon Caulle volcanic complex at 40.5 degrees S in the Andean southern volcanic zone (SVZ). The complex preserves similar to 131 km(3) of lava and tephra that erupted from numerous vents widely separated in time and space. Approximately 80% of the total volume consists of basaltic to andesitic lava that formed two broad shield volcanoes between 314 and 70 ka. The modern Puyehue stratovolcano was built on the southerly shield during the past 69 k.y. following a hiatus of 25 k.y. Puyehue has erupted similar to 15 km(3) of basaltic to rhyolitic magma that spans the entire compositional range found in the southern SVZ and evolved via at least six phases including: (1) basaltic andesitic to dacitic lavas between 69 and 32 ka, (2) a shift to bimodal magma compositions that is first expressed by a rhyodacite mingled with inclusions of MgO-rich basaltic andesite at 34 ka, (3) dacitic to rhyolitic flows and domes from 19 to 12 ka, (4) basaltic to basaltic andesitic flows between 15 and 12 ka, (5) subsequent rhyolitic dome growth in several effusive and explosive stages between 7 and 5 ka, followed by (6) a powerful series of phreatomagmatic and sub-Plinian eruptions at ca. 1.1 ka that obliterated the preceding rhyolite domes and formed the present 2.5-km-diameter, 280-m-deep summit crater. Along the Cordon Caulle fissure zone, similar to 5 km(3) of rhyodacitic to rhyolitic lavas, domes, and cones have formed during the past similar to 16.5 k.y., including explosive and effusive eruptions in 1921-1922 and 1960.Eruptive rates were nonuniform over time, with background growth at 0.04 km(3)/k.y. or less, punctuated by spurts at up to 0.90 km(3)/ k.y. The time-averaged rate, 0.42 km(3)/k.y., is nearly double that at the Tatara-San Pedro complex 500 km to the north during the past 300 k.y. These findings indicate that within a single are the magmatic and eruptive fluxes at individual frontal volcanoes can be highly variable. The last three stratocone-building events on Puyehue began during periods of deglaciation, suggesting a relationship between unloading of ice and ease of magma ascent. Puyehue basalt exhibits subtle changes in U-238-Th-230, Sr-87/Sr-86, and trace element composition over time that signal shifts in the composition and degree of melting of the mantle wedge, or the extent to which basalt was modified by assimilation of heterogeneous crustal melts. The complex has become exceptionally bimodal and more explosive over time with recent rhyolites evolving by extreme crystal fractionation of malic magma and lesser volumes of andesite and dacite created via mixing of rhyolite and basalt. Despite the high flux of basalt during the past 300 k.y., no large silicic magma reservoir formed in the upper crust. Instead, U-238-Th-230 data favor rapid ascent of several small bodies of basaltic and silicic magma from the lower crust, promoted perhaps by conduits that reflect strike-slip faulting beneath the complex.
300ujTimes Cited:61Cited References Count:55

The Global Stratotype Section and Point (GSSP) for the base of the Holocene Series/Epoch (Quaternary System/Period) in the NGRIP ice core RID B-5560-2008 RID F-1111-2011 - Walker, Mike; Johnsen, Sigfu's; Rasmussen, Sune Olander; Steffensen, Jorgen-Peder; Popp, Trevor; Gibbard, Philip; Hoek, Wim; Lowe, John; Andrews, John; Bjorck, Svante; Cwynar, Les; Hughen, Konrad; et al. (Episodes, 2008)
The Greenland ice core from NorthGRIP (NGRIP) contains a proxy climate record across the Pleistocene-Holocene boundary of unprecedented clarity and resolution. Analysis of an array of physical and chemical parameters within the ice enables the base of the Holocene, as reflected in the first signs of climatic warming at the end of the Younger Dryas/Greenland Stadial 1 cold phase, to be located with a high degree of precision. This climatic event is most clearly reflected in an. abrupt shaft in deuterium excess values, accompanied by more gradual changes in delta(18)O, dust concentration, a range of chemical species, and annual layer thickness. A timescale based on multi-parameter annual layer counting provides an age of 11,700 yr b2k (before AD2000) for the base of the Holocene, with, an estimated 2 sigma uncertainty of 99 yr: It is proposed that an archived core from this unique sequence should constitute the Global Stratotype Section and Point (GSSP) for the base of the Holocene Series/Epoch (Quaternary System/Period).
id: 1988; PT: J; CT: 17th Congress of the International-Union-for-Quaternary-Research; CY: JUL 28-AUG 03, 2007; CL: Cairns, AUSTRALIA; SP: Int Union Quaternary Res; UT: WOS:000258669100017

Increased terrestrial to ocean sediment and carbon fluxes in the northern chesapeake bay associated with twentieth century land alteration - Saenger, C.; Cronin, T. M.; Willard, D.; Halka, J.; Kerhin, R. (Estuaries and Coasts, 2008)
We calculated Chesapeake Bay (CB) sediment and carbon fluxes before and after major anthropogenic land clearance using robust monitoring, modeling and sedimentary data. Four distinct fluxes in the estuarine system were considered including (1) the flux of eroded material from the watershed to streams, (2) the flux of suspended sediment at river fall lines, (3) the burial flux in tributary sediments, and (4) the burial flux in main CB sediments. The sedimentary maximum in Ambrosia (ragweed) pollen marked peak land clearance (similar to 1900 A.D.). Rivers feeding CB had a total organic carbon (TOC)/total suspended solids of 0.24 +/- 0.12, and we used this observation to calculate TOC fluxes from sediment fluxes. Sediment and carbon fluxes increased by 138-269% across all four regions after land clearance. Our results demonstrate that sediment delivery to CB is subject to significant lags and that excess post-land clearance sediment loads have not reached the ocean. Post-land clearance increases in erosional flux from watersheds, and burial in estuaries are important processes that must be considered to calculate accurate global sediment and carbon budgets.
id: 812; 316CY Times Cited:1 Cited References Count:54Y

Interpreting sea surface temperature from strontium/calcium ratios in Montastrea corals: Link with growth rate and implications for proxy reconstructions - Saenger, C.; Cohen, A. L.; Oppo, D. W.; Hubbard, D. (Paleoceanography, 2008)
[1] We analyzed strontium/calcium ratios (Sr/Ca) in four colonies of the Atlantic coral genus Montastrea with growth rates ranging from 2.3 to 12.6 mm a(-1). Derived Sr/Ca-sea surface temperature (SST) calibrations exhibit significant differences among the four colonies that cannot be explained by variations in SST or seawater Sr/Ca. For a single coral Sr/Ca ratio of 8.8 mmol mol(-1), the four calibrations predict SSTs ranging from 24.0 degrees to 30.9 degrees C. We find that differences in the Sr/Ca-SST relationships are correlated systematically with the average annual extension rate (ext) of each colony such that Sr/Ca ( mmol mol(-1)) = 11.82 (+/- 0.13) - 0.058 (+/- 0.004) x ext ( mm a(-1)) - 0.092 (+/- 0.005) x SST (degrees C). This observation is consistent with previous reports of a link between coral Sr/Ca and growth rate. Verification of our growth-dependent Sr/Ca - SST calibration using a coral excluded from the calibration reconstructs the mean and seasonal amplitude of the actual recorded SST to within 0.3 degrees C. Applying a traditional, nongrowth-dependent Sr/Ca - SST calibration derived from a modern Montastrea to the Sr/Ca ratios of a conspecific coral that grew during the early Little Ice Age (LIA) ( 400 years B. P.) suggests that Caribbean SSTs were > 5 degrees C cooler than today. Conversely, application of our growth-dependent Sr/Ca - SST calibration to Sr/Ca ratios derived from the LIA coral indicates that SSTs during the 5-year period analyzed were within error (+/- 1.4 degrees C) of modern values.
id: 864; ISI Document Delivery No.: 333MS Times Cited: 3 Cited Reference Count: 49 Cited References: *DEP CONS CULT AFF, 1986, MAR WAT QUAL MEAS CH *NAT RES COUNC, 2006, SURF TEMP REC LAST 2 BEVINGTON PR, 1969, DATA REDUCTION ERROR, P56 BLACK DE, 2004, PALEOCEANOGRAPHY, V19, ARTN PA2022 BLACK DE, 2007, PALEOCEANOGRAPHY, V22, ARTN PA4204 CARDINAL D, 2001, CHEM GEOL, V176, P213 CARRICARTGANIVET JP, 2004, J EXP MAR BIOL ECOL, V302, P249, DOI 10.1016/j.jembe.2003.10.015 CHIANG JCH, 2002, J GEOPHYS RES-ATMOS, V107, ARTN 4004 COBB KM, 2003, EARTH PLANET SC LETT, V210, P91, DOI 10.1016/S0012-821X(03)00138-9 COHEN AL, 2004, GEOPHYS RES LETT, V31, ARTN L16310 COHEN AL, 2004, MAR ECOL-PROG SER, V271, P147 COHEN AL, 2006, GEOCHEM GEOPHY GEOSY, V7, ARTN Q12004 COHEN AL, 2007, GEOPHYS RES LETT, V34, ARTN L17706 CRONIN TM, 2003, GLOBAL PLANET CHANGE, V36, P17 DEVILLIERS S, 1995, SCIENCE, V269, P1247 DEVILLIERS S, 1999, EARTH PLANET SC LETT, V171, P623 FELIS T, 2004, NATURE, V429, P164, DOI 10.1038/nature02546 GABITOV RI, 2006, GEOCHIM COSMOCHIM S, V70, A187, DOI 10.1016/j.gca.2006.06.377 GAETANI GA, 2006, GEOCHIM COSMOCHIM AC, V70, P4617, DOI 10.1016/j.gca.2006.07.008 GOODKIN NF, 2005, PALEOCEANOGRAPHY, V20, ARTN PA4016 HAASESCHRAMM A, 2003, PALEOCEANOGRAPHY, V18, ARTN 1073 HAASESCHRAMM A, 2005, PALEOCEANOGRAPHY, V20, ARTN PA4015 HAUG GH, 2001, SCIENCE, V293, P1304 HENDY EJ, 2002, SCIENCE, V295, P1511 HERNANDEZGUERRA A, 2000, GEOPHYS RES LETT, V27, P3497 HODELL DA, 2005, QUATERNARY RES, V63, P109, DOI 10.1016/j.yqres.2004.11.004 HUBBARD DK, 2005, J SEDIMENT RES, V75, P97, DOI 10.2110/jsr.2005.009 HUGHEN KA, 2004, RADIOCARBON, V46, P1059 JONES PD, 2004, REV GEOPHYS, V42, ARTN RG2002 LEDER JJ, 1996, GEOCHIM COSMOCHIM AC, V60, P2857 LOUGH JM, 2004, PALAEOGEOGR PALAEOCL, V204, P115, DOI 10.1016/S0031-0182(03)00727-2 LUND DC, 2006, PALEOCEANOGRAPHY, V21, ARTN PA2009 MEIBOM A, 2006, GEOPHYS RES LETT, V33, ARTN L11608 MOHIUDDIN MM, 2004, DEEP-SEA RES PT I, V51, P1659, DOI 10.1016/j.dsr.2004.06.002 NYBERG J, 2002, PALAEOGEOGR PALAEOCL, V183, P25 OSTERMANN DR, 2000, PALEOCEANOGRAPHY, V15, P353 PFLAUMANN U, 2003, PALEOCEANOGRAPHY, V18, ARTN 1065 REYNAUD S, 2007, GEOCHIM COSMOCHIM AC, V71, P354, DOI 10.1016/j.gca.2006.09.009 REYNOLDS RW, 1994, J CLIMATE, V7, P929 ROSENTHAL Y, 1999, ANAL CHEM, V71, P3248 SCHMIDT MW, 2006, GEOCHEM GEOPHY GEOSY, V7, ARTN Q02P10 SMITH JM, 2006, PALEOCEANOGRAPHY, V21, ARTN PA1010 SWART PK, 2002, GEOCHEM GEOPHY GEOSY, V3, ARTN 8402 THUNELL RC, 1984, MICROPALEONTOLOGY, V30, P243 VELLINGA M, 2004, J CLIMATE, V17, P4498 WATANABE T, 2001, MAR GEOL, V173, P21 WEIL E, 1994, B MAR SCI, V55, P151 WINTER A, 2000, GEOPHYS RES LETT, V27, P3365 YOO JM, 1990, J PHYS OCEANOGR, V20, P831 Saenger, Casey Cohen, Anne L. Oppo, Delia W. Hubbard, Dennis Amer geophysical union Washington; YY

Late Holocene marine productivity changes in Northern Patagonia-Chile inferred from a multi-proxy analysis of Jacaf channel sediments - Rebolledo, Lorena; Sepulveda, Julio; Lange, Carina B.; Pantoja, Silvio; Bertrand, Sbastien; Hughen, Konrad; Figueroae, Dante (Estuarine Coastal and Shelf Science, 2008)
A multi-proxy approach based on organic (organic carbon, alkenones, and C/N) and inorganic geochemical proxies (biogenic opal, inorganic carbon, Fe, Ti, and Ca) preserved in the sediments of the Jacaf channel (CF7-PC33; 44 degrees 21'S, 72 degrees 58'W, 510 m water depth), Chilean fjords, yields evidence of major past productivity fluctuations in accordance with climatic changes over the last similar to 1800 years. The downcore record clearly shows two productivity/climate modes. The first period, prior to 900 cal yr BP, is characterized by decreased marine productivity and a reduced continental signal, pointing to diminished precipitation and runoff. In contrast, the second period between similar to 750 cal yr BP and the late 1800s (top of core) is illustrated by elevated productivity and an increased continental signal, suggesting higher precipitation and runoff. Both time intervals are separated by a relatively abrupt transition of similar to 150 years which roughly coincides with the beginning of the Little Ice Age. The increased content of freshwater diatoms and Chrysophyte cysts that characterize the last 200 years of the latter mode coincides with a significant decrease in the carbonate content of the sediment; together they further indicate increased terrigenous contributions and decreased marine carbonate productivity at the end of the Little Ice Age. The correspondence between our record and other paleoclimate studies carried out in South America and Antarctica demonstrates that the Chilean fjord area of Northern Patagonia is not just sensitive to local climatic variability but also to regional and possibly global variability. (C) 2008 Elsevier Ltd. All rights reserved.
id: 2117; PT: J; TC: 5; J9: ESTUAR COAST SHELF S; UT: WOS:000261562600002

A late holocene pollen and charcoal record from La Selva biological station, Costa Rica - Kennedy, Lisa M.; Horn, Sally P. (Biotropica, 2008)
Pollen and charcoal analysis of a 5.9-m-long sediment profile from a swamp on an alluvial terrace on the edge of La Selva biological station, Costa Rica (10 degrees 26 ' 23 '' N, 84 degrees 00 ' 24 '' W, 36 m asl), documents three millennia of human and natural disturbance within a lowland tropical rain forest. The record indicates that the highly diverse rain forest that presently surrounds the Cantarrana swamp regrew following forest clearing and maize agriculture that ended only a few centuries ago. The first maize pollen appears in sediments deposited similar to 1070 calendar-year BP. Older sediments below the 'maize zone' contain macroscopic charcoal, abundant microscopic charcoal, and possible pollen indicators of forest clearance, perhaps signaling local cultivation of root crops that left no pollen in the sediments. Interpretation of local archaeology indicates that La Selva reserve may have been most heavily populated during the El Bosque and La Selva regional archaeological phases from 2250-950 yr BP. However, the distribution of maize pollen in the sediments is clear evidence that the reserve was also occupied during the later La Cabana phase (950-400 yr BP), from which few artifacts have yet surfaced. Natural forest disturbance from treefalls and stream dynamics, and hydrological shifts associated with late-Holocene climate variability, form a backdrop to the human land-use history preserved in the Cantarrana sediment profile.
id: 1997; PT: J; UT: WOS:000252319600004

Late Quaternary vegetation reconstruction from the Eastern Arc Mountains, Tanzania - Mumbi, C. T.; Marchant, R.; Hooghiemstra, H.; Wooller, M. J. (Quaternary Research, 2008)
Pollen, spore, macrofossil and stable isotope (C and N) analyses from a 266-cm sediment core collected from a swamp on the Eastern Arc Mountains, Tanzania, are used to reconstruct vegetation and environmental history. An estimated time scale based on five C-14 ages records approximately 38,000 yr. This palaeorecord is the first from this biodiversity hotspot and importantly extends through the last glacial maximum (LGM). The altitudinal transition from montane to upper montane forest shifted from 1700-1800 in (38,000 C-14 yr BP) to 1800-1900 in (35,000-29,000 C-14 yr BP). From 29,000 to 10,000 C-14 yr BP, it shifted from 1850-1950 in across the LGM to 1750-1800 in (during 10,000-3500 C-14 yr BP), and to present-day elevations at 2000 in during the last 3500 C-14 yr BP. The relative ecosystem stability across the LGM may be explained by the Indian Ocean's influence in maintaining continuous moist forest cover during a period of East African regional climate aridity. During the late Holocene, presence of abundant coprophilous fungi and algal blooms demonstrates increasing human impact. Neurospora spores indicate frequent fires, coinciding with clear signals of decline in Podocarpus and Psychotria trees that possibly represent selective logging. (C) 2007 University of Washington. All rights reserved.
id: 1836; 285PB Times Cited:6 Cited References Count:105Y

Lateral organic carbon supply to the deep Canada Basin - Hwang, J.; Eglinton, T. I.; Krishfield, R. A.; Manganini, S. J.; Honjo, S. (Geophysical Research Letters, 2008)
Understanding the processes driving the carbon cycle in the Arctic Ocean is important for assessing the impacts of the predicted rapid and amplified climate change in this region. We analyzed settling particle samples intercepted by a time-series sediment trap deployed in the abyssal Canada Basin ( at 3067 m) in order to examine carbon export to the deep Arctic Ocean. Strikingly old radiocarbon ages ( apparent mean 14 C age = similar to 1900 years) of the organic carbon, abundant lithogenic material (similar to 80%), and mass flux variations temporally decoupled from the cycle of primary productivity in overlying surface waters together suggest that, unlike other ocean basins, the majority of the particulate organic carbon entering the deep Canada Basin is supplied from the surrounding margins.
id: 1830; 314KU Times Cited:7 Cited References Count:33Y

Loess record of the Pleistocene-Holocene transition on the northern and central Great Plains, USA - Mason, Joseph A.; Miao, Xiaodong; Hanson, Paul R.; Johnson, William C.; Jacobs, Peter M.; Goble, Ronald J. (Quaternary Science Reviews, 2008)
Various lines of evidence support conflicting interpretations of the timing, abruptness. and nature of climate change in the Great Plains during the Pleistocene-Holocene transition. Loess deposits and paleosols on both the central and northern Great Plains provide a valuable record that can help address these issues. A synthesis of new and previously reported optical and radiocarbon ages indicates that the Brady Soil, which marks the boundary between late Pleistocene Peoria Loess and Holocene Bignell Loess, began forming after a reduction in the rate of Peoria Loess accumulation that most likely occurred between 13.5 and 15 cal ka. Brady Soil formation spanned all or part of the Bolling-Allerod episode (approximately 14.7-12.9 cal ka) and all of the Younger Dryas episode (12.9-11.5 cal ka) and extended at least 1000 years beyond the end of the Younger Dryas. The Brady Soil was buried by Bignell Loess sedimentation beginning around 10.5-9 cal ka, and continuing episodically through the Holocene. Evidence for a brief increase in loess influx during the Younger Dryas is noteworthy but very limited. Most late Quaternary loess accumulation in the central Great Plains was nonglacigenic and was under relatively direct climatic control. Thus, Brady Soil formation records climatic conditions that minimized eolian activity and allowed effective pedogenesis, probably through relatively high effective moisture. Optical dating of loess in North Dakota supports correlation of the Leonard Paleosol on the northern Great Plains with the Brady Soil. Thick loess in North Dakota was primarily derived from the Missouri River floodplain; thus, its stratigraphy may in part reflect glacial influence on the Missouri River. Nonetheless, the persistence of minimal loess accumulation and soil formation until 10 cal ka at our North Dakota study site is best explained by a prolonged interval of high effective moisture correlative with the conditions that favored Brady Soil formation. Burial of both the Brady Soil and the Leonard Paleosol by renewed loess influx probably represents eolian system response that occurred when gradual change toward a drier climate eventually crossed the threshold for eolian activity. Overall, the loess-paleosol sequences of the central and northern Great Plains record a broad peak of high effective moisture across the late Pleistocene to Holocene boundary, rather than well-defined climatic episodes corresponding to the Bolling-Allerod and Younger Dryas episodes in the North Atlantic region. (C) 2008 Elsevier Ltd. All rights reserved.
id: 1993; PT: J; UT: WOS:000260545800008

Micropaleontologic record of late pliocene and quaternary paleoenvironments in the northern Albemarle embayment, North Carolina, USA - Culver, S. J.; Farrell, K. M.; Mallinson, D. J.; Horton, B. P.; Willard, D. A.; Thieler, E. R.; Riggs, S. R.; Snyder, S. W.; Wehmiller, J. F.; Bernhardt, C. E.; Hillier, C. (Palaeogeography Palaeoclimatology Palaeoecology, 2008)
Micropaleontological data provide a strong actualistic basis for detailed interpretations of Quaternary paleoenvironmental change. The 90 m-thick Quaternary record of the Albemarle Embayment in the mid-Atlantic coastal plain of the USA provides an excellent opportunity to use such an approach in a region where the details of Quaternary environmental change are poorly known. The foraminiferal record in nine cores from the northern Outer Banks, east of Albemarle Sound, North Carolina, indicates the deposition of subhorizontal, mostly open-marine early to late Pleistocene units unconformably upon a basement of late Pliocene reduced-oxygen, fine-grained, shelf-basin deposits. Pollen data record several warm-cool fluctuations within the early to mid-Pleistocene deposits. Diatom data indicate that some fresh and brackish-water units occur within the generally open-marine Pleistocene succession. A channel cut by the paleo-Roanoke River during the last glacial sea-level lowstand occurs in the northern part of the study area. Pollen indicates that the basal fluvial valley fill accumulated in cooler than modern climate conditions in the latest Pleistocene. Overlying silts and muds accumulated under cool climatic, estuarine conditions according to diatom and pollen data. Radiocarbon ages from the estuarine deposits indicate that the bulk of these sediments accumulated during the latest Pleistocene. The estuarine channel-fill deposits are overlain by Holocene open-marine sands deposited as the rising sea transgressed into the estuary approximately 8.5 to 9.0 kyr BR Within the barrier island drill cores of this study, fully marine sedimentation occurred throughout the Holocene. However, immediately west of the present barrier island, mid- to late Holocene estuarine deposits underlie the modern Albemarle Sound. The islands that currently form a continuous barrier across the mouth of Albemarle Sound have a complex history of Holocene construction and destruction and large portions of them may be less than 3 kyr old. The barrier island sands overlie open-marine sands of Colington Shoal in the north and to the south overlie fluvial and marine sand filling paleo-Roanoke tributary valleys. The Pleistocene sediments underlying the northern Outer Banks study area are mainly of open inner to midshelf origin. If, as is likely, sea level continues to rise, a return to such environmental conditions is likely in the near future. (c) 2008 Elsevier B.V. All rights reserved.
id: 815; 331MZ Times Cited:2 Cited References Count:79Y

The most extensive Holocene advance in the Stauning Alper, East Greenland, occurred in the Little Ice Age - Hall, B. L.; Baroni, C.; Denton, G. H. (Polar Research, 2008)
We present glacial geologic and chronologic data concerning the Holocene ice extent in the Stauning Alper of East Greenland. The retreat of ice from the late-glacial position back into the mountains was accomplished by at least 11 000 cal years B.P. The only recorded advance after this time occurred during the past few centuries (the Little Ice Age). Therefore, we postulate that the Little Ice Age event represents the maximum Holocene ice extent in this part of East Greenland.
id: 823; 327VY Times Cited:1 Cited References Count:45Y

Mutation and evolutionary rates in adelie penguins from the antarctic - Millar, C. D.; Dodd, A.; Anderson, J.; Gibb, G. C.; Ritchie, P. A.; Baroni, C.; Woodhams, M. D.; Hendy, M. D.; Lambert, D. M. (Plos Genetics, 2008)
Precise estimations of molecular rates are fundamental to our understanding of the processes of evolution. In principle, mutation and evolutionary rates for neutral regions of the same species are expected to be equal. However, a number of recent studies have shown that mutation rates estimated from pedigree material are much faster than evolutionary rates measured over longer time periods. To resolve this apparent contradiction, we have examined the hypervariable region (HVR I) of the mitochondrial genome using families of Adelie penguins (Pygoscelis adeliae) from the Antarctic. We sequenced 344 bps of the HVR I from penguins comprising 508 families with 915 chicks, together with both their parents. All of the 62 germline heteroplasmies that we detected in mothers were also detected in their offspring, consistent with maternal inheritance. These data give an estimated mutation rate (micro) of 0.55 mutations/site/Myrs (HPD 95% confidence interval of 0.29-0.88 mutations/site/Myrs) after accounting for the persistence of these heteroplasmies and the sensitivity of current detection methods. In comparison, the rate of evolution (k) of the same HVR I region, determined using DNA sequences from 162 known age sub-fossil bones spanning a 37,000-year period, was 0.86 substitutions/site/Myrs (HPD 95% confidence interval of 0.53 and 1.17). Importantly, the latter rate is not statistically different from our estimate of the mutation rate. These results are in contrast to the view that molecular rates are time dependent.
id: 1195; Millar, Craig D Dodd, Andrew Anderson, Jennifer Gibb, Gillian C Ritchie, Peter A Baroni, Carlo Woodhams, Michael D Hendy, Michael D Lambert, David M PLoS Genet. 2008 Oct 3;4(10):e1000209.2546446

A New Look at Perishable Technologies from the Ozark Plateau: Focus - Horton, Elizabeth T. (31st Annual Conference of the Society of Ethnobiology, 2008)
id: 777

Northern hemisphere controls on tropical southeast African climate during the past 60,000 years - Tierney, Jessica E.; Russell, James M.; Huang, Yongsong; Damste, Jaap S. Sinninghe; Hopmans, Ellen C.; Cohen, Andrew S. (Science, 2008)
The processes that control climate in the tropics are poorly understood. We applied compound-specific hydrogen isotopes (delta D) and the TEX(86) (tetraether index of 86 carbon atoms) temperature proxy to sediment cores from Lake Tanganyika to independently reconstruct precipitation and temperature variations during the past 60,000 years. Tanganyika temperatures follow Northern Hemisphere insolation and indicate that warming in tropical southeast Africa during the last glacial termination began to increase similar to 3000 years before atmospheric carbon dioxide concentrations. delta D data show that this region experienced abrupt changes in hydrology coeval with orbital and millennial-scale events recorded in Northern Hemisphere monsoonal climate records. This implies that precipitation in tropical southeast Africa is more strongly controlled by changes in Indian Ocean sea surface temperatures and the winter Indian monsoon than by migration of the Intertropical Convergence Zone.
id: 2047; PT: J; UT: WOS:000259902300046

Palaeoclimate - Tree rings floating on ice cores - Reimer, Paula J.; Hughen, Konrad A. (Nature Geoscience, 2008)
id: 1984; PT: J; UT: WOS:000256433500013

Radiocarbon evidence for the importance of surface vegetation on fermentation and methanogenesis in contrasting types of boreal peatlands - Chanton, J. P.; Glaser, P. H.; Chasar, L. S.; Burdige, D. J.; Hines, M. E.; Siegel, D. I.; Tremblay, L. B.; Cooper, W. T. (Global Biogeochemical Cycles, 2008)
We found a consistent distribution pattern for radiocarbon in dissolved organic carbon (DOC), dissolved inorganic carbon (DIC), and methane replicated across spatial and temporal scales in northern peatlands from Minnesota to Alaska. The (14)C content of DOC is relatively modern throughout the peat column, to depths of 3 m. In sedge-dominated peatlands, the (14)C contents of the products of respiration, CH(4) and DIC, are essentially the same and are similar to that of DOC. In Sphagnum- and woody plant-dominated peatlands with few sedges, however, the respiration products are similar but intermediate between the (14)C contents of the solid phase peat and the DOC. Preliminary data indicates qualitative differences in the pore water DOC, depending on the extent of sedge cover, consistent with the hypothesis that the DOC in sedge-dominated peatlands is more reactive than DOC in peatlands where Sphagnum or other vascular plants dominate. These data are supported by molecular level analysis of DOC by ultrahigh-resolution mass spectrometry that suggests more dramatic changes with depth in the composition of DOC in the sedge-dominated peatland pore waters relative to changes observed in DOC where Sphagnum dominates. The higher reactivity of DOC from sedge-dominated peatlands may be a function of either different source materials or environmental factors that are related to the abundance of sedges in peatlands.
id: 1949; PT: J; UT: WOS:000262041000002

A radiocarbon-based assessment of the preservation characteristics of crenarchaeol and alkenones from continental margin sediments - Mollenhauer, G.; Eglinton, T. I.; HopmanSd, E. C.; Damste, J. S. S. (Organic Geochemistry, 2008)
Crenarchaeotal glycerol dibiphytanyl glycerol tetraether (GDGT) lipids and alkenones are two types of biomarkers, derived from planktonic marine microorganisms, which are used for reconstruction of sea surface temperature. We determined the radiocarbon contents of the archaeal GDGT crenarchaeol and of alkenones isolated from continental margin sediments. Systematic differences were found between the two biomarkers, with higher radiocarbon content in crenarchaeol than in the phytoplankton-derived alkenones. These differences can be explained by variable contributions of pre-aged, laterally-advected material to the core sites. Crenarchaeol appears to be more efficiently degraded during transport in oxygen-replete environments than alkenones. Whether this reflects the influence of chemical structure or mode of protection (e.g., particle association) is not known. (C) 2008 Elsevier Ltd. All rights reserved.
id: 883; 344AQ Times Cited:11 Cited References Count:33Y

Relative sea-level change, Kjove Land, Scoresby Sund, East Greenland: implications for seasonality in Younger Dryas time - Hall, B.; Baroni, C.; Denton, G.; Kelly, M. A.; Lowell, T. (Quaternary Science Reviews, 2008)
The age of the Milne Land Stade (MLS) moraines in the Scoresby Sund region of East Greenland is key for testing the hypothesis that strong seasonality marked abrupt cooling events, such as the Younger Dryas, registered in Greenland ice cores. The relevant chronology is based on 69 radiocarbon dates of shells from raised beaches and deltas related to marine inundation and isostatic rebound that accompanied glacier retreat from the moraines. Taken together, these dates form the basis for a relative sea-level curve that shows very high rates of emergence typical of recently deglaciated regions. Upward extrapolation of this curve suggests that the marine limit (134 m a.s.l.) dates to about 12,400 cal yr B.R The shorelines that mark the marine limit lie within areas that were ice-covered when the glaciers were at the outer limit of the MLS advance; hence, the moraines that form the outer limit must antedate 12,400 cal yr B.R and probably are from earliest Younger Dryas or Allerod time. At Holger Danskes Briller, an inner moraine grades to a massive ice-contact delta, now at 101 m a.s.l., which is dated to 11,000-11,300 cal yr B.P. The age of the outer MLS moraines, along with constraints on the maximum possible Younger Dryas ice extent and snowline lowering are consistent with the idea that East Greenland climate experienced strong seasonality during Younger Dryas time. (C) 2008 Elsevier Ltd. All rights reserved.
id: 824; 389XX Times Cited:3 Cited References Count:43Y

Robust deterministic model describing the bomb radiocarbon signal for use in fish age validation - Hamel, O. S.; Piner, K. R.; Wallace, J. R. (Transactions of the American Fisheries Society, 2008)
The bomb radiocarbon chronometer has become a standard tool for assessing the accuracy of otolith-based fish age estimates. Use of the chronometer depends upon the increase in C-14 that occurred due to the atmospheric testing of nuclear weapons in the middle of the 20th century. In previous analyses, a variety of ad hoc methods have been used to compare test chronologies with reference chronologies. This paper proposes a deterministic coupled-functions model that describes bomb radiocarbon chronologies and standardizes and facilitates comparisons within and across species. In this model, a Gaussian pulse of radiocarbon over time is assumed, and dispersion and dilution are described by continuous exponential decay. The model simplifies to the product of a cumulative normal function and an exponential function; despite its simplicity, the model approximates the observed changes in oceanic radiocarbon quite well. It also allows for statistical testing of the timing of increase between different time series and thus permits quantitative aging validation as well as analysis of geographical differences in the timing of the bomb radiocarbon signal. Estimated model parameters describe the timing of the onset and temporal midpoint of the bomb-related increase in C-14 and the rate of C-14 dispersion or dilution, which corresponds to the observed rate of decline during the postbomb period. Nine published chronologies are used to demonstrate the model and compare it with other published methods of summarizing bomb radiocarbon data for age validation purposes.
id: 775; 306ZU Times Cited:2 Cited References Count:21Y

Subdecadally resolved paleoceanography of the Peru margin during the last two millennia - Agnihotri, R.; Altabet, M. A.; Herbert, T. D.; Tierney, J. E. (Geochemistry Geophysics Geosystems, 2008)
Using multiproxy sediment core data from the El Nino-Southern Oscillation (ENSO)-sensitive Peru margin, subdecadally resolved (down to similar to 0.6 year) surface productivity and subsurface denitrification are reconstructed for the last similar to 2300 years. Scanning XRF generated major elemental data (Ti, Fe, Si) correlate well with discrete inductively coupled plasma-atomic emission spectometry (ICP-AES) analyses and together with X-radiography (core density) are used as productivity indices. As surface productivity in this marine region is strongly impacted by ENSO, higher (lower) periods of surface productivity are inferred to represent a persistent normal/La Nina (El Nino)-like state. Surface productivity and subsurface denitrification appear to have remained intimately coupled during this period due to direct stimulation of requisite subsurface suboxia and/or hydrographic restructuring. The late Holocene Peru margin is characterized by persistent moderate productivity and subsurface denitrification punctuated at centennial scale by shorter-duration periods of high production and intense denitrification. These centennial-scale events are likely analogous to modern observations of decadal-scale "regime shifts'' but of higher amplitude and provide a background history for future natural changes to this system. Solar (irradiance) variability is suggested to have influenced Peru productivity as evidenced in numerous high-resolution paleorecords from the northern hemisphere.
id: 780; 303SA Times Cited:7 Cited References Count:54Y

Assessing environmental factors associated with changes in the growth rate of a bivalve mollusk species through the Holocene - Krause R.A, Jr.; Huntley, J. W.; Kowalewski, M.; Romanek, C. R.; Kaufmann, D. S.; Simoes, M. G. (First International Sclerochronology Conference, 2007)
id: 1169

Atlantic meridional overturning circulation during the Last Glacial Maximum - Lynch-Stieglitz, J.; Adkins, J. F.; Curry, W. B.; Dokken, T.; Hall, I. R.; Herguera, J. C.; Hirschi, J. J. M.; Ivanova, E. V.; Kissel, C.; Marchal, O.; Marchitto, T. M.; McCave, I. N.; et al. (Science, 2007)
The circulation of the deep Atlantic Ocean during the height of the last ice age appears to have been quite different from today. We review observations implying that Atlantic meridional overturning circulation during the Last Glacial Maximum was neither extremely sluggish nor an enhanced version of present-day circulation. The distribution of the decay products of uranium in sediments is consistent with a residence time for deep waters in the Atlantic only slightly greater than today. However, evidence from multiple water-mass tracers supports a different distribution of deep-water properties, including density, which is dynamically linked to circulation.
id: 1897; ISI Document Delivery No.: 153XD Times Cited: 46 Cited Reference Count: 61 Cited References: ADKINS JF, 1997, NATURE, V390, P154 ADKINS JF, 1999, RECONSTRUCTING OCEAN, P103 ADKINS JF, 2003, EARTH PLANET SC LETT, V216, P109, DOI 10.1016/S0012-821X(03)00502-8 BACON MP, 1982, J GEOPHYS RES, V87, P2045 BICKERT T, 2004, S ATLANTIC LATE QUAT, P671 BOYLE EA, 1982, SCIENCE, V218, P784 BROECKER W, 1988, RADIOCARBON, V30, P261 CHASE Z, 2002, EARTH PLANET SC LETT, V204, P215 CLARK PU, 2002, NATURE, V415, P863 CONKRIGHT ME, 2002, WORLD OCEAN ATLAS 20 CURRY WB, 1982, QUATERNARY RES, V18, P218 CURRY WB, 2005, PALEOCEANOGRAPHY, V20, ARTN PA1017 DUPIESSY JC, 1980, NATURE, V286, P479 DUPLESSY JC, 1988, PALEOCEANOGRAPHY, V3, P343 DUPLESSY JC, 1989, RADIOCARBON, V31, P493 ELDERFIELD H, 2006, EARTH PLANET SC LETT, V250, P633, DOI 10.1016/j.epsl.2006.07.041 EMILIANI C, 1955, J GEOL, V63, P538 GANACHAUD A, 2000, NATURE, V408, P453 GEBBIE G, 2006, GEOCHEM GEOPHY GEOSY, V7, ARTN Q11N07 GHERARDI JM, 2005, EARTH PLANET SC LETT, V240, P710, DOI 10.1016/j.epsl.2005.09.061 HALL IR, 2006, GEOPHYS RES LETT, V33, ARTN L16616 HALL MM, 1982, DEEP-SEA RES, V29, P339 HEWITT CD, 2003, CLIM DYNAM, V20, P203, DOI 10.1007/s00382-002-0272-6 HIRSCHI JJM, 2006, GEOCHEM GEOPHY GEOSY, V7, ARTN Q10N04 HUYBERS P, 2007, J PHYS OCEANOGR, V37, P394, DOI 10.1175/JPO3018.1 KEIGWIN LD, 2004, PALEOCEANOGRAPHY, V19, ARTN PA4012 KISSEL C, 1999, EARTH PLANET SC LETT, V171, P489 KITOH A, 2001, GEOPHYS RES LETT, V28, P2221 KUCERA M, 2005, QUATERNARY SCI REV, V24, P951, DOI 10.1016/j.quascirev.2004.07.014 KUMAR N, 1993, NATURE, V362, P45 LEGRAND P, 1995, PALEOCEANOGRAPHY, V10, P1011 LEGRANDE AN, 2006, P NATL ACAD SCI USA, V103, P837 LYNCHSTIEGLITZ J, 1999, PALEOCEANOGRAPHY, V14, P360 LYNCHSTIEGLITZ J, 2001, GEOCHEM GEOPHY GEOSY, V2, DOI 10.1029/2001GC000208 LYNCHSTIEGLITZ J, 2003, TREATISE GEOCHEMISTR, V6, P433 LYNCHSTIEGLITZ J, 2006, GEOCHEM GEOPHY GEOSY, V7, ARTN Q10N03 MANABE S, 1988, J CLIMATOL, V1, P841 MANGINI A, 1998, NATURE, V392, P347 MARCHAL O, 2000, PALEOCEANOGRAPHY, V15, P625 MARCHITTO TM, 2000, PALEOCEANOGRAPHY, V15, P299 MARCHITTO TM, 2006, GEOCHEM GEOPHY GEOSY, V7, ARTN Q12003 MAROTZKE J, 1999, J GEOPHYS RES-OCEANS, V104, P29529 MATSUMOTO K, 1999, PALEOCEANOGRAPHY, V14, P149 MCCAVE IN, 2006, GEOCHEM GEOPHY GEOSY, V7, ARTN Q10N05 MCMANUS JF, 2004, NATURE, V428, P834, DOI 10.1038/nature02494 MIX AC, 2001, QUATERNARY SCI REV, V20, P627 OTTOBLIESNER BL, 2006, J CLIMATE, V19, P2526 PAUL A, 2003, PALEOCEANOGRAPHY, V18, ARTN 1058 PIOTROWSKI AM, 2005, SCIENCE, V307, P1933, DOI 10.1126/science.1104883 ROBINSON LF, 2005, SCIENCE, V310, P1469, DOI 10.1126/science.1114832 ROEMMICH D, 1985, DEEP-SEA RES, V32, P619 SARNTHEIN M, 1994, PALEOCEANOGRAPHY, V9, P209 SCHMITTNER A, 2005, GLOBAL BIOGEOCHEM CY, V19, ARTN GB3004 SHACKLETON NJ, 1988, NATURE, V335, P708 SHIN SI, 2003, CLIM DYNAM, V20, P127, DOI 10.1007/s00382-002-0260-x STOMMEL H, 1961, TELLUS, V13, P224 STREETER SS, 1979, SCIENCE, V203, P168 VELLINGA M, 2002, CLIMATIC CHANGE, V54, P251 WUNSCH C, 2003, QUATERNARY SCI REV, V22, P371 YU EF, 1996, NATURE, V379, P689 ZHANG R, 2005, J CLIMATE, V18, P1853 Lynch-Stieglitz, Jean Adkins, Jess F. Curry, William B. Dokken, Trond Hall, Ian R. Herguera, Juan Carlos Hirschi, Joel J. -M. Ivanova, Elena V. Kissel, Catherine Marchal, Olivier Marchitto, Thomas M. McCave, I. Nicholas McManus, Jerry F. Mulitza, Stefan Ninnemann, Ulysses Peeters, Frank Yu, Ein-Fen Zahn, Rainer Amer assoc advancement science Washington; YY

Century-to-millennial scale climatic variability in Lake Malawi revealed by isotope records - Barker, P. A.; Leng, M. J.; Gasse, F.; Huang, Y. (Earth and Planetary Science Letters, 2007)
Diatom-based oxygen isotope data ( delta super(1) super(8)O sub(d) sub(i) sub(a) sub(t) sub(o) sub(m)) from Lake Malawi show multi-centennial scale wet-dry intervals spaced approximately every 2.3 ka throughout a 25 ka sequence. The delta super(1) super(8)O sub(d) sub(i) sub(a) sub(t) sub(o) sub(m) record is supported by a lower resolution deuterium ( delta D sub(p) sub(a))isotope curve derived from palmitic acid. We interpret these isotope data in terms of major shifts in precipitation and evaporation moderated by seasonal controls on the host organisms. Dry periods marked by relatively positive isotope values, represent the extension of abrupt Holocene events noted from northern and equatorial Africa to 10-15 super(o)S. These events in Lake Malawi correspond to cool episodes in Greenland, thereby demonstrating teleconnections generated by meridional temperature gradients. Sea surface temperatures are likely to be the primary transmitter of deglacial climate changes, although trade wind strength and direction is critical in controlling precipitation patterns in tropical regions. Conversely, the global hydrological cycle, driven by low latitude regions represents an important positive feedback amplifying deglacial processes.
id: 2222; Source type: scholarlyjournals; Object type: Article; Object type: Feature; CSAUnique: OB-MD-0006626237; AccNum: 7631572; DOI: 10.1016/j.epsl.2007.06.010; ISSN: 0012-821X; Peer Reviewed: true

Computer simulation of MC-SNICS for performance improvements - Han, B. X.; Southon, J. R.; Roberts, M. L.; von Reden, K. F. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2007)
Increasing ion source current output while keeping the beam emittance small is a key for improving measurement throughput and quality of an accelerator mass spectrometry (AMS) system. The NEC MC-SNICS ion sources have widely been used for AMS around the world. In this work, a computer simulation study on MC-SNICS ion source was carried out using the code PBGUNS. The primary Cs+ beam is simulated as space-charge limited emission from the ionizer surface. The secondary negative ion beam is simulated in the presence of the space-charge induced by both the primary and the secondary beam. Two different configurations of the MC-SNICS have been studied: the original factory version and the UC Irvine modified version. The latter has a 0.668 in. radius spherical ionizer and an immersion lens at cathode potential with the original Cs focus lens removed. Simulation showed that the modified version provides more intense and better focused Cs+ beam at the cathode target, hence higher negative ion production from the sample by sputtering. The new arrangement of Einzel-preacceleration section of the MC-SNICS at UC Irvine was also simulated and discussed. Simulation results are in good agreement with the experimental observations made at UC Irvine. Hints for selection of an immersion lens geometry have been obtained. (c) 2007 Elsevier B.V. All rights reserved.
200swTimes Cited:8Cited References Count:8

Electromagnetic field modeling and ion optics calculations for a continuous-flow AMS system - Han, B. X.; von Reden, K. F.; Roberts, M. L.; Schneider, R. J.; Hayes, J. M.; W. J. Jenkins (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2007)
A continuous-flow C-14 AMS (CFAMS) system is under construction at the NOSAMS facility. This system is based on a NEC Model 1.5SDH-10.5 MV Pelletron accelerator and will utilize a combination of a microwave ion source (MIS) and a charge exchange canal (CXC) to produce negative carbon ions from a continuously flowing stream Of CO2 gas. For high-efficiency transmission of the large emittance, large energy-spread beam from the ion source unit, a large-acceptance and energy-achromatic injector consisting of a 45 degrees electrostatic spherical analyzer (ESA) and a 90 degrees double-focusing magnet has been designed. The 45 degrees ESA is rotatable to accommodate a 134-sample MC-SNICS as a second ion source. The high-energy achromat (90 degrees double focusing magnet and 90 degrees ESA) has also been customized for large acceptance. Electromagnetic field modeling and ion optics calculations of the beamline were done with Infolytica MagNet, ElecNet, and Trajectory Evaluator. PBGUNS and SIMION were used for the modeling of ion source unit. (c) 2007 Elsevier B.V. All rights reserved.
id: 1698; 182WV Times Cited:6 Cited References Count:14

Flux and age of dissolved organic carbon exported to the Arctic Ocean: A carbon isotopic study of the five largest arctic rivers RID C-4087-2009 RID C-5396-2008 - Raymond, Peter A.; McClelland, J. W.; Holmes, R. M.; Zhulidov, A. V.; Mull, K.; Peterson, B. J.; Striegl, R. G.; Aiken, G. R.; Gurtovaya, T. Y. (Global Biogeochemical Cycles, 2007)
The export and Delta C-14-age of dissolved organic carbon (DOC) was determined for the Yenisey, Lena, Ob', Mackenzie, and Yukon rivers for 2004 - 2005. Concentrations of DOC elevate significantly with increasing discharge in these rivers, causing approximately 60% of the annual export to occur during a 2-month period following spring ice breakup. We present a total annual flux from the five rivers of similar to 16 teragrams (Tg), and conservatively estimate that the total input of DOC to the Arctic Ocean is 25 - 36 Tg, which is similar to 5-20% greater than previous fluxes. These fluxes are also similar to 2.5 x greater than temperate rivers with similar watershed sizes and water discharge. Delta C-14-DOC shows a clear relationship with hydrology. A small pool of DOC slightly depleted in Delta C-14 is exported with base flow. The large pool exported with spring thaw is enriched in D14C with respect to current-day atmospheric Delta C-14-CO2 values. A simple model predicts that similar to 50% of DOC exported during the arctic spring thaw is 1 - 5 years old, similar to 25% is 6 - 10 years in age, and 15% is 11 - 20 years old. The dominant spring melt period, a historically undersampled period, exports a large amount of young and presumably semilabile DOC to the Arctic Ocean.
id: 2033; PT: J; UT: WOS:000250704000002

Holocene Reworking of a Sand Sheet in the Merrimack Embayment, Western Gulf of Maine - Hein, C. J.; FitzGerald, D. M.; Barnhardt, W. (Journal of Coastal Research, 2007)
Recent bathymetric, backscatter, and seafloor sediment samples demonstrate that a large sand sheet was formed in the inner shelf by the reworking of the Merrimack River lowstand delta (deposited 12 kya; currently at 45 m depth) and braid plain during the Holocene transgression. Asymmetric bedforms and distinct grain size distributions suggest the sand sheet is actively being reworked by inner-shelf processes.Bottom sediments range from silty sand at the submerged delta to coarse sand and fine gravel in the innermost shelf (depth: 10-50 m). Coarse-grained sand comprises an expansive (32 km(2)) featureless sand sheet centered off the Merrimack River. Fine-grained sand discontinuously overlies this sand sheet in many locations and forms long wavelength (100 - 800 m), low amplitude (1-2 m), asymmetrical bedforms. Sets of these bedforms are oriented from slightly oblique offshore to onshore; several bedform sets are located within I km and oriented orthogonally to one another. Along the paleo-delta front north-northwest oriented bedforms are dominant. Inshore of these features, the bedforms become more closely spaced and have orientations to the west and west-southwest. Preliminary data suggest that the combined forces of instantaneous storm-wave generated shear stress and storm-induced currents associated with high energy northeast storm events may be responsible for sand sheet reworking and bedform development.
Sp. Iss. 50V16hi Times Cited:2 Cited References Count:22
Keywords: backscatter; bedforms; shallow seismic; shelf sediment transport

Holocene sea-level oscillations and environmental changes on the Eastern Black Sea shelf - Ivanova, E. V.; Murdmaa, I. O.; Chepalyga, A. L.; Cronin, T. M.; Pasechnik, I. V.; Levchenko, O. V.; Howe, S. S.; Manushkina, A. V.; Platonova, E. A. (Palaeogeography Palaeoclimatology Palaeoecology, 2007)
A multi-proxy study of four sediment cores from the Eastern (Caucasian) Black Sea shelf revealed five transgressive-regressive cycles overprinted on the general trend of glacioeustatic sea-level rise during the last 11,000 C-14 yr. These cycles are well represented in micro-and macrofossil assemblages, sedimentation rates, and gain size variations. The oldest recovered sediments were deposited in the Neoeuxinian semi-freshwater basin (similar to 10,500-9000 C-14 yr BP) and contain a Caspian-type mollusk fauna dominated by Dreissena rostriformis. Low delta O-18 and delta C-13 values are measured on this species. The first appearance of marine mollusks and ostracodes from the Mediterranean is established in this part of the Black Sea at similar to 8200 C-14 yr BP, i.e., about 1000-2000 yr later than the appearance of marine microfossils in the deeper part of the sea. The Early Holocene (Bugazian to Vityazevian) condensed section of shell and shelly mud sediments with at least two hiatuses represent a high-energy shelf-edge facies. It contains a transitional assemblage representing a mixture of Caspian and Mediterranean fauna. This pattern suggests a dual-flow regime via the Bosphorus after 8200 C-14 yr BR Caspian species disappear and oligolialine species decrease in abundance during the Vityazevian-Prekalamitian cycle. Later, during the Middle to Late Holocene, low sea-level stands are characterized by shell layers, whereas silty mud with various mollusk and ostracode assemblages rapidly accumulated during transgressions. Restricted mud accumulation, as well as benthic faunal composition and abundance, suggest high-energy and well-ventilated bottom water during low sea-level stands. A trend of O-18 enrichment in mollusk shells points to an increase in bottom-water salinity during the Vityazevian to Kalamitian transgressions (similar to 7000 to 5700 C-14 yr BP) due to a more open connection with the Mediterranean, while a pronounced increase in polyhaline species abundance is established during the Kalamitian to Djemetean transgressions (similar to 6400 to 2700 C-14 yr BP). However, the composition of the faunal assemblage indicates that bottom-water salinity never exceeded modem values of 18-20 psu. (c) 2006 Elsevier B.V. All rights reserved.
156gzTimes Cited:22Cited References Count:51

Last millennia sedimentary record on a micro-tidal, low-accumulation prodelta (Tet NW Mediterranean) - Bourrin, F.; Monaco, A.; Aloisi, J. C.; Sanchez-Cabeza, J. A.; Lofi, J.; Heussner, S.; de Madron, X. D.; Jeanty, G.; Buscail, R.; Saragoni, G. (Marine Geology, 2007)
Statistical sequential analysis was performed on a series of sediment cores collected from the Tet prodelta in the Gulf of Lions, northwestern Mediterranean Sea, between October 2003 and October 2004. Seabed changes during that period were correlated to hydrodynamic conditions (waves and currents) and river discharge. Low sediment supply prevents full preservation of new sediment strata on this low-accumulation prodelta located on a microtidal, storm-dorninated inner shelf. Severe meteorological events caused a rapid succession of erosion and deposition phases. For example, the December 2003 flood and storm produced a flood layer deposit that persisted for 2 months with only slight transformations due to early diagenesis and/or bioturbation, until a new, storm event eroded this layer. A typical sedimentary sequence was observed for the secular deposits composed of a 10-cm-thick sandy layer overlaying siltyclayey layers. These characteristic features were used to analyse the last millennia sedimentary record of the Tet prodelta. The low preservation of freshly deposited sediments and variable sedimentation rates during the last millennia period yield a sedimentary sequence formed by the outcropping of muddy prodeltaic units intersected by heterogeneous siltysandy units similar to those formed under present day hydrodynamic conditions. No flood layer was found related to catastrophic flooding of the last century in the sedimentary record. The Little lee Age (similar to 1550-1850 AD) probably favoured the formation of a well-developed muddy prodelta in the mouth of the Tet River. Later on, the decrease of sediment supply by rivers due to climate change and/or human activities (damming, irrigation), and the increase of the number of high-energy storms reaching the coast, induced a coarsening of the top sediment layer on this prodelta. This modem change of the substrate is also observed in the composition of benthic biota found in the substrate. (c) 2007 Elsevier B.V All rights reserved.
id: 1904; 210TU Times Cited:8 Cited References Count:68Y

Late Holocene barrier island collapse; Outer Banks, North Carolina, USA - Culver, Stephen J.; Grand Pre, Candace A.; Mallinson, David J.; Riggs, Stanley R.; Corbett, D. Reide; Foley, Jennifer; Hale, Michael; Metger, Lauren; Ricardo, John; Rosenberger, Jeb; Smith, Christopher G.; Smith, Curtis W.; et al. (The Sedimentary Record, 2007)
We document here the threat of large scale destruction (collapse) of barrier islands based on the study of many cores taken along the Outer Banks and in Pamlico Sound, North Carolina.Around 1,100 cal yr BP, probably as the result of hurricane activity, portions of the southern Outer Banks must have collapsed to allow normal salinity waters to bathe southern Pamlico Sound for several hundred years. Such collapse could occur again during our current regime of global warming, rising sea level and increased tropical cyclone activity. The economic effect of barrier island break collapse on Outer Banks communities would be devastating.
id: 1887; ISSN: 1543-8740 Language: English References: 16; illus. incl. strat. col., geol. sketch map United States (USA) Latitude:N350000,N353000 Longitude:W0753000,W0760000
Keywords: 24, Quaternary geology; algae; assemblages; barrier islands; Cenozoic; changes; clastic sediments; cores; diatoms; erosion; Foraminifera; geologic hazards; Holocene; hurricanes; Invertebrata; landform evolution; lithofacies; littoral; microfossils; North Carolina; Outer Banks; Pamlico Sound; Plantae; preservation; Protista; Quaternary; salinity; sand; sea-level; sediments; United States; upper Holocene; Vibroseis

Late quaternary lake and swamp sediments: records of climate and environment - Horn, S. P. (Central America: Geology, Resources, Hazards, 2007)
id: 622

A late-glacial transition from Picea glauca to Picea mariana in southern New England - Lindbladh, M.; Oswald, W. W.; Foster, D. R.; Faison, E. K.; Hou, J. Z.; Huang, Y. S. (Quaternary Research, 2007)
Picea is an important taxon in late-glacial pollen records from eastern North America, but little is known about which species of Picea were present. We apply a recently developed palynological method for discriminating the three Picea species in eastern North America to three records from New England. Picea glauca was dominant at similar to 14,500-14,000 cal yr BP, followed by a transition to Picea mariana between similar to 14,000 and 13,500 cal yr BP. Comparison of the pollen data with hydrogen isotope data shows clearly that this transition began before the beginning of the Younger Dryas Chronozone. The ecological changes of the late-glacial interval were not a simple oscillation in the position of a single species' range, but rather major changes in vegetation structure and composition occurring during an interval of variations in several environmental factors, including climate, edaphic conditions, and atmospheric CO2 levels. (c) 2007 University of Washington. All rights reserved.
id: 1841; 160RU Times Cited:5 Cited References Count:61Y

Placing late Neanderthals in a climatic context RID A-5197-2008 - Tzedakis, P. C.; Hughen, K. A.; Cacho, I.; Harvati, K. (Nature, 2007)
Attempts to place Palaeolithic finds within a precise climatic framework are complicated by both uncertainty over the radiocarbon calibration beyond about 21,500 (14)C years BP(1) and the absence of a master calendar chronology for climate events from reference archives such as Greenland ice cores or speleothems(2). Here we present an alternative approach, in which (14)C dates of interest are mapped directly onto the palaeoclimate record of the Cariaco Basin by means of its (14)C series(3), circumventing calendar age model and correlation uncertainties, and placing dated events in the millennial-scale climate context of the last glacial period. This is applied to different sets of dates from levels with Mousterian artefacts, presumably produced by late Neanderthals, from Gorham's Cave in Gibraltar: first, generally accepted estimates of about 32,000 (14)C years BP for the upper-most Mousterian levels(4,5); second, a possible extended Middle Palaeolithic occupation until about 28,000 (14)C years BP(6); and third, more contentious evidence for persistence until about 24,000 (14)C years BP(6). This study shows that the three sets translate to different scenarios on the role of climate in Neanderthal extinction. The first two correspond to intervals of general climatic instability between stadials and interstadials that characterized most of the Middle Pleniglacial and are not coeval with Heinrich Events. In contrast, if accepted, the youngest date indicates that late Neanderthals may have persisted up to the onset of a major environmental shift, which included an expansion in global ice volume and an increased latitudinal temperature gradient. More generally, our radiocarbon climatostratigraphic approach can be applied to any 'snapshot' date from discontinuous records in a variety of deposits and can become a powerful tool in evaluating the climatic signature of critical intervals in Late Pleistocene human evolution.
id: 1991; PT: J; UT: WOS:000249394500047

Post-glacial changes in spatial patterns of vegetation across southern New England - Oswald, W. W.; Faison, E. K.; Foster, D. R.; Doughty, E. D.; Hall, B. R.; Hansen, B. C. S. (Journal of Biogeography, 2007)
Aim We analysed lake-sediment pollen records from eight sites in southern New England to address: (1) regional variation in ecological responses to post-glacial climatic changes, (2) landscape-scale vegetational heterogeneity at different times in the past, and (3) environmental and ecological controls on spatial patterns of vegetation. Location The eight study sites are located in southern New England in the states of Massachusetts and Connecticut. The sites span a climatic and vegetational gradient from the lowland areas of eastern Massachusetts and Connecticut to the uplands of north-central and western Massachusetts. Tsuga canadensis and Fagus grandifolia are abundant in the upland area, while Quercus, Carya and Pinus species have higher abundances in the lowlands. Methods We collected sediment cores from three lakes in eastern and north-central Massachusetts (Berry East, Blood and Little Royalston Ponds). Pollen records from those sites were compared with previously published pollen data from five other sites. Multivariate data analysis (non-metric multi-dimensional scaling) was used to compare the pollen spectra of these sites through time. Results Our analyses revealed a sequence of vegetational responses to climate changes occurring across southern New England during the past 14,000 calibrated radiocarbon years before present (cal yr BP). Pollen assemblages at all sites were dominated by Picea and Pinus banksiana between 14,000 and 11,500 cal yr BP; by Pinus strobus from 11,500 to 10,500 cal yr BP; and by P. strobus and Tsuga between 10,500 and 9500 cal yr BP. At 9500-8000 cal yr BP, however, vegetation composition began to differentiate between lowland and upland sites. Lowland sites had higher percentages of Quercus pollen, whereas Tsuga abundance was higher at the upland sites. This spatial heterogeneity strengthened between 8000 and 5500 cal yr BP, when Fagus became abundant in the uplands and Quercus pollen percentages increased further in the lowland records. The differentiation of upland and lowland vegetation zones remained strong during the mid-Holocene Tsuga decline (5500-3500 cal yr BP), but the pattern weakened during the late-Holocene (3500-300 cal yr BP) and European-settlement intervals. Within-group similarity declined in response to the uneven late-Holocene expansion of Castanea, while between-group similarity increased due to homogenization of the regional vegetation by forest clearance and ongoing disturbances. Main conclusions The regional gradient of vegetation composition across southern New England was first established between 9500 and 8000 cal yr BP. The spatial heterogeneity of the vegetation may have arisen at that time in response to the development or strengthening of the regional climatic gradient. Alternatively, the differentiation of upland and lowland vegetation types may have occurred as the climate ameliorated and an increasing number of species arrived in the region, arranging themselves in progressively more complex vegetation patterns across relatively stationary environmental gradients. The emergence of a regional vegetational gradient in southern New England may be a manifestation of the increasing number of species and more finely divided resource gradient.
id: 1840; 157BN Times Cited:5 Cited References Count:70Y

Progress on a gas-accepting ion source for continuous-flow accelerator mass spectrometry - Roberts, M. L.; Schneider, R. J.; von Reden, K. F.; Wills, J. S. C.; Han, B. X.; Hayes, J. M.; Rosenheim, B. E.; W. J. Jenkins (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2007)
A gas-accepting microwave-plasma ion source is being developed for continuous-flow accelerator mass spectrometry (AMS). Characteristics of the ion source will be presented. Schemes for connecting a gas or liquid chromatograph to the ion source will also be discussed. (c) 2007 Ellsevier B.V. All rights reserved.
182wvTimes Cited:24Cited References Count:12

Radiocarbon age of late glacial deep water from the equatorial Pacific - Broecker, W.; Clark, E.; Barker, S.; Hajdas, I.; Bonani, G.; Moreno, E. (Paleoceanography, 2007)
Radiocarbon age differences for pairs of coexisting late glacial age benthic and planktic foraminifera shells handpicked from 10 sediment samples from a core from a depth of 2.8 km in the western equatorial Pacific are not significantly different from that of 1600 years calculated from measurements on prenuclear seawater. This places a lower limit on the depth of the interface for the hypothetical radiocarbon-depleted glacial age seawater reservoir required to explain the 190% drop in the (14)C/C for atmospheric CO(2), which occurred during the mystery interval (17.5 to 14.5 calendar years ago). These measurements restrict the volume of this reservoir to be no more than 35% that of the ocean. Further, (14)C measurements on a single Last Glacial Maximum age sample from a central equatorial Pacific core from a depth of 4.4 km water fail to reveal evidence for the required 5- to 7-kyr age difference between benthic and planktic foraminifera shells if the isolated reservoir occupied only one third of the ocean. Nor does the (13)C record for benthic forams from this abyssal core yield any evidence for the excess respiration CO(2) expected to be produced during thousands of years of isolation. Nor, as indicated by the presence of benthic foraminifera, was the dissolved oxygen used up in this abyssal water.
id: 413; 165MC Times Cited:10 Cited References Count:18

Radiocarbon age offsets of foraminifera resulting from differential dissolution and fragmentation within the sedimentary bioturbated zone - Barker, Stephen; Broecker, Wallace; Clark, Elizabeth; Hajdas, Irka (Paleoceanography, 2007)
Shells of coexisting species of planktonic foraminifera from the Ontong Java Plateau reveal radiocarbon age offsets of up to 2200 years. Similar offsets are found between fragments and whole shells of single species. Steady state modelling of dissolution and bioturbation within the sedimentary mixed layer predicts age differences of up to several kiloyears due to the interplay between differential dissolution and fragmentation of foraminifer shells and bioturbation. The observation that fragile foraminiferal shells are systematically older than those of more robust species is more difficult to explain. Mechanisms of chemical erosion, interface dissolution, and sediment redistribution are all apparently unable to explain this phenomenon. A possible solution is presented in which a particular species may be represented by two distinct classes of shells which are more or less robust. In this case, differential dissolution and fragmentation causes an increase in the mean age as the fragile class contributes less to the remaining intact shells. This study highlights the vulnerability of low sedimentation rate cores to the effects of dissolution and bioturbation.
id: 1920; PT: J; UT: WOS:000246308600002

Radiocarbon dating of deep-sea sediments - Hughen, K. A. (Paleoceanography of the Late Cenozoic, 2007)
id: 552

Rapid sea level rise and ice sheet response to 8,200-year climate event - Cronin, T. M.; Vogt, P. R.; Willard, D. A.; Thunell, R.; Halka, J.; Berke, M.; Pohlman, J. (Geophysical Research Letters, 2007)
The largest abrupt climatic reversal of the Holocene interglacial, the cooling event 8.6 - 8.2 thousand years ago (ka), was probably caused by catastrophic release of glacial Lake Agassiz-Ojibway, which slowed Atlantic meridional overturning circulation (AMOC) and cooled global climate. Geophysical surveys and sediment cores from Chesapeake Bay reveal the pattern of sea level rise during this event. Sea level rose similar to 14 m between 9.5 to 7.5 ka, a pattern consistent with coral records and the ICE- 5G glacio-isostatic adjustment model. There were two distinct periods at similar to 8.9 - 8.8 and similar to 8.2 - 7.6 ka when Chesapeake marshes were drown as sea level rose rapidly at least similar to 12 mm yr(-1). The latter event occurred after the 8.6 - 8.2 ka cooling event, coincided with extreme warming and vigorous AMOC centered on 7.9 ka, and may have been due to Antarctic Ice Sheet decay.
id: 810; 225MA Times Cited:4 Cited References Count:32Y

Response of vegetation and fire to Little Ice Age climate change: regional continuity and landscape heterogeneity - Hotchkiss, S. C.; Calcote, R.; Lynch, E. A. (Landscape Ecology, 2007)
Late-Holocene climatic conditions in the upper Great Lakes region have changed sufficiently to produce significant changes in vegetation and fire regimes. The objective of this study was to determine how the vegetation mosaic and fire regimes on an oak (Quercus spp.)- and pine (Pines spp.)-dominated sand plain in northwestern Wisconsin responded to climatic changes of the past 1,200 years. We used pollen and charcoal records from a network of sites to investigate the range of natural variability of vegetation on a 1,500-km(2) landscape on the southern part of the sand plain. A major vegetation shift from jack pine (Pines banksiana) and red pine (P. resinosa) to increased abundance of white pine (P. strobus) occurred between 700 and 600 calendar years before present (cal yr BP), apparently corresponding to more mesic conditions regionally. A decrease in charcoal accumulation rate also occurred at most sites but was not synchronous with the vegetation change. At some sites there were further changes in vegetation and fire regimes occurring similar to 500-300 cal yr BP, but these changes were not as strong or unidirectional as those that occurred 700-600 cal yr BP. Our results suggest that both the composition and the distribution of vegetation of the southern part of the sand plain have been sensitive to relatively small climatic changes, and that the vegetation at the time of European settlement was a transitory phenomenon, rather than a long-term stable condition.
Suppl. 1239unTimes Cited:25Cited References Count:92

Sea level rise in Tampa Bay - Cronin, Thomas M.; Edgar, N. Terence; Brooks, Gregg; Hastings, David; Larson, Rebekka; Hine, Albert; Locker, Stanley; Suthard, Beau; Flower, Benjamin; Hollander, David; Wehmiller, John; Willard, Debra A.; et al. (Eos, Transactions, American Geophysical Union, 2007)
id: 1899; References: 14; illus. incl. geol. sketch map Latitude:N272700,N280200 Longitude:W0822200,W0825100Y

Searching for a suitable gas ion source for C-14 accelerator mass spectrometry - von Reden, K.; Roberts, M.; Han, B.; Schneider, R.; Wills, J. (Preceeding of PNNIB-11 (9/2006), 2007)
id: 689

Source apportionment of atmospheric PAHs in the western Balkans by natural abundance radiocarbon analysis - Zencak, Zdenek; Klanova, Jana; Holoubek, Ivan; Gustafsson, Örjan (Environmental Science and Technology, 2007)
id: 519

Strandplain evolution along the southern coast of Santa Caterina, Brazil - FitzGerald, D. M.; Cleary, W. J.; Buynevich, I. V.; Hein, C. J.; Kleins, A. H. F.; Asp, N.; Angulo, R. (Journal of Coastal Research, 2007)
id: 1099

A study of secondary organic aerosol formation in the anthropogenic-influenced southeastern United States - Weber, R. J.; Sullivan, A. P.; Peltier, R. E.; Russell, A.; Yan, B.; Zheng, M.; de Gouw, J.; Warneke, C.; Brock, C.; Holloway, J. S.; Atlas, E. L.; Edgerton, E. (Journal of Geophysical Research-Atmospheres, 2007)
[1] The formation of secondary organic aerosol (SOA) in an anthropogenic-influenced region in the southeastern United States is investigated by a comparison with urban plumes in the northeast. The analysis is based on measurements of fine-particle organic compounds soluble in water (WSOC) as a measure of secondary organic aerosol. Aircraft measurements over a large area of northern Georgia, including the Atlanta metropolitan region, and in plumes from New York City and surrounding urban regions in the northeast show that fine-particle WSOC are spatially correlated with vehicle emission tracers (e.g., CO), yet the measurements indicate that vehicles do not directly emit significant particulate WSOC. In addition to being correlated, WSOC concentrations were in similar proportions to anthropogenic tracers in both regions, despite biogenic volatile organic compounds (VOCs) that were on average 10-100 times higher over northern Georgia. In contrast, radiocarbon analysis on WSOC extracted from integrated filters deployed in Atlanta suggests that roughly 70-80% of the carbon in summertime WSOC is modern. If both findings are valid, the combined results indicate that in northern Georgia, fine-particle WSOC was secondary and formed through a process that involves mainly modern biogenic VOCs but which is strongly linked to an anthropogenic component that may largely control the mass of SOA formed. Independent of the radiocarbon results, a strong association between SOA and anthropogenic sources has implications for control strategies in urban regions with large biogenic VOC emissions.
id: 788; 187XB Times Cited:47 Cited References Count:39Y

A study of secondary organic aerosol formation in the anthropogenic-influenced southeastern United States - Weber, R. J.; Sullivan, A. P.; Peltier, R. E.; Russell, A.; Yan, B.; Zheng, M.; de Gouw, J.; Warneke, C.; Brock, C.; Holloway, J. S.; Atlas, E. L.; Edgerton, E. (Journal of Geophysical Research-Atmospheres, 2007)
[1] The formation of secondary organic aerosol (SOA) in an anthropogenic-influenced region in the southeastern United States is investigated by a comparison with urban plumes in the northeast. The analysis is based on measurements of fine-particle organic compounds soluble in water (WSOC) as a measure of secondary organic aerosol. Aircraft measurements over a large area of northern Georgia, including the Atlanta metropolitan region, and in plumes from New York City and surrounding urban regions in the northeast show that fine-particle WSOC are spatially correlated with vehicle emission tracers (e.g., CO), yet the measurements indicate that vehicles do not directly emit significant particulate WSOC. In addition to being correlated, WSOC concentrations were in similar proportions to anthropogenic tracers in both regions, despite biogenic volatile organic compounds (VOCs) that were on average 10-100 times higher over northern Georgia. In contrast, radiocarbon analysis on WSOC extracted from integrated filters deployed in Atlanta suggests that roughly 70-80% of the carbon in summertime WSOC is modern. If both findings are valid, the combined results indicate that in northern Georgia, fine-particle WSOC was secondary and formed through a process that involves mainly modern biogenic VOCs but which is strongly linked to an anthropogenic component that may largely control the mass of SOA formed. Independent of the radiocarbon results, a strong association between SOA and anthropogenic sources has implications for control strategies in urban regions with large biogenic VOC emissions.
263D13302
Keywords: AMBIENT AEROSOL; atmosphere; C-14; emissions; evolution; GASOLINE; OXIDATION; PARTICLES; RATIOS; ZURICH

Is there a thorium-230 deficit in Arctic sediments? - Hoffmann, S. S.; McManus, J. F. (Earth and Planetary Science Letters, 2007)
id: 711

Tropical Pacific - mid-latitude teleconnections in medieval times - Graham, N. E.; Hughes, M. K.; Ammann, C. M.; Cobb, K. M.; Hoerling, M. P.; Kennett, D. J.; Kennett, J. P.; Rein, B.; Stott, L.; Wigand, P. E.; Xu, T. Y. (Climatic Change, 2007)
Terrestrial and marine late Holocene proxy records from the western and central US suggest that climate between approximately 500 and 1350 A.D. was marked by generally arid conditions with episodes of severe centennial-scale drought, elevated incidence of wild fire, cool sea surface temperatures (SSTs) along the California coast, and dune mobilization in the western plains. This Medieval Climate Anomaly (MCA) was followed by wetter conditions and warming coastal SSTs during the transition into the "Little Ice Age" (LIA). Proxy records from the tropical Pacific Ocean show contemporaneous changes indicating cool central and eastern tropical Pacific SSTs during the MCA, with warmer than modern temperatures in the western equatorial Pacific. This pattern of mid-latitude and tropical climate conditions is consistent with the hypothesis that the dry MCA in the western US resulted (at least in part) from tropically forced changes in winter NH circulation patterns like those associated with modern La Nina episodes. We examine this hypothesis, and present other analyses showing that the imprint of MCA climate change appears in proxy records from widely distributed regions around the planet, and in many cases is consistent with a cool medieval tropical Pacific. One example, explored with numerical model results, is the suggestion of increased westerlies and warmer winter temperatures over northern Europe during medieval times. An analog technique for the combined use of proxy records and model results, Proxy Surrogate Reconstruction (PSR), is introduced.
160ufTimes Cited:125Cited References Count:151

Abrupt vegetation changes in tropical South America over the last 120,000 years - Hughen, K. A.; Drenzek, N.; Bice, M.; Eglinton, T. I. (EOS Abstracts, 2006 Ocean Sciences Meeting, 2006)
id: 1078

Alkenone-based reconstruction of late-Holocene surface temperature and salinity changes in Lake Qinghai, China - Liu, Z.; Henderson, A. C. G.; Huang, Y. (Geophysical Research Letters, 2006)
id: 1157

Anomalous radiocarbon ages for foraminifera shells - Broecker, W.; Barker, S.; Clark, E.; Hajdas, I.; Bonani, G. (Paleoceanography, 2006)
The causes for discordant radiocarbon results on multiple species of planktonic foraminifera from high-sedimentation-rate marine sediments are investigated. We have documented two causes for these anomalous results. One is the addition of secondary radiocarbon for which we have, to date, only one firm example. It involves an opal-rich sediment. The other is the incorporation of reworked material. Again, we have, to date, only one firm example. It involves a rapidly deposited ocean margin sediment. However, we have three other examples where reworking is the most likely explanation. On the basis of this study it is our conclusion that, where precise radiocarbon dating of high-deposition-rate marine sediment is required, a prerequisite is to demonstrate that concordant ages can be obtained on pairs of fragile and robust planktic shells. For sediment rich in opal, it is advisable to check for secondary calcite by comparing ages obtained on acid-leached samples with those on unleached samples.
id: 980; 041JB Times Cited:7 Cited References Count:7

Chemical composition of the graphitic black carbon fraction in riverine and marine sediments at submicron scales using carbon X-ray spectromicroscopy - Haberstroh, P. R.; Brandes, J. A.; Gelinas, Y.; Dickens, A. F.; Wirick, S. (Geochimica et Cosmochimica Acta, 2006)
id: 1703

The Chilean Fjords - Lange, C. B.; Pantoja, S.; Sepulveda, J.; Rebolledo, L.; Smith-Wellner, J.; Anderson, J. B.; Hughen, K. A. (Abstracts, EGU General Assembly, 2006)
id: 561

A climatic driver for abrupt mid-Holocene vegetation dynamics and the hemlock decline in New England - Foster, D. R.; Oswald, W. W.; Faison, E. K.; Doughty, E. D.; Hansen, B. C. (Ecology, 2006)
The mid-Holocene decline of eastern hemlock is widely viewed as the sole prehistorical example of an insect- or pathogen-mediated collapse of a North American tree species and has been extensively studied for insights into pest-host dynamics and the consequences to terrestrial and aquatic ecosystems of dominant-species removal. We report paleoecological evidence implicating climate as a major driver of this episode. Data drawn from sites across a gradient in hemlock abundance from dominant to absent demonstrate: a synchronous, dramatic decline in a contrasting taxon (oak); changes in lake sediments and aquatic taxa indicating low water levels; and one or more intervals of intense drought at regional to continental scales. These results, which accord well with emerging climate reconstructions, challenge the interpretation of a biotically driven hemlock decline and highlight the potential for climate change to generate major, abrupt dynamics in forest ecosystems.
Foster, David ROswald, W Wyatt Faison, Edward K Doughty, Elaine D Hansen, Barbara C S eng Research Support, Non-U.S. Gov't Research Support, U.S. Gov't, Non-P.H.S. 2007/01/26 09:00 Ecology. 2006 Dec;87(12):2959-66.
Keywords: *Climate; *Ecosystem; Geologic Sediments; new england; Tsuga/*physiology

Cosmogenic isotope 14C: production and carbon cycle - Hughen, K. A. (PAGES Newsletter, 2006)
id: 1075

Early holocene openlands in southern New England - Faison, E. K.; Foster, D. R.; Oswald, W. W.; Hansen, B. C.; Doughty, E. (Ecology, 2006)
The pre-historical vegetation structure in temperate forest regions is much debated among European and North American ecologists and conservationists. Frans Vera's recent hypothesis that large mammals created mosaics of forest and openland vegetation in both regions throughout the Holocene has been particularly controversial and has provoked new approaches to conservation management. Thirty years earlier, American paleoecologists Herb Wright and Margaret Davis debated whether abundant ragweed pollen at Rogers Lake, Connecticut at 9500 yr BP signified local forest openings or long-distance transport of pollen from Midwestern prairies. Using new pollen records from Harvard Forest and the North American Pollen Database, we address this question and offer insights to the openland discussion. Ragweed and other forbs exceed 3.5% at five sites in a restricted area of southern New England between 10,100 and 7700 yr BP. Strong evidence suggests this pollen originated from the landscapes surrounding these sites (supporting Davis), as ragweed pollen percentages do not increase with longitude from New England to the Midwest. Ragweed pollen percentages are also unrelated to basin size and therefore unrelated to the proportion of extraregional pollen in New England. High forbs values were associated with increases in oak, decreases in white pine, and relatively high charcoal values. Modern pollen records with similar forb and tree percentages occur along the Prairie Peninsula region of the Upper Midwest. However, the closest analogue to the southern New England early Holocene assemblages comes from Massachusetts' Walden Pond in the early 18th century. These results and the affiliation of ragweed for open, disturbed habitats suggest that oak-pine forests with large openings persisted for over 2000 years due to dry conditions and perhaps increased fire frequency. This conclusion is corroborated by independent lake level and climate reconstructions. Because these early Holocene openlands have no detectable analogue in New England for the past 7000 years before European settlement, we suggest that all important openlands today are almost exclusively a legacy of Colonial agriculture and should be managed accordingly. Nonetheless, our results may have implications for forest dynamics accompanying projected climate change to more arid conditions in New England over the next century.
Faison, E KFoster, D R Oswald, W W Hansen, B C S Doughty, E eng Research Support, Non-U.S. Gov't Research Support, U.S. Gov't, Non-P.H.S. 2006/11/09 09:00 Ecology. 2006 Oct;87(10):2537-47.
Keywords: *Ambrosia; *Pollen; Ecosystem; Geography; new england; Paleontology

Evaluation of ageing accuracy of bocaccio (Sebastes paucispinis) rockfish using bomb radiocarbon - Piner, K. R.; Wallace, J. R.; Hamel, O. S.; Mikus, R. (Fisheries Research, 2006)
The accuracy of bocaccio rockfish age assignments was evaluated using radiocarbon levels measured in otoliths collected from fish taken off the coast of Washington state (USA). Otoliths from 24 randomly selected fish with estimated birth years from 1950 to 1977, based on paired otolith age estimates, were used in this study. The level of radiocarbon measured in the core of each otolith was compared to a reference radiocarbon chronology based on radiocarbon levels in otoliths from known-age Pacific halibut. The degree of graphical phase correspondence between the two series was sufficient to support the hypothesis that the annuli were formed yearly in bocaccio otoliths but were somewhat difficult to identify. Statistical analysis of the ageing errors could not document a bias in production ageing of bocaccio. Pre-bomb radiocarbon levels measured in otolith cores confirm that bocaccio can live at least 37 years. Published by Elsevier B.V.
011qtTimes Cited:10Cited References Count:40

Holocene elephant seal distribution implies warmer-than-present climate in the Ross Sea - Hall, B. L.; Hoelzel, A. R.; Baroni, C.; Denton, G. H.; Le Boeuf, B. J.; Overturf, B.; Topf, A. L. (Proceedings of the National Academy of Sciences of the United States of America, 2006)
We show that southern elephant seal (Mirounga leonina) colonies existed proximate to the Ross Ice Shelf during the Holocene, well south of their core sub-Antarctic breeding and molting grounds. We propose that this was due to warming (including a previously unrecognized period from approximate to 1,100 to 2,300 C-14 yr B.P.) that decreased coastal sea ice and allowed penetration of warmer-than-present climate conditions into the Ross Embayment. If, as proposed in the literature, the ice shelf survived this period, it would have been exposed to environments substantially warmer than present.
id: 1918; PT: J; NR: 25; TC: 14; J9: P NATL ACAD SCI USA; PG: 5; GA: 064DM; UT: WOS:000239069400013

Incorporation of aged dissolved organic carbon (DOC) onto oceanic particulate organic carbon (POC): an experimental approach using carbon isotopes - Hwang, J.; Druffel, E. R. M.; Bauer, J. E. (Marine Chemistry, 2006)
id: 682

IntCal04 Update: The future of radiocarbon calibration - Reimer, P.; Hughen, K. A. (PAGES Newsletter, 2006)
id: 557

Investigating the temperoral relationship between the synthesis and sediment incorporation of vascular plant biomarkers using molecular level 14C analysis - Drenzek, N.; Poussart, P.; Lima, A. L.; Hughens, K.; Reddy, C.; Eglinton, T. I. (EOS Abstracts, 2006 AGU Ocean Sciences Meeting, 2006)
id: 562

Late Holocene climate variability of South America reconstructed by a multi-proxy analysis of Chilean fjord sediments - Bertrand, S.; Hughen, K. A.; Giosan, L.; Tierney, J.; Sepfulveda, J.; Pantoja, S. (Abstracts, EGU General Assembly, 2006)
id: 560

Marine 14C calibration and activity record for the past 50,000 years from the Cariaco Basin, Abstract - Hughen, K. A.; Southon, J.; Lehman, S. J.; Jenkins, W. (Eos Trans AGU 87, Fall Meeting Supple., 2006)
id: 1076

Marine 14C data sets: contributions to calibration and Earth Systems research, Abstract - Hughen, K. A. (19th International Radiocarbon Conference, 2006)
id: 1077

Marine-derived 14C calibration and activity record for the past 50,000 years updated from the Cariaco Basin - Hughen, K. A.; Southon, J. A.; Lehman, S. J.; Bertrand, C. J. H.; Turnbull, J. (Quaternary Science Reviews, 2006)
id: 553

Modern saltmarsh diatom distributions of the Outer Banks, North Carolina, and the development of a transfer function for high resolution reconstructions of sea level - Horton, B. P.; Corbett, R.; Culver, S. J.; Edwards, R. J.; Hillier, C. (Estuarine Coastal and Shelf Science, 2006)
We collected modern diatom samples from Currituck Barrier Island, Oregon inlet and Pea Island marshes, Outer Banks, North Carolina, USA, which have different salinity regimes due to their varying distances from a major barrier island inlet. Multivariate analyses separate the saltmarsh diatom assemblages into distinct elevational zones, dominated by differing abundances of polyhalobous, mesohalobous and oliohalobous taxa. suggesting that the distribution of saltmarsh diatoms is a direct function of elevation, with the most important controlling factors being the duration and frequency of subaerial exposure.We developed the first diatom-based transfer function for the east coast of North America to reconstruct former sea levels based upon the relationship between diatom assemblage and elevation. Results imply that this is possible to a precision of +/- 0.08 m, superior to most similar studies from temperate, mid-latitude environments. The transfer function is used to construct a relative sea-level curve from fossil assemblages from Salvo. North Carolina. These results suggest a sea-level rise of 0.7 m over the last c. 150 years, at an average of c. 3.7 mm year(-1). This is consistent with existing sea-level data, and illustrates the utility of the transfer function approach. (c) 2006 Elsevier Ltd. All rights reserved.
090jmTimes Cited:37Cited References Count:74

Origin of PCDD in ball clay assessed with compound-specifric chlorine isotope analysis and radiocarbon dating - Holmstrand, H. D.; Gadomski, D.; Mandalakis, M.; Tysklind, M.; Irvine, R.; Andersson, P.; Gustafsson, O. (Environmental Science and Technology, 2006)
id: 1040

Postglacial climate reconstruction based on compound-specific D/H ratios of fatty acids from Blood Pond, New England - Hou, J. Z.; Huang, Y. S.; Wang, Y.; Shuman, B.; Oswald, W. W.; Faison, E.; Foster, D. R. (Geochemistry Geophysics Geosystems, 2006)
We determined hydrogen isotope ratios of individual fatty acids in a sediment core from Blood Pond, Massachusetts, USA, in order to reconstruct climate changes during the past 15 kyr. In addition to palmitic acid (C-16 n-acid), which has been shown to record lake water D/H ratios, our surface sediments and down core data indicate that behenic acid (C-22 n-acid), produced mainly by aquatic macrophytes, is also effective for capturing past environmental change. Calibration using surface sediments from two transects across eastern North America indicates that behenic acid records delta D variation of lake water. Down core variations in delta D values of behenic acid and pollen taxa are consistent with the known climate change history of New England. By evaluating the hypothesis that D/H fractionations of long chain even numbered fatty acids (C-24-C-32 n-acids) relative to lake water provide independent estimates of relative humidity during the growing season, we find that differences between lake-level records and isotopically inferred humidity estimates may provide useful insight into seasonal aspects of the hydrologic cycle. Combined analyses of D/H of short and long chain fatty acids from lake sediment cores thus allow reconstructions of both past temperature and growing season relative humidity. Comparison of delta D records from two lakes in New England provides critical information on regional climate variation and abrupt climate change, such as the 8.2 ka event.
031uaTimes Cited:32 Cited References Count:43
Keywords: atmospheric processes : paleoclimatology; eastern north-america; fatty acids; geochemistry : organic and biogenic geochemistry; geochemistry : stable isotope geochemistry; Holocene; hydrogen isotope; hydrogen isotope ratios; lacustrine organic-matter; lake-sediments; Paleoclimate; record; Stable isotopes; united-states; vegetation history; younger-dryas

Pre-Columbian maize agriculture in Costa Rice: Pollen and other evidence from lake and swamp sediments - Horn, S. P. (Histories of Maize: Multidisciplinary Approaches to the Prehistory, Biogeography, Domestication, and Evolution of Maize, 2006)
id: 1113

Quantifying archaeal community autotrophy in the mesopelogic ocean using natural radiocarbon - Ingalls, A. E.; Shah, S. R.; Hansman, R. L.; Aluwihare, L. I.; Santos, G. M.; Druffel, E. R. M.; Pearson, A. (Proc. Natl. Acad. Sci. USA, 2006)
id: 502

Reduced agulhas leakage at the LGM inferred from an integrated provenance and flux dtudy - Franzese, A. M.; Hemming, S. R.; Goldstein, S. L.; Anderson, R. F. (Earth & Planatary Science Letters, 2006)
id: 632

Refining the radiocarbon dating of Antarctic marine sediments via stepped combustion - Schrum, H.; Hayes, J.; Domack, E. (Eps Trans AGU, 2006)
id: 702

Rotasonic vibracores from northeastern North Carolina, cores OBX-10 through OBX-18 - Hoffman, C. W.; Farrell, K. M.; Pierson, J. A.; Ward, A. N.; Nickerson, J. G.; Brooks, R. W.; Ganey, J. G. (NCGS Open-file Report, 2006)
id: 704

Solid-state 13C NMR analysis of size and density fractions of marine sediments: Insight into organic carbon sources and preservation mechanisms - Dickens, A. F.; Baldock, J. A.; Smernik, R. J.; Wakeham, S. G.; Arnarson, T. S.; Gelinas, Y.; Hedges, J. I. (Geochimica et Cosmochimica Acta, 2006)
id: 1702

An updated 14C calibration and activity record for the past 50,000 years from marine Cariaco Basin, Abstract - Hughen, K. A.; Southon, J. A.; Lehman, S. J.; Bertrand, C. J. H.; Turnbull, J. (19th International Radiocarbon Conference, 2006)
id: 559

Western Atlantic intertropical convergence zone variability over the last full glacial cycle, Abstract - Drenzek, N.; Hughe, K.; Sessions, A.; Bice, M.; Eglinton, T. I. (Eos Trans. AGU 87, Fall Meeting Suppl., 2006)
id: 558

A 17,000 year history of Andean climatic and vegetation change from Laguna de Chochos, Peru - Bush, M. B.; Hansen, B. C. S.; Rodbell, D. T.; Seltzer, G. O.; Young, K. R.; Leon, B.; Abbott, M. B.; Silman, M. R.; Gosling, W. D. (Journal of Quaternary Science, 2005)
The manifestation of major climatic events such as the timing of deglaciation and whether, or not, the Younger Dryas affected Andean systems has garnered considerable recent attention. Even the Holocene is rapidly emerging as a time of considerable interest in Neotropical palaeoclimatology and palaeoecology. The Holocene of the Neotropics is now revealed as a time of some temperature change with precipitation:evaporation ratios fluctuating markedly. Major changes in lake level, ice-accumulation, and vegetation are indicative of changes both in precipitation and temperature regimes. Although global-scale forcing mechanisms may underlie some of these changes, e.g. the precessional rhythm, other variability appears to be localised. In a record from near the upper forest limit of the eastern Peruvian Andes, pollen, charcoal, and sedimentary data suggest that the deglaciational period from ca. 17 000 to ca. 11 500 cal. yr BP was a period of rapid climatic oscillations, set against an overall trend of warming. A warm-dry event is evident between ca. 9500 and ca. 7300 cal. yr BP, and comparisons with other regional archives suggest that it was regional in scale. A ca. 1500-yr periodicity in the magnetic susceptibility data is evident between 12 000 and 6000 cal. yr BP, reaching a peak intensity during the dry event. A weaker oscillation with a 500–600-yr periodicity is present throughout much of the Holocene. The uppermost sample of the pollen analysis reveals deforestation as modern human land use simplified the landscape.
id: 1015

A 2000-year reconstruction of forest disturbance from southern Pacific Costa Rica - Anchukaitis, K. J.; Horn, S. P. (Palaeogeography Palaeoclimatology Palaeoecology, 2005)
We reconstruct prehistoric and historic human forest disturbance and vegetation change in southern Pacific Costa Rica, in the vicinity of the Las Cruces Biological Station and the La Amistad International Park and Biosphere Reserve. Pollen and charcoal in sediments from Laguna Santa Elena reveal a nearly continuous record of human alteration of these tropical forests over the past two millennia. The basal portion of the core shows nearly intact premontane forests approximately 1800 cal. year B.P., although there is evidence of human presence on the landscape in the form of maize pollen and charcoal. Clearing for agriculture resulted in the dominance of disturbance taxa in the watershed beginning at least 1400 cal. year B.P. The pollen record reveals a possible, brief hiatus in human occupation of the watershed at approximately 540 cal. year B.P., although secondary succession began to occur in the Laguna Santa Elena watershed prior to that time, beginning about 700 cal. year B.P. Three eruptions of nearby Volcan Baru which we date to approximately 610, 1080, and 1440 cal. year B.P., apparently had little direct effect on the prehistoric populations in the immediate vicinity of the lake. Historic and modern land clearance has perpetuated a modem vegetation assemblage of disturbance and successional taxa, (c) 2005 Elsevier B.V. All rights reserved.
id: 1112; 931QJ Times Cited:14 Cited References Count:114

A 2.45 GHz Ion Source for use in Accelerator Mass Spectrometry - von Reden, K. F.; Schneider, R. J.; Roberts, M. L.; Han, B. X.; Wills, J. (11th International Conference on Ion Ssources, 2005)
id: 1707

3-D Electromagnetic Field Modeling and Ion Optics Calculations for a Continuous-Flow AMS System - Han, B. X.; von Reden, K. F.; Roberts, M. L.; Schneider, R. J.; Hayes, J. M. (10th International Conference on Accelerator Mass Spectrometry, 2005)
id: 1708

Age and origin of Late Quaternary eolianite, Kaiehu Point (Moomomi), Molokai, Hawaii - Fletcher, C. H.; Murray-Wallace, C. V.; Glenn, C. R.; Sherman, C. E.; Popp, B.; Hessler, A. (Journal of Coastal Research, 2005)
A well-preserved, vertically stacked succession of two genetically distinct eolianites and associated caliche paleosol units, capped by modern and Holocene coastal dunes, occurs at Kaiehu Point, west Molokai, Hawaii. The Pleistocene eolianite facies comprise well-cemented, medium grained skeletal carbonate sand and their morphostratigraphic context implies formation at times of lower than present sea level. Amino acid racernization (AAR) evidence suggests eolianite formation late in marine Oxygen Isotope Stage (OIS) 5, but lacks the precision to uniquely define in which isotopic substage the deposits formed. Coupled with the AAR results, the morphostratigraphic evidence, would suggest that the Lower Eolianite formed in OIS 5c and the Middle Eolianite during 5a with their superposed caliche paleosols having formed in subsequent stadial stages. The unconsolidated coastal sand dunes of Holocene age contain reworked Late Pleistocene skeletal carbonate sand based on AAR evidence. The most likely source of the reworked carbonate is from the erosion of the eolianites at Kaiehu Point. The Pleistocene eolianite-caliche paleosol sediments reveal variable Mg-content, stable isotope ratios and petrological characteristics consistent with changing degrees of weathering intensity and meteoric diagenesis. These changes are attributed to orographic effects resulting from relative sea-level changes. Accordingly, a two-phase model is favored for the formation of the eolianite-paleosol successions at Kaiehu Point, west Molokai. Eolianite sedimentation is initiated at times of marginally lower sea levels promoting the landward migration of bioclastic sand to form extensive eolian sandsheets. This is followed by a more pronounced phase of pedogenesis associated with a further fall in sea level and concomitant increased rainfall due to enhanced orographic effects.
Sp. Iss. 42947fu Times Cited:3 Cited References Count:50
Keywords: Amino acid racemization; aminostratigraphy; bermuda; carbonate lithofacies; cementation; cliche paleosols; eolianite; hawaii; island; Late Quaternary; limestone petrology; Marine; molokai; oahu; precipitation; sea level; sea-level; south-australia; Stable isotopes; stratigraphy

Age validation of canary rockfish (Sebastes pinniger) from off the Oregon coast (USA) using the bomb radiocarbon method - Piner, K. R.; Hamel, O. S.; Menkel, J. L.; Wallace, J. R.; Hutchinson, C. E. (Canadian Journal of Fisheries and Aquatic Sciences, 2005)
The alternating translucent and opaque banding pattern in canary rockfish (Sebastes pinniger) otoliths, aged using a break-and-burn methodology, are annual markings. To validate age assignment, we compared measured radiocarbon levels in canary rockfish otolith cores with a reference chronology developed from known age Pacific halibut (Hippoglossus stenolepis). An average 2- to 3-year phase shift was detected between the canary rockfish and a Pacific halibut reference chronology that was likely the result of differences in the regional oceanography or underageing bias. The assumption of ageing bias consistency was tested with two sampling designs. The first design controled for age-related ageing error, and the second design related birth year to estimated age. No change in the magnitude of ageing bias as a function of age was detected.
932zxTimes Cited:27Cited References Count:27

Blank correction for Delta 14C measurements in organic compound classes of oceanic particulate matter - Hwang, Jeomshik; Druffel, Ellen R. M. (Radiocarbon, 2005)
id: 1054

Calculation of hydrogen isotopic fractionations in biogeochemical systems - Sessions, A. L.; Hayes, J. M. (Geochimica Et Cosmochimica Acta, 2005)
Hydrogen-isotopic data are often interpreted using mathematical approximations originally intended for other isotopes. One of the most common. apparent in literature over the last several decade's. assumes that delta values of reactants and products are separated by a constant fractionation factor delta(p) = delta(r) + epsilon(p/r). Because of the large fractionations that affect hydrogen isotopes, such approximations can lead to substantial errors. Here we review and develop general equations for isotopic mass balances that include the differential fractionation of each component in a mixture and discuss their use in three geochemical applications. For the fractionation of a single component. the reactant and product are related by delta(p) = a(p/r)delta(r) + epsilon(p/r), where alpha and epsilon refer to the same fractionation. Regression of delta(p) on delta(r) should give equivalent fractionations based on the intercept and slope, but this has not generally been recognized in studies of D/H fractionation. In a mixture of two components, each of which is fractionated during mixing, there is no unique solution for the three unknown variables (two fractionation factors and the elemental mixing ratio of the two hydrogen sources). The flow of H from CH4 and H2O to bacterial lipids in the metabolism of Methylococcus capsulatus provides an example of such a case. Data and conclusions from an earlier study of that system (Sessions et al., 2002) are reexamined here. Several constraints on the variables are available based on plausible ranges for fractionation factors. A possible refinement to current experimental procedures is the measurement of three different isotopes, which would allow unique determination of all variables. Copyright (C) 2005 Elsevier Ltd.
892wiTimes Cited:55Cited References Count:21

Computer Control - Roberts, M. L. (Electrostatic accelerators: fundamentals and applications, 2005)
id: 1686

Continuous-Flow Accelerator Mass Spectrometry - Roberts, M. L.; von Reden, K. F.; Han, B. X.; Schneider, R. J.; Benthien, A.; Hayes, J. M. (the International Symposium on Utilization of Accelerators, 2005)
id: 767

Contribution of biomass burning to polycyclic aromatic hydrocarbons in European background aerosols - Mandalakis, M.; Gustafsson, O.; Alsberg, T.; Reddy, C.; Xu, L.; Klanova, J.; Holoubek, I.; Stephanou, E. (Environmental Science and Technology, 2005)
id: 510

Cross-formational flow and salinity sources inferred from a combined study of helium concentrations, isotopic ratios, and major elements in the Marshall aquifer, southern Michigan - Ma, L.; Castro, M. C.; Hall, C. M.; Walter, L. M. (Geochemistry Geophysics Geosystems, 2005)
Helium data and major ion chemistry are presented for the shallow Marshall aquifer in southern Michigan. This data set is subsequently analyzed in conjunction with major element data sets from deeper and shallower water levels previously collected in this area. He excesses and isotopic ratios suggest the presence of tritiogenic He-3 in young waters in the Marshall aquifer. He excesses in old groundwater samples are mostly of crustal origin although the presence of a significant mantle He component in some samples cannot be ruled out. He excesses in the Marshall aquifer are unusually high for such shallow depths ( <= 300 m) and reach over two and three orders of magnitude above those of air- saturated water ( ASW) for He-3 and He-4, respectively. He isotopes require a source external to the aquifer, partly supplied by underlying formations within the sedimentary sequence, partly from the crystalline basement. Calibration of He concentrations observed in the Marshall aquifer requires He fluxes of 1 x 10(-13) and 1.6 x 10(-6) cm(3) STP cm(-2) yr(-1) for He-3 and He-4, respectively. These He fluxes are far greater than those reported in other sedimentary basins around the world ( e. g., Paris Basin, Gulf Coast Basin) at similar and far greater depths. Such high He fluxes present at such shallow depths within the Michigan Basin strongly suggest the presence of a dominant vertical water flow component and further indicate that impact of recharge water at depth is minor. Upward cross- formational flow is also likely responsible for the extremely high salinities present in the shallow subsurface of the Michigan Basin. The observed positive correlation between helium and bromide strongly suggests that these two very distinct conservative tracers both originate at greater depths and further suggests that advection is the dominant transport mechanism within the basin. The occurrence of large- scale cross- formational flow is also consistent with the evolution displayed by the major ion chemistry throughout most of the sedimentary sequence, indicating that solutes from shallow levels carry the signature of deep formation brines.
973vwTimes Cited:18Cited References Count:63

An evaluation of 14C age relationships between co-occurring foraminifera, alkenones, and total organic carbon in continental margin sediments - Mollenhauer, Gesine; Kienast, Markus; Lamy, Frank; Meggers, Helge; Schneider, Ralph R.; Hayes, John M.; Eglinton, Timothy I. (Paleoceanography, 2005)
id: 492

The Fe3+/ΣFe ratios of MORB glasses and their implications for mantle melting - Bezos, Antoine; Humler, Eric (Geochimica et Cosmochimica Acta, 2005)
The Fe3+/ΣFe ratio of 104 MORB glasses from the Pacific, the Atlantic, the Indian, and the Red Sea spreading centers have been determined using wet chemical Fe2+ analyses and electron microprobe FeOtotal measurements. The data provide a new estimate for the MORB oxygen fugacity (fO2) of 0.41 ± 0.43 (1sigma, N = 100) log units below the fayalite-magnetite-quartz buffer (FMQ), equivalent to a Fe3+/ΣFe = 0.12 ± 0.02 (1sigma, N = 104). This new fO2 estimate is 0.8 log units more oxidized than the average fO2 proposed by Christie et al. (1986) (FMQ-1.20 ± 0.44; Fe3+/ΣFe = 0.07 ± 0.01; N = 87). This slight difference may be related in part to the 3.5% underestimation of the Fe2+ concentration determined by Christie et al. (1986) compared with this study. MORB oxygen fugacity does not display any significant difference between the three main oceanic domains, or between enriched and depleted MORB. Yet, the iron red-ox state ratio shows a broad increase during fractional crystallization. Detailed study of magmatic suites highlights the lack of systematic Fe3+/ΣFe ratio fractionation during differentiation. Despite the large variations of inferred partial melting degrees (from 5 to 20%), the present data set does not provide any evidence of Fe3+/ΣFe relationships with partial melting proxies such as Na8.0. Based on the Fe3+ systematics during partial melting, it is suggested that the oxidation state of MORB reflects a “buffered mantle melting process” resulting in the apparent compatible behavior of Fe3+ during partial melting, and in the relatively constant Fe3+/ΣFe ratio irrespective of the extent of melting. This result implies that partial melting processes may be open relative to oxygen. We propose a model where the Fe3+/ΣFe ratio in the melt is buffered during partial melting. The MORB Fe2O3 systematics can be accounted for by using a fO2 of FMQ-1 that is equivalent to the average fO2 reported for abyssal peridotites.
id: 1578

Fluctuations in export productivity over the last century from sediments of a southern Chilean fjord (44 degrees S) - Sepulveda, J.; Pantoja, S.; Hughen, K.; Lange, C.; Gonzalez, F.; Munoz, P.; Rebolledo, L.; Castro, R.; Contreras, S.; Avila, A.; Rossel, P.; Lorca, G.; et al. (Estuarine Coastal and Shelf Science, 2005)
Here we present the first reconstruction of changes in surface primary production during the last century from the Puyuhuapi fjord in southern Chile, using a variety of parameters (diatoms, biogenic silica, total organic carbon, chlorins, and proteins) as productivity proxies. Two sediment cores from the head and the center of the fjord were analyzed and compared to gain insights on past changes in productivity in these two different depositional environments. Higher sedimentation rates found at the head of the fjord result from the combination of a shallower water column and a restricted circulation by the occurrence of a sill. Additionally, sediment mixing depths estimated from (210)Pb data suggest that suboxic conditions may dominate the bottom water and the sediment-water interface in this location.Productivity of the Puyuhuapi fjord during the last century was characterized by a constant increase from the late 19th century to the early 1980s, then decreased until the late 1990s, and then rose again to present-day values. The influence of rainfall on productivity was most noticeable during periods of low rainfall, which coincided with decreased overall productivity within the Puyuhuapi fjord. Simultaneous variations in productivity and rainfall in the study area suggest that marine productivity could respond to atmospheric-oceanic interactions at a local scale. At a regional scale, marine productivity of the area may be related to other large-scale processes such as the El Nino Southern Oscillation. (c) 2005 Elsevier Ltd. All rights reserved.
975sfTimes Cited:22Cited References Count:53

Geochemical and hydrogeological contrasts between shallow and deeper aquifers in two villages of Araihazar, Bangladesh: Implications for deeper aquifers as drinking water sources - Zheng, Y.; van Geen, A.; Stute, M.; Dhar, R.; Mo, Z.; Cheng, Z.; Horneman, A.; Gavrieli, I.; Simpson, H. J.; Versteeg, R.; Steckler, M.; Grazioli-Venier, A.; et al. (Geochimica et Cosmochimica Acta, 2005)
Sediment and groundwater profiles were compared in two villages of Bangladesh to understand the geochemical and hydrogeological factors that regulate dissolved As concentrations in groundwater. In both villages, fine-grained sediment layers separate shallow aquifers ( 50 ka ago and a groundwater age of thousands of years. In the other village (Bay), the sediment is
id: 604; 999UZ Times Cited:59 Cited References Count:49

High-resolution historical records from Pettaquamscutt River basin sediments; 2. Chronology and record of 137Cs released by the Chernobyl accident - Lima, A. L.; Hubeny, J. B.; Reddy, C. M.; King, J. W.; Hughen, K. A.; Eglinton, T. I. (Geochimica et Cosmochimica Acta, 2005)
id: 555

The Holocene radiocarbon reservoir effect in the western Ross Sea - Hall, Brenda L.; Henderson, Gideon M.; Baroni, Carlo; Kellog, Thomas (Annual West Antarctic Ice Sheet Meeting, 2005)
id: 434

Long term calibration of the Noble gas temperature system in a shallow unconfined Pleistocene aquifer - Hall, C. M.; Castro, M. C.; Lohmann, K. C.; Ma, L. (Eos Trans. AGU Fall Meeting Supplement, 2005)
id: 438

Millennial scale variability in tropical South American vegetation during the last glaciation - Hughen, K. A.; Drenzek, N.; Bice, M.; Eglinton, T. I. (Eos Trans. AGU, 86(52), Fall Meeting Suppl., 2005)
id: 563

Moving-wire device for carbon isotopic analyses of nanogram quantities of nonvolatile organic carbon - Sessions, A. L.; Sylva, S. P.; Hayes, J. M. (Anal Chem, 2005)
We describe a moving-wire analyzer for measuring 13C in dissolved, involatile organic materials. Liquid samples are first deposited and dried on a continuously spooling nickel wire. The residual sample is then combusted as the wire moves through a furnace, and the evolved CO2 is analyzed by continuous-flow isotope ratio mass spectrometry. A typical analysis requires 1 microL of sample solution and produces a CO2 peak approximately 5 s wide. The system can measure "bulk" delta13C values of approximately 10 nmol of organic carbon with precision better than 0.2 per thousand. For samples containing approximately 1 nmol of C, precision is approximately 1 per thousand. Precision and sensitivity are limited mainly by background noise derived from carbon within the wire. Instrument conditions minimizing that background are discussed in detail. Accuracy is better than 0.5 per thousand for nearly all dissolved analytes tested, including lipids, proteins, nucleic acids, sugars, halocarbons, and hydrocarbons. The sensitivity demonstrated here for 13C measurements represents a approximately 1000-fold improvement relative to existing elemental analyzers and should allow the use of many new preparative techniques for collecting and purifying nonvolatile biochemicals for isotopic analysis.
Sessions, Alex LSylva, Sean PHayes, John MengResearch Support, U.S. Gov't, Non-P.H.S.2005/10/15 09:00Anal Chem. 2005 Oct 15;77(20):6519-27.

Multiple sources for late-Holocene tsunamis at Discovery Bay, Washington State, USA - Williams, H. F. L.; Hutchinson, I.; Nelson, A. R. (Holocene, 2005)
Nine muddy sand beds interrupt a 2500- yr- old sequence of peat deposits beneath a tidal marsh at the head of Discovery Bay on the south shore of the Strait of Juan de Fuca, Washington. An inferred tsunami origin for the sand beds is assessed by means of six criteria. Although all the sand beds contain marine diatoms and almost all the beds display internal strati. cation, the areal extent of the oldest beds is too limited to confirm their origin as tsunami deposits. The ages of four beds overlap with known late Holocene tsunamis generated by plate- boundary earthquakes at the Cascadia subduction zone. Diatom assemblages in peat deposits bracketing these four beds do not indicate concurrent change in elevation at Discovery Bay. Diatoms in the peat bracketing a tsunami bed deposited about 1000 cal. yr BP indicate a few decimeters of submergence, suggesting deformation on a nearby upper- plate fault. Other beds may mark tsunamis caused by more distant upper- plate earthquakes or local submarine landslides triggered by earthquake shaking. Tsunamis from both subduction zone and upper- plate sources pose a significant hazard to shoreline areas in this region.
894xjTimes Cited:37Cited References Count:67

Noble gases and stable isotopes in a shallow aquifer in southern Michigan: Implications for noble gas paleotemperature reconstructions for cool climates - Hall, C. M.; Castro, M. C.; Lohmann, K. C.; Ma, L. (Geophysical Research Letters, 2005)
Noble gas data from the Glacial Drift, the shallowest aquifer in southern Michigan confirm findings by Ma et al. (2004) that modern noble gas temperatures (NGTs) are systematically below the current mean annual air temperature (MAAT) which, in turn, is similar to the ground temperature of these recharge waters. By tracking noble gas concentrations as well as stable isotope ratios through an autumn, winter, spring and into summer, we show that although water in this aquifer is modern, noble gases do not track the atmosphere on a short time scale. Specifically, excess He-3 and He-4 indicate that the gas environment at the water table is integrating conditions over years or decades rather than weeks or months. Our results are interpreted using various NGT interpretational models and possible mechanisms for the production of low apparent NGTs are discussed.
968qnTimes Cited:26 Cited References Count:14
Keywords: water

One-year record of organic and elemental carbon in fine particles in downtown Beijing and Shanghai - Yang, F.; He, K.; Ye, B.; Chen, X.; Cha, L.; Cadle, S. H.; Chan, T.; Mulawa, P. A. (Atmospheric Chemistry and Physics, 2005)
Weekly PM2.5 samples were collected for one year ( 1999 - 2000) in Beijing and Shanghai and the carbonaceous species analyzed to investigate and compare their time series patterns and possible sources in the two biggest cities of China. Weekly carbonaceous concentrations varied in wide ranges with 8.6 - 59 mu g m(-3) for OC and 1.5-25.4 mu g m(-3) for EC in Beijing, and with 5.1 - 38.4 mu g m(-3) for OC and 2.3 - 13.0 mu g m(-3) for EC in Shanghai. Similar weekly and seasonal variations of OC and EC concentrations were found in each city though major combustion sources presented source-dependent emission characteristics and seasonal differences in emission amount for carbonaceous species. Both OC and EC maintained much higher concentrations in late fall through winter, probably due to enhanced emissions coupled with unfavorable meteorological conditions. In Beijing, the C-14 analysis of limited samples suggested there was a significant contribution ( 33 - 48%) of modern carbon to the total fine carbonaceous PM burden with higher fractions in the harvest seasons. The high mass ratios of excessive potassium to EC in both Beijing and Shanghai also indicated that biomass burning had important contribution to fine carbonaceous particles.
936dsTimes Cited:77Cited References Count:45

The Paleoproterozoic snowball Earth: a climate disaster triggered by the evolution of oxygenic photosynthesis - Kopp, R. E.; Kirschvink, J. L.; Hilburn, I. A.; Nash, C. Z. (Proc Natl Acad Sci U S A, 2005)
Although biomarker, trace element, and isotopic evidence have been used to claim that oxygenic photosynthesis evolved by 2.8 giga-annum before present (Ga) and perhaps as early as 3.7 Ga, a skeptical examination raises considerable doubt about the presence of oxygen producers at these times. Geological features suggestive of oxygen, such as red beds, lateritic paleosols, and the return of sedimentary sulfate deposits after a approximately 900-million year hiatus, occur shortly before the approximately 2.3-2.2 Ga Makganyene "snowball Earth" (global glaciation). The massive deposition of Mn, which has a high redox potential, practically requires the presence of environmental oxygen after the snowball. New age constraints from the Transvaal Supergroup of South Africa suggest that all three glaciations in the Huronian Supergroup of Canada predate the Snowball event. A simple cyanobacterial growth model incorporating the range of C, Fe, and P fluxes expected during a partial glaciation in an anoxic world with high-Fe oceans indicates that oxygenic photosynthesis could have destroyed a methane greenhouse and triggered a snowball event on time-scales as short as 1 million years. As the geological evidence requiring oxygen does not appear during the Pongola glaciation at 2.9 Ga or during the Huronian glaciations, we argue that oxygenic cyanobacteria evolved and radiated shortly before the Makganyene snowball.
Kopp, Robert EKirschvink, Joseph LHilburn, Isaac ANash, Cody ZengResearch Support, Non-U.S. Gov'tResearch Support, U.S. Gov't, Non-P.H.S.2005/08/03 09:00Proc Natl Acad Sci U S A. 2005 Aug 9;102(32):11131-6. Epub 2005 Aug 1.

Pre- and post-industrial environmental changes as revealed by the biogeochemical sedimentary record of Drammensfjord, Norway - Smittenberg, R. H.; Baas, M.; Green, M. J.; Hopmans, E. C.; Schouten, S.; Damste, J. S. S. (Marine Geology, 2005)
The biogeochemical sedimentary record of the anoxic Drammensfjord, Norway, was investigated on a decadal to centennial time scale over the last millennium, in order to reconstruct the pre-industrial fjord environment and ecosystem and human-induced environmental changes. The sediments were dated by a combination of C-14 and Pb-210 analysis and varve counting. Analysis of the bulk sedimentary parameters and of the biomarker distribution revealed that the sedimentary organic matter of the fjord is primarily of terrigetious origin, indicating that the fjord was oligotrophic or mesotrophic. The fjord's bottom water has been continuously euxinic since at least 1000 AD, but photic zone euxinia occurred only irregularly in the fjord. The organic matter flux and composition remained virtually invariable until the 18th century. After that time, the flux of material derived from coniferous trees started to increase, indicated by elevated concentrations of dehydroabietic acid and related compounds, but also by raising levels of C-24 n-alcohols and fatty acids. This marked the onset of sawmill activities in the hinterland. After the beginning of the industrial revolution, around 1850, the flux of organic waste from sawmills and paper mills increased substantially. It is suggested that slow bacterial degradation of this relatively nutrient-poor organic waste caused a gradual eutrophication trend, which is reflected in substantial increased bacterial and moderately increased other aquatic biomarker accumulation rates. After the industrial revolution, this trend accelerated and was possibly enhanced by a growing population of the area with accompanymg agricultural and domestic waste. This promoted primary productivity and changed the phytoplankton composition in the fjord.(C) 2004 Elsevier B.V. All rights reserved.
890unTimes Cited:23Cited References Count:105

Progress on a Gas Ion Source for Continuous-Flow Accelerator Mass Spectrometry - Roberts, M. L.; Schneider, R. J.; von Reden, K. F.; Han, B. X.; Rosenheim, B. E.; Hayes, J. M. (10th International Conference on Accelerator Mass Spectrometry, 2005)
id: 768

Radiocarbon dating of alkenones from marine sediments-III. Influence of solvent extractions procedures on 14C measurements of foraminifera - Ohkouchi, N.; Eglinton, T. I.; Hughen, K. A.; Roosen, E.; Keigwin, L. (Radiocarbon, 2005)
id: 554

Recent 2000-year geological records of mud in the inner shelf of the East China Sea and their climatic implications - Xiao, S. B.; Li, A. C.; Jiang, F. Q.; Li, T. G.; Huang, P.; Xu, Z. K. (Chinese Science Bulletin, 2005)
AXIS(14)C dating and grain-size analysis for Core DD2, located at the north of the Yangtze River-derived mud off the Zhejiang-Fujian coasts in the inner shelf of the East China Sea, provide us a high-resolution grain-size distribution curve varying with depth and time. Data in the upper mud layer of Core DD2 indicate that there are at least 9 abrupt grain-size increasing in recent 2000 years, with each corresponding very well with the low-temperature events in Chinese history, which might result from the periodical strengthening of the East Asian Winter Monsoon (EAWM), including the first-revealed maximum temperature lowering event at around 990 a BP. At the same time, the finer grain size section in Core DD2 agrees well with the Sui-Tang Warming Period (600-1000 a AD) defined previously by Zhu Kezhen, during which the climate had a warm, cold and warm fluctuation, with a dominated cooling period of 750-850 a AD. The Little Ice Age (LIA) can also be identified in the core. It starts around 1450 a AD and was followed by a subsequent cooling events at 1510, 1670 and 1840 a AD. Timing of these cold events revealed here still needs to be further verified owing to some current uncertainty of dating we used in this study.
923yeTimes Cited:20Cited References Count:58

On the sedimentological origin of downcore variations of bulk sedimentary nitrogen isotope ratios - Kienast, M.; Higginson, M. J.; Mollenhauer, G.; Eglinton, T. I.; Chen, M. T.; Calvert, S. E. (Paleoceanography, 2005)
The bulk sedimentary nitrogen isotopic composition of two cores from nearby sites on the northern slope of the South China Sea (Site 17940 and Ocean Drilling Program (ODP) Site 1144) differs by up to >2‰ during the last glacial period. Given their close proximity, both core sites are located in the same biogeographic zone and nutrient regime, and it is thus unlikely that this offset is due to a true gradient in surface ocean conditions. In an attempt to resolve this offset, we have investigated the possible effects of two sedimentological parameters that can affect bulk sedimentary δ15N, namely, the variable contribution of inorganic N to bulk N in the sediment and the grain-size dependence of bulk δ15N. We find that neither effect, singly or in combination, is sufficient to explain the significant δ15N offset between the two down-core records. By elimination the most likely explanation for the observed discrepancy is a different origin of both the organic and inorganic nitrogen at each site. This study adds to the growing body of evidence highlighting the complex nature and origin of the sedimentary components in sediment drifts, such as ODP Site 1144.
id: 1066

Subducting oceanic crust: The source of deep diamonds - Tappert, R.; Stachel, T.; Harris, J. W.; Muehlenbachs, K.; Ludwig, T.; Brey, G. P. (Geology, 2005)
Inclusions of majoritic garnet in diamonds from the Jagersfontein kimberlite formed at unusually great depths of similar to 250 to > 500 km in the asthenosphere and transition zone. The original host rocks were derived from a much shallower, basaltic (eclogitic) source. The presence of negative Eu anomalies in all majoritic garnets requires a crustal origin, thereby linking these very deep diamond sources to subducting oceanic crust. The carbon isotope values (delta(13)C) of the host diamonds fall within a narrow range at similar to -20%, which is fundamentally different from the broad range (-24% to -2%) and bimodal distribution of carbon isotopes of Jagersfontein diamonds that formed in the shallower lithosphere. This indicates that majoritic garnet-bearing diamonds at Jagersfontein inherited their light carbon isotopic composition directly from organic matter contained in a subducting slab. These diamonds were likely formed by direct conversion from graphite, well within the diamond stability field.
938hnTimes Cited:65Cited References Count:26

Toward a Neoproterozoic composite carbon-isotope record - Halverson, G. P.; Hoffman, P. F.; Schrag, D. P.; Maloof, A. C.; Rice, A. H. N. (Geological Society of America Bulletin, 2005)
Glacial deposits of Sturtian and Marinoan age occur in the well-studied Neoproterozoic successions of northern Namibia, South Australia, and northwestern Canada. In all three regions, the Marinoan glaciation is presaged by a large negative delta(13)C anomaly, and the cap carbonates to both glacial units share a suite of unique sedimentological, stratigraphic, and geochemical features. These global chronostratigraphic markers are the bases of a new correlation scheme for the Neoproterozoic that corroborates radiometric data that indicate that there were three glacial epochs between ca. 750 and 580 Ma. Intraregional correlation of Neoproterozoic successions in the present-day North Atlantic region suggests that glacial diamictite pairs in the Polarisbreen Group in northeastern Svalbard and the Tillite Group in eastern Greenland were deposited during the Marinoan glaciation, whereas the younger of a pair of glacials (Mortensnes Formation) in the Vestertana Group of northern Norway was deposited during the third (Gaskiers) Neoproterozoic glaciation. Gaskiers-aged glacial deposits are neither globally distributed nor overlain by a widespread cap carbonate but are associated with an extremely negative delta(13)C anomaly. The chronology developed here provides the framework for a new, high-resolution model carbon-isotope record for the Neoproterozoic comprising new delta(13)C (carbonate) data from Svalbard (Akademikerbreen Group) and Namibia (Otavi Group) and data in the literature from Svalbard, Namibia, and Oman. A new U-Pb zircon age of 760 +/- 1 Ma from an ash bed in the Ombombo Subgroup in Namibia provides the oldest direct time-calibration point in the compilation, but the time scale of this preliminary delta(13)C record remains poorly constrained.
960jtTimes Cited:414Cited References Count:174

Tsunami history of an Oregon coastal lake reveals a 4600 yr record of great earthquakes on the Cascadia subduction zone - Kelsey, H. M.; Nelson, A. R.; Hemphill-Haley, E.; Witter, R. C. (Geological Society of America Bulletin, 2005)
Bradley Lake, on the southern Oregon coastal plain, records local tsunamis and seismic shaking on the Cascadia subduction zone over the last 7000 yr. Thirteen marine incursions delivered landward-thinning sheets of sand to the lake from nearshore, beach, and dune environments to the west. Following each incursion, a slug of marine water near the bottom of the freshwater take instigated a few-year-to-several-decade period of a brackish (<= 4 parts per thousand salinity) lake. Four additional disturbances without marine incursions destabilized sideslopes and bottom sediment, producing a suspension deposit that blanketed the lake bottom.Considering the magnitude and duration of the disturbances necessary to produce Bradley Lake's marine incursions, a local tsunami generated by a great earthquake on the Cascadia subduction zone is the only accountable mechanism. Extreme ocean levels must have been at least 5-8 m above sea level, and the cumulative duration of each marine incursion must have been at least 10 min. Disturbances without marine incursions require seismic shaking as well.Over the 4600 yr period when Bradley Lake was an optimum tsunami recorder, tsunamis from Cascadia plate-boundary earthquakes came in clusters. Between 4600 and 2800 cal yr B.P., tsunamis occurred at the average frequency of similar to 3-4 every 1000 yr. Then, starting similar to 2800 cal yr B.P., there was a 930-1260 yr interval with no tsunamis. That gap was followed by a similar to 1000 yr period with 4 tsunamis. In the last millennium, a 670-750 yr gap preceded the A.D. 1700 earthquake and tsunami. The A.D. 1700 earthquake may be the first of a new cluster of plate-boundary earthquakes and accompanying tsunamis.Local tsunamis entered Bradley Lake an average of every 390 yr, whereas the portion of the Cascadia plate boundary that underlies Bradley Lake ruptured in a great earthquake less frequently, about once every 500 yr. Therefore, the entire length of the subduction zone does not rupture in every earthquake, and Bradley Lake has recorded earthquakes caused by rupture along the entire length of the Cascadia plate boundary as well as earthquakes caused by rupture of shorter segments of the boundary. The tsunami record from Bradley Lake indicates that at times, most recently similar to 1700 yr B.P., overlapping or adjoining segments of the Cascadia plate boundary ruptured within decades of each other.
938hsTimes Cited:103Cited References Count:73

Unusually high helium fluxes in the shallow Marshall aquifer in southern Michigan: implications for cross-formational flow and salinity sources - Ma, L.; Castro, M. C.; Hall, C. M.; Walter, L. M. (Eos Trans. AGU Fall Meeting Supplement, 2005)
id: 437

14C activity and global carbon cycle changes over the past 50,000 years - Hughen, K.; Lehman, S.; Southon, J.; Overpeck, J.; Marchal, O.; Herring, C.; Turnbull, J. (Science, 2004)
A series of 14C measurements in Ocean Drilling Program cores from the tropical Cariaco Basin, which have been correlated to the annual-layer counted chronology for the Greenland Ice Sheet Project 2 (GISP2) ice core, provides a high-resolution calibration of the radiocarbon time scale back to 50,000 years before the present. Independent radiometric dating of events correlated to GISP2 suggests that the calibration is accurate. Reconstructed 14C activities varied substantially during the last glacial period, including sharp peaks synchronous with the Laschamp and Mono Lake geomagnetic field intensity minimal and cosmogenic nuclide peaks in ice cores and marine sediments. Simulations with a geochemical box model suggest that much of the variability can be explained by geomagnetically modulated changes in 14C production rate together with plausible changes in deep-ocean ventilation and the global carbon cycle during glaciation.
Hughen, KLehman, SSouthon, JOverpeck, JMarchal, OHerring, CTurnbull, Jeng2004/01/13 05:00Science. 2004 Jan 9;303(5655):202-7.

The 14C AMS system at the University of Georgia - Roberts, M. L.; Culp, R. A.; Dvoracek, D. K.; Hodgins, G. W. L.; Neary, M. P.; Noakes, J. E. (Nuclear Instruments and Methods in Physics Research, 2004)
id: 1809

The 14C AMS system at The University of Georgia - Roberts, M. L.; Culp, R. A.; Dvoracek, D. K.; Hodgins, G. W. L.; Neary, M. P.; Noakes, J. E. (Proceedings of the Ninth International Conference on Accelerator Mass Spectrometry, 2004)
The Center for Applied Isotope Studies at the University of Georgia has installed a compact 14C accelerator mass spectrometry (AMS) system manufactured by the National Electrostatics Corporation, Middleton, Wisconsin. The system utilizes a 134 sample ion source and a 500 kV Pelletron. In terms of cost and size, the new system is a significant advance over previous technology. Details and performance of the new system will be presented.
id: 2103

Abrupt tropical vegetation response to rapid climate changes - Hughen, K. A.; Eglinton, T. I.; Xu, L.; Makou, M. (Science, 2004)
Identifying leads and lags between high- and low-latitude abrupt climate shifts is needed to understand where and how such events were triggered. Vascular plant biomarkers preserved in Cariaco basin sediments reveal rapid vegetation changes in northern South America during the last deglaciation, 15,000 to 10,000 years ago. Comparing the biomarker records to climate proxies from the same sediment core provides a precise measure of the relative timing of changes in different regions. Abrupt deglacial climate shifts in tropical and high-latitude North Atlantic regions were synchronous, whereas changes in tropical vegetation consistently lagged climate shifts by several decades.
Hughen, Konrad AEglinton, Timothy IXu, LiMakou, MatthewengResearch Support, Non-U.S. Gov't2004/05/25 05:00Science. 2004 Jun 25;304(5679):1955-9. Epub 2004 May 20.

Advective controls on the age of marine sedimentary organic matter - Mollenhauer, Gesine; Eglinton, Timothy I.; Hayes, John M. (Gordon Research Conference Organic Geochemistry, 2004)
id: 1068

AMS 14C measurement and preparative techniques at NIES-TERRA - Yoneda, Minoru; Shibata, Yasuyuki; Tanaka, Atsushi; Uehiro, Takashi; Morita, Masatoshi; Uchida, Masao; Kobayashi, Toshiyuki; Kobayashi, Chiaki; Suzuki, Ryo; Miyamoto, Keisuke; Hancock, Boze; Dibden, Chris; et al. (Nuclear Instruments and Methods in Physics Research B, 2004)
The AMS facility at the National Institute for Environmental Studies (NIES) has now been operating for five years since 1997. This AMS-dedicated facility named NIES-TERRA (Tandem accelerator for Environmental Research and Radiocarbon Analysis) consists of a 5MV tandem Pelletron (15SDH-2), a solid ion source with sequential injection system, a gas ion source with a simultaneous injection system, and a gas ionization detector. Typical precision with 14C measurements is around 0.5% and the background level has been achieved at around 50 kBP. Our main target is radiocarbon in environmental sciences, while other cosmogenic isotopes (10Be and 26Al) have been measured. Recently we have improved our preparation laboratory to increase sample throughput. CO2 production and purification using a commercial elemental analyzer connected to cryogenic traps (EA–CT) were investigated. We used a modified elemental analyzer with a chemical trap for separation and this is expected to reduce memory effect and background in comparison with an analyzer using gas-chromatography. This newly designed EA–CT system showed high precision and accuracy. Source of background contamination was also discussed based on the analysis of various amounts of standard materials.
id: 1492

Carbon-isotopic shifts associated with heterotrophy and biosynthetic pathways in direct- and indirect-developing sea urchins - Villinski, J. C.; Hayes, J. M.; Villinski, J. T.; Brassell, S. C.; Raff, R. A. (Marine Ecology Progress Series, 2004)
Natural abundances of C-13 were measured in bulk biomass and in individual lipids isolated from 2 species of sea urchins, Heliocidaris erythrogramma and H. tuberculata, and from calcareous and green benthic algae on which they were feeding. Planktonic larvae of H. erythrogramma are lecithotrophic whereas those of H. tuberculata are planktotrophic. The organisms were collected from a subtidal environment in Botany Bay, Sydney, Australia. The biomass of both consumers was enriched in C-13 relative to their diets by up to 1.8parts per thousand. The carbon skeletons of sterols from the urchins derive at least in part from de novo biosynthesis by the urchins. Depending on chain length and degree of unsaturation, carboxylic acids from the urchins derive from de novo blosynthesis (14:0, unsaturated acids), from the diet (18:0), or from both these sources (16:0). H. tuberculata synthesizes a greater distribution and proportion of unsaturated carboxylic acids. Odd-C and branched-chain carboxylic acids derive in part from bacterial sources and are enriched in C-13 relative to algal lipids and depleted relative to those in urchins. Only H. erythrogramma, which uses wax esters-as storage lipids in its relatively large and buoyant eggs, produces significant quantities of n-alkanols; n-alkanols in H, tuberculata derive from the diet. In terms of molecular distributions and isotopic compositions, the lipids in fecal matter from both heterotrophs resemble those of the diet rather than those of the urchins.
847vnTimes Cited:4Cited References Count:34

Chronology of sediment deposition in Upper Klamath Lake, Oregon - Colman, S. M.; Bradbury, J. P.; McGeehin, J. P.; Holmes, C. W.; Sarna-Wojcicki, A. M.; Edgington, D. (Journal of Paleolimnology, 2004)
A combination of tephrochronology and 14C, 210Pb, and 137Cs measurements provides a robust chronology for sedimentation in Upper Klamath Lake during the last 45 000 years. Mixing of surficial sediments and possible mobility of the radio-isotopes limit the usefulness of the 137Cs and 210Pb data, but 210Pb profiles provide reasonable average sediment accumulation rates for the last 100–150 years. Radiocarbon ages near the top of the core are somewhat erratic and are too old, probably as a result of detrital organic carbon, which may have become a more common component in recent times as surrounding marshes were drained. Below the tops of the cores, radiocarbon ages in the center of the basin appear to be about 400 years too old, while those on the margin appear to be accurate, based on comparisons with tephra layers of known age.Taken together, the data can be combined into reasonable age models for each site. Sediments have accumulated at site K1, near the center of the basin, about 2 times faster than at site CM2, on the margin of the lake. The rates are about 0.10 and 0.05 cm/yr, respectively. The chronological data also indicate that accumulation rates were slower during the early to middle Holocene than during the late Holocene, consistent with increasing wetness in the late Holocene.
id: 182

The CO2-He-Ar-H2O systematics of the Manus back-arc basin: Resolving source composition from degassing and contamination effects - Shaw, A. M.; Hilton, D. R.; Macpherson, C. G.; Sinton, J. M. (Geochimica Et Cosmochimica Acta, 2004)
We report new stepped heating He, Ar, CO2 and water data on a petrogenetically diverse suite of lavas from the Manus back-arc basin, where a plume component has previously been identified. The aim of this study is to evaluate the superimposed effects of degassing and contamination in order to identify mantle source characteristics. CO2 abundances and carbon isotopes in both the vesicle ([CO2] up to 180ppm; delta(13)C as low as -33.6 parts per thousand) and glass ([CO2] up to 270ppm; delta(13)C as low as -34.3parts per thousand) phases reveal that samples have been modified by varying degrees of degassing. High water concentration samples (back-arc basin basalts (BABB) and arc type samples) show the highest degrees of degassing (i.e. lower delta(13)C values and lower CO2 contents). The results are modelled for both the glass and vesicle phases using batch and fractional degassing models. Parental melt compositions can be constrained to show the following CO2 concentration trend: are-type > BABB s.r. (southern rift) > MORB-2, E-MORB, X-BABB (extreme BABB), BABB > MORB-1 and MORB-smt. He-4/Ar-40* ratios of samples (14.6-1100) are consistent with residual volatiles from a degassed source. Variations in CO2/(3) He values are likely due to degassing, followed by contamination from a crustal source (either the subducting Solomon Sea Plate or the pre-existing crust through which the lavas erupt), as evidenced by high K2O/TiO2 ratios and low delta(13)C. The CO2/(3) He of the Manus plume is best estimated by the MORB-smt and MORB-1 samples at 3.1 +/- 0.6 X 10(9). This value is similar to previous estimates of plume CO2/(3) He values, which are either equal to or slightly greater than the upper mantle average of 2 X 10(9). Copyright (C) 2004 Elsevier Ltd.
813fdTimes Cited:30Cited References Count:76

Comments on potential geologic and seismic hazards affecting coastal Ventura County, CCalifornia - Ross, S. D. Boore; Fisher, M.; Frankel, A.; Geist, E.; Hudnut, K.; Kayen, R.; Lee, H.; Normark, W. R.; Wong, F. (U. S. Geological Survey OFR 1004-1286, 2004)
id: 420

Compound-specific radiocarbon dating of the varved Holocene sedimentary record of Saanich Inlet, Canada - Smittenberg, R. H.; Hopmans, E. C.; Schouten, S.; Hayes, J. M.; Eglinton, T. I.; Damste, J. S. S. (Paleoceanography, 2004)
[1] The radiocarbon contents of various biomarkers extracted from the varve-counted sediments of Saanich Inlet, Canada, were determined to assess their applicability for dating purposes. Calibrated ages obtained from the marine planktonic archaeal biomarker crenarchaeol compared favorably with varve-count ages. The same conclusion could be drawn for a more general archaeal biomarker (GDGT-0), although this biomarker proved to be less reliable due to its less-specific origin. The results also lend support to earlier indications that marine crenarchaeota use dissolved inorganic carbon (DIC) as their carbon source. The average reservoir age offset DeltaR of 430 years, determined using the crenarchaeol radiocarbon ages, varied by +/-110 years. This may be caused by natural variations in ocean-atmosphere mixing or upwelling at the NE Pacific coast but variability may also be due to an inconsistency in the marine calibration curve when used at sites with high reservoir ages.
819piTimes Cited:18 Cited References Count:69
Keywords: british-columbia; compound-specific radiocarbon dating; crenarchaeol; ionization mass-spectrometry; marine-sediments; mediterranean sea; membrane-lipids; ne pacific; odp leg 169s; organic-matter; pacific-ocean; rapid isolation; Reservoir age; reservoir ages; saanich inlet

Dating the rise of atmospheric oxygen - Bekker, A.; Holland, H. D.; Wang, P. L.; Rumble, D.; Stein, H. J.; Hannah, J. L.; Coetzee, L. L.; Beukes, N. J. (Nature, 2004)
Several lines of geological and geochemical evidence indicate that the level of atmospheric oxygen was extremely low before 2.45 billion years (Gyr) ago, and that it had reached considerable levels by 2.22 Gyr ago. Here we present evidence that the rise of atmospheric oxygen had occurred by 2.32 Gyr ago. We found that syngenetic pyrite is present in organic-rich shales of the 2.32-Gyr-old Rooihoogte and Timeball Hill formations, South Africa. The range of the isotopic composition of sulphur in this pyrite is large and shows no evidence of mass-independent fractionation, indicating that atmospheric oxygen was present at significant levels (that is, greater than 10(-5) times that of the present atmospheric level) during the deposition of these units. The presence of rounded pebbles of sideritic iron formation at the base of the Rooihoogte Formation and an extensive and thick ironstone layer consisting of haematitic pisolites and oolites in the upper Timeball Hill Formation indicate that atmospheric oxygen rose significantly, perhaps for the first time, during the deposition of the Rooihoogte and Timeball Hill formations. These units were deposited between what are probably the second and third of the three Palaeoproterozoic glacial events.
id: 1534; Bekker, A Holland, H D Wang, P-L Rumble, D 3rd Stein, H J Hannah, J L Coetzee, L L Beukes, N J England Nature. 2004 Jan 8;427(6970):117-20.

Decline of surface temperature and salinity in the western tropical Pacific Ocean in the Holocene epoch - Stott, L.; Cannariato, K.; Thunell, R.; Haug, G. H.; Koutavas, A.; Lund, S. (Nature, 2004)
In the present-day climate, surface water salinities are low in the western tropical Pacific Ocean and increase towards the eastern part of the basin. The salinity of surface waters in the tropical Pacific Ocean is thought to be controlled by a combination of atmospheric convection, precipitation, evaporation and ocean dynamics, and on interannual timescales significant variability is associated with the El Nino/Southern Oscillation cycles. However, little is known about the variability of the coupled ocean-atmosphere system on timescales of centuries to millennia. Here we combine oxygen isotope and Mg/Ca data from foraminifers retrieved from three sediment cores in the western tropical Pacific Ocean to reconstruct Holocene sea surface temperatures and salinities in the region. We find a decrease in sea surface temperatures of approximately 0.5 degrees C over the past 10,000 yr, whereas sea surface salinities decreased by approximately 1.5 practical salinity units. Our data imply either that the Pacific basin as a whole has become progressively less salty or that the present salinity gradient along the Equator has developed relatively recently.
Stott, LowellCannariato, KevinThunell, RobertHaug, Gerald HKoutavas, AthanasiosLund, SteveengResearch Support, U.S. Gov't, Non-P.H.S.England2004/09/03 05:00Nature. 2004 Sep 2;431(7004):56-9.

Deep global cycling of carbon constrained by the solidus of anhydrous, carbonated eclogite under upper mantle conditions - Dasgupta, R.; Hirschmann, M. M.; Withers, A. C. (Earth and Planetary Science Letters, 2004)
We present partial melting experiments that constrain the near solidus phase relations of carbonated eclogite from 2 to 8.5 GPa. The starting material was prepared by adding 5 wt.% CO2 in the form of a mixture of Fe-Mg-Ca-Na-K carbonates to an eclogite from Salt Lake crater, Oahu, Hawaii and is a reasonable approximation of carbonated oceanic crust from which siliceous hydrous fluids have been extracted during subduction. Melt-present versus melt-absent conditions are distinguished based on textural criteria. Garnet and clinopyroxene appear in all the experiments. Between 2 and 3 GPa, the subsolidus assemblage also includes ilmenite+/-calcio-dolomite(ss)+/-CO2, whereas above the solidus (1050-1075 degreesC at 3 GPa) calcio-dolomitic liquid appears. From 3 to 4.5 GPa, dolomite(ss) is stable at the solidus and the near-solidus melt becomes increasingly dolomitic. The appearance of dolomite above 3 GPa is accompanied by a negative Clapeyron slope of the solidus, with a minimum located between 995 and 1025 degreesC at ca. 4 GPa. Above 4 GPa, the solidus rises with increasing pressure to 1245+35 degreesC at 8.5 GPa and magnesite becomes the subsolidus carbonate. Dolomitic melt coexists with magnesite+garnet+cpx+rutile along the solidus from 5 to 8.5 GPa.Comparison of our results to other recent experimental studies [T. Hammouda, High-pressure melting of carbonated eclogite and experimental constraints on carbon recycling and storage in the mantle, Earth Planet. Sci. Lett. 214 (2003) 357-368; G.M. Yaxley, G.P. Brey, Phase relations of carbonate-beating eclogite assemblages from 2.5 to 5.5 GPa: implications for petropnesis of carbonatites, Contrib. Mineral. Petrol. 146 (2004) 606-6191 shows that carbonate minerals are preserved in anhydrous or slightly hydrous carbonated eclogite to temperatures >1100 and >1200 degreesC at 5 and 9 GPa, respectively. Thus, deep subduction of carbonate is expected along any plausible subduction geotherm. If extrapolated to higher pressures, the carbonated eclogite solidus is likely to intersect the oceanic geotherm at a depth close to 400 km. Carbonated eclogite bodies entering the convecting upper mantle will thus release carbonate melt near the top of the mantle transition zone and may account for anomalously slow seismic velocities at depths of 280-400 km. Upon release, this small volume, highly reactive melt could be an effective agent of deep mantle metasomatism. Comparison of the carbonated eclogite solidus with that of peridotite-CO2 shows a shallower solidus-geotherm intersection for the latter. This implies that carbonated peridotite is a more likely proximal source of magmatic carbon in oceanic provinces. However, carbonated eclogite is a potential source of continental carbonatites, as its solidus crosses the continental shield geotherm at ca. 4 GPa. Transfer of eclogite-derived carbonate melt to peridotite may account for the geochemical characteristics of some oceanic island basalts (OIBs) and their association with high CaO and CO2. (C) 2004 Elsevier B.V. All rights reserved.
864qyTimes Cited:192Cited References Count:49

Deglacial history of the Ecuadorian Andes and implication for climate variations: Preliminary results - Hall, M.; Rinterknecht, V. R.; Schaefer, J. M.; R, Seager; Greene, A. (Eos Trans. AGU Fall Meeting Supplement, 2004)
id: 1003

Deglacial sea surface temperatures of the western tropical Pacific: A new look at old coral - Cohen, A. L.; Hart, S. R. (Paleoceanography, 2004)
Using Secondary Ion Mass Spectrometry ( SIMS) ion microprobe techniques, we generated annual Sr/Ca cycles with subweekly resolution from chunks of Porites coral retrieved from a Tahiti barrier reef drill core (149degreesW, 17degreesS), representing the period 13,650 to 13,100 years B.P. The centers of pristine skeletal septa were selectively targeted with a 10 mum diameter ion beam spot, avoiding adjacent pore spaces occupied by secondary aragonite needles. Applying a Sr/Ca-sea surface temperature (SST) calibration equation derived from modern Tahiti Porites having the same low growth rate as the fossil specimens, we obtained SSTs similar to0.5degrees-1.5degreesC cooler during the Bolling-Allerod relative to the present day, with no significant change in seasonality. On the contrary, we estimate that analysis of bulk samples would yield excessively cool Sr/Ca-based SST estimates due to the occupation by secondary aragonite crystals of up to 50% of the skeletal pore space in the ancient samples. We find that growth rate effects on coral Sr/Ca further depress the apparent mean annual derived SSTs (by >3degreesC) and amplify the apparent seasonality by selectively enhancing wintertime cooling. Our microscale analysis of pristine skeleton and application of an appropriate growth-dependent calibration yield Sr/Ca-derived SSTs that are in good agreement with those derived from Mg/Ca ratios of calcitic foraminifera which indicate a continuous postglacial warming of the western tropical Pacific, in phase with the warming of the tropical Atlantic.
885czTimes Cited:30 Cited References Count:37
Keywords: bolling-allerod; climate-change; coral sr/ca; diagenesis; ion microprobe; last deglaciation; paleotemperature proxy; radiocarbon; record; sea surface temperature; sr/ca; strontium; symbiotic coral; trace-elements; tropical pacific

Dynamics of tidal salt barren formation and the record of present-day sea level change - Hsieh, Y. P. (The Ecogeomorphology of Tidal Marshes, American Geophysical Union, 2004)
id: 1164

Episodic methane release events from Last Glacial marginal sediments in the western North Pacific - Uchida, M.; Shibata, Y.; Ohkushi, K.; Ahagon, N.; Hoshiba, M. (Geochemistry Geophysics Geosystems, 2004)
[1] According to recent observations of anomalous bottom-simulating reflections (BSR),the northwest Pacific marginal sediments around Japan main islands bear large abundances of methane hydrate [Satoh, 2002]. During the Last Glacial, direct and indirect evidence accumulated from geochemical data suggests that methane episodically released from hydrate trapped in the seafloor sediments [ Dickens et al., 1995; Hinrichs et al., 2003; Kennett et al., 2000]. Here we show that marginal sediments from the western North Pacific contain a hopanoid 17alpha( H), 21beta(H)-hop-22(29)-ene ( diploptene) derived from the activity of methanotrophic bacteria in water column and/or surface sediment during a warming period (Interstadial 3) in the Last Glacial. The carbon isotopic compositions of diploptene range between - 41.0parts per thousand and - 27.9parts per thousand ( relative to PDB). In the horizon indicative of a contribution of methanotrophic bacteria, foraminiferal isotope signals were also found with highly depleted C-13 compositions of planktonic foraminifera ( similar to - 1.9parts per thousand, PDB) and benthic foraminifera ( similar to - 0.8parts per thousand, PDB), suggesting indirect records of enhanced incorporation of C-13-depleted CO2 formed by methanotrophic process that use C-12-enriched methane as their main source of carbon. From combined isotopic data of molecular ( diploptene) and foraminifera, the most prominent signal of methane release was detected in the sediments deposited around 25.4 cal. kyr BP ( similar to 100 year time span), corresponding to the Interstadial 3. This is the first evidence of methane hydrate instability in the open western North Pacific during the Last Glacial. Considering the glacial-interglacial hydrographic conditions in this region, the instability of methane hydrate may be modulated by intermediate water warming and/or the lowering of sea level. Our results suggest that the western North Pacific marginal regions may be a profound effect on rapid global warming climate changes during the Last Glacial.
849mvTimes Cited:13 Cited References Count:73
Keywords: atmospheric composition and structure : geochemical cycles; atmospheric methane; carbon isotopes; carbon isotopic fractionation; climate-change; cold seeps; diploptene; Foraminifera; gas-hydrate; geochemistry : isotopic composition/chemistry; geochemistry : organic geochemistry; hydrocarbons; interglacial; intermediate water; methane hydrate; santa-barbara basin; sea sediments; subduction zone; western north pacific

Evidence for Late Holocene earthquakes on the Utsalady Point Fault, northern puget lowland, Washington - Johnson, S. Y.; Nelson, A. R.; Personius, S. F.; Wells, R. E.; Kelsey, H. N.; Sherrod, B. L.; Okumura, K.; Koehler, R.; Witter, R. C.; Bradley, L. A.; Harding, D. J. (Bulletin of the Seismological Society of America, 2004)
Trenches across the Utsalady Point fault in the northern Puget Lowland of Washington reveal evidence of at least one and probably two late Holocene earthquakes. The "Teeka"' and "Duffers" trenches were located along a 1.4-km-long. 1- to 4-m-high, northwest-trending, southwest-facing. topographic scarp recognized from Airborne Laser Swath Mapping. Glaciomarine drift exposed in the trenches reveals evidence of about 95 to 150 cm of vertical and 200 to 220 cm of left-lateral slip in the Teeka trench. Radiocarbon ages from a buried soil A horizon and overlying slope colluvium alone, with the historical record of earthquakes suggest that this faulting occurred 100 to 400 calendar years B.P. (A.D. 1550 to 1850). In the Duffers trench, 370 to 450 cm of vertical separation is accommodated by faulting (similar to210 cm) and folding (similar to160 to 240 cm), with probable but undetermined amounts of lateral slip. Stratigraphic relations and radiocarbon ages from buried soil, colluvium. and fissure fill in the hanging wall suggest the deformation at Duffers is most likely from two earthquakes that occurred between 100 to 500 and 1100 to 2200 calendar years B.P., but deformation during a single earthquake is also possible. For the two-earthquake hypothesis, deformation at Teeka trench in the first event involved folding but not faulting. Regional relations suggest that the earthquake(s) were M greater than or equal to similar to6.7 and that offshore rupture may have produced tsunamis. Based on this investigation and related recent studies, the maximum recurrence interval for large ground-rupturing crustal-fault earthquakes in the Puget Lowland is about 400 to 600 years or less.
887giTimes Cited:18Cited References Count:46

A gas ion source for continuous-flow AMS - Schneider, R. J.; Kim, S. W.; von Reden, K. F.; Hayes, J. M.; Wills, J. S. C.; Griffin, V. S.; Sessions, A. L.; Sylva, S. (Proceedings of the Ninth International Conference on Accelerator Mass Spectrometry, 2004)
The first gas-fed ion source for radiocarbon AMS applications (without sputtering) has been operated at the Woods Hole NOSAMS Facility. A three-year, off-line test program resulted in positive carbon ion currents up to 1 mA and negative ion currents up to 80 μA. Recently, the compact, permanent-magnet microwave plasma ion source and magnesium vapor charge-exchange canal were coupled to the recombinator injector of the 2.5 MV Tandetron. When the ion source was operated on CO2 at a flow rate of about 200 μl per minute, negative carbon ion beams up to 20 μA were obtained, at an energy of 35 keV. Radiocarbon measurements were performed on standard reference gases and the dynamic response to square-wave pulses of gas was determined. Time constants in the ion source are less than 1 s, which should allow analysis of chromatographic peaks of CO2 with very little broadening. A combustion device has been constructed to generate CO2 for direct injection into the source. Argon carrier gas is used to buffer the pressure at one atmosphere in the sample gas injector. A dedicated ion-beam injector, with higher angular acceptance and higher transmitted currents, is being constructed for the AMS system.
id: 2104

Holocene fault scarps near Tacoma, Washington, USA - Sherrod, B. L.; Brocher, T. M.; Weaver, C. S.; Bucknam, R. C.; Blakely, R. J.; Kelsey, H. M.; Nelson, A. R.; Haugerud, R. (Geology, 2004)
Airborne laser mapping confirms that Holocene active faults traverse the Puget Sound metropolitan area, northwestern continental United States. The mapping, which detects forest-floor relief of as little as 15 cm, reveals scarps along geophysical lineaments that separate areas of Holocene uplift and subsidence. Along one such line of scarps, we found that a fault warped the ground surface between A.D. 770 and 1160. This reverse fault, which projects through Tacoma, Washington, bounds the southern and western sides of the Seattle uplift. The northern flank of the Seattle uplift is bounded by a reverse fault beneath Seattle that broke in A.D. 900-930. Observations of tectonic scarps along the Tacoma fault demonstrate that active faulting with associated surface rupture and ground motions pose a significant hazard in the Puget Sound region.
765ehTimes Cited:50Cited References Count:22

Holocene relative sea-level history of the Southern Victoria Land Coast, Antarctica - Hall, B. L.; Baroni, C.; Denton, G. H. (Global and Planetary Change, 2004)
More than 130 radiocarbon dates of penguin remains and guano, sealskin, shells, and seaweed from raised beach ridges afford relative sea-level information for southern Victoria Land. A new relative sea-level curve suggests that the final unloading of grounded ice from the coast took place about 6600 C-14 years BP, in keeping with previous estimates of the timing of deglaciation. Since this time, the coast has experienced 32 m of relative sea-level fall at rates ranging from 2 to 15 mm/year, consistent with glacioisostatic rebound. (C) 2004 Elsevier B.V. All rights reserved.
845idTimes Cited:40Cited References Count:25

Isotopic order, biogeochemical processes, and earth history - Goldschmidt Lecture, Davos, Switzerland, August 2002 - Hayes, J. M. (Geochimica Et Cosmochimica Acta, 2004)
The impetus to interpret carbon isotopic signals comes from an understanding of isotopic fractionations imposed by living organisms. That understanding rests in turn on studies of enzymatic isotope effects, on fruitful concepts of isotopic order, and on studies of the distribution of (13)C both between and within biosynthetic products. In sum, these studies have shown that the isotopic compositions of biological products are governed by reaction kinetics and by pathways of carbon flow.Isotopic compositions of individual compounds can indicate specific processes or environments. Examples include biomarkers which record the isotopic compositions of primary products in aquatic communities, which indicate that certain bacteria have used methane as a carbon source, and which show that some portions of marine photic zones have been anaerobic. In such studies, the combination of structural and isotopic lines of evidence reveals relationships between compounds and leads to process-related thinking. These are large steps. Reconstruction of the sources and histories of molecular fossils redeems much of the early promise of organic geochemistry by resolving and clarifying paleoenviron-mental signals. In turn, contemplation of this new information is driving geochemists to study microbial ecology and evolution, oceanography, and sedimentology. Copyright (C) 2004 Elsevier Ltd.
813fdTimes Cited:17Cited References Count:70

A late Pleistocene-Holocene noble gas paleotemperature record in southern Michigan - Ma, L.; Castro, M. C.; Hall, C. M. (Geophysical Research Letters, 2004)
Noble gas temperatures (NGTs) and C-14 derived ages in groundwaters of the Michigan Basin reveal a ground temperature of similar to1degreesC toward the end of the Last Glacial Maximum (LGM) suggesting that groundwater recharge occurred under the Laurentide Ice Sheet (LIS) cover. In addition to the general warming observed since the LGM, the NGT record indicates an abrupt warming event between similar to12.8 and 11.1 kyrs BP, correlative to the Bolling-Allerod (BOA) warm phases. Ice-sheet-linked changes in freshwater delivery to the North Atlantic, together with changes in the North Atlantic Deep Water (NADW) circulation are possible causes of such abrupt climate shifts in northeastern US. Pleistocene waters yielding the lowest NGTs have the highest delta(18)O and deltaD values, suggesting an atmospheric circulation pattern distinct from today, with a stronger moisture component from the Gulf of Mexico, possibly due to the presence of the LIS which weakened the Pacific westerly flow.
881pcTimes Cited:31Cited References Count:24

Mantle Samples Included in Volcanic Rocks: Xenoliths and Diamonds - Pearson, D. G.; Canil, D.; Shirey, S. B. (Treatise on Geochemistry, 2004)
id: 1575

A new Holocene relative sea-level curve for Terra Nova Bay, Victoria Land, Antarctica - Baroni, C.; Hall, B. L. (Journal of Quaternary Science, 2004)
More than 100 radiocarbon dates of penguin guano and remains, shells and seal skin afford ages for raised beaches adjacent to Terra Nova Bay, Antarctica. These dates permit construction of a new relative sea-level curve that bears on the timing of deglaciation. Recession of the Ross Sea ice-sheet grounding line from Terra Nova Bay occurred no earlier than 7200 C-14 yr (8000 cal. yr) BP. Retreat along the Victoria Land coast may have been rapid, possibly contributing to eustatic sea-level rise centred at ca. 7600 cal. yr BP. The presence of a significant amount of ice remaining in the Ross Sea Embayment in Holocene time lessens the chance that Antarctica contributed significantly to meltwater pulse 1A several thousand years earlier. Copyright (C) 2004 John Wiley Sons, Ltd.
833xiTimes Cited:38Cited References Count:36

NotCal04-Comparison/Calibration 14 C records 26-50 cal kBP - van der Plicht, J.; Beck, J. W.; Bard, E.; Baillie, M. G. L.; Blackwell, P. G.; Buck, C. E.; Friedrich, M.; Guilderson, T. P.; Hughen, K. A.; Kromer, B. (Radiocarbon, 2004)
id: 399

Phylogenetically specific spearation of rRNA from prokaryotes for isotopic analysis - Pearson, Ann; Sessions, Alex L.; Edwards, Katrina J.; Hayes, John M. (Marine Chemistry, 2004)
id: 1805

Plans for Expanded 14C Analyses at the NOSAMS Facility--a status and progress report. 9th International Conference on Accelerator Mass Spectrometry, Nagoya, Japan, 9/2002 - von Reden, K.; Donoghue, J.; Elder, K.; Gagnon, A.; Gerlach, D.; Griffin, V. S.; Healy, R.; Long, P.; McNichol, A. P.; Percy, D.; Roberts, M. L.; Schneider, R. J.; et al. (Nuclear Instruments and Methods in Physics Research, 2004)
id: 1810

Prehistoric marine mammal overkill in the northeastern Pacific: A review of new evidence - Jones, T. L.; Hildebrandt, W. R.; Kennett, D. J.; Porcasi, J. J. (Journal of California and Great Basin Anthropology, 2004)
id: 469

Radiocarbon ages of marine bimarkers and co-occurring foraminifera: evidence for differential particle transport on continental margins, Poster - Mollenhauer, Gesine; Eglinton, Timothy I.; Hayes, John M.; Kienast, Markus; Lamy, Frank; Meggers, Helge; Schneider, Ralph R. (Eighth International Conference on Palaeoceanography, 2004)
id: 549

Sampling Mantle Heterogeneity through Oceanic Basalts: Isotopes and Trace Elements - Hofmann, A. W. (Treatise on Geochemistry, 2004)
id: 1525

Sensitivity of present and future surface temperatures to precipitation characteristics - Lynn, Barry H.; Druyan, Leonard; Hogrefe, Christian; Dudhia, Jimy; Rosenzweig, Cynthia; Goldberg, Richard; Rind, David; Healy, Richard; Rosenthal, Joyce; Kinney, Patrick (Climate Research, 2004)
A model simulation study shows that different diurnal cycles of precipitation are consistent with radically different present and future climate characteristics. In projected future climate scenarios, divergence in the time of day and type of precipitation had very divergent impacts on the radiation balance and consequently on surface temperatures. The relationship between the diurnal cycle of precipitation versus the present and future climate was examined using the GISS-MM5 (Goddard Institute for Space Studies Mesoscale Model 5) regional climate modeling system with 2 alternative moist convection schemes. June-August (JJA) mean surface temperatures of the 1990s, 2050s, and 2080s were simulated over the eastern US on a double nested 108/36 km domain, with the 36 km domain centered over the eastern US. In the 1990s, one model version simulated maxima in (convective) precipitation during the early morning, while the second model simulated the hour of precipitation maxima with considerable spatial variability (in better agreement with observations). In the futuristic climate scenarios, differences in the time of day of precipitation had very important impacts on the radiation balance at the surface. One version gave more precipitation at night and fewer clouds during the day, promoting higher surface temperatures. The alternative version created more precipitation during the day, consistent with diminished absorption of solar radiation at the surface and consequently lower surface temperatures. The results demonstrate the importance of improving cumulus parameterizations in regional mesoscale and global climate models and suggest that such improvements would lead to greater confidence in model projections of climate change.
id: 1696

Stable carbon isotope ratios in lake and swamp sediments as a proxy for prehistoric forest clearance and crop cultivation in the Neotropics - Lane, C. S.; Horn, S. P.; Mora, C. I. (Journal of Paleolimnology, 2004)
Close correspondence between stable carbon isotope ratios (delta(13)C), pollen, and charcoal profiles in sediment cores from Laguna Zoncho and Machita swamp, Costa Rica, shows that prehistoric forest clearance and crop cultivation can be detected in the stable carbon isotope ratios of total organic carbon (delta(13)C(TOC)). Analyses of delta(13)C(TOC) complement evidence from pollen, charcoal, and phytoliths and provide a proxy that is sensitive to the intensity and/or proximity to core sites of prehistoric forest clearance and agriculture in watersheds. Stable carbon isotope analyses are particularly useful in situations in which other evidence of forest clearance and agriculture is limited.
881ycTimes Cited:30Cited References Count:36

Temporal variability of Delta 14C, delta13C, and C/N in sinking particulate organic matter at a deep time series station in the northeast Pacific Ocean - Hwang, Jeomshik; Druffel, Ellen R. M.; Griffin, Sheila; L, Smith Kenneth, Jr.; Baldwin, Roberta J.; Bauer, James E. (Global Biogeochemical Cycles, 2004)
id: 531

Vegetation and climate changes around the Lama Lake, Taymyr Peninsula, Russia during the Late Pleistocene and Holocene - Andreev, A.A.; Tarasov, P.E.; Klimanov, V.A.; Melles, M.; Lisitsyna, O.M.; Hubberten, H.-W. (HIgh resolution lake sediment records in climate and Environment variability studies:European lake drilling program, 2004)
A continuous lacustrine sequence from the western part of Lama Lake (69°32′N, 90°12′E), complemented by a peat sequence from the lake catchment provides the first detailed environmental reconstruction for the Late Glacial and Holocene on the Taymyr Peninsula. Scarce steppe-like communities with Artemisia, Poaceae, and Cyperaceae dominated during the Late Glacial. Tundra-like communities with Betula nana, Dryas, and Salix grew on more mesic sites. There are distinct climatic signals, which may be correlated with the Bølling and Allerød warming and Middle and Younger Dryas cooling. The Late Glacial/Preboreal transition, at about 10,000 14C yr BP, was characterized by changes from predominantly open herb communities to shrub tundra ones. Larch forest might have been established as early as 9700–9600 14C yr BP, whilst shrub alder came to the area ca 9500–9400 14C yr BP, and spruce did not reach area before ca 9200 14C yr BP. Spruce-larch forests with shrub alder and tree birch dominated the vegetation around the Lama Lake from ca 9000 14C yr BP. Dwarf birch communities were also broadly distributed. The role of spruce in the forest gradually decreased after 4500 14C yr BP. The vegetation cover in the Lama Lake area became similar to the modern larch-spruce forest ca 2500 14C yr BP. A pollen-based biome reconstruction supports a quantitative interpretation of the pollen spectra. Climate reconstructions obtained with information-statistical and plan-functional-type methods show very similar trends in reconstructed July temperature since ca 12,300 14C yr BP, while precipitation anomalies are less coherent, especially during the Late Glacial–Holocene transition.

Ventilation of the glacial deep Pacific Ocean - Broecker, W.; Barker, S.; Clark, E.; Hajdas, I.; Bonani, G.; Stott, L. (Science, 2004)
Measurements of the age difference between coexisting benthic and planktic foraminifera from western equatorial Pacific deep-sea cores suggest that during peak glacial time the radiocarbon age of water at 2-kilometers depth was no greater than that of today. These results make unlikely suggestions that a slowdown in deep-ocean ventilation was responsible for a sizable fraction of the increase of the ratio of carbon-14 (14C) to carbon in the atmosphere and surface ocean during glacial time. Comparison of 14C ages for coexisting wood and planktic foraminifera from the same site suggests that the atmosphere to surface ocean 14C to C ratio difference was not substantially different from today's.
Broecker, WallaceBarker, StephenClark, ElizabethHajdas, IrkaBonani, GeorgesStott, Lowelleng2004/11/13 09:00Science. 2004 Nov 12;306(5699):1169-72.

14C activity and global carbon cycle changes over the past 50,000 years - Hughen, K. A.; Lehman, S. J.; Southon, J.; Overpeck, J. T.; Marchal, O.; Herring, C.; Turnbull, J. (Abstracts, 18th International Radiocarbon Conf., 2003)
id: 1079

Acceptance of the 2002 V. M. Goldschmidt Award - Hayes, J. M. (Geochimica Et Cosmochimica Acta, 2003)
693mfTimes Cited:0Cited References Count:0

Analog for Holocene and future Climate? - McManus, J. F.; Oppo, D. W.; Cullen, J. L.; Healey, S. L. (Geophysical Monograph 137, Earth's Climate and Orbital Eccentricity: The Marine Isotope State 11 Questions, 2003)
id: 1166

Climate and the collapse of Mayan civilization - Haug, G. H.; Gunther, D.; Peterson, L. C.; Sigman, D. M.; Hughen, K. A. (Science, 2003)
id: 556

COMPARE04-Comparison/calibration of 14C records 26-50 ka - van der Plicht, J.; Hughen, K. A.; Guilderson, T. P.; Reimer, P. (Abstracts, 18th International Radiocarbon Conf., 2003)
id: 564

Compound specific radiocarbon dating of alkenones: methodological considerations and applications in paleoceanography - Mollenhauer, Gesine; Eglinton, Timothy I.; Schneider, Ralph R.; Meggers, Helge; Lamy, Frank; Ohkouchi, Nao; Hayes, John M. (18th International Radiocarbon Conference, 2003)
id: 1070

Continuous-Flow Accelerator Mass Spectrometry - Roberts, M. L.; Benthien, A.; Schneider, R. J.; von Reden, K. F.; Hayes, J. M. (International Symposium on Radiation Physics, 2003)
id: 1683

Contrasting He-C relationships in Nicaragua and Costa Rica: insights into C cycling through subduction zones - Shaw, A. M.; Hilton, D. R.; Fischer, T. P.; Walker, J. A.; Alvarado, G. E. (Earth and Planetary Science Letters, 2003)
We report He-3/He-4 ratios, relative He, Ne, and CO2 abundances as well as delta(13)C values for volatiles from the volcanic output along the Costa Rica and Nicaragua segments of the Central American arc utilising fumaroles, geothermal wells, water springs and bubbling hot springs. CO2/He-3 ratios are relatively constant throughout Costa Rica (av. 2.1 X 10(10)) and Nicaragua (av. 2.5 X 10(10)) and similar to arcs worldwide (similar to1.5 X 10(10)). delta(13)C values range from -6.8parts per thousand (MORB-like) to -0.1parts per thousand (similar to marine carbonate (0parts per thousand)). He-3/He-4 ratios are essentially MORB-like (8 +/- R-A) with some samples showing evidence of crustal He additions - water spring samples are particularly susceptible to modification. The He-CO2 relationships are consistent with an enhanced input of slab-derived C to magma sources in Nicaragua ((L+S)/M = 16; where L, M and S represent the fraction of CO2 derived from limestone and/or marine carbonate (L), the mantle (M) and sedimentary organic C (S) sources) relative to Costa Rica ((L+S)/M = 10). This is consistent with prior studies showing a higher sedimentary flux to the arc volcanics in Nicaragua (as traced by Ba/La, Be-10 and La/Yb). Possible explanations include: (1) offscraping of the uppermost sediments in the Costa Rica forearc, and (2) a cooler thermal regime in the Nicaragua subduction zone, preserving a higher proportion of melt-inducing fluids to subarc depths, leading to a higher degree of sediment transfer to the subarc mantle. The absolute flux Of CO2 from the Central American arc as determined by correlation spectrometry methods (5.8 X 10(10) mol/yr) and CO2/He-3 ratios (7.1 X 10(10) mol/yr) represents approximately 14-18% of the amount of CO2 input at the trench from the various slab contributors (carbonate sediments, organic C, and altered oceanic crust). Although the absolute flux is comparable to other arcs, the efficiency Of CO2 recycling through the Central American are is surprisingly low (14-18% vs. a global average of similar to50%). This may be attributed to either significant C loss in the forearc region, or incomplete decarbonation of carbonate sediments at subarc depths. The implication of the latter case is that a large fraction of C (up to 86%) may be transferred to the deep mantle (depths beyond the source of arc magmas). (C) 2003 Elsevier B.V. All rights reserved.
725paTimes Cited:98Cited References Count:50

Cosmochemical Estimates of Mantle Composition - Palme, H.; O'Neill, H. St C. (Treatise on Geochemistry, 2003)
id: 1583

Ecosystem modulation of dissolved carbon age in a temperate marsh-dominated estuary - Raymond, P. A.; Hopkinson, C. S. (Ecosystems, 2003)
We measured the concentrations and isotopic values (Delta(14)C and delta(13)C) of dissolved inorganic, dissolved organic, and particulate organic carbon (DIC, DOC, and POC, respectively) in the Parker River watershed and estuary in Massachusetts, USA, to determine the age of carbon (C) entering the estuary and how estuarine processing affects the quantity and apparent age of C transported to the Gulf of Maine. The watershed measurements indicated the transport of Delta(14)C-enriched modern DIC and DOC and variably aged POC from the watershed to the estuary. The transport of organic matter from the watershed was dominated by DOC transport, with POC making up less than 10% of the total. Surveys within the watershed aimed at determining which land-use type dominated the DOC export indicated that wetlands, although they made up only around 20% of the land use, could be responsible for approximately 75% of the DOC export. We therefore conclude that the wetland land uses of the Parker River watershed are exporting mainly Delta(14)C-enriched modem DOC. DIC isotopes indicate that the source of DIC in the Parker River watershed is dominated by the weathering of noncarbonate parent material by Delta(14)C-enriched carbon dioxide (CO2) originating from the respiration of young organic matter in soils. Transects in the estuary displayed net additions of all C species. For DOC and DIC, the export of this internally added DOC and DIC was approximately equal to the amount being exported from the watershed, showing the importance of focusing on estuaries when estimating the export of C to the coastal ocean. With respect to DIC, the total input is even larger when the atmospheric exchange of excess PCO2 is calculated. The Delta(14)C -DOC and Delta(14)C-DIC transects indicate that the internally added DOC and DIC is Delta(14)C-enriched modern material. The source of this material is the fringing marshes and estuarine phytoplankton, with the relative importance of these two sources changing over time. Taken together, the bulk C and Delta(14)C measurements show that the estuary is adding significant quantities of young DOC despite the presence of vast quantities of old marsh peat flanking the entire estuary. Furthermore, the DIC data indicate that Delta(14)C-enriched modern material is what is fueling the majority of heterotrophic respiration within the system.
746zrTimes Cited:42Cited References Count:73

Evolution of Sedimentary Rocks - Veizer, J.; Mackenzie, F. T. (Treatise on Geochemistry, 2003)
id: 1604

Geochemistry of hydrothermally altered oceanic crust: DSDP/ODP Hole 504B - Implications for seawater-crust exchange budgets and Sr- and Pb-isotopic evolution of the mantle - Bach, Wolfgang; Peucker-Ehrenbrink, Bernhard; Hart, STanly R.; Blusztajn, Jerzy S. (Geochemistry, Geophysics, Geosystems G3, 2003)
id: 1536

Isotopic and geochemical assessment of in situ biodegradation of chlorinated hydrocarbons - Kirtland, B. C.; Aelion, C. M.; Stone, P. A.; Hunkeler, D. (Environ Sci Technol, 2003)
Currently there is no in situ method to detect and quantify complete mineralization of chlorinated hydrocarbons (CHCs) to CO2. Combined isotopic measurements in conjunction with traditional chemical techniques were used to assess in situ biodegradation of trichloroethylene (TCE) and carbon tetrachloride (CT). Vadose zone CHC, ethene, ethane, methane, O2, and CO2 concentrations were analyzed using gas chromatography over 114 days at the Savannah River Site. delta13C of CHC and delta13C and 14C of vadose zone CO2, sediment organic matter, and groundwater dissolved inorganic carbon (DIC)were measured. Intermediate metabolites of TCE and CT accounted for < or = 10% of total CHCs. Delta13C of cis-1,2-dichloroethylene (DCE) was always heavier than TCE indicating substantial DCE biodegradation. 14C-CO2 values ranged from 84 to 128 percent modern carbon (pMC), suggesting that plant root-respired CO2 was dominant. 14C-CO2 values decreased over time (up to 12 pMC), and contaminated groundwater 14C-DIC (76 pMC) was substantially depleted relative to the control (121 pMC). 14C provided a direct measure of complete CHC mineralization in vadose zone and groundwater in situ and may improve remediation strategies.
Kirtland, Brian CAelion, C MarjorieStone, Peter AHunkeler, DanielengResearch Support, Non-U.S. Gov'tResearch Support, U.S. Gov't, Non-P.H.S.2003/10/04 05:00Environ Sci Technol. 2003 Sep 15;37(18):4205-12.

Lipid-Like material as the source of the uncharacterized organic carbon in the ocean? - Hwang, Jeomshik; Druffel, Ellen R. M. (Science, 2003)
id: 530

Mantle Volatiles--Distribution and Consequences - Luth, R. W. (Treatise on Geochemistry, 2003)
id: 1597

Map and data for Quaternary faults and folds in Washington State - Lidke, D. J.; Johnson, S. Y.; McCory, P. A.; Personius, S. F.; Nelson, A. R.; Dart, R. L.; Bradley, L. A.; Haller, K. M.; Machette, M. N. (Geological Survey Open-File Report, 2003)
id: 997

Maps and data from a trench investigation of the Utsalady Point fault, Whidbey Island, Washington - Johnson, S. Y.; Nelson, A. R.; Personius, S. F.; Wells, R. E.; Kelsey, H. M.; Sherrod, B. L.; Okumura, K.; Koehler, R., III; Witter, R. C.; Bradley, L. A.; Harding, D. J. (U. S. Geological Survey Miscellaneous Field Studies, 2003)
id: 996

Mid-holocene climate change in Lake Bosumtwi, Ghana - Russell, J.; Talbot, M. R.; Haskell, B. J. (Quaternary Research, 2003)
Lake Bosumtwi is one of the most widely studied palaeoclimate archives in West Africa. Results from numerous AMS C-14 dates of samples from four piston cores from Lake Bosumtwi show that an abrupt sedimentary transition from a mid-Holocene sapropel to calcareous laminated muds occurred at about 3200 cal yr B.P. High-resolution analyses of the nitrogen isotopic composition of organic matter across this transition confirm its abrupt nature, and suggest that the change may signal a step toward increased aridity and intensified surface winds that affected western equatorial Africa from Ghana to the Congo basin. Northern and Eastern Africa experienced a similar abrupt shift toward aridity during the late Holocene, but at about 5000 cal yr B.P., a difference in timing that illustrates the regional nature of climate changes during the Holocene and the importance of feedback mechanisms in regulating Holocene climate variability. Furthermore, an abrupt change at about 3000 cal yr B.P. occurs at several sites adjacent to the tropical and subtropical Atlantic, which may hint at major changes in the surface temperatures of the tropical Atlantic and/or Pacific at this time. (C) 2003 University of Washington. Published by Elsevier Inc. All rights reserved.
716arTimes Cited:43Cited References Count:39

Modeling the d180 in precipitation over the Americas: 1. Simulation of the stable isotope in Andean ice cores - Vuille, M.; Bradley, R. S.; Healy, R.; Werner, M.; Handy, D. R.; Thompson, L. G.; Keimig, F. (JGR, 2003)
id: 1771

Modeling the d18O in precipitation over the Americas: 1. Simulation of the stable isotope in Andean ice cores - Vuille, M.; Bradley, R. S.; Healy, R.; Werner, M.; Hardy, D. R.; Thompson, L. G.; Keimig, F. (JGR, 2003)
id: 1691

Modeling the d18O in precipitation over the Americas: 2. Interannual variability and climatic controls - Vuille, M.; Bradley, R. S.; Werner, M.; Healy, R.; Keimig, F. (JGR, 2003)
id: 1692

Penetration of anthropogenic carbon into organic particles of the deep ocean - Druffel, E. R. M.; Bauer, J. E.; Griffin, S.; Hwang, J. (Geophysical Research Letters, 2003)
[1] In the late 1980s, bomb C-14 was present in suspended particulate organic carbon (POC) from the North Central Pacific (NCP) and Sargasso Sea ( SS) throughout most of the water column, demonstrating that deep POC had exchanged with atmospheric CO2 in the past 30 years. Upon reoccupation of these sites in 1999 and 2000, respectively, we observed that the delta(13)C values of suspended POC were lower than those measured a decade earlier. This demonstrates that anthropogenic CO2 from fossil fuel and biomass burning has penetrated a major organic matter pool in the deep ocean. Delta(14)C measured in the suspended POC showed similar or higher values in the deep Sargasso Sea and decreased values in the deep NCP compared to those measured previously. We use a box model to show that the differences in the radiocarbon results are likely due to the presence of resuspended sediment that is laterally advected from the continental margin to the deep Sargasso Sea.
709dpTimes Cited:12 Cited References Count:29
Keywords: bomb radiocarbon; C-14; CO2; delta-c-13; MATTER; NORTH PACIFIC-OCEAN; SARGASSO SEA; Sediment; variability; water

The persistence of memory: The fate of ancient sedimentary organic carbon in a modern sedimentary system - Blair, N. E.; Leithold, E. L.; Ford, S. T.; Peeler, K. A.; Holmes, J. C.; Perkey, D. W. (Geochimica Et Cosmochimica Acta, 2003)
The cycle of organic carbon burial and exhumation moderates atmospheric chemistry and global climate over geologic timescales. The burial of organic carbon occurs predominantly at sea in association with clay-sized particles derived from the erosion of uplifted continental rocks. It follows that the history of the fine-grained particles on land may bear on the nature of the organic carbon buried. In this study, the evolution of clay-associated organic matter was followed from bedrock source to the seabed in the Eel River sedimentary system of northern California using natural abundance C-13 and C-14 tracers. Approximately half of the fine-grained organic carbon delivered to the shelf is derived from ancient sedimentary organic carbon found in the uplifted Mesozoic-Tertiary Franciscan Complex of the watershed. The short residence time of friable soils on steep hill slopes, coupled with rapid sediment accumulation rates on the shelf-slope, act to preserve the ancient organic carbon. A comparable quantity of modem organic carbon is added to particles in the watershed and on the shelf and slope. The bimodal mixture of ancient and modem C in soils and sediments may be characteristic of many short, mountainous rivers. If the Eel River chemistry is typical of such rivers, more than 40 Tg of ancient organic C may be delivered to the world's oceans each year. A flux of that magnitude would have a significant influence on marine and global C-cycles. Copyright (C) 2003 Elsevier Science Ltd.
634jvTimes Cited:143Cited References Count:63

Radiocarbon ages of marine biomarkers and co-occurring foraminifera: evidence for differential particle transport on continental margins - Mollenhauer, Gesine; Eglinton, Timothy I.; Hayes, John M.; Keinast, Markus; Lamy, Frank; Meggers, Helge; Schneider, Ralph R. (AGU Fall Meeting 2003, 2003)
id: 1069

Radiocarbon dating of individual fatty acids as a tool for refining Antarctic margin sediment chronologies - Ohkouchi, N.; Eglinton, T. I.; Hayes, J. M. (Radiocarbon, 2003)
We have measured the radiocarbon contents of individual, solvent-extractable, short-chain (C-14, C-16, and C-18) fatty acids isolated from Ross Sea surface sediments. The corresponding C-14 ages are equivalent to that of the post-bomb dissolved inorganic carbon (DIC) reservoir. Moreover, molecular C-14 variations in surficial (upper 15 cm) sediments indicate that these compounds may prove useful for reconstructing chronologies of Antarctic margin sediments containing uncertain (and potentially variable) quantities of relict organic carbon. A preliminary molecular C-14 chronology suggests that the accumulation rate of relict organic matter has not changed during the last 500 C-14 yr. The focus of this study is to determine the validity of compound-specific C-14 analysis as a technique for reconstructing chronologies of Antarctic margin sediments.
735tqTimes Cited:25 Cited References Count:29
Keywords: carbon; ice-sheet; marine-sediments; north-atlantic; organic-matter; ross-sea; southern-ocean

Soil-productivity relationships and organic matter turnover in dry tropical forests of the Florida Keys - Ross, M. S.; Coultas, C. L.; Hsieh, Y. P. (Plant and Soil, 2003)
Soils and aboveground production in five types of upland forest in the Florida Keys were examined. Throughout the habitat gradient represented by these forest types, the soils were predominantly shallow and organic, forming in place directly on the limestone bedrock. However, the well-drained soils in the most productive broadleaved forests were deep enough to qualify as Histosols (Folists). Soils decreased in electrical conductivity and increased in nutrient content with increasing aboveground production. At 3-12 Mg ha(-1) yr(-1), production was within the range reported for dry tropical forests. Measured rates of decomposition were moderate or fast, and estimates of the organic C turnover of several soils based on their bomb radiocarbon signature were 100 years or less. In the face of these rapid turnover rates, we attribute the development of organic soils to the absence of mineral residues from weathering of the underlying limestone bedrock. Fast turnover of organic matter, and rapid and efficient cycling of nutrients are necessary to sustain the high production rates obtained on these shallow organic soils.
702ymTimes Cited:12Cited References Count:46

The 14C AMS system at the University of Georgia - Roberts, M. L.; Culp, R. A.; Dvoracek, D. K.; Hodgins, G. W. L.; Neary, M. P.; Noakes, J. E. (International Conference on Accelerator Mass Spectrometry, 2002)
id: 1684

A 4000-Year Lacustrine Record of Environmental Change in the Southern Maya Lowlands, Petén, Guatemala - Rosenmeier, Michael F.; Hodell, David A.; Brenner, Mark; Curtis, Jason H.; Guilderson, Thomas P. (Quaternary Research, 2002)
A 4000-yr sediment core record from Lake Salpetén, Guatemala, provides evidence for Maya-induced forest clearance and consequent soil erosion between ∼1700 cal yr B.C. and 850 cal yr A.D. Radiocarbon ages of wood, seeds, and charcoal support an age-depth model with average errors of ±110 cal yr. Relatively low carbonate δ18O values between 1300 and 400 cal yr B.C. coincide with pollen evidence for forest loss, consistent with increased surface and groundwater flow to the lake. Minimum δ18O values between 400 cal yr B.C. and 150 cal yr A.D. suggest a high lake level, as do 14C-dated aquatic gastropods as much as 7.5 m above the present lake stage. High lake levels resulted from reduced evaporation-to-precipitation ratios, increased hydrologic input caused by anthropogenic deforestation, or both. The Preclassic abandonment (150 A.D.) and Early Classic/Late Classic boundary (550 A.D.) are marked by relatively high δ18O values indicating reduced lake levels. Oxygen isotope composition increased further coincident with the Terminal Classic Maya demographic decline between 800 and 900 A.D. This period of high δ18O may have been caused by the greater aridity that has been documented in northern Yucatán lakes or by decreased hydrologic input to the lake as a consequence of forest recovery. Reduced soil erosion after 850 cal yr A.D. coincided with the Terminal Classic Maya demographic decline and permitted forest recovery and resumption of organic sedimentation.
id: 2106

Blackwood Creek Stream restoration project design draft report - Beck, Nicole; Hydrology, Swanson (U.S. Forest Service Lake Tahoe Basin Management Unit, South Lake Tahoe, CA, 2002)
id: 350

Blackwood Creek Strem restoration project design draft report - Beck, N.; Hydrology, S. (2002)
id: 1140

A Budget of Carbonate and Terrigenous Sediments, Hanalei Bay, Kauai, Hawaiian Islands - Calhoun, R. S.; Fletcher, C. H.; Harney, J. N. (Marine Geology, 2002)
The sediment budget of Hanalei Bay on the north shore of Kauai was calculated using sedimentological and geophysical methods. The calculations of the budget subsequently allowed an interpretation of the Holocene history of the bay. The bay sediments are easily separated into marine (carbonate) and terrigenous (siliciclastic) grains. Surficial sediments are dominated by carbonate grains (∼70%) of coralline algae, coral, and mollusc fragments as well as foraminifera, Halimeda, bryozoa, and echinoderm tests. However, siliciclastic grains (e.g. olivine, plagioclase, volcanic lithics) from the Hanalei River watershed draining shield volcanic highlands are the most common individual grain type (∼27%) and form a zone of high concentration from the mouth of the Hanalei River into the center of the bay. Flooding in the bay by the post-glacial sea-level rise began soon after 11.7 kyears. The resulting marine environment caused the net deposition of 45.5±1.5×106 m3 of sediment in the bay and approximately 33.7±11.2×106 m3 of sediment on the Hanalei coastal plain. The total volume of carbonate sediment stored in the bay and coastal plain is greater than the volume likely to have been produced exclusively within the bay during the same time. Calculations indicate that approximately 2490 m3 year−1 have been imported into the bay or coastal plain and deposited since 11,700 years ago. The majority of this sediment influx is likely delivered from the east by the strong tradewind-driven littoral currents that characterize Kauai's north shore. Net carbonate sediment deposition in Hanalei Bay peaked at a rate of 15,500 m3 year−1 between 5000 and 3000 years ago (when sea level may have been 2 m above present) diminishing to 3890 m3 year−1 from 1000 years ago to the present. This influx is likely to have played a significant role in the mid to late Holocene progradation of the Hanalei shoreline.
id: 105

Carbon isotopic composition of DOM - Bauer, J. E. (Biogeochemistry of Marine Dissolved Organic Matter, 2002)
id: 687

Chemical and carbon isotopic evidence for the source and fate of dissolved organic matter in the northern Everglades - Wang, Y.; Hsieh, Y. P.; Landing, W. M.; Choi, Y. H.; Salters, V.; Campbell, D. (Biogeochemistry, 2002)
id: 616

A Critical Evaluation of Interlaboratory Data on Total, Elemental, and Isotopic Carbon in the Carbonaceous Particle Reference Material, NIST SRM 1649a - Currie, L. A.; Benner, B. A., Jr.; Kessler, J. D.; Klinedinst, D. B.; Klouda, G. A.; Marolf, J. V.; Slater, J. F.; Wise, S. A.; Cachier, H.; Cary, R.; Chow, J. C.; Watson, J.; et al. (J Res Natl Inst Stand Technol, 2002)
Because of increased interest in the marine and atmospheric sciences in elemental carbon (EC), or black carbon (BC) or soot carbon (SC), and because of the difficulties in analyzing or even defining this pervasive component of particulate carbon, it has become quite important to have appropriate reference materials for intercomparison and quality control. The NIST "urban dust" Standard Reference Material((R)) SRM 1649a is useful in this respect, in part because it comprises a considerable array of inorganic and organic species, and because it exhibits a large degree of ((14)C) isotopic heterogeneity, with biomass carbon source contributions ranging from about 2 % (essentially fossil aliphatic fraction) to about 32 % (polar fraction). A primary purpose of this report is to provide documentation for the new isotopic and chemical particulate carbon data for the most recent (31 Jan. 2001) SRM 1649a Certificate of Analysis. Supporting this is a critical review of underlying international intercomparison data and methodologies, provided by 18 teams of analytical experts from 11 institutions. Key results of the intercomparison are: (1) a new, Certified Value for total carbon (TC) in SRM 1649a; (2) (14)C Reference Values for total carbon and a number of organic species, including for the first time 8 individual PAHs; and (3) elemental carbon (EC) Information Values derived from 13 analytical methods applied to this component. Results for elemental carbon, which comprised a special focus of the intercomparison, were quite diverse, reflecting the confounding of methodological-matrix artifacts, and methods that tended to probe more or less refractory regions of this universal, but ill-defined product of incomplete combustion. Availability of both chemical and (14)C speciation data for SRM 1649a holds great promise for improved analytical insight through comparative analysis (e.g., fossil/biomass partition in EC compared to PAH), and through application of the principle of isotopic mass balance.
Currie, L ABenner, B A JrKessler, J DKlinedinst, D BKlouda, G AMarolf, J VSlater, J FWise, S ACachier, HCary, RChow, J CWatson, JDruffel, E R MMasiello, C AEglinton, T IPearson, AReddy, C MGustafsson, OQuinn, J GHartmann, P CHedges, J IPrentice, K MKirchstetter, T WNovakow, TPuxbaum, HSchmid, Heng2002/01/01 00:00J Res Natl Inst Stand Technol. 2002 Jun 1;107(3):279-98. doi: 10.6028/jres.107.022. Print 2002 May-Jun.

Data report: Australian Bight - Hine, A. C.; Brooks, G. R.; Mallinson, D.; Brunner, C. A.; James, N. P.; Feary, D. A.; Holbourn, A. E.; Drexler, T. M.; Howd, P. (Proc. ODP, Sci. Results, 2002)
id: 271

Field and laboratory data from an earthquake history study of the Toe Jam Hill fault, Bainbridge Island, Washington - Nelson, A. R.; Johnson, S. Y.; Wells, R. E.; Kelsey, H. M.; Pezzopane, S. K.; Sherrod, B. L.; Bradley, L. A.; Iii, Koehler R. D.; Bucknam, R. C.; Haugerud, R. A.; LaPrade, W. T. (U.S. Geological Survey Open-File Report, 2002)
id: 428

Field and Laboratory data from an earthquake history study of the Toe Jam Hill fault, Bainbridge Island, Washington - Nelson, A. R.; Johnson, S. Y.; Wells, R. E.; Pezzopane, S. K.; Kelsey, H. M.; Sherrod, B. L.; Bradley, L. A.; Koehler, R. D., III; Bucknam, R. C.; Haugerud, R. A.; LaPrade, W. T. (U.S. Geological Survey Open-File Report 02-60, 2002)
id: 259

Holocene moisture changes and fire frequency at Rio Rubens Bog, Southern Patagonia - Huber, U. M.; Markgraf, V. (Fire History, 2002)
id: 233

Influence of Vegetation Change on Watershed Hydrology: Implications for Paleoclimatic Interpretation of Lacustrine d180 Records - Rosenmeier, M. F.; Hodell, D. A.; Brenner, M.; Curtis, J. H.; Martin, J. B.; Anselmetti, F. S.; Ariztegui, D.; Guilderson, T. P. (Journal of Paleolimnology, 2002)
id: 1386

Kilimanjaro ice core records: evidence of holocene climate change in tropical Africa - Thompson, L. G.; Mosley-Thompson, E.; Davis, M. E.; Henderson, K. A.; Brecher, H. H.; Zagorodnov, V. S.; Mashiotta, T. A.; Lin, P. N.; Mikhalenko, V. N.; Hardy, D. R.; Beer, J. (Science, 2002)
Six ice cores from Kilimanjaro provide an approximately 11.7-thousand-year record of Holocene climate and environmental variability for eastern equatorial Africa, including three periods of abrupt climate change: approximately 8.3, approximately 5.2, and approximately 4 thousand years ago (ka). The latter is coincident with the "First Dark Age," the period of the greatest historically recorded drought in tropical Africa. Variable deposition of F- and Na+ during the African Humid Period suggests rapidly fluctuating lake levels between approximately 11.7 and 4 ka. Over the 20th century, the areal extent of Kilimanjaro's ice fields has decreased approximately 80%, and if current climatological conditions persist, the remaining ice fields are likely to disappear between 2015 and 2020.
Thompson, Lonnie GMosley-Thompson, EllenDavis, Mary EHenderson, Keith ABrecher, Henry HZagorodnov, Victor SMashiotta, Tracy ALin, Ping-NanMikhalenko, Vladimir NHardy, Douglas RBeer, Jurgeng2002/10/19 04:00Science. 2002 Oct 18;298(5593):589-93.

The limits of paleontological resolution - Kowalewski, M.; Bambach, R. K. (High Resolution Approachews in Paleontology: Kluwer Academic/Plenum, 2002)
id: 1415

A marine record of Holocene climate events in tropical South America, abstract - Haug, G. H.; Gunther, D.; Hughen, K. A.; Peterson, L. C.; Rohl, U. (Eos Trans. AGU 83, Fall Meeting Suppl, 2002)
id: 1080

Noble gases and volatile recycling at subduction zones - Hilton, D. R.; Fischer, T. P.; Marty, B. (Noble Gases in Geochemistry and Cosmochemistry, 2002)
Bw12hTimes Cited:243Cited References Count:219Reviews in Mineralogy & Geochemistry

Numerical models, geochemistry and the zero-paradox noble-gas mantle - Ballentine, C. J.; Van Keken, P. E.; Porcelli, D.; Hauri, E. H. (Philos Transact A Math Phys Eng Sci, 2002)
Numerical models of whole-mantle convection demonstrate that degassing of the mantle is an inefficient process, resulting in ca. 50% of the (40)Ar being degassed from the mantle system. In this sense the numerical simulations are consistent with the (40)Ar mass balance between the atmosphere and mantle reservoir. These models, however, are unable to preserve the large-scale heterogeneity predicted by models invoking geochemical layering of the mantle system. We show that the three most important noble-gas constraints on the geochemically layered mantle are entirely dependent on the (3)He concentration of the convecting mantle derived from the (3)He flux into the oceans and the average ocean-crust generation rate. A factor of 3.5 increase in the convecting-mantle noble-gas concentration removes all requirements for: a (3)He flux into the upper mantle from a deeper high (3)He source; a boundary in the mantle capable of separating heat from helium; and a substantial deep-mantle reservoir to contain a hidden (40)Ar rich reservoir. We call this model concentration for the convecting mantle the 'zero-paradox' concentration. The time-integrated flux of (3)He into the oceans is a robust observation, but only representative of the ocean-floor activity over the last 1000 years. In contrast, ocean-floor generation occurs over tens of millions of years. We argue that combining these two observations to obtain the (3)He concentration of the mantle beneath mid-ocean ridges is unsound. Other indicators of mantle (3)He concentration suggest that the real value may be at least a factor of two higher. As the zero-paradox concentration is approached, the noble-gas requirement for mantle layering is removed. We further consider the role that recycled material plays in ocean-island-basalt generation and show that a source with high (3)He and (3)He/(4)He must exist within the mantle. Nevertheless, only a small amount of this material is required to generate both the observed ocean-island (3)He/(4)He ratios and the concentrations inferred from basalt samples for this mantle source.
id: 1579; Ballentine, Chris J Van Keken, Peter E Porcelli, Don Hauri, Erik H England Philos Transact A Math Phys Eng Sci. 2002 Nov 15;360(1800):2611-31.

Oak, chestnut and fire: climatic and cultural controls of long-term forest dynamics in New England, USA - Foster, D. R.; Clayden, S.; Orwig, D. A.; Hall, B. (Journal of Biogeography, 2002)
Aim Despite decades of study we have limited insights into the nature of the pre-European landscape of the north-eastern USA and the forces and changes that shaped modern forest patterns. Information on such long-term forest dynamics would provide critical insights into the relationships among environmental change, land-use history and biotic responses and is greatly needed for conservation planning. To address these issues we used modern, historical, and palaeoecological approaches to reconstruct the 3500-year history of a New England upland region dominated by oak and (formerly) chestnut forests and to interpret the interactions among climate change, natural and human disturbance, and site factors in controlling vegetation patterns and dynamics at different spatial scales.Location The study focused on a broad upland ridge dominated by oak forests in the north-central Massachusetts town of New Salem. Detailed palaeoecological analyses were undertaken of wetland (Chamberlain Swamp) and lake (Lily Pond) basins in order to reconstruct local to regional scale vegetation dynamics, which were interpreted within the context of regional vegetation data from central Massachusetts.Methods Palaeoecological methods were used to reconstruct the vegetation, fire and land-use history of the local and subregional vegetation from the two basins and to place these in the context of regional information on vegetation and climate change based on other published data. Historical information including maps, archaeological and census data, and vegetation information were gathered for the landscape and areas surrounding the coring sites. Vegetation sampling in transects adjacent to the swamp coring area included tree cores for dendrochronological reconstructions.Results Stand, landscape and regional forest dynamics were most strongly driven by climate, notably an apparent cooling and increase in moisture availability c. 1500 yr BP, and European land-use activities commencing 260 yr BP. However, the abundance of oak and chestnut (fire-tolerant, sprouting species) and the distribution of hemlock (fire-intolerant) at a stand to landscape scale were also influenced by fire, which, in turn, varied with climate and human activity. Despite, or perhaps as a consequence of ongoing disturbance by fire and presumably windstorms in this hurricane-prone region, the pre-European period was marked by two 1000+ year periods of remarkably stable forest composition, separated by an abrupt compositional shift. In contrast, over the past 260 years the vegetation has changed rather continuously in response to human activity, producing stand, landscape and regional patterns that are novel as well as recent in origin.The results indicate that chestnut was a major component of some pre-European landscapes in New England, in part because of occasional fire, and that cultural and physical factors have interacted over millennia to control vegetation patterns and dynamics. Our analyses also suggest that the composition of low diversity forests can be remarkably stable over millennia. The range of ecological, cultural and management insights afforded by this study underscores the fundamental utility of very long-term research in science and policy development.
618gtTimes Cited:53Cited References Count:126

Ostracoda and paleoceanography - Cronin, T. M.; Boomer, I.; Dwyer, G. S.; Rodriguez-Lazaro, J. (American Geophysical Union Monograph - The Ostracoda: Applications in Quaternay Research, 2002)
id: 1473

Plans for expanded 14C analyses at the NOSAMS facility - a status and progress report - von Reden, K. F.; Donoghue, J.; Elder, K.; Gagnon, A.; Gerlach, D.; Griffin, V.; Healy, R.; Long, P.; McNichol, A.; Percy, D.; Roberts, M. L.; Schneider, R. J.; et al. (International Conference on Accelerator Mass Spectrometry, 2002)
id: 1685

Radiocarbon analysis, calibration and applications - Kromer, B.; Hughen, K. (Current methods in geochronology: Temporal resolution in geology, palaeontology, archaeoloty, and anthropology, 2002)
id: 326

Radiocarbon dates bason on organic matter in diatom frustules, Abstract - Donoghue, Joanne C.; Hayes, John M.; Manganini, Steven J.; Francois, Roger (EOS. Trans. AGU, 2002)
OS42E-156
id: 1720

Rapid isolation of biomarkers for compound specific radiocarbon dating using high-performance liquid chromatography and flow injection analysis - atmoospheric pressure chemical ionisation mass spectrometry - Smittenberg, R. H.; Hopmans, E. C.; Schouten, S.; Sinninghe-Damste, J. S. (Journal of Chromatography A, 2002)
id: 669

Rates of evolution in ancient DNA from Adelie penguins - Lambert, D. M.; Ritchie, P. A.; Millar, C. D.; Holland, B.; Drummond, A. J.; Baroni, C. (Science, 2002)
Well-preserved subfossil bones of Adelie penguins, Pygoscelis adeliae, underlie existing and abandoned nesting colonies in Antarctica. These bones, dating back to more than 7000 years before the present, harbor some of the best-preserved ancient DNA yet discovered. From 96 radiocarbon-aged bones, we report large numbers of mitochondrial haplotypes, some of which appear to be extinct, given the 380 living birds sampled. We demonstrate DNA sequence evolution through time and estimate the rate of evolution of the hypervariable region I using a Markov chain Monte Carlo integration and a least-squares regression analysis. Our calculated rates of evolution are approximately two to seven times higher than previous indirect phylogenetic estimates.
Lambert, D MRitchie, P AMillar, C DHolland, BDrummond, A JBaroni, CengResearch Support, Non-U.S. Gov'tResearch Support, U.S. Gov't, P.H.S.2002/03/23 10:00Science. 2002 Mar 22;295(5563):2270-3.

Spatial and temporal offsets between proxy records in a sediment drift - Ohkouchi, N.; Eglinton, T. I.; Keigwin, L. D.; Hayes, J. M. (Science, 2002)
Chronologies for Late Quaternary marine sediment records are usually based on radiocarbon ages of planktonic foraminifera. Signals carried by other sedimentary components measured in parallel can provide complementary paleoclimate information. A key premise is that microfossils and other indicators within a given sediment horizon are of equal age. We show here that haptophyte-derived alkenones isolated from Bermuda Rise drift sediments are up to 7000 years older than coexisting planktonic foraminifera. This temporal offset, which is apparently due to lateral transport of alkenones on fine-grained particles from the Nova Scotian margin, markedly influences molecular estimates of sea surface temperatures. More broadly, the observation raises questions about both the temporal and the geographic delity of paleoenvironmental records encoded by readily transported components of sediments.
612mqTimes Cited:147Cited References Count:38

Stable chlorine and carbon isotopic compositions of selected semi-volatile organochlorine compounds - Drenzek, N. J.; Tarr, C. H.; Eglinton, T. I.; Heraty, L. J.; Sturchio, N. C.; Shiner, V. J.; Reddy, C. M. (Organic Geochemistry, 2002)
To assess whether the isotopic composition of semi-volatile organochlorine compounds (SVOCs) may be a useful tool, we measured the bulk delta(37)Cl and delta(13)C values of several pesticides and Aroclor mixtures from different suppliers. Overall, the delta(37)Cl and delta(13)C values ranged from -5.10 to + 1.22% and -31.63 to -22.39%, respectively. These values are narrower than the ranges observed previously for volatile organic contaminants (VOCs). In particular, the isotopic compositions of the Aroclor mixtures were very tightly constrained for both chlorine and carbon, We also observed that SVOCs synthesized from hexachlorocyclopentadiene had the most enriched delta(37)Cl values. These data provide a baseline for future work employing isotope ratios to study the environmental fate of SVOCs. (C) 2002 Elsevier Science Ltd. All rights reserved.
545bnTimes Cited:41 Cited References Count:25
Keywords: aroclors; fractionation; hydrocarbons; intrinsic bioremediation; samples; solvents; trichloroethene

Test of negative ion beams from a microwave ion source with a charge exchange canal for accelerator mass spectrometry applications - Kim, S. W.; Schneider, R. J.; von Reden, K. F.; Hayes, J. M.; Wills, J. S. C. (Review of Scientific Instruments, 2002)
A test facility has been constructed to evaluate negative ion beams from small gaseous samples for accelerator mass spectrometry applications. The positive ion beams from the microwave ion source are passed into a charge-exchange canal (CXC) where the ions exchange electrons with magnesium vapor and become negatively charged. Positive molecular ions were: either neutralized or broken up into atomic ions and neutral atoms and molecules by collision processes. Most of the resulting particles were suspected to be neutrals. In studies with injections of CO2 pulses, the resulting positive and negative C-12 current peaks gave a 0.09% yield of C- ions from CO2 molecules, which includes a charge-exchange efficiency of 10%. Since nitrogen does not form a stable negative ion, N-14 background is virtually eliminated after the beam goes through the CXC, which is necessary for radiocarbon measurements. (C) 2002 American Institute of Physics.
2522wyTimes Cited:8Cited References Count:7

Uncertainties and novel prospects in the study of the soil carbon dynamics - Wang, Y.; Hsieh, Y. P. (Chemosphere, 2002)
Establishment of the Kyoto Protocol has resulted in an effort to look towards living biomass and soils for carbon sequestration. In order for carbon credits to be meaningful, sustained carbon sequestration for decades or longer is required. It has been speculated that improved land management could result in sequestration of a substantial amount of carbon in soils within several decades and therefore can be an important option in reducing atmospheric CO2 concentration. However, evaluation of soil carbon sources and sinks is difficult because the dynamics of soil carbon storage and release is complex and still not well understood. There has been rapid development of quantitative techniques over the past two decades for measuring the component fluxes of the global carbon cycle and for studying the soil carbon cycle. Most significant development in the soil carbon cycle study is the application of accelerator mass spectrometry (AMS) in radiocarbon measurements. This has made it possible to unravel rates of carbon cycling in soils, by studying natural levels of radiocarbon in soil organic matter and soil CO2. Despite the advances in the study of the soil carbon cycle in the recent decades, tremendous uncertainties exist in the sizes and turnover times of soil carbon pools. The uncertainties result from lack of standard methods and incomplete understanding of soil organic carbon dynamics, compounded by natural variability in soil carbon and carbon isotopic content even within the same ecosystem. Many fundamental questions concerning the dynamics of the soil carbon cycle have yet to be answered. This paper reviews and synthesizes the isotopic approaches to the study of the soil carbon cycle. We will focus on uncertainties and limitations associated with these approaches and point out areas where more research is needed to improve our understanding of this important component of the global carbon cycle.
Wang, YangHsieh, Yuch-Ping eng England 2002/11/15 04:00 Chemosphere. 2002 Dec;49(8):791-804.
Keywords: Carbon Dioxide/chemistry/metabolism; Carbon Radioisotopes/analysis; Carbon/*chemistry/metabolism; Ecosystem; Kinetics; Models, Chemical; Plants/metabolism; Seasons; Soil/*analysis

Vapour undersaturation in primitive mid-ocean-ridge basalt and the volatile content of Earth's upper mantle - Saal, A. E.; Hauri, E. H.; Langmuir, C. H.; Perfit, M. R. (Nature, 2002)
The analysis of volatiles in magmatic systems can be used to constrain the volatile content of the Earth's mantle and the influence that magmatic degassing has on the chemistry of the oceans and the atmosphere. But most volatile elements have very low solubilities in magmas at atmospheric pressure, and therefore virtually all erupted lavas are degassed and do not retain their primary volatile signatures. Here we report the undersaturated pre-eruptive volatile content for a suite of mid-ocean-ridge basalts from the Siqueiros intra-transform spreading centre. The undersaturation leads to correlations between volatiles and refractory trace elements that provide new constraints on volatile abundances and their behaviour in the upper mantle. Our data generate improved limits on the abundances of carbon dioxide, water, fluorine, sulphur and chlorine in the source of normal mid-ocean-ridge basalt. The incompatible behaviour of carbon dioxide, together with the CO(2)/Nb and CO(2)/Cl ratios, permit estimates of primitive carbon dioxide and chlorine to be made for degassed and chlorine-contaminated mid-ocean-ridge basalt magmas, and hence constrain degassing and contamination histories of mid-ocean ridges.
Saal, Alberto EHauri, Erik HLangmuir, Charles HPerfit, Michael RengEngland2002/10/09 04:00Nature. 2002 Oct 3;419(6906):451-5.

Volcanic gases, black smokers, and the Great Oxidation Event - Holland, H. D. (Geochimica Et Cosmochimica Acta, 2002)
This paper proposes that gradual changes in the composition of volatiles that have been added to the atmosphere-ocean system are responsible for the Great Oxidation Event (G.O.E.) ca. 2.3 Ga. Before ca. 2.3 Ga, the composition of these volatiles was probably such that 20% of the carbon gases could be reduced to organic matter and all of the sulfur gases could be reduced to pyrite. Since 2.3 Ga, the composition of these volatiles has been such that 20% of the carbon gases could be reduced to organic matter, but only a fraction of the sulfur gases could be reduced to pyrite. This change led to the oxygenation of the atmosphere and to a large increase in the SO4-2 concentration of seawater. A considerable body of observational data supports these proposals. Copyright (C) 2002 Elsevier Science Ltd.
608ztTimes Cited:295 Cited References Count:57
Keywords: atmospheric oxygen; carbon; chemistry; east pacific rise; evolution; hydrothermal vent fluids; midocean ridges; precambrian cherts; south-africa; sulfur cycle

The West Falmouth oil spill after thirty years: the persistence of petroleum hydrocarbons in marsh sediments - Reddy, C. M.; Eglinton, T. I.; Hounshell, A.; White, H. K.; Xu, L.; Gaines, R. B.; Frysinger, G. S. (Environ Sci Technol, 2002)
The long-term fate of petroleum hydrocarbons in marsh sediments (West Falmouth, MA) contaminated in 1969 by the spill of the barge Florida was investigated. A 36-cm-long sediment core was collected in August 2000, and sediment extracts were analyzed by gas chromatography (GC) and comprehensive two-dimensional gas chromatography (GC x GC). The latter technique is capable of separating 1 order of magnitude more compounds than the former and was used to observe whether any compositional changes in the unresolved complex mixture (UCM) occurred. No evidence of petroleum residues was detected in the top 6 cm (0-6 cm) and the lower 8 cm (28-36 cm) of the core. However, the central sections 16-28 cm) were dominated by a UCM in the boiling range of n-C13-n-C25 alkanes, consistent with a No. 2 fuel oil source. The 12-14- and 14-16-cm sections had the highest concentrations of UCM approximately 8 mg g(-1)). These values are similar to concentrations observed shortly after the spill. Initial GC x GC analysis revealed that only the n-alkanes were completely degraded, and contrary to previous studies, pristane and phytane as well as numerous other branched alkanes are still present in the sediments. These results suggestthatatthis site hydrocarbon contamination will persist indefinitely in the sedimentary record.
Reddy, Christopher MEglinton, Timothy I Hounshell, Aubrey White, Helen K Xu, Li Gaines, Richard B Frysinger, Glenn S eng Research Support, Non-U.S. Gov't Research Support, U.S. Gov't, Non-P.H.S. 2002/12/19 04:00 Environ Sci Technol. 2002 Nov 15;36(22):4754-60.
Keywords: *Accidents; Chromatography, Gas; Environmental Monitoring; Geologic Sediments/*chemistry; Hydrocarbons/*analysis; Massachusetts; Petroleum/*analysis; Ships; Time Factors; Water Pollutants, Chemical/*analysis

A 700 year sedimentary record of intense hurricane landfalls in southern New England - Donnelly, Jeffrey P.; Bryant, Sarah Smith; Butler, Jessica; Dowling, Jennifer; Fan, Linda; Hausmann, Neil; Newby, Paige; Shuman, Bryan; Stern, Jennifer; Westover, Karlyn; Webb, Thompson, III (GSA Bulletin, 2001)
id: 1343

Abrupt climate change and pre-Columbian cultural collapse - Brenner, M.; Hodell, D. A.; Curtis, J. H.; Rosenmeier, M.; Binford, M. W.; Abbott, M. B. (Interhemispheric Climate Linkages, 2001)
id: 1408

Algal and archaeal polyisoprenoids in a recent marine sediment: Molecular isotopic evidence for anaerobic oxidation of methane - Bian, L. Q.; Hinrichs, K. U.; Xie, T. M.; Brassell, S. C.; Iversen, H.; Fossing, H.; Jorgensen, B. B.; Hayes, J. M. (Geochemistry Geophysics Geosystems, 2001)
Analyses of C-13 contents of individual organic molecules in a marine sediment show that crocetane, 2,6,11,15-tetramethylhexadecane, an isomer of phytane, is produced by microorganisms that use methane as their main source of carbon. The sediments lie at a water depth of 68 m in the Kattegat, the strait between Denmark and Sweden. Crocetane appears first 185 cm below the sediment-water interface, in the zone marking the transition from sulfate reduction to methanogenesis. Its delta C-13 value is -90 +/- 10 parts per thousand versus Vienna Pee Dee Belemnite (VPDB). Its structure, which includes four isoprene units arranged symmetrically around a tail-to-tail linkage, suggests that it is produced by a member of the archaea. Growing at the intersection of the diffusion gradients for sulfate and methane in sedimentary pore waters, the source organism apparently function as a methane-consuming member of the microbial consortium responsible for the anaerobic oxidation of methane [Hoehler et al., 1994], in which, as first demonstrated quantitatively in these sediments [Iversen and Jorgensen, 1985], electrons are transferred from methane to sulfate. The presence of archaeal biomass throughout the sediment section is indicated by significant concentrations of 2,6,10,15,19-pentamethylicosane (PMI) and of ether-bound phytane and biphytane. The PMI reaches a minimum delta value of -47 parts per thousand well below the transition zone. Its isotopic depletion could reflect either methanogenic or methanotrophic sources. The ether-bound lipids are isotopically uniform throughout the section and are presumed to derive from archaea that utilize a carbon source unaffected by the oxidation of methane.
458jvTimes Cited:51Cited References Count:79

A budget of Holocene carbonate sediments, Kailua Bay, Oahu, Hawaiian Islands - Harney, Jodi N.; Fletcher, Charles H. (University of Hawaii, 2001)
id: 329

Climate change in the circum-Caribbean (late Pleistocene-to-Present) and implications for regional biogeography - Curtis, J. H.; Brenner, M.; Hodell, D. A. (Biogeography of the West Indies: Patterns and Perspectives, 2nd Edition, 2001)
id: 265

Comparative analysis of methane-oxidizing archaea and sulfate-reducing bacteria in anoxic marine sediments - Orphan, V. J.; Hinrichs, K. U.; Ussler, W.; Paull, C. K.; Taylor, L. T.; Sylva, S. P.; Hayes, J. M.; DeLong, E. F. (Appl Environ Microbiol, 2001)
The oxidation of methane in anoxic marine sediments is thought to be mediated by a consortium of methane-consuming archaea and sulfate-reducing bacteria. In this study, we compared results of rRNA gene (rDNA) surveys and lipid analyses of archaea and bacteria associated with methane seep sediments from several different sites on the Californian continental margin. Two distinct archaeal lineages (ANME-1 and ANME-2), peripherally related to the order Methanosarcinales, were consistently associated with methane seep marine sediments. The same sediments contained abundant (13)C-depleted archaeal lipids, indicating that one or both of these archaeal groups are members of anaerobic methane-oxidizing consortia. (13)C-depleted lipids and the signature 16S rDNAs for these archaeal groups were absent in nearby control sediments. Concurrent surveys of bacterial rDNAs revealed a predominance of delta-proteobacteria, in particular, close relatives of Desulfosarcina variabilis. Biomarker analyses of the same sediments showed bacterial fatty acids with strong (13)C depletion that are likely products of these sulfate-reducing bacteria. Consistent with these observations, whole-cell fluorescent in situ hybridization revealed aggregations of ANME-2 archaea and sulfate-reducing Desulfosarcina and Desulfococcus species. Additionally, the presence of abundant (13)C-depleted ether lipids, presumed to be of bacterial origin but unrelated to ether lipids of members of the order Desulfosarcinales, suggests the participation of additional bacterial groups in the methane-oxidizing process. Although the Desulfosarcinales and ANME-2 consortia appear to participate in the anaerobic oxidation of methane in marine sediments, our data suggest that other bacteria and archaea are also involved in methane oxidation in these environments.
Orphan, V JHinrichs, K UUssler, W 3rdPaull, C KTaylor, L TSylva, S PHayes, J MDelong, E FengComparative StudyResearch Support, Non-U.S. Gov'tResearch Support, U.S. Gov't, Non-P.H.S.2001/04/03 10:00Appl Environ Microbiol. 2001 Apr;67(4):1922-34.

Composition of hydrothermal vent microbial communities as revealed by analyses of signature lipids, stable carbon isotopes, and Aquificales cultures - Jahnke, Linda L.; Eder, Wolfgang; Huber, Robert; Hope, Janet M.; Hinrichs, Kai-Uwe; Hayes, John M.; Des Marais, David J.; Cady, Sherry L.; Summons, Roger E. (Applied and Environmental Microbiology, 2001)
id: 1783

Compound-specific D/H ratios of lipid biomarkers from sediments as a proxy for environmental and climatic conditions - Sauer, P. E.; Eglinton, T. I.; Hayes, J. M.; Schimmelmann, A.; Sessions, A. L. (Geochimica Et Cosmochimica Acta, 2001)
Hydrogen isotope ratios (D/H) of lipid biomarkers extracted from aquatic sediments were measured to determine whether they can be used as a proxy for D/H of environmental water. Values of deltaD were determined by using a recently developed isotope-ratio-monitoring gas chromatograph-mass spectrometer system (irmGCMS) and were confirmed by conventional hydrogen isotopic measurements (i.e., combustion followed by reduction) on individual compounds isolated by preparative capillary gas chromatography. Diverse lipids (alkanes, n-alkanols, sterols, and pentacyclic triterpenols) were analyzed to examine hydrogen-isotopic controls on lipids of varying origin and biosynthetic pathway. For algal sterols (24-methylcholest-3 beta -ol, 24-ethylcholest-5,22-dien-3 beta -ol, and 4,23,24-trimethylcholesterol, or dinosterol), the fractionation between sedimentary lipids and environmental water was -201 +/- 10 parts per thousand and was similar in both marine and freshwater sites. In a sediment from a small lake in a forested catchment, triterpenols from terrestrial sources were enriched in D by 30 parts per thousand relative to algal sterols. Apparent fractionation factors for n-alkyl lipids were smaller than those of triterpenols and were more variable, probably reflecting multiple sources for these compounds. We conclude that hydrogen-isotopic analyses of algal sterols provide a viable means of reconstructing D/H of environmental waters. Results are less ambiguous than reconstructions based on analyses of kerogen or other operationally defined organic matter fractions. Copyright (C) 2001 Elsevier Science Ltd.
395npTimes Cited:209Cited References Count:64

Correction of H3+ contributions in hydrogen isotope ratio monitoring mass spectrometry - Sessions, A. L.; Burgoyne, T. W.; Hayes, J. M. (Anal Chem, 2001)
Two fundamentally different approaches, termed "pointwise" and "peakwise," are currently used to correct hydrogen isotope ratio monitoring data for the presence of H3+ ion contributions. Consideration of the underlying assumptions shows that the peakwise approach is valid only for peaks with the same functional shape and only when background signals do not vary. The pointwise correction is much more versatile and can be used even when peak shapes and sizes, as well as background signals, vary significantly. It is not exact and is limited in accuracy by (1) the signal-broadening effects of electronic time constants, (2) the analog-to-digital conversion frequency, and (3) the highest frequency of the sample signal. To minimize errors for typical gas chromatographic signals, time constants of <500 ms and analog-to-digital sampling intervals of < or =250 ms are needed. Errors are further minimized by matching sample and standard peaks in both amplitude and D/H ratio. Using the pointwise algorithm, we demonstrate that a series of 14 homologous n-alkanes varying in concentration over a 5-fold range can be analyzed with a mean precision of 2.3 per thousand and no systematic errors.
Sessions, A LBurgoyne, T W Hayes, J M eng 2001/02/24 12:00 Anal Chem. 2001 Jan 15;73(2):192-9.

Determination of the the H3 factor in hydrogen isotope ratio monitoring mass spectrometry - Sessions, A. L.; Burgoyne, T. W.; Hayes, J. M. (Anal Chem, 2001)
The H3 factor, K, is a parameter required in high-precision, mass spectrometric analyses of hydrogen isotopic abundances. When H2 is used as the sample gas, R* = R - Ki2, where R* is the true HD/H2 ratio, R is the observed (mass 3)/(mass 2) ion-current ratio, and i2 is the ion current at mass 2. Four different methods for the determination of K were defined and tested under conditions characteristic of isotope ratio monitoring systems. Three of these were peak-based. The fourth employed steady flows of H2 from a conventional inlet system. Results obtained using the latter method were more precise (standard deviation of K = 0.1 versus approximately 0.6 ppm mV(-1) for the peak-based methods). However, use of the resulting values of K for correction of isotope ratio monitoring GC/MS results led to systematic errors as large as 9 per thousand, whereas use of the peak-based values led to no systematic errors. Values of K were only weakly dependent on the pressure of He, declining approximately 5% for each 10-fold increase in P(He). Small variations in partial pressures of H2O and CH4, potential contaminants under isotope ratio monitoring conditions, had no significant effect on values of K.
Sessions, A LBurgoyne, T W Hayes, J M eng 2001/02/24 12:00 Anal Chem. 2001 Jan 15;73(2):200-7.

Effects of biosynthesis and physiology on relative abundances and isotopic compositions of alkenones - Gonzalez, E. L.; Riebesell, U.; Hayes, J. M.; Laws, E. A. (Geochemistry Geophysics Geosystems, 2001)
The number of double bonds in long-chain, unsaturated ketones (alkenones) produced by some members of the Haptophyceae is correlated with the ambient temperature at the time of synthesis. For these same organisms the depletion of carbon-13 in biosynthetic products relative to dissolved inorganic carbon is related directly to the specific growth rate and inversely to the concentration of dissolved carbon dioxide. This report summarizes issues relating to the physiology, metabolism, and biochemistry of alkenone producers and how they affect the abundances and isotopic compositions of alkenones. These considerations show that an understanding of cellular responses to parameters governing uptake of inorganic carbon (C-i), isotopic fractionation, growth under diverse nutrient conditions, and genetic variability, both in the field and in culture, is necessary for developing a conceptual understanding of the biological significance of the epsilonp and U-37(K') indices. Emiliana huxleyi is the best known alkenone producer and can serve as a model organism for these studies. This report identifies knowledge gaps and appropriate objectives for both field- and laboratory-based research.
458kdTimes Cited:6 Cited References Count:39
Keywords: algae; alkenones; anhydrase; biogeochemical processes; biosynthesis; calcification; carbon-13; emiliania-huxleyi prymnesiophyceae; fractionation; Haptophytes; inorganic carbon utilization; instruments and techniques; isoprenoid biosynthesis; marine diatom; paleoceanography; photosynthesis; physiology; phytoplankton; sea surface temperature

Fractionation of the isotopes of carbon and hydrogen in biosynthetic processes - Hayes, John M. (Stable Isotope Geochemistry, Reviews in Mineralogy and Geochemistry, 2001)
id: 1709

Holocene–late Pleistocene non-tropical carbonate sediments and tectonic history of the western rift basin margin of the southern Gulf of California - Halfar, J.; Godinez-Orta, L.; Goodfriend, G. A.; Mucciarone, D. A.; Ingle, J. C.; Holden, P. (Sedimentary Geology, 2001)
Using high-resolution seismic reflection profiling and dating of (1) shallow marine vibracores and (2) sediments collected from uplifted marine terraces we reconstruct the tectonic history and sediment accumulation patterns of Holocene to late Pleistocene warm-temperate to subtropical carbonates in the southern Gulf of California, Mexico. The study was conducted in the vicinity of La Paz where carbonates form along the fault bounded narrow western shelf of the tectonically active Gulf of California rift basin. The non-tropical nature of the setting is responsible for (1) poor cementation of the bioclastic carbonates, and (2) a composition which is dominated by rhodoliths (coralline red algae), corals and mollusks. Unrimmed carbonate flats forming in small pocket bays and a rhodolith bioherm, which has a surface area of more than 20 km2 and is up to 16 m thick, constitute the major carbonate factories. Holocene carbonate accumulation rates were deduced from seismic and core data and are highest on the rhodolith bioherm (260 cm/ka) and in subtidal zones of pocket bays (210 cm/ka), and lowest on the inner and middle shelf (100 cm/ka). Taken together, rates of carbonate accumulation are intermediate in magnitude between higher rates recorded in fully tropical carbonate settings and lower rates typical of cool-water carbonates. Seismic reflection profiles demonstrate that Isla Espiritu Santo in the center of the study area is a west dipping fault block, which is tectonically influenced by two distinct faults, the La Paz and Espiritu Santo faults. The latter fault accommodates at least 700 m of east-side down normal offset, and forms a steep eastern escarpment leading into the La Paz slope basin. Some of the sediments produced in the shallow carbonate factories of the narrow La Paz shelf are transported across this escarpment and are redeposited in the slope basin at a water depth of 750 m. Uranium-series dates of marine terraces exposed on Isla Espiritu Santo indicate that late Pleistocene uplift along the eastern side of the island could be as high as 310 mm/ka whereas downdropping along the western side of the island occurred at a rate of up to 15 mm/ka. Isla Espiritu Santo therefore constitutes part of the uplifted shoulder of the western margin of the Gulf of California rift basin. Patterns of vertical tectonic movements of Isla Espiritu Santo together with fault offsets on the surrounding seafloor and slump features on steep submarine slopes, point to continuous activity of the La Paz and Espiritu Santo faults. Results of this study will assist in recognizing and interpreting similar settings along ancient non-tropical rift basin margins worldwide and especially in the Neogene of the Gulf of California.
id: 1316

Hypothesized climate forcing time series for the last 500 years - Robertson, A.; Overpeck, J.; Rind, D.; Mosley-Thompson, E.; Zielinski, G.; Lean, J.; Koch, D.; Penner, J.; Tegen, I.; Healy, R. (Journal of Geophysical Research-Atmospheres, 2001)
A new compilation of annually resolved time series of atmospheric trace gas concentrations, solar irradiance, tropospheric aerosol optical depth, and stratospheric (volcanic) aerosol optical depth is presented for use in climate modeling studies of the period 1500 to 1999 A.D. Atmospheric CO2 CH4, and N2O concentrations over this period are well established on the basis of fossil air trapped in ice cores and instrumental measurements over the last few decades. Estimates of solar irradiance, ranging between 1364.2 and 1368.2 W/m(2), are presented using calibrated historical observations of the Sun back to 1610, along with cosmogenic isotope variations extending back to 1500. Tropospheric aerosol distributions are calculated by scaling the modern distribution of sulfate and carbonaceous aerosol optical depths back to 1860 using reconstructed regional CO2 emissions; prior to 1860 the anthropogenic tropospheric aerosol optical depths are assumed to be zero. Finally, the first continuous, annually dated record of zonally averaged stratospheric (volcanic) optical depths back to 1500 is constructed using sulfate flux data from multiple ice cores from both Greenland and Antarctica, in conjunction with historical and instrumental (satellite and pyrheliometric) observations. The climate forcings generated here are currently being used as input to a suite of transient (time dependent) paleoclimate model simulations of the past 500 years. These forcings are also available for comparison with instrumental and proxy paleoclimate data of the same period.
456yeTimes Cited:108Cited References Count:89

The impact of sea ice concentration accuracies on climate model simulations with the GISS GCM - Parkinson, C. L.; Rind, D.; Healy, R. J.; Martinson, D. G. (Journal of Climate, 2001)
The Goddard Institute for Space Studies global climate model (GISS GCM) is used to examine the sensitivity of the simulated climate to sea ice concentration specifications in the type of simulation done in the Atmospheric Model Intercomparison Project (AMIP), with specified oceanic boundary conditions. Results show that sea ice concentration uncertainties of +/-7% can affect simulated regional temperatures by more than 6 degreesC, and biases in sea ice concentrations of +7% and -7% alter simulated annually averaged global surface air temperatures by -0.10 degrees and +0.17 degreesC, respectively, over those in the control simulation. The resulting 0.27 degreesC difference in simulated annual global surface air temperatures is reduced by a third, to 0.18 degreesC, when considering instead biases of +4% and -4%. More broadly, least squares fits through the temperature results of 17 simulations with ice concentration input changes ranging from increases of 50% versus the control simulation to decreases of 50% yield a yearly average global impact of 0.0107 degreesC warming for every 1% ice concentration decrease, that is, 1.07 degreesC warming for the full +50% to -50% range. Regionally and on a monthly average basis, the differences can be far greater, especially in the polar regions, where wintertime contrasts between the +50% and -50% cases can exceed 30 degreesC. However, few statistically significant effects are found outside the polar latitudes, and temperature effects over the nonpolar oceans tend to be under 1 degreesC, due in part to the specification of an unvarying annual cycle of sea surface temperatures. The +/-7% and +/-4% results provide bounds on the impact (on GISS GCM simulations making use of satellite data) of satellite-derived ice concentration inaccuracies, +/-7% being the current estimated average accuracy of satellite retrievals and +/-4% being the anticipated improved average accuracy for upcoming satellite instruments. Results show that the impact on simulated temperatures of imposed ice concentration changes is least in summer, encouragingly the same season in which the satellite accuracies are thought to be worst. Hence, the impact of satellite inaccuracies is probably less than the use of an annually averaged satellite inaccuracy would suggest.
id: 1944; PT: J; UT: WOS:000169239100008

Implications of the carbon isotope and mineral inclusion record for the formation of diamonds in the mantle underlying a mobile belt: Venetia, South Africa - Deines, P.; Viljoen, F.; Harris, J. W. (Geochimica Et Cosmochimica Acta, 2001)
A total of 199 diamonds from the Venetia kimberlite, South Africa, whose mineral inclusion chemistry had already been measured, were analyzed for their carbon isotopic composition. Silicate inclusions in these diamonds either belong to a peridotitic (P-Type), an eclogitic (E-Type) or transitional, websteritic (W-Type), paragenesis.The carbon isotopic composition of 161 P-Type diamonds ranges from delta C-13 = -2.23 to - 18 parts per thousand vs. PDB. The large number of samples available and the wide range in delta C-13 permitted, for the first time, a detailed analysis of the relationships between P-Type inclusion chemistry and the carbon isotopic composition of the diamond host. The delta C-13 Sampling frequency distribution is multi-modal. Examination of the inclusion chemistry (chromite, olivine, garnet) as a function of the carbon isotope composition mode to which the host belongs, as well as multivariate regression analyses, revealed no correlation between inclusion chemistry and C-13 content. The inclusion compositions in diamonds of low C-13 content are not distinctive. For a given carbon isotopic composition the combination of Ni/Fe and Mg/(Mg + Fe) of olivine inclusions varies systematically along fractionation trends. The composition of the olivine inclusions and the C-13 content of their hosts can be interpreted as reflecting similar petrogenetic processes occurring in several mantle environments into which carbon of variable isotopic composition was introduced. The iron/magnesium distribution between coexisting garnets and olivines permits an estimate of their pressure/temperature equilibration conditions. Diamonds whose inclusions were equilibrated at lower temperatures and pressures tend to have, on average, lower C-13 contents. The compositions of coexisting olivines and chromites suggest oxygen fugacities between 2.9 and 5.8 log units below the quartz-fayalite-magnetite buffer at 50 kbar, and temperatures between 1280 and 1490 degreesC prevailed during diamond formation. Inclusions from diamonds of lower C-13 content do not indicate systematically lower fO(2) values during their formation. The fO(2)/T conditions determined suggest minimal (0.0 to -0.5 parts per thousand) isotope fractionation between a C-H-O vapor phase (carbon dioxide, carbon monoxide, methane, water, hydrogen) and diamond. The large C-13 depletion of some Venetia P-Type diamonds appears to be unrelated to the composition of their inclusions, igneous fractionation trends, oxygen fugacity, and vapor isotope fractionation processes. This conclusion is consistent with evidence deduced from more limited data sets from other kimberlites.
412wtTimes Cited:31Cited References Count:90

Installation of a 134-sample MC-SNICS at the NOSAMS facility and first results - Bellino, Mary; von Reden, Karl F.; Schneider, Robert J.; Long, Patricia Long; Healy, Richard (Symposium of NorthEastern Accelerator Personnel, Oak Ridge National Lab., USA, October 25-28, 1999, 2001)
id: 1718

The last interglacial to glacial transition, Togiak Bay, Southwestern Alaska - Kaufman, D. S.; Manley, W. F.; Wolfe, A. P.; Hu, F. S.; Preece, S. J.; Westgate, J. A.; Forman, S. L. (Quaternary Research, 2001)
An 18-m-high coastal bluff at Togiak Bay (northwestern Bristol Bay, southwestern Alaska) exposes marine, lacustrine, fluvial, glacial, volcanic, and organic deposits that record the ∼50,000-year-long transition from the peak of the last interglaciation to the early Wisconsin glaciation. The base of the section is dominated by stratified sand and silt extending up to 4.3 m above sea level; marine diatoms are present, and pollen assemblages are characterized by relatively high percentages of Picea, Alnus, and Betula and low percentages of Poaceae and Cyperaceae. The marine sediment was probably deposited during the peak of marine oxygen-isotope stage (OIS) 5e. An infrared stimulated luminescence (IRSL) age of 151,000±13,000 yr from near the base of the exposure is permissive of this correlation. The marine sand and silt are overlain by 0.8 m of peaty silt with diatoms that record a transition from marine to lacustrine conditions. During this interval, Poaceae and Cyperaceae dominate the pollen assemblages, and Picea and shrubs are nearly absent, suggesting that herb tundra occupied the landscape. This interval probably encompasses OIS 5d on the basis of the herb tundra and an IRSL age of 119,000±10,000 yr from 60 cm below the marine/lacustrine transition. The organic mud is overlain by 3.1 m of stratified sand and organic silt that apparently record shallowing of the lake; reappearance of spruce and shrubs (=OIS 5c?); and subsequent deepening of the lake (=OIS 5b?); followed by aggradation of a floodplain (=OIS 5a?), which was dry at the time basaltic lava buried the site. Thermoluminescence analyses on lava-baked sediment indicate that the eruption occurred 70,000±10,000 yr ago. Sometime thereafter, but prior to 53,600 14C yr B.P. an outlet of the Ahklun Mountains ice cap advanced over the site and deposited ∼7 m of bouldery ice-contact drift. The sedimentary sequence contains at least four tephra beds. Major- and trace-element chemistry provide a basis for correlating two of the tephras with tephra beds at nearby sites. The tephras, luminescence ages, and correlations with marine isotope stages provide the geochronological control to place the Togiak Bay section into a global context. The site serves as an important new reference section for late Pleistocene paleoenvironmental change in eastern Beringia.
id: 1392

A marine record of holocene climate events in tropical South America - Haug, G. H.; Hughen, K. A.; Sigman, D. M.; Peterson, L. C.; Rohl, U. (Science, 2001)
id: 1466

New records show pronounced changes in Arctic Ocean circulation and climate (cover article) - Darby, D.; Bischof, J.; Cutter, G.; de Vernal, A.; Hillaire-Marcel, C.; Dwyer, G.; McManus, J.; Polyak, L.; Osterman, L.; Poore, R. (EOS, Transactions, American Geophysical Union, 2001)
id: 332

Optical dating, ages, and scatter from tsunami-laid sands from Bradley Lake, Oregon - Ollerhead, Jeff; Huntley, David J.; Nelson, Alan R.; Kelsey, Harvey M. (Quaternary Science Reviews, 2001)
id: 1406

Optical dating of tsunami-laid sand from an Oregon coastal lake - Ollerhead, J.; Huntley, D. J.; Nelson, A. R.; Kelsey, H. M. (Quaternary Science Reviews, 2001)
Optical ages for five samples of tsunami-laid sand from an Oregon coastal lake were determined using an infrared optical-dating method on K-feldspar separates and, as a test of accuracy, compared to ages determined by AMS C-14 dating or detrital plant fragments found in the same beds. Two optical ages were about 20% younger than calibrated C-14 ages of about 3.1 and 4.3 ka. Correction of the optical ages using measured anomalous fading rates brings them into agreement with the C-14 ages. The approach used holds significant promise for improving the accuracy of infrared optical-dating methods.Luminescence data for the other three samples result in optical age limits much greater than the C-14 ages. These data provide a textbook demonstration of the correlation between scatter in the luminescence intensity of individual sample aliquots and their normalization values that is expected when the samples contain sand grains not adequately exposed to daylight just prior to or during deposition and burial. Thus, the data for these three samples suggest that the tsunamis eroded young and old sand deposits before dropping the sand in the lake. (C) 2001 Elsevier Science Ltd. All rights reserved.
500nqTimes Cited:24Cited References Count:39

Origins of lipid biomarkers in Santa Monica Basin surface sediment: A case study using compound-specific D14C analysis - Pearson, A.; McNichol, A. P.; Benitez-Nelson, B. C.; Hayes, J. M.; Eglinton, T. I. (Geochimica et Cosmochimica Acta, 2001)
id: 1419

Paleoclimate through the ages from the Cariaco Basin, Abstract - Hughen, K. A.; Peterson, L. C.; Black, D.; Haug, G.; Poore, R. (American Geophysical Union, 2001)
id: 1467

Persistent solar influence on North Atlantic climate during the Holocene - Bond, G.; Kromer, B.; Beer, J.; Muscheler, R.; Evans, M. N.; Showers, W.; Hoffmann, S.; Lotti-Bond, R.; Hajdas, I.; Bonani, G. (Science, 2001)
Surface winds and surface ocean hydrography in the subpolar North Atlantic appear to have been influenced by variations in solar output through the entire Holocene. The evidence comes from a close correlation between inferred changes in production rates of the cosmogenic nuclides carbon-14 and beryllium-10 and centennial to millennial time scale changes in proxies of drift ice measured in deep-sea sediment cores. A solar forcing mechanism therefore may underlie at least the Holocene segment of the North Atlantic's "1500-year" cycle. The surface hydrographic changes may have affected production of North Atlantic Deep Water, potentially providing an additional mechanism for amplifying the solar signals and transmitting them globally.
id: 1397; Bond, G Kromer, B Beer, J Muscheler, R Evans, M N Showers, W Hoffmann, S Lotti-Bond, R Hajdas, I Bonani, G New York, N.Y. Science. 2001 Dec 7;294(5549):2130-6. Epub 2001 Nov 15.

Proceedings of a Workshop on Alkenone-Based Paleoceanographic Indicators (Introduction to special issue of journal) - Eglinton, T. I.; Conte, M. H.; Eglinton, G.; Hayes, John M. (Geochem. Geophys. Geosyst., 2001)
id: 1739

Stratigraphic Development of a Northeastern South Carolina Barrier Island: Waites Island - Wright, E.; Harris, M. S.; Sapp, A.; Lewis, K.; Kruse, S.; Edgar, T. (Geological Society of America National Meeting, Abstracts with Program, 2001)
id: 1410

Tropical cooling and the isotopic composition of precipitation in general circulation model simullations of the ice age climate - Charles, C. D.; Rind, D.; Healy, R.; Webb, R. (Climate Dynamics, 2001)
id: 1716

U-Th dating of carbonate platform and slope sediments - Henderson, G. M.; Slowey, N. C.; Fleisher, M. Q. (Geochimica Et Cosmochimica Acta, 2001)
Absolute chronology of marine sediment beyond the C-14 age range provides a test for models of climate change and has many other applications. U-Th techniques have been used for such chronology by dating corals, but extending these techniques to marine sediment is complicated by the presence of significant initial Th-230-both in detrital material and scavenged from seawater. In this study, we investigate four methods of solving the initial Th-230 problem for a particular type of marine sediment-the aragonite-rich sediments of carbonate platforms and slopes. Bulk sediment U-Th analyses can be corrected for initial Th to yield ages with approximate to2 to 3 kyr precision for highstand periods when sediment aragonite contents are particularly high. Uncertainty on the corrections causes inadequate precision for sediment from other periods, however. Removal of scavenged Th before analysis would enable a dramatic increase in this precision but has not proved successful despite a range of chemical leach approaches. Using heavy liquids to separate the various carbonate minerals found in Bahamas sediment enables an isochron approach to correct for initial Th, but the presence of initial Th from two sources requires correction or removal of one source of initial Th before the other is deconvolved by the isochron. Quantitative removal of detrital material before isochron analysis proves a successful approach. Such isochron data demonstrate that, although sediment remains closed to U-Th on a centimetre scale, nuclides are moved from grain to grain by alpha -recoil. Such intergrain exchange is expected to be observed in all sediments containing mineral grains with different U concentrations. Measured U-234/U-238 allows the recoil movement to be corrected and results in isochron ages with precision sometimes as low as 3 kyr. The accuracy of this approach has been proved by dating samples within the 14C age range. Sediments spanning the penultimate deglaciation have also been dated. After a small correction for bioturbation, the age for this event is found to be 135.2 +/- 3.5 ka. TWs date is approximate to8 kyr before the peak in northern hemisphere insolation and suggests that deglaciation is initiated by a mechanism in the southern hemisphere or tropics. This isochron approach shows considerable promise for dating of sediments older than this event, which will provide further information about the timing and mechanisms of global climate change. Copyright (C) 2001 Elsevier Science Ltd.
462zlTimes Cited:49Cited References Count:44

Validation of compound-specific 14C dating using the varved sedimentary record of Saanich Inlet, Canada - Smittenberg, R. H.; Hopmans, E. C.; Eglinton, T. I.; Hayes, J. M.; Whiticar, M. J.; Schouten, S.; Sinninghe Damsté, J. S. (Proceedings of the 20th international meeting on organic geochemistry, 2001)
id: 270

Vegetation succession and carbon sequestration in a coastal wetland in northwestern Florida: evidence from carbon isotopes - Choi, Y.; Wang, Y.; Hsieh, Y. P.; Robinson, L. (Global Biogeochemical Cycles, 2001)
id: 267

Were Rhyolitic Glasses in the Vedde Ash and in the North Atlantic's Ash Zone 1 produced by the Same Volcanic Eruption? - Bond, G. C.; Mandeville, C.; Hoffmann, S. (Quaternary Science Reviews, 2001)
New evidence from North Atlantic deep-sea sediment cores suggests that rhyolitic glass shards in Ash Zone 1 and in the Vedde Ash may not have been produced by the same eruption as has been widely assumed. Our argument is based on (1) a marine ice-rafted deposit approximately 1000 years older than the Vedde Ash contains rhyolitic shards with the same major element chemistry as the Vedde Ash itself and (2) coincidence of Ash Zone 1 with an abrupt increase in discharge of glacial icebergs into the North Atlantic. Hence, we cannot rule out the possibility that Vedde-like rhyolitic glasses were erupted onto Icelandic glaciers before eruption of the Vedde Ash, stored in the glacial ice, then dispersed by icebergs into the North Atlantic and deposited partly or entirely as Ash Zone 1. While not disproving that Ash Zone 1 and the Vedde Ash came from the same eruption, our findings indicate that further study is needed to establish the exact relation between the two ash deposits.
id: 253

Acceptance of the 1997 Alfred E. Treibs Award - Hayes, J. M. (Geochimica Et Cosmochimica Acta, 2000)
287naTimes Cited:0Cited References Count:0

Age and composition of carbonate shoreface sediments, Kailua Bay, Oahu, Hawaii - Harney, J. N.; Grossman, E. E.; Richmond, B. M.; Fletcher, C. H. (Coral Reefs, 2000)
The origin, age, and dynamics of carbonate sediments in Kailua Bay on Oahu, Hawaii, are described. The shoreface (from shoreline to 4 km offshore) consists of a broad (5 km(2)) fringing coral reef ecosystem bisected by a sinuous, shore-normal, sand-filled paleostream channel 200-300 m wide. The median grain diameter of surface sands is finest on the beach face (<0.3 mm) and increases offshore along the channel axis. Kailua sands are >90% biogenic carbonate, dominated by skeletal fragments of coralline algae (e.g. Porolithon, up to 50%) followed by the calcareous green alga Halimeda (up to 32%), coral fragments (1-24%), mollusc fragments (6-21%), and benthic foraminifera (1-10%). Sand composition and age across the shoreface are correlated to carbonate production. Corals and coralline algae, principal builders of the reef framework, are younger and more abundant in sands along the channel axis and in offshore reefal areas, while Halimeda, molluscs, and foraminifera are younger and more dominant in nearshore waters shoreward of the main region of framework building. Shoreface sediments are relatively old. Of 20 calibrated radiocarbon dates on skeletal constituents of sand, only three are younger than 500 years B.P.; six are 500-1000 years B.P.; six are 1000-2000 years B.P.; and five are 2000-5000 years B.P. Dated fine sands are older than medium to coarse sands and hence may constitute a reservoir of fossil carbonate that is distributed over the entire shoreface. Dominance of fossiliferous sand indicates long storage times for carbonate grains, which tend to decrease in size with age, such that the entire period of relative sea-level inundation (similar to 5000 years) is represented in the sediment. Despite an apparently healthy modern coral ecosystem, the surficial sand pool of Kailua Bay is dominated by sand reflecting an antecedent system, possibly one that existed under a + 1-2 m sea-level high stand during the mid- to late Holocene.
341wmTimes Cited:32Cited References Count:43

Chesapeake Bay sedimentary record of Holocene climatic variability and human ecosystem disturbance - Cronin, T.; Willard, D.; Karlsen, A.; Ishman, S.; Verardo, S.; McGeehin, J.; Kerhin, R.; Holmes, C.; Colman, S. M.; Zimmerman, A. (Geology, 2000)
id: 184

Chronostratigraphy of sediments in the southern Gulf of California, based on amino acid racemization analysis of mollusks and rhodolith (Book Section) - Goodfriend, G. A.; Halfar, J.; Godinez-Orta, L. (Perspectives in Amino Acid and Protein Geochemistry, 2000)
id: 174

Climate change in the northern American tropics since the last ice age: implications for environment and culture (Book Section) - Hodell, D. A.; Brenner, M.; Curtis, J. H. (Imperfect Balance: Landscape transformations in the Precolumbian Americas, 2000)
id: 198

Evidence from U-Th dating against Northern Hemisphere forcing of the penultimate deglaciation - Henderson, G. M.; Slowey, N. C. (Nature, 2000)
Milankovitch proposed that summer insolation at mid-latitudes in the Northern Hemisphere directly causes the ice-age climate cycles. This would imply that times of ice-sheet collapse should correspond to peaks in Northern Hemisphere June insolation. But the penultimate deglaciation has proved controversial because June insolation peaks 127 kyr ago whereas several records of past climate suggest that change may have occurred up to 15 kyr earlier. There is a clear signature of the penultimate deglaciation in marine oxygen-isotope records. But dating this event, which is significantly before the 14C age range, has not been possible. Here we date the penultimate deglaciation in a record from the Bahamas using a new U-Th isochron technique. After the necessary corrections for alpha-recoil mobility of 234U and 230Th and a small age correction for sediment mixing, the midpoint age for the penultimate deglaciation is determined to be 135 +/- 2.5 kyr ago. This age is consistent with some coral-based sea-level estimates, but it is difficult to reconcile with June Northern Hemisphere insolation as the trigger for the ice-age cycles. Potential alternative driving mechanisms for the ice-age cycles that are consistent with such an early date for the penultimate deglaciation are either the variability of the tropical ocean-atmosphere system or changes in atmospheric CO2 concentration controlled by a process in the Southern Hemisphere.
HendersonSloweyengEngland2000/03/15 09:00Nature. 2000 Mar 2;404(6773):61-6.

Glacial deep water geometry: South Atlantic Benthic foraminiferal Cd/Ca and delta13C evidence - Oppo, Delia W.; Horowitz, Michael (Paleoceanography, 2000)
id: 13050883-8305/00/1999PA000436

Global Distribution of Total Inorganic Carbon and Total Alkalinity Below the Deepest Winter Mixed Layer Depths - Goyet, C.; Healy, R.; Ryan, J. (Carbon Dioxide Information Analysis Center, Oak Ridge National Laboratory, 2000)
Modeling the global ocean-atmosphere carbon dioxide system is becoming increasingly important to greenhouse gas policy. These models require initialization with realistic three- dimensional (3-D) oceanic carbon fields. This report presents an approach to establishing these initial conditions from an extensive global database of ocean carbon dioxide (CO2) system measurements and well-developed interpolation methods. These methods are limited to waters below the deepest mixed layer. The data used for these interpolations include the recent high-quality data sets from the World Ocean Circulation Experiment (WOCE), Joint Global Ocean Flux Study (JGOFS), and Ocean-Atmosphere Carbon Exchange Study (OACES) programs. Prior to analysis, all carbon data were adjusted to established reference material listed in http://andrew.ucsd.edu/co2qc/. The interpolation methodology employs correlation between CO2 system properties and other more widely measured properties: potential temperature, salinity, and apparent oxygen utilization. The correlations are computed for each profile, and the coefficients are interpolated to the 1°×1°×32 vertical-layer grid at a monthly temporal resolution. Finally, the gridded coefficients are applied to a global monthly climatology of ocean temperature, salinity, and oxygen to compute total CO2 (TCO2) and total alkalinity (TALK) for the 3-D grid. This approach offers advantages over spin up of a single profile in defining spatial variation in CO2 system properties because it reduces initialization time and provides a more accurate carbon field. The results provide an unprecedented "view" of the global distribution of TALK and TCO2 in the ocean. These results as well as those from the monthly mixed layer depths can be used in diagnostic and prognostic global ocean models. The data set of the gridded climatological fields of TCO2, TALK, and mixed layer depths is available free of charge as a numeric data package from the Carbon Dioxide Information Analysis Center (CDIAC). The interpolated data set includes seasonal TCO2 and TALK fields as well as the coefficients used to estimate these concentrations and the monthly mixed layer depths.
id: 1970

Ice Core Paleoclimate Records in Tropical South America Since the Last Glacial Maximum - Thompson, L. G.; Mosley-Thompson, E.; Henderson, K. A. (Journal of Quaternary Science, 2000)
id: 245

Lipids as a Common Interest of Microorganisms and Geochemists (Commentary) - Hayes, John M. (Proc. National Academy Sciences USE, 2000)
id: 1778

Los caminos prehispanicos de la amazonia boliviana (Book Section) - Erickson, Clark L. (Vias Precolombinas: los caminos, los ingenieros y los viajeros, 2000)
id: 179

Mapping of C4 plant input from North West Africa into North East Atlantic Sediments - Huang, Yongsong; Dupont, Lydie; Sarnthein, Michael; Hayes, John M.; Eglinton, Geoffrey (Geochimica et Cosmochima Acta, 2000)
id: 1777

Mass spectra of sn-2hydroxyarchaeol, a Polar-lipid Biomarker for Anaerobic Methanotrophy - Hinrichs, Kai-Uwe; Pancost, Richard D.; Summons, Roger E.; Sprott, G. Dennis; Sylva, Sean P.; Sinninghe-Damste, Jaap S.; Hayes, John M. (Geochem. Geophys. Geosyst., 2000)
id: 1735

Memorial to Henry G. Thode, 1910-1997 - Shaw, Denis M.; Epstein, Sam; Hayes, John M. (Geological Society of America Memorials, 2000)
id: 1737

Molecular and isotopic analysis of anaerobic methane-oxidizing communities in marine sediments - Hinrichs, K. U.; Summons, R. E.; Orphan, V.; Sylva, S. P.; Hayes, J. M. (Organic Geochemistry, 2000)
Convergent lines of molecular, carbon-isotopic, and phylogenetic evidence have previously indicated (Hinrichs, K.U., Hayes, J.M., Sylva, S.P., Brewer. P.G.. DeLong, E.F., 1999. Methane-consuming archaebacteria in marine sediments. Nature 398, 802-805.) that archaea are involved in the anaerobic oxidation of methane in sediments from the Eel River Basin. offshore northern California. Now, further studies of those same sediments and of sediments from a methane seep in the Santa Barbara Basin have confirmed and extended those results. Mass spectrometric and chromatographic analyses of an authentic standard of sn-2-hydroxyarchaeol (hydroxylated at C-3 in the sn-2 phytanyl moiety) have confirmed our previous, tentative identification of this compound but shown that the previously examined product was the mono-TMS, rather than di-TMS, derivative. Further analyses of C-13-depleted lipids, appreciably more abundant in samples from the Santa Barbara Basin, have shown that the archaeal lipids are accompanied by two sets of products that are only slightly less depleted in C-13. These are additional glycerol ethers and fatty acids. The alkyl substituents in the ethers (mostly monoethers, with some diethers) are non-isoprenoidal. The carbon-number distributions and isotopic compositions of the alkyl substituents and of the fatty acids are similar, suggesting strongly that they are produced by the same organisms. Their structures, n-alkyl and methyl-branched n-alkyl, require a bacterial rather than archaeal source. The non-isoprenoidal glycerol ethers are novel constituents in marine sediments but have been previously reported in thermophilic, sulfate- and nitrate-reducing organisms which lie near the base of the rRNA-based phylogenetic tree. Based on previous observations that the anaerobic oxidation of methane involves a net transfer of electrons from methane to sulfate, it appears likely that the non-archaeal, C-13-depleted lipids are products of one or more previously unknown sulfate-reducing bacteria which grow syntrophically with the methane-utilizing archaea. Their products account for 50% of the fatty acids in the sample from the Santa Barbara Basin. At all methane-seep sites examined, the preservation of aquatic products is apparently enhanced because the methane-oxidizing consortium utilizes much of the sulfate that would otherwise be available for remineralization of materials from the water column. Crown Copyright (C) 2000 Published by Elsevier Science Ltd. All rights reserved.
384quTimes Cited:204Cited References Count:49

The N and W Iceland Shelf: insights into Last Glacial Maximum ice extent and deglaciation based on acoustic stratigraphy and basal radiocarbon AMS dates - Andrews, J. T.; Hardardottir, J.; Helgadottir, G.; Jennings, A. E.; Geirsdottir, A.; Sveinbjornsdottir, A. E.; Schoolfield, S.; Kristjansdottir, G. B.; Smith, L. M.; Thors, K.; Syvitski, J. P. M. (Quaternary Science Reviews, 2000)
We present 32 AMS radiocarbon dates collected from sediments obtained during cruises of CSS Hudson (1993, RV Jan Mayen (1996), and Bjarni Saemundsson (1997). The radiocarbon dates were obtained on samples from the basal part of sediment cores collected across an area between 64 and 67 degrees N and 18-29 degrees W. Core sites were based on 3.5 kHz acoustic subbottom surveys. The 3.5 kHz subbottom profiles indicate that several of the troughs contain greater than or equal to 30 m of Quaternary sediment. At many sites, the acoustic surveys suggest the presence of one or more strong reflectors which can be traced over extended areas ( > 100 km) of the seafloor. These may represent large-scale volcanic ash falls, such as the Vedde ash and its correlatives, as well as other regionally significant tephras. We report dates from seven areas; (1) Northern troughs - Eyjafjardarall, Hunafloadjup, and Reykjafjardarall: (2) Hunafloi area and inner shelf and fjords; (3) Djupall area; (4) Isafjardardjup area; (5) Kolluall; (6) western shelf break and slope; and 7) Jokuldjup. The dates range in age from Marine Isotope Stages 3-1. Five cores have basal dates greater than or equal to 16 ka and thus provide information on the timing and environments during the deglaciation, Several dates of similar to 12 ka indicate that the inner shelf may have been largely ice-free by that time. Estimates of average sediment accumulation rates vary between 4 and 90 cm/kyr, with modal estimates of 30-30 cm/kyr, (C) 2000 Elsevier Science Ltd. All rights reserved.
298udTimes Cited:71Cited References Count:75

The origin of Antarctic precipitation: a modelling approach - Delaygue, G.; Masson, V.; Jouzel, J.; Koster, R. D.; Healy, R. J. (Tellus Series B-Chemical and Physical Meteorology, 2000)
The contribution of different moisture sources to Antarctic precipitation for present-day and glacial conditions is estimated with the NASA/GISS Atmospheric General Circulation Model. Despite its low horizontal resolution (8 degrees x 10 degrees), this model simulates reasonably well the broad features of the observed present-day hydrological cycle. Simulated present-day Antarctic precipitation is dominated throughout the year by moisture from a subtropical/midlatitude band (30 degrees S-60 degrees S). The moisture supplied to a given coastal area of Antarctica originates mostly in the adjacent oceanic basin; closer to the pole, other oceanic basins can also contribute significantly. Replacing the present-day sea surface temperatures (SSTs) and sea ice cover in the GCM with those from the CLIMAP oceanic reconstruction for the last glacial maximum (LGM), greatly increases the simulated latitudinal temperature gradient, with the consequence of slightly enhancing the contribution of low latitude moisture to Antarctic precipitation. It also changes the seasonality of the different contributions and thus their budget, particularly in coastal regions. Because the nature of LGM tropical SSTs is still under debate, Ne performed an additional LGM simulation in which the tropical SSTs are reduced relative to those of CLIMAP. The resulting decrease in the latitudinal gradient brings the relative contributions to Antarctic precipitation more in line with those of the present-day simulation.
id: 1942; PT: J; UT: WOS:000085432600002

Osmium isotopes demonstrate distal trnasport of contaminated sediments in Chesapeake Bay - Helz, G. R.; Adelson, J. M.; Miller, C. V.; Cornwell, J. C.; Hill, J. M.; Horan, M.; Walker, R. J. (Environmental Science Technology, 2000)
id: 1371

OxCal analyses and varve-based sedimentation rates constrain the times of 14C-dated tsunamis in southern Oregon - Nelson, A. R.; Kelsey, H. M.; Hemphill-Haley, Eileen; Witter, R. C. (Abstract for Geological Society of America Penbrose Conference on Great Cascadia Earthquake Tricentennial Seaside, 2000)
id: 1405

Particle mixing and sediment accumulation rates of Peconic Estuary sediments: A sediment accretion study in support of the Peconic Estuary Program (Report) - Cochran, J. K.; Hirschberg, D. J.; Amiel, D. (2000)
id: 1344

Radiocarbon calibration and abruptchanges in atmospheric 14Cconcentration during Marine Isotope Stage 3 - Hughen, K. A.; Southon, J.; Lehman, S. J.; Peterson, L. C.; Overpeck, J. T. (American Geophysical Union, 2000)
id: 327

Stable- and radio-carbon isotopic composition of porewater DOC in an organic-rich marine sediment - Alperin, M. J.; Hee, C. A.; Albert, D. A.; Martens, C. S. (EOS, 2000)
id: 1438

Stable chlorine isotopic compositions of aroclors and aroclor-contaminated sediments - Reddy, C. M.; Heraty, L. J.; Holt, B. D.; Sturchio, N. C.; Eglinton, T. I.; Drenzek, N. J.; Xu, L.; Lake, J. L.; Maruya, K. A. (Environmental Science & Technology, 2000)
An exploratory investigation was conducted to evaluate if stable chlorine isotopic ratios of polychlorinated biphenyls (PCBs) could be useful in studying the processes that determine their transport and fate in the environment First, we determined the variability of delta(37)Cl in the source materials for PCBs. Second, we determined if the delta(37)Cl values of contaminated environmental samples fell outside the range in source variability. The isotopic variability among the source materials (Aroclors) was rather small; delta(37)- Cl values ranged from -3.37 to -2.11% (mean and standard deviation, -2.78 +/- 0.39%, n = 12). There was no correlation between the delta(37)Cl values and percentages of chlorine in the mixtures. We also found very similar values in several Clophen mixtures and one Phenoclor. The delta(37)Cl values in the total PCBs isolated from Aroclor-contaminated sediments from the Hudson River, New Bedford Harbor, and Turtle River Estuary ranged from -4.54 to -2.25% (n = 19). While most of the delta(37)Cl values were within 2 standard deviations of the mean Aroclor value (our assumed estimate for overall source variability), two of the PCB contaminated sediment samples from New Bedford Harbor did appear to be isotopically distinct. The PCBs in these sediments had lower amounts of less chlorinated congeners (when compared to the source material) and were likely isotopically affected by alteration processes that preferentially removed these congeners. Compound specific measurements of two congeners in Aroclor 1268 suggest that there are no large congener-specific differences in the stable chlorine isotope ratios in Aroclors. This study shows that the delta(37)Cl Values of PCBs may be a potentially useful diagnostic tool in studying the transport and fate of PCBs and indicates that additional research is warranted.
330rcTimes Cited:39Cited References Count:16

Tests of positive ion beams from a microwave ion source for AMS - Schneider, R. J.; von Reden, K. F.; Hayes, J. M.; Wills, J. S. C.; Kern, W. G. E.; Kim, S. W. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2000)
A test facility has been constructed to evaluate high-current positive ion beams from small gaseous samples for AMS applications. The major components include a compact permanent magnet microwave ion source built at the AECL Chalk River Laboratory and now on loan from the University of Toronto, and a double-focusing spectrometer magnet on loan from Argonne National Laboratory. Samples are introduced by means of a silica capillary injection system. Loop injection into a carrier gas provides a stable feed for the microwave driven plasma. The magnetic analysis system is utilized to isolate carbon ions derived from CO? samples from other products of the plasma discharge, including argon ions of the carrier gas. With a smaller discharge chamber, we hope to exceed a conversion efficiency of 14% for carbon ions produced per atom, which we reported at AMS-7. The next step will be to construct an efficient charge-exchange cell, to produce negative ions for injection into the WHOI recombinator injector. (C) 2000 Elsevier Science B.V. All rights reserved.
372jrTimes Cited:16Cited References Count:4

Was it melt-water outflor or ice-sheet discharge? A high-resolution study of ice-sheet discharge from the high-latitude sector of the LIS during the LGM - Rashid, H.; Hesse, R.; Piper, D. J. W. (EOS, 2000)
id: 138

2-Methylhopanoids as biomarkers for cyanobacterial oxygenic photosynthesis - Summons, R. E.; Jahnke, L. L.; Hope, J. M.; Logan, G. A. (Nature, 1999)
Oxygenic photosynthesis is widely accepted as the most important bioenergetic process happening in Earth's surface environment(1). It is thought to have evolved within the cyanobacterial lineage, but it has been difficult to determine when it began. Evidence based on the occurrence and appearance of stromatolites(2) and microfossils' indicates that phototrophy occurred as long ago as 3,465 Myr although no definite physiological inferences can be he made from these objects. Carbon isotopes and other geological phenomena(4,5) provide clues but are also equivocal, Biomarkers are potentially useful because the three domains of extant life-Bacteria, Archaea and Eukarya-have signature membrane lipids with recalcitrant carbon skeletons. These lipids turn into hydrocarbons in sediments and can be found wherever the record is sufficiently well preserved. Here we show that 2-methylbacteriohopanepolyols occur in a high proportion of cultured cyanobacteria and cyanobacterial mats, Their 2-methylhopane hydrocarbon derivatives are abundant in organic-rich sediments as old as 2,500 Myr. These biomarkers may help constrain the age of the oldest cyanobacteria and the advent of oxygenic photosynthesis. They could also be used to quantify the ecological importance of cyanobacteria through geological time.
223rtTimes Cited:510Cited References Count:28

The abundance of 13C in marine organic matter and isotopic fractionation in the global biogeochemical cycle of carbon during the past 800 Ma - Hayes, John M.; Strauss, Harald; Kaufman, Alan J. (Chemical Geology, 1999)
id: 1547

Application of a compact microwave ion source to radiocarbon analysis - Schneider, R. J.; von Reden, K. F.; Hayes, J. M.; Wills, J. S. C. (The eighth international conference on heavy-ion accelerator technology, 1999)
The compact, high current, 2.45 GHz microwave-driven plasma ion source which was built for the Chalk River TASCC facility is presently being adapted for testing as a gas ion source for accelerator mass spectrometry, at the Woods Hole Oceanographic Institution accelerator mass spectrometer. The special requirements for producing carbon-ion beams from micromole quantities of carbon dioxide produced from environmental samples will be discussed. These samples will be introduced into the ion source by means of argon carrier gas and a silicon capillary injection system. Following the extraction of positive ions from the source, negative ion formation in a charge exchange vapor will effectively remove the argon from the carbon beam. Simultaneous injection of the three carbon isotopes into the accelerator is planned.
id: 1977
Keywords: carbon; ion sources; mass spectroscopy; spectrochemical analysis; tandem accelerators

Application of Compact Microwave Ion Source to Radiocarbon Analysis - Schneider, R. J.; von Reden, K. F.; Hayes, J. M.; Wills, J. S. C. (8th International Conference on Heavy Ion Accelerator Technology, 1999)
id: 1824

An Archaeological Investigation of Late Archaic Cerros de Trincheras Sites in Chihuahua, Mexico - Hard, R.; Roney, J. (University of Texas, Center for Archaeological Research, 1999)
id: 1389

Biogenic silica records from the BDP-93 drill site and adjacent areas of the Selenga Delta, Lake Baikal, Siberia - Colman, S. M.; Peck, J. A.; Hatton, J.; Karabanov, E. B.; King, J. W. (Journal of Paleolimnology, 1999)
id: 186

Carbon sequestration and vegetation succession in a coastal wetland in northwest Florida (abstract) - Choi, Y.; Wang, Y.; Hsieh, Y.; Robinson, L. (Spring meeting of American Geophysical Union, 1999)
id: 164

Climate change in the Lake Valencia Basin, Venezuela, approximately 12,600 yr BP to present - Curtis, J. H.; Brenner, M.; Hodell, D. A. (The Holocene, 1999)
id: 197

Deltas, radiocarbon dating, and measurements of sediment storage and subsidence - Stanley, D. J.; Hait, A. K. (Geology, 1999)
id: 1376

The distribution and carbon isotopic composition of dissolved organic matter in Florida Everglades (abstract) - Wang, Y.; Hsieh, Y. P.; Landing, W. M.; Salters, V.; Cooper, W.; Proctor, L. (The Sixth Symposium on Biogeochemistry of Wetlands, 1999)
id: 165

Fractionation of hydrogen isotopes in lipid biosynthesis - Sessions, A. L.; Burgoyne, T. W.; Schimmelmann, A.; Hayes, J. M. (Organic Geochemistry, 1999)
Isotopic compositions of carbon-bound hydrogen in individual compounds from eight different organisms were measured using isotope-ratio-monitoring gas chromatography-mass spectrometry. This technique is capable of measuring D/H ratios at natural abundance in individual lipids yielding as little as 20 nmol of H-2, and is applicable to a wide range of compounds including hydrocarbons, sterols, and fatty acids. The hydrogen isotopic compositions of lipids are controlled by three factors: isotopic compositions of biosynthetic precursors, fractionation and exchange accompanying biosynthesis, and hydrogenation during biosynthesis. delta D values of lipids from the eight organisms examined here suggest that all three processes are important for controlling natural variations in isotopic abundance. n-Alkyl lipids are depleted in D relative to growth water by 113-262 parts per thousand, while polyisoprenoid lipids are depleted in D relative to growth water by 142-376 parts per thousand. Isotopic variations within compound classes (e.g., n-alkanes) are usually less than similar to 50 parts per thousand, but variations as large as 150 parts per thousand are observed among isoprenoid lipids from a single organism. Phytol is consistently depleted in D by up to 50 parts per thousand relative to other isoprenoid lipids. Inferred isotopic fractionations between cellular water and lipids are greater than those indicated by previous studies. (C) 1999 Elsevier Science Ltd. All rights reserved.
254efTimes Cited:281Cited References Count:26

Holocene depositional patterns, neotectonics and Sundarban Mangroves in the western Ganges-Brahmaputra delta - Stanley, D. J.; Hait, A. (Jour. Coastal Res., 1999)
id: 229

Interdisciplinary environmental project probes Chesapeake Bay down to the core - Cronin, T.; Colman, S. M.; Willard, D.; Kerhin, R.; Holmes, C.; Karlsen, A.; Ishman, S.; Bratton, J. (EOS, 1999)
id: 185

Methane-consuming archaebacteria in marine sediments - Hinrichs, K. U.; Hayes, J. M.; Sylva, S. P.; Brewer, P. G.; DeLong, E. F. (Nature, 1999)
Large amounts of methane are produced in marine sediments but are then consumed before contacting aerobic waters or the atmosphere. Although no organism that can consume methane anaerobically has ever been isolated, biogeochemical evidence indicates that the overall process involves a transfer of electrons from methane to sulphate and is probably mediated by several organisms, including a methanogen (operating in reverse) and a sulphate-reducer (using an unknown intermediate substrate). Here we describe studies of sediments related to a decomposing methane hydrate. These provide strong evidence that methane is being consumed by archaebacteria that are phylogenetically distinct from known methanogens. Specifically, lipid biomarkers that are commonly characteristic of archaea are so strongly depleted in carbon-13 that methane must be the carbon source, rather than the metabolic product, for the organisms that have produced them. Parallel gene surveys of small-subunit ribosomal RNA (16S rRNA) indicate the predominance of a new archael group which is peripherally related to the methanogenic orders Methanomicrobiales and Methanosarcinales.
Hinrichs, K UHayes, J MSylva, S PBrewer, P GDeLong, E FengResearch Support, Non-U.S. Gov'tResearch Support, U.S. Gov't, Non-P.H.S.England1999/05/11 02:03Nature. 1999 Apr 29;398(6730):802-5.

New Developments at the NOSAMS Facility - von Reden, K. F.; Schneider, R. J.; McNichol, A. P.; Hayes, J. M.; Pearson, A.; Eglinton, T. I. (Proceeding of the International Workshop on Frontiers in Accelerator Mass Spectrometry, 1999)
id: 1723(JISTEC)

New Developments at the NOSAMS Facility - von Reden, K. F.; Schneider, R. J.; McNichol, A. P.; Hayes, J. M.; Pearson, A.; Eglinton, T. I. (International Workshop on Frontiers in Accelerator Mass Spectrometry, 1999)
id: 1679

The North Atlantic's 1-2 kyr climate rhythm: Relation to Heinrich events, Dansgaard/Oeschger cycles and the Little Ice Age (Book Section) - Bond, G. C.; Showers, W.; Elliot, M.; Evans, M.; Lotti, R.; Hajdas, I.; Bonani, G.; Johnson, S. (Mechanisms of global climate change at mellennial time scales, 1999)
id: 216

Paleoclimate of Southwestern China for the past 50,000 yr inferred from lake sediment records - Hodell, D. A.; Brenner, M.; Kanfoush, S. L.; Curtis, J. H.; Stoner, J. S.; Song, X. L.; Yuan, W.; Whitmore, T. J. (Quaternary Research, 1999)
Long sediment cores (12.5 and 13.5 m) from two lakes in Yunnan Province were used to infer the paleoclimate of southwest China over the past 50,000 yr, During the Holocene and marine isotope stage (MIS 3), bio-induced carbonate precipitation and organic matter (OM) production was high, suggesting warm temperatures and high primary productivity. In contrast, sediment inorganic carbon (IC) and organic carbon (OC) concentrations were low in last glacial deposits from 38,000 to 12,000 cal yr B.P., indicating cool temperatures and low productivity. The 50,000-yr record has alternating peaks of carbonate and coarse-grain (>38 mu m) quartz that reflect warm, moist interglacial or interstadial conditions alternating with cold, dry glacial or stadial conditions, respectively. Spectral analysis of the carbonate and quartz signals reveals power concentrated at periods of 7200 and 8900 cal yr, respectively, that may reflect a nonlinear climate response to precessional forcing at a time of reduced eccentricity modulation (McIntyre and Molfino, 1996). Oxygen isotope values of calcite from Yunnan lake cores indicate the summer monsoon was weak during the last glaciation from 50,000 to 12,000 cal yr B.P. The summer monsoon intensified between 12,000 and 8000 cal yr B.P., but weakened gradually in response to insolation forcing during the mid-to-late Holocene. Our results support the Overpeck ef al. (1996) model that posits a weak summer monsoon during the last glaciation that responded nonlinearly to insolation forcing when its intensity was affected by Eurasian snow cover and ice-sheet extent. The summer monsoon intensified and responded linearly to seasonal insolation forcing in the Holocene when ice volume diminished. (C) 1999 University of Washington.
255ltTimes Cited:85Cited References Count:58

Records of Heinrich Events at the confluence of the distal Northwest Atlantic Mid-Ocean Channel, and the Immarssauk Mid-Ocean Channel of the North Atlantic, Europ. Union - Rashid, H.; Hesse, R.; Piper, D. J. W. (Geoscience 10th Annual Meeting, 1999)
id: 137; 1

The role of oceanic forcing in mid-Holocene Northern Hemisphere climatic change - Kerwin, M. W.; Overpeck, J. T.; Webb, R. S.; DeVernal, A.; Rind, D. H.; Healy, R. J. (Paleoceanography, 1999)
Previous model investigations suggested that changes in orbital forcing and feedbacks associated with northward expansion of the boreal forest were both required to explain the full magnitude of enhanced high-latitude Northern Hemisphere summer warming at 6 ka, thus implying that biospheric feedbacks (decreased planetary albedo associated with forest expansion) may be large in the future [Foley ct at., 1994; TEMPO (Testing Earth System Models with Paleo-Observations), 1996]. Before the magnitude of past biospheric and other feedbacks can be estimated with confidence, however, the role of realistic high-latitude oceanic forcing (i.e., sea surface temperature (SST) increases and sea ice reductions) should also be considered. Here we review existing paleoceanographic observations that suggest portions of the North Atlantic were up to 4 degrees C warmer than today at 6 ka. We then combine our estimates of mid-Holocene North Atlantic SST and sea ice conditions with new climate model simulations to suggest that a significant portion of high-latitude summer warming at 6 ka in the Northern Hemisphere can be accounted for by altered orbital forcing, SSTs, and sea ice relative to today. Our results underscore the importance of incorporating realistic boundary conditions when using paleoenvironmental data to evaluate the climate system's sensitivity to altered forcing and suggest that high-latitude oceanic feedbacks were major contributors to enhanced high-latitude summer warming in the Northern Hemisphere at 6 ka.
id: 1943; PT: J; UT: WOS:000079325100009

Sedimentary organic matter preservation: A test for selective degradation under oxic conditions - Hedges, J. I.; Hu, F. S.; Devol, A. H.; Hartnett, H. E.; Tsamakis, E.; Keil, R. G. (American Journal of Science, 1999)
We report here a test of the hypothesis that the extent of organic matter preservation in continental margin sediments is controlled by the average period accumulating particles reside in oxic porewater immediately beneath the water/sediment interface. Oxygen penetration depths, organic element compositions, and mineral surface areas were determined for 16 sediment cores collected along an offshore transect across the Washington continental shelf, slope, and adjacent Cascadia Basin. Individual amino acid, sugar, and pollen distributions were analyzed for a 11 to 12 cm horizon from each core, and (14)C-based sediment accumulation rates and stable carbon isotope compositions were determined from depth profiles within a subset of six cores from representative sites. Sediment accumulation rates decreased, and dissolved O(2) penetration depths increased offshore along the sampling transect. As a result, oxygen exposure times (OET) increased seaward from decades (mid-shelf and upper slope) to more than a thousand years (outer Cascadia Basin). Organic contents and compositions were essentially constant within individual sediment cores but varied consistently with location. In particular, organic carbon/surface area ratios decreased progressively offshore and with increasing OET. Three independent compositional parameters demonstrated that the remnant organic matter in farther offshore sediments is more degraded. Both concentration and compositional patterns indicated that sedimentary organic matter exhibits a distinct and reproducible "oxic effect" OET helps integrate and explain organic matter preservation in accumulating continental margin sediments and hence provides a useful tool for assessing transfer of organic matter from the biosphere to the geosphere.
263rmTimes Cited:194Cited References Count:104

Simulated time-dependent climate response to solar radiative forcing since 1600 - Rind, D.; Lean, J.; Healy, R. (Journal of Geophysical Research-Atmospheres, 1999)
Estimated solar irradiance variations since 1500 have been used to force the GISS atmospheric GCM coupled to a mixed layer "q-flux" ocean with heat diffusion through the bottom of the mixed layer. The goal is to assess solar-induced climate change in preindustrial and postindustrial epochs. Six simulations and control runs were made to test the effects of different initial conditions, estimates of initial solar forcing conditions, and ocean heat uptake. The results show that an estimated solar forcing increase of 0.25% accounts for a 0.45 degrees C temperature increase since 1600 and an increase of about 0.2 degrees C over the past 100 years. Global surface temperatures lag solar fluctuations by up to 10 years; the lag is greater over the oceans and so is the correlation due to reduced noise. With only a mixed layer ocean the phase lag is 5 years less. Solar forcing and water vapor feedback each directly account for 35% of the temperature response, with cloud cover changes contributing 20% and sea ice/snow cover 10%. Uncertainty in the initial radiation imbalance or solar forcing affects the surface temperatures for 60-90 years. Modeled and observed periodicities show dominance of long-period forcing (>50 years), as provided by the solar input in these experiments. Tropical temperatures correlate best with solar forcing, due to the influence of water vapor feedback, especially at these multidecadal periods. Sea ice and extratropical temperatures have less long-period power, while high-frequency fluctuations dominate simulated cloud cover variations, which are relatively independent of solar forcing changes. Global and extratropical precipitation increase as the climate warms, but not low and subtropical precipitation, due to conflicting influences of absolute temperature and temperature gradient changes. Solar forcing by itself was not sufficient to produce the rapid warming during the last several decades. A comparison experiment varying trace gas forcing suggests that if the solar estimate is correct, then negative forcing by tropospheric aerosols (and perhaps volcanoes, ozone, and land use changes) has been about -1.2 W m(-)2 since 1700, implying approximately equal contribution from direct and indirect tropospheric aerosol effects.
id: 1945; PT: J; UT: WOS:000078242200003

The speciation and sources of dissolved phosphorus in the Everglades (Report) - Copper, W.; Hsieh, Y. P.; Landing, W. M.; Proctor, L.; Salters, V.; Wang, Y. (1999)
id: 1348

Terminal Proterozoic Mid-Shelf Benthic Microbial Mats in the Centralian Supervasin and their Environmental Significance - Logan, Graham A.; Calver, Clive R.; Gorjan, Paul; Summons, Roger E.; Hayes, John M.; Walter, Malcolm R. (Geochimica et Cosmochimica Acta, 1999)
id: 1734

Terrace Construction in Northern Chihuahua, Mexico at 1150 B.C. and the Present - Hard, R.; Roney, J.; Zapata, J.; Moses, B. (Journal of Field Archaeology, 1999)
id: 238

Use of Hydrogen and Carbon Stable Isotopes in the Characterization of Oils from the Potiguar Basin (onshore), Northeastern Brazil - Neto, Eugenio Vaz dos Santos; Hayes, John M. (Bulletin of the American Association of Petroleum Geologists, 1999)
id: 1732

Variability in shallow- and intermediate-water hydrography during the last climate cycle of the Quaternary - McManus, J. F.; Healey, S. L.; Oppo, D. W.; Curry, W. B. (EOS, 1999)
id: 170

Warm-temperate to subtropical shallow water carbonates of the southern Gulf of California and geochemistry of rhodoliths (Thesis) - Halfar, J. (Stanford University, 1999)

A 25,000-year tropical climate history from bolivian ice cores - Thompson, L. G.; Davis, M. E.; Mosley-Thompson, E.; Sowers, T. A.; Henderson, K. A.; Zagorodnov, V. S.; Lin, P.; Mikhalenko, V. N.; Campen, R. K.; Bolzan, J. F.; Cole-Dai, J.; Francou, B. (Science, 1998)
Ice cores that were recovered from the summit of Sajama mountain in Bolivia provide carbon-14-dated tropical records and extend to the Late Glacial Stage (LGS). Oxygen isotopic ratios of the ice decreased 5.4 per mil between the early Holocene and the Last Glacial Maximum, which is consistent with values from other ice cores. The abrupt onset and termination of a Younger Dryas-type event suggest atmospheric processes as the probable drivers. Regional accumulation increased during the LGS, during deglaciation, and over the past 3000 years, which is concurrent with higher water levels in regional paleolakes. Unlike polar cores, Sajama glacial ice contains eight times less dust than the Holocene ice, which reflects wetter conditions and extensive snow cover.
ThompsonDavis Mosley-Thompson Sowers Henderson Zagorodnov Lin Mikhalenko Campen Bolzan Cole-Dai Francou eng 1998/12/04 03:02 Science. 1998 Dec 4;282(5395):1858-64.

Controls of chemical and isotopic composition of Lake water, Peten, Guatemala and implications for Holocene climatic variability in Central America. Abstracts with Programs - Martin, J. B.; Rosenmeier, M. F.; Hodell, D. A.; Brenner, M.; Curtis, J. H. (Geological Society of America Annual Meeting, 1998)
id: 140

Early to middle Holocene climatic variability in Central America: evidence from lacustrine sediments in the Peten, Guatemala - Rosenmeier, M. F.; Hodel, D. A.; Martin, J. B.; Brenner, M.; Curtis, J. H. (EOS: Transactions American Geophysical Union, 1998)
id: 1209

High-precision Measurements of 14C as a Circulation Tracer in the Pacific, Indian, and Southern Oceans with Accelerator Mass Spectrometry (AMS) - von Reden, K. F.; Peden, J. C.; Schneider, R. J.; Bellino, M.; Donoghue, J.; Elder, K. L.; Gagnon, A. R.; Long, P.; McNichol, A. P.; Morin, T.; Stuart, D.; Hayes, J. M.; et al. (8th International Conference on Heavy Ion Accelerator Technology, 1998)
id: 1636

How much deep water is formed in the Southern Ocean? - Broecker, W. S.; Peacock, S. L.; Walker, S.; Weiss, R.; Fahrbach, E.; Schroeder, M.; Mikolajewicz, U.; Heinze, C.; Key, R.; Peng, T. H.; Rubin, S. (Journal of Geophysical Research-Oceans, 1998)
Three tracers are used to place constraints on the production rate of ventilated deep water in the Southern Ocean. The distribution of the water mass tracer PO4* ("phosphate star") in the deep sea suggests that the amount of ventilated deep water produced in the Southern Ocean is equal to or greater than the outflow of North Atlantic Deep Water from the Atlantic. Radiocarbon distributions yield an export flux of water from the North Atlantic which has averaged about 15 Sv over the last several hundred years. CFC inventories are used as a direct indicator of the current production rate of ventilated deep water in the Southern Ocean. Although coverage is as yet sparse, it appears that the CFC inventory is not inconsistent with the deep water production rate required by the distributions of PO4* and radiocarbon. It has been widely accepted that the major part of the deep water production in the Southern Ocean takes place in the Weddell Sea. However, our estimate of the Southern Ocean ventilated deep water flux is in conflict with previous estimates of the flux of ventilated deep water from the Weddell Sea, which lie in the range 1-5 Sv. Possible reasons for this difference are discussed.
Zz547Times Cited:115Cited References Count:44

Influence of oxygen exposure time on organic carbon preservation in continental margin sediments - Hartnett, H. E.; Keil, R. G.; Hedges, J. I.; Devol, A. H. (Nature, 1998)
Today, over 90% of all organic carbon burial in the ocean occurs in continental margin sediments(1). This burial is intrinsically linked to the cycling of biogeochemically important elements (such as N, P, S, Fe and Mn) and, on geological timescales, largely controls the oxygen content of the atmosphere(2-4). Currently there is a volatile debate over which processes govern sedimentary organic carbon preservation(5-8). In spite of numerous studies demonstrating empirical relationships between organic carbon burial and such factors as primary productivity(9), the flux of organic carbon through the water column(10), sedimentation rate(11,12), organic carbon degradation rate(13), and bottom-water oxygen concentration(8,14), the mechanisms directly controlling sedimentary organic carbon preservation remain unclear. Furthermore, as organic carbon burial is the process that, along with pyrite burial(15), balances O-2 concentrations in the atmosphere, it is desirable that any mechanism proposed to control organic carbon preservation include a feedback buffering atmospheric oxygen concentrations over geological time. Here we compare analyses of sediments underlying two regions of the eastern North Pacific Ocean, one which has oxygen-depleted bottom waters and one with typical oxygen distributions. Organic carbon burial efficiency is strongly correlated with the length of time accumulating particles are exposed to molecular oxygen in sediment pore waters. Oxygen exposure time effectively incorporates other proposed environmental variables(8-14), and may exert a direct control on sedimentary organic carbon preservation and atmospheric oxygen concentrations.
Yv594Times Cited:355Cited References Count:27

Isotopic Biogeochemistry of the Neocomian Lacustrine and Upper Aptian Marine-Evaporitic Sediments of the Potiguar Basin, Northeastern Brazil - Neto, Eugenio Vaz dos Santos; Hayes, John M.; Takaki, Tikae (Organic Geochemistry, 1998)
id: 1729

Late Holocene climatic variability in Central America: evidence from lacustrine sediments in the Peten, Guatemala and implications for Maya cultural evolution; Procedings of the PEP 1 - Rosenmeier, M. F.; Hodell, D. A.; Martin, J. B.; Brenner, M.; Curtis, J. H. (PEP 1 (Pole-Equator-Pole, Paleoclimate of the Americas), 1998)
id: 141

Late Pleistocene Mammuthus primigenious from coastal mMaine - Hoyle, B. G.; Fisher, D. C.; Dorion, C. C.; Churchill, L. L.; W, Borns H., Jr.; Nelson, R. E. (33rd annual meeting, Geological Society of America, Northeastern Section, 1998)
id: 21

A massive terraced village complex in Chihuahua, Mexico, 3000 years before present - Hard, R. J.; Roney, J. R. (Science, 1998)
Cerro Juanaquena is a residential complex with 8 kilometers of terrace walls in northwestern Mexico that was occupied at similar to 3000 calendar years before present based on radiocarbon dates on maize (Zea mays L.), Most other similar sized terrace complex sites that have been found date to similar to 1000 years before present, Cerro Juanaquena was contemporaneous with 10 other sites in the southwestern United States that have yielded 18 of the earliest maize or squash radiocarbon dates yet, and it is by far the largest and most complex site, The archaeological evidence from this site, combined with other recent data, implies that highly variable combinations of population aggregation, agricultural dependence, and degrees of sedentism were present during the time maize was being introduced into the American Southwest.
Zb612Times Cited:32Cited References Count:59

A multi-proxy study of Holocene environmental change in the Maya lowlands of Peten, Guatemala - Curtis, J. H.; Brenner, M.; Hodell, D. A.; Balser, R. A.; Islebe, G. A.; Hooghiemstra, H. (Journal of Paleolimnology, 1998)
We used multiple variables in a sediment core from Lake Peten-Itza, Peten, Guatemala, to infer Holocene climate change and human influence on the regional environment. Multiple proxies including pollen, stable isotope geochemistry, elemental composition, and magnetic susceptibility in samples from the same core allow differentiation of natural versus anthropogenic environmental changes. Core chronology is based on AMS (14)C measurement of terrestrial wood and charcoal and thus avoids the vagaries of hard-water-lake error. During the earliest Holocene, prior to similar to 9000 (14)C yr BP, the coring site was not covered by water and all proxies suggest that climatic conditions were relatively dry. Water covered the coring site by similar to 9000 (14)C yr BP, coinciding with filling of other lakes in Peten and farther north on the Yucatan Peninsula. During the early Holocene (similar to 9000 to similar to 6800 (14)C yr BP), pollen data suggest moist conditions, but high delta(18)O values are indicative of relatively high E/P. This apparent discrepancy may be due to a greater fractional loss of the lake's water budget to evaporation during the early stages of lake filling. Nonetheless, conditions were moist enough to support semi-deciduous lowland forest. Decrease in delta(18)O values and associated change in ostracod species at similar to 6800 (14)C yr BP suggest a transition to even moister conditions. Decline in lowland forest taxa beginning similar to 5780 (14)C yr BP may indicate early human disturbance. By similar to 2800 (14)C yr BP, Maya impact on the environment is documented by accelerated forest clearance and associated soil erosion. Multiple proxies indicate forest recovery and soil stabilization beginning similar to 1100 to 1000 (14)C yr BP, following the collapse of Classic Maya civilization.
Zj856Times Cited:92Cited References Count:96

Paleoclimatic Assessment of Cretaceous Lacustrine and Marine-Evaporitic Sequences from the Potiguar Basin Based on the Hydrogen Isotopic Compositions of Saturated Hydrocarbons - Neto, Eugenio Vaz dos Santos; Hayes, John M.; Takaki, Tikae (Revista Latino Americana de Geoquimica Ogranica, 1998)
id: 1776

Preparation for continuous flow accelerator mass spectrometry Radiocarbon - Schneider, R. J.; Hayes, J. M.; von Reden, K. F.; McNichol, A. P.; Eglinton, T.; Wills, J. S. C. (Radiocarbon, 1998)
id: 1623

Proceedings of the 8th International Conference on Heavy Ion Accelerator Technology - Schneider, R. J.; von Reden, K. F.; Hayes, J. M.; Wills, J. S. C. (American Institute of Physics, Conference Proceeding Series, 1998)
id: 1624; submitted

Quantitative Production of H2 by Pyrolysis of Gas Chromatographic Effluents - Burgoyne, Thomas W.; Hayes, John M. (Analytical Chemistry, 1998)
id: 1731

Radiometrically determined sedimentary fluxes in the sub-polar North Atlantic during the last 140,000 years - McManus, J. F.; Anderson, R. F.; Broecker, W. S.; Fleisher, M. Q.; Higgins, S. M. (Earth and Planetary Science Letters, 1998)
We have examined the record of sediment input during the last 140000 years in a deep-sea core from 49 degrees 27'N, 22 degrees 16'W in the eastern North Atlantic. Using uranium-series disequilibria to constrain time, we have calculated mass fluxes of total sediment, as well as mass and particle fluxes of major sedimentary components. Sediment accumulation rates were generally lower and relatively constant during broadly defined interglacial intervals, driven primarily by the burial of biogenic material. Accumulation rates were higher and more variable during glacial intervals, and were influenced primarily by terrigenous material. Peaks in bulk mass fluxes were associated with particular episodes (Heinrich events) within the last glacial and during each of the last two deglaciations. The flux of ice-rafted debris, as uniquely identified by coarse detrital fragments, was higher during layers representing each of the glacial Heinrich events, with modest increases during events H3 and H6 and dramatic increases during the others, confirming the widespread interpretation of these layers as episodes of enhanced iceberg delivery. The burial flux of foraminifera was markedly lower during each of the glacial Heinrich events, also confirming the original identification of these layers as barren intervals. Ice-rafting events within marine isotope stage 5 left neither a large detrital nor biogenic flux imprint at our study site. Variations in the burial rates of non-carbonate sediments were largely responsible for overall changes in sediment accumulation throughout the last climate cycle. Ice-rafting was apparently an important delivery mechanism for this terrigenous material. The instantaneous chronometer established here for the last 140000 years in the subpolar North Atlantic allows the transformation of existing and subsequent data from relative values to absolute burial fluxes. (C) 1998 Elsevier Science B.V.
Ze160Times Cited:70Cited References Count:55

Status Report of the National Ocean Sciences AMS Facility at Woods Hole Oceanographic Institution: Operations and Recent Developments - Bellino, M.; von Reden, K. F.; Schneider, R. J.; Peden, J. C.; Donoghue, J.; Elder, K. L.; Gagnon, A. R.; Long, P.; McNichol, A. P.; Odegaard, A. P.; Stuart, D.; Handwork, S.; et al. (15th International Conference on the Applications of Accelerators in Research and Industry, 1998)
id: 1647

Target preparation for continuous flow accelerator mass spectrometry - Schneider, R. J.; Hayes, J. M.; von Reden, K. F.; McNichol, A. P.; Eglinton, T. I.; Wills, J. S. C. (Radiocarbon, 1998)
For very small samples, it is difficult to prepare graphitic targets that will yield a useful and steady sputtered ion beam. Working with materials separated by preparative capillary gas chromatography, we have succeeded with amounts as small as 20 mu g C. This seems to be a practical limit, as it involves 1) multiple chromatographic runs with trapping of effluent fractions, 2) recovery and combustion of the fractions, 3) graphitization and 4) compression of the resultant graphite/cobalt matrix into a good sputter target. Through such slow and intricate work, radiocarbon ages of lignin derivatives and hydrocarbons from coastal sediments have been determined. If this could be accomplished as an "online" measurement by flowing the analytes directly into a microwave gas ion source, with a carrier gas, then the number of processing steps could be minimized. Such a system would be useful not just for chromatographic effluents, but for any gaseous material, such as CO2 produced from carbonates. We describe tests using such an ion source.
1 Sp. Iss. SI113kt Times Cited:11 Cited References Count:10
Keywords: gas; ion-source

Una Investigacion Arqueologica de los Sitios Cerros con Trincheras del Arcaico Tardio en Chihuahua, Mexico: Las Investigaciones de Campo de 1997 - Hard, R.; Roney, J. (University of Texas, Center for Archaeological Research, 1998)
id: 242

Water-induced errors in continuous-flow carbon isotope ratio mass spectrometry - Leckrone, K. J.; Hayes, J. M. (Anal Chem, 1998)
Formation of HCO2+ from CO2 and background H2O in isotope ratio mass spectrometers has been examined in detail. The process is troublesome because its product is not resolved from 13C16O2+. The resulting, artifactual enhancement of the mass 45 ion current (and analogous enhancement of the mass 46 ion current by transfer of hydrogen to mass 45 species) can cause systematic errors in analyses of 13C based on measurement of ion current ratios in the mass spectrum of CO2. Such errors are neutralized when isotopic analyses are based on differential comparisons in which ion currents and background water levels are precisely equal during admission and ionization of both sample and standard gases. In continuous-flow systems, however, that requirement is generally not met. The resulting systematic error is proportional to the 18/44 ion current ratio. When the widely used MAT252 mass spectrometer is tuned to yield maximum sensitivity, the constant of proportionality is 26 +/- 2/1000 (i.e., the error will be 0.26/1000 if the mass 18 ion current is 100 times smaller than that at mass 44). Errors can be reduced 5-fold when the ion-source residence time of CO2+ is decreased by use of stronger ion-extraction potential gradients. Under those same conditions, sensitivity is decreased by 60%. For operation at highest sensitivity, carrier gas dew points on the order of -70 degrees C are required to obtain errors < or = 0.1/1000 for samples yielding mass 44 ion currents of 10 nA. Carrier gas dew points < or = -80 degrees C are conveniently reached by use of a Nafion dryer operated at approximately 0 degree C.
Leckrone, K JHayes, J MengResearch Support, Non-U.S. Gov'tResearch Support, U.S. Gov't, Non-P.H.S.1998/07/17Anal Chem. 1998 Jul 1;70(13):2737-44.

Carbon isotopic fractionation associated with lipid biosynthesis by a cyanobacterium: relevance for interpretation of biomarker records - Sakata, S.; Hayes, J. M.; McTaggart, A. R.; Evans, R. A.; Leckrone, K. J.; Togasaki, R. K. (Geochim Cosmochim Acta, 1997)
For the cyanobacterium Synechocystis UTEX 2470, grown photoautotrophically to a logarithmic stage of growth, the total lipid extract is depleted in 13C by 4.8% relative to average biomass. Depletions observed for acetogenic (straight-chain) lipids range from 7.6 (hexadecanoic acid) to 9.9% (a C16 n-alkyl chain bound in a polar-lipid fraction), with a mass-weighted average of 9.1%. Polyisoprenoid lipids fall into two isotopic groups, with phytol, diplopterol, and diploptene depleted by 6.4-6.9% and bishomohopanol (produced from the extracts by the preparative degradation of bacteriohopanepolyol) depleted by 8.4%. Analysis of the pattern of depletions indicates that two carbon positions in each C5 biomonomer leading to polyisoprenoid products are probably depleted in 13C relative to average biomass. The depletion of bacteriohopanepolyol relative to other polyisoprenoids can be ascribed to changes that occur over the life of each cell: (1) the 13C content of carbon flowing to lipid biosynthesis decreases as the cell size increases and (2) a greater proportion of the bacteriohopanepolyol which, unlike other polyisoprenoids, is present mainly in the cytoplasm rather than in membranes and is synthesized when cells are larger. Chlorophyll a is depleted relative to average biomass by O.7%. Given the observed depletion of 13C in phytol, the heteroaromatic, chlorophyllide portion of chlorophyll must be enriched in 13C by 2.7%. This enrichment is large relative to that in chlorophyllides produced by eukaryotes and may be related to a parallel enrichment of 13C in cyanobacterial glutamic acid. As in many previous investigations of cyanobacterial lipids, long-chain n-alkanes (C22-C29) are found in the extracts. They are, however, enriched in 13C relative to biomass and have isotopic compositions suggesting that they are contaminants of petrochemical origin. Available results indicate that cyanobacterial lipids will be depleted relative to dissolved CO2 that has served as a carbon source by 22-30% and that a wider range of depletions will be characteristic of eukaryotic products. The absence of long-chain n-alkanes in cyanobacteria reduces the possibility that petroleum ever formed from pre-eukaryotic sedimentary debris.
Sakata, SHayes, J M McTaggart, A R Evans, R A Leckrone, K J Togasaki, R K eng Research Support, U.S. Gov't, Non-P.H.S. 1997/01/01 00:00 Geochim Cosmochim Acta. 1997;61(24):5379-89.
Keywords: *Biomass; Acetic Acid/metabolism; Alkanes/*analysis/chemistry; Biomarkers/chemistry; carbon isotopes; Carbon/*chemistry; Chlorophyll/metabolism; Cyanobacteria/chemistry/*metabolism; Geologic Sediments/*chemistry; Lipids/*biosynthesis; NASA Discipline Exobiology; Non-NASA Center; Palmitic Acid/metabolism; Phytol/metabolism; Pigments, Biological/metabolism

Consistent Fractionation of 13C in Nature and in the Laboratory: Growth-rate Effects in Some Haptophyte Algae - Bidigare, Robert R.; Fluegge, Arnim; Freeman, Katherine H.; Hanson, Kristi L.; Hayes, John M.; Hollander, David; Jasper, John P.; King, Linda L.; Laws, Edward A.; Milder, Jeffrey; Millero, Frank J.; Pancost, Richard; et al. (Global Biogeochemical Cycles, 1997)
The carbon isotopic fractionation accompanying formation of biomass by alkenone-producing algae in natural marine environments varies systematically with the concentration of dissolved phosphate. Specifically, if the fractionation is expressed by єP ≈ δe − δp, where δe and δp are the δ13C values for dissolved CO2 and for algal biomass (determined by isotopic analysis of C37 alkadienones), respectively, and if Ce is the concentration of dissolved CO2, μmol kg−1, then b = 38 + 160*[PO4], where [PO4] is the concentration of dissolved phosphate, μM, and b = (25 − єp)Ce. The correlation found between b and [PO4] is due to effects linking nutrient levels to growth rates and cellular carbon budgets for alkenone-containing algae, most likely by trace-metal limitations on algal growth. The relationship reported here is characteristic of 39 samples (r2 = 0.95) from the Santa Monica Basin (six different times during the annual cycle), the equatorial Pacific (boreal spring and fall cruises as well as during an iron-enrichment experiment), and the Peru upwelling zone. Points representative of samples from the Sargasso Sea ([PO4] ≤ 0.1 μM) fall above the b = f[PO4] line. Analysis of correlations expected between μ (growth rate), єp, and Ce shows that, for our entire data set, most variations in єp result from variations in μ rather than Ce. Accordingly, before concentrations of dissolved CO2 can be estimated from isotopic fractionations, some means of accounting for variations in growth rate must be found, perhaps by drawing on relationships between [PO4] and Cd/Ca ratios in shells of planktonic foraminifera.
id: 1727

Efficiency and temperature dependence of water removal by membrane dryers - Leckrone, K. J.; Hayes, J. M. (Anal Chem, 1997)
The vapor pressure of water in equilibrium with sorption sites within a Nafion membrane is given by log P(WN) = -3580/T + 10.01, where P(WN) is expressed in Torr and T is the membrane temperature, in kelvin. The efficiency of dryers based on selective permeation of water through Nafion can thus be enhanced by cooling the membrane. Residual water in effluents exceeds equilibrium levels if insufficient time is allowed for water to diffuse to the membrane surface as gas passes through the dryer. For tubular configurations, this limitation can be avoided if L > or = Fc(10(3.8)/120 pi D), where L is the length of the tubular membrane, in centimeters, Fc is the gas flow rate, in mL/ min, and D is the diffusion coefficient for water in the carrier gas at the operating temperature of the dryer, in cm2/s. An efficient dryer that at room temperature dries gas to a dew point of -61 degrees C is described; the same dryer maintained at 0 degrees C yields a dew point of -80 degrees C and removes water as effectively as Mg(ClO4)2 or a dry ice/acetone slush. The use of Nafion membranes to construct devices capable of delivering gas streams with low but precisely controlled humidities is discussed.
Leckrone, K JHayes, J MengComparative StudyResearch Support, U.S. Gov't, Non-P.H.S.1997/03/01 00:00Anal Chem. 1997 Mar 1;69(5):911-8.

An isotopic biogeochemical study of Neoproterozoic and Early Cambrian sediments from the Centralian Superbasin, Australia - Logan, G. A.; Summons, R. E.; Hayes, J. M. (Geochim Cosmochim Acta, 1997)
Organic matter from Neoproterozoic and Early Cambrian sediments of the Amadeus and Officer basins of the Centralian Superbasin, Australia, has been studied for biomarker distributions and the carbon isotopic compositions of kerogen and individual hydrocarbons. These sediments represent both shallow and deep water marine facies in the older sections and marine and saline lacustrine carbonate deposits in the Cambrian. Hydrocarbon biomarker patterns were found to be quite consistent with the known sedimentary environments and provide valuable insights into the biogeochemical changes which accompanied the transition from a microbially-dominated ocean to the early stages of metazoan radiation. In particular, carbon isotopic data for n-alkyl and isoprenoid lipids presented here, and in earlier studies, showed a reversal in carbon isotopic ordering between the Proterozoic and Phanerozoic. By comparison with the delta 13C of kerogen, n-alkyl lipids from deep-water Proterozoic sediments were enriched in 13C and appear to be derived mainly from heterotrophs whilst open marine Phanerozoic counterparts are 13C depleted and evidently derived mainly from autotrophs. Data from the samples studied here are consistent with a model invoking a change in the redox structure of the ocean, possibly aided by the innovation of faecal pellets.
Logan, G ASummons, R E Hayes, J M eng Research Support, U.S. Gov't, Non-P.H.S. 1997/01/01 00:00 Geochim Cosmochim Acta. 1997;61(24):5391-409.
Keywords: Alkanes/analysis/chemistry; Animals; australia; biomarkers; carbon isotopes; Carbon/analysis/*chemistry; Cyanobacteria; Eukaryota; Feces; Fossils; Geologic Sediments/*analysis/chemistry; Hydrocarbons/analysis; NASA Discipline Exobiology; Non-NASA Center; Paleontology; phytoplankton; SEAWATER; Terpenes/analysis; Zooplankton

Preliminary results of the first scientific drilling on Lake Baikal, Buguldeika site, southeastern Siberia - Colman, S.; Grachev, M.; Hearn, P.; Horie, S.; Kawai, T.; Kuzmin, M.; Logachov, N.; Fialkov, V.; Gorigljad, A.; Tomilov, B.; Khakhaev, B.; Kochikov, S.; et al. (Quaternary International, 1997)
The Baikal Drilling Project (BDP) is a multinational effort to investigate the paleoclimatic history and tectonic evolution of the Baikal sedimentary basin during the Late Neogene. In March 1993 the Baikal drilling system was successfuly deployed from a barge frozen into position over a topographic high, termed the Buguldeika saddle, in the southern basin of Lake Baikal. The BDP-93 scientific team, made up of Russian, American and Japanese scientists, successfully recovered the first long (>100 m) hydraulic piston cores from two holes in 354 m of water. High quality cores of 98 m (Hole 1) and 102 m (Hole 2), representing sedimentation over the last 500,000 years, were collected in 78 mm diameter plastic liners with an average recovery of 72% and 90%, respectively. Magnetic susceptibility logging reveals an excellent hole-to-hole correlation. In this report the scientific team describes the preliminary analytical results from BDP-93 hole 1 cores. Radiocarbon dating by accelerator mass spectrometry provides an accurate chronology for the upper portion of Hole 1. Detailed lithologic characteristics, rock magnetic properties and inorganic element distributions show a significant change to the depositional environment occuring at 50 m subbottom depth, approximately 250,000 BP. This change may be due to uplift and rotation of the horst block in the Buguldeika saddle. The sedimentary section above 50 m is pelitic with varve-like laminae, whereas the section below 50 m contains a high proportion of sand and gravel horizons often organized into turbidite sequences. Accordingly, high resolution seismic records reveal a change in sonic velocity at this depth. It is inferred that sedimentation prior to 250 ka BP was from the west via the Buguldeika river system. After 250 ka BP the Buguldeika saddle reflects an increase in hemipelagic sediments admired with fine-grained material from the Selenga River drainage basin, east of Lake Baikal. Variations in the spore-pollen assemblage, diatoms, biogenic silica content, rock magnetic properties, clay mineralogy and organic carbon in the upper 50 m of BDP-93-1 reveal a detailed record of climate change over approximately the last 250,000 years. These variables alternate in a pattern characteristic of glacial/interglacial climatic fluctuations. The present age model suggests that the climate signal recorded in Lake Baikal sediments is similar to Late Quaternary signals recorded in Chinese loess sections and in marine sediments. Copyright (C) 1996 INQUA/Elsevier Science Ltd
Vq100Times Cited:44 Cited References Count:29
Keywords: asia; tectonics

Productivity-induced sulphur enrichment of hydrocarbon-rich sediments from the Kimmeridge Clay Formation - Lallier-Verges, E.; Hayes, J. M.; Boussafir, M.; Zaback, D. A.; Tribovillard, N. P.; Connan, J.; Bertrand, P. (Chem Geol, 1997)
This work aims to highlight the relationship between primary productivity, sulphate reduction and organic carbon preservation in cyclic marine sediments from the Kimmeridge Clay Formation. A concomitant increase of the total sulphur content with the preserved organic content (TOC), shows the progressive supply of both metabolisable organic matter and resistant organic matter is linked to primary productivity. However, variations in sulphate reduction efficiency, based on elemental abundance and isotopic composition of sulphur, reveal that the proportion of metabolisable vs. resistant organic matter has varied along the cycles. This is interpreted in terms of the variation in organic delivery. Organic sulphur content is found to be proportional to the organic matter content, whereas concentrations of pyritic sulphur are constant at very high (> 10% TOC) values. This result is explained by a limitation of available iron for pyritisation at times of very high organic flux. Under such conditions, HS- in excess could be responsible for the early formation of organo-sulphur compounds and thus for the preservation of highly aliphatic (i.e. lipid-rich) organic matter.
Lallier-Verges, EHayes, J MBoussafir, MZaback, D ATribovillard, N PConnan, JBertrand, PengResearch Support, Non-U.S. Gov'tNetherlands1997/01/01 00:00Chem Geol. 1997;134:277-88.

Target preparation for continuous flow accelerator mass spectrometry - Schneider, R. J.; Hayes, J. M.; Eglinton, T. I.; McNichol, A. P.; von Reden, K. F. (16th International Radiocarbon Conference, 1997)
id: 953

Target preparation for continuous flow accelerator mass spectrometry - Schneider, R. J.; Hayes, J. M.; von Reden, K. F.; McNichol, A. P.; Eglinton, T. I. (Radiocarbon, 1997)
id: 1661

Target preparation for continuous flow accelerator mass spectrometry: (Proceedings of the 16th International Radiocarbon Conference, 1997) - Schneider, R. J.; Hayes, J. M.; von Reden, K. F.; McNichol, A. P.; Eglinton, T. (Radiocarbon, 1997)
id: 1752

Western South Atlantic deepwater hydrography derived from benthic Cd/Ca and stable isotope data - Horowitz, M.; Oppo, D. W. (Supplement to EOS, 1997)
id: 1269

Automated systems and techniques utilized at the NOSAMS sample preparation laboratory: An update of productivity and quality issues - Gagnon, A. R.; McNichol, A. P.; Hutton, D. L.; Osborne, E. A.; Donoghue, J. C. (Radiocarbon, 1996)
id: 959

Cape May site report - Miller, K. G.; Liu, C.; Browning, J. V.; Pekar, S.; Sugarman, P.; Van Fossen, M. C.; Mullikin, L.; Queen, D.; Feigenson, M. D.; Aubry, M. P.; Burckle, L. D.; Powars, D.; et al. (Proc. ODP, Init. Repts, 1996)
id: 55

Carbon isotopes and the rise of atmospheric oxygen - Karhu, J. A.; Holland, H. D. (Geology, 1996)
New data for the isotopic composition of carbon in carbonate sediments deposited between 2.6 and 1.6 Ga indicate that the value of delta(13)C in these sediments underwent a very large positive excursion between 2.22 and 2.06 Ga. A reassessment of the earlier delta(13)C data for carbonate sediments shows that this excursion was probably worldwide, and that it was preceded and followed by several hundred million years during which the delta(13)C of carbonate sediments differed little from that of modern carbonates. The large delta(13)C excursion between 2.22 and 2.06 Ga was probably related to an abnormally high rate of organic carbon deposition, which generated an abnormally high rate of O-2 production, We estimate that the total excess O-2 produced during the excursion was between 12 and 22 times the present atmospheric O-2 inventory. The delta(13)C data therefore suggest that the O-2 content of the atmosphere increased very significantly between 2.22 and 2.06 Ga. This inference is supported strongly by several other lines of evidence.
Vm224Times Cited:257Cited References Count:44

Concentrations of carbonyl compounds and the carbon isotopy of formaldehyde at a coastal site in Nova Scotia during the NARE summer intensive - Tanner, Roger L.; Zielinska, Barbara; Uberna, Ewa; Harshfield, Gregory; McNichol, Ann P. (Journal of Geophysical Research: AtmospheresJ. Geophys. Res., 1996)
Keywords: 0315 Biosphere/atmosphere interactions; 0345 Pollution: urban and regional; 0365 Troposphere: composition and chemistry; 0394 Instruments and techniques

Concentrations of carbonyl compounds and the carbon isotopy of formaldehyde at a coastal site in Nova Scotia during the NARE summer intensive - Tanner, R. L.; Zielinska, B.; Uberna, E.; Harshfield, G.; McNichol, A. P. (Journal of Geophysical Research-Atmospheres, 1996)
The concentrations of gaseous atmospheric carbonyl compounds have been measured at a coastal site on the southern tip of Nova Scotia during August 1993 as part of the National Oceanic and Atmospheric Administration's North Atlantic Regional Experiment (NARE) summer intensive. The DNPH-cartridge technique was used for sampling, with analysis by HPLC with UV absorbance detection. The carbon isotopic content of formaldehyde was measured using a novel collection technique on bisulfite-coated fillers followed by accelerator mass spectrometric determination of C-14 content and C-13/C-12 isotopic ratios. Results from this study indicate that quantifiable levels above about 100 parts per trillion by volume were found at the Chebogue Point, Nova Scotia, site for several carbonyls, formaldehyde, acetaldehyde, acetone, propionaldehyde, methyl ethyl ketone, and benzaldehyde, for most 6-hour sampling periods. Six-hour averaged formaldehyde levels of <0.5 to about 3.5 parts per billion were found during periods of local influence and during influence of continental air masses crossing eastern Canada and northeastern US. In contrast, background levels of formaldehyde of 200-400 pptv were found under conditions of predominantly marine back trajectories. Large fractions of contemporary carbon (of the order of 80%) were found in collected formaldehyde samples for all transport regimes and formaldehyde concentrations, suggesting that biogenic sources of hydrocarbon precursors to formaldehyde predominated during the summer season.
Vz788Times Cited:38Cited References Count:42

Dating of explosive volcanic events associated with dome growth at Soufriere Hills volcano, Montserrat - Young, S. R.; Hoblitt, R. P.; Smith, A. L.; Devine, J. D.; Wadge, G.; Shepherd, J. B. (Proceedings of the Special Symposium on Volcanism in Montserrat, Second Caribbean Conference on Natural Hazards and Hazard Management, 1996)
id: 1306

Direct U-Th dating of marine sediments from the two most recent interglacial periods - Slowey, N. C.; Henderson, G. M.; Curry, W. B. (Nature, 1996)
A KNOWLEDGE of the age of marine sediments is necessary to determine the timing of events and rates of processes in the marine realm, and the relationships among marine and other climatically sensitive records. The establishment of an accurate chronology for Pleistocene marine sediments beyond the range of radiocarbon dating (approximately the past 45 kyr) has therefore been a goal of palaeoceanographers for decades. Early attempts(1,2) based on measurements of the radionuclides Th-230 and Pa-231 mere beset with problems, and subsequent studies focused on tying fluctuations in marine sediment oxygen-isotope records to events such as the formation of col al reef terraces and changes in the Earth's magnetic polarity(3,4), and tuning the resultant chronologies to the Earth's orbitally driven insolation variations(5-8). But these chronologies (especially the age and duration of the last interglacial period) have been challenged by several studies(9-12), raising questions about the fundamental cause of Pleistocene climate fluctuations. Here we report the direct U-Th dating of aragonite-rich marine sediments from the Bahamas, and present an accurately dated marine oxygen-isotope record for the last two interglacials. We obtain dates of 120-127 kyr BP for the last interglacial and 189-190 kyr np for the late stage 7 interglacial. These dates are in accord with the general theory of orbitally forced climate fluctuations and demonstrate the potential of our direct-dating approach for developing an absolute chronology for the Pleistocene marine oxygen-isotope record.
Vh315Times Cited:39Cited References Count:40

Holocene paleoclimatic changes in the Lake Winnebago basin, east-central Wisconsin - Haase, Alisa A.; Smith, G. L.; Hardacker, E. P. (Abstracts with Programs - Geological Society of America, 1996)
id: 77

A Holocene vegetation history from lowland Guatemala - Islebe, G. A.; Hooghiemstra, H.; Brenner, M.; Curtis, J. H.; Hodell, D. A. (Holocene, 1996)
A 5.45-m core from Lake Peten-Irza, lowland Guatemala, contains a near-complete record of Holocene sedimentation. The age-depth relationship for the core is based on AMS C-14 dating of terrestrial wood fragments and provides a reliable chronology in this karst region where hard-water lake error has typically confounded sediment geochronology. In the basal part of the sequence, pollen of the Moraceae-Urticaceae group dominate, indicating the presence of widespread tropical forest during the early Holocene (c. 8600-5600 yr BP). Relative abundance of pollen of high forest taxa declined beginning as early as 5600 yr BP, indicating climatic drying or perhaps initial land clearance. Deforestation by prehistoric Mayan inhabitants is documented clearly in the pollen record beginning about 2000 pr BP (106 cal BC-122 cal Ao, 95.4%, 2 sigmas) by the appearance of disturbance taxa (e.g. Ambrosia and Poaceae) and presence of Zea. Forest regrowth occurred following the Classic Maya collapse, c. AD 900, as reflected by a relative increase in Moraceae-Urticaceae pollen.
Vh189Times Cited:103Cited References Count:44

Inorganic radiocarbon in time-series trap samples: implication of seasonal variation of 14C in the upper ocean - Honda, Makio C. (Radiocarbon, 1996)
id: 27

Kinematic Effects in the Sputtering of Carbon Isotopes - Schneider, R. J.; Hartman, J.; von Reden, K. F.; McNichol, A. P. (7th International Conference on Accelerator Mass Spectrometry, 1996)
id: 1801; 1

Kinematic Effects in the Sputtering of Carbon Isotopes - Schneider, R. J.; Hartman, J.; von Reden, K. F.; McNichol, A. P. (Radiocarbon, 1996)
id: 1660

Petroleum Geochemistry and Geology - Hunt, John M. (W. H. Freeman & Company, 1996)
id: 1558

Age and paleoclimate of submerged late Pleistocene reef system, Southeast Florida shelf; implications for substage 5A sea level - Toscano, M. A.; Lundberg, J.; Hine, A. C. (Geological Society of America, 1995 annual meeting, 1995)
id: 1242; 6

The eastern chenier plain; an update on downrift coastal progradation associated with the building of a new Holocene delta lobe in the Mississippi delta complex - Roberts, Harry H.; Huh, O. K. (AAPG Bulletin, 1995)
id: 64

Improvements in procedural blanks at NOSAMS: Reflections of improvements in sample preparation and accelerator operation - McNichol, A. P.; Gagnon, A. R.; Osborne, E. a; Hutton, D. L.; von Reden, K. F.; Schneider, R. J. (15th International 14C Conference, 1995)
id: 1641; 15th International Radiocarbon Conference, Glasgow, Scotland, August 15-19, 1994

Improvements in procedural blanks at NOSAMS: Reflections of improvements in sample preparation and accelerator operation - McNichol, A. P.; Gagnon, A. R.; Osborne, E. A.; Hutton, D. L.; vonReden, K. F.; Schneider, R. J. (Radiocarbon, 1995)
During the four years the Sample Preparation Laboratory (SPL) at the National Ocean Sciences Accelerator Mass Spectrometer (NOSAMS) Facilty has been in operation we have accumulated much data from which we can assess our progress. We evaluate our procedural blanks here and describe modifications in our procedures that have improved our analyses of older samples. In the SPL, we convert three distinct types of samples-seawater, CaCO3 and organic carbon-to CO2 prior to preparing graphite for the accelerator and have distinct procedural blanks for each procedure. Dissolved inorganic carbon (Sigma CO2) is extracted from acidified seawater samples by sparging with a nitrogen carrier gas. We routinely analyze ''line blanks'' by processing CO2 from a C-14-dead source through the entire stripping procedure. Our hydrolysis blank, IAEA C-1, is prepared by acidifying in vacuo with 100% H3PO4 at 60 degrees C overnight, identical to our sample preparation. We use a dead graphite, NBS-21, or a commercially available carbon powder for our organic combustion blank; organic samples are combusted at 850 degrees C for 5 h using CuO to provide the oxidant. Analysis of our water stripping data suggests that one step in the procedure contributes the major portion of the line blank. At present, the contribution from the line blank has no effect on our seawater analyses (fraction modern (fm) between 0.7 and 1.2). Our hydrolysis blanks can have an fm value as low as 0.0006, but are more routinely between 0.0020 and 0.0025. The fm of our best organic combustion blanks is higher than those routinely achieved in other laboratories and we are currently altering our methods to reduce it.
Ud868Times Cited:16 Cited References Count:6
Keywords: SPECTROMETRY

Intracrystalline proteins in aragonite-needle mud from Florida Bay: an immunological and biogeochemica study, Thesis - Hawkins, Sharon (University of North Carolina at Chapel Hill, 1995)

Late Pleistocene Oxygen-Isotope Records of Biogenic Silica from the Atlantic Sector of the Southern-Ocean - Shemesh, A.; Burckle, L. H.; Hays, J. D. (Paleoceanography, 1995)
We determined the isotopic composition of oxygen in marine diatoms in eight deepsea cores recovered from the Atlantic sector of the Southern Ocean. The analytical reproducibility and core-to-core consistency of the isotopic signal suggests that diatom delta(18)O can be used as a new paleocenographic tool to reconstruct past variations in surface water characteristics and to generate O-18 -isotope-based stratigraphy for the Southern Ocean. The data indicate that diatom delta(18)O reflects sea surface temperature and seawater isotopic composition and that diatoms retain their isotopic signal on timescales of a least 430 ka. The delta(18)O analyses of different diatom assemblages reveal that the isotopic signal is free of species effects and that the common Antarctic species have the same water-opal fractionation. The transition from the last glacial maximum (LGM) to the Holocene is fully recorded in high sedimentation rate cores. An O-18 enrichment during the LGM, a post-LGM meltwater spike and an input of meltwater during the late Holocene are the main isotopic features observed in down core records. The origin of this meltwater was very likely melting icebergs and/or continental ice or by melting sea ice that had accumulated snow. The most pronounced meltwater effects are recorded in cores that are associated with the Weddel gyre. Our results provide the basis for extending isotope studies to oceanic regions devoid of carbonate; further, isotopic stratigraphies may be constructed for records and regions where they were previously not possible.
Rd382Times Cited:82Cited References Count:23

Possible Role of Climate in the Collapse of Classic Maya Civilization - Hodell, D. A.; Curtis, J. H.; Brenner, M. (Nature, 1995)
THE Maya civilization developed around 3,000 years ago in Mesoamerica, and after flourishing during the so-called Classic period, it collapsed around 750-900 AD(1). It has been speculated(2-6) that climate change may have played a part in this collapse. But efforts to reconstruct the last three millennia of Mesoamerican climate using palynological methods have met with equivocal success, because human-mediated deforestation has altered regional vegetation in ways that mimic climate shifts, making it difficult to discriminate between natural and anthropogenic changes(7-15). Here we use temporal variations in oxygen isotope and sediment composition in a 4.9-m sediment core from Lake Chichancanab, Mexico, to reconstruct a continuous record of Holocene climate change for the central Yucatan peninsula. The interval between 1,300 and 1,100 yr up (AD 800-1,000) was the driest of the middle to late Holocene epoch, and coincided with the collapse of Classic Maya civilization, This continuous climate proxy record thus provides evidence of climate deterioration in the Maya region during the terminal Classic period.
Rb101Times Cited:439Cited References Count:41

Variability in the Benguela Current upwelling system over the past 70,000 years - Summerhayes, C. P.; Kroon, D.; Rosell-Mele, A.; Jordan, R. W.; Schrader, H. J.; Hearn, R.; Villanueva, J.; Grimali, J. O.; Eglinton, G. (Progress in Oceanography, 1995)
This study was designed to see if the intensity and location of upwelling in the Benguela Current Upwelling System off Namibia changed significantly during the last 70,000 years. Most of the analytical work focused on geochemical, micropalaeontological and stable isotopic analyses of a 6.5m long combined pilot and piston core, PGPC12, from 1017m on the continental slope close to Walvis Bay. The slope sediments are rich in organic matter. Most of it is thought to represent deposition beneath a productive shelf edge upwelling system, but some is supplied by downslope near-bottom flow of material probably resuspended on the outer continental shelf. Temporal changes in upwelling intensity as represented by fluctuations in the accumulation of organic matter do not show the simple 'classical' pattern of less upwelling and lower productivity in interglacials and more upwelling and higher productivity in glacials, but instead show a pattern of higher frequency fluctuations. The broad changes in organic carbon accumulation reach maxima at times when the earth-sun distance was greatest, indicating that this accumulation responded to changes in the precession index; at these times monsoons would have been weakest and Trade Winds strongest. Maximum accumulation of organic matter on the slope occurred in the last interstadial (isotope stage 3), and coincided with coldest sea surface temperatures as recorded by alkenone data (U(37)(k)), and by nannofossil assemblages. It is attributed largely to increased productivity in situ, rather than the lateral supply of material eroded from older organic rich deposits exposed by the lowering of sealevel at that time. The enhanced productivity is attributed to a strengthening of upwelling-favourable winds in this area in response to the minimal solar insolation typical of this period. Diatoms generally are not abundant in these sediments, so appear to be unreliable indicators of productivity over the continental slope. When sealevel was lowest (isotope stages 2 and 4) organic matter previously deposited on the continental shelf was eroded and dumped on the continental slope; this reworked material constitutes up to 43% of the flux of organic matter to the slope at these times. This process did not affect the slope in stage 3, when sealevel fell by only 50m. The accumulation of terrigenous material was highest in stages 2 and 4. The available data suggest that the terrigenous influx at those times was primarily aeolian. We interpret this to mean that more of the winds then came from the east ('Berg' winds), bringing an influx of aeolian dust from the hinterland; these easterlies were less favoarable for upwelling than were the more southerly Trade Winds that dominated during stage 3. Carbonate accumulation was least in stages 2 and 4, largely in response to dissolution induced by CO(2)-rich bottom waters.
V07zbTimes Cited:100Cited References Count:147

Automated Sample Processing at the National Ocean Sciences Ams Facility - Cohen, G. J.; Hutton, D. L.; Osborne, E. A.; vonReden, K. F.; Gagnon, A. R.; McNichol, A. P.; Jones, G. A. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 1994)
The high throughput and high precision requirements for the NOSAMS facility have made it essential to automate many of the stages in sample processing. These automated procedures increase the sample capacity for the lab while reducing errors in sample preparation. Automation has also allowed sample histories to be recorded and saved in Sybase, a relational data base.
Nv547Times Cited:9Cited References Count:1

Deglaciation, Lake Levels, and Meltwater Discharge in the Lake-Michigan Basin - Colman, S. M.; Clark, J. A.; Clayton, L.; Hansel, A. K.; Larsen, C. E. (Quaternary Science Reviews, 1994)
The deglacial history of the Lake Michigan basin, including discharge and routing of meltwater, is complex because of the interaction among (1) glacial retreats and re-advances in the basin (2) the timing of occupation and the isostatic adjustment of lake outlets and (3) the depositional and erosional processes that left evidence of past lake levels. In the southern part of the basin, a restricted area little affected by differential isostasy, new studies of onshore and offshore areas allow refinement of a lake-level history that has evolved over 100 years. Important new data include the recognition of two periods of influx of meltwater from Lake Agassiz into the basin and details of the highstands gleaned from sedimentological evidence. Major disagreements still persist concerning the exact timing and lake-level changes associated with the Algonquin phase, approximately 11,000 BP. A wide variety of independent data suggests that the Lake Michigan Lobe was thin, unstable, and subject to rapid advances and retreats. Consequently, lake-level changes were commonly abrupt and stable shorelines were short-lived. The long-held beliefs that the southern part of the basin was stable and separated from deformed northern areas by a hinge-line discontinuity are becoming difficult to maintain. Numerical modeling of the ice-earth system and empirical modeling of shoreline deformation are both consistent with observed shoreline tilting in the north and with the amount and pattern of modern deformation shown by lake-level gauges. New studies of subaerial lacustrine features suggest the presence of deformed shorelines higher than those originally ascribed to the supposed horizontal Glenwood level. Finally, the Lake Michigan region as a whole appears to behave in a similar manner to other areas, both local (other Great Lakes) and regional (U.S. east coast), that have experienced major isostatic changes. Detailed sedimentological and dating studies of field sites and additional development of geophysical models offer hope for reconciling the field data with our understanding of earth theology.
Qq080Times Cited:30Cited References Count:48

Glacial geology of the Penobscot River basin between Millinocket and Medway (Book Section) - Weddle, T. K.; Lowell, T. V.; Dorion, C. C. (New England Intercollegiate Geological Conference Guidebook for Field Trips in North Central Maine, 1994)
id: 19

Global methanotrophy at the Archean-Proterozoic transition - Hayes, J. M. (Early Life on Earth. Nobel Symposium, 1994)
id: 1565

High resolution sediment changes on the Pleistocene NJ upper slope - Christensen, B. A.; Hoppie, B. W.; Miller, K. G.; Thunell, R. C.; Le, J. (Eos, Transactions, American Geophysical Union, 1994)
id: 53

High-Resolution Climate Records from the North-Atlantic during the Last Interglacial - McManus, J. F.; Bond, G. C.; Broecker, W. S.; Johnsen, S.; Labeyrie, L.; Higgins, S. (Nature, 1994)
THE two deep ice cores recovered by the GRIP(1) and GISP(2) projects at Summit, Greenland, agree in detail over the past 100,000 years(3) and demonstrate dramatic climate variability in the North Atlantic region during the last glacial, before the current period of Holocene stability. This glacial climate instability has subsequently been documented in the marine sedimentary record of surface-ocean conditions in the North Atlantic(4). Before 100 kyr ago the two ice core records are discrepant, however, casting doubt on whether the oxygen isotope fluctuations during the last interglacial (Eemian) seen in the GRIP core(1,5) represent a true climate signal. Here we present high-resolution records of foraminiferal assemblages and ice-rafted detritus from two North Atlantic cores for the interval 65 kyr to 135 kyr ago, extending the surface-ocean record back to the Eemian. The correlation between our records and the Greenland ice-core records is good throughout the period in which the two ice cores agree, suggesting a regionally coherent climate response. During the Eemian, our marine records show a more stable climate than that implied by the GRIP ice core, suggesting that localized phenomena may be responsible for the variability in the latter record during the Eemian.
Ph254Times Cited:313Cited References Count:25

Holocene neotectonic deformation and earthquake history in sediments from Lake Washington - Karlin, R.; Holmes, M.; Abella, S. (Abstracts with Programs - Geological Society of America, 1994)
id: 32

Internal and External Checks in the Nosams Sample Preparation Laboratory for Target Quality and Homogeneity - Osborne, E. A.; McNichol, A. P.; Gagnon, A. R.; Hutton, D. L.; Jones, G. A. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 1994)
In the NOSAMS sample preparation laboratory (SPL) we have developed rigorous internal procedures aimed at ensuring that sample preparation introduces as little error into our analyses as possible and identifying problems rapidly. Our three major CO2 preparation procedures are: stripping inorganic carbon from seawater, hydrolyzing CaCO3, and oxidizing organic matter. For seawater, approximately 10% of our analyses are standards or blanks which we use to demonstrate extraction of virtually all the inorganic carbon. Analysis of the stable carbon isotopic composition of the CO2 extracted from our standards indicates a precision of better than 0.15-0.20 parts per thousand. We also routinely process C-14-free CO2 in our stripping lines to demonstrate the absence of a significant process-dependent blank. For organic combustions and CaCO3 hydrolyses, we use the carbon yield (% organic carbon (OC) or % CaCO3 by weight) as a check on our sample procedures. We have analyzed the blank contribution of these procedures as a function of sample size. Our organic carbon blank is constant at approximately 0.4% modem for samples containing greater than 1 mg C and our carbonate blank is less than 0.2% modern for samples containing more than 0.5 mg C. We use a standard Fe/H-2 catalytic reduction to prepare graphite from CO2. We check the completeness of our reactions with the pressure data stored during the reaction as well as use a robot to determine a gravimetric yield. All graphite undergoes a visual inspection and is rejected if any heterogeneities are present. We have recombusted graphite made from CO2 with deltaC-13 values ranging from -42 to 1 parts per thousand and determined that the deltaC-13 of the recombusted carbon agrees with that from the pure gas to within 0.05 parts per thousand, demonstrating little or no fractionation during the treatment of the sample. The deltaC-13 we measure on the CO2 generated from more than 75% of our samples is compared to the deltaC-13 measured on the AMS as a further check of our procedures. As further external checks, we analyzed the International Atomic Energy Association (IAEA) samples during the establishment of our laboratory and are presently participating in the third international radiocarbon intercalibration (TIRI) exercise.
Nv547Times Cited:14Cited References Count:5

Methods for Data Screening, Flagging and Error Analysis at the National-Ocean-Sciences-Ams-Facility - Schneider, R. J.; Jones, G. A.; McNichol, A. P.; vonReden, K. F.; Elder, K. L.; Huang, K.; Kessel, E. D. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 1994)
All data collection, from sample submittal through processing into targets and AMS analysis, is integrated within a large relational database (Sybase). Over 50 tables are linked through key fields. Through structured queries, the information is analysed and presented for a wide variety of applications. Benefits include enhanced quality control, more complete reports to users and more accurate transfer of data among the several laboratories on the network.
Nv547Times Cited:14Cited References Count:4

ODP Initial Reports, Leg 150X - Miller, K. G.; Liu, C.; Browning, J. V.; Pekar, S. F.; Sugarman, P. J.; Van Fossen, M. C.; Mullikin, L.; Queen, D.; Feigenson, M. D.; Aubry, M. P.; Burckle, L. D.; Powars, D.; et al. (Ocean Drilling Program, 1994)
id: 1347

Rapid analysis of seawater samples at the National Ocean Sciences Accelerator Mass Spectrometry Facility, Woods Hole, MA - McNichol, A. P.; Jones, G. A.; Hutton, D. L.; Gagnon, A. R.; Key, R. M. (Radiocarbon, 1994)
id: 305

The Rapid Preparation of Seawater Sigma-Co2 for Radiocarbon Analysis at the National Ocean Sciences Ams Facility - McNichol, A. P.; Jones, G. A.; Hutton, D. L.; Gagnon, A. R.; Key, R. M. (Radiocarbon, 1994)
We have established a laboratory for extracting Sigma CO2 from seawater samples for AMS analysis of the radiocarbon content. The seawater samples are collected at sea, poisoned and stored until analysis in the laboratory. Each sample is acidified; the inorganic carbon is stripped out as CO2 with an inert carrier gas and then converted to graphite. We present results for Buzzards Bay surface H2O and Na2CO3 standards that demonstrate we strip > 98% of inorganic carbon from seawater. Stable isotope analyses are performed to better than 0.2 parts per thousand, and the reproducibility of C-14 measurements on Buzzards Bay seawater is better than 13 parts per thousand. Finally, we compare data from samples collected in 1991 to those collected in the 1970s and to large volume samples.
Pz926Times Cited:61 Cited References Count:14
Keywords: accelerator mass-spectrometry; C-14; samples

Redifinition of the "Blake Event" based on new paleomagnetic results from deep sea sediments of the Blake-Bahama Outer Ridge - Henyey, S.; Lund, S. P.; Schwart, M.; Keigwin, L. (Eos, Transactions, American Geophysical Union, 1994)
id: 33

Sources of Urban Contemporary Carbon Aerosol - Hildemann, L. M.; Klinedinst, D. B.; Klouda, G. A.; Currie, L. A.; Cass, G. R. (Environmental Science & Technology, 1994)
Emissions from the major sources of fine carbonaceous aerosol in the Los Angeles basin atmosphere have been analyzed to determine the amounts of the C-12 and C-14 isotopes present. From these measurements, an inventory of the fossil carbon and contemporary carbon particle emissions to the Los Angeles atmosphere has been created. In the winter, more than half of the fine primary carbonaceous aerosol emissions are from sources containing contemporary carbon, including fireplaces, charbroilers, paved road dust, cigarette smoke, and brake lining dust, while in the summer at least one-third of the carbonaceous particle emissions are contemporary. Using a mathematical model for atmospheric transport, predictions are made of the atmospheric fine particulate fossil carbon and contemporary carbon concentrations expected due to primary source emissions. Model predictions are in reasonable agreement with the measured radiocarbon content of the fine ambient aerosol samples. It is concluded that the high fraction of contemporary carbon measured historically in Los Angeles is not due to local emission sources of biogenic material; rather, it is due to a combination of local anthropogenic pollution sources and background marine aerosol advected into the city.
Pe258Times Cited:111Cited References Count:45

Internal and external checks in the NOSAMS Sample Preparation Laboratory for target quality and homogeneity - McNichol, A. P.; Gagnon, A. R.; Osborne, E. A.; Hutton, D. L.; Jones, G. A. (6th International Conference on Accelerator Mass Spectrometry, 1993)
id: 958

Laboratory automation at the National Ocean Sciences AMS Facility - Cohen, G. J.; Hutton, D. L.; von Reden, K. F.; Osborne, E. A.; McNichol, A. P.; Jones, G. A. (6th Internation Conference on Accelerator Mass Spectrometry, 1993)
id: 927

The National Ocean Sciences AMS Facility at Woods Hole Oceanographic Institution - Jones, G. A.; Schneider, R. J.; von Reden, K. F.; McNichol, A. P.; Gagnon, A. R.; Cohen, G. J.; Osborne, E. A.; Hutton, D. L.; Kessel, E. D.; Elder, K. L. (6th International Conference on Accelerator Mass Spectrometry, 1993)
id: 930

Geochemistry of Precambrian carbonates: IV. Early Paleoproterozoic (2.25 +/-0.25 Ga) seawater - Veizer, J.; Clayton, K. R. N.; Hinton, R. W. (Geochimica et Cosmochimica Acta, 1992)
id: 1602

Initial Dating and Paleoenvironmental Results From Lake Baikal, Southeastern Siberia - Colman, S. M.; Karabanov, E. B.; Williams, D. F.; Hearn, P. P., Jr.; King, J. W.; Orem, W. H.; Bradbury, J. P.; Shanks, W. C., III; Jones, G. A.; Carter, S. J. (Abstracts With Programs of the American Quaternary Association, 1992)
id: 905